Cortical and trabecular bone in pediatric end-stage kidney disease - Carvalho, Catarina G.; Pereira, Renata C.; Gales, Barbara; Salusky, Isidro B.; Wesseling-Perry, Katherine (Pediatric Nephrology, 2015)

Finite element analysis of pectus carinatum surgical correction via a minimally invasive approach - Neves, Sara C.; Pinho, A. C. M.; Fonseca, Jaime C.; Rodrigues, Nuno F.; Henriques-Coelho, Tiago; Correia-Pinto, Jorge; Vilaca, Joao L. (Computer Methods in Biomechanics and Biomedical Engineering, 2015)

Modulation of the inflammatory response to chitosan through M2 macrophage polarization using pro-resolution mediators - Vasconcelos, Daniela P.; Costa, Madalena; Amaral, Isabel F.; Barbosa, Mario A.; Aguas, Artur P.; Barbosa, Judite N. (Biomaterials, 2015)

Optic disc segmentation using the sliding band filter - Dashtbozorg, Behdad; Mendonca, Ana Maria; Campilho, Aurelio (Computers in Biology and Medicine, 2015)

Rehab@home: a tool for home-based motor function rehabilitation - Faria, Carlos; Silva, Jorge; Campilho, Aurelio (Disability and rehabilitation. Assistive technology, 2015)

Study of paraffin-embedded colon cancer tissue using terahertz spectroscopy - Wahaia, Faustino; Kasalynas, Irmantas; Seliuta, Dalius; Molis, Gediminas; Urbanowicz, Andrzej; Carvalho Silva, Catia D.; Carneiro, Fatima; Valusis, Gintaras; Granja, Pedro L. (Journal of Molecular Structure, 2015)

Terahertz spectroscopy for the study of paraffin-embedded gastric cancer samples - Wahaia, Faustino; Kasalynas, Irmantas; Seliuta, Dalius; Molis, Gediminas; Urbanowicz, Andrzej; Silva, Catia D. Carvalho; Carneiro, Fatima; Valusis, Gintaras; Granja, Pedro L. (Journal of Molecular Structure, 2015)

Adsorbed fibrinogen enhances production of bone- and angiogenic-related factors by monocytes/macrophages - Maciel, J.; Oliveira, M.I.; Colton, E.; McNally, A.K.; Oliveira, C.; Anderson, J.M.; Barbosa, M.A. (Tissue Engineering - Part A, 2014)
Macrophages are phagocytic cells with great importance in guiding multiple stages of inflammation and tissue repair. By producing a large number of biologically active molecules, they can affect the behavior of other cells and events, such as the foreign body response and angiogenesis. Since protein adsorption to biomaterials is crucial for the inflammatory process, we addressed the ability of the pro-inflammatory molecule fibrinogen (Fg) to modulate macrophage behavior toward tissue repair/regeneration. For this purpose, we used chitosan (Ch) as a substrate for Fg adsorption. Freshly isolated human monocytes were seeded on Ch substrates alone or previously adsorbed with Fg, and allowed to differentiate into macrophages for 10 days. Cell adhesion and morphology, formation of foreign body giant cells (FBGC), and secretion of a total of 80 cytokines and growth factors were evaluated. Both substrates showed similar numbers of adherent macrophages along differentiation as compared with RGD-coated surfaces, which were used as positive controls. Fg did not potentiate FBGC formation. In addition, actin cytoskeleton staining revealed the presence of punctuate F-actin with more elongated and interconnecting cells on Ch substrates. Antibody array screening and quantification of inflammation- and wound-healing-related factors indicated an overall reduction in Ch-based substrates versus RGD-coated surfaces. At late times, most inflammatory agents were down-regulated in the presence of Fg, in contrast to growth factor production, which was stimulated by Fg. Importantly, on Ch+Fg substrates, fully differentiated macrophages produced significant amounts of macrophage inflammatory protein-1delta (MIP-1δ), platelet-derived growth factor-BB, bone morphogenetic protein (BMP)-5, and BMP-7 compared with Ch alone. In addition, other important factors involved in bone homeostasis and wound healing, such as growth hormone, transforming growth factor-β3, and insulin-like growth factor-binding proteins, as well as several angiogenic mediators, including endocrine gland-derived vascular endothelial factor, fibroblast growth factor-7, and placental growth factor, were significantly promoted by Fg. This work provides a new perspective on the inflammatory response in the context of bone repair/regeneration mediated by a pro-inflammatory protein (Fg) adsorbed onto a biomaterial (Ch) that does not otherwise exhibit osteogenic properties. © Copyright 2014, Mary Ann Liebert, Inc.
Cited By (since 1996):1Export Date: 21 November 2014

Age-period-cohort effects in the incidence of hip fractures: Political and economic events are coincident with changes in risk - Alves, S.M.; Castiglione, D.; Oliveira, C.M.; de Sousa, B.; Pina, M.F. (Osteoporosis International, 2014)
Summary: An age-period cohort model was fitted to analyse time effects on hip fracture incidence rates by sex (Portugal, 2000-2008). Rates increased exponentially with age (age effect). Incidence rates decreased after 2004 for women and were random for men (period effect). New but comprehensive fluctuations in risk were coincident with major political/economic changes (cohort effect). Introduction: Healthcare improvements have allowed prevention but have also increased life expectancy, resulting in more people being at risk. Our aim was to analyse the separate effects of age, period and cohort on incidence rates by sex in Portugal, 2000-2008. Methods: From the National Hospital Discharge Register, we selected admissions (aged ≥49 years) with hip fractures (ICD9-CM, codes 820.x) caused by low/moderate trauma (falls from standing height or less), readmissions and bone cancer cases. We calculated person-years at risk using population data from Statistics Portugal. To identify period and cohort effects for all ages, we used an age-period-cohort model (1-year intervals) followed by generalised additive models with a negative binomial distribution of the observed incidence rates of hip fractures. Results: There were 77,083 hospital admissions (77.4% women). Incidence rates increased exponentially with age for both sexes (age effect). Incidence rates fell after 2004 for women and were random for men (period effect). There was a general cohort effect similar in both sexes; risk of hip fracture altered from an increasing trend for those born before 1930 to a decreasing trend following that year. Risk alterations (not statistically significant) coincident with major political and economic change in the history of Portugal were observed around birth cohorts 1920 (stable-increasing), 1940 (decreasing-increasing) and 1950 (increasing-decreasing only among women). Conclusions: Hip fracture risk was higher for those born during major economically/politically unstable periods. Although bone quality reflects lifetime exposure, conditions at birthmay determine future risk for hip fractures. © International Osteoporosis Foundation and National Osteoporosis Foundation 2013.
Cited By (since 1996):1Export Date: 21 November 2014
Keywords: Age-period-cohort; Hip fractures; Osteoporosis; Population-based study; Time trend

An Automatic Graph-Based Approach for Artery/Vein Classification in Retinal Images - Dashtbozorg, Behdad; Mendonca, Ana Maria; Campilho, Aurelio (Ieee Transactions on Image Processing, 2014)

Bioactivity of surface tethered Osteogenic Growth Peptide motifs - Panseri, Silvia; Russo, Laura; Montesi, Monica; Taraballi, Francesca; Cunha, Carla; Marcacci, Maurilio; Cipolla, Laura (Medchemcomm, 2014)

Can artificial neural networks be used to predict the origin of ozone episodes? - Fontes, T.; Silva, L.M.; Silva, M. P.; Barros, N.; Carvalho, A. C. (Science of the Total Environment, 2014)
Tropospheric ozone is a secondary pollutant having a negative impact on health and environment. To control and minimize such impact the European Community established regulations to promote a clean air all over Europe. However, when an episode is related with natural mechanisms as Stratosphere-Troposphere Exchanges (STE), the benefits of an action plan to minimize precursor emissions are inefficient. Therefore, this work aims to develop a tool to identify the sources of ozone episodes in order to minimize misclassification and thus avoid the implementation of inappropriate air quality plans. For this purpose, an artificial neural network model - the Multilayer Perceptron - is used as a binary classifier of the source of an ozone episode. Long data series, between 2001 and 2010, considering the ozone precursors, 7Be activity and meteorological conditions were used. With this model, 2-7% of a mean error was achieved, which is considered as a good generalization. Accuracy measures for imbalanced data are also discussed. The MCC values show a good performance of the model (0.65-0.92). Precision and F1-measure indicate that the model specifies a little better the rare class. Thus, the results demonstrate that such a tool can be used to help authorities in the management of ozone, namely when its thresholds are exceeded due natural causes, as the above mentioned STE. Therefore, the resources used to implement an action plan to minimize ozone precursors could be better managed avoiding the implementation of inappropriate measures. © 2014 Elsevier B.V.
Keywords: artificial neural network; Classification; Human health; Ozone; Stratosphere; Troposphere

Cellular strategies to promote vascularisation in tissue engineering applications - Costa-Almeida, R.; Granja, P.L.; Soares, R.; Guerreiro, S.G. (European Cells and Materials, 2014)
Vascularisation is considered to be one of the greatest challenges in tissue engineering. Different strategies exist but cell-based approaches have emerged as a promising therapy to achieve successful vascularisation. The use of endothelial cells to engineer vascularised tissues has been extensively investigated. This field of research has evolved with the discovery of endothelial progenitor cells, a subpopulation with a high regenerative potential. However, the survival of endothelial cell populations alone seems to be impaired. To overcome this problem, co-culture systems, involving supporting cells, like mural cells, fibroblasts, or more tissue-specific cells have been developed. Endothelial cells benefit from the extracellular matrix components and growth factors produced by the supporting cells, which results in neovessel stabilisation and maturation. The use of endothelial progenitor cells in co-culture systems appears to be a promising strategy to promote vascularisation in approaches of increasing complexity. Herein, the authors provide an overview of the cellular strategies that can be used for increasing vascularisation in tissue engineering and regeneration.
Keywords: angiogenesis; Cellular therapies; Co-culture models; Endothelial progenitor cells; Regeneration

Characterization of hLF1-11 immobilization onto chitosan ultrathin films, and its effects on antimicrobial activity - Costa, F.; Maia, S.; Gomes, J.; Gomes, P.; Martins, M.C.L. (Acta Biomaterialia, 2014)
hLF1-11 (GRRRRSVQWCA) is an antimicrobial peptide (AMP) with high activity against methicillin-resistant Staphylococcus aureus (MRSA), the most prevalent species in implant-associated infection. In this work, the effect of the surface immobilization on hLF1-11 antimicrobial activity was studied. Immobilization was performed onto chitosan thin films as a model for an implant coating due to its reported osteogenic and antibacterial properties. Chitosan thin films were produced by spin-coating on gold surfaces. hLF1-11 was immobilized onto these films by its C-terminal cysteine in an orientation that exposes the antimicrobial activity-related arginine-rich portion of the peptide. Two levels of exposure (with and without a polyethylene glycol (PEG) spacer) were analyzed. Covalent immobilization was further compared with the AMP physical adsorption onto chitosan films. Surfaces were characterized using ellipsometry, contact angle measurements, atomic force microscopy, infrared and X-ray photoelectron spectroscopies and using a fluorimetric assay for hLF1-11 quantification. Surface antimicrobial activity was assessed through surface adhesion and viability assays using an MRSA (S. aureus ATCC 33591). The incorporation of hLF1-11 increased significantly bacterial adhesion to chitosan films. However, the presence of hLF1-11, namely when immobilized through a PEG spacer, decreased the viability of adherent bacteria with regard to the control surface. These results demonstrated that hLF1-11 after covalent immobilization by its cysteine can maintain activity, particularly if a spacer is applied. However, further studies, exploring the opposite orientation or the same C-terminal orientation, but non-cysteine related, can help to clarify the potential of the hLF1-11 immobilization strategy. © 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Cited By (since 1996):1Export Date: 21 November 2014
Keywords: Antimicrobial peptides (AMP); Bacterial adhesion; chitosan; Surface characterization; Surface immobilization

Complexity-loss in fetal heart rate dynamics during labor as a potential biomarker of acidemia - Costa, Madalena D.; Schnettler, William T.; Amorim-Costa, Celia; Bernardes, Joao; Costa, Antonia; Goldberger, Ary L.; Ayres-de-Campos, Diogo (Early Human Development, 2014)

Crucial CD8+ T-lymphocyte cytotoxic role in amphotericin B nanospheres efficacy against experimental visceral leishmaniasis - Costa Lima, S.A.; Silvestre, R.; Barros, D.; Cunha, J.; Baltazar, M.T.; Dinis-Oliveira, R.J.; Cordeiro-da-Silva, A. (Nanomedicine: Nanotechnology, Biology, and Medicine, 2014)
This work aims to develop poly(d,l-lactide-co-glycolide) (PLGA)-nanospheres containing amphotericin B (AmB) with suitable physicochemical properties and anti-parasitic activity for visceral leishmaniasis (VL) therapy. When compared with unloaded-PLGA-nanospheres, the AmB-loaded PLGA-nanospheres displayed an increased particle size without affecting the polydispersity and its negative surface charge. AmB stability in the PLGA-nanospheres was >90% over 60-days at 30°C. The AmB-PLGA-nanospheres demonstrated significant in vitro and in vivo efficacy and preferential accumulation in the visceral organs. In addition, an immune-modulatory effect was observed in mice treated with AmB-PLGA-nanospheres, correlating with improved treatment efficacy. The in vitro cytotoxic response of the T-lymphocytes revealed that AmB-PLGA-nanospheres efficacy against VL infection was strictly due to the action of CD8+- but not CD4+-T lymphocytes. Overall, we demonstrate a crucial role for CD8+ cytotoxic T lymphocytes in the efficacy of AmB-PLGA nanospheres, which could represent a potent and affordable alternative for VL therapy. From the Clinical Editor: This study demonstrates a crucial role for CD8+ T lymphocytes in eliminating visceral leishmaniasis in a murine model by enhancing the cytotoxic efficacy of CD8+ T-cells via amphotericin-B-PLGA nanospheres, paving a way to a unique, potentially more potent and cost-effective therapeutic strategy. © 2014 Elsevier Inc.
Keywords: Amphotericin B; Immune-modulation; Poly(d,l-lactide-co-glycolide) nanospheres; Visceral leishmaniasis

Development and evaluation of an algorithm for computer analysis of maternal heart rate during labor - Pinto, P.; Bernardes, J.; Costa-Santos, C.; Amorim-Costa, C.; Silva, M.; Ayres-de-Campos, D. (Computers in Biology and Medicine, 2014)
Background: Maternal heart rate (MHR) recordings are morphologically similar and sometimes coincident with fetal heart rate (FHR) recordings and may be useful for maternal-fetal monitoring if appropriately interpreted. However, similarly to FHR, visual interpretation of MHR features may be poorly reproducible. Methods: A computer algorithm for on-line MHR analysis was developed based on a previously existing version for FHR analysis. Inter-observer and computer-observer agreement and reliability were assessed in 40 one-hour recordings obtained from 20 women during the last 2. h of labor. Agreement and reliability were evaluated for the detection of basal MHR, long-term variability (LTV), accelerations and decelerations, using proportions of agreement (PA) and Kappa statistic (K), with 95% confidence intervals (95% CI). Changes in MHR characteristics between the first and the second hour of the tracings were also evaluated. Results: There was a statistically significant inter-observer and computer-observer agreement and reliability in estimation of basal MHR, accelerations, decelerations and LTV, with PA values ranging from 0.72 (95% CI: 0.62-0.79) to 1.00 (95% CI: 0.99-1.00), and K values ranging from 0.44 (95% CI: 0.28-0.60) to 0.89 (95% CI: 0.82-0.96). Moreover, basal MHR, number of accelerations and LTV were significantly higher in the last hour of labor, when compared to the initial hour. Discussion: The developed algorithm for on-line computer analysis of MHR recordings provided good to excellent computer-observer agreement and reliability. Moreover, it allowed an objective detection of MHR changes associated with labor progression, providing more information about the interpretation of maternal-fetal monitoring during labor. © 2014 Elsevier Ltd.
Keywords: Agreement; Cardiotocography; computer analysis; Fetal heart rate; Maternal heart rate; reliability

Differences between external and internal fetal heart rate monitoring during the second stage of labor: a prospective observational study - Nunes, Ines; Ayres-de-Campos, Diogo; Costa-Santos, Cristina; Bernardes, Joao (Journal of Perinatal Medicine, 2014)

DNAJB4 molecular chaperone distinguishes WT from mutant E-cadherin, determining their fate in vitro and in vivo - Simões-Correia, J.; Silva, D.I.; Melo, S.; Figueiredo, J.; Caldeira, J.; Pinto, M.T.; Girão, H.; Pereira, P.; Seruca, R. (Human Molecular Genetics, 2014)
E-cadherin (Ecad) is a well-known invasion suppressor and its loss of expression is common in invasive carcinomas. Germline Ecad mutations are the only known genetic cause of hereditary diffuse gastric cancer (HDGC), demonstrating the causative role of Ecad impairment in gastric cancer. HDGC-associated Ecad missense mutations can lead to folding defects and premature proteasome-dependent endoplasmic reticulum-associated degradation (ERAD), but the molecular determinants for this fate were unidentified. Using a Drosophilabased genetic screen, we found that Drosophila DnaJ-1 interacts with wild type (WT) and mutant human Ecad in vivo. DnaJ (Hsp40) homolog, subfamily B, member 4 (DNAJB4), the human homolog of DnaJ-1, influences Ecad localization and stability even in the absence of Ecad endogenous promoter, suggesting a post-transcriptional level of regulation. Increased expression of DNAJB4 leads to stabilization of WT Ecad in the plasma membrane, while it induces premature degradation of unfolded HDGC mutants in the proteasome. The interaction between DNAJB4 and Ecad is direct, and is increased in the context of the unfolded mutant E757K, especially when proteasome degradation is inhibited, suggesting that DNAJB4 is a molecular mediator of ERAD. Post-translational regulation of native Ecad by DNAJB4 molecular chaperone is sufficient to influence cell adhesion in vitro. Using a chick embryo chorioallantoic membrane assay with gastric cancer derived cells, we demonstrate that DNAJB4 stimulates the anti-invasive function of WT Ecad in vivo. Additionally, the expression of DNAJB4 and Ecad is concomitantly decreased in human gastric carcinomas. Altogether, we demonstrate that DNAJB4 is a sensor of Ecad structural features that might contribute to gastric cancer progression. © The Author 2013. Published by Oxford University Press. All rights reserved.

Dysregulation of T cell receptor N-glycosylation: A molecular mechanism involved in ulcerative colitis - Dias, A.M.; Dourado, J.; Lago, P.; Cabral, J.; Marcos-Pinto, R.; Salgueiro, P.; Almeida, C.R.; Carvalho, S.; Fonseca, S.; Lima, M.; Vilanova, M.; Dinis-Ribeiro, M.; et al. (Human Molecular Genetics, 2014)
The incidence of inflammatory bowel disease is increasing worldwide and the underlying molecular mechanisms are far from being fully elucidated. Herein, we evaluated the role of N-glycosylation dysregulation in T cells as a key mechanism in the ulcerative colitis (UC) pathogenesis. The evaluation of the branched N-glycosylation levelsandprofile of intestinalTcell receptor (TCR)wereassessedin colonic biopsies fromUCpatientsand healthy controls. Expression alterations of the glycosyltransferase gene MGAT5 were also evaluated. We demonstrated thatUCpatients exhibit a dysregulation ofTCRbranchedN-glycosylationonlamina propriaTlymphocytes. Patients with severe UC showed the most pronounced defect on N-glycan branching in T cells. Moreover, UC patients showed a significant reduction of MGAT5 gene transcription in T lymphocytes. In this study, we disclose for the first time that a deficiency in branched N-glycosylation on TCR due to a reduced MGAT5 gene expression is a new molecular mechanism underlying UC pathogenesis, being a potential novel biomarker with promising clinical and therapeutic applications. © The Author 2013. Published by Oxford University Press. All rights reserved.

Endoplasmic Reticulum Degradation-Enhancing alpha-Mannosidase-like Protein 1 Targets Misfolded HLA-B27 Dimers for Endoplasmic Reticulum-Associated Degradation - Guiliano, David B.; Fussell, Helen; Lenart, Izabela; Tsao, Edward; Nesbeth, Darren; Fletcher, Adam J.; Campbell, Elaine C.; Yousaf, Nasim; Williams, Sarah; Santos, Susana; Cameron, Amy; Towers, Greg J.; et al. (Arthritis & Rheumatology, 2014)

An evaluation of the latest in vitro tools for drug metabolism studies - Costa, A.; Sarmento, B.; Seabra, V. (Expert Opinion on Drug Metabolism and Toxicology, 2014)
Introduction: Drugs are indispensable for human welfare nevertheless there is a lack of safe drugs. Obtaining pharmacokinetics information, especially metabolism, is a requirement during preclinical and clinical drug development so that in vitro tools represent a simple path where it is possible to assess drug toxicity and predict drug safety in humans. Areas covered: This review covers the latest in vitro tools developed for assessing drug toxicity in different organs. A special focus is given to hepatic models, as it is the main organ responsible for drug metabolism and consequently bioactivation and detoxification reactions. Three-dimensional culture models have been widely developed, resembling in vivo-like conditions, and are also discussed in this review. Expert opinion: Several in vitro tools to assess hepatic drug metabolism have been developed, however, novel in vitro methods to investigate extra-hepatic drug metabolism still need to be improved. These methods are able to reduce the number of animal used in preclinical experiments, but in vivo tests are mandatory for drug approval and commercialization. © 2014 Informa UK, Ltd.
Keywords: Hepatic metabolism; in vitro models; Intestinal metabolism; Pulmonary metabolism; Renal metabolism

Extracellular matrix stiffness and composition jointly regulate the induction of malignant phenotypes in mammary epithelium - Chaudhuri, Ovijit; Koshy, Sandeep T.; Branco da Cunha, Cristiana; Shin, Jae-Won; Verbeke, Catia S.; Allison, Kimberly H.; Mooney, David J. (Nature Materials, 2014)

HA/TCP Scaffolds Obtained by Sucrose Crystal Leaching Method: Preliminary in vitro Evaluation - Rodrigues, Leonardo Ribeiro; Laranjeira, Marta de Sousa; Fernandes, Maria Helena; Monteiro, Fernando Jorge; de Carvalho Zavaglia, Cecilia Amelia (Materials Research-Ibero-American Journal of Materials, 2014)

Human umbilical cord tissue-derived mesenchymal stromal cells attenuate remodeling after myocardial infarction by proangiogenic, antiapoptotic, and endogenous cell-activation mechanisms - Nascimento, D.S.; Mosqueira, D.; Sousa, L.M.; Teixeira, M.; Filipe, M.; Resende, TP; Araújo, A.F.; Valente, M.; Almeida, J.; Martins, J.P.; Santos, J.M.; Bárcia, R.N.; et al. (Stem Cell Research and Therapy, 2014)
Introduction. Among the plethora of cells under investigation to restore a functional myocardium, mesenchymal stromal cells (MSCs) have been granted considerable interest. However, whereas the beneficial effects of bone marrow MSCs (BM-MSCs) in the context of the diseased heart are widely reported, data are still scarce on MSCs from the umbilical cord matrix (UCM-MSCs). Herein we report on the effect of UCM-MSC transplantation to the infarcted murine heart, seconded by the dissection of the molecular mechanisms at play. Methods. Human umbilical cord tissue-derived MSCs (UCX®), obtained by using a proprietary technology developed by ECBio, were delivered via intramyocardial injection to C57BL/6 females subjected to permanent ligation of the left descending coronary artery. Moreover, medium produced by cultured UCX® preconditioned under normoxia (CM) or hypoxia (CMH) was collected for subsequent in vitro assays. Results: Evaluation of the effects upon intramyocardial transplantation shows that UCX® preserved cardiac function and attenuated cardiac remodeling subsequent to myocardial infarction (MI). UCX® further led to increased capillary density and decreased apoptosis in the injured tissue. In vitro, UCX®-conditioned medium displayed (a) proangiogenic activity by promoting the formation of capillary-like structures by human umbilical vein endothelial cells (HUVECs), and (b) antiapoptotic activity in HL-1 cardiomyocytes subjected to hypoxia. Moreover, in adult murine cardiac Sca- 1§ssup§+§esup§ progenitor cells (CPCs), conditioned medium enhanced mitogenic activity while activating a gene program characteristic of cardiomyogenic differentiation. Conclusions: UCX® preserve cardiac function after intramyocardial transplantation in a MI murine model. The cardioprotective effects of UCX® were attributed to paracrine mechanisms that appear to enhance angiogenesis, limit the extent of the apoptosis, augment proliferation, and activate a pool of resident CPCs. Overall, these results suggest that UCX® should be considered an alternative cell source when designing new therapeutic approaches to treat MI. © 2014 Nascimento et al.; licensee BioMed Central Ltd.
Cited By (since 1996):2Export Date: 21 November 2014

Impact of the introduction of fetal central monitoring on hospital expenses with cardiotocographic paper - Amorim-Costa, C.; Ayres-de-Campos, D.; Costa-Santos, C.; Bernardes, J. (Journal of Obstetrics and Gynaecology, 2014)

In vitro intestinal absorption of amino acid mixtures extracted from codfish (Gadus morhua L.) salting wastewater - Ferraro, V.; Ferreira Jorge, R.; Cruz, I.B.; Antunes, F.; Sarmento, B.; Castro, P.M.L.; Pintado, M.E. (International Journal of Food Science and Technology, 2014)
Summary: This study reports on the intestinal permeability of salt-containing mixtures of amino acids extracted from codfish salting wastewater. Permeability was evaluated in vitro using the Caco-2 cell line model; cell integrity during exposure to mixtures of amino acids was estimated by measuring the transepithelial electrical resistance (TEER). The effect of salt (NaCl) on the permeability and on the intestinal cell's integrity was also examined. Permeation rate (i.e. transport) was ≥95% for all amino acids except for creatine, for which it was 6%. Values for apparent permeability coefficients, Papp > 10-5 cm s-1, for mixture with isotonic concentration of NaCl suggest that amino acids are very likely to be absorbed in humans. Mixture with a hypertonic level of NaCl exerts a cytotoxic effect in intestinal cells resulting in a loss of epithelium integrity. Results show that isotonic mixture of amino acids extracted from codfish salting wastewater could be used in food, feed, cosmetic and pharmaceutical formulations. These applications could contribute to the fish industry sustainability. © 2013 Institute of Food Science and Technology.
Keywords: Absorption; Amino acids; Caco-2 cell; Codfish; Small intestine

Influence of the stiffness of three-dimensional alginate/collagen-I interpenetrating networks on fibroblast biology - Branco da Cunha, C.; Klumpers, D.D.; Li, W.A.; Koshy, S.T.; Weaver, J.C.; Chaudhuri, O.; Granja, P.L.; Mooney, D.J. (Biomaterials, 2014)
Wound dressing biomaterials are increasingly being designed to incorporate bioactive molecules to promote healing, but the impact of matrix mechanical properties on the biology of resident cells orchestrating skin repair and regeneration remains to be fully understood. This study investigated whether tuning the stiffness of a model wound dressing biomaterial could control the behavior of dermal fibroblasts. Fully interpenetrating networks (IPNs) of collagen-I and alginate were fabricated to enable gel stiffness to be tuned independently of gel architecture, polymer concentration or adhesion ligand density. Three-dimensional cultures of dermal fibroblasts encapsulated within matrices of different stiffness were shown to promote dramatically different cell morphologies, and enhanced stiffness resulted in upregulation of key-mediators of inflammation such as IL-10 and COX-2. These findings suggest that simply modulating the matrix mechanical properties of a given wound dressing biomaterial deposited at the wound site could regulate the progression of wound healing. © 2014 Elsevier Ltd.
Keywords: ECM (extracellular matrix); Inflammation; Interpenetrating networks (IPNs); Mechanical properties; Wound dressing biomaterial; Wound healing

Macrophages stimulate gastric and colorectal cancer invasion through EGFR Y 1086, c-Src, Erk1/2 and Akt phosphorylation and smallGTPase activity - Cardoso, A.P.; Pinto, M.L.; Pinto, A.T.; Oliveira, M.I.; Pinto, M.T.; Gonçalves, R.; Relvas, J.B.; Figueiredo, C.; Seruca, R.; Mantovani, A.; Mareel, M.; Barbosa, M.A.; et al. (Oncogene, 2014)
The interactions between cancer cells and their microenvironment are crucial for malignant progression, as they modulate invasion-related activities. Tumor-associated macrophages are generally considered allies in the process of tumor progression in several types of cancer, although their role on gastric and colorectal carcinomas is still poorly understood. In this report, we studied the influence of primary human macrophages on gastric and colorectal cancer cells, considering invasion, motility/migration, proteolysis and activated intracellular signaling pathways. We demonstrated that macrophages stimulate cancer cell invasion, motility and migration, and that these effects depend on matrix metalloproteinase (MMP) activity and on the activation of epidermal growth factor receptor (EGFR) (at the residue Y 1086), PLC-γ (phospholipase C-gamma) and Gab1 (GRB2-associated binding protein-1), as evidenced by siRNA (small interference RNA) experiments. Epidermal growth factor (EGF)-immunodepletion impaired macrophage-mediated cancer cell invasion and motility, suggesting that EGF is the pro-invasive and pro-motile factor produced by macrophages. Macrophages also induced gastric and colorectal cancer cell phosphorylation of Akt, c-Src and ERK1/2, and led to an increase of RhoA and Cdc42 activity. Interestingly, whereas macrophage-mediated cancer cell c-Src and ERK1/2 phosphorylation occurred downstream EGFR activation, Akt phosphorylation seems to be a parallel event, taking place in an EGFR-independent manner. The involvement of EGF, EGFR-downstream signaling partners and MMPs in macrophage-mediated invasion provides novel insights into the molecular crosstalk established between cancer cells and macrophages, opening new perspectives for the design of new and more efficient therapeutic strategies to counteract cancer cell invasion. © 2014 Macmillan Publishers Limited.
Cited By (since 1996):2Export Date: 21 November 2014
Keywords: cancer cell invasion; colon cancer; Gastric cancer; invasion-related signaling pathways; Macrophages; tumor microenvironment

Magnetic Bioinspired Hybrid Nanostructured Collagen-Hydroxyapatite Scaffolds Supporting Cell Proliferation and Tuning Regenerative Process - Tampieri, Anna; Iafisco, Michele; Sandri, Monica; Panseri, Silvia; Cunha, Carla; Sprio, Simone; Savini, Elisa; Uhlarz, Marc; Herrmannsdoerfer, Thomas (Acs Applied Materials & Interfaces, 2014)

Modulation of human dermal microvascular endothelial cell and human gingival fibroblast behavior by micropatterned silica coating surfaces for zirconia dental implant applications - Laranjeira, M.S.; Carvalho, Â.; Pelaez-Vargas, A.; Hansford, D.; Ferraz, M.P.; Coimbra, S.; Costa, E.; Santos-Silva, A.; Fernandes, M.H.; Monteiro, F.J. (Science and Technology of Advanced Materials, 2014)
Dental ceramic implants have shown superior esthetic behavior and the absence of induced allergic disorders when compared to titanium implants. Zirconia may become a potential candidate to be used as an alternative to titanium dental implants if surface modifications are introduced. In this work, bioactive micropatterned silica coatings were produced on zirconia substrates, using a combined methodology of sol-gel processing and soft lithography. The aim of the work was to compare the in vitro behavior of human gingival fibroblasts (HGFs) and human dermal microvascular endothelial cells (HDMECs) on three types of silica-coated zirconia surfaces: flat and micropatterned (with pillars and with parallel grooves). Our results showed that cells had a higher metabolic activity (HGF, HDMEC) and increased gene expression levels of fibroblast-specific protein-1 (FSP-1) and collagen type I (COL I) on surfaces with pillars. Nevertheless, parallel grooved surfaces were able to guide cell growth. Even capillary tube-like networks of HDMEC were oriented according to the surface geometry. Zirconia and silica with different topographies have shown to be blood compatible and silica coating reduced bacteria adhesion. All together, the results indicated that microstructured bioactive coating seems to be an efficient strategy to improve soft tissue integration on zirconia implants, protecting implants from peri-implant inflammation and improving long-term implant stabilization. This new approach of micropatterned silica coating on zirconia substrates can generate promising novel dental implants, with surfaces that provide physical cues to guide cells and enhance their behavior. © 2014 National Institute for Materials Science.
Keywords: bacteria adhesion; Biomaterials; hemolysis; human dermal microvascular endothelial cells (HDMECs); human gingival fibroblasts (HGFs); Micropatterning; Soft lithography

Optimization of the production of solid Witepsol nanoparticles loaded with rosmarinic acid - Campos, D.A.; Madureira, A.R.; Gomes, A.M.; Sarmento, B.; Pintado, M.M. (Colloids and Surfaces B: Biointerfaces, 2014)
During the last decade there has been a growing interest in the formulation of new food and nutraceutical products containing compounds with antioxidant activity. Unfortunately, due to their structure, certain compounds such as polyphenols, in particular rosmarinic acid (RA) are not stable and may interact easily with matrices in which they are incorporated. To overcome such limitations, the formulation of loaded polyphenols nanoparticles can offer an efficient solution to protect such compounds. Based on this rationale, the aim of this study was to prepare solid lipid nanoparticles (SLNs) loaded with RA using a hot melt ultrasonication method, where Witepsol H15 was used as lipid and Polysorbate 80 (Tween 80) as surfactant, following a 32 fractional factorial design, resulting in the use of 3 different percentages of surfactant (viz. 1, 2 and 3%, v/v) and lipid (0.5, 1.0 and 1.5%, w/v). The stability of the nanoparticles systems were tested during 28d in aqueous solution stored at refrigeration temperature (ca. 5°C), tracking the mean particle size of different formulations by photon correlation spectroscopy. To confirm RA entrapment, thermal analyses of the nanoparticles by DSC and FTIR were performed. The association efficiencies percentages (AE%) were determined using HPLC to quantitatively assess the RA in supernatants. Results showed that Witepsol H15 produced nanoparticles with initial mean diameters between 270 and 1000nm, yet over time, a slight increase occurred, but without occurrence of aggregation. The AE% showed a high percentage of encapsulation (ca. 99%), which reveals low polyphenol releases from SLNs throughout storage time. In general, results showed a successful production of SLNs with properties that can be used to food applications. © 2013 Elsevier B.V.
Keywords: Optimization; Rosmarinic acid; SLNs; Witepsol

Plasma and urine renalase levels and activity during the recovery of renal function in kidney transplant recipients - Quelhas-Santos, J.; Soares-Silva, I.; Fernandes-Cerqueira, C.; Simões-Silva, L.; Ferreira, I.; Carvalho, C.; Coentrão, L.; Vaz, R.; Sampaio-Maia, B.; Pestana, M. (Experimental Biology and Medicine, 2014)
Renalase is a recently described enzyme secreted by the kidney into both plasma and urine, where it was suggested to degrade catecholamines contributing to blood pressure control. While there is a controversy regarding the relationship between renal function and plasma renalase levels, there is virtually no data in humans on plasma renalase activity as well as on both urine renalase levels and activity. We prospectively examined the time course of plasma and urine renalase levels and activity in 26 end-stage renal disease (ESRD) patients receiving a cadaver kidney transplant (cadaver kidney recipients [CKR]) before surgery and during the recovery of renal function up to day 90 post transplant. The relationship with sympathetic and renal dopaminergic activities was also evaluated. The recovery of renal function in CKR closely predicted decreases in plasma renalase levels (r = 0.88; P < 0.0001), urine renalase levels (r = 0.75; P < 0.0001) and urine renalase activity (r = 0.56; P < 0.03), but did not predict changes in plasma renalase activity (r = -0.02; NS). Plasma norepinephrine levels positively correlated with plasma renalase levels (r = 0.64, P < 0.002) as well as with urine renalase levels and activity (r = 0.47 P < 0.02; r = 0.71, P < 0.0005, respectively) and negatively correlated with plasma renalase activity (r = -0.57, P < 0.002). By contrast, plasma epinephrine levels positively correlated with plasma renalase activity (r = 0.67, P < 0.0001) and negatively correlated with plasma renalase levels (r = -0.62, P < 0.003). A significant negative relationship was observed between urine dopamine output and urine renalase levels (r = -0.48; P < 0.03) but not with urine renalase activity (r = -0.33, NS). We conclude that plasma and urine renalase levels closely depend on renal function and sympathetic nervous system activity. It is suggested that epinephrine-mediated activation of circulating renalase may occur in renal transplant recipients with good recovery of renal function. The increase in plasma renalase activity observed in ESRD patients and renal transplant recipients can be explained on the basis of reduced inhibition of the circulating enzyme. © 2014 by the Society for Experimental Biology and Medicine.
Cited By (since 1996):1Export Date: 21 November 2014
Keywords: catecholamines; CKD; renal function; renal transplant; renalase

The predominance of M2-polarized macrophages in the stroma of low-hypoxic bladder tumors is associated with BCG immunotherapy failure - Lima, L.; Oliveira, D.; Tavares, A.; Amaro, T.; Cruz, R.; Oliveira, M.J.; Ferreira, J.A.; Santos, L. (Urologic Oncology: Seminars and Original Investigations, 2014)
Objective: Bacillus Calmette-Guérin (BCG) immunotherapy is the gold standard treatment for superficial bladder tumors with intermediate/high risk of recurrence or progression. However, approximately 30% of patients fail to respond to the treatment. Effective BCG therapy needs precise activation of the type 1 helper cells immune pathway. Tumor-associated macrophages (TAMs) often assume an immunoregulatory M2 phenotype and may directly interfere with the BCG-induced antitumor immune response. Thus, we aim to clarify the influence of TAMs, in particular of the M2 phenotype in stroma and tumor areas, in BCG treatment outcome. Patients and methods: The study included 99 patients with bladder cancer treated with BCG. Tumors resected before treatment were evaluated using immunohistochemistry for CD68 and CD163 antigens, which identify a lineage macrophage marker and a M2-polarized specific cell surface receptor, respectively. CD68+ and CD163+ macrophages were evaluated within the stroma and tumor areas, and high density of infiltrating cells spots were selected for counting. Hypoxia, an event known to modulate macrophage phenotype, was also assessed through hypoxia induced factor (HIF)-1α expression. Results: Patients in whom BCG failed had high stroma-predominant CD163+ macrophage counts (high stroma but low tumor CD163+ macrophages counts) when compared with the ones with a successful treatment (71% vs. 47%, P = 0.017). Furthermore, patients presenting this phenotype showed decreased recurrence-free survival (log rank, P = 0.008) and a clear 2-fold increased risk of BCG treatment failure was observed in univariate analysis (hazard ratio = 2.343; 95% CI: 1.197-4.587; P = 0.013). Even when adjusted for potential confounders, such as age and therapeutic scheme, multivariate analysis revealed 2.6-fold increased risk of recurrence (hazard ratio = 2.627; 95% CI: 1.340-5.150; P = 0.005). High stroma-predominant CD163+ macrophage counts were also associated with low expression of HIF-1α in tumor areas, whereas high counts of CD163+ in the tumor presented high expression of HIF-1α in tumor nests. Conclusions: TAMs evaluation using CD163 is a good indicator of BCG treatment failure. Moreover, elevated infiltration of CD163+ macrophages, predominantly in stroma areas but not in the tumor, may be a useful indicator of BCG treatment outcome, possibly owing to its immunosuppressive phenotype. © 2014 Elsevier Inc.
Keywords: BCG immunotherapy; Bladder cancer; CD163; CD68; Tumor-associated macrophages

Production, characterization and biocompatibility of marine collagen matrices from an alternative and sustainable source: The sea urchin Paracentrotus lividus - Di Benedetto, C.; Barbaglio, A.; Martinello, T.; Alongi, V.; Fassini, D.; Cullorà, E.; Patruno, M.; Bonasoro, F.; Barbosa, M.A.; Carnevali, M.D.C.; Sugni, M. (Marine Drugs, 2014)
Collagen has become a key-molecule in cell culture studies and in the tissue engineering field. Industrially, the principal sources of collagen are calf skin and bones which, however, could be associated to risks of serious disease transmission. In fact, collagen derived from alternative and riskless sources is required, and marine organisms are among the safest and recently exploited ones. Sea urchins possess a circular area of soft tissue surrounding the mouth, the peristomial membrane (PM), mainly composed by mammalian-like collagen. The PM of the edible sea urchin Paracentrotus lividus therefore represents a potential unexploited collagen source, easily obtainable as a food industry waste product. Our results demonstrate that it is possible to extract native collagen fibrils from the PM and produce suitable substrates for in vitro system. The obtained matrices appear as a homogeneous fibrillar network (mean fibril diameter 30-400 nm and < 2 μm) and display remarkable mechanical properties in term of stiffness (146 ± 48 MPa) and viscosity (60.98 ± 52.07 GPa·s). In vitro tests with horse pbMSC show a good biocompatibility in terms of overall cell growth. The obtained results indicate that the sea urchin P. lividus can be a valuable low-cost collagen source for mechanically resistant biomedical devices.
Keywords: Biocompatibility; Collagen matrix; Mesenchimal stromal cells; Native fibril; Sea urchin collagen; Tissue regeneration

Propolis varnish: Antimicrobial properties against cariogenic bacteria, cytotoxicity, and sustained-release profile - De Luca, M.P.; Franca, J.R.; Macedo, F.A.F.F.; Grenho, L.; Cortes, M.E.; Faraco, A.A.G.; Moreira, A.N.; Santos, V.R. (BioMed Research International, 2014)
Varnishes are preparations that differ in the polymeric matrix and therapeutical agents. In dentistry they are used to prevent caries. In this study we developed a propolis varnish, considering propolis properties against cariogenic bacteria. To a chitosan polymeric base (CHV) was added ethanolic propolis extract in different concentrations: PV1 (5%), PV2 (10%), and PV3 (15%). Antimicrobial activity was carried out against Streptococcus mutans (SM), Streptococcus sanguinis (SG), Streptococcus salivarius (SS), and Lactobacillus casei (LC) through agar diffusion method. The three propolis concentrations incorporated were effective in inhibiting the growth of all microorganisms, but without significant difference between the zones of inhibition observed. Cytotoxicity assay was done by MTT method. Data were analyzed by one-way ANOVA and Bonferroni test. None of the varnishes were cytotoxic, keeping 80% of viable cells, while CHV allowed cellular proliferation (120%). Sustained-release test was carried out by applying 40 μL of each varnish in the buccal surface of bovine teeth and kept in an ethanol/water solution removed in regular times. According to the "independent model approach," the release profiles were distinct from each varnish and the most prolonged was PV3 (8 weeks). Varnish formulations had satisfactory antimicrobial activity against cariogenic bacteria and have a low cytotoxicity (<50%). © 2014 Mariana P. De Luca et al.

Quality by Design: Discussing and Assessing the Solid Dispersions Risk - Chaves, Luise L.; Vieira, Alexandre C. C.; Reis, Salette; Sarmento, Bruno; Ferreira, Domingos C. (Current Drug Delivery, 2014)

Sca-1+cardiac progenitor cells and heart-making: A critical synopsis - Valente, M.; Nascimento, D.S.; Cumano, A.; Pinto-Do-Ó, P. (Stem Cells and Development, 2014)
The identification, in the adult, of cardiomyocyte turnover events and of cardiac progenitor cells (CPCs) has revolutionized the field of cardiovascular medicine. However, the low rate of CPCs differentiation events reported both in vitro and in vivo, even after injury, raised concerns on the biological significance of these subsets. In this Comprehensive Review, we discuss the current understanding of cardiac Lin-Sca-1+cells in light of what is also known for cellular compartments with similar phenotypes in other organs. The Lin-Sca-1+heart subset is heterogeneous and displays a mesenchymal profile, characterized by a limited ability to generate cardiomyocytes in vitro and in vivo, even after injury. There is no evidence for Sca-1 expression in embryonic cardiovascular progenitors. In other organs, Sca-1 expression is mainly observed on mesoderm-derived cells, although it is not restricted to stem/progenitor cell populations. It is urgent to determine, at a single cell level, to which extent cardiac Lin-Sca-1+cells overlap with the fibroblast compartment.

Stability study perspective of the effect of freeze-drying using cryoprotectants on the structure of insulin loaded into PLGA nanoparticles - Fonte, P.; Soares, S.; Sousa, F.; Costa, A.; Seabra, V.; Reis, S.; Sarmento, B. (Biomacromolecules, 2014)
This work aimed to evaluate the influence of a freeze-drying process using different cryoprotectants on the structure of insulin loaded into poly(lactic-co-glycolic acid) (PLGA) nanoparticles and to assess the stability of these nanoparticles upon 6 months of storage following ICH guidelines. Insulin-loaded PLGA nanoparticles with a size around 450 nm were dehydrated using a standard freeze-drying cycle, using trehalose, glucose, sucrose, fructose, and sorbitol at 10% (w/v) as cryoprotectants. All formulations, except those nonadded of cryoprotectant and added with trehalose, collapsed after freeze-drying. The addition of cryoprotectants increased the nanoparticles stability upon storage. FTIR results showed that insulin maintained its structure after encapsulation in about 88%, decreasing to 71% after freeze-drying. The addition of cryoprotectants prior to freeze-drying increased insulin structural stability an average of up to 79%. Formulations collapsed after freeze-drying showed better protein stabilization upon storage, in special sorbitol added formulation, preserving 76, 80, and 78% of insulin structure at 4 °C, 25 °C/60% RH, and 40 °C/75% RH, respectively. Principal component analysis also showed that the sorbitol-added formulation showed the most similar insulin structural modifications among the tested storage conditions. These findings suggested that regarding nanoparticles stability, cryoprotectants are versatile to be used in a standard freeze-drying, however they present different performances on the stabilization of the loaded protein. Thus, on the freeze-drying of the nanoparticles field, this work gives rise to the importance of the process of optimization, searching for a balance between a good obtainable cake with an optimal structural stabilization of the loaded protein.

Stable phenotype and function of immortalized Lin-Sca-1 + cardiac progenitor cells in long-term culture: A step closer to standardization - Freire, AG; Nascimento, D.S.; Forte, G.; Valente, M.; Resende, TP; Pagliari, S.; Abreu, C; Carvalho, I; Nardo, P.D.; Pinto-Do-Ó, P. (Stem Cells and Development, 2014)
Putative cardiac progenitor cells (CPCs) have been identified in the myocardium and are regarded as promising candidates for cardiac cell-based therapies. Although two distinct populations of CPCs reached the clinical setting, more detailed studies are required to portray the optimal cell type and therapeutic setting to drive robust cell engraftment and cardiomyogenesis after injury. Owing to the scarcity of the CPCs and the need for reproducibility, the generation of faithful cellular models would facilitate this scrutiny. Here, we evaluate whether immortalized Lin-Sca-1+ CPCs (iCPC Sca-1) represent their native-cell counterpart, thereby constituting a robust in vitro model system for standardized investigation in the cardiac field. iCPCSca-1 were established in vitro as plastic adherent cells endowed with robust self-renewal capacity while preserving a stable phenotype in long-term culture. iCPCSca-1 differentiated into cardiomyocytic-, endothelial-, and smooth muscle-like cells when subjected to appropriate stimuli. The cell line consistently displayed features of Lin -Sca-1+ CPCs in vitro, as well as in vivo after intramyocardial delivery in the onset of myocardial infarction (MI). Transplanted iCPCSca-1 significantly attenuated the functional and anatomical alterations caused by MI while promoting neovascularization. iCPCSca-1 are further shown to engraft, establish functional connections, and differentiate in loco into cardiomyocyte- and vasculature-like cells. These data validate iCPCSca-1 as an in vitro model system for Lin-Sca-1+ progenitors and for systematic dissection of mechanisms underlying CPC subsets engraftment/differentiation in vivo. Moreover, iCPCSca-1 can be regarded as a ready-to-use CPCs source for pre-clinical bioengineering studies toward the development of novel strategies for restoration of the damaged myocardium. © Copyright 2014, Mary Ann Liebert, Inc. 2014.
Cited By (since 1996):2Export Date: 21 November 2014

Automatic lane segmentation in TLC images using the continuous wavelet transform - Moreira, B.; Sousa, A.; Mendonça, A.M.; Campilho, A. (Computational and Mathematical Methods in Medicine, 2013)

Automatic localization of the optic disc by combining vascular and intensity information - Mendonça, A.M.; Sousa, A.; Mendonça, L.; Campilho, A. (Computerized Medical Imaging and Graphics, 2013)

Characterization of human NLZ1/ZNF703 identifies conserved domains essential for proper subcellular localization and transcriptional repression - Pereira-Castro, I.; Costa, Â.M.S.; Oliveira, M.J.; Barbosa, I.; Rocha, A.S.; Azevedo, L.; Da Costa, L.T. (Journal of Cellular Biochemistry, 2013)

Comparison of real beat-to-beat signals with commercially available 4 Hz sampling on the evaluation of foetal heart rate variability - Gonçalves, H.; Costa, A.; Ayres-de-Campos, D.; Costa-Santos, C.; Rocha, A.P.; Bernardes, J. (Medical and Biological Engineering and Computing, 2013)

E-cadherin and adherens-junctions stability in gastric carcinoma: Functional implications of glycosyltransferases involving N-glycan branching biosynthesis, N-acetylglucosaminyltransferases III and v - Pinho, S.S.; Figueiredo, J.; Cabral, J.; Carvalho, S.; Dourado, J.; Magalhães, A.; Gärtner, F.; Mendonça, A.M.; Isaji, T.; Gu, J.; Carneiro, F.; Seruca, R.; et al. (Biochimica et Biophysica Acta - General Subjects, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Effect of freeze-drying, cryoprotectants and storage conditions on the stability of secondary structure of insulin-loaded solid lipid nanoparticles - Soares, S.; Fonte, P.; Costa, A.; Andrade, J.; Seabra, V.; Ferreira, D.; Reis, S.; Sarmento, B. (International Journal of Pharmaceutics, 2013)

Effects of density of anisotropic microstamped silica thin films on guided bone tissue regeneration - In vitro study - Pelaez-Vargas, A.; Gallego-Perez, D.; Carvalho, A.; Fernandes, M.H.; Hansford, D.J.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part B Applied Biomaterials, 2013)

Engineering of a 3D nanostructured scaffold made of functionalized self-assembling peptides and encapsulated neural stem cells - Cunha, C.; Panseri, S.; Gelain, F. (Methods in Molecular Biology, 2013)

Enzymatic, physicochemical and biological properties of MMP-sensitive alginate hydrogels - Fonseca, K.B.; Maia, F.R.; Cruz, F.A.; Andrade, D.; Juliano, M.A.; Granja, P.L.; Barrias, C.C. (Soft Matter, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Expression of ST3GAL4 Leads to SLex Expression and Induces c-Met Activation and an Invasive Phenotype in Gastric Carcinoma Cells - Gomes, C.; Osório, H.; Pinto, M.T.; Campos, D.; Oliveira, M.J.; Reis, C.A. (PLoS ONE, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: ScopusArt. No.: e66737

High biocompatibility and improved osteogenic potential of novel Ca-P/titania composite scaffolds designed for regeneration of load-bearing segmental bone defects - Cunha, C.; Sprio, S.; Panseri, S.; Dapporto, M.; Marcacci, M.; Tampieri, A. (Journal of Biomedical Materials Research - Part A, 2013)

Highly focalised thermotherapy using a ferrimagnetic cement in the treatment of a melanoma mouse model by low temperature hyperthermia - Portela, A.; Vasconcelos, M.; Fernandes, M.H.; Garcia, M.; Silva, A.; Gabriel, J.; Gartner, F.; Amorim, I.; Cavalheiro, J. (International Journal of Hyperthermia, 2013)
Cited By (since 1996):2Export Date: 12 December 2013Source: Scopus

Hydrolyzed galactomannan-modified nanoparticles and flower-like polymeric micelles for the active targeting of rifampicin to macrophages - Moretton, M.A.; Chiappetta, D.A.; Andrade, F.; Das Neves, J.; Ferreira, D.; Sarmento, B.; Sosnik, A. (Journal of Biomedical Nanotechnology, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Information-based measure of disagreement for more than two observers: A useful tool to compare the degree of observer disagreement - Henriques, T.; Antunes, L.; Bernardes, J.; Matias, M.; Sato, D.; Costa-Santos, C. (BMC Medical Research Methodology, 2013)

Keratins and lipids in ethnic hair - Cruz, C.F.; Fernandes, M.M.; Gomes, A.C.; Coderch, L.; Martí, M.; Méndez, S.; Gales, L.; Azoia, N.G.; Shimanovich, U.; Cavaco-Paulo, A. (International Journal of Cosmetic Science, 2013)
Cited By (since 1996):3Export Date: 12 December 2013Source: Scopus

Loss of WNK2 expression by promoter gene methylation occurs in adult gliomas and triggers Rac1-mediated tumour cell invasiveness - Moniz, S.; Martinho, O.; Pinto, F.; Sousa, B.; Loureiro, C.; Oliveira, M.J.; Moita, L.F.; Honavar, M.; Pinheiro, C.; Pires, M.; Lopes, J.M.; Jones, C.; et al. (Human Molecular Genetics, 2013)
Cited By (since 1996):2Export Date: 12 December 2013Source: ScopusArt. No.: dds405

Macrophage polarization following chitosan implantation - Vasconcelos, D.P.; Fonseca, A.C.; Costa, M.; Amaral, I.F.; Barbosa, M.A.; Águas, A.P.; Barbosa, J.N. (Biomaterials, 2013)

Macrophages stimulate gastric and colorectal cancer invasion through EGFR Y1086, c-Src, Erk1/2 and Akt phosphorylation and smallGTPase activity - Cardoso, A.P.; Pinto, M.L.; Pinto, A.T.; Oliveira, M.I.; Pinto, M.T.; Gonçalves, R.; Relvas, J.B.; Figueiredo, C.; Seruca, R.; Mantovani, A.; Mareel, M.; Barbosa, M.A.; et al. (Oncogene, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: ScopusArticle in Press

A novel bioactive peptide: Assessing its activity over murine neural stem cells and its potential for neural tissue engineering - Caprini, A.; Silva, D.; Zanoni, I.; Cunha, C.; Volontè, C.; Vescovi, A.; Gelain, F. (New Biotechnology, 2013)

Overexpression of tumour-associated carbohydrate antigen sialyl-Tn in advanced bladder tumours - Ferreira, J.A.; Videira, P.A.; Lima, L.; Pereira, S.; Silva, M.; Carrascal, M.; Severino, P.F.; Fernandes, E.; Almeida, A.; Costa, C.; Vitorino, R.; Amaro, T.; et al. (Molecular Oncology, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Physical activity-friendly neighbourhood among older adults from a medium size urban setting in Southern Europe - Ribeiro, A.I.; Mitchell, R.; Carvalho, M.S.; De Pina, M.D.F. (Preventive Medicine, 2013)

Protective effects of Lavandula viridis L'Hér extracts and rosmarinic acid against H2O2-induced oxidative damage in A172 human astrocyte cell line - Costa, P.; Sarmento, B.; Gonçalves, S.; Romano, A. (Industrial Crops and Products, 2013)

Should European perinatal indicators be revisited? - Santos, J.V.; Correia, C.; Cabral, F.; Bernardes, J.; Costa-Pereira, A.; Freitas, A. (European Journal of Obstetrics Gynecology and Reproductive Biology, 2013)
Cited By (since 1996):2Export Date: 12 December 2013Source: Scopus

The smart connective tissue of echinoderms: A materializing promise for biotech applications - Barbaglio, A.; Tricarico, S.; Di Benedetto, C.; Fassini, D.; Lima, A.P.; Ribeiro, A.R.; Ribeiro, C.C.; Sugni, M.; Bonasoro, F.; Wilkie, L.; Barbosa, M.; Candia Carnevali, M.D. (Cahiers de Biologie Marine, 2013)

Sociodemographic determinants of prevalence and incidence of helicobacter pylori infection in portuguese adults - Bastos, J.; Peleteiro, B.; Barros, R.; Alves, L.; Severo, M.; de Fátima Pina, M.; Pinto, H.; Carvalho, S.; Marinho, A.; Guimarães, J.T.; Azevedo, A.; La Vecchia, C.; et al. (Helicobacter, 2013)

Stable phenotype and function of immortalized Lin-Sca-1+ cardiac progenitor cells in long-term culture: a step closer to standardization. - Freire, AG; Nascimento, D.S.; Forte, G.; Valente, M.; Resende, TP; Pagliari, S.; Abreu, C; Carvalho, I; Di Nardo, P.; Pinto-Do-Ó, P. (Stem Cells Dev, 2013)

Automatic assessment of Leishmania infection indexes on in vitro macrophage cell cultures - Leal, P.; Ferro, L.; Marques, M.; Romão, S.; Cruz, T.; Tomá, A.M.; Castro, H.; Quelhas, P. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2012)
Evaluation of parasite infection indexes on in vitro cell cultures is a practice commonly employed by biomedical researchers to address biological questions or to test the efficacy of novel anti-parasitic compounds. In the particular case of Leishmania infantum, a unicellular parasite that parasitizes macrophages, infection indexes are usually determined either by visual inspection of cells directly under the microscope or by counting digital images using appropriate software. In either case assessment of infection indexes is time consuming, thus motivating the creation of automatic image analysis approaches that allow large scale studies of Leishmania-infected macrophage cultures. We propose a fully automated method for automatic evaluation of parasite infection indexes through the segmentation of individual macrophages nucleus and cytoplasm, as well as the segmentation and co-localization of the parasites in the image. To perform such analysis with robustness and increased performance we propose the use of local image filters tuned to the specific size of the objects to detect, in conjunction with image segmentation approaches. The objects size estimation is then improved through a learning feedback loop. Cytoplasm is detected by seeded watershed segmentation. Our approach obtains, for 86 images from 4 experiments, an average parasite infection index evaluation error of 2.3%. © 2012 Springer-Verlag.
Conference code: 91199Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-31298-4_51Language of Original Document: EnglishCorrespondence Address: Leal, P.; Universidade Do Porto, Faculdade de Engenharia, Departamento de Engenharia QuímicaPortugalReferences: Castro, H., Sousa, C., Santos, M., Cordeiro-da-Silva, A., Flohé, L., Tomás, A., Complementary antioxidant defence by cytoplasmic and mitochondrial peroxiredoxins in Leishmania infantum (2002) Free Radical Biology and Medicine, 33, pp. 1552-1562;Chen, X., Zhou, X., Wong, S., Automated segmentation, classification, and tracking of cancer cell nuclei in time-lapse microscopy IEEE Trans. on Biomedical Engineering, 53 (4), pp. 762-766; Marcuzzo, M., Quelhas, P., Campilho, A., Maria Mendonça, A., Campilho, A., Automated arabidopsis plant root cell segmentation based on svm classification and region merging (2009) Computers in Biology and Medicine, 39 (9); Chen, Y., Ladi, E., Herzmark, P., Robey, E., Roysam, B., Automated 5-d analysis of cell migration and interaction in the thymic cortex from time-lapse sequences of 3-d multi-channel multi-photon images (2009) J. Immunol. Methods, 340 (1), pp. 65-80; Esteves, T., Quelhas, P., Mendonça, A.M., Campilho, A., Gradient convergence filters and a phase congruency approach for in vivo cell nuclei detection Machine Vision and Applications, , in press; Schmitt, O., Hasse, M., Morphologic multiscale decomposition of connected regions with emphasis on cell clusters (2009) CVIU, 113 (2), pp. 188-201; Usaj, M., Torkar, D., Kanduser, M., Miklavcic, D., Cell counting tool parameters optimization approach for electroporation efficiency determination of attached cells in phase contrast image (2010) Journal of Microscopy, 241 (3), pp. 303-314; Sezgin, M., Sankur, B., Survey over image thresholding techniques and quantitative performance evaluation (2003) Journal of Electronic Imaging, 13 (1), pp. 146-165; Lowe, D., Distinctive Image Features from Scale-Invariant Keypoints (2004) International Journal of Computer Vision; Lindberg, T., Scale-space theory: A basic tool for analysing structures at different scales (1994) Journal of Applied Statistics, pp. 11-24; Yan, P., Zhou, X., Shah, M., Wong, S.T.C., Automatic segmentation of high-throughput RNAi fluorescent cellular images (2008) IEEE Trans. Inf. Technol. Biomed., 12 (1), pp. 109-117; CellNote: Plataforma para An?alise Assistida de Imagens, Bruno Afonso Da Cruz Lopes, , Master Thesis, Faculty of Sciences of the University of Porto
Keywords: Automated methods; Automatic assessment; Automatic evaluation; Automatic image analysis; Cell culture; Cell nuclei detection; cell nucleus; Colocalization; Digital image; Enzyme inhibition; Feed-back loop; Image analysis; Image filters; Image segmentation; In-vitro; Leishmania; Leishmania infantum; Macrophage cells; Macrophage culture; Macrophages; microscopy image segmentation; Microscopy images; Parasite infection; Parasite-; Size estimation; Visual inspection; Watershed segmentation

Automatic lane detection in chromatography images - Moreira, B.M.; Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2012)
This paper proposes a method for automating the detection of lanes in Thin-Layer Chromatography images. Our approach includes a preprocessing step to detect the image region of interest, followed by background estimation and removal. This image is then projected onto the horizontal direction to integrate the information into a one-dimensional profile. A smoothing filter is applied to this profile and the outcome is the input of the lane detection process, which is performed in three phases. The first one aims at obtaining an initial set of candidate lanes that are further validated or removed in the second phase. The last phase is a refinement step that allows the inclusion of lanes that are not clearly distinguishable in the profile and that were not included in the initial set. The method was evaluated in 66 chromatography images and achieved values of recall, precision and F β -measure of 97.0%, 99.4% and 98.2%, respectively. © 2012 Springer-Verlag.
Conference code: 91199Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-31298-4_22Language of Original Document: EnglishCorrespondence Address: Moreira, B.M.; Instituto de Engenharia Biomédica, Universidade Do Porto, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: moreira@fe.up.ptReferences: Fried, B., Sherma, J., (1999) Thin-Layer Chromatography, , Marcel Dekker, New York;Rodrigues, L.G., Ferraz, M.J., Rodrigues, D., Pais-Vieira, M., Lima, D., Brady, R.O., Sá-Miranda, M.C., Neurophysiological behavioral and morphological abnormalities in the Fabry knockout mice (2009) Neurobiology of Disease, 33 (1), pp. 48-56; Elstein, D., Altarescu, G., Beck, M., (2010) Fabry Disease, , Springer, Heidelberg; Houck, M.M., Siegel, J.A., (2010) Fundamentals of Forensic Science, , Elsevier, Oxford; Machado, A.M.C., Campos, M.F.M., Siqueira, A.M., De Carvalho, O.S.F., An iterative algorithm for segmenting lanes in gel electrophoresis images (1997) Proc. X Brazilian Symposium on Computer Graphics and Image Processing, pp. 140-146. , October; Elder, J.K., Southern, E.M., Computer-aided analysis of one dimensional restriction fragment gels (1987) Nucleic Acid and Protein Sequence Analysis - A Practical Aproach, pp. 165-172. , Bishop, M.J., Rawlings, C.J. (eds.) IRL Press, Oxford; Bajla, I., Holländer, I., Fluch, S., Burg, K., Kollár, M., An alternative method for electrophoretic gel image analysis in the GelMaster software (2005) Computer Methods and Programs in Biomedicine, 77, pp. 209-231; Lin, C., Ching, Y., Yang, Y., An Automatic Method to Compare the Lanes in Gel Electrophoresis (GE) Images (2007) IEEE Transaction on Information Technology in Biomedicine, 11 (2), pp. 179-189; Akbari, A., Fritz, A., Jackobsen, K.S., Automatic lane detection and separation in one dimensional gel images using continuous wavelet transform (2010) The Royal Society of Chemistry, Analytical Methods, 2, pp. 1360-1371; Sousa, A.V., Aguiar, R.L., Mendonça, A.M., Campilho, A.C., Automatic Lane and Band Detection in Images of Thin Layer Chromatography (2004) LNCS, 3212, pp. 158-165. , Campilho, A.C., Kamel, M.S. (eds.) ICIAR 2004. Springer, Heidelberg; Sotaquira, M., On the use of distance maps in the analysis of 1D DNA gel images (2009) ICDIP 2009: Proceedings of the International Conference on Digital Image Processing, pp. 172-176. , IEEE Computer Society; Barrantes, P., Alvarado, P., Lane Detection on Gel Electrophoresis Images using Active Shape Models (2011) Proc. of the Conference on Technologies for Sustainable Development, TSD 2011, pp. 43-46. , February; Mendonça, A.M., Sousa, A.V., Sá-Miranda, M.C., Campilho, A.C., Automatic segmentation of chromatographic images for region of interest delineation (2011) Proc. SPIE, 7962, pp. 79623B1-79623B7; Chau, F., Liang, Y., Gao, J., Shao, X., (2004) Chemometrics - from Basics to Wavelet Transform, , John Wiley & Sons, New Jersey; Press, W.H., Flannery, B.P., Teukolsky, S.A., Vetterling, W.T., (1992) Numerical Recipes in C: The Art of Scientific Computing, , Syndicate of the University of Cambridge; Soille, P., Jones, C.D., Smith, A.B., Roberts, E.F., (2004) Morphological Image Analysis - Principles and Applications, , Springer; Visa, S., Ralescu, A., Learning Imbalanced and Overlapping Classes using Fuzzy Sets Workshop on Learning from Imbalanced Datasets II, ICML (2003)
Keywords: Background estimation; Bio-medical image processing; Biomedical image processing; Chromatography; Chromatography images; Computer aided diagnosis; Image analysis; Image regions; Lane detection; Pre-processing step; Refinement step; Second phase; Smoothing filters; Three phasis

Automatic localization of the optic disc in retinal images based on the entropy of vascular directions - Mendonça, A.M.; Cardoso, F.; Sousa, A.V.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2012)
This paper proposes an automatic method for estimating the location of the optic disc in color images of the retina. The proposed methodology is founded in a new concept, the entropy of vascular directions, which proved to be a reliable measure for assessing the convergence of vessels around an image point. To improve the robustness of the method, the search for the maximum value of entropy is restricted to image areas with high intensity. This new method was evaluated in two publicly available databases, containing both normal and pathological images, and was able to obtain a valid location for the optic disc in 115 out of the 121 images of the two datasets. © 2012 Springer-Verlag.
Conference code: 91199Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-31298-4_50Language of Original Document: EnglishCorrespondence Address: Mendonça, A.M.; Instituto de Engenharia Biomédica, Universidade Do Porto, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: amendon@fe.up.ptReferences: Jelinek, H., Cree, M., (2010) Automated Image Detection of Retinal Pathology, , CRC Press, Taylor & Francis Group, Boca Raton;Couper, D.J., Klein, R., Hubbard, L.D., Wong, T.Y., Sorlie, P., Cooper, L.S., Brothers, R.J., Nieto, F.J., Reliability of Retinal Photography in the Assessment of Retinal Microvascular Characteristics: The Atherosclerosis Risk in Communities Study (2002) American Journal of Ophthalmology, 133 (1), pp. 78-88; Sinthanayothin, C., Boyce, J.F., Cook, H.L., Williamson, T.H., Automated localization of the optic disc, fovea, and retinal blood vessels from digital colour fundus images (1999) Br. J. Ophthalmol., 83, pp. 902-910; Aquino, A., Gegúndez-Arias, M.E., Marin, D., Detecting the Optic Disc Boundary in Digital Fundus Images Using Morphological, Edge Detection and Feature Extraction Techniques (2010) IEEE Trans. Medical Imaging, 29 (11), pp. 1860-1869; Aquino, A., Gegúndez-Arias, M.E., Marin, D., Automated Optic Disc Detection in Retinal Images of Patients with Diabetic Retinopathy and Risk of Macular Edema (2012) Int. J. of Biological and Life Sciences, 8 (2), pp. 87-92; Lalonde, M., Beaulieu, M., Gagnon, L., Fast and Robust Optic Disc Detection Using Pyramidal Decomposition and Hausdorff-based Template Matching (2001) IEEE Trans. Medical Imaging, 20 (11), pp. 1193-1200; Osareh, A., Mirmehdi, M., Thomas, B., Markham, R., Classification and Localisation of Diabetic-Related Eye Disease (2002) LNCS, 2353, pp. 502-516. , Heyden, A., Sparr, G., Nielsen, M., Johansen, P. (eds.) ECCV 2002. Springer, Heidelberg; Lowell, J., Hunter, A., Steel, D., Basu, A., Ryder, R., Fletcher, E., Kennedy, L., Optic Nerve head Segmentation (2004) IEEE Trans. Medical Imaging, 23 (2), pp. 256-264; Abdel-Ghafar, R.A., Morris, T., Progress towards automated detection and characterization of the optic disc in glaucoma and diabetic retinopathy (2007) Medical Informatics and the Internet in Medicine, 32 (1), pp. 19-25; Hoover, A., Glodbaum, M., Locating the Optic Nerve in a Retinal Image Using the Fuzzy Convergence of the Blood Vessels (2003) IEEE Trans. Medical Imaging, 22 (8), pp. 951-958; Foracchia, M., Grisan, E., Ruggeri, A., Detection of Optic Disc in Retinal Images by Means of a Geometrical Model of Vessel Structure (2004) IEEE Trans. Medical Imaging, 23 (10), pp. 1189-1195; Haar, F., (2005) Automatic Localization of the Optic Disc in Digital Colour Images of the Human Retina, , Msc Thesis, University of Utrecht; Youssif, A., Ghalwash, A.Z., Ghoneim, A., Optic Disc Detection from Normalized Digital Fundus Images by Means of a Vessels' Direction Matched Filter (2008) IEEE Trans. Medical Imaging, 27 (1), pp. 11-18; Niemeijer, M., Abràmoff, M.D., Van Ginneken, B., Fast detection of the optic disc and fovea in color fundus photographs (2009) Medical Image Analysis, 13, pp. 859-870; Xu, X., Gravin, M.K., Abràmoff, M.D., Reinhardt, J.M., Simultaneous Automatic Detection of the Optic Disc and Fovea on Fundus Photographs (2011) Proc. SPIE Medical Imaging 2011: Image Processing, 7962, pp. 7962T. , Dawant, B.M., Haynor, D.R. (eds.) SPIE; http://www.isi.uu.nl/Research/Databases/DRIVEhttp://www.ces.clemson.edu/~ahoover/stare, The STARE projectMendonça, A., Campilho, A., Segmentation of Retinal Blood Vessels by Combining the Detection of Centerlines and Morphological Reconstruction (2006) IEEE Trans. Medical Imaging, 25 (9), pp. 1200-1213; Chaudhuri, S., Chattererjee, S., Katz, N., Glodbaum, M., Detection of blood Vessels in Retinal Images using Two-Dimensional Matched Filters (1989) IEEE Trans. Medical Imaging, 28 (3), pp. 263-269
Keywords: Automatic localization; Automatic method; Color images; Data sets; entropy; High intensity; Image analysis; Image points; Maximum values; Ophthalmology; optic disc; Pathological images; Retinal image; Retinal image analysis; vessel segmentation

Bioengineered surfaces to improve the blood compatibility of biomaterials through direct thrombin inactivation - Freitas, S.C.; Cereija, T.B.; Figueiredo, A.C.; Osório, H.; Pereira, P.J.B.; Barbosa, M.A.; Martins, M.C.L. (Acta BiomaterialiaActa Biomater., 2012)
Thrombus formation, due to thrombin generation, is a major problem affecting blood-contacting medical devices. This work aimed to develop a new strategy to improve the hemocompatibility of such devices by the immobilization of a naturally occurring thrombin inhibitor into a nanostructured surface. Boophilin, a direct thrombin inhibitor from the cattle tick Rhipicephalus microplus, was produced as a recombinant protein in Pichia pastoris. Boophilin was biotinylated and immobilized on biotin-terminated self-assembled monolayers (SAM) via neutravidin. In order to maintain its proteinase inhibitory capacity after surface immobilization, boophilin was biotinylated after the formation of a boophilin-thrombin complex to minimize the biotinylation of the residues involved in thrombin-boophilin interaction. The extent of boophilin biotinylation was determined using matrix-assisted laser desorption/ionization-time of flight/time of flight mass spectrometry. Boophilin immobilization and thrombin adsorption were quantified using quartz crystal microbalance with dissipation. Thrombin competitive adsorption from human serum was assessed using 125I-thrombin. Thrombin inhibition and plasma clotting time were determined using spectrophotometric techniques. Boophilin-coated SAM were able to promote thrombin adsorption in a selective way, inhibiting most of its activity and delaying plasma coagulation in comparison with boophilin-free surfaces, demonstrating boophilin's potential to improve the hemocompatibility of biomaterials used in the production of blood-contacting devices. © 2012 Acta Materialia Inc.
Keywords: Coagulation; Hemocompatibility; Protein adsorption; Surface functionalization; Thrombin

E-cadherin dysfunction in gastric cancer - Cellular consequences, clinical applications and open questions - Carneiro, P.; Fernandes, M.S.; Figueiredo, J.; Caldeira, J.; Carvalho, J.; Pinheiro, H.; Leite, M.; Melo, S.; Oliveira, P.; Simões-Correia, J.; Oliveira, M.J.; Carneiro, F.; et al. (FEBS LettersFEBS Lett., 2012)
E-cadherin plays a major role in cell-cell adhesion and inactivating germline mutations in its encoding gene predispose to hereditary diffuse gastric cancer. Evidence indicates that aside from its recognized role in early tumourigenesis, E-cadherin is also pivotal for tumour progression, including invasion and metastization. Herein, we discuss E-cadherin alterations found in a cancer context, associated cellular effects and signalling pathways, and we raise new key questions that will impact in the management of GC patients and families. © 2012 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
Keywords: Adhesion; Cadherins; cancer growth; cancer invasion; cancer patient; cancer susceptibility; cell adhesion; complex formation; conference paper; E-cadherin; embryo development; endocytosis; epigenetics; epithelial mesenchymal transition; Gastric cancer; gene mutation; gene silencing; genetic susceptibility; Germ-Line Mutation; HDGC; Helicobacter infection; Helicobacter Infections; Helicobacter pylori; histone deacetylase inhibitor; human; Humans; Invasion; metastasis; molecular pathology; nonhuman; priority journal; protein analysis; protein depletion; protein expression; protein function; protein structure; regulatory mechanism; signal transduction; Signalling; stomach cancer; stomach carcinogenesis; Stomach Neoplasms; Tumour; uvomorulin

Epithelial E- and P-cadherins: Role and clinical significance in cancer - Paredes, J.; Figueiredo, J.; Albergaria, A.; Oliveira, P.; Carvalho, J.; Ribeiro, A.S.; Caldeira, J.; Costa, A.M.; Simões-Correia, J.; Oliveira, M.J.; Pinheiro, H.; Pinho, S.S.; et al. (Biochimica et Biophysica Acta - Reviews on CancerBiochim. Biophys. Acta Rev. Cancer, 2012)
E-cadherin and P-cadherin are major contributors to cell-cell adhesion in epithelial tissues, playing pivotal roles in important morphogenetic and differentiation processes during development, and in maintaining integrity and homeostasis in adult tissues. It is now generally accepted that alterations in these two molecules are observed during tumour progression of most carcinomas. Genetic or epigenetic alterations in E- and P-cadherin-encoding genes (CDH1 and CDH3, respectively), or alterations in their proteins expression, often result in tissue disorder, cellular de-differentiation, increased invasiveness of tumour cells and ultimately in metastasis. In this review, we will discuss the major properties of E- and P-cadherin molecules, its regulation in normal tissue, and their alterations and role in cancer, with a specific focus on gastric and breast cancer models. © 2012 Elsevier B.V.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: BBACEdoi: 10.1016/j.bbcan.2012.05.002Language of Original Document: EnglishCorrespondence Address: Seruca, R.; IPATIMUP, Institute of Molecular Pathology and Immunology, University of Porto, Rua Dr. Roberto Frias s/n, 4200-465 Porto, Portugal; email: rseruca@ipatimup.ptChemicals/CAS: uvomorulin, 112956-45-3Tradenames: pf 03732010References: Cavallaro, U., Christofori, G., Cell adhesion and signalling by cadherins and Ig-CAMs in cancer (2004) Nat. Rev. Cancer, 4, pp. 118-132;Gerrow, K., El-Husseini, A., Cell adhesion molecules at the synapse (2006) Front. Biosci., 11, pp. 2400-2419; Nollet, F., Kools, P., van Roy, F., Phylogenetic analysis of the cadherin superfamily allows identification of six major subfamilies besides several solitary members (2000) J. Mol. Biol., 299, pp. 551-572; Takeichi, M., Cadherins in cancer: implications for invasion and metastasis (1993) Curr. Opin. Cell Biol., 5, pp. 806-811; Pignatelli, M., Bodmer, W.F., Genetics and biochemistry of collagen binding-triggered glandular differentiation in a human colon carcinoma cell line (1988) Proc. Natl. Acad. Sci. U. S. A., 85, pp. 5561-5565; Takeichi, M., Morphogenetic roles of classic cadherins (1995) Curr. Opin. Cell Biol., 7, pp. 619-627; Shapiro, L., Fannon, A.M., Kwong, P.D., Thompson, A., Lehmann, M.S., Grubel, G., Legrand, J.F., Hendrickson, W.A., Structural basis of cell-cell adhesion by cadherins (1995) Nature, 374, pp. 327-337; Ozawa, M., Ringwald, M., Kemler, R., Uvomorulin-catenin complex formation is regulated by a specific domain in the cytoplasmic region of the cell adhesion molecule (1990) Proc. Natl. Acad. Sci. U. S. A., 87, pp. 4246-4250; Blaschuk, O.W., Sullivan, R., David, S., Pouliot, Y., Identification of a cadherin cell adhesion recognition sequence (1990) Dev. Biol., 139, pp. 227-229; Ozawa, M., Baribault, H., Kemler, R., The cytoplasmic domain of the cell adhesion molecule uvomorulin associates with three independent proteins structurally related in different species (1989) EMBO J., 8, pp. 1711-1717; Gumbiner, B.M., McCrea, P.D., Catenins as mediators of the cytoplasmic functions of cadherins (1993) J. Cell Sci. Suppl., 17, pp. 155-158; Yap, A.S., Niessen, C.M., Gumbiner, B.M., The juxtamembrane region of the cadherin cytoplasmic tail supports lateral clustering, adhesive strengthening, and interaction with p120ctn (1998) J. Cell Biol., 141, pp. 779-789; Van Aken, E., De Wever, O., Correia da Rocha, A.S., Mareel, M., Defective E-cadherin/catenin complexes in human cancer (2001) Virchows Arch., 439, pp. 725-751; Mareel, M., Oliveira, M.J., Madani, I., Cancer invasion and metastasis: interacting ecosystems (2009) Virchows Arch., 454, pp. 599-622; Makrilia, N., Kollias, A., Manolopoulos, L., Syrigos, K., Cell adhesion molecules: role and clinical significance in cancer (2009) Cancer Invest., 27, pp. 1023-1037; Bussemakers, M.J., van Bokhoven, A., Voller, M., Smit, F.P., Schalken, J.A., The genes for the calcium-dependent cell adhesion molecules P- and E-cadherin are tandemly arranged in the human genome (1994) Biochem. Biophys. Res. Commun., 203, pp. 1291-1294; Berx, G., Staes, K., van Hengel, J., Molemans, F., Bussemakers, M.J., van Bokhoven, A., van Roy, F., Cloning and characterization of the human invasion suppressor gene E-cadherin (CDH1) (1995) Genomics, 26, pp. 281-289; Jarrard, D.F., Paul, R., van Bokhoven, A., Nguyen, S.H., Bova, G.S., Wheelock, M.J., Johnson, K.R., Isaacs, W.B., P-cadherin is a basal cell-specific epithelial marker that is not expressed in prostate cancer (1997) Clin. Cancer Res., 3, pp. 2121-2128; Hubbard, T.J., Aken, B.L., Ayling, S., Ballester, B., Beal, K., Bragin, E., Brent, S., Flicek, P., Ensembl 2009 (2009) Nucleic Acids Res., 37, pp. D690-D697; Faraldo, M.L., Cano, A., The 5' flanking sequences of the mouse P-cadherin gene. Homologies to 5' sequences of the E-cadherin gene and identification of a first 215 base-pair intron (1993) J. Mol. Biol., 231, pp. 935-941; van Roy, F., Berx, G., The cell-cell adhesion molecule E-cadherin (2008) Cell. Mol. Life Sci., 65, pp. 3756-3788; Stemmler, M.P., Cadherins in development and cancer (2008) Mol. Biosyst., 4, pp. 835-850; Paredes, J., Albergaria, A., Oliveira, J.T., Jeronimo, C., Milanezi, F., Schmitt, F.C., P-cadherin overexpression is an indicator of clinical outcome in invasive breast carcinomas and is associated with CDH3 promoter hypomethylation (2005) Clin. Cancer Res., 11, pp. 5869-5877; Sakharkar, K.R., Chow, V.T., PPD-proteome profile database (2004) In Silico Biol., 4, pp. 219-223; Thomas, D.J., Rosenbloom, K.R., Clawson, H., Hinrichs, A.S., Trumbower, H., Raney, B.J., Karolchik, D., Kent, W.J., The ENCODE Project at UC Santa Cruz (2007) Nucleic Acids Res., 35, pp. D663-D667; Oliveira, P., Sanges, R., Huntsman, D., Stupka, E., Oliveira, C., Characterization of the intronic portion of cadherin superfamily members, common cancer orchestrators (2012) Eur. J. Hum. Genet.; Hosono, S., Gross, I., English, M.A., Hajra, K.M., Fearon, E.R., Licht, J.D., E-cadherin is a WT1 target gene (2000) J. Biol. Chem., 275, pp. 10943-10953; Liu, Y.N., Lee, W.W., Wang, C.Y., Chao, T.H., Chen, Y., Chen, J.H., Regulatory mechanisms controlling human E-cadherin gene expression (2005) Oncogene, 24, pp. 8277-8290; Behrens, J., Lowrick, O., Klein-Hitpass, L., Birchmeier, W., The E-cadherin promoter: functional analysis of a G.C-rich region and an epithelial cell-specific palindromic regulatory element (1991) Proc. Natl. Acad. Sci. U. S. A., 88, pp. 11495-11499; Cano, A., Perez-Moreno, M.A., Rodrigo, I., Locascio, A., Blanco, M.J., del Barrio, M.G., Portillo, F., Nieto, M.A., The transcription factor snail controls epithelial-mesenchymal transitions by repressing E-cadherin expression (2000) Nat. Cell Biol., 2, pp. 76-83; Hajra, K.M., Chen, D.Y., Fearon, E.R., The SLUG zinc-finger protein represses E-cadherin in breast cancer (2002) Cancer Res., 62, pp. 1613-1618; Perez-Moreno, M.A., Locascio, A., Rodrigo, I., Dhondt, G., Portillo, F., Nieto, M.A., Cano, A., A new role for E12/E47 in the repression of E-cadherin expression and epithelial-mesenchymal transitions (2001) J. Biol. Chem., 276, pp. 27424-27431; Comijn, J., Berx, G., Vermassen, P., Verschueren, K., van Grunsven, L., Bruyneel, E., Mareel, M., van Roy, F., The two-handed E box binding zinc finger protein SIP1 downregulates E-cadherin and induces invasion (2001) Mol. Cell, 7, pp. 1267-1278; Eger, A., Aigner, K., Sonderegger, S., Dampier, B., Oehler, S., Schreiber, M., Berx, G., Foisner, R., DeltaEF1 is a transcriptional repressor of E-cadherin and regulates epithelial plasticity in breast cancer cells (2005) Oncogene, 24, pp. 2375-2385; Peinado, H., Olmeda, D., Cano, A., Snail, Zeb and bHLH factors in tumour progression: an alliance against the epithelial phenotype? (2007) Nat. Rev. Cancer, 7, pp. 415-428; Shi, Y., Sawada, J., Sui, G., Affar el, B., Whetstine, J.R., Lan, F., Ogawa, H., Nakatani, Y., Coordinated histone modifications mediated by a CtBP co-repressor complex (2003) Nature, 422, pp. 735-738; Jamora, C., DasGupta, R., Kocieniewski, P., Fuchs, E., Links between signal transduction, transcription and adhesion in epithelial bud development (2003) Nature, 422, pp. 317-322; Vandewalle, C., Comijn, J., De Craene, B., Vermassen, P., Bruyneel, E., Andersen, H., Tulchinsky, E., Berx, G., SIP1/ZEB2 induces EMT by repressing genes of different epithelial cell-cell junctions (2005) Nucleic Acids Res., 33, pp. 6566-6578; Aigner, K., Dampier, B., Descovich, L., Mikula, M., Sultan, A., Schreiber, M., Mikulits, W., Eger, A., The transcription factor ZEB1 (deltaEF1) promotes tumour cell dedifferentiation by repressing master regulators of epithelial polarity (2007) Oncogene, 26, pp. 6979-6988; Spaderna, S., Schmalhofer, O., Wahlbuhl, M., Dimmler, A., Bauer, K., Sultan, A., Hlubek, F., Brabletz, T., The transcriptional repressor ZEB1 promotes metastasis and loss of cell polarity in cancer (2008) Cancer Res., 68, pp. 537-544; Graff, J.R., Herman, J.G., Lapidus, R.G., Chopra, H., Xu, R., Jarrard, D.F., Isaacs, W.B., Baylin, S.B., E-cadherin expression is silenced by DNA hypermethylation in human breast and prostate carcinomas (1995) Cancer Res., 55, pp. 5195-5199; Shimomura, Y., Wajid, M., Shapiro, L., Christiano, A.M., P-cadherin is a p63 target gene with a crucial role in the developing human limb bud and hair follicle (2008) Development, 135, pp. 743-753; Carroll, D.K., Carroll, J.S., Leong, C.O., Cheng, F., Brown, M., Mills, A.A., Brugge, J.S., Ellisen, L.W., P63 regulates an adhesion programme and cell survival in epithelial cells (2006) Nat. Cell Biol., 8, pp. 551-561; Faraldo, M.M., Teuliere, J., Deugnier, M.A., Birchmeier, W., Huelsken, J., Thiery, J.P., Cano, A., Glukhova, M.A., Beta-catenin regulates P-cadherin expression in mammary basal epithelial cells (2007) FEBS Lett., 581, pp. 831-836; Le, T.L., Yap, A.S., Stow, J.L., Recycling of E-cadherin: a potential mechanism for regulating cadherin dynamics (1999) J. Cell Biol., 146, pp. 219-232; Bryant, D.M., Stow, J.L., The ins and outs of E-cadherin trafficking (2004) Trends Cell Biol., 14, pp. 427-434; Hinck, L., Nathke, I.S., Papkoff, J., Nelson, W.J., Dynamics of cadherin/catenin complex formation: novel protein interactions and pathways of complex assembly (1994) J. Cell Biol., 125, pp. 1327-1340; Chen, Y.T., Stewart, D.B., Nelson, W.J., Coupling assembly of the E-cadherin/beta-catenin complex to efficient endoplasmic reticulum exit and basal-lateral membrane targeting of E-cadherin in polarized MDCK cells (1999) J. Cell Biol., 144, pp. 687-699; Lock, J.G., Stow, J.L., Rab11 in recycling endosomes regulates the sorting and basolateral transport of E-cadherin (2005) Mol. Biol. Cell, 16, pp. 1744-1755; Bryant, D.M., Kerr, M.C., Hammond, L.A., Joseph, S.R., Mostov, K.E., Teasdale, R.D., Stow, J.L., EGF induces macropinocytosis and SNX1-modulated recycling of E-cadherin (2007) J. Cell Sci., 120, pp. 1818-1828; Ling, K., Bairstow, S.F., Carbonara, C., Turbin, D.A., Huntsman, D.G., Anderson, R.A., Type I gamma phosphatidylinositol phosphate kinase modulates adherens junction and E-cadherin trafficking via a direct interaction with mu 1B adaptin (2007) J. Cell Biol., 176, pp. 343-353; Mosesson, Y., Mills, G.B., Yarden, Y., Derailed endocytosis: an emerging feature of cancer (2008) Nat. Rev. Cancer, 8, pp. 835-850; Ireton, R.C., Davis, M.A., van Hengel, J., Mariner, D.J., Barnes, K., Thoreson, M.A., Anastasiadis, P.Z., Reynolds, A.B., A novel role for p120 catenin in E-cadherin function (2002) J. Cell Biol., 159, pp. 465-476; Davis, M.A., Ireton, R.C., Reynolds, A.B., A core function for p120-catenin in cadherin turnover (2003) J. Cell Biol., 163, pp. 525-534; Xiao, K., Garner, J., Buckley, K.M., Vincent, P.A., Chiasson, C.M., Dejana, E., Faundez, V., Kowalczyk, A.P., P120-Catenin regulates clathrin-dependent endocytosis of VE-cadherin (2005) Mol. Biol. Cell, 16, pp. 5141-5151; Taniuchi, K., Nakagawa, H., Hosokawa, M., Nakamura, T., Eguchi, H., Ohigashi, H., Ishikawa, O., Nakamura, Y., Overexpressed P-cadherin/CDH3 promotes motility of pancreatic cancer cells by interacting with p120ctn and activating rho-family GTPases (2005) Cancer Res., 65, pp. 3092-3099; Paredes, J., Stove, C., Stove, V., Milanezi, F., Van Marck, V., Derycke, L., Mareel, M., Schmitt, F., P-cadherin is up-regulated by the antiestrogen ICI 182,780 and promotes invasion of human breast cancer cells (2004) Cancer Res., 64, pp. 8309-8317; Palacios, F., Price, L., Schweitzer, J., Collard, J.G., D'Souza-Schorey, C., An essential role for ARF6-regulated membrane traffic in adherens junction turnover and epithelial cell migration (2001) EMBO J., 20, pp. 4973-4986; Figueiredo, J., Simoes-Correia, J., Soderberg, O., Suriano, G., Seruca, R., ADP-ribosylation factor 6 mediates E-cadherin recovery by chemical chaperones (2011) PLoS One, 6, pp. e23188; Palacios, F., Schweitzer, J.K., Boshans, R.L., D'Souza-Schorey, C., ARF6-GTP recruits Nm23-H1 to facilitate dynamin-mediated endocytosis during adherens junctions disassembly (2002) Nat. Cell Biol., 4, pp. 929-936; Otsuki, Y., Tanaka, M., Yoshii, S., Kawazoe, N., Nakaya, K., Sugimura, H., Tumor metastasis suppressor nm23H1 regulates Rac1 GTPase by interaction with Tiam1 (2001) Proc. Natl. Acad. Sci. U. S. A., 98, pp. 4385-4390; Morishige, M., Hashimoto, S., Ogawa, E., Toda, Y., Kotani, H., Hirose, M., Wei, S., Sabe, H., GEP100 links epidermal growth factor receptor signalling to Arf6 activation to induce breast cancer invasion (2008) Nat. Cell Biol., 10, pp. 85-92; Daniel, J.M., Reynolds, A.B., Tyrosine phosphorylation and cadherin/catenin function (1997) Bioessays, 19, pp. 883-891; Palacios, F., Tushir, J.S., Fujita, Y., D'Souza-Schorey, C., Lysosomal targeting of E-cadherin: a unique mechanism for the down-regulation of cell-cell adhesion during epithelial to mesenchymal transitions (2005) Mol. Cell. Biol., 25, pp. 389-402; Fujita, Y., Krause, G., Scheffner, M., Zechner, D., Leddy, H.E., Behrens, J., Sommer, T., Birchmeier, W., Hakai, a c-Cbl-like protein, ubiquitinates and induces endocytosis of the E-cadherin complex (2002) Nat. Cell Biol., 4, pp. 222-231; Pinho, S.S., Seruca, R., Gartner, F., Yamaguchi, Y., Gu, J., Taniguchi, N., Reis, C.A., Modulation of E-cadherin function and dysfunction by N-glycosylation (2011) Cell. Mol. Life Sci., 68, pp. 1011-1020; Zhu, W., Leber, B., Andrews, D.W., Cytoplasmic O-glycosylation prevents cell surface transport of E-cadherin during apoptosis (2001) EMBO J., 20, pp. 5999-6007; Zhou, F., Su, J., Fu, L., Yang, Y., Zhang, L., Wang, L., Zhao, H., Zha, X., Unglycosylation at Asn-633 made extracellular domain of E-cadherin folded incorrectly and arrested in endoplasmic reticulum, then sequentially degraded by ERAD (2008) Glycoconj. J., 25, pp. 727-740; Liwosz, A., Lei, T., Kukuruzinska, M.A., N-glycosylation affects the molecular organization and stability of E-cadherin junctions (2006) J. Biol. Chem., 281, pp. 23138-23149; Pinho, S.S., Reis, C.A., Paredes, J., Magalhaes, A.M., Ferreira, A.C., Figueiredo, J., Xiaogang, W., Seruca, R., The role of N-acetylglucosaminyltransferase III and V in the post-transcriptional modifications of E-cadherin (2009) Hum. Mol. Genet., 18, pp. 2599-2608; Pinho, S.S., Oliveira, P., Cabral, J., Carvalho, S., Huntsman, D., Gartner, F., Seruca, R., Oliveira, C., Loss and recovery of Mgat3 and GnT-III mediated E-cadherin N-glycosylation is a mechanism involved in epithelial-mesenchymal-epithelial transitions (2012) PLoS One, 7, pp. e33191; Osumi, D., Takahashi, M., Miyoshi, E., Yokoe, S., Lee, S.H., Noda, K., Nakamori, S., Taniguchi, N., Core fucosylation of E-cadherin enhances cell-cell adhesion in human colon carcinoma WiDr cells (2009) Cancer Sci., 100, pp. 888-895; Takeichi, M., Functional correlation between cell adhesive properties and some cell surface proteins (1977) J. Cell Biol., 75, pp. 464-474; Hyafil, F., Morello, D., Babinet, C., Jacob, F., A cell surface glycoprotein involved in the compaction of embryonal carcinoma cells and cleavage stage embryos (1980) Cell, 21, pp. 927-934; Ogou, S., Okada, T.S., Takeichi, M., Cleavage stage mouse embryos share a common cell adhesion system with teratocarcinoma cells (1982) Dev. Biol., 92, pp. 521-528; Takeichi, M., The cadherins: cell-cell adhesion molecules controlling animal morphogenesis (1988) Development, 102, pp. 639-655; Fleming, T.P., Javed, Q., Hay, M., Epithelial differentiation and intercellular junction formation in the mouse early embryo (1992) Dev. Suppl., pp. 105-112; Aplin, J.D., Jones, C.J., Harris, L.K., Adhesion molecules in human trophoblast-a review. I. Villous trophoblast (2009) Placenta, 30, pp. 293-298; Nose, A., Takeichi, M., A novel cadherin cell adhesion molecule: its expression patterns associated with implantation and organogenesis of mouse embryos (1986) J. Cell Biol., 103, pp. 2649-2658; Larue, L., Ohsugi, M., Hirchenhain, J., Kemler, R., E-cadherin null mutant embryos fail to form a trophectoderm epithelium (1994) Proc. Natl. Acad. Sci. U. S. A., 91, pp. 8263-8267; Riethmacher, D., Brinkmann, V., Birchmeier, C., A targeted mutation in the mouse E-cadherin gene results in defective preimplantation development (1995) Proc. Natl. Acad. Sci. U. S. A., 92, pp. 855-859; Radice, G.L., Ferreira-Cornwell, M.C., Robinson, S.D., Rayburn, H., Chodosh, L.A., Takeichi, M., Hynes, R.O., Precocious mammary gland development in P-cadherin-deficient mice (1997) J. Cell Biol., 139, pp. 1025-1032; Frebourg, T., Oliveira, C., Hochain, P., Karam, R., Manouvrier, S., Graziadio, C., Vekemans, M., Seruca, R., Cleft lip/palate and CDH1/E-cadherin mutations in families with hereditary diffuse gastric cancer (2006) J. Med. Genet., 43, pp. 138-142; Kjaer, K.W., Hansen, L., Schwabe, G.C., Marques-de-Faria, A.P., Eiberg, H., Mundlos, S., Tommerup, N., Rosenberg, T., Distinct CDH3 mutations cause ectodermal dysplasia, ectrodactyly, macular dystrophy (EEM syndrome) (2005) J. Med. Genet., 42, pp. 292-298; Sprecher, E., Bergman, R., Richard, G., Lurie, R., Shalev, S., Petronius, D., Shalata, A., Szargel, R., Hypotrichosis with juvenile macular dystrophy is caused by a mutation in CDH3, encoding P-cadherin (2001) Nat. Genet., 29, pp. 134-136; Nelson, W.J., Epithelial cell polarity from the outside looking in (2003) News Physiol. Sci., 18, pp. 143-146; Hirai, Y., Nose, A., Kobayashi, S., Takeichi, M., Expression and role of E- and P-cadherin adhesion molecules in embryonic histogenesis. II. Skin morphogenesis (1989) Development, 105, pp. 271-277; Berx, G., Van Roy, F., The E-cadherin/catenin complex: an important gatekeeper in breast cancer tumorigenesis and malignant progression (2001) Breast Cancer Res., 3, pp. 289-293; Shimoyama, Y., Hirohashi, S., Expression of E- and P-cadherin in gastric carcinomas (1991) Cancer Res., 51, pp. 2185-2192; Hines, M.D., Jin, H.C., Wheelock, M.J., Jensen, P.J., Inhibition of cadherin function differentially affects markers of terminal differentiation in cultured human keratinocytes (1999) J. Cell Sci., 112 (PART 24), pp. 4569-4579; Ribeiro, A.S., Albergaria, A., Sousa, B., Correia, A.L., Bracke, M., Seruca, R., Schmitt, F.C., Paredes, J., Extracellular cleavage and shedding of P-cadherin: a mechanism underlying the invasive behaviour of breast cancer cells (2010) Oncogene, 29, pp. 392-402; Moll, R., Mitze, M., Frixen, U.H., Birchmeier, W., Differential loss of E-cadherin expression in infiltrating ductal and lobular breast carcinomas (1993) Am. J. Pathol., 143, pp. 1731-1742; Gamallo, C., Palacios, J., Suarez, A., Pizarro, A., Navarro, P., Quintanilla, M., Cano, A., Correlation of E-cadherin expression with differentiation grade and histological type in breast carcinoma (1993) Am. J. Pathol., 142, pp. 987-993; Reis-Filho, J.S., Cancela Paredes, J., Milanezi, F., Schmitt, F.C., Clinicopathologic implications of E-cadherin reactivity in patients with lobular carcinoma in situ of the breast (2002) Cancer, 94, pp. 2114-2115; author reply 2115-2116Weigelt, B., Geyer, F.C., Natrajan, R., Lopez-Garcia, M.A., Ahmad, A.S., Savage, K., Kreike, B., Reis-Filho, J.S., The molecular underpinning of lobular histological growth pattern: a genome-wide transcriptomic analysis of invasive lobular carcinomas and grade- and molecular subtype-matched invasive ductal carcinomas of no special type (2010) J. Pathol., 220, pp. 45-57; Simpson, P.T., Reis-Filho, J.S., Lambros, M.B., Jones, C., Steele, D., Mackay, A., Iravani, M., Lakhani, S.R., Molecular profiling pleomorphic lobular carcinomas of the breast: evidence for a common molecular genetic pathway with classic lobular carcinomas (2008) J. Pathol., 215, pp. 231-244; Mahler-Araujo, B., Savage, K., Parry, S., Reis-Filho, J.S., Reduction of E-cadherin expression is associated with non-lobular breast carcinomas of basal-like and triple negative phenotype (2008) J. Clin. Pathol., 61, pp. 615-620; Lopes, N., Carvalho, J., Duraes, C., Sousa, B., Gomes, M., Costa, J.L., Oliveira, C., Schmitt, F., 1Alpha,25-dihydroxyvitamin D3 induces de novo E-cadherin expression in triple-negative breast cancer cells by CDH1-promoter demethylation (2012) Anticancer. Res., 32, pp. 249-257; Berx, G., Cleton-Jansen, A.M., Strumane, K., de Leeuw, W.J., Nollet, F., van Roy, F., Cornelisse, C., E-cadherin is inactivated in a majority of invasive human lobular breast cancers by truncation mutations throughout its extracellular domain (1996) Oncogene, 13, pp. 1919-1925; Keller, G., Vogelsang, H., Becker, I., Hutter, J., Ott, K., Candidus, S., Grundei, T., Hofler, H., Diffuse type gastric and lobular breast carcinoma in a familial gastric cancer patient with an E-cadherin germline mutation (1999) Am. J. Pathol., 155, pp. 337-342; Schrader, K.A., Masciari, S., Boyd, N., Wiyrick, S., Kaurah, P., Senz, J., Burke, W., Huntsman, D.G., Hereditary diffuse gastric cancer: association with lobular breast cancer (2008) Fam. Cancer, 7, pp. 73-82; Becker, K.F., Atkinson, M.J., Reich, U., Becker, I., Nekarda, H., Siewert, J.R., Hofler, H., E-cadherin gene mutations provide clues to diffuse type gastric carcinomas (1994) Cancer Res., 54, pp. 3845-3852; Becker, K.F., Kremmer, E., Eulitz, M., Becker, I., Handschuh, G., Schuhmacher, C., Muller, W., Hofler, H., Analysis of E-cadherin in diffuse-type gastric cancer using a mutation-specific monoclonal antibody (1999) Am. J. Pathol., 155, pp. 1803-1809; Machado, J.C., Carneiro, F., Beck, S., Rossi, S., Lopes, J., Taveira-Gomes, A., Cardoso-Oliveira, M., E-cadherin expression is correlated with the isolated cell/diffuse histotype and with features of biological aggressiveness of gastric carcinoma (1998) Int. J. Surg. Pathol., 6, pp. 135-144; Carneiro, F., Machado, J.C., Seruca, R., Sobrinho-Simoes, M., E-cadherin changes in gastric carcimona (1999) Histopathology, 35, pp. 477-478; Carvalho, J., van Grieken, N.C., Pereira, P.M., Sousa, S., Tijssen, M., Buffart, T.E., Diosdado, B., Oliveira, C., Lack of microRNA-101 causes E-cadherin functional deregulation through EZH2 upregulation in intestinal gastric cancer (2012) J. Pathol.; Machado, J.C., Oliveira, C., Carvalho, R., Soares, P., Berx, G., Caldas, C., Seruca, R., Sobrinho-Simoes, M., E-cadherin gene (CDH1) promoter methylation as the second hit in sporadic diffuse gastric carcinoma (2001) Oncogene, 20, pp. 1525-1528; Guilford, P., Hopkins, J., Harraway, J., McLeod, M., McLeod, N., Harawira, P., Taite, H., Reeve, A.E., E-cadherin germline mutations in familial gastric cancer (1998) Nature, 392, pp. 402-405; Oliveira, C., Senz, J., Kaurah, P., Pinheiro, H., Sanges, R., Haegert, A., Corso, G., Huntsman, D., Germline CDH1 deletions in hereditary diffuse gastric cancer families (2009) Hum. Mol. Genet., 18, pp. 1545-1555; Pinheiro, H., Bordeira-Carrico, R., Seixas, S., Carvalho, J., Senz, J., Oliveira, P., Inacio, P., Oliveira, C., Allele-specific CDH1 downregulation and hereditary diffuse gastric cancer (2010) Hum. Mol. Genet., 19, pp. 943-952; Guilford, P., Humar, B., Blair, V., Hereditary diffuse gastric cancer: translation of CDH1 germline mutations into clinical practice (2010) Gastric Cancer, 13, pp. 1-10; Suriano, G., Seixas, S., Rocha, J., Seruca, R., A model to infer the pathogenic significance of CDH1 germline missense variants (2006) J. Mol. Med., 84, pp. 1023-1031; Suriano, G., Oliveira, C., Ferreira, P., Machado, J.C., Bordin, M.C., De Wever, O., Bruyneel, E.A., Seruca, R., Identification of CDH1 germline missense mutations associated with functional inactivation of the E-cadherin protein in young gastric cancer probands (2003) Hum. Mol. Genet., 12, pp. 575-582; Suriano, G., Oliveira, M.J., Huntsman, D., Mateus, A.R., Ferreira, P., Casares, F., Oliveira, C., Seruca, R., E-cadherin germline missense mutations and cell phenotype: evidence for the independence of cell invasion on the motile capabilities of the cells (2003) Hum. Mol. Genet., 12, pp. 3007-3016; Brooks-Wilson, A.R., Kaurah, P., Suriano, G., Leach, S., Senz, J., Grehan, N., Butterfield, Y.S., Huntsman, D., Germline E-cadherin mutations in hereditary diffuse gastric cancer: assessment of 42 new families and review of genetic screening criteria (2004) J. Med. Genet., 41, pp. 508-517; Kaurah, P., MacMillan, A., Boyd, N., Senz, J., De Luca, A., Chun, N., Suriano, G., Huntsman, D., Founder and recurrent CDH1 mutations in families with hereditary diffuse gastric cancer (2007) JAMA, 297, pp. 2360-2372; Corso, G., Roviello, F., Paredes, J., Pedrazzani, C., Novais, M., Correia, J., Marrelli, D., Suriano, G., Characterization of the P373L E-cadherin germline missense mutation and implication for clinical management (2007) Eur. J. Surg. Oncol., 33, pp. 1061-1067; More, H., Humar, B., Weber, W., Ward, R., Christian, A., Lintott, C., Graziano, F., Guilford, P., Identification of seven novel germline mutations in the human E-cadherin (CDH1) gene (2007) Hum. Mutat., 28, p. 203; Oliveira, C., de Bruin, J., Nabais, S., Ligtenberg, M., Moutinho, C., Nagengast, F.M., Seruca, R., Carneiro, F., Intragenic deletion of CDH1 as the inactivating mechanism of the wild-type allele in an HDGC tumour (2004) Oncogene, 23, pp. 2236-2240; Barber, M., Murrell, A., Ito, Y., Maia, A.T., Hyland, S., Oliveira, C., Save, V., Fitzgerald, R.C., Mechanisms and sequelae of E-cadherin silencing in hereditary diffuse gastric cancer (2008) J. Pathol., 216, pp. 295-306; Oliveira, C., Sousa, S., Pinheiro, H., Karam, R., Bordeira-Carrico, R., Senz, J., Kaurah, P., Seruca, R., Quantification of epigenetic and genetic 2nd hits in CDH1 during hereditary diffuse gastric cancer syndrome progression (2009) Gastroenterology, 136, pp. 2137-2148; Grady, W.M., Willis, J., Guilford, P.J., Dunbier, A.K., Toro, T.T., Lynch, H., Wiesner, G., Markowitz, S., Methylation of the CDH1 promoter as the second genetic hit in hereditary diffuse gastric cancer (2000) Nat. Genet., 26, pp. 16-17; Peinado, H., Ballestar, E., Esteller, M., Cano, A., Snail mediates E-cadherin repression by the recruitment of the Sin3A/histone deacetylase 1 (HDAC1)/HDAC2 complex (2004) Mol. Cell. Biol., 24, pp. 306-319; Fujii, S., Ochiai, A., Enhancer of zeste homolog 2 downregulates E-cadherin by mediating histone H3 methylation in gastric cancer cells (2008) Cancer Sci., 99, pp. 738-746; Cao, Q., Yu, J., Dhanasekaran, S.M., Kim, J.H., Mani, R.S., Tomlins, S.A., Mehra, R., Chinnaiyan, A.M., Repression of E-cadherin by the polycomb group protein EZH2 in cancer (2008) Oncogene, 27, pp. 7274-7284; Pena, C., Garcia, J.M., Silva, J., Garcia, V., Rodriguez, R., Alonso, I., Millan, I., Bonilla, F., E-cadherin and vitamin D receptor regulation by SNAIL and ZEB1 in colon cancer: clinicopathological correlations (2005) Hum. Mol. Genet., 14, pp. 3361-3370; Liu, Y., Hong, Y., Zhao, Y., Ismail, T.M., Wong, Y., Eu, K.W., Histone H3 (lys-9) deacetylation is associated with transcriptional silencing of E-cadherin in colorectal cancer cell lines (2008) Cancer Invest., 26, pp. 575-582; von Burstin, J., Eser, S., Paul, M.C., Seidler, B., Brandl, M., Messer, M., von Werder, A., Saur, D., E-cadherin regulates metastasis of pancreatic cancer in vivo and is suppressed by a SNAIL/HDAC1/HDAC2 repressor complex (2009) Gastroenterology, 137, pp. 361-371. , (371 e361-365); Herranz, N., Pasini, D., Diaz, V.M., Franci, C., Gutierrez, A., Dave, N., Escriva, M., Peiro, S., Polycomb complex 2 is required for E-cadherin repression by the Snail1 transcription factor (2008) Mol. Cell. Biol., 28, pp. 4772-4781; Ambros, V., The functions of animal microRNAs (2004) Nature, 431, pp. 350-355; He, L., Hannon, G.J., MicroRNAs: small RNAs with a big role in gene regulation (2004) Nat. Rev. Genet., 5, pp. 522-531; Hurteau, G.J., Carlson, J.A., Spivack, S.D., Brock, G.J., Overexpression of the microRNA hsa-miR-200c leads to reduced expression of transcription factor 8 and increased expression of E-cadherin (2007) Cancer Res., 67, pp. 7972-7976; Korpal, M., Lee, E.S., Hu, G., Kang, Y., The miR-200 family inhibits epithelial-mesenchymal transition and cancer cell migration by direct targeting of E-cadherin transcriptional repressors ZEB1 and ZEB2 (2008) J. Biol. Chem., 283, pp. 14910-14914; Gregory, P.A., Bert, A.G., Paterson, E.L., Barry, S.C., Tsykin, A., Farshid, G., Vadas, M.A., Goodall, G.J., The miR-200 family and miR-205 regulate epithelial to mesenchymal transition by targeting ZEB1 and SIP1 (2008) Nat. Cell Biol., 10, pp. 593-601; Park, S.M., Gaur, A.B., Lengyel, E., Peter, M.E., The miR-200 family determines the epithelial phenotype of cancer cells by targeting the E-cadherin repressors ZEB1 and ZEB2 (2008) Genes Dev., 22, pp. 894-907; Tan, H.X., Wang, Q., Chen, L.Z., Huang, X.H., Chen, J.S., Fu, X.H., Cao, L.Q., Zhang, L.J., MicroRNA-9 reduces cell invasion and E-cadherin secretion in SK-Hep-1 cell (2010) Med. Oncol., 27, pp. 654-660; Ma, L., Young, J., Prabhala, H., Pan, E., Mestdagh, P., Muth, D., Teruya-Feldstein, J., Weinberg, R.A., MiR-9, a MYC/MYCN-activated microRNA, regulates E-cadherin and cancer metastasis (2010) Nat. Cell Biol., 12, pp. 247-256; Oki, Y., Issa, J.P., Epigenetic mechanisms in AML-a target for therapy (2010) Cancer Treat. Res., 145, pp. 19-40; Simoes-Correia, J., Figueiredo, J., Oliveira, C., van Hengel, J., Seruca, R., van Roy, F., Suriano, G., Endoplasmic reticulum quality control: a new mechanism of E-cadherin regulation and its implication in cancer (2008) Hum. Mol. Genet., 17, pp. 3566-3576; Sitia, R., Braakman, I., Quality control in the endoplasmic reticulum protein factory (2003) Nature, 426, pp. 891-894; Meusser, B., Hirsch, C., Jarosch, E., Sommer, T., ERAD: the long road to destruction (2005) Nat. Cell Biol., 7, pp. 766-772; van Hengel, J., van Roy, F., Diverse functions of p120ctn in tumors (2007) Biochim. Biophys. Acta, 1773, pp. 78-88; Jawhari, A.U., Noda, M., Pignatelli, M., Farthing, M., Up-regulated cytoplasmic expression, with reduced membranous distribution, of the src substrate p120(ctn) in gastric carcinoma (1999) J. Pathol., 189, pp. 180-185; Karayiannakis, A.J., Syrigos, K.N., Alexiou, D., Kalahanis, N., Rosenberg, T., Bastounis, E., Pignatelli, M., Expression patterns of the novel catenin p120cas in gastrointestinal cancers (1999) Anticancer. Res., 19, pp. 4401-4405; Karatzas, G., Karayiannakis, A.J., Syrigos, K.N., Chatzigianni, E., Papanikolaou, S., Simatos, G., Papanikolaou, D., Bogris, S., Expression patterns of the E-cadherin-catenin cell-cell adhesion complex in gastric cancer (2000) Hepatogastroenterology, 47, pp. 1465-1469; Apweiler, R., Hermjakob, H., Sharon, N., On the frequency of protein glycosylation, as deduced from analysis of the SWISS-PROT database (1999) Biochim. Biophys. Acta, 1473, pp. 4-8; Dube, D.H., Bertozzi, C.R., Glycans in cancer and inflammation-potential for therapeutics and diagnostics (2005) Nat. Rev. Drug Discov., 4, pp. 477-488; Pinho, S.S., Osorio, H., Nita-Lazar, M., Gomes, J., Lopes, C., Gartner, F., Reis, C.A., Role of E-cadherin N-glycosylation profile in a mammary tumor model (2009) Biochem. Biophys. Res. Commun., 379, pp. 1091-1096; Iijima, J., Zhao, Y., Isaji, T., Kameyama, A., Nakaya, S., Wang, X., Ihara, H., Gu, J., Cell-cell interaction-dependent regulation of N-acetylglucosaminyltransferase III and the bisected N-glycans in GE11 epithelial cells. Involvement of E-cadherin-mediated cell adhesion (2006) J. Biol. Chem., 281, pp. 13038-13046; Yoshimura, M., Ihara, Y., Matsuzawa, Y., Taniguchi, N., Aberrant glycosylation of E-cadherin enhances cell-cell binding to suppress metastasis (1996) J. Biol. Chem., 271, pp. 13811-13815; Giles, R.H., van Es, J.H., Clevers, H., Caught up in a Wnt storm: Wnt signaling in cancer (2003) Biochim. Biophys. Acta, 1653, pp. 1-24; Reynolds, A.B., Roczniak-Ferguson, A., Emerging roles for p120-catenin in cell adhesion and cancer (2004) Oncogene, 23, pp. 7947-7956; Christofori, G., Changing neighbours, changing behaviour: cell adhesion molecule-mediated signalling during tumour progression (2003) EMBO J., 22, pp. 2318-2323; Gottardi, C.J., Wong, E., Gumbiner, B.M., E-cadherin suppresses cellular transformation by inhibiting beta-catenin signaling in an adhesion-independent manner (2001) J. Cell Biol., 153, pp. 1049-1060; Stockinger, A., Eger, A., Wolf, J., Beug, H., Foisner, R., E-cadherin regulates cell growth by modulating proliferation-dependent beta-catenin transcriptional activity (2001) J. Cell Biol., 154, pp. 1185-1196; Suriano, G., Mulholland, D., de Wever, O., Ferreira, P., Mateus, A.R., Bruyneel, E., Nelson, C.C., Seruca, R., The intracellular E-cadherin germline mutation V832 M lacks the ability to mediate cell-cell adhesion and to suppress invasion (2003) Oncogene, 22, pp. 5716-5719; Sahai, E., Marshall, C.J., RHO-GTPases and cancer (2002) Nat. Rev. Cancer, 2, pp. 133-142; Deplazes, J., Fuchs, M., Rauser, S., Genth, H., Lengyel, E., Busch, R., Luber, B., Rac1 and Rho contribute to the migratory and invasive phenotype associated with somatic E-cadherin mutation (2009) Hum. Mol. Genet., 18, pp. 3632-3644; Mateus, A.R., Seruca, R., Machado, J.C., Keller, G., Oliveira, M.J., Suriano, G., Luber, B., EGFR regulates RhoA-GTP dependent cell motility in E-cadherin mutant cells (2007) Hum. Mol. Genet., 16, pp. 1639-1647; Mateus, A.R., Simoes-Correia, J., Figueiredo, J., Heindl, S., Alves, C.C., Suriano, G., Luber, B., Seruca, R., E-cadherin mutations and cell motility: a genotype-phenotype correlation (2009) Exp. Cell Res., 315, pp. 1393-1402; Crepaldi, T., Pollack, A.L., Prat, M., Zborek, A., Mostov, K., Comoglio, P.M., Targeting of the SF/HGF receptor to the basolateral domain of polarized epithelial cells (1994) J. Cell Biol., 125, pp. 313-320; Pece, S., Gutkind, J.S., Signaling from E-cadherins to the MAPK pathway by the recruitment and activation of epidermal growth factor receptors upon cell-cell contact formation (2000) J. Biol. Chem., 275, pp. 41227-41233; Thiery, J.P., Epithelial-mesenchymal transitions in tumour progression (2002) Nat. Rev. Cancer, 2, pp. 442-454; Qian, X., Karpova, T., Sheppard, A.M., McNally, J., Lowy, D.R., E-cadherin-mediated adhesion inhibits ligand-dependent activation of diverse receptor tyrosine kinases (2004) EMBO J., 23, pp. 1739-1748; Takahashi, K., Suzuki, K., Density-dependent inhibition of growth involves prevention of EGF receptor activation by E-cadherin-mediated cell-cell adhesion (1996) Exp. Cell Res., 226, pp. 214-222; Mook, O.R., Frederiks, W.M., Van Noorden, C.J., The role of gelatinases in colorectal cancer progression and metastasis (2004) Biochim. Biophys. Acta, 1705, pp. 69-89; Munshi, H.G., Ghosh, S., Mukhopadhyay, S., Wu, Y.I., Sen, R., Green, K.J., Stack, M.S., Proteinase suppression by E-cadherin-mediated cell-cell attachment in premalignant oral keratinocytes (2002) J. Biol. Chem., 277, pp. 38159-38167; Lochter, A., Galosy, S., Muschler, J., Freedman, N., Werb, Z., Bissell, M.J., Matrix metalloproteinase stromelysin-1 triggers a cascade of molecular alterations that leads to stable epithelial-to-mesenchymal conversion and a premalignant phenotype in mammary epithelial cells (1997) J. Cell Biol., 139, pp. 1861-1872; Davies, G., Jiang, W.G., Mason, M.D., Matrilysin mediates extracellular cleavage of E-cadherin from prostate cancer cells: a key mechanism in hepatocyte growth factor/scatter factor-induced cell-cell dissociation and in vitro invasion (2001) Clin. Cancer Res., 7, pp. 3289-3297; Noe, V., Fingleton, B., Jacobs, K., Crawford, H.C., Vermeulen, S., Steelant, W., Bruyneel, E., Mareel, M., Release of an invasion promoter E-cadherin fragment by matrilysin and stromelysin-1 (2001) J. Cell Sci., 114, pp. 111-118; Ryniers, F., Stove, C., Goethals, M., Brackenier, L., Noe, V., Bracke, M., Vandekerckhove, J., Bruyneel, E., Plasmin produces an E-cadherin fragment that stimulates cancer cell invasion (2002) Biol. Chem., 383, pp. 159-165; Comoglio, P.M., Boccaccio, C., Trusolino, L., Interactions between growth factor receptors and adhesion molecules: breaking the rules (2003) Curr. Opin. Cell Biol., 15, pp. 565-571; Ferreira, P., Oliveira, M.J., Beraldi, E., Mateus, A.R., Nakajima, T., Gleave, M., Yokota, J., Suriano, G., Loss of functional E-cadherin renders cells more resistant to the apoptotic agent taxol in vitro (2005) Exp. Cell Res., 310, pp. 99-104; Ferreira, A.C., Suriano, G., Mendes, N., Gomes, B., Wen, X., Carneiro, F., Seruca, R., Machado, J.C., E-cadherin impairment increases cell survival through Notch-dependent upregulation of Bcl-2 (2012) Hum. Mol. Genet., 21, pp. 334-343; Huang, F.Y., Chan, A.O., Rashid, A., Wong, D.K., Cho, C.H., Yuen, M.F., Helicobacter pylori induces promoter methylation of E-cadherin via interleukin-1beta activation of nitric oxide production in gastric cancer cells (2012) Cancer; Chan, A.O., Lam, S.K., Wong, B.C., Wong, W.M., Yuen, M.F., Yeung, Y.H., Hui, W.M., Kwong, Y.L., Promoter methylation of E-cadherin gene in gastric mucosa associated with Helicobacter pylori infection and in gastric cancer (2003) Gut, 52, pp. 502-506; Leung, W.K., Man, E.P., Yu, J., Go, M.Y., To, K.F., Yamaoka, Y., Cheng, V.Y., Sung, J.J., Effects of Helicobacter pylori eradication on methylation status of E-cadherin gene in noncancerous stomach (2006) Clin. Cancer Res., 12, pp. 3216-3221; Perri, F., Cotugno, R., Piepoli, A., Merla, A., Quitadamo, M., Gentile, A., Pilotto, A., Andriulli, A., Aberrant DNA methylation in non-neoplastic gastric mucosa of H. pylori infected patients and effect of eradication (2007) Am. J. Gastroenterol., 102, pp. 1361-1371; Chan, A.O., Peng, J.Z., Lam, S.K., Lai, K.C., Yuen, M.F., Cheung, H.K., Kwong, Y.L., Wong, B.C., Eradication of Helicobacter pylori infection reverses E-cadherin promoter hypermethylation (2006) Gut, 55, pp. 463-468; Schirrmeister, W., Gnad, T., Wex, T., Higashiyama, S., Wolke, C., Naumann, M., Lendeckel, U., Ectodomain shedding of E-cadherin and c-Met is induced by Helicobacter pylori infection (2009) Exp. Cell Res., 315, pp. 3500-3508; Hoy, B., Lower, M., Weydig, C., Carra, G., Tegtmeyer, N., Geppert, T., Schroder, P., Wessler, S., Helicobacter pylori HtrA is a new secreted virulence factor that cleaves E-cadherin to disrupt intercellular adhesion (2010) EMBO Rep., 11, pp. 798-804; O'Connor, P.M., Lapointe, T.K., Jackson, S., Beck, P.L., Jones, N.L., Buret, A.G., Helicobacter pylori activates calpain via toll-like receptor 2 to disrupt adherens junctions in human gastric epithelial cells (2011) Infect. Immun., 79, pp. 3887-3894; Conlin, V.S., Curtis, S.B., Zhao, Y., Moore, E.D., Smith, V.C., Meloche, R.M., Finlay, B.B., Buchan, A.M., Helicobacter pylori infection targets adherens junction regulatory proteins and results in increased rates of migration in human gastric epithelial cells (2004) Infect. Immun., 72, pp. 5181-5192; Suzuki, M., Mimuro, H., Suzuki, T., Park, M., Yamamoto, T., Sasakawa, C., Interaction of CagA with Crk plays an important role in Helicobacter pylori-induced loss of gastric epithelial cell adhesion (2005) J. Exp. Med., 202, pp. 1235-1247; Franco, A.T., Israel, D.A., Washington, M.K., Krishna, U., Fox, J.G., Rogers, A.B., Neish, A.S., Peek, R.M., Activation of beta-catenin by carcinogenic Helicobacter pylori (2005) Proc. Natl. Acad. Sci. U. S. A., 102, pp. 10646-10651; Murata-Kamiya, N., Kurashima, Y., Teishikata, Y., Yamahashi, Y., Saito, Y., Higashi, H., Aburatani, H., Hatakeyama, M., Helicobacter pylori CagA interacts with E-cadherin and deregulates the beta-catenin signal that promotes intestinal transdifferentiation in gastric epithelial cells (2007) Oncogene, 26, pp. 4617-4626; Sokolova, O., Bozko, P.M., Naumann, M., Helicobacter pylori suppresses glycogen synthase kinase 3beta to promote beta-catenin activity (2008) J. Biol. Chem., 283, pp. 29367-29374; Ogden, S.R., Wroblewski, L.E., Weydig, C., Romero-Gallo, J., O'Brien, D.P., Israel, D.A., Krishna, U.S., Peek, R.M., P120 and Kaiso regulate Helicobacter pylori-induced expression of matrix metalloproteinase-7 (2008) Mol. Biol. Cell, 19, pp. 4110-4121; Bebb, J.R., Leach, L., Zaitoun, A., Hand, N., Letley, D.P., Thomas, R., Atherton, J.C., Effects of Helicobacter pylori on the cadherin-catenin complex (2006) J. Clin. Pathol., 59, pp. 1261-1266; Oliveira, M.J., Costa, A.M., Costa, A.C., Ferreira, R.M., Sampaio, P., Machado, J.C., Seruca, R., Figueiredo, C., CagA associates with c-Met, E-cadherin, and p120-catenin in a multiproteic complex that suppresses Helicobacter pylori-induced cell-invasive phenotype (2009) J. Infect. Dis., 200, pp. 745-755; Oliveira, M.J., Costa, A.C., Costa, A.M., Henriques, L., Suriano, G., Atherton, J.C., Machado, J.C., Figueiredo, C., Helicobacter pylori induces gastric epithelial cell invasion in a c-Met and type IV secretion system-dependent manner (2006) J. Biol. Chem., 281, pp. 34888-34896; Jang, A.C., Starz-Gaiano, M., Montell, D.J., Modeling migration and metastasis in Drosophila (2007) J. Mammary Gland Biol. Neoplasia, 12, pp. 103-114; Pereira, P.S., Teixeira, A., Pinho, S., Ferreira, P., Fernandes, J., Oliveira, C., Seruca, R., Casares, F., E-cadherin missense mutations, associated with hereditary diffuse gastric cancer (HDGC) syndrome, display distinct invasive behaviors and genetic interactions with the Wnt and Notch pathways in Drosophila epithelia (2006) Hum. Mol. Genet., 15, pp. 1704-1712; Caldeira, J., Pereira, P.S., Suriano, G., Casares, F., Using fruitflies to help understand the molecular mechanisms of human hereditary diffuse gastric cancer (2009) Int. J. Dev. Biol., 53, pp. 1557-1561; Humar, B., Blair, V., Charlton, A., More, H., Martin, I., Guilford, P., E-cadherin deficiency initiates gastric signet-ring cell carcinoma in mice and man (2009) Cancer Res., 69, pp. 2050-2056; Mbalaviele, G., Dunstan, C.R., Sasaki, A., Williams, P.J., Mundy, G.R., Yoneda, T., E-cadherin expression in human breast cancer cells suppresses the development of osteolytic bone metastases in an experimental metastasis model (1996) Cancer Res., 56, pp. 4063-4070; Perl, A.K., Wilgenbus, P., Dahl, U., Semb, H., Christofori, G., A causal role for E-cadherin in the transition from adenoma to carcinoma (1998) Nature, 392, pp. 190-193; Kuwabara, Y., Yamada, T., Yamazaki, K., Du, W.L., Banno, K., Aoki, D., Sakamoto, M., Establishment of an ovarian metastasis model and possible involvement of E-cadherin down-regulation in the metastasis (2008) Cancer Sci., 99, pp. 1933-1939; Shimoyama, Y., Hirohashi, S., Hirano, S., Noguchi, M., Shimosato, Y., Takeichi, M., Abe, O., Cadherin cell-adhesion molecules in human epithelial tissues and carcinomas (1989) Cancer Res., 49, pp. 2128-2133; Sanders, D.S., Bruton, R., Darnton, S.J., Casson, A.G., Hanson, I., Williams, H.K., Jankowski, J., Sequential changes in cadherin-catenin expression associated with the progression and heterogeneity of primary oesophageal squamous carcinoma (1998) Int. J. Cancer, 79, pp. 573-579; Rocha, A.S., Soares, P., Machado, J.C., Maximo, V., Fonseca, E., Franssila, K., Sobrinho-Simoes, M., Mucoepidermoid carcinoma of the thyroid: a tumour histotype characterised by P-cadherin neoexpression and marked abnormalities of E-cadherin/catenins complex (2002) Virchows Arch., 440, pp. 498-504; Kim, M.A., Jung, E.J., Lee, H.S., Lee, H.E., Yang, H.K., Oh, D.Y., Bang, Y.J., Kim, W.H., P-cadherin expression in gastric carcinoma: its regulation mechanism and prognostic significance (2010) Hum. Pathol., 41, pp. 877-885; Imai, K., Hirata, S., Irie, A., Senju, S., Ikuta, Y., Yokomine, K., Harao, M., Nishimura, Y., Identification of a novel tumor-associated antigen, cadherin 3/P-cadherin, as a possible target for immunotherapy of pancreatic, gastric, and colorectal cancers (2008) Clin. Cancer Res., 14, pp. 6487-6495; Lo Muzio, L., Campisi, G., Farina, A., Rubini, C., Pannone, G., Serpico, R., Laino, G., Carinci, F., P-cadherin expression and survival rate in oral squamous cell carcinoma: an immunohistochemical study (2005) BMC Cancer, 5, p. 63; Han, A.C., Edelson, M.I., Peralta Soler, A., Knudsen, K.A., Lifschitz-Mercer, B., Czernobilsky, B., Rosenblum, N.G., Salazar, H., Cadherin expression in glandular tumors of the cervix (2000) Cancer, 89, pp. 2053-2058; Longatto Filho, A., Albergaria, A., Paredes, J., Moreira, M.A., Milanezi, F., Schmitt, F.C., P-cadherin expression in glandular lesions of the uterine cervix detected by liquid-based cytology (2005) Cytopathology, 16, pp. 88-93; Stefansson, I.M., Salvesen, H.B., Akslen, L.A., Prognostic impact of alterations in P-cadherin expression and related cell adhesion markers in endometrial cancer (2004) J. Clin. Oncol., 22, pp. 1242-1252; Moreno-Bueno, G., Hardisson, D., Sarrio, D., Sanchez, C., Cassia, R., Prat, J., Herman, J.G., Palacios, J., Abnormalities of E- and P-cadherin and catenin (beta-, gamma-catenin, and p120ctn) expression in endometrial cancer and endometrial atypical hyperplasia (2003) J. Pathol., 199, pp. 471-478; Quattrocchi, L., Green, A.R., Martin, S., Durrant, L., Deen, S., The cadherin switch in ovarian high-grade serous carcinoma is associated with disease progression (2011) Virchows Arch., 459, pp. 21-29; Sarrio, D., Moreno-Bueno, G., Sanchez-Estevez, C., Banon-Rodriguez, I., Hernandez-Cortes, G., Hardisson, D., Palacios, J., Expression of cadherins and catenins correlates with distinct histologic types of ovarian carcinomas (2006) Hum. Pathol., 37, pp. 1042-1049; Soler, A.P., Harner, G.D., Knudsen, K.A., McBrearty, F.X., Grujic, E., Salazar, H., Han, A.C., Keshgegian, A.A., Expression of P-cadherin identifies prostate-specific-antigen-negative cells in epithelial tissues of male sexual accessory organs and in prostatic carcinomas. Implications for prostate cancer biology (1997) Am. J. Pathol., 151, pp. 471-478; Bryan, R.T., Atherfold, P.A., Yeo, Y., Jones, L.J., Harrison, R.F., Wallace, D.M., Jankowski, J.A., Cadherin switching dictates the biology of transitional cell carcinoma of the bladder: ex vivo and in vitro studies (2008) J. Pathol., 215, pp. 184-194; Matos, I., Dufloth, R., Alvarenga, M., Zeferino, L.C., Schmitt, F., P63, cytokeratin 5, and P-cadherin: three molecular markers to distinguish basal phenotype in breast carcinomas (2005) Virchows Arch., 447, pp. 688-694; Arnes, J.B., Brunet, J.S., Stefansson, I., Begin, L.R., Wong, N., Chappuis, P.O., Akslen, L.A., Foulkes, W.D., Placental cadherin and the basal epithelial phenotype of BRCA1-related breast cancer (2005) Clin. Cancer Res., 11, pp. 4003-4011; Palacios, J., Benito, N., Pizarro, A., Suarez, A., Espada, J., Cano, A., Gamallo, C., Anomalous expression of P-cadherin in breast carcinoma. Correlation with E-cadherin expression and pathological features (1995) Am. J. Pathol., 146, pp. 605-612; Peralta Soler, A., Knudsen, K.A., Salazar, H., Han, A.C., Keshgegian, A.A., P-cadherin expression in breast carcinoma indicates poor survival (1999) Cancer, 86, pp. 1263-1272; Paredes, J., Milanezi, F., Reis-Filho, J.S., Leitao, D., Athanazio, D., Schmitt, F., Aberrant P-cadherin expression: is it associated with estrogen-independent growth in breast cancer? (2002) Pathol. Res. Pract., 198, pp. 795-801; Kovacs, A., Dhillon, J., Walker, R.A., Expression of P-cadherin, but not E-cadherin or N-cadherin, relates to pathological and functional differentiation of breast carcinomas (2003) Mol. Pathol., 56, pp. 318-322; Gamallo, C., Moreno-Bueno, G., Sarrio, D., Calero, F., Hardisson, D., Palacios, J., The prognostic significance of P-cadherin in infiltrating ductal breast carcinoma (2001) Mod. Pathol., 14, pp. 650-654; Paredes, J., Correia, A.L., Ribeiro, A.S., Milanezi, F., Cameselle-Teijeiro, J., Schmitt, F.C., Breast carcinomas that co-express E- and P-cadherin are associated with p120-catenin cytoplasmic localisation and poor patient survival (2008) J. Clin. Pathol., 61, pp. 856-862; Foulkes, W.D., Stefansson, I.M., Chappuis, P.O., Begin, L.R., Goffin, J.R., Wong, N., Trudel, M., Akslen, L.A., Germline BRCA1 mutations and a basal epithelial phenotype in breast cancer (2003) J. Natl. Cancer Inst., 95, pp. 1482-1485; Lakhani, S.R., Reis-Filho, J.S., Fulford, L., Penault-Llorca, F., van der Vijver, M., Parry, S., Bishop, T., Easton, D.F., Prediction of BRCA1 status in patients with breast cancer using estrogen receptor and basal phenotype (2005) Clin. Cancer Res., 11, pp. 5175-5180; Palacios, J., Honrado, E., Osorio, A., Cazorla, A., Sarrio, D., Barroso, A., Rodriguez, S., Benitez, J., Immunohistochemical characteristics defined by tissue microarray of hereditary breast cancer not attributable to BRCA1 or BRCA2 mutations: differences from breast carcinomas arising in BRCA1 and BRCA2 mutation carriers (2003) Clin. Cancer Res., 9, pp. 3606-3614; Palacios, J., Honrado, E., Osorio, A., Cazorla, A., Sarrio, D., Barroso, A., Rodriguez, S., Benitez, J., Phenotypic characterization of BRCA1 and BRCA2 tumors based in a tissue microarray study with 37 immunohistochemical markers (2005) Breast Cancer Res. Treat., 90, pp. 5-14; Gorski, J.J., James, C.R., Quinn, J.E., Stewart, G.E., Staunton, K.C., Buckley, N.E., McDyer, F.A., Harkin, D.P., BRCA1 transcriptionally regulates genes associated with the basal-like phenotype in breast cancer (2010) Breast Cancer Res. Treat., 122, pp. 721-731; Albergaria, A., Ribeiro, A.S., Pinho, S., Milanezi, F., Carneiro, V., Sousa, B., Sousa, S., Schmitt, F., ICI 182,780 induces P-cadherin overexpression in breast cancer cells through chromatin remodelling at the promoter level: a role for C/EBPbeta in CDH3 gene activation (2010) Hum. Mol. Genet., 19, pp. 2554-2566; Sato, N., Fukushima, N., Maitra, A., Matsubayashi, H., Yeo, C.J., Cameron, J.L., Hruban, R.H., Goggins, M., Discovery of novel targets for aberrant methylation in pancreatic carcinoma using high-throughput microarrays (2003) Cancer Res., 63, pp. 3735-3742; Milicic, A., Harrison, L.A., Goodlad, R.A., Hardy, R.G., Nicholson, A.M., Presz, M., Sieber, O., Jankowski, J.A., Ectopic expression of P-cadherin correlates with promoter hypomethylation early in colorectal carcinogenesis and enhanced intestinal crypt fission in vivo (2008) Cancer Res., 68, pp. 7760-7768; Van Marck, V., Stove, C., Van Den Bossche, K., Stove, V., Paredes, J., Vander Haeghen, Y., Bracke, M., P-cadherin promotes cell-cell adhesion and counteracts invasion in human melanoma (2005) Cancer Res., 65, pp. 8774-8783; Sarrio, D., Palacios, J., Hergueta-Redondo, M., Gomez-Lopez, G., Cano, A., Moreno-Bueno, G., Functional characterization of E- and P-cadherin in invasive breast cancer cells (2009) BMC Cancer, 9, p. 74; Bauer, K., Dowejko, A., Bosserhoff, A.K., Reichert, T.E., Bauer, R.J., P-cadherin induces an epithelial-like phenotype in oral squamous cell carcinoma by GSK-3beta-mediated Snail phosphorylation (2009) Carcinogenesis, 30, pp. 1781-1788; Bauer, K., Dowejko, A., Bosserhoff, A.K., Reichert, T.E., Bauer, R., Slit-2 facilitates interaction of P-cadherin with Robo-3 and inhibits cell migration in an oral squamous cell carcinoma cell line (2011) Carcinogenesis, 32, pp. 935-943; Mandeville, J.A., Silva Neto, B., Vanni, A.J., Smith, G.L., Rieger-Christ, K.M., Zeheb, R., Loda, M., Summerhayes, I.C., P-cadherin as a prognostic indicator and a modulator of migratory behaviour in bladder carcinoma cells (2008) BJU Int., 102, pp. 1707-1714; Cheung, L.W., Leung, P.C., Wong, A.S., Cadherin switching and activation of p120 catenin signaling are mediators of gonadotropin-releasing hormone to promote tumor cell migration and invasion in ovarian cancer (2010) Oncogene, 29, pp. 2427-2440; Reynolds, A.B., Daniel, J.M., Mo, Y.Y., Wu, J., Zhang, Z., The novel catenin p120cas binds classical cadherins and induces an unusual morphological phenotype in NIH3T3 fibroblasts (1996) Exp. Cell Res., 225, pp. 328-337; Baki, L., Marambaud, P., Efthimiopoulos, S., Georgakopoulos, A., Wen, P., Cui, W., Shioi, J., Robakis, N.K., Presenilin-1 binds cytoplasmic epithelial cadherin, inhibits cadherin/p120 association, and regulates stability and function of the cadherin/catenin adhesion complex (2001) Proc. Natl. Acad. Sci. U. S. A., 98, pp. 2381-2386; Jacobs, K., Van Gele, M., Forsyth, R., Brochez, L., Vanhoecke, B., De Wever, O., Bracke, M., P-cadherin counteracts myosin II-B function: implications in melanoma progression (2010) Mol. Cancer, 9, p. 255; Radice, G.L., Sauer, C.L., Kostetskii, I., Peralta Soler, A., Knudsen, K.A., Inappropriate P-cadherin expression in the mouse mammary epithelium is compatible with normal mammary gland function (2003) Differentiation, 71, pp. 361-373; Gregory, D.J., Mikhaylova, L., Fedulov, A.V., Selective DNA demethylation by fusion of TDG with a sequence-specific DNA-binding domain (2012) Epigenetics, 7; Zhang, C.C., Yan, Z., Zhang, Q., Kuszpit, K., Zasadny, K., Qiu, M., Painter, C.L., VanArsdale, T., PF-03732010: a fully human monoclonal antibody against P-cadherin with antitumor and antimetastatic activity (2010) Clin. Cancer Res., 16, pp. 5177-5188
Keywords: antineoplastic activity; antineoplastic agent; Breast; breast cancer; Cancer; cancer chemotherapy; cancer model; cancer survival; drug effect; E-cadherin; Gastric; gene expression regulation; gene function; gene location; gene overexpression; gene structure; genetic association; genetic code; Helicobacter infection; Hereditary diffuse gastric cancer; human; in vivo study; loss of function mutation; lymph node metastasis; malignant neoplastic disease; molecular dynamics; molecular pathology; molecularly targeted therapy; nonhuman; P cadherin; P cadherin gene; P-cadherin; pf 03732010; priority journal; protein expression; protein function; protein inhibitor; protein processing; review; signal transduction; stomach cancer; transcription regulation; tumor gene; unclassified drug; uvomorulin; uvomorulin gene; vasculotropin inhibitor

FTIR analysis and cytotoxicity test of titanium dioxide nanoparticles - Rodrigues, L.R.; Dias, C.G.B.T.; Ceragioli, H.J.; Rodas, A.C.D.; Monteiro, F.J.M.; Zavaglia, C.A.C. (Key Engineering MaterialsKey Eng Mat, 2012)
Titanium dioxide is a material widely used in electronics industry and little explored in the biomedical area, which is the objective of this work. Nowadays one can find surgical instruments coated with thin films that have bactericidal properties when they are activated in the presence of ultraviolet light. For crystalline phase control TiO 2 was calcinated at 500°C. The crystallite mean size for sample calcinated at 500°C was 27nm. With the results of cytotoxicity it is possible to say that biomedical applications are possible. Electron microscopy images showed nanoparticles obtained by sol-gel process and the compounds were identified by FTIR analysis. Raman spectroscopy confirmed the existence of anatase titania phase and X-ray diffraction showed this material to be composed of a crystalline phase. X-ray fluorescence identified chemical contaminants. © (2012) Trans Tech Publications.
Conference code: 87411Export Date: 21 November 2012Source: ScopusCODEN: KEMAEdoi: 10.4028/www.scientific.net/KEM.493-494.768Language of Original Document: EnglishCorrespondence Address: Rodrigues, L.R.; Department of Materials Engineering, Faculty of Mechanical Engineering, State University of Campinas, Campinas, São Paulo, Brazil; email: leo5002@fem.unicamp.brReferences: Pavlova, A., Barloti, J., Teters, V., Locs, J., Berzina-Cimdina, L., (2009) Processing and Application of Ceramics, 3 (4), pp. 187-190;Naldoni, A., Minguzzi, A., Vertova, A., Santo, V.D., Borgesec, L., Bianchi, C.L., (2010) J. Mater. Chem., 21, pp. 400-407; Li, Y., Jiang, Y., Liu, F., Ren, F., Zhao, G., Leng, X., (2011) Food Hydrocolloids, 25 (5), pp. 1098-1104; Topuz, B.B., Gunduz, G., Mavis, B., Çolak, U., (2011) Dyes and Pigments, 90 (2), pp. 123-128; Nag, N., Guin, D., Basak, P., Manorama, S.V., (2008) Materials Research Bulletin, 43 (12), pp. 3270-3285; Yu, W., Qiu, J., Zhang, F., (2011) Colloids and Surfaces B: Biointerfaces, 84 (2), pp. 400-405; Wang, J., Li, S., Yan, W., Tse, S.D., Yao, Q., (2011) Proceeding of the Combustion Institute, 33 (2), pp. 1925-1932; Ma, P.X., (2008) Advanced Drug Delivery Reviews, 60, pp. 184-198; Liu, X., Smith, L.A., Hu, J., Ma, P.X., (2009) Biomaterials, 30, pp. 2252-2258; Qui, D., Yang, L., Yin, Y., Wang, A., (2011) Surface and Coatings Technology, 205 (10), pp. 3280-3284; Amin, R., Hwang, S., Park, S.H., (2011) NANO: Brief Reports and Reviews, 6 (2), pp. 101-111; Allounia, A.E., Cimpan, M.R., Hol, P.J., Skodvind, T., Gjerdet, N.R., (2009) Colloids and Surfaces B: Biointerfaces, 68, pp. 83-87; Akurati, K.K., (2008) Synthesis of TiO 2 Based Nanoparticles for Photocatalytic Applications, , 1st edition. Cuvillier Verlag Göttingen; Nag, M., Guin, D., Manorama, S.V., (2007) Materials Research Bulletin, 9, pp. 1691-1704; Birks, L.S., Friedman, H., (1946) Journal of Applied Physics, 17, pp. 687-692; Rodas, A.C.D., Maizato, M.J.S., Leiner, A.A., Pitombo, R.N.M., Polakiewicz, B., Beppu, M.M., Higa, O.Z., (2008) Artificial Organs, 32 (4), pp. 272-276; Zhang, J.Y., Boyd, I.W., O'Sullivan, B.J., Hurley, P.K., Kelly, P.V., Sénateur, J.P., (2002) Journal of Non-Crystalline Solids, 303, pp. 134-138; Arconada, N., Durán, A., Suárez, S., Portela, R., Coronado, J.M., Sánchez, B., Castro, Y., (2009) Applied Catalysis B: Environmental, 86 (1-2), pp. 1-7; Wang, J., Li, R.H., Zhang, Z.H., Sun, W., Wang, X.F., Xing, Z.Q., Xu, R., Zhang, X.D., (2008) Inorganic Materials, 44 (6), pp. 608-614; Orendorz, A., Brodyanski, A., Lösch, J., Bai, L.H., Chen, Z.H., Le, Y.K., Ziegler, C., Gnaser, H., (2007) Surface Science, 601, pp. 4390-4394
Keywords: Anatase titania; Bactericidal properties; Bioceramics; Biomedical applications; Chemical contaminants; Crystalline materials; Crystalline phase; Crystallite size; Cytotoxicity; Cytotoxicity test; Electron microscopy images; Electronics industry; FTIR; FTIR analysis; Gels; Mean size; Medical applications; nanoparticles; Nanotechnology; Oxides; Raman spectroscopy; Scherrer equation; Scherrer equations; Sol-gel process; Sol-gel with sucrose; Sol-gels; Sols; Sugar (sucrose); Surgical equipment; Surgical instrument; TiO; Titanium; Titanium dioxide; Titanium dioxide nanoparticles; Ultra-violet light; Ultraviolet radiation; X ray diffraction; X ray fluorescence

(Gd,Yb,Tb)PO 4 up-conversion nanocrystals for bimodal luminescence-MR imaging - Debasu, M.L.; Ananias, D.; Pinho, S.L.C.; Geraldes, C.F.G.C.; Carlos, L.D.; Rocha, J. (NanoscaleNanoscale, 2012)
Up-conversion (Gd,Yb,Tb)PO 4 materials and their potential for bimodal imaging have received little attention in the literature. Herein, we report the first study on the up-conversion emission of (Gd,Yb,Tb)PO 4 nanocrystals synthesized via a hydrothermal method at 150°C. These materials exhibit ultraviolet, blue and green up-conversion emissions upon excitation with a 980 nm continuous wave laser diode. The intensity of the blue-emission band at 479 nm, ascribed to the cooperative up-conversion emission of a pair of excited Yb 3+ ions, depends on the Yb 3+/Tb 3+ concentration ratio, calcination temperature and particle size. Strong green up-conversion emission of Tb 3+ is observed at 543 nm for the 5D 4 → 7F 5 transition. Relaxometry measurements reveal that the nanocrystals are efficient T 2-weighted (negative) contrast agents which, combined with visible-light emission generated by infrared excitation, affords them considerable potential for being used in bimodal, photoluminescence-magnetic resonance, imaging. © 2012 The Royal Society of Chemistry.
Keywords: Blue-emission; Calcination; Calcination temperature; Concentration ratio; Continuous wave lasers; Contrast agent; Gadolinium; Hydrothermal methods; Infrared excitation; Magnetic resonance; Magnetic resonance imaging; Nanocrystals; Relaxometry; Up-conversion; Up-conversion emission; Visible light; Ytterbium

Gradient convergence filters and a phase congruency approach for in vivo cell nuclei detection - Esteves, T.; Quelhas, P.; Mendonça, A.M.; Campilho, A. (Machine Vision and ApplicationsMach Vision Appl, 2012)
Computational methods used in microscopy cell image analysis have largely augmented the impact of imaging techniques, becoming fundamental for biological research. The understanding of cell regulation processes is very important in biology, and in particular confocal fluorescence imaging plays a relevant role for the in vivo observation of cells. However, most biology researchers still analyze cells by visual inspection alone, which is time consuming and prone to induce subjective bias. This makes automatic cell image analysis essential for large scale, objective studies of cells. While the classic approach for automatic cell analysis is to use image segmentation, for in vivo confocal fluorescence microscopy images of plants, such approach is neither trivial nor is it robust to image quality variations. To analyze plant cells in in vivo confocal fluorescence microscopy images with robustness and increased performance, we propose the use of local convergence filters (LCF). These filters are based in gradient convergence and as such can handle illumination variations, noise and low contrast.We apply a range of existing convergence filters for cell nuclei analysis of the Arabidopsis thaliana plant root tip. To further increase contrast invariance, we present an augmentation to local convergence approaches based on image phase information. Through the use of convergence index filters we improved the results for cell nuclei detection and shape estimation when compared with baseline approaches. Using phase congruency information we were able to further increase performance by 11% for nuclei detection accuracy and 4% for shape adaptation. Shape regularization was also applied, but with no significant gain, which indicates shape estimation was good for the applied filters. © 2011 Springer-Verlag.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: MVAPEdoi: 10.1007/s00138-012-0407-7Language of Original Document: EnglishCorrespondence Address: Quelhas, P.; INEB-Instituto de Engenharia Biomédica, Oporto, Portugal; email: quelhas@fe.up.ptReferences: Bleau, A., Leon, L.J., Watershed-based segmentation and region merging (2000) Computer Vision and Image Understanding, 77 (3), pp. 317-370. , DOI 10.1006/cviu.1999.0822;Bresson, X., Vandergheynst, P., Thiran, J., A priori information in image segmentation: Energy functional based on shape statistical model and image information (2003) Proceedings of International Conference on Image Processing, pp. 428-428. , ICIP; Bunyak, F., Palaniappan, K., Nath, S.K., Baskin, T.I., Dong, G., Quantitative cellmotility for in vitrowound healing using level setbased active contour tracking (2011) Proceedings of the IEEE International Conference on Biomedical Imaging (ISBI), pp. 1-4; Byun, J., Verardo, M.R., Sumengen, B., Lewis, G.P., Manjunath, B.S., Fisher, S.K., Automated tool for the detection of cell nuclei in digital microscopic images: Application to retinal images (2006) Mol. Vis., 12, pp. 949-960; Campilho, A., Garcia, B., Toorn, H.V.D., Wijk, H.V., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the Arabidopsis thaliana root meristem (2006) Plant Journal, 48 (4), pp. 619-627. , DOI 10.1111/j.1365-313X.2006.02892.x; Chan, T.F., Vese, L.A., Active contours without edges (2001) IEEE Transactions on Image Processing, 10 (2), pp. 266-277. , DOI 10.1109/83.902291; Chen, X., Zhou, X., Wong, S.T.C., Automated segmentation, classification, and tracking of cancer cell e nuclei in time-lapse microscopy (2006) IEEE Trans. Biomed. Eng., 53 (4), pp. 762-766; Chen, Y., Ladi, E., Herzmark, P., Robey, E., Roysam, B., Automated 5-d analysis of cell migration and interaction in the thymic cortex from time-lapse sequences of 3-d multi-channel multi-photon images (2009) J. Immunol. Methods, 340 (1), pp. 65-80; Chen, Y., Quelhas, P., Campilho, A., Low frame rate cell tracking: A delaunay graph matching approach (2011) Proceedings of the IEEE International Conference on Biomedical Imaging (ISBI), pp. 1-4; Clocksin, W., Automatic segmentation of overlapping nuclei with high background variation using robust estimation and flexible contour models (2003) Proceedings of the International Conference on Image Analysis and Processing, pp. 682-687; Dewitte, W., Murray, J., The plant cell cycle (2003) Annu. Rev. Plant Biol., 54, pp. 235-297; Fang, W., Chan, K.L., Incorporating shape prior into geodesic active contours for detecting partially occluded object (2007) Pattern Recognition, 40 (8), pp. 2163-2172. , DOI 10.1016/j.patcog.2006.12.014, PII S0031320306005292; Fok, Y.-L., Chan, J.C.K., Chin, R.T., Automated analysis of nerve-cell images using active contour models (1996) IEEE Transactions on Medical Imaging, 15 (3), pp. 353-368. , PII S0278006296042425; Guan, P., Yan, H., Blood cell image segmentation based on the hough transform and fuzzy curve tracing (2011) International Conference on Machine Learning and Cybernetics (ICMLC), 4, pp. 1696-1701; Hafiane, A., Bunyak, F., Palaniappan, K., Clustering initiated multiphase active contours and robust separation of nuclei groups for tissue segmentation (2008) International Conference on Pattern Recognition (ICPR), pp. 1-4; Hafiane, A., Bunyak, F., Palaniappan, K., Fuzzy clustering and active contours for histopathology image segmentation and nuclei detection (2008) Advanced Concepts for Intelligent Vision Systems LNCS, 5259, pp. 903-914. , Springer, Berlin; Han, J., Breckon, T., Randell, D., Landini, G., The application of support vector machine classification to detect cell nuclei for automated microscopy (2010) Mach. Vis. Appl., 23 (1), pp. 15-24; Harder, N., M-Bermudez, F., Godinez, W., Ellenberg, J., Eils, R., Rohr, K., Automated analysis of mitotic cell nuclei in 3d fluorescence microscopy image sequences (2008) Workshop on Bio- Image Informatics: Biological Imaging, ComputerVision AndData Mining; Hu, M., Ping, X., Ding, Y., A new active contour model and its application on cell segmentation (2004) 2004 8th International Conference on Control, Automation, Robotics and Vision (ICARCV), 2, pp. 1104-1107. , TuA7.09 - P0673, 2004 8th International Conference on Control, Automation, Robotics and Vision (ICARCV); Kobatake, H., Hashimoto, S., Convergence index filter for vector fields (1999) IEEE Trans. Image Process., 8 (8), pp. 1029-1038; Kovesi, P., Image features from phase congruency (1999) Videre, pp. 1-26; Kovesi, P., Phase congruency detects corners and edges (2003) Digital Image Computing: Techniques and Applications, pp. 309-318; Kube, P., Properties of energy edge detectors (1992) IEEE Conference on ComputerVision and Pattern Recognition (CVPR), pp. 586-591; Leibe, B., Leonardis, A., Schiele, B., Combined object categorization and segmentation with an implicit shape model (2004) ECCV Workshop on Statistical Learning in Computer Vision, pp. 17-32; Leventon, M., Grimson, W., Faugeras, O., Statistical shape influence in geodesic active contours (2000) Proceedings of IEEE Conference on Computer Vision and Pattern Recognition (CVPR, pp. 316-323; Li, C., Xu, C., Gui, C., Fox, M.D., Level set evolution without re-initialization: A new variational formulation (2005) IEEE International Conference on Computer Vision and Pattern Recognition (CVPR), pp. 430-436; Li, K., Miller, E.D., Chen, M., Kanade, T., Weiss, L.E., Campbell, P.G., Cell population tracking and lineage construction with spatiotemporal context (2008) Med. Image Anal., 12, pp. 546-566; Lindeberg, T., Scale-space theory: A basic tool for analysing structures at different scales (1994) J. Appl. Stat., 21 (2), pp. 224-270; Marcuzzo, M., Guichard, T., Quelhas, P., Mendonça, A.M., Campilho, A., Cell division detection on the Arabidopsis thaliana root (2009) Proceedings of the Iberian Conference on Pattern Recognition and Image Analysis, LNCS, 5524, pp. 168-175. , Springer, Berlin; Marcuzzo, M., Quelhas, P., Campilho, A., Maria Mendonça, A., Campilho, A., Automated Arabidopsis plant root cell segmentation based on svm classification and region merging (2009) Comput Biol Med, 39 (9), pp. 785-793; Marcuzzo, M., Quelhas, P., Mendonça, A.M., Campilho, A., Evaluation of symmetry enhanced sliding band filter for plant cell nuclei detection in low contrast noisy fluorescent images (2009) Proceedings of the International Conference on Image Analysis and Recognition, 5627, pp. 824-831. , Springer, Berlin; Marcuzzo, M., Quelhas, P., Mendonça, A.M., Campilho, A., Tracking of Arabidopsis thaliana root cells in time-lapsemicroscopy (2009) Proceedings of the International Conference on Pattern Recognition (ICPR), pp. 1-4; Moore, P., Molloy, D., A survey of computer-based deformable models (2007) International Machine Vision and Image Processing Conference, pp. 55-66; Morrone, M., Burr, D., Feature detection in human vision: A phase-dependent energy model (1988) Proc. Roy. Soc. Lond. B Biol. Sci., 235 (1280), pp. 221-245; Mosaliganti, K., Gelas, A., Gouaillard, A., Megason, S., Microscopy image analysis: Blob segmentation using geodesic active contours (2009) Insight J.; Otsu Nobuyuki, Threshold selection method from gray-level histograms (1979) IEEE Trans Syst Man Cybern, SMC-9 (1), pp. 62-66; Pereira, C.S., Fernandes, H., Mendonça, A.M., Campilho, A.C., Detection of lung nodule candidates in chest radiographs (2007) Iberian Conference on Pattern Recognition and Image Analysis, 2, pp. 170-177; Perona Pietro, Malik Jitendra, Scale-space and edge detection using anisotropic diffusion (1990) IEEE Transactions on Pattern Analysis and Machine Intelligence, 12 (7), pp. 629-639. , DOI 10.1109/34.56205; Quelhas, P., Monay, F., Odobez, J.-M., Gatica-Perez, D., Tuytelaars, T., A thousand words in a scene (2007) IEEE Transactions on Pattern Analysis and Machine Intelligence, 29 (9), pp. 1575-1589. , DOI 10.1109/TPAMI.2007.1155; Quelhas, P., Marcuzzo, M., Oliveira, M.J., Mendonça, A.M., Campilho, A., Cancer cell detection and invasion depth estimation in brightfield images (2009) Proceedings of the British Machine Vision Conference; Quelhas, P., Marcuzzo, M., Mendonca, A.M., Campilho, A., Cell nuclei and cytoplasm joint segmentation using the sliding band filter (2010) IEEE Trans. Med. Imaging, 29 (8), pp. 1463-1473; Quelhas, P., Mendonça, A.M., Campilho, A., 3d cell nuclei fluorescence quantification using sliding band filter (2010) International Conference on Pattern Recognition (ICPR), pp. 2508-2511; Roberts, T., McKenna, S., Du, C.J., Wuyts, N., Valentine, T., Bengough, A., Estimating the motion of plant root cells from in vivo confocal laser scanning microscopy images (2010) Mach. Vis. Appl., 21, pp. 921-939; Sanz, L., Dewitte, W., Forzani, C., Patell, F., Nieuwland, J., Wen, B., Quelhas, P., Murray, J.A., The Arabidopsis d-type cyclin cycd2;1 and the inhibitor ick2/krp2 modulate auxin-induced lateral root formation (2011) Plant Cell, 23, pp. 641-660; Sivic, J., Zisserman, A., Video google: A text retrieval approach to object matching in videos (2003) Proceedings of the IEEE International Conference on Computer Vision (ICCV), pp. 1-8; Tek, F.B., Dempster, A.G., Kale, I., Blood cell segmentation using minimum area watershed and circle radon transformations (2005) Mathematical Morphology: 40 Years On, Computational Imaging and Vision, 30, pp. 441-454. , Ronse, C., Najman, L., Decencière, E. (eds.), Springer, Netherlands; Usaj, M., Torkar, D., Kanduser, M., Mikalavcic, D., Cell counting tool parameters optimization approach for electroporation efficiency determination of attached cells in phase contrast images (2011) J. Microsc., 241 (3), pp. 303-314; Vincent Luc, Soille Pierre, Watersheds in digital spaces: An efficient algorithm based on immersion simulations (1991) IEEE Transactions on Pattern Analysis and Machine Intelligence, 13 (6), pp. 583-598. , DOI 10.1109/34.87344; Wei Jun, Hagihara Yoshihiro, Kobatake Hidefumi, Detection of cancerous tumors on chest X-ray images - candidate detection filter and its evaluation (1999) IEEE International Conference on Image Processing, 3, pp. 397-401; Wei, J., Hagihara, Y., Kobatake, H., Edge detection and skeletonization using quantized localized phase (2009) European Signal Processing Conference (EUSIPCO), pp. 1542-1546; Willamowski, J., Arregui, D., Csurka, G., Dance, C.R., Fan, L., Categorizing nine visual classes using local appearance descriptors (2004) ICPR Workshop on Learning for Adaptable Visual Systems, pp. 1-11; Willemse, J., Kulikova, O., Jong, H., Bisseling, T., A new wholemount dna quantification method and the analysis of nuclear DNA content in the stem-cell niche of Arabidopsis roots (2008) Plant J., 55 (5), pp. 886-894; Xiong, G., Zhou, X., Ji, L., Automated segmentation of drosophila RNAi fluorescence cellular images using deformable models (2006) IEEE Transactions on Circuits and Systems I: Regular Papers, 53 (11), pp. 2415-2424. , DOI 10.1109/TCSI.2006.884461; Xiong, G., Zhou, X., Ji, L., Bradley, P., Perrimon, N., Wong, S., Segmentation ofDrosophila RNAI fluorescence images using level sets (2006) Proceedings of IEEE International Conference on Image Processing, pp. 73-76; Xue, Q., Degrelle, S., Wang, J., Hue, I., Guillomot, M., A level set based hybrid framework for confocal image segmentation (2008) Proceedings of the IASTED International Conference on Biomedical Engineering, pp. 453-457; Yan, P., Zhou, X., Shah, M., Wong, S.T.C., Automatic segmentation of high-throughput RNAi fluorescent cellular images (2008) IEEE Transactions on Information Technology in Biomedicine, 12 (1), pp. 109-117. , DOI 10.1109/TITB.2007.898006; Yang, X., Li, H., Zhou, X., Nuclei segmentation using marker-controlled watershed, tracking using mean-shift, and Kalman filter in time-lapse microscopy (2006) IEEE Transactions on Circuits and Systems I: Regular Papers, 53 (11), pp. 2405-2414. , DOI 10.1109/TCSI.2006.884469; Yi Wang, F.H., Jiankun, H., Fengling, H., Enhanced gradientbased algorithm for the estimation of fingerprint orientation fields Appl. Math. Comput., 185, pp. 823-833. , http://seit.unsw.adfa.edu.au/staff/sites/hu/Sample_Publication/ Elsevier_Wang.pdf; Yin, Z., Bise, R., Chen, M., Kanade, T., Cell segmentation in microscopy imagery using a bag of local Bayesian classifiers (2010) Proceedings of the IEEE International Conference on Biomedical Imaging (ISBI), pp. 125-128
Keywords: Arabidopsis thaliana; Biological research; Cell analysis; Cell images; cell nucleus; Cell regulation; Cell segmentation; Cells; Confocal fluorescence imaging; Confocal fluorescence microscopy; Convergence filters; cytology; Detection accuracy; Estimation; Fluorescence microscopy; Illumination variation; Image analysis; Image filtering; Image segmentation; Imaging techniques; In-vivo; Information use; Local Convergence; Local image filtering; Medical applications; Phase congruency; Phase information; Plant cells; Plant roots; Plants (botany); Quality variation; Shape adaptation; Shape estimation; Shape regularization; Visual inspection

Hand detection and tracking using the skeleton of the blob for medical rehabilitation applications - Gil-Jiménez, P.; Losilla-López, B.; Torres-Cueco, R.; Campilho, A.; López-Sastre, R. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2012)
This article presents an image processing application for hand detection and tracking using the 4-connected skeleton of the segmentation mask. The system has been designed to be used with techniques of virtual reality to develop an interactive application for phantom limb pain reduction in therapeutic treatments. One of the major contributions is the design of a fast and accurate skeleton extractor, that has proven to be faster than those available in the literature. The skeleton allows the system to precisely detect the position of all the interest points of the hand (namely the fingers and the hand center). The system, composed of both the hand detector and tracker, and the virtual reality application, can work in real-time, allowing the patient to watch the virtual image of his own hand on a screen. © 2012 Springer-Verlag.
Conference code: 91199Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-31298-4_16Language of Original Document: EnglishCorrespondence Address: Gil-Jiménez, P.; Universidad de Alcalá, Alcalá de Henares, Madrid, Spain; email: pedro.gil@uah.esReferences: Breuer, P., Eckes, C., Müller, S., Hand Gesture Recognition with a Novel IR Time-of-Flight Range Camera-A Pilot Study (2007) LNCS, 4418, pp. 247-260. , Gagalowicz, A., Philips, W. (eds.) MIRAGE 2007. Springer, Heidelberg;Chang, C., Lin, C., (2001) LIBSVM: A Library for Support Vector Machines, , http://www.csie.ntu.edu.tw/~cjlin/libsvm, software available at; Cole, J., Crowle, S., Austwick, G., Slater, D.H., Exploratory findings with virtual reality for phantom limb pain; from stump motion to agency and analgesia (2009) Disability and Rehabilitation, 31 (10), pp. 846-854; Elgammal, A., Muang, C., Hu, D., Skin detection - A short tutorial (2009) Encyclopedia of Biometrics; Gómez-Moreno, H., Maldonado-Bascón, S., Gil-Jiménez, P., Lafuente-Arroyo, S., (2010) Goal Evaluation of Segmentation Algorithms for Traffic Sign Recognition, 11 (4), pp. 917-930. , July; González, R., Woods, R., (1993) Digital Image Processing, , Addison-Wesley; Von Hardenberg, C., Bérard, F., Bare-hand human-computer interaction (2001) Proceedings of the 2001 Workshop on Perceptive User Interfaces, PUI 2001, pp. 1-8; Hsieh, C.C., Liou, D.H., Lee, D., A real time hand gesture recognition system using motion history image (2010) 2010 2nd International Conference on Signal Processing Systems (ICSPS), 2, pp. V2394-V2398. , July; Imai, A., Shimada, N., Shirai, Y., 3-d hand posture recognition by training contour variation (2004) Proceedings of Sixth IEEE International Conference on Automatic Face and Gesture Recognition, pp. 895-900. , May; Isaacs, J., Foo, J., Hand pose estimation for american sign language recognition (2004) Southern Symposium on System Theory, pp. 132-136; Lakshmi, J.K., Punithavalli, M., A survey on skeletons in digital image processing (2009) Digital Image Processing, pp. 260-269; Letessier, J., Bérard, F., Visual tracking of bare fingers for interactive surfaces (2004) Proceedings of the 17th Annual ACM Symposium on User Interface Software and Technology, UIST 2004, pp. 119-122. , ACM; Lewis, J.S., Kersten, P., McCabe, C.S., McPherson, K.M., Blake, D.R., Body perception disturbance: A contribution to pain in complex regional pain syndrome (2007) CRPS; McCabe, C.S., Haigh, R.C., Ring, E.F., Halligan, P.W., Wall, P.D., Blake, D.R., A controlled pilot study of the utility of mirror visual feedback in the treatment of complex regional pain syndrome (type 1) (2003) Rheumatology, 42 (1), pp. 97-101; Murray, C.D., Patchick, E., Pettifer, S., Howard, T., Caillette, F., Kulkarni, J., Bamford, C., Investigating the efficacy of a virtual mirror box in treating phantom limb pain in a sample of chronic sufferers (2006) Disabil Human Dev., 5 (3), pp. 227-234; Nope, R., Sandra, E., Humberto Loaiza, C., Eduardo Caicedo, B., Estudio omparativo de técnicas para el reconocimiento de gestos por visión artificial (2009) Avances en Sistemas e Informtica, 5 (3); Oikonomidis, I., Nikolaos, K., Argyros, A.A., Efficient model-based 3d tracking of hand articulations using kinect (2011) Tracking Hand Articulations Using Kinect; Pugeault, N., Bowden, R., Spelling it out: Real-time ASL fingerspelling recognition IEEE Workshop on Consumer Depth Cameras for Computer Vision (2011); Ren, Z., Meng, J., Yuan, J., Zhang, Z., Robust hand gesture recognition with kinect sensor (2011) Proceedings of the 19th ACM International Conference on Multimedia, MM 2011, pp. 759-760. , ACM; Yoruk, E., Konukoglu, E., Sankur, B., Darbon, J., Shape-based hand recognition (2006) IEEE Transactions on Image Processing, 15 (7), pp. 1803-1815
Keywords: blob skeleton; Hand detection; hand detection and tracking; Image analysis; Image processing applications; Interactive applications; Musculoskeletal system; phantom limb pain reduction; Therapeutic treatments; Virtual images; virtual reality

Interactions of microbicide nanoparticles with a simulated vaginal fluid - Das Neves, J.; Rocha, C.M.R.; Gonçalves, M.P.; Carrier, R.L.; Amiji, M.; Bahia, M.F.; Sarmento, B. (Molecular PharmaceuticsMol. Pharm., 2012)
The interaction with cervicovaginal mucus presents the potential to impact the performance of drug nanocarriers. These systems must migrate through this biological fluid in order to deliver their drug payload to the underlying mucosal surface. We studied the ability of dapivirine-loaded polycaprolactone (PCL)-based nanoparticles (NPs) to interact with a simulated vaginal fluid (SVF) incorporating mucin. Different surface modifiers were used to produce NPs with either negative (poloxamer 338 NF and sodium lauryl sulfate) or positive (cetyltrimethylammonium bromide) surface charge. Studies were performed using the mucin particle method, rheological measurements, and real-time multiple particle tracking. Results showed that SVF presented rheological properties similar to those of human cervicovaginal mucus. Analysis of NP transport indicated mild interactions with mucin and low adhesive potential. In general, negatively charged NPs underwent subdiffusive transport in SVF, i.e., hindered as compared to their diffusion in water, but faster than for positively charged NPs. These differences were increased when the pH of SVF was changed from 4.2 to 7.0. Diffusivity was 50- and 172-fold lower in SVF at pH 4.2 than in water for negatively charged and positively charged NPs, respectively. At pH 7.0, this decrease was around 20- and 385-fold, respectively. The estimated times required to cross a layer of SVF were equal to or lower than 1.7 h for negatively charged NPs, while for positively charged NPs these values were equal to or higher than 7 h. Overall, our results suggest that negatively charged PCL NPs may be suitable to be used as carriers in order to deliver dapivirine and potentially other antiretroviral drugs to the cervicovaginal mucosal lining. Also, they further reinforce the importance in characterizing the interactions of nanosystems with mucus fluids or surrogates when considering mucosal drug delivery. © 2012 American Chemical Society.
Keywords: microbicides; mucin; mucoadhesion; mucosal drug delivery; particle tracking; rheology

Micropatterned silica thin films with nanohydroxyapatite micro-aggregates for guided tissue regeneration - Carvalho, A.; Pelaez-Vargas, A.; Gallego-Perez, D.; Grenho, L.; Fernandes, M.H.; De Aza, A.H.; Ferraz, M.P.; Hansford, D.J.; Monteiro, F.J. (Dental MaterialsDent. Mater., 2012)
Surface modification of biomaterials has been shown to improve the biological response to dental implants. The ability to create a controlled micro-texture on the implant via additive surface modification techniques with bioactive nanohydroxyapatite (nanoHA) may positively influence guided tissue regeneration. Objective: The main goal of this study was to produce micro-fabricated SiO 2 surfaces modified with nanohydroxyapatite particles and to characterize their influence on the biological response of Human Dental-Pulp Mesenchymal Stem Cells (hDP-MSCs) and Streptococcus mutans. Materials and methods: A combined methodology of sol-gel and soft-lithography was used to produce micropatterned SiO 2 thin films with different percentages of nanoHA micro-aggregates. The surfaces were characterized by SEM/EDS, FT-IR/ATR, AFM, XPS quantitative elemental percentage and contact angle measurements. Biological characterization was performed using hDP-MSCs cultures, while Streptococcus mutans was the selected microorganism to evaluate the bacterial adhesion on the thin films. Results: Micropatterned SiO 2 surfaces with 0%, 1% and 5% of nanoHA micro-aggregates were successfully produced using a combination of sol-gel and soft-lithography. These surfaces controlled the biological response, triggering alignment and oriented proliferation of hDP-MSCs and significant differences in the adhesion of S. mutans to the different surfaces. Significance: The micropatterned surfaces exhibited biocompatible behavior that induced an oriented adhesion and proliferation of hDP-MSCs while SiO 2 presented low bacterial adhesion. These results show that the combination of sol-gel with soft-lithography is a good approach to create micropatterned surfaces with bioactive nanoparticles for guided tissue regeneration. © 2012 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Adhesion; AFM; Aggregates; Bacteria; Bacterial adhesion; Bioactive nanoparticles; Biological characterization; Biological materials; Biological response; Biomaterials; Cell culture; Contact angle; Dental prostheses; Flowcharting; FTIR/ATR; Guided tissue regeneration; Lithography; Mesenchymal stem cell; Micro patterning; Micro-texture; Microaggregates; Micropatterned; Micropatterned surface; Micropatterning; Nano-HA; Nano-hydroxyapatite; S. mutans; SEM/EDS; Silica; Silica thin films; Soft-lithography; Sol-gel; Sol-gel process; Sol-gels; Streptococcus mutans; Surface modification techniques; Surfaces; Thin films

Proactive engineering - Duarte, C.; Oliveira, H.P.; Magalhaes, F.; Tavares, V.G.; Campilho, A.C.; De Oliveira, P.G. (IEEE Global Engineering Education Conference, EDUCONIEEE Global Eng. Edu. Conf., EDUCON, 2012)
This paper presents two initiatives run by groups of engineering students at the University of Porto: the Microelectronics Students' Group and BioStar. These groups are student-led initiatives that promote different scientific fields through self-guided projects. Both experiences have proven to be very successful in increasing the undergraduate student's interest in science and technology. This work reports the activities, organization and main methodologies employed by these groups, which can be seen as successful approaches to enhance the technical curriculum of students. © 2012 IEEE.
Conference code: 91215Export Date: 21 November 2012Source: ScopusArt. No.: 6201104doi: 10.1109/EDUCON.2012.6201104Language of Original Document: EnglishCorrespondence Address: Duarte, C.; INESC TEC (Formerly INESC Porto), Faculty of Engineering, University of Porto, Rua Dr. Roberto Frias, 378, 4200-465 Porto, PortugalReferences: Gheorghe, C., Covrig, M., Uncuta, S., Popescu, M., Does the implementation of the Bologna process in higher technical education require a new approach to motivate the actors involved in the educational process? (2011) 7th International Symposium on Advanced Topics in Electrical Engineering (ATEE'2011), pp. 1-4. , May;(2011) Microelectronics Students' Group, , http://usgroup.eu; (2011) BioStar, , http://biostar.fe.up.pt; Coke, P., Duarte, C., Cardoso, A., Tavares, V.G., De Oliveira, P.G., Network Infrastructure for academic IC CAD environments (2011) IEEE International Conference on Computer As A Tool (EUROCON'2011), pp. 1-4. , Apr; Clarke, P., Students win training for being Cadence's fastest' designers (2009) EE Times, , http://eetimes.eu, ID 217500055 May 14; Magalhães, F., Oliveira, H.P., Campilho, A., (2010) SPD2010-Fingerprint Singular Points Detection Competition, , http://fe.up.pt/-spd2010/; Magalhães, F., Oliveira, H.P., Matos, H., Campilho, A., (2011) HGC2011-Hand Geometric Points Detection Competition, , http://www.fe.up.pt/-hgc2011/; Duarte, C., Student group works on designs for a fully integrated wireless receiver (2009) IEEE Region 8 News, 2 (4), p. 9. , Dec; Dias, D., (2011) Computational Vision Applied to the Segmentation and Morphmetric Characterization of the Sciatic Nerve in Microscopic Images, , M.Sc. Thesis, Faculdade de Engenharia, Universidade do Porto, Jul; Martins, D., (2011) Biometric Recognition Based on the Texture Along Palmprint Principal Lines, , M.Sc. Thesis, Faculdade de Engenharia, Universidade do Porto, Jul; Matos, H., (2011) Hand Geometry Based Recognition System, , M.Sc. Thesis, Faculdade de Engenharia, Universidade do Porto, Jan; Soares, J., (2011) Uncalibrated Stereo Vision Applied to Breast Cancer Treatment Aesthetic Assessment, , M.Sc. Thesis, Faculdade de Engenharia, Universidade do Porto, Jul; Matos, H., Magalhães, F., Oliveira, H.P., Cardoso, J.S., Hand geometry based recognition system-A new method with no constraints on image acquisition (2011) Proceedings of the 4th Meeting of Young Researchers of the University of Porto; Gaspar, D., Bre, L., Bishoff, N., Domingues, I., Mammograms image processing (2011) Proceedings of the 4th Meeting of Young Researchers of the University of Porto; Magalhães, F., Oliveira, H.P., Campilho, A.C., A new method for the detection of singular points in fingerprint images (2009) Proceedings of the IEEE Workshop on Applications of Computer Vision, pp. 157-162; Moreira, I.C., Amaral, I., Domingues, I., Cardoso, A., Cardoso, M.J., Cardoso, J.S., INbreast: Toward a full-field digital mammographic database (2011) Academic Radiology; Oliveira, H.P., Magalhaes, A., Cardoso, M.J., Cardoso, J.S., An accurate and interpretable model for BCCT.core (2010) Proceedings of the 32nd Annual International Conference of the IEEE Engineering in Medicine and Biology Society, pp. 6158-6161; (2011) IJUP-Junior Reasearch at UP, , http://ijup.up.pt, University of Porto
Keywords: Curricula; Engineering education; Microelectronics; Project based learning; project-based learning; Science and Technology; Scientific fields; student-led initiatives; Students; Undergraduate students

Regenerative medicine for the treatment of spinal cord injury: More than just promises? - Pêgo, A.P.; Kubinova, S.; Cizkova, D.; Vanicky, I.; Mar, F.M.; Sousa, M.M.; Sykova, E. (Journal of Cellular and Molecular MedicineJ. Cell. Mol. Med., 2012)
Spinal cord injury triggers a complex set of events that lead to tissue healing without the restoration of normal function due to the poor regenerative capacity of the spinal cord. Nevertheless, current knowledge about the intrinsic regenerative ability of central nervous system axons, when in a supportive environment, has made the prospect of treating spinal cord injury a reality. Among the range of strategies under investigation, cell-based therapies offer the most promising results, due to the multifactorial roles that these cells can fulfil. However, the best cell source is still a matter of debate, as are clinical issues that include the optimal cell dose as well as the timing and route of administration. In this context, the role of biomaterials is gaining importance. These can not only act as vehicles for the administered cells but also, in the case of chronic lesions, can be used to fill the permanent cyst, thus creating a more favourable and conducive environment for axonal regeneration in addition to serving as local delivery systems of therapeutic agents to improve the regenerative milieu. Some of the candidate molecules for the future are discussed in view of the knowledge derived from studying the mechanisms that facilitate the intrinsic regenerative capacity of central nervous system neurons. The future challenge for the multidisciplinary teams working in the field is to translate the knowledge acquired in basic research into effective combinatorial therapies to be applied in the clinic. © 2012 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
Keywords: Biomaterials; Cell therapies; Clinical trials; Conditioning lesion; Gene therapy; Growth factors; Spinal cord injury; Stem cells

Supervised content based image retrieval using radiology reports - Ramos, J.; Kockelkorn, T.; Van Ginneken, B.; Viergever, M.A.; Ramos, R.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2012)
Content based image retrieval (CBIR) is employed in medicine to improve radiologists' diagnostic performance. Today effective medical CBIR systems are limited to specific applications, as to reduce the amount of medical knowledge to model. Although supervised approaches could ease the incorporation of medical expertise, its application is not common due to the scarce number of available user annotations. This paper introduces the application of radiology reports to supervise CBIR systems. The concept is to make use of the textual distances between reports to build a transformation in image space through a manifold learning algorithm. A comparison was made between the presented approach and non-supervised CBIR systems, using a Leave-One-Patient-Out evaluation in a database of computer tomography scans of interstitial lung diseases. Supervised CBIR augmented the mean average precision consistently with an increase between 3 to 8 points, which suggests supervision by radiology reports increases CBIR performance. © 2012 Springer-Verlag.
Conference code: 91199Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-31298-4_30Language of Original Document: EnglishCorrespondence Address: Ramos, J.; INEB - Instituto de Engenharia Biomédica, Faculdade de Engenharia, Universidade Do PortoPortugalReferences: Aisen, A.M., Broderick, L.S., Winer-Muram, H., Brodley, C.E., Kak, A.C., Pavlopoulou, C., Dy, J., Marchiori, A., Automated storage and retrieval of thin-section CT images to assist diagnosis: System description and preliminary assessment (2003) Radiology, 228 (1), pp. 265-270;Akgul, C.B., Rubin, D.L., Napel, S., Beaulieu, C.F., Greenspan, H., Acar, B., Content-Based image retrieval in radiology: Current status and future directions (2010) Journal of Digital Imaging, 24 (2), pp. 208-222; Dreyer, K.J., Kalra, M.K., Maher, M.M., Hurier, A.M., Asfaw, B.A., Schultz, T., Halpern, E.F., Thrall, J.H., Application of recently developed computer algorithm for automatic classification of unstructured radiology reports: Validation study1 (2005) Radiology, 234 (2), pp. 323-329; Hersh, W.R., Mülller, H., Jensen, J.R., Yang, J., Gorman, P.N., Ruch, P., Advancing biomedical image retrieval: Development and analysis of a test collection (2006) Journal of the American Medical Informatics Association: JAMIA, 13 (5), pp. 488-496; Kelly, D., Teevan, J., Implicit feedback for inferring user preference: A bibliography (2003) SIGIR Forum, 37 (2), pp. 18-28; Kockelkorn, T.T.J.P., De Jong, P.A., Gietema, H.A., Grutters, J.C., Prokop, M., Van Ginneken, B., Interactive annotation of textures in thoracic CT scans (2010) Proceedings of SPIE, 7624 (1), pp. 76240X-76240X-8. , March; Li, Q., Li, F., Shiraishi, J., Katsuragawa, S., Sone, S., Doi, K., Investigation of new psychophysical measures for evaluation of similar images on thoracic computed tomography for distinction between benign and malignant nodules (2003) Medical Physics, 30 (10), pp. 2584-2593; Van Rikxoort, E.M., De Hoop, B., Van De Vorst, S., Prokop, M., Van Ginneken, B., Automatic segmentation of pulmonary segments from volumetric chest CT scans (2009) IEEE Transactions on Medical Imaging, 28 (4), pp. 621-630; Sammon, J.W., A nonlinear mapping for data structure analysis (1969) IEEE Transactions on Computers, C-18 (5), pp. 401-409; Slaney, M., Weinberger, K., White, W., Learning a metric for music similarity (2008) Procedings of the 9th International Society for Music Information Retrieval Conference, pp. 313-318; Sluimer, I.C., Prokop, M., Hartmann, I., Van Ginneken, B., Automated classification of hyperlucency, fibrosis, ground glass, solid, and focal lesions in high-resolution CT of the lung (2006) Medical Physics, 33 (7), p. 2610; Yang, L., Jin, R., Mummert, L., Sukthankar, R., Goode, A., Zheng, B., Hoi, S.C., Satyanarayanan, M., A boosting framework for Visuality-Preserving distance metric learning and its application to medical image retrieval (2010) IEEE Transactions on Pattern Analysis and Machine Intelligence, 32 (1), pp. 30-44
Keywords: CBIR system; Computer tomography; Content based retrieval; Content-Based Image Retrieval; Diagnostic performance; Image analysis; Image space; Interstitial lung disease; Learning algorithms; Manifold learning algorithm; Medical computing; Medical knowledge; Radiation; Radiology; Radiology reports; User annotations

Tumor cell-educated periprostatic adipose tissue acquires an aggressive cancer-promoting secretory profile - Ribeiro, R.J.T.; Monteiro, C.P.D.; Cunha, V.F.P.M.; Azevedo, A.S.M.; Oliveira, M.J.; Monteiro, R.; Fraga, A.M.; Príncipe, P.; Lobato, C.; Lobo, F.; Morais, A.; Silva, V.; et al. (Cellular Physiology and BiochemistryCell. Physiol. Biochem., 2012)
Background/Aims: The microenvironment produces important factors that are crucial to prostate cancer (PCa) progression. However, the extent to which the cancer cells stimulate periprostatic adipose tissue (PPAT) to produce these proteins is largely unknown. Our purpose was to determine whether PCa cell-derived factors influence PPAT metabolic activity. Methods: Primary cultures of human PPAT samples from PCa patients (adipose tissue organotypic explants and primary stromal vascular fraction, SVF) were stimulated with conditioned medium (CM) collected from prostate carcinoma (PC3) cells. Cultures without CM were used as control. We used multiplex analysis and ELISA for protein quantification, qPCR to determine mitochondrial DNA (mtDNA) copy number and zymography for matrix metalloproteinase activity, in order to evaluate the response of adipose tissue explants and SVFs to PC3 CM. Results: Stimulation of PPAT explants with PCa PC3 CM induced adipokines associated with cancer progression (osteopontin, tumoral necrosis factor alpha and interleukin-6) and reduced the expression of the protective adipokine adiponectin. Notably, osteopontin protein expression was 13-fold upregulated. Matrix metalloproteinase 9 activity and mitochondrial DNA copy number were higher after stimulation with cancer CM. Stromovascular cells from PPAT in culture were not influenced by tumor-derived factors. Conclusion: The modulation of adipokine expression by tumor CM indicates the pervasive extent to which tumor cells command PPAT to produce factors favorable to their aggressiveness. © 2012 S. Karger AG, Basel.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: CEPBEdoi: 10.1159/000337604PubMed ID: 22415092Language of Original Document: EnglishCorrespondence Address: Ribeiro, R.J.T.; Portuguese Institute of Oncology, Porto Centre Molecular Oncology Group -CI, Edifício Laboratórios -Piso 4, Rua Dr. António Bernardino Almeida, 4200-072 Porto, Portugal; email: oriebir.r@gmail.comChemicals/CAS: adiponectin, 283182-39-8; gelatinase B, 146480-36-6; osteopontin, 106441-73-0; Adiponectin; Culture Media, Conditioned; Cytokines; DNA, Mitochondrial; Interleukin-6; Matrix Metalloproteinase 2, 3.4.24.24; Matrix Metalloproteinase 9, 3.4.24.35; Osteopontin, 106441-73-0; Tumor Necrosis Factor-alphaReferences: Hsing, A.W., Sakoda, L.C., Chua Jr., S., Obesity, metabolic syndrome, and prostate cancer (2007) Am J Clin Nutr, 86, pp. s843-857;Cao, Y., Ma, J., Body mass index, prostate cancer-specific mortality, and biochemical recurrence: A systematic review and meta-analysis (2011) Cancer Prev Res (Phila), 4, pp. 486-501; Baillargeon, J., Rose, D.P., Obesity, adipokines, and prostate cancer (review) (2006) Int J Oncol, 28, pp. 737-745; Mistry, T., Digby, J.E., Desai, K.M., Randeva, H.S., Obesity and Prostate Cancer: A Role for Adipokines (2007) European Urology, 52 (1), pp. 46-53. , DOI 10.1016/j.eururo.2007.03.054, PII S0302283807004307; Hirano, T., Morii, H., Nakazawa, K., Murakami, D., Yamashita, A., Asahi, J., Orimo, H., Tokura, Y., Enhancement of adipogenesis induction by conditioned media obtained from cancer cells (2008) Cancer Lett, 268, pp. 286-294; Andarawewa, K.L., Motrescu, E.R., Chenard, M.-P., Gansmuller, A., Stoll, I., Tomasetto, C., Rio, M.-C., Stromelysin-3 is a potent negative regulator of adipogenesis participating to cancer cell-adipocyte interaction/crosstalk at the tumor invasive front (2005) Cancer Research, 65 (23), pp. 10862-10871. , DOI 10.1158/0008-5472.CAN-05-1231; Jotzu, C., Alt, E., Welte, G., Li, J., Hennessy, B.T., Devarajan, E., Krishnappa, S., Song, Y.H., Adipose tissue derived stem cells differentiate into carcinoma-associated fibroblast-like cells under the influence of tumor derived factors (2011) Cell Oncol (Dordr), 34, pp. 55-67; Dolinkova, M., Dostalova, I., Lacinova, Z., Michalsky, D., Haluzikova, D., Mraz, M., The endocrine profile of subcutaneous and visceral adipose tissue of obese patients (2008) Mol Cell Endocrinol, 291, pp. 63-70; Van Roermund, J.G., Hinnen, K.A., Tolman, C.J., Bol, G.H., Witjes, J.A., Bosch, J.L., Kiemeney, L.A., Van Vulpen, M., Periprostatic fat correlates with tumour aggressiveness in prostate cancer patients (2011) BJU Int, 107, pp. 1775-1779; Sumitomo, M., Asakuma, J., Yoshii, H., Sato, A., Horiguchi, A., Ito, K., Nagakura, K., Asano, T., Anterior perirectal fat tissue thickness is a strong predictor of recurrence after high-intensity focused ultrasound for prostate cancer (2010) Int J Urol, 17, pp. 776-782; Finley, D.S., Calvert, V.S., Inokuchi, J., Lau, A., Narula, N., Petricoin, E.F., Zaldivar, F., Ornstein, D.K., Periprostatic adipose tissue as a modulator of prostate cancer aggressiveness (2009) J Urol, 182, pp. 1621-1627; Thalmann, S., Juge-Aubry, C.E., Meier, C.A., Explant cultures of white adipose tissue (2008) Methods Mol Biol, 456, pp. 195-199; Song, G.J., Lewis, V., Mitochondrial DNA integrity and copy number in sperm from infertile men (2008) Fertil Steril, 90, pp. 2238-2244; Park, J., Euhus, D.M., Scherer, P.E., Paracrine and Endocrine Effects of Adipose Tissue on Cancer Development and Progression (2011) Endocr Rev, 32, pp. 550-570; George, D.J., Halabi, S., Shepard, T.F., Sanford, B., Vogelzang, N.J., Small, E.J., Kantoff, P.W., The prognostic significance of plasma interleukin-6 levels in patients with metastatic hormone-refractory prostate cancer: Results from cancer and leukemia group B 9480 (2005) Clinical Cancer Research, 11 (5), pp. 1815-1820. , DOI 10.1158/1078-0432.CCR-04-1560; Michalaki, V., Syrigos, K., Charles, P., Waxman, J., Serum levels of IL-6 and TNF-α correlate with clinicopathological features and patient survival in patients with prostate cancer (2004) British Journal of Cancer, 90 (12), pp. 2312-2316; Dirat, B., Bochet, L., Dabek, M., Daviaud, D., Dauvillier, S., Majed, B., Wang, Y.Y., Muller, C., Cancerassociated adipocytes exhibit an activated phenotype and contribute to breast cancer invasion (2011) Cancer Res, 71, pp. 2455-2465; Culig, Z., New insights into the role of interleukin-6 in human prostate cancer (2009) J Urol, 182, pp. 1255-1256; Chun, J.Y., Nadiminty, N., Dutt, S., Lou, W., Yang, J.C., Kung, H.J., Evans, C.P., Gao, A.C., Interleukin-6 regulates androgen synthesis in prostate cancer cells (2009) Clin Cancer Res, 15, pp. 4815-4822; Weber, G.F., Lett, G.S., Haubein, N.C., Osteopontin is a marker for cancer aggressiveness and patient survival (2010) Br J Cancer, 103, pp. 861-869; Thalmann, G.N., Sikes, R.A., Devoll, R.E., Kiefer, J.A., Markwalder, R., Klima, I., Farach-Carson, C.M., Chung, L.W.K., Osteopontin: Possible role in prostate cancer progression (1999) Clinical Cancer Research, 5 (8), pp. 2271-2277; McAllister, S.S., Gifford, A.M., Greiner, A.L., Kelleher, S.P., Saelzler, M.P., Ince, T.A., Reinhardt, F., Weinberg, R.A., Systemic Endocrine Instigation of Indolent Tumor Growth Requires Osteopontin (2008) Cell, 133 (6), pp. 994-1005. , DOI 10.1016/j.cell.2008.04.045, PII S0092867408006211; Balkwill, F., TNF-alpha in promotion and progression of cancer (2006) Cancer Metastasis Rev, 25, pp. 409-416; Yan, B., Wang, H., Rabbani, Z.N., Zhao, Y., Li, W., Yuan, Y., Li, F., Li, C.-Y., Tumor necrosis factor-α is a potent endogenous mutagen that promotes cellular transformation (2006) Cancer Research, 66 (24), pp. 11565-11570. , DOI 10.1158/0008-5472.CAN-06-2540; Bates, R.C., Mercurio, A.M., Tumor necrosis factor-α stimulates the epithelial-tomesenchymal transition of human colonic organoids (2003) Molecular Biology of the Cell, 14 (5), pp. 1790-1800. , DOI 10.1091/mbc.E02-09-0583; Yamauchi, T., Kamon, J., Waki, H., Terauchi, Y., Kubota, N., Hara, K., Mori, Y., Kadowaki, T., The fat-derived hormone adiponectin reverses insulin resistance associated with both lipoatrophy and obesity (2001) Nature Medicine, 7 (8), pp. 941-946. , DOI 10.1038/90984; Li, H., Stampfer, M.J., Mucci, L., Rifai, N., Qiu, W., Kurth, T., Ma, J., A 25-year prospective study of plasma adiponectin and leptin concentrations and prostate cancer risk and survival (2010) Clin Chem, 56, pp. 34-43; Ribeiro, R., Lopes, C., Medeiros, R., The link between obesity and prostate cancer: The leptin pathway and therapeutic perspectives (2006) Prostate Cancer and Prostatic Diseases, 9 (1), pp. 19-24. , DOI 10.1038/sj.pcan.4500844, PII 4500844; Vaday, G.G., Peehl, D.M., Kadam, P.A., Lawrence, D.M., Expression of CCL5 (RANTES) and CCR5 in prostate cancer (2006) Prostate, 66 (2), pp. 124-134. , DOI 10.1002/pros.20306; Kessenbrock, K., Plaks, V., Werb, Z., Matrix metalloproteinases: Regulators of the tumor microenvironment (2010) Cell, 141, pp. 52-67; Bouloumie, A., Sengenes, C., Portolan, G., Galitzky, J., Lafontan, M., Adipocyte Produces Matrix Metalloproteinases 2 and 9 Involvement in Adipose Differentiation (2001) Diabetes, 50 (9), pp. 2080-2086; Bergers, G., Brekken, R., McMahon, G., Vu, T.H., Itoh, T., Tamaki, K., Tanzawa, K., Hanahan, D., Matrix metalloproteinase-9 triggers the angiogenic switch during carcinogenesis (2000) Nat Cell Biol, 2, pp. 737-744; Lin, C.Y., Tsai, P.H., Kandaswami, C.C., Lee, P.P., Huang, C.J., Hwang, J.J., Lee, M.T., Matrix metalloproteinase-9 cooperates with transcription factor Snail to induce epithelial-mesenchymal transition (2011) Cancer Sci, 102, pp. 815-827; Chakrabarti, S., Patel, K.D., Matrix metalloproteinase-2 (MMP-2) and MMP-9 in pulmonary pathology (2005) Experimental Lung Research, 31 (6), pp. 599-621. , DOI 10.1080/019021490944232; Sehgal, G., Hua, J., Bernhard, E.J., Sehgal, I., Thompson, T.C., Muschel, R.J., Requirement for matrix metalloproteinase-9 (Gelatinase B) expression in metastasis by murine prostate carcinoma (1998) American Journal of Pathology, 152 (2), pp. 591-596; Johnson, T.R., Koul, S., Kumar, B., Khandrika, L., Venezia, S., Maroni, P.D., Meacham, R.B., Koul, H.K., Loss of PDEF, a prostatederived Ets factor is associated with aggressive phenotype of prostate cancer: Regulation of MMP 9 by PDEF (2010) Mol Cancer, 9, p. 148; Trudel, D., Fradet, Y., Meyer, F., Tetu, B., Matrix metalloproteinase 9 is associated with Gleason score in prostate cancer but not with prognosis (2010) Hum Pathol, 41, pp. 1694-1701; Zhang, L., Shi, J., Feng, J., Klocker, H., Lee, C., Zhang, J., Type IV collagenase (matrix metalloproteinase-2 and -9) in prostate cancer (2004) Prostate Cancer and Prostatic Diseases, 7 (4), pp. 327-332. , DOI 10.1038/sj.pcan.4500750, PII 4500750; Zhong, W.D., Han, Z.D., He, H.C., Bi, X.C., Dai, Q.S., Zhu, G., Ye, Y.K., Chen, Z.N., CD147, MMP-1, MMP-2 and MMP-9 protein expression as significant prognostic factors in human prostate cancer (2008) Oncology, 75, pp. 230-236; Sauer, C.G., Kappeler, A., Spath, M., Kaden, J.J., Michel, M.S., Mayer, D., Bleyl, U., Grobholz, R., Expression and activity of matrix metalloproteinases-2 and -9 in serum, core needle biopsies and tissue specimens of prostate cancer patients (2004) Virchows Archiv, 444 (6), pp. 518-526; Opdenakker, G., Masure, S., Grillet, B., Van Damme, J., Cytokine-mediated regulation of human leukocyte gelatinases and role in arthritis (1991) Lymphokine Cytokine Res, 10, pp. 317-324; Unal, R., Yao-Borengasser, A., Varma, V., Rasouli, N., Labbate, C., Kern, P.A., Ranganathan, G., Matrix metalloproteinase-9 is increased in obese subjects and decreases in response to pioglitazone (2010) J Clin Endocrinol Metab, 95, pp. 2993-3001; Catalan, V., Gomez-Ambrosi, J., Rodriguez, A., Ramirez, B., Silva, C., Rotellar, F., Gil, M.J., Frühbeck, G., Increased adipose tissue expression of lipocalin-2 in obesity is related to inflammation and matrix metalloproteinase-2 and metalloproteinase-9 activities in humans (2009) J Mol Med (Berl), 87, pp. 803-813; Villarroya, J., Giralt, M., Villarroya, F., Mitochondrial DNA: An up-and-coming actor in white adipose tissue pathophysiology (2009) Obesity (Silver Spring), 17, pp. 1814-1820; Robin, E.D., Wong, R., Mitochondrial DNA molecules and virtual number of mitochondria per cell in mammalian cells (1988) J Cell Physiol, 136, pp. 507-513; Kaaman, M., Sparks, L.M., Van Harmelen, V., Smith, S.R., Sjolin, E., Dahlman, I., Arner, P., Strong association between mitochondrial DNA copy number and lipogenesis in human white adipose tissue (2007) Diabetologia, 50 (12), pp. 2526-2533. , DOI 10.1007/s00125-007-0818-6; Yamauchi, T., Kamon, J., Waki, H., Murakami, K., Motojima, K., Komeda, K., Ide, T., Kadowaki, T., The mechanisms by which both heterozygous peroxisome proliferator- activated receptor gamma (PPARgamma) deficiency and PPARgamma agonist improve insulin resistance (2001) J Biol Chem, 276, pp. 41245-41254; Wilson-Fritch, L., Burkart, A., Bell, G., Mendelson, K., Leszyk, J., Nicoloro, S., Czech, M., Corvera, S., Mitochondrial biogenesis and remodeling during adipogenesis and in response to the insulin sensitizer rosiglitazone (2003) Molecular and Cellular Biology, 23 (3), pp. 1085-1094. , DOI 10.1128/MCB.23.3.1085-1094.2003; Ducluzeau, P.H., Priou, M., Weitheimer, M., Flamment, M., Duluc, L., Iacobazi, F., Soleti, R., Malthièry, Y., Dynamic regulation of mitochondrial network and oxidative functions during 3T3-L1 fat cell differentiation (2011) J Physiol Biochem, 67, pp. 285-296; Bogacka, I., Ukropcova, B., McNeil, M., Gimble, J.M., Smith, S.R., Structural and functional consequences of mitochondrial biogenesis in human adipocytes in vitro (2005) Journal of Clinical Endocrinology and Metabolism, 90 (12), pp. 6650-6656. , http://jcem.endojournals.org/cgi/reprint/90/12/6650, DOI 10.1210/jc.2005-1024; Toda, S., Uchihashi, K., Aoki, S., Sonoda, E., Yamasaki, F., Piao, M., Ootani, A., Sugihara, H., Adipose tissueorganotypic culture system as a promising model for studying adipose tissue biology and regeneration (2009) Organogenesis, 5, pp. 50-56; Tuxhorn, J.A., Ayala, G.E., Rowley, D.R., Reactive stroma in prostate cancer progression (2001) Journal of Urology, 166 (6), pp. 2472-2483
Keywords: Adipokines; adiponectin; adipose tissue; adult; article; cancer cell; cancer growth; Cells, Cultured; clinical article; controlled study; Culture Media, Conditioned; culture medium; Cytokines; DNA, Mitochondrial; enzyme activity; enzyme linked immunosorbent assay; explant; gelatinase B; human; human cell; human tissue; Humans; interleukin 6; Interleukin-6; male; Matrix Metalloproteinase 2; Matrix Metalloproteinase 9; Middle Aged; mitochondrial DNA; Osteopontin; Periprostatic adipose tissue; priority journal; Prostate cancer; Prostatic Neoplasms; protein expression; protein induction; protein secretion; quantitative analysis; stroma cell; tissue metabolism; tumor necrosis factor alpha; Tumor Necrosis Factor-alpha

The Arabidopsis D-Type Cyclin CYCD2;1 and the Inhibitor ICK2/KRP2 Modulate Auxin-Induced Lateral Root Formation - Sanz, L.; Dewitte, W.; Forzani, C.; Patell, F.; Nieuwland, J.; Wen, B.; Quelhas, P.; de Jager, S.; Titmus, C.; Campilho, A.; Ren, H.; Estelle, M.; et al. (Plant CellPlant Cell, 2011)
The integration of cell division in root growth and development requires mediation of developmental and physiological signals through regulation of cyclin-dependent kinase activity. Cells within the pericycle form de novo lateral root meristems, and D-type cyclins (CYCD), as regulators of the G 1-to-S phase cell cycle transition, are anticipated to play a role. Here, we show that the D-type cyclin protein CYCD2;1 is nuclear in Arabidopsis thaliana root cells, with the highest concentration in apical and lateral meristems. Loss of CYCD2;1 has a marginal effect on unstimulated lateral root density, but CYCD2;1 is rate-limiting for the response to low levels of exogenous auxin. However, while CYCD2;1 expression requires sucrose, it does not respond to auxin. The protein Inhibitor-Interactor of CDK/Kip Related Protein2 (ICK2/KRP2), which interacts with CYCD2;1, inhibits lateral root formation, and ick2/krp2 mutants show increased lateral root density. ICK2/ KRP2 can modulate the nuclear levels of CYCD2;1, and since auxin reduces ICK2/KRP2 protein levels, it affects both activity and cellular distribution of CYCD2;1. Hence, as ICK2/KRP2 levels decrease, the increase in lateral root density depends on CYCD2;1, irrespective of ICK2/CYCD2;1 nuclear localization. We propose that ICK2/KRP2 restrains root ramification by maintaining CYCD2;1 inactive and that this modulates pericycle responses to auxin fluctuations. © 2011 American Society of Plant Biologists.
Cited By (since 1996): 14Export Date: 21 November 2012Source: ScopusCODEN: PLCEEdoi: 10.1105/tpc.110.080002PubMed ID: 21357490Language of Original Document: EnglishCorrespondence Address: Murray, J. A. H.; Cardiff School of Biosciences, Cardiff University, CF10 3AX Cardiff, United Kingdom; email: murrayja1@cardiff.ac.ukChemicals/CAS: proteasome, 140879-24-9; ATP dependent 26S protease, 3.4.99.-; Arabidopsis Proteins; Cell Cycle Proteins; CycD2 protein, Arabidopsis; Cyclins; ICK2 protein, Arabidopsis; Indoleacetic Acids; Proteasome Endopeptidase Complex, 3.4.25.1References: Achard, P., Gusti, A., Cheminant, S., Alioua, M., Dhondt, S., Coppens, F., Beemster, G.T., Genschik, P., Gibberellin signaling controls cell proliferation rate in Arabidopsis (2009) Curr. Biol., 19, pp. 1188-1193;Alonso, J.M., Genome-wide insertional mutagenesis of Arabidopsis thaliana (2003) Science, 301, pp. 653-657; Baluska, F., Mancuso, S., Volkmann, D., Barlow, P.W., Root apex transition zone: A signalling-response nexus in the root (2010) Trends Plant Sci., 15, pp. 402-408; Bechtold, N., Pelletier, G., In planta Agrobacterium-mediated transformation of adult Arabidopsis thaliana plants by vacuum infiltration (1998) Methods Mol. Biol., 82, pp. 259-266; Bird, D.A., Buruiana, M.M., Zhou, Y., Fowke, L.C., Wang, H., Arabidopsis cyclin-dependent kinase inhibitors are nuclearlocalized and show different localization patterns within the nucleoplasm (2007) Plant Cell Rep., 26, pp. 861-872; Boerjan, W., Cervera, M.T., Delarue, M., Beeckman, T., Dewitte, W., Bellini, C., Caboche, M., Inzé, D., Superroot, a recessive mutation in Arabidopsis, confers auxin overproduction (1995) Plant Cell, 7, pp. 1405-1419; Boisnard-Lorig, C., Colon-Carmona, A., Bauch, M., Hodge, S., Doerner, P., Bancharel, E., Dumas, C., Berger, F., Dynamic analyses of the expression of the HISTONE:YFP fusion protein in Arabidopsis show that syncytial endosperm is divided in mitotic domains (2001) Plant Cell, 13, pp. 495-509; Boniotti, M.B., Gutierrez, C., A cell-cycle-regulated kinase activity phosphorylates plant retinoblastoma protein and contains, in Arabidopsis, a CDKA/cyclin D complex (2001) Plant J., 28, pp. 341-350; Boruc, J., Van den Daele, H., Hollunder, J., Rombauts, S., Mylle, E., Hilson, P., Inzé, D., Russinova, E., Functional modules in the Arabidopsis core cell cycle binary proteinprotein interaction network (2010) Plant Cell, 22, pp. 1264-1280; Brady, S.M., Orlando, D.A., Lee, J.Y., Wang, J.Y., Koch, J., Dinneny, J.R., Mace, D., Benfey, P.N., A high-resolution root spatiotemporal map reveals dominant expression patterns (2007) Science, 318, pp. 801-806; Casimiro, I., Beeckman, T., Graham, N., Bhalerao, R., Zhang, H., Casero, P., Sandberg, G., Bennett, M.J., Dissecting Arabidopsis lateral root development (2003) Trends Plant Sci., 8, pp. 165-171; Casimiro, I., Marchant, A., Bhalerao, R.P., Beeckman, T., Dhooge, S., Swarup, R., Graham, N., Bennett, M., Auxin transport promotes Arabidopsis lateral root initiation (2001) Plant Cell, 13, pp. 843-852; Chevray, P.M., Nathans, D., Protein interaction cloning in yeast: Identification of mammalian proteins that react with the leucine zipper of Jun (1992) Proc. Natl. Acad. Sci. USA, 89, pp. 5789-5793; Churchman, M.L., SIAMESE, a plant-specific cell cycle regulator, controls endoreplication onset in Arabidopsis thaliana (2006) Plant Cell, 18, pp. 3145-3157; Cleary, A., Fowke, L., Wang, H., John, P., The effect of ICK1, a plant cyclin-dependent kinase inhibitor, on mitosis in living plant cells (2002) Plant Cell Rep., 20, pp. 814-820; Clough, S.J., Bent, A.F., Floral dip: A simplified method for Agrobacterium-mediated transformation of Arabidopsis thaliana (1998) Plant J., 16, pp. 735-743; Cockcroft, C.E., den Boer, B.G., Healy, J.M., Murray, J.A.H., Cyclin D control of growth rate in plants (2000) Nature, 405, pp. 575-579; de Smet, I., Vanneste, S., Inzé, D., Beeckman, T., Lateral root initiation or the birth of a new meristem (2006) Plant Mol. Biol., 60, pp. 871-887; de Smet, I., Auxin-dependent regulation of lateral root positioning in the basal meristem of Arabidopsis (2007) Development, 134, pp. 681-690; de Smet, I., Bimodular auxin response controls organogenesis (2010) Proc. Natl. Acad. Sci. USA, 107, pp. 2705-2710; de Veylder, L., Beeckman, T., Beemster, G.T., de Almeida Engler, J., Ormenese, S., Maes, S., Naudts, M., Inzé, D., Control of proliferation, endoreduplication and differentiation by the Arabidopsis E2Fa-DPa transcription factor (2002) EMBO J., 21, pp. 1360-1368; de Veylder, L., Beeckman, T., Beemster, G.T., Krols, L., Terras, F., Landrieu, I., van der Schueren, E., Inzé, D., Functional analysis of cyclin-dependent kinase inhibitors of Arabidopsis (2001) Plant Cell, 13, pp. 1653-1668; de Veylder, L., de Almeida Engler, J., Burssens, S., Manevski, A., Lescure, B., Van Montagu, M., Engler, G., Inzé, D., A new D-type cyclin of Arabidopsis thaliana expressed during lateral root primordia formation (1999) Planta, 208, pp. 453-462; Dewitte, W., Murray, J.A.H., The plant cell cycle (2003) Annu. Rev. Plant Biol., 54, pp. 235-264; Dewitte, W., Riou-Khamlichi, C., Scofield, S., Healy, J.M., Jacqmard, A., Kilby, N.J., Murray, J.A.H., Altered cell cycle distribution, hyperplasia, and inhibited differentiation in Arabidopsis caused by the D-type cyclin CYCD3 (2003) Plant Cell, 15, pp. 79-92; Dewitte, W., Scofield, S., Alcasabas, A.A., Maughan, S.C., Menges, M., Braun, N., Collins, C., Murray, J.A.H., Arabidopsis CYCD3 D-type cyclins link cell proliferation and endocycles and are rate-limiting for cytokinin responses (2007) Proc. Natl. Acad. Sci. USA, 104, pp. 14537-14542; Dharmasiri, N., Dharmasiri, S., Weijers, D., Karunarathna, N., Jurgens, G., Estelle, M., AXL and AXR1 have redundant functions in RUB conjugation and growth and development in Arabidopsis (2007) Plant J., 52, pp. 114-123; Ditengou, F.A., Teale, W.D., Kochersperger, P., Flittner, K.A., Kneuper, I., van der Graaff, E., Nziengui, H., Palme, K., Mechanical induction of lateral root initiation in Arabidopsis thaliana (2008) Proc. Natl. Acad. Sci. USA, 105, pp. 18818-18823; Dubrovsky, J.G., Rost, T.L., Colón-Carmona, A., Doerner, P., Early primordium morphogenesis during lateral root initiation in Arabidopsis thaliana (2001) Planta, 214, pp. 30-36; Dubrovsky, J.G., Sauer, M., Napsucialy-Mendivil, S., Ivanchenko, M.G., Friml, J., Shishkova, S., Celenza, J., Benková, E., Auxin acts as a local morphogenetic trigger to specify lateral root founder cells (2008) Proc. Natl. Acad. Sci. USA, 105, pp. 8790-8794; Duttweiler, H.M., A highly sensitive and non-lethal beta-galactosidase plate assay for yeast (1996) Trends Genet., 12, pp. 340-341; Ebel, C., Mariconti, L., Gruissem, W., Plant retinoblastoma homologues control nuclear proliferation in the female gametophyte (2004) Nature, 429, pp. 776-780; Fukaki, H., Tameda, S., Masuda, H., Tasaka, M., Lateral root formation is blocked by a gain-of-function mutation in the SOLITARY-ROOT/IAA14 gene of Arabidopsis (2002) Plant J., 29, pp. 153-168; Fukaki, H., Tasaka, M., Hormone interactions during lateral root formation (2009) Plant Mol. Biol., 69, pp. 437-449; Healy, J.M., Menges, M., Doonan, J.H., Murray, J.A.H., The Arabidopsis D-type cyclins CycD2 and CycD3 both interact in vivo with the PSTAIRE cyclin-dependent kinase Cdc2a but are differentially controlled (2001) J. Biol. Chem., 276, pp. 7041-7047; Himanen, K., Boucheron, E., Vanneste, S., de Almeida Engler, J., Inzé, D., Beeckman, T., Auxin-mediated cell cycle activation during early lateral root initiation (2002) Plant Cell, 14, pp. 2339-2351; Himanen, K., Vuylsteke, M., Vanneste, S., Vercruysse, S., Boucheron, E., Alard, P., Chriqui, D., Beeckman, T., Transcript profiling of early lateral root initiation (2004) Proc. Natl. Acad. Sci. USA, 101, pp. 5146-5151; Hirano, H., Harashima, H., Shinmyo, A., Sekine, M., Arabidopsis RETINOBLASTOMA-RELATED PROTEIN 1 is involved in G1 phase cell cycle arrest caused by sucrose starvation (2008) Plant Mol. Biol., 66, pp. 259-275; Huntley, R., The maize retinoblastoma protein homologue ZmRb-1 is regulated during leaf development and displays conserved interactions with G1/S regulators and plant cyclin D (CycD) proteins (1998) Plant Mol. Biol., 37, pp. 155-169; Inzé, D., De Veylder, L., Cell cycle regulation in plant development (2006) Annu. Rev. Genet., 40, pp. 77-105; Jakoby, M.J., Weinl, C., Pusch, S., Kuijt, S.J., Merkle, T., Dissmeyer, N., Schnittger, A., Analysis of the subcellular localization, function, and proteolytic control of the Arabidopsis cyclin-dependent kinase inhibitor ICK1/KRP1 (2006) Plant Physiol., 141, pp. 1293-1305; James, P., Halladay, J., Craig, E.A., Genomic libraries and a host strain designed for highly efficient two-hybrid selection in yeast (1996) Genetics, 144, pp. 1425-1436; Jasinski, S., Riou-Khamlichi, C., Roche, O., Perennes, C., Bergounioux, C., Glab, N., The CDK inhibitor NtKIS1a is involved in plant development, endoreduplication and restores normal development of cyclin D3;1-overexpressing plants (2002) J. Cell Sci., 115, pp. 973-982; Karimi, M., Depicker, A., Hilson, P., Recombinational cloning with plant gateway vectors (2007) Plant Physiol., 145, pp. 1144-1154; Kohalmi, S.E., Nowak, J., Crosby, W.L., The yeast twohybrid system (1997) Differentially Expressed Genes in Plants: A Bench Manual, pp. 63-82. , In, E. Hansen and G. Harper, eds (London: Taylor & Francis); Laskowski, M., Grieneisen, V.A., Hofhuis, H., Hove, C.A., Hogeweg, P., Marée, A.F., Scheres, B., Root system architecture from coupling cell shape to auxin transport (2008) PLoS Biol., 6, pp. e307; Laskowski, M.J., Williams, M.E., Nusbaum, H.C., Sussex, I.M., Formation of lateral root meristems is a two-stage process (1995) Development, 121, pp. 3303-3310; Lechner, E., Xie, D., Grava, S., Pigaglio, E., Planchais, S., Murray, J.A.H., Parmentier, Y., Genschik, P., The AtRbx1 protein is part of plant SCF complexes, and its down-regulation causes severe growth and developmental defects (2002) J. Biol. Chem., 277, pp. 50069-50080; Lincoln, C., Britton, J.H., Estelle, M., Growth and development of the axr1 mutants of Arabidopsis (1990) Plant Cell, 2, pp. 1071-1080; López-Bucio, J., Cruz-Ramírez, A., Herrera-Estrella, L., The role of nutrient availability in regulating root architecture (2003) Curr. Opin. Plant Biol., 6, pp. 280-287; Marcuzzo, M., Quelhas, P., Campilho, A., Mendonça, A.M., Campilho, A., Automated Arabidopsis plant root cell segmentation based on SVM classification and region merging (2009) Comput. Biol. Med., 39, pp. 785-793; Masubelele, N.H., Dewitte, W., Menges, M., Maughan, S., Collins, C., Huntley, R., Nieuwland, J., Murray, J.A.H., D-type cyclins activate division in the root apex to promote seed germination in Arabidopsis (2005) Proc. Natl. Acad. Sci. USA, 102, pp. 15694-15699; Menges, M., de Jager, S.M., Gruissem, W., Murray, J.A.H., Global analysis of the core cell cycle regulators of Arabidopsis identifies novel genes, reveals multiple and highly specific profiles of expression and provides a coherent model for plant cell cycle control (2005) Plant J., 41, pp. 546-566; Menges, M., Samland, A.K., Planchais, S., Murray, J.A.H., The D-type cyclin CYCD3;1 is limiting for the G1-to-S-phase transition in Arabidopsis (2006) Plant Cell, 18, pp. 893-906; Minet, M., Dufour, M.E., Lacroute, F.B., Complementation of Saccharomyces cerevisiae auxotrophic mutants by Arabidopsis thaliana cDNAs (1992) Plant J., 2, pp. 417-422; Moreno-Risueno, M.A., Van Norman, J.M., Moreno, A., Zhang, J., Ahnert, S.E., Benfey, P.N., Oscillating gene expression determines competence for periodic Arabidopsis root branching (2010) Science, 329, pp. 1306-1311; Nieuwland, J., Maughan, S., Dewitte, W., Scofield, S., Sanz, L., Murray, J.A.H., The D-type cyclin CYCD4;1 modulates lateral root density in Arabidopsis by affecting the basal meristem region (2009) Proc. Natl. Acad. Sci. USA, 106, pp. 22528-22533; Okushima, Y., Fukaki, H., Onoda, M., Theologis, A., Tasaka, M., ARF7 and ARF19 regulate lateral root formation via direct activation of LBD/ASL genes in Arabidopsis (2007) Plant Cell, 19, pp. 118-130; Péret, B., De Rybel, B., Casimiro, I., Benková, E., Swarup, R., Laplaze, L., Beeckman, T., Bennett, M.J., Arabidopsis lateral root development: An emerging story (2009) Trends Plant Sci., 14, pp. 399-408; Petersson, S.V., Johansson, A.I., Kowalczyk, M., Makoveychuk, A., Wang, J.Y., Moritz, T., Grebe, M., Ljung, K., An auxin gradient and maximum in the Arabidopsis root apex shown by high-resolution cell-specific analysis of IAA distribution and synthesis (2009) Plant Cell, 21, pp. 1659-1668; Petroski, M.D., Deshaies, R.J., Function and regulation of cullin-RING ubiquitin ligases (2005) Nat. Rev. Mol. Cell Biol., 6, pp. 9-20; Planchais, S., Samland, A.K., Murray, J.A.H., Differential stability of Arabidopsis D-type cyclins: CYCD3;1 is a highly unstable protein degraded by a proteasome-dependent mechanism (2004) Plant J., 38, pp. 616-625; Qi, R., John, P.C., Expression of genomic AtCYCD2;1 in Arabidopsis induces cell division at smaller cell sizes: Implications for the control of plant growth (2007) Plant Physiol., 144, pp. 1587-1597; Ren, H., Santner, A., del Pozo, J.C., Murray, J.A.H., Estelle, M., Degradation of the cyclin-dependent kinase inhibitor KRP1 is regulated by two different ubiquitin E3 ligases (2008) Plant J., 53, pp. 705-716; Richter, G.L., Monshausen, G.B., Krol, A., Gilroy, S., Mechanical stimuli modulate lateral root organogenesis (2009) Plant Physiol., 151, pp. 1855-1866; Riou-Khamlichi, C., Huntley, R., Jacqmard, A., Murray, J.A.H., Cytokinin activation of Arabidopsis cell division through a D-type cyclin (1999) Science, 283, pp. 1541-1544; Riou-Khamlichi, C., Menges, M., Healy, J.M., Murray, J.A.H., Sugar control of the plant cell cycle: Differential regulation of Arabidopsis D-type cyclin gene expression (2000) Mol. Cell. Biol., 20, pp. 4513-4521; Sabatini, S., Beis, D., Wolkenfelt, H., Murfett, J., Guilfoyle, T., Malamy, J., Benfey, P., Scheres, B., An auxin-dependent distal organizer of pattern and polarity in the Arabidopsis root (1999) Cell, 99, pp. 463-472; Schnittger, A., Schöbinger, U., Bouyer, D., Weinl, C., Stierhof, Y.D., Hülskamp, M., Ectopic D-type cyclin expression induces not only DNA replication but also cell division in Arabidopsis trichomes (2002) Proc. Natl. Acad. Sci. USA, 99, pp. 6410-6415; van Leene, J., Targeted interactomics reveals a complex core cell cycle machinery in Arabidopsis thaliana (2010) Mol. Syst. Biol., 6, p. 397; Vanneste, S., Cell cycle progression in the pericycle is not sufficient for SOLITARY ROOT/IAA14-mediated lateral root initiation in Arabidopsis thaliana (2005) Plant Cell, 17, pp. 3035-3050; Verkest, A., Manes, C.L., Vercruysse, S., Maes, S., van der Schueren, E., Beeckman, T., Genschik, P., De Veylder, L., The cyclin-dependent kinase inhibitor KRP2 controls the onset of the endoreduplication cycle during Arabidopsis leaf development through inhibition of mitotic CDKA;1 kinase complexes (2005) Plant Cell, 17, pp. 1723-1736; Verkest, A., Weinl, C., Inzé, D., De Veylder, L., Schnittger, A., Switching the cell cycle. Kip-related proteins in plant cell cycle control (2005) Plant Physiol., 139, pp. 1099-1106; Wang, H., Qi, Q., Schorr, P., Cutler, A.J., Crosby, W.L., Fowke, L.C., ICK1, a cyclin-dependent protein kinase inhibitor from Arabidopsis thaliana interacts with both Cdc2a and CycD3, and its expression is induced by abscisic acid (1998) Plant J., 15, pp. 501-510; Wildwater, M., Campilho, A., Perez-Perez, J.M., Heidstra, R., Blilou, I., Korthout, H., Chatterjee, J., Scheres, B., The RETINOBLASTOMA-RELATED gene regulates stem cell maintenance in Arabidopsis roots (2005) Cell, 123, pp. 1337-1349; Willemse, J., Kulikova, O., de Jong, H., Bisseling, T., A new whole-mount DNA quantification method and the analysis of nuclear DNA content in the stem-cell niche of Arabidopsis roots (2008) Plant J., 55, pp. 886-894; Winter, D., Vinegar, B., Nahal, H., Ammar, R., Wilson, G.V., Provart, N.J., An "Electronic Fluorescent Pictograph" browser for exploring and analyzing large-scale biological data sets (2007) PLoS ONE, 2, pp. e718; Zhou, Y., Fowke, L.C., Wang, H., Plant CDK inhibitors: Studies of interactions with cell cycle regulators in the yeast twohybrid system and functional comparisons in transgenic Arabidopsis plants (2002) Plant Cell Rep., 20, pp. 967-975; Zhou, Y., Niu, H., Brandizzi, F., Fowke, L.C., Wang, H., Molecular control of nuclear and subnuclear targeting of the plant CDK inhibitor ICK1 and ICK1-mediated nuclear transport of CDKA (2006) Plant Mol. Biol., 62, pp. 261-278; Zhou, Y., Wang, H., Gilmer, S., Whitwill, S., Fowke, L.C., Effects of co-expressing the plant CDK inhibitor ICK1 and D-type cyclin genes on plant growth, cell size and ploidy in Arabidopsis thaliana (2003) Planta, 216, pp. 604-613
Keywords: Arabidopsis; Arabidopsis protein; Arabidopsis Proteins; Arabidopsis thaliana; article; ATP dependent 26S protease; cell cycle; cell cycle protein; Cell Cycle Proteins; cell nucleus; CycD2 protein, Arabidopsis; cycline; Cyclins; gene expression regulation; Gene Expression Regulation, Plant; genetics; growth, development and aging; ICK2 protein, Arabidopsis; indoleacetic acid derivative; Indoleacetic Acids; metabolism; mutation; plant root; Plant roots; proteasome; Proteasome Endopeptidase Complex

Arabidopsis thaliana automatic cell file detection and cell length estimation - Quelhas, P.; Nieuwland, J.; Dewitte, W.; Mendonça, A.M.; Murray, J.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2011)
In plant development biology, the study of the structure of the plant's root is fundamental for the understanding of the regulation and interrelationships of cell division and cellular differentiation. This is based on the high connection between cell length and progression of cell differentiation and the nuclear state. However, the need to analyse a large amount of images from many replicate roots to obtain reliable measurements motivates the development of automatic tools for root structure analysis. We present a novel automatic approach to detect cell files, the main structure in plant roots, and extract the length of the cells in those files. This approach is based on the detection of local cell file characteristic symmetry using a wavelet based image symmetry measure. The resulting detection enables the automatic extraction of important data on the plant development stage and of characteristics for individual cells. Furthermore, the approach presented reduces in more than 90% the time required for the analysis of each root, improving the work of the biologist and allowing the increase of the amount of data to be analysed for each experimental condition. While our approach is fully automatic a user verification and editing stage is provided so that any existing errors may be corrected. Given five test images it was observed that user did not correct more than 20% of all automatically detected structure, while taking no more than 10% of manual analysis time to do so. © 2011 Springer-Verlag.
Conference code: 85546Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-21596-4_1Language of Original Document: EnglishCorrespondence Address: Quelhas, P.; INEB - Divisão de Sinal e Imagem, Instituto de Engenharia Biomédica, Porto, PortugalReferences: Terpstra, I., Heidstra, R., Stem cells: The root of all cells (2009) Semin. Cell Dev. Biol., 20 (9), pp. 1089-1096;Bennett, T., Scheres, B., Root development-two meristems for the price of one? (2010) Curr. Top Dev. Bio., 91, pp. 67-102; De Smet, I., Tetsumura, T., De Rybel, B., Frey, N.F., Laplaze, L., Casimiro, I., Swarup, R., Beeckman, T., Auxin-dependent regulation of lateral root positioning in the basal meristem of arabidopsis (2007) Development, 134 (4), pp. 681-690; Nieuwland, J., Maughan, S., Dewitte, W., Scofield, S., Sanz, L., Murray, J.A., The d-type cyclin cycd4;1 modulates lateral root density in arabidopsis by affecting the basal meristem region (2009) Proc. Natl. Acad. Sci. U S A, 106 (52), pp. 22528-22533; Vanstraelen, M., Baloban, M., Da Ines, O., Cultrone, A., Lammens, T., Boudolf, V., Brown, S.C., Kondorosi, E., Apc/c-ccs52a complexes control meristem maintenance in the arabidopsis root (2009) Proc. Natl. Acad. Sci. U S A, 106 (28), pp. 11806-11811; Beemster, G., Baskin, T., Analysis of cell division and elongation underlying the developmental acceleration of root growth in arabidopsis thaliana (1998) Plant Physiology, 116, pp. 1515-1526; Iwamoto, A., Satoh, D., Furutani, M., Maruyama, S., Ohba, H., Sugiyama, M., Insight into the basis of root growth in arabidopsis thaliana provided by a simple mathematical model (2006) J. Plant Res., 119, pp. 85-93; Immink, R., Gadella, T., Ferrario, S., Busscher, M., Angenent, G., Analysis of mads box protein-protein interactions in living plant cells (2002) Proc. Natl. Acad. Sci. USA, 99, pp. 2416-2421; Willemse, J., Kulikova, O., Jong, H., Bisseling, T., A new whole-mount dna quantification method and the analysis of nuclear dna content in the stem-cell niche of arabidopsis roots (2008) The Plant Journal, 10, pp. 1365-1374; Marcuzzo, M., Quelhas, P., Campilho, A., Mendonça, A.M., Campilho, A., Automated arabidopsis plant root cell segmentation based on svm classification and region merging (2009) Comp. in Biology and Medicine, 39, pp. 785-793; Marcuzzo, M., Guichard, T., Quelhas, P., Mendonça, A.M., Campilho, A., Cell division detection on the arabidopsis thaliana root (2009) LNCS, 5524, pp. 168-175. , Araujo, H., Mendonça, A.M., Pinho, A.J., Torres, M.I. (eds.) IbPRIA 2009. Springer, Heidelberg; Kovesi, P., Symmetry and asymmetry from local phase Proc. of the 10th Australian Joint Conf. on Artificial Intelligence (December 1997); Campilho, A., Garcia, B., Toorn, H., Wijk, H., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the arabidopsis thaliana root meristem (2006) The Plant Journal, 48, pp. 619-627; Dabov, K., Foi, A., Katkovnik, V., Egiazarian, K., Image denoising by sparse 3d transform-domain collaborative filtering (2007) IEEE Trans. on Image Processing, 16 (8), pp. 2080-2095; Otsu, N., A threshold selection method from gray-level histograms (1979) IEEE Transactions on Systems, Man, and Cybernetics, SMC-9 (1), pp. 62-66
Keywords: Arabidopsis thaliana; Automatic extraction; Automatic tools; Bio-imaging; BioImaging; cell differentiation; Cell divisions; Cell lengths; cell proliferation; Cells; Cellular differentiation; Experimental conditions; Image analysis; image symmetry; Individual cells; Main structure; Manual analysis; Nuclear state; Plant development; Plant roots; Plants (botany); Reliable measurement; Root structure; Test images; User verification; Wavelet analysis; Wavelet-based images

Automatic segmentation of chromatographic images for region of interest delineation - Mendonça, A.M.; Sousa, A.V.; Sá-Miranda, M.C.; Campilho, A.C. (Progress in Biomedical Optics and Imaging - Proceedings of SPIEProgr. Biomed. Opt. Imaging Proc. SPIE, 2011)
This paper describes a segmentation method for automating the region of interest (ROI) delineation in chromatographic images, thus allowing the definition of the image area that contains the fundamental information for further processing while excluding the frame of the chromatographic plate that does not contain relevant data for disease identification. This is the first component of a screening tool for Fabry disease, which will be based on the automatic analysis of the chromatographic patterns extracted from the image ROI. Image segmentation is performed in two phases, where each individual pixel is finally considered as frame or ROI. In the first phase, an unsupervised learning method is used for classifying image pixels into three classes: frame, ROI or unknown. In the second phase, distance features are used for deciding which class the unknown pixels belong to. The segmentation result is post-processed using a sequence of morphological operators in order to obtain the final ROI rectangular area. The proposed methodology was successfully evaluated in a dataset of 41 chromatographic images. © 2011 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).
Conference code: 84913Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusArt. No.: 79623Bdoi: 10.1117/12.877671Language of Original Document: EnglishCorrespondence Address: Mendonça, A. M.; Instituto de Engenharia Biomédica, Universidade Do Porto, Rua Dr. Roberto Frias, s/n, 4200-465 Porto, Portugal; email: amendon@fe.up.ptReferences: Zarate, Y., Hopkin, R., Fabry's disease (2008) The Lancet, 372 (9647), pp. 1427-1435;Gerasimov, A.V., Use of the Software Processing of Scanned Chromatogram Images in Quantitative Planar Chromatography (2004) J. of Anal Chem., 59 (4), pp. 348-353; Bajla, I., Hollander, I., Fluch, S., Burg, K., Kollar, M., An alternative method for electrophoretic gel image analysis in the GelMaster software (2005) Comput Methods Programs Biomed, 77 (3), pp. 209-231; Sousa, A.V., Mendonca, A.M., Campilho, A., Chromatographic pattern classification (2008) IEEE Trans on Biomedical Engineering, 55 (6), pp. 1687-1696; Bajla, I., Rublík, F., Arendacká, B., Farkaš, I., Hornišová, K., Štolc, S., Witkovský, V., Segmentation and supervised classification of image objects in Epo doping-control (2009) Machine Vision and Applications, 20 (4), pp. 243-259; Sousa, A.V., Aguiar, R., Mendonça, A.M., Campilho, A., Automatic lane and band detection in images of Thin-Layer Chromatography (2004) LNCS, 3212, pp. 158-216. , Springer; Dempster, A., Laird, N., Rubin, D., Maximum Likelihood from incomplete data via the EM algorithm (1977) J. of the Royal Statistical Society. Series B, 39 (1), pp. 1-38; Heijden, F., Duin, R.P.W., Ridder, D., Tax, D.M.J., (2004) Classification, Parameter Estimation and State Estimation - An Engineering Approach Using Matlab, , John Wiley & Sons Sponsors: The Society of Photo-Optical Instrumentation Engineers (SPIE); Dynasil Corporation/RMD Research; American Association of Physicists in Medicine (AAPM); DQE Instruments, Inc.; Ocean Thin Films, Inc.
Keywords: Automatic analysis; Automatic segmentations; Chromatographic images; Chromatographic plates; Chromatography; Data sets; Distance feature; Fabry disease; Image pixels; Image segmentation; Imaging systems; Medical imaging; Morphological operator; Pixels; Rectangular area; Region of interest; Region of interest delineation; Screening tool; Second phase; Segmentation methods; Segmentation results; Unsupervised learning; Unsupervised learning method

Bone marrow-derived endothelial progenitors expressing delta-like 4 (Dll4) regulate tumor angiogenesis - Real, C.; Remédio, L.; Caiado, F.; Igreja, C.; Borges, C.; Trindade, A.; Pinto-Do-Ó, P.; Yagita, H.; Duarte, A.; Dias, S. (PLoS ONEPLoS ONE, 2011)
Neo-blood vessel growth (angiogenesis), which may involve the activation of pre-existing endothelial cells (EC) and/or the recruitment of bone marrow-derived vascular precursor cells (BM-VPC), is essential for tumor growth. Molecularly, besides the well established roles for Vascular endothelial growth factor (VEGF), recent findings show the Notch signalling pathway, in particular the ligand Delta-like 4 (Dll4), is also essential for adequate tumor angiogenesis; Dll4 inhibition results in impaired, non-functional, angiogenesis and reduced tumor growth. However, the role of BM-VPC in the setting of Notch pathway modulation was not addressed and is the subject of the present report. Here we show that SDF-1 and VEGF, which are produced by tumors, increase Dll4 expression on recruited BM-VPC. Mechanistically, BM-VPC activated, in a Dll4-dependent manner, a transcriptional program on mature EC suggestive of EC activation and stabilization. BM-VPC induced ICAM-2 and Fibronectin expression on EC, an effect that was blocked by a Dll4-specific neutralizing antibody. In vivo, transplantation of BM-VPC with decreased Dll4 into tumor-bearing mice resulted in the formation of microvessels with decreased pericyte coverage and reduced fibronectin expression. Consequently, transplantation of BM-VPC with decreased Dll4 resulted in impaired tumor angiogenesis, increased tumor hypoxia and apoptosis, and decreased tumor growth. Taken together, our data suggests that Dll4 expression by BM-VPC affects their communication with tumor vessel endothelial cells, thereby modulating tumor angiogenesis by affecting vascular stability. © 2011 Real et al.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusArt. No.: e18323doi: 10.1371/journal.pone.0018323Language of Original Document: EnglishCorrespondence Address: Dias, S.; Angiogenesis Laboratory, CIPM/Portuguese Institute of Oncology, Lisbon, Portugal; email: sergidias@ipolisboa.min-saude.ptChemicals/CAS: fibronectin, 86088-83-7; vasculotropin, 127464-60-2; DLL4 protein, mouse; Intracellular Signaling Peptides and Proteins; Membrane ProteinsReferences: Asahara, T., Masuda, H., Takahashi, T., Kalka, C., Pastore, C., Bone marrow origin of endothelial progenitor cells responsible for postnatal vasculogenesis in physiological and pathological neovascularization (1999) Circ Res, 85, pp. 221-228;Rafii, S., Lyden, D., Benezra, R., Hattori, K., Heissig, B., Vascular and haematopoietic stem cells: Novel targets for anti-angiogenesis therapy? (2002) Nat Rev Cancer, 2, pp. 826-835. , Review; Lyden, D., Hattori, K., Dias, S., Costa, C., Blaikie, P., Impaired recruitment of bone-marrow-derived endothelial and hematopoietic precursor cells blocks tumor angiogenesis and growth (2001) Nat Med, 7, pp. 1194-1201; Larrivee, B., Niessen, K., Pollet, I., Corbel, S.Y., Long, M., Minimal contribution of marrow-derived endothelial precursors to tumor vasculature (2005) J Immunol, 175, pp. 2890-2899; Peters, B.A., Diaz, L.A., Polyak, K., Meszler, L., Romans, K., Contribution of bone marrow-derived endothelial cells to human tumor vasculature (2005) Nat Med, 11, pp. 261-262; Pasquier, E., Dias, S., Endothelial progenitor cells: Hope beyond controversy (2010) Curr Cancer Drug Targets, 10 (8), pp. 914-921; Dudley, A.C., Udagawa, T., Melero-Martin, J.M., Shih, S.C., Curatolo, A., Bone marrow is a reservoir for proangiogenic myelomonocytic cells but not endothelial cells in spontaneous tumors (2010) Blood, 116 (17), pp. 2267-2271; Krebs, L.T., Xue, Y., Norton, C.R., Shutter, J.R., Maguire, M., Notch signaling is essential for vascular morphogenesis in mice (2000) Genes Dev, 14, pp. 1343-1352; Uyttendaele, H., Ho, J., Rossant, J., Kitajewski, J., Vascular patterning defects associated with expression of activated Notch4 in embryonic endothelium (2001) Proc Natl Acad Sci U S A, 98, pp. 5643-5648; Duarte, A., Hirashima, M., Benedito, R., Trindade, A., Diniz, P., Dosage-sensitive requirement for mouse Dll4 in artery development (2004) Genes Dev, 18, pp. 2474-2478; Gale, N.W., Dominguez, M.G., Noguera, I., Pan, L., Hughes, V., Haploinsufficiency of delta-like 4 ligand results in embryonic lethality due to major defects in arterial and vascular development (2004) Proc Natl Acad Sci U S A, 101, pp. 15949-15954; Carmeliet, P., Ferreira, V., Breier, G., Pollefeyt, S., Kieckens, L., Abnormal blood vessel development and lethality in embryos lacking a single VEGF allele (1996) Nature, 380, pp. 435-439; Mailhos, C., Modlich, U., Lewis, J., Harris, A., Bicknell, R., Delta4, an endothelial specific notch ligand expressed at sites of physiological and tumor angiogenesis (2001) Differentiation, 69, pp. 135-144; Oliner, J., Min, H., Leal, J., Yu, D., Rao, S., Suppression of angiogenesis and tumor growth by selective inhibition of angiopoietin-2 (2004) Cancer Cell, 6, pp. 507-516; Patel, N.S., Li, J.L., Generali, D., Poulsom, R., Cranston, D.W., Up-regulation of delta-like 4 ligand in human tumor vasculature and the role of basal expression in endothelial cell function (2005) Cancer Res, 65, pp. 8690-8697; Williams, C.K., Li, J.L., Murga, M., Harris, A.L., Tosato, G., Up-regulation of the Notch ligand Delta-like 4 inhibits VEGF-induced endothelial cell function (2006) Blood, 107, pp. 931-939; Caiado, F., Real, C., Carvalho, T., Dias, S., Notch pathway modulation on bone marrow-derived vascular precursor cells regulates their angiogenic and wound healing potential (2008) PLoS One, 3, pp. e3752; Escudier, B., Eisen, T., Stadler, W.M., Szczylik, C., Oudard, S., Sorafenib in advanced clear-cell renal-cell carcinoma (2007) N Engl J Med, 356, pp. 125-134; Llovet, J.M., Ricci, S., Mazzaferro, V., Hilgard, P., Gane, E., Sorafenib in advanced hepatocellular carcinoma (2008) N Engl J Med, 359, pp. 378-390; Motzer, R.J., Bukowski, R.M., Targeted therapy for metastatic renal cell carcinoma (2006) J Clin Oncol, 24, pp. 5601-5608; Bergers, G., Hanahan, D., Modes of resistance to anti-angiogenic therapy (2008) Nat Rev Cancer, 8, pp. 592-603; Verheul, H.M., Pinedo, H.M., Possible molecular mechanisms involved in the toxicity of angiogenesis inhibition (2007) Nat Rev Cancer, 7, pp. 475-485; Noguera-Troise, I., Daly, C., Papadopoulos, N.J., Coetzee, S., Boland, P., Blockade of Dll4 inhibits tumour growth by promoting non-productive angiogenesis (2006) Nature, 444, pp. 1032-1037; Ridgway, J., Zhang, G., Wu, Y., Stawicki, S., Liang, W.C., Inhibition of Dll4 signalling inhibits tumour growth by deregulating angiogenesis (2006) Nature, 444, pp. 1083-1087; Moore, M.A., Hattori, K., Heissig, B., Shieh, J.H., Dias, S., Mobilization of endothelial and hematopoietic stem and progenitor cells by adenovector-mediated elevation of serum levels of SDF-1, VEGF, and angiopoietin-1 (2001) Ann N Y Acad Sci, 938, pp. 36-45. , discussion 45-37; Yamaguchi, J., Kusano, K.F., Masuo, O., Kawamoto, A., Silver, M., Stromal cell-derived factor-1 effects on ex vivo expanded endothelial progenitor cell recruitment for ischemic neovascularization (2003) Circulation, 107, pp. 1322-1328; Leslie, J.D., Ariza-McNaughton, L., Bermange, A.L., McAdow, R., Johnson, S.L., Endothelial signalling by the Notch ligand Delta-like 4 restricts angiogenesis (2007) Development, 134, pp. 839-844; Trindade, A., Kumar, S.R., Scehnet, J.S., Lopes-da-Costa, L., Becker, J., Overexpression of delta-like 4 induces arterialization and attenuates vessel formation in developing mouse embryos (2008) Blood, 112, pp. 1720-1729; Huang, M.T., Mason, J.C., Birdsey, G.M., Amsellem, V., Gerwin, N., Endothelial intercellular adhesion molecule (ICAM)-2 regulates angiogenesis (2005) Blood, 106, pp. 1636-1643; Deutsch, U., Schlaeger, T.M., Dehouck, B., Doring, A., Tauber, S., Inducible endothelial cell-specific gene expression in transgenic mouse embryos and adult mice (2008) Exp Cell Res, 314, pp. 1202-1216; Dias, S., Thomas, H., Balkwill, F., Multiple molecular and cellular changes associated with tumour stasis and regression during IL-12 therapy of a murine breast cancer model (1998) Int J Cancer, 75 (1), pp. 151-157; Scott, K.A., Holdsworth, H., Balkwill, F.R., Dias, S., Exploiting changes in the tumour microenvironment with sequential cytokine and matrix metalloprotease inhibitor treatment in a murine breast cancer model (2000) Br J Cancer, 83 (11), pp. 1538-1543
Keywords: angiogenesis; animal; animal cell; animal tissue; Animals; apoptosis; article; blood vessel; Blood Vessels; bone marrow; bone marrow cell; Bone Marrow Cells; cell activation; Cell Line, Tumor; cell proliferation; controlled study; cytology; delta like 4 protein; DLL4 protein, mouse; Endothelial Cells; endothelium cell; Female; Fibronectin; gene expression; gene expression regulation; genetics; human; human cell; Humans; hypoxia; in vitro study; in vivo study; intercellular adhesion molecule 2; Intracellular Signaling Peptides and Proteins; membrane protein; Membrane Proteins; metabolism; Mice; mouse; Mus; neoplasm; Neoplasms; neovascularization (pathology); Neovascularization, Pathologic; neutralizing antibody; nonhuman; Notch receptor; Pathology; pericyte; protein expression; signal peptide; solid tumor; stem cell; stem cell transplantation; Stem cells; stromal cell derived factor 1; tumor cell line; tumor growth; unclassified drug; vascularization; vasculotropin

Classification-based segmentation of the region of interest in chromatographic images - Sousa, A.V.; Mendonça, A.M.; Sá-Miranda, M.C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2011)
This paper proposes a classification-based method for automating the segmentation of the region of interest (ROI) in digital images of chromatographic plates. Image segmentation is performed in two phases. In the first phase an unsupervised learning method classifies the image pixels into three classes: frame, ROI or unknown. In the second phase, distance features calculated for the members of the three classes are used for deciding on the new label, ROI or frame, for each individual connected segment previously classified as unknown.The segmentation result is post-processed using a sequence of morphological operators before obtaining the final ROI rectangular area. The proposed methodology, which is the initial step for the development of a screening tool for Fabry disease, was successfully evaluated in a dataset of 58 chromatographic images. © 2011 Springer-Verlag.
Conference code: 85546Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-21596-4_8Language of Original Document: EnglishCorrespondence Address: Sousa, A.V.; Instituto de Engenharia Biomédica, Universidade Do Porto, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: asousa@eu.ipp.ptReferences: Zarate, Y., Hopkin, R., Fabry's Disease (2008) The Lancet, 372 (9647), pp. 1427-1435;Linthorst, G.E., Vedder, A., Aerts, J.M., Hollak, C.E., Screening for Fabry Disease Using Whole Blood Spots Fails to Identify One-third of Female Carriers (2005) Clinica Chimica Acta, 353 (1-2), pp. 201-203; Eng, C.M., Germain, D.P., Banikazemi, M., Warnock, D.G., Wanner, C., Hopkin, R.J., Bultas, J., Wilcox, W.R., Fabry Disease: Guidelines for the Evaluation and Management of Multi-organ System Involvement (2006) Genetics in Medicine, 8 (9), pp. 539-548; Gerasimov, A.V., Use of the Software Processing of Scanned Chromatogram Images in Quantitative Planar Chromatography (2004) J. of Anal. Chem., 59 (4), pp. 348-353; Bajla, I., Hollander, I., Fluch, S., Burg, K., Kollar, M., An Alternative Method for Electrophoretic Gel Image Analysis in the Gelmaster Software (2005) Comput. Methods Programs Biomed., 77 (3), pp. 209-231; Sousa, A.V., Mendonça, A.M., Campilho, A., Chromatographic Pattern Classification (2008) IEEE Trans. on Biomedical Engineering, 55 (6), pp. 1687-1696; Bajla, I., Rublík, F., Arendacká, B., Farkaš, I., Hornišová, K., Štolc, S., Witkovský, V., Segmentation and Supervised Classification of Image Objects in Epo Doping-control (2009) Machine Vision and Applications, 20 (4), pp. 243-259; Sousa, A.V., Aguiar, R., Mendonça, A.M., Campilho, A., Automatic Lane and Band Detection in Images of Thin Layer Chromatography (2004) LNCS, 3212, pp. 158-165. , Campilho, A.C., Kamel, M.S. (eds.) ICIAR 2004. Springer, Heidelberg; Mendonça, A.M., Sousa, A.V., Sá-Miranda, M.C., Campilho, A., Automatic segmentation of chromatographic images for region of interest delineation (2011) SPIE Medical Imaging; Dempster, A., Laird, N., Rubin, D., Maximum Likelihood from Incomplete Data via the EM Algorithm (1997) J. of the Royal Statistical Society. Series B, 39 (1), pp. 1-38; Heijden, F., Robert, P.W.D., Ridder, D., Tax, D.M.J., (2004) Classification, Parameter Estimation and State Estimation, , John Wiley & Sons, Chichester
Keywords: Chromatographic images; Chromatographic plates; Chromatography; Data sets; Digital image; Distance feature; Fabry disease; Image analysis; Image pixels; Image segmentation; Morphological operator; Rectangular area; Region of interest; Region of interest delineation; Screening tool; Second phase; Segmentation results; Unsupervised learning; Unsupervised learning method

Complexity and categorical analysis may improve the interpretation of agreement studies using continuous variables - Costa-Santos, C.; Bernardes, J.; Antunes, L.; Ayres-de-Campos, D. (Journal of Evaluation in Clinical PracticeJ. Eval. Clin. Pract., 2011)
Rationale Complex clinical scenarios involving a high degree of uncertainty frequently lead to a poor agreement over diagnosis and management. However, inconsistent results can be found with the most widely used measures of agreement for continuous variables - the limits of agreement and the intraclass correlation coefficient. Aims and objectives We aim to improve the interpretation of agreement studies using continues variables. Methods and results Evaluation of agreement may be improved by complexity analysis and by categorization of variables, followed by the use of the proportions of agreement. Conclusions The average never characterizes a complex phenomenon and the methods used to access agreement in continuous variables are based on the mean. For future agreement studies, involving complex continuous variables, we recommend a complexity and categorical analysis. © 2011 Blackwell Publishing Ltd.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JECPFdoi: 10.1111/j.1365-2753.2011.01668.xPubMed ID: 21489051Language of Original Document: EnglishCorrespondence Address: Costa-Santos, C.; Department of Biostatistics and Medical Informatics, Faculty of Medicine, University of Porto, Al. Prof. Hernâni Monteiro, 4200-319 Porto, Portugal; email: csantos@med.up.ptReferences: Costa Santos, C., Costa Pereira, A., Bernardes, J., Agreement studies in obstetrics and gynaecology: Inappropriateness, controversies and consequences (2005) BJOG: An International Journal of Obstetrics and Gynaecology, 112 (5), pp. 667-669. , DOI 10.1111/j.1471-0528.2004.00505.x;Khan, K.S., Chien, P.F., Evaluation of a clinical test. I: Assessment of reliability (2001) BJOG, 108, pp. 562-567; Luiz, R.R., Szklo, M., More than one statistical strategy to assess agreement of quantitative measurements may usefully be reported (2005) Journal of Clinical Epidemiology, 58 (3), pp. 215-216. , DOI 10.1016/j.jclinepi.2004.07.007; Costa-Santos, C., Bernardes, J., Ayres-De-Campos, D., Costa, A., Costa, C., The limits of agreement and the intraclass correlation coefficient may be inconsistent in the interpretation of agreement (2011) Journal of Clinical Epidemiology, 64 (3), pp. 264-269; Costa-Santos, C., Antunes, L., Souto, A., Bernardes, J., Assessment of disagreement: A new information-based approach (2010) Annals of Epidemiology, 20, pp. 555-561; Luiz, R.R., Costa, A.J.L., Kale, P.L., Werneck, G.L., Assessment of agreement of a quantitative variable: A new graphical approach (2003) Journal of Clinical Epidemiology, 56 (10), pp. 963-967. , DOI 10.1016/S0895-4356(03)00164-1; Plsek, P.E., Greenhalgh, T., The challenge of complexity in health care (2001) British Medical Journal, 323 (7313), pp. 625-628; Shiell, A., Hawe, P., Gold, L., Complex interventions or complex systems? Implications for health economic evaluation (2008) BMJ, 336 (7656), pp. 1281-1283; Wilson, T., Holt, T., Complexity science: Complexity and clinical care (2001) British Medical Journal, 323 (7314), pp. 685-688; Miles, A., Complexity in medicine and healthcare: People and systems, theory and practice (2009) Journal of Evaluation in Clinical Practice, 15 (3), pp. 409-410; Shannon, Î., A mathematical theory of communication (1948) Bell System Technical Journal, 27, pp. 379-423. , 623- 656; Bernardes, J., Costa-Pereira, A., Ayres-De-Campos, D., Van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) International Journal of Gynecology and Obstetrics, 57 (1), pp. 33-37. , DOI 10.1016/S0020-7292(97)02846-4, PII S0020729297028464; Ayres-De-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) British Journal of Obstetrics and Gynaecology, 106, pp. 1307-1310; Rooth, G., Guidelines for the use of fetal monitoring (1987) International Journal of Gynaecology and Obstetrics, 25, pp. 159-167; Grant, J.M., The fetal heart rate is normal, isn't it? Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Müller, R., Büttner, P., A critical discussion of intraclass correlation coefficients (1994) Statistics in Medicine, 13, pp. 2465-2476; Byrt, T., Bishop, J., Carlin, J.B., Bias, prevalence and kappa (1993) Journal of Clinical Epidemiology, 46 (5), pp. 423-429. , DOI 10.1016/0895-4356(93)90018-V; West, B.J., Homeostasis and Gauss statistics: Barriers to understanding natural variability (2010) Journal of Evaluation in Clinical Practice, 16, pp. 403-408; Goncalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Medical and Biological Engineering and Computing, 44 (10), pp. 847-855. , DOI 10.1007/s11517-006-0105-6; Costa Santos, C., Vitanyi, P.M.B., Bernardes, J., Antunes, L., Clustering fetal heart rate tracings by compression (2006) Proceedings - IEEE Symposium on Computer-Based Medical Systems, 2006, pp. 685-690. , DOI 10.1109/CBMS.2006.68, 1647650, Proceedings - 19th IEEE International Symposium on Computer-Based Medical Systems, CBMS 2006
Keywords: article; Biomedical research; Cardiotocography; clinical decision making; clinical practice; complexity; Data Interpretation, Statistical; Decision Making; entropy; Female; fetus heart rate; Heart Rate, Fetal; human; Humans; observer variation; Pregnancy; Pregnancy Outcome; priority journal; Reproducibility of Results; statistical data interpretation; Uncertainty

Covalent immobilization of antimicrobial peptides (AMPs) onto biomaterial surfaces - Costa, F.; Carvalho, I.F.; Montelaro, R.C.; Gomes, P.; Martins, M.C.L. (Acta BiomaterialiaActa Biomater., 2011)
Bacterial adhesion to biomaterials remains a major problem in the medical devices field. Antimicrobial peptides (AMPs) are well-known components of the innate immune system that can be applied to overcome biofilm-associated infections. Their relevance has been increasing as a practical alternative to conventional antibiotics, which are declining in effectiveness. The recent interest focused on these peptides can be explained by a group of special features, including a wide spectrum of activity, high efficacy at very low concentrations, target specificity, anti-endotoxin activity, synergistic action with classical antibiotics, and low propensity for developing resistance. Therefore, the development of an antimicrobial coating with such properties would be worthwhile. The immobilization of AMPs onto a biomaterial surface has further advantages as it also helps to circumvent AMPs' potential limitations, such as short half-life and cytotoxicity associated with higher concentrations of soluble peptides. The studies discussed in the current review report on the impact of covalent immobilization of AMPs onto surfaces through different chemical coupling strategies, length of spacers, and peptide orientation and concentration. The overall results suggest that immobilized AMPs may be effective in the prevention of biofilm formation by reduction of microorganism survival post-contact with the coated biomaterial. Minimal cytotoxicity and long-term stability profiles were obtained by optimizing immobilization parameters, indicating a promising potential for the use of immobilized AMPs in clinical applications. On the other hand, the effects of tethering on mechanisms of action of AMPs have not yet been fully elucidated. Therefore, further studies are recommended to explore the real potential of immobilized AMPs in health applications as antimicrobial coatings of medical devices. © 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Cited By (since 1996): 24Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2010.11.005PubMed ID: 21056701Language of Original Document: EnglishCorrespondence Address: Martins, M. C. L.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade Do Porto, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: cmartins@ineb.up.ptChemicals/CAS: amoxicillin, 26787-78-0, 34642-77-8, 61336-70-7; ampicillin, 69-52-3, 69-53-4, 7177-48-2, 74083-13-9, 94586-58-0; carbenicillin, 17230-86-3, 4697-36-3, 4800-94-6; cefazolin, 25953-19-9, 27164-46-1; gentamicin, 1392-48-9, 1403-66-3, 1405-41-0; penicillin G, 1406-05-9, 61-33-6; teicoplanin, 61036-62-2, 61036-64-4; tobramycin, 32986-56-4; vancomycin, 1404-90-6, 1404-93-9; Antimicrobial Cationic Peptides; Biocompatible Materials; Coated Materials, Biocompatible; Immobilized ProteinsReferences: Glinel, K., Jonas, A.M., Jouenne, T., Leprince, J., Galas, L., Huck, W.T., Antibacterial and antifouling polymer brushes incorporating antimicrobial peptide (2009) Bioconj Chem, 20 (1), pp. 71-77;Vila, J., Soriano, A., Mensa, J., Molecular basis of microbial adherence to prosthetic materials. Role of biofilms in prosthesis-associated infection (2008) Enferm Infecc Microbiol Clin, 26 (1), pp. 48-54; Hetrick, E.M., Schoenfisch, M.H., Reducing implant-related infections: Active release strategies (2006) Chemical Society Reviews, 35 (9), pp. 780-789. , DOI 10.1039/b515219b; Darouiche, R.O., Treatment of Infections Associated with Surgical Implants (2004) New England Journal of Medicine, 350 (14), pp. 1422-1429. , DOI 10.1056/NEJMra035415; Zhao, L., Chu, P.K., Zhang, Y., Wu, Z., Antibacterial coatings on titanium implants (2009) J Biomed Mater Res B Appl Biomater, 91 (1), pp. 470-480; Dee, K.C., Puleo, D.A., Bizios, R., (2002) An Introduction to Tissue-biomaterial Interactions, , Wiley-Liss New York; Subramani, K., Jung, R.E., Molenberg, A., Hammerle, C.H., Biofilm on dental implants: A review of the literature (2009) Int J Oral Maxillofac Implants, 24 (4), pp. 616-626; Fey, P.D., Olson, M.E., Current concepts in biofilm formation of Staphylococcus epidermidis (2010) Future Microbiol, 5 (6), pp. 917-933; De Carvalho, C.C., Biofilms: Recent developments on an old battle (2007) Recent Pat Biotechnol, 1 (1), pp. 49-57; Costerton, J.W., Stewart, P.S., Greenberg, E.P., Bacterial biofilms: A common cause of persistent infections (1999) Science, 284 (5418), pp. 1318-1322. , DOI 10.1126/science.284.5418.1318; Willcox, M.D., Hume, E.B., Aliwarga, Y., Kumar, N., Cole, N., A novel cationic-peptide coating for the prevention of microbial colonization on contact lenses (2008) J Appl Microbiol, 105 (6), pp. 1817-1825; Lewis, K., Riddle of biofilm resistance (2001) Antimicrobial Agents and Chemotherapy, 45 (4), pp. 999-1007. , DOI 10.1128/AAC.45.4.999-1007.2001; Monteiro, D.R., Gorup, L.F., Takamiya, A.S., Ruvollo-Filho, A.C., De Camargo, E.R., Barbosa, D.B., The growing importance of materials that prevent microbial adhesion: Antimicrobial effect of medical devices containing silver (2009) Int J Antimicrob Agents, 34 (2), pp. 103-110; Gooderham, W.J., Bains, M., McPhee, J.B., Wiegand, I., Hancock, R.E., Induction by cationic antimicrobial peptides and involvement in intrinsic polymyxin and antimicrobial peptide resistance, biofilm formation, and swarming motility of PsrA in Pseudomonas aeruginosa (2008) J Bacteriol, 190 (16), pp. 5624-5634; Bagge, N., Schuster, M., Hentzer, M., Ciofu, O., Givskov, M., Greenberg, E.P., Hoiby, N., Pseudomonas aeruginosa Biofilms Exposed to Imipenem Exhibit Changes in Global Gene Expression and β-Lactamase and Alginate Production (2004) Antimicrobial Agents and Chemotherapy, 48 (4), pp. 1175-1187. , DOI 10.1128/AAC.48.4.1175-1187.2004; Ahmed, N.A., Petersen, F.C., Scheie, A.A., AI-2/LuxS is involved in increased biofilm formation by Streptococcus intermedius in the presence of antibiotics (2009) Antimicrob Agents Chemother, 53 (10), pp. 4258-4263; Hoffman, L.R., D'Argenio, D.A., MacCoss, M.J., Zhang, Z., Jones, R.A., Miller, S.I., Aminoglycoside antibiotics induce bacterial biofilm formation (2005) Nature, 436 (7054), pp. 1171-1175. , DOI 10.1038/nature03912; Harbers, G.M., Emoto, K., Greef, C., Metzger, S.W., Woodward, H.N., Mascali, J.J., Grainger, D.W., Lochhead, M.J., Functionalized poly(ethylene glycol)-based bioassay surface chemistry that facilitates bio-immobilization and inhibits nonspecific protein, bacterial, and mammalian cell adhesion (2007) Chemistry of Materials, 19 (18), pp. 4405-4414. , DOI 10.1021/cm070509u; Chapman, R.G., Ostuni, E., Liang, M.N., Meluleni, G., Kim, E., Yan, L., Pier, G., Whitesides, G.M., Polymeric thin films that resist the adsorption of proteins and the adhesion of bacteria (2001) Langmuir, 17 (4), pp. 1225-1233. , DOI 10.1021/la001222d; Goncalves, I.C., Martins, M.C., Barbosa, M.A., Naeemi, E., Ratner, B.D., Selective protein adsorption modulates platelet adhesion and activation to oligo(ethylene glycol)-terminated self-assembled monolayers with C18 ligands (2009) J Biomed Mater Res A, 89 (3), pp. 642-653; Chung, D., Papadakis, S.E., Yam, K.L., Evaluation of a polymer coating containing triclosan as the antimicrobial layer for packaging materials (2003) International Journal of Food Science and Technology, 38 (2), pp. 165-169. , DOI 10.1046/j.1365-2621.2003.00657.x; Leung, D., Spratt, D.A., Pratten, J., Gulabivala, K., Mordan, N.J., Young, A.M., Chlorhexidine-releasing methacrylate dental composite materials (2005) Biomaterials, 26 (34), pp. 7145-7153. , DOI 10.1016/j.biomaterials.2005.05.014, PII S0142961205003881; Ravikumar, T., Murata, H., Koepsel, R.R., Russell, A.J., Surface-active antifungal polyquaternary amine (2006) Biomacromolecules, 7 (10), pp. 2762-2769. , DOI 10.1021/bm060476w; Bach, A., Darby, D., Bottiger, B., Bohrer, H., Motsch, J., Martin, E., Retention of the antibiotic teicoplanin on a hydromer-coated central venous catheter to prevent bacterial colonization in postoperative surgical patients (1996) Intensive Care Medicine, 22 (10), pp. 1066-1069. , DOI 10.1007/s001340050214; Jose, B., Antoci Jr., V., Zeiger, A.R., Wickstrom, E., Hickok, N.J., Vancomycin covalently bonded to titanium beads kills Staphylococcus aureus (2005) Chemistry and Biology, 12 (9), pp. 1041-1048. , DOI 10.1016/j.chembiol.2005.06.013, PII S1074552105002309; Kilic, D., Agalar, C., Ozturk, E., Denkbas, E.B., Cime, A., Agalar, F., Antimicrobial activity of cefazolin-impregnated mesh grafts (2007) ANZ Journal of Surgery, 77 (4), pp. 256-260. , DOI 10.1111/j.1445-2197.2007.04029.x; Gallardo-Moreno, A.M., Pacha-Olivenza, M.A., Saldana, L., Perez-Giraldo, C., Bruque, J.M., Vilaboa, N., In vitro biocompatibility and bacterial adhesion of physico-chemically modified Ti6Al4V surface by means of UV irradiation (2009) Acta Biomater, 5 (1), pp. 181-192; Jansen, B., Kohnen, W., Prevention of biofilm formation by polymer modification (1995) Journal of Industrial Microbiology, 15 (4), pp. 391-396. , DOI 10.1007/BF01569996; Martins, M.C.L., Wang, D., Ji, J., Feng, L., Barbosa, M.A., Albumin and fibrinogen adsorption on Cibacron blue F3G-A immobilised onto PU-PHEMA (polyurethane-poly (hydroxyethylmethacrylate)) surfaces (2003) Journal of Biomaterials Science, Polymer Edition, 14 (5), pp. 439-455. , DOI 10.1163/156856203766652057; Zhang, F., Zhang, Z., Zhu, X., Kang, E.T., Neoh, K.G., Silk-functionalized titanium surfaces for enhancing osteoblast functions and reducing bacterial adhesion (2008) Biomaterials, 29 (36), pp. 4751-4759; Flemming, R.G., Capelli, C.C., Cooper, S.L., Proctor, R.A., Bacterial colonization of functionalized polyurethanes (2000) Biomaterials, 21 (3), pp. 273-281; Singla, A.K., Chawla, M., Chitosan: Some pharmaceutical and biological aspects - An update (2001) Journal of Pharmacy and Pharmacology, 53 (8), pp. 1047-1067. , DOI 10.1211/0022357011776441; Murata, H., Koepsel, R.R., Matyjaszewski, K., Russell, A.J., Permanent, non-leaching antibacterial surfaces-2: How high density cationic surfaces kill bacterial cells (2007) Biomaterials, 28 (32), pp. 4870-4879. , DOI 10.1016/j.biomaterials.2007.06.012, PII S0142961207004681; Aumsuwan, N., Danyus, R.C., Heinhorst, S., Urban, M.W., Attachment of ampicillin to expanded poly(tetrafluoroethylene): Surface reactions leading to inhibition of microbial growth (2008) Biomacromolecules, 9 (7), pp. 1712-1718; Cevher, E., Orhan, Z., Mulazimoglu, L., Sensoy, D., Alper, M., Yildiz, A., Characterization of biodegradable chitosan microspheres containing vancomycin and treatment of experimental osteomyelitis caused by methicillin-resistant Staphylococcus aureus with prepared microspheres (2006) Int J Pharm, 317 (2), pp. 127-135; Faber, C., Stallmann, H.P., Lyaruu, D.M., Joosten, U., Von Eiff, C., Van Nieuw Amerongen, A., Wuisman, P.I.J.M., Comparable efficacies of the antimicrobial peptide human lactoferrin 1-11 and gentamicin in a chronic methicillin-resistant Staphylococcus aureus osteomyelitis model (2005) Antimicrobial Agents and Chemotherapy, 49 (6), pp. 2438-2444. , DOI 10.1128/AAC.49.6.2438-2444.2005; Aumsuwan, N., Heinhorst, S., Urban, M.W., Antibacterial surfaces on expanded polytetrafluoroethylene; penicillin attachment (2007) Biomacromolecules, 8 (2), pp. 713-718. , DOI 10.1021/bm061050k; Palumbi, S.R., Humans as the world's greatest evolutionary force (2001) Science, 293 (5536), pp. 1786-1790. , DOI 10.1126/science.293.5536.1786; Andreu, D., Rivas, L., Animal antimicrobial peptides: An overview (1998) Biopolymers, 47 (6), pp. 415-433; Rivas, L., Luque-Ortega, J.R., Andreu, D., Amphibian antimicrobial peptides and Protozoa: Lessons from parasites (2009) Biochim Biophys Acta, 1788 (8), pp. 1570-1581; Gordon, Y.J., Romanowski, E.G., McDermott, A.M., Mini review: A review of antimicrobial peptides and their therapeutic potential as anti-infective drugs (2005) Current Eye Research, 30 (7), pp. 505-515. , DOI 10.1080/02713680590968637; Guani-Guerra, E., Santos-Mendoza, T., Lugo-Reyes, S.O., Teran, L.M., Antimicrobial peptides: General overview and clinical implications in human health and disease (2010) Clin Immunol, 135 (1), pp. 1-11; Perron, G.G., Zasloff, M., Bell, G., Experimental evolution of resistance to an antimicrobial peptide (2006) Proceedings of the Royal Society B: Biological Sciences, 273 (1583), pp. 251-256. , DOI 10.1098/rspb.2005.3301; Reddy, K.V.R., Yedery, R.D., Aranha, C., Antimicrobial peptides: Premises and promises (2004) International Journal of Antimicrobial Agents, 24 (6), pp. 536-547. , DOI 10.1016/j.ijantimicag.2004.09.005, PII S092485790400322X; Van 'T Hof, W., Veerman, E.C.I., Heimerhorst, E.J., Nieuw Amerongen, A.V., Antimicrobial peptides: Properties and applicability (2001) Biological Chemistry, 382 (4), pp. 597-619. , DOI 10.1515/BC.2001.072; Li, M., Cha, D.J., Lai, Y., Villaruz, A.E., Sturdevant, D.E., Otto, M., The antimicrobial peptide-sensing system aps of Staphylococcus aureus (2007) Molecular Microbiology, 66 (5), pp. 1136-1147. , DOI 10.1111/j.1365-2958.2007.05986.x; Li, M., Lai, Y., Villaruz, A.E., Cha, D.J., Sturdevant, D.E., Otto, M., Gram-positive three-component antimicrobial peptide-sensing system (2007) Proceedings of the National Academy of Sciences of the United States of America, 104 (22), pp. 9469-9474. , DOI 10.1073/pnas.0702159104; Otto, M., Bacterial sensing of antimicrobial peptides (2009) Contrib Microbiol, 16, pp. 136-149; Peschel, A., Vincent Collins, L., Staphylococcal resistance to antimicrobial peptides of mammalian and bacterial origin (2001) Peptides, 22 (10), pp. 1651-1659. , DOI 10.1016/S0196-9781(01)00500-9, PII S0196978101005009; Peschel, A., Jack, R.W., Otto, M., Collins, L.V., Staubitz, P., Nicholson, G., Kalbacher, H., Van Strijp, J.A.G., Staphylococcus aureus resistance to human defensins and evasion of neutrophil killing via the novel virulence factor MprF is based on modification of membrane lipids with L-lysine (2001) Journal of Experimental Medicine, 193 (9), pp. 1067-1076. , DOI 10.1084/jem.193.9.1067; Cao, M., Helmann, J.D., The Bacillus subtilis Extracytoplasmic-Function σ X Factor Regulates Modification of the Cell Envelope and Resistance to Cationic Antimicrobial Peptides (2004) Journal of Bacteriology, 186 (4), pp. 1136-1146. , DOI 10.1128/JB.186.4.1136-1146.2004; Clarke, S.R., Foster, S.J., IsdA protects Staphylococcus aureus against the bactericidal protease activity of apolactoferrin (2008) Infection and Immunity, 76 (4), pp. 1518-1526. , DOI 10.1128/IAI.01530-07; Vuong, C., Voyich, J.M., Fischer, E.R., Braughton, K.R., Whitney, A.R., DeLeo, F.R., Otto, M., Polysaccharide intercellular adhesin (PIA) protects Staphylococcus epidermidis against major components of the human innate immune system (2004) Cellular Microbiology, 6 (3), pp. 269-275. , DOI 10.1046/j.1462-5822.2004.00367.x; Zasloff, M., Antimicrobial peptides of multicellular organisms (2002) Nature, 415 (6870), pp. 389-395. , DOI 10.1038/415389a; Hancock, R.E.W., Peptide antibiotics (1997) Lancet, 349 (9049), pp. 418-422. , DOI 10.1016/S0140-6736(97)80051-7; Cho, W.-M., Joshi, B.P., Cho, H., Lee, K.-H., Design and synthesis of novel antibacterial peptide-resin conjugates (2007) Bioorganic and Medicinal Chemistry Letters, 17 (21), pp. 5772-5776. , DOI 10.1016/j.bmcl.2007.08.056, PII S0960894X0701013X; Statz, A.R., Park, J.P., Chongsiriwatana, N.P., Barron, A.E., Messersmith, P.B., Surface-immobilised antimicrobial peptoids (2008) Biofouling, 24 (6), pp. 439-448; Deslouches, B., Gonzalez, I.A., DeAlmeida, D., Islam, K., Steele, C., Montelaro, R.C., Mietzner, T.A., De novo-derived cationic antimicrobial peptide activity in a murine model of Pseudomonas aeruginosa bacteraemia (2007) Journal of Antimicrobial Chemotherapy, 60 (3), pp. 669-672. , DOI 10.1093/jac/dkm253; Novak, K.F., Diamond, W.J., Kirakodu, S., Peyyala, R., Anderson, K.W., Montelaro, R.C., Mietzner, T.A., Efficacy of the de novo-derived antimicrobial peptide WLBU2 against oral bacteria (2007) Antimicrobial Agents and Chemotherapy, 51 (5), pp. 1837-1839. , DOI 10.1128/AAC.00924-06; Deslouches, B., Islam, K., Craigo, J.K., Paranjape, S.M., Montelaro, R.C., Mietzner, T.A., Activity of the de novo engineered antimicrobial peptide WLBU2 against Pseudomonas aeruginosa in human serum and whole blood: Implications for systemic applications (2005) Antimicrobial Agents and Chemotherapy, 49 (8), pp. 3208-3216. , DOI 10.1128/AAC.49.8.3208-3216.2005; Deslouches, B., Phadke, S.M., Lazarevic, V., Cascio, M., Islam, K., Montelaro, R.C., Mietzner, T.A., De novo generation of cationic antimicrobial peptides: Influence of length and tryptophan substitution on antimicrobial activity (2005) Antimicrobial Agents and Chemotherapy, 49 (1), pp. 316-322. , DOI 10.1128/AAC.49.1.316-322.2005; Levin, M., Quint, P.A., Goldstein, B., Barton, P., Bradley, J.S., Shemie, S.D., Recombinant bactericidal/permeability-increasing protein (rBPI21) as adjunctive treatment for children with severe meningococcal sepsis: A randomised trial. rBPI21 Meningococcal Sepsis Study Group (2000) Lancet, 356 (9234), pp. 961-967; Giroir, B.P., Scannon, P.J., Levin, M., Bactericidal/permeability-increasing protein-lessons learned from the phase III, randomized, clinical trial of rBPI21 for adjunctive treatment of children with severe meningococcemia (2001) Crit Care Med, 29 (7 SUPPL.), pp. 130-135; Brogden, K.A., Antimicrobial peptides: Pore formers or metabolic inhibitors in bacteria? (2005) Nature Reviews Microbiology, 3 (3), pp. 238-250. , DOI 10.1038/nrmicro1098; Bastos, M., Bai, G., Gomes, P., Andreu, D., Goormaghtigh, E., Prieto, M., Energetics and partition of two cecropin-melittin hybrid peptides to model membranes of different composition (2008) Biophys J, 94 (6), pp. 2128-2141; Melo, M.N., Ferre, R., Castanho, M.A., Antimicrobial peptides: Linking partition, activity and high membrane-bound concentrations (2009) Nat Rev Microbiol, 7 (3), pp. 245-250; Haynie, S.L., Crum, G.A., Doele, B.A., Antimicrobial activities of amphiphilic peptides covalently bonded to a water-insoluble resin (1995) Antimicrob Agents Chemother, 39 (2), pp. 301-307; Humblot, V., Yala, J.F., Thebault, P., Boukerma, K., Hequet, A., Berjeaud, J.M., The antibacterial activity of Magainin i immobilized onto mixed thiols self-assembled monolayers (2009) Biomaterials, 30 (21), pp. 3503-3512; Bagheri, M., Beyermann, M., Dathe, M., Immobilization reduces the activity of surface-bound cationic antimicrobial peptides with no influence upon the activity spectrum (2009) Antimicrob Agents Chemother, 53 (3), pp. 1132-1141; Gabriel, M., Nazmi, K., Veerman, E.C., Nieuw Amerongen, A.V., Zentner, A., Preparation of LL-37-grafted titanium surfaces with bactericidal activity (2006) Bioconj Chem, 17 (2), pp. 548-550; Hilpert, K., Elliott, M., Jenssen, H., Kindrachuk, J., Fjell, C.D., Korner, J., Screening and characterization of surface-tethered cationic peptides for antimicrobial activity (2009) Chem Biol, 16 (1), pp. 58-69; Batista, M.K.S., Gallemi, M., Adeva, A., Gomes, C.A.R., Gomes, P., Facile regioselective synthesis of a novel chitosan-pexiganan conjugate with potential interest for the treatment of infected skin lesions (2009) Synthetic Commun, 39 (7), pp. 1228-1240; Venter, J.C., Immobilized and insolubilized drugs, hormones, and neurotransmitters: Properties, mechanisms of action and applications (1982) Pharmacological Reviews, 34 (2), pp. 153-187; Endo, Y., Tani, T., Kodama, M., Antimicrobial activity of tertiary amine covalently bonded to a polystyrene fiber (1987) Appl Environ Microbiol, 53 (9), pp. 2050-2055; Chuang, H.F., Shukla, A., Loose, C.R., Hammond-Cunningham, P.T., Stephanopoulos, G., (2009) Structures Including Antimicrobial Peptides, , United States; Chen, R., Cole, N., Willcox, M.D., Park, J., Rasul, R., Carter, E., Synthesis, characterization and in vitro activity of a surface-attached antimicrobial cationic peptide (2009) Biofouling, 25 (6), pp. 517-524; Steven, M.D., Hotchkiss, J.H., Covalent immobilization of an antimicrobial peptide on poly(ethylene) film (2008) J Appl Polym Sci, 110 (5), pp. 2665-2670; Appendini, P., Hotchkiss, J.H., Surface modification of poly(styrene) by the attachment of an antimicrobial peptide (2001) J Appl Polym Sci, 81 (3), pp. 609-616; Fields, G.B., Noble, R.L., Solid phase peptide synthesis utilizing 9-fluorenylmethoxycarbonyl amino acids (1990) International Journal of Peptide and Protein Research, 35 (3), pp. 161-214; Rostovtsev, V.V., Green, L.G., Fokin, V.V., Sharpless, K.B., A stepwise huisgen cycloaddition process: Copper(I)-catalyzed regioselective "ligation" of azides and terminal alkynes (2002) Angewandte Chemie - International Edition, 41 (14), pp. 2596-2599. , DOI 10.1002/1521-3773(20020715)41: 14<2596::AID-ANIE2596>3.0.CO;2-4; Abad, J.M., Velez, M., Santamaria, C., Guisan, J.M., Matheus, P.R., Vazquez, L., Gazaryan, I., Fernandez, V.M., Immobilization of peroxidase glycoprotein on gold electrodes modified with mixed epoxy-boronic acid monolayers (2002) Journal of the American Chemical Society, 124 (43), pp. 12845-12853. , DOI 10.1021/ja026658p; Lee, M.-R., Shin, I., Fabrication of chemical microarrays by efficient immobilization of hydrazide-linked substances on epoxide-coated glass surfaces (2005) Angewandte Chemie - International Edition, 44 (19), pp. 2881-2884. , DOI 10.1002/anie.200462720; Hudalla, G.A., Murphy, W.L., Immobilization of peptides with distinct biological activities onto stem cell culture substrates using orthogonal chemistries (2010) Langmuir, 26 (9), pp. 6449-6456; Cole, N., Hume, E.B., Vijay, A.K., Sankaridurg, P., Kumar, N., Willcox, M.D., In vivo performance of melimine as an antimicrobial coating for contact lenses in models of CLARE and CLPU (2010) Invest Ophthalmol Vis Sci, 51 (1), pp. 390-395
Keywords: Amino Acid Sequence; amoxicillin; ampicillin; Animals; antibiotic agent; antibiotic resistance; Antimicrobial Cationic Peptides; Antimicrobial peptides; Bacteria (microorganisms); Bacterial adhesion; bacterial survival; Biocompatible Materials; biofilm; Biofilms; biomaterial; carbenicillin; cefazolin; Coated Materials, Biocompatible; Cytotoxicity; drug activity; drug half life; drug solubility; drug stability; drug targeting; gentamicin; human; Humans; Immobilized Proteins; Molecular Sequence Data; mouth inflammation; Nanostructured surfaces; nonhuman; penicillin G; polypeptide antibiotic agent; priority journal; review; sepsis; skin infection; soft tissue infection; Surface functionalization; Surface Properties; teicoplanin; tobramycin; vancomycin

Friction and wear behaviour of bacterial cellulose against articular cartilage - Lopes, J.L.; Machado, J.M.; Castanheira, L.; Granja, P.L.; Gama, F.M.; Dourado, F.; Gomes, J.R. (WearWear, 2011)
Bacterial cellulose (BC) is a natural and biocompatible material with unique properties, such as high water holding capacity, ultra-fine fibre network and high strength that makes it an attractive material for the repair of articular cartilage lesions. However, data on the tribological properties of BC is very scarce, particularly if natural articular cartilage is involved in the contact. In this work, unmodified BC pellicles were grown from Gluconacetobacter xylinus in order to be used as tribological samples against bovine articular cartilage (BAC) in the presence of phosphate buffered saline (PBS). The tribological assessment of the sliding pairs was accomplished using reciprocating pin-on-flat tests at 37°C. The reciprocating sliding frequency and stroke length were kept constant at 1Hz and 8mm, respectively. Contact pressures ranging from 0.80 to 2.40MPa were applied. The friction coefficient evolution was continuously monitored during the tests and the release of total carbohydrates into the lubricating solution was followed by means of the phenol-H 2SO 4 method as an attempt to evaluate wear losses. The morphology of worn surfaces was characterized by SEM/EDS and the main wear mechanisms were identified. Low friction coefficient values (∼0.05) combined with the preservation of the mating surfaces (BC and BAC) indicate the potential of BC to be used as artificial cartilage for articular joints. © 2011 Elsevier B.V.
Keywords: Articular cartilage; Articular cartilages; Articular joints; Artificial cartilages; Bacterial cellulose; Bacteriology; Biocompatible Materials; Biological materials; Biotribology; Bovine articular cartilage; Carbohydrates; Cartilage; Cellulose; Contact pressures; Fibre network; Friction; Friction and wear; Friction coefficients; Gluconacetobacter xylinus; High strength; High water; Low friction coefficients; Mating surfaces; Phenols; Phosphate-buffered salines; Pin-on-flat; Reciprocating sliding; SEM/EDS; Stroke length; Total carbohydrates; Tribological properties; Tribology; Wear; Wear loss; Wear mechanisms; Worn surface

Interactions of leukocytes and platelets with poly(lysine/leucine) immobilized on tetraethylene glycol-terminated self-assembled monolayers - Martins, M.C.L.; Ochoa-Mendes, V.; Ferreira, G.; Barbosa, J.N.; Curtin, S.A.; Ratner, B.D.; Barbosa, M.A. (Acta BiomaterialiaActa Biomater., 2011)
Surfaces that bind heparin are important for biomaterials for blood deheparinization. In our recent work it was demonstrated that a polypeptide composed of l-lysine and l-leucine (pKL), after immobilization onto tetra(ethylene glycol) terminated self-assembled monolayers (EG4-SAMs), can bind heparin from blood plasma in a selective, concentration-dependent way. During this work the effect of this peptide on platelet adhesion and activation and leukocyte adhesion was studied. The surface charge of these nanostructured surfaces was evaluated in order to correlate the effect of positively charged amine groups and hydrophobic methyl groups on the behavior of platelets and leukocyte adhesion. The results demonstrated that the presence of pKL decreased leukocyte adhesion to EG4-SAMs at all concentrations used. This effect is even more pronounced when surfaces were pre-immersed in heparinized plasma. In contrast, there is an increase in platelet adhesion and activation with increased percentage immobilized pKL. This effect is enhanced when surfaces were pre-immersed in heparinized plasma. However, adsorbed pKL in very low amounts does not induce platelet adhesion and activation compared with EG4, even when pre-immersed in plasma. Since only low pKL amounts are necessary to induce heparin selectivity, these results are promising for the development of heparin-binding biomaterials for blood deheparinization. © 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2011.01.013PubMed ID: 21237292Language of Original Document: EnglishCorrespondence Address: Martins, M. C. L.; Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade Do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cmartins@ineb.up.ptChemicals/CAS: heparin, 37187-54-5, 8057-48-5, 8065-01-8, 9005-48-5; leucine, 61-90-5, 7005-03-0; polylysine, 25104-18-1, 25988-63-0, 33960-24-6, 38000-06-5, 73565-56-7; Ethylene Glycol, 107-21-1; Imidazoles; Immobilized Proteins; N,N-carbonyldiimidazole, 530-62-1; Polyethylene Glycols; Polylysine, 25104-18-1; ProteinsReferences: Dailey, J., (1998) Blood, , 2nd ed. Ipswich (MA, USA): Medical Consulting Group;Section V: Chronic intermittent haemodialysis and prevention of clotting in the extracorporal system (2002) Nephrol Dial Transplant, 17 (SUPPL. 7), pp. 63-71. , European Best Practice Guidelines Working Group; Martins, M.C., Curtin, S.A., Freitas, S.C., Salgueiro, P., Ratner, B.D., Barbosa, M.A., Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide (2009) J Biomed Mater Res A, 88, pp. 162-173; Love, J.C., Estroff, L.A., Kriebel, J.K., Nuzzo, R.G., Whitesides, G.M., Self-assembled monolayers of thiolates on metals as a form of nanotechnology (2005) Chemical Reviews, 105 (4), pp. 1103-1169. , DOI 10.1021/cr0300789; Cardin, A.D., Weintraub, H.J.R., Molecular modeling of protein-glycosaminoglycan interactions (1989) Arteriosclerosis, 9 (1), pp. 21-32; Prime, K.L., Whitesides, G.M., Adsorption of proteins onto surfaces containing end-attached oligo(ethylene oxide) - A model system using self-assembled monolayers (1993) J Am Chem Soc, 115, pp. 10714-10721; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl-terminated alkanethiols self-assembled monolayers (2003) Journal of Biomedical Materials Research - Part A, 67 (1), pp. 158-171; Werner, C., Konig, U., Augsburg, A., Arnhold, C., Korber, H., Zimmermann, R., Jacobasch, H.-J., Electrokinetic surface characterization of biomedical polymers - A survey (1999) Colloids and Surfaces A: Physicochemical and Engineering Aspects, 159 (2-3), pp. 519-529. , DOI 10.1016/S0927-7757(99)00290-3, PII S0927775799002903; Frank, R.D., Dresbach, H., Thelen, H., Sieberth, H.-G., Glutardialdehyde induced fluorescence technique (GIFT): A new method for the imaging of platelet adhesion on biomaterials (2000) Journal of Biomedical Materials Research, 52 (2), pp. 374-381. , DOI 10.1002/1097-4636(200011)52:2<374::AID-JBM18>3.0.CO;2-Z; Chan, Y.H.M., Schweiss, R., Werner, C., Grunze, M., Electrokinetic characterization of oligo- and poly(ethylene glycol)-terminated self-assembled monolayers on gold and glass surfaces (2003) Langmuir, 19, pp. 7380-7385; Schweiss, R., Welzel, P.B., Werner, C., Knoll, W., Dissociation of surface functional groups and preferential adsorption of ions on self-assembled monolayers assessed by streaming potential and streaming current measurements (2001) Langmuir, 17 (14), pp. 4304-4311. , DOI 10.1021/la001741g; Rodrigues, S.N., Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27 (31), pp. 5357-5367. , DOI 10.1016/j.biomaterials.2006.06.010, PII S0142961206005515; Goncalves, I.C., Martins, M.C., Barbosa, M.A., Naeemi, E., Ratner, B.D., Selective protein adsorption modulates platelet adhesion and activation to oligo(ethylene glycol)-terminated self-assembled monolayers with C18 ligands (2009) J Biomed Mater Res, 89 A, pp. 642-653; Prime, K.L., Whitesides, G.M., Self-assembled organic monolayers: Model systems for studying adsorption of proteins at surfaces (1991) Science, 252 (5009), pp. 1164-1167; Mrksich, M., Using self-assembled monolayers to model the extracellular matrix (2009) Acta Biomater, 5, pp. 832-841; Sagnella, S., Mai-Ngam, K., Chitosan based surfactant polymers designed to improve blood compatibility on biomaterials (2005) Colloids Surf B Biointerfaces, 42, pp. 147-155; Chuang, W.H., Lin, J.C., Surface characterization and platelet adhesion studies for the mixed self-assembled monolayers with amine and carboxylic acid terminated functionalities (2007) J Biomed Mater Res A, 82, pp. 820-830; Chen, S., Yu, F., Yu, Q., He, Y., Jiang, S., Strong resistance of a thin crystalline layer of balanced charged groups to protein adsorption (2006) Langmuir, 22 (19), pp. 8186-8191. , DOI 10.1021/la061012m; Chen, S.F., Jiang, S.Y., A new avenue to nonfouling materials (2008) Adv Mater, 20, p. 335; Li, D., Chen, H., Glenn McClung, W., Brash, J.L., Lysine-PEG-modified polyurethane as a fibrinolytic surface. effect of PEG chain length on protein interactions, platelet interactions and clot lysis (2009) Acta Biomater, 5, pp. 1864-1871; Tsai, W.-B., Grunkemeier, J.M., Horbett, T.A., Variations in the ability of adsorbed fibrinogen to mediate platelet adhesion to polystyrene-based materials: A multivariate statistical analysis of antibody binding to the platelet binding sites of fibrinogen (2003) Journal of Biomedical Materials Research - Part A, 67 (4), pp. 1255-1268; Weisel, J.W., Nagaswami, C., Vilaire, G., Bennett, J.S., Examination of the platelet membrane glycoprotein IIb-IIIa complex and its interaction with fibrinogen and other ligands by electron microscopy (1992) J Biol Chem, 267 (23), pp. 16637-16643; Gorbet, M.B., Sefton, M.V., Biomaterial-associated thrombosis: Roles of coagulation factors, complement, platelets and leukocytes (2004) Biomaterials, 25 (26), pp. 5681-5703. , DOI 10.1016/j.biomaterials.2004.01.023, PII S0142961204000687; Brash, J.L., Tenhove, P., Protein adsorption studies on standard polymeric materials (1993) J Biomater Sci Polym Ed, 4, pp. 591-599; Sigal, G.B., Mrksich, M., Whitesides, G.M., Effect of surface wettability on the adsorption of proteins and detergents (1998) Journal of the American Chemical Society, 120 (14), pp. 3464-3473. , DOI 10.1021/ja970819l; Silin, V., Weetall, H., Vanderah, D.J., SPR studies of the nonspecific adsorption kinetics of human IgG and BSA on gold surfaces modified by self-assembled monolayers (SAMs) (1997) Journal of Colloid and Interface Science, 185 (1), pp. 94-103. , DOI 10.1006/jcis.1996.4586; Jenney, C.R., Anderson, J.M., Adsorbed serum proteins responsible for surface dependent human macrophage behavior (2000) Journal of Biomedical Materials Research, 49 (4), pp. 435-447. , DOI 10.1002/(SICI)1097-4636(20000315)49:4<435::AID-JBM2>3.0.CO;2-Y; Werthen, M., Sellborn, A., Kalltorp, M., Elwing, H., Thomsen, P., In vitro study of monocyte viability during the initial adhesion to albumin- and fibrinogen-coated surfaces (2001) Biomaterials, 22, pp. 827-832; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) Journal of Biomedical Materials Research, 50 (3), pp. 291-301. , DOI 10.1002/(SICI)1097-4636(20000605)50:3<291::AID-JBM2>3.0.CO;2-1; Barbosa, J.N., Martins, M.C.L., Freitas, S.C., Goncalves, I.C., Aguas, A.P., Barbosa, M.A., Adhesion of human leucocytes on mixtures of hydroxyl- and methyl-terminated self-assembled monolayers: Effect of blood protein adsorption (2010) J Biomed Mater Res, 93 A, pp. 12-19; Sperling, C., Schweiss, R.B., Streller, U., Werner, C., In vitro hemocompatibility of self-assembled monolayers displaying various functional groups (2005) Biomaterials, 26, pp. 6547-6557; Toda, M., Kitazawa, T., Hirata, I., Hirano, Y., Iwata, H., Complement activation on surfaces carrying amino groups (2008) Biomaterials, 29 (4), pp. 407-417. , DOI 10.1016/j.biomaterials.2007.10.005, PII S014296120700796X
Keywords: article; Blood Platelets; Cell Communication; Cell Shape; Ethylene Glycol; heparin; heparin binding protein; Humans; hydrophobicity; Imidazoles; Immobilized Proteins; leucine; leukocyte; leukocyte adherence; Leukocytes; methyl group; nanomaterial; plasma; Platelet Adhesiveness; Platelets; Polyethylene Glycols; polylysine; polypeptide; priority journal; Proteins; self assembled monolayer; Self-assembled monolayers; static electricity; Surface charge; Surface Properties; Tetra; thrombocyte; thrombocyte adhesion

Knowledge of adverse neonatal outcome alters clinicians' interpretation of the intrapartum cardiotocograph - Ayres-de-Campos, D.; Arteiro, D.; Costa-Santos, C.; Bernardes, J. (BJOG: An International Journal of Obstetrics and GynaecologyBJOG Int. J. Obstet. Gynaecol., 2011)
Objective: To evaluate the impact of knowledge of neonatal outcome on clinicians' interpretation of the intrapartum cardiotocograph (CTG). Design: Prospective evaluation of pre-recorded cases. Setting: Five maternity hospitals. Population: From a database of intrapartum CTGs acquired with a scalp electrode in singleton near-term fetuses, 20 tracings were sequentially selected from cases with newborn umbilical artery pH < 7.05 and 20 from cases with pH > 7.20. Methods: Five experienced obstetricians practising in different maternity hospitals were asked to analyse the 40 tracings individually, according to the International Federation of Gynaecology and Obstetrics guidelines. In a first round, clinicians were given no information on neonatal outcome. In a second round, carried out 2 months later, clinicians were asked to analyse the same tracings, but the order was randomly altered and information on the newborn's arterial pH was provided. Clinicians were not informed of the purpose of the study or whether the tracings were the same. Main outcome measures: The incidence of individual fetal heart rate feature identification and tracing classification, before and after neonatal outcome was made available. Results: In the group with pH < 7.05, repetitive decelerations and reduced variability were more common in the second round (P < 0.001 and P = 0.001, respectively), as was a pathological classification (P = 0.002); variable decelerations were less common (P = 0.008). In the group with normal pH, less tracings in the second round had prolonged decelerations (P = 0.013) and no accelerations (P = 0.013), but more had pronounced decelerations (P = 0.031) and reduced variability (P = 0.007); there was a reduction in pathological classifications, but this difference failed to reach statistical significance (P = 0.051). Conclusions: A knowledge of adverse neonatal outcome leads to a more severe classification of the intrapartum CTG, which derives mainly from the evaluation of decelerations and variability. © 2011 The Authors BJOG An International Journal of Obstetrics and Gynaecology © 2011 RCOG.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: BIOGFdoi: 10.1111/j.1471-0528.2011.03003.xPubMed ID: 21609381Language of Original Document: EnglishCorrespondence Address: Ayres-de-Campos, D.; Departmento de Ginecologia e Obstetrícia, Faculdade de Medicina do Porto, 4200-309 Porto, Portugal; email: dcampos@med.up.ptReferences: (2006) Perinatal Mortality Surveillance 2004: England, Wales and Northern Ireland, , CEMACH - Centre for Maternal and Child Enquiries (previously Confidential Enquiries into Maternal and Child Health). London: CEMACH;(1997) CESDI - Confidential Enquiry into Stillbirths and Deaths in Infancy, , 4th Annual Report. London: CESDI; Wood, C., Renou, P., Oats, J., A controlled trial of fetal heart rate monitoring in a low-risk obstetric population (1981) American Journal of Obstetrics and Gynecology, 141 (5), pp. 527-534; MacDonald, D., Grant, A., Sheridan-Pereira, M., The Dublin randomized controlled trial of intrapartum fetal heart rate monitoring (1985) American Journal of Obstetrics and Gynecology, 152 (5), pp. 524-539; Shy, K.K., Luthy, D.A., Bennett, F.C., Whitfield, M., Larson, E.B., Van Belle, G., Hughes, J.P., Stenchever, M.A., Effects of electronic fetal-heart-rate monitoring, as compared with periodic auscultation, on the neurologic development of premature infants (1990) New England Journal of Medicine, 322 (9), pp. 588-593; Dillner, L., Babies' deaths linked to suboptimal care (1995) Br Med J, 310, p. 757; Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310; Palomaki, O., Luukkaala, T., Luoto, R., Tuimala, R., Intrapartum cardiotocography - The dilemma of interpretational variation (2006) Journal of Perinatal Medicine, 34 (4), pp. 298-302. , DOI 10.1515/JPM.2006.057, PII JPME344298; Westerhuis, M., Van Horen, E., Kwee, A., Van Der Tweel, I., Visser, G., Moons, K., Inter- and intra-observer agreement of intrapartum ST analysis of the fetal electrocardiogram in women monitored by STAN (2009) BJOG, 116, pp. 545-551; Caplan, R.A., Posner, K.L., Cheney, F.W., Effect of outcome on physician judgment of appropriateness of care (1991) J Am Med Assoc, 265, pp. 1957-1960; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring (1987) Int J Gynecol Obstet, 25, pp. 159-167. , FIGO News; Amer-Wahlin, I., Hellsten, C., Noren, H., Hagberg, H., Herbst, A., Kjellmer, I., Lilja, H., Marsal, K., Cardiotocography only versus cardiotocography plus ST analysis of fetal electrocardiogram for intrapartum fetal monitoring: A Swedish randomised controlled trial (2001) Lancet, 358 (9281), pp. 534-538. , DOI 10.1016/S0140-6736(01)05703-8; Westgate, J., Garibaldi, J.M., Greene, K.R., Umbilical cord blood gas analysis at delivery: A time for quality data (1994) British Journal of Obstetrics and Gynaecology, 101 (12), pp. 1054-1063; Figueras, F., Albela, S., Bonino, S., Palacio, M., Barrau, E., Hernandez, S., Casellas, C., Cararach, V., Visual analysis of antepartum fetal heart rate tracings: Inter- and intra-observer agreement and impact of knowledge of neonatal outcome (2005) Journal of Perinatal Medicine, 33 (3), pp. 241-245. , http://www.extenza-eps.com/extenza/loadPDF?objectIDValue=64432, DOI 10.1515/JPM.2005.044; Zain, H.A., Wright, J.W., Parrish, G.E., Diehl, S.J., Interpreting the fetal heart rate tracing: Effect of knowledge of neonatal outcome (1998) Journal of Reproductive Medicine for the Obstetrician and Gynecologist, 43 (4), pp. 367-370; Almström, H., Axelsson, O., Ekman, G., Ingemarsson, I., Maesel, A., Arström, K., Umbilical artery velocimetry may influence clinical interpretation of intrapartum cardiotocograms (1995) Acta Obstet Gynecol Scand, 74, pp. 526-529; Spencer, J.A.D., Clinical overview of cardiotocography (1993) British Journal of Obstetrics and Gynaecology, Supplement, 100 (9), pp. 4-7; Ayres-de-Campos, D., Bernardes, J., Early, variable and late decelerations: Can a consensus be reached in their identification? (1999) Int J Gynecol Obstet, 65, pp. 305-306; Capstick, J.B., Edwards, P.J., Trends in obstetric malpractice claims (1990) Lancet, 336 (8720), pp. 931-932. , DOI 10.1016/0140-6736(90)92291-O; Symonds, E.M., Litigation and the cardiotocogram (1993) British Journal of Obstetrics and Gynaecology, Supplement, 100 (9), pp. 8-9; Williams, B., Arulkumaran, S., Cardiotocography and medicolegal issues (2004) Best Practice and Research: Clinical Obstetrics and Gynaecology, 18 (3), pp. 457-466. , DOI 10.1016/j.bpobgyn.2004.02.005, PII S1521693404000318
Keywords: adverse outcome; Agreement; article; bradycardia; Cardiotocography; clinical competence; Female; Fetal; Fetal hypoxia; Fetal monitoring; fetus heart rate; fetus outcome; health practitioner; Heart rate; Heart Rate, Fetal; human; Humans; Hydrogen-Ion Concentration; incidence; Infant, Newborn; intrapartum care; Labor, Obstetric; medical practice; pH; practice guideline; Practice Guidelines as Topic; Pregnancy; Pregnancy Outcome; priority journal; Prospective Studies; Questionnaires; Reference Standards; Reproducibility of Results; Research Design; Risk Factors; Sweden; tachycardia; umbilical artery

The limits of agreement and the intraclass correlation coefficient may be inconsistent in the interpretation of agreement - Costa-Santos, C.; Bernardes, J.; Ayres-de-Campos, D.; Costa, A.; Costa, C. (Journal of Clinical EpidemiologyJ. Clin. Epidemiol., 2011)
Objective: To compare the interpretation of agreement in the prediction of neonatal outcome variables, using the limits of agreement (LA) and the intraclass correlation coefficient (ICC). Study Design and Setting: Three obstetricians were asked to predict neonatal outcomes independently based on the evaluation of intrapartum cardiotocographic tracings. Interobserver agreement was assessed with the LA and the ICC, and the results obtained were interpreted by six clinicians and six statisticians on a scale that established agreement as very poor, poor, fair, good, or very good. Results: Interpretation of the LA results was less consensual than the ICC results, with proportions of agreement of 0.36 (95% confidence interval [CI]: 0.28-0.44) vs. 0.63 (95% CI: 0.54-0.73), respectively. LA results suggested a fair to good agreement among obstetricians, whereas interpretation of ICC results suggested a poor to fair agreement. LA results were more plausible with reality, suggesting that obstetricians predicted neonatal outcomes better than randomly generated values, whereas it was not always the case with the ICC. Conclusions: LA and ICC can provide inconsistent results in agreement studies. Accordingly, in the absence of better strategies to assess agreement, both should be used for this purpose, but their results need to be interpreted with caution keeping their respective limitations in mind. © 2011 Elsevier Inc. All rights reserved.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JCEPEdoi: 10.1016/j.jclinepi.2009.11.010PubMed ID: 20189765Language of Original Document: EnglishCorrespondence Address: Costa-Santos, C.; Biostatistics and Medical Informatics Department, Faculty of Medicine, University of Porto, Al. Prof. Hernâni Monteiro, 4200-319 Porto, Portugal; email: csantos@med.up.ptReferences: De Vet, H., Observer reliability and agreement (1999) Encyclopedia of Biostatistics, pp. 3123-3127;Ayres-De-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in expert's classification of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310; Santos, C.C., Pereira, C.A., Bernardes, J., Agreement studies in obstetrics and gynaecology: Inappropriateness, controversies and consequences (2005) Br J Obstet Gynaecol, 112, pp. 667-669; Luiz, R.R., Szklo, M., More than one statistical strategy to assess agreement of quantitative measurements may usefully be reported (2003) J Clin Epidemiol, 56, pp. 963-967; Bland, J.M., Altman, D.G., Statistical methods for assessing two methods of clinical measurement (1986) Lancet, 1, pp. 307-310; Bartko, J.J., The intraclass correlation coefficient as a measure of reliability (1966) Psychol Rep, 19, pp. 3-11; Muller, R., Buttner, P., A critical discussion of intraclass correlation coefficients (1994) Stat Med, 13, pp. 2465-2476; Burdock, E., Fleiss, J.L., Hardesty, A.S., A new view of interobserver agreement (1963) Person Psychol, 16, pp. 373-384; Casey, B.M., McLntire, D.D., Leveno, K.J., The continuing value of the Apgar score for the assessment of newborn infants (2001) N Engl J Med, 344, pp. 467-471; Van De Riet, J.E., Vandenbussche, F.P., Le Cessie, S., Keirse, M.J., Newborn assessment and long-term adverse outcome: A systematic review (1999) Am J Obstet Gynecol, 180, pp. 1024-1029; Shrout, P.E., Fleiss, J.L., Intraclass correlations: Uses in assessing rater reliability (1979) Psychol Bull, 86, pp. 420-427; Fleiss, J.U., Davies, M., Measuring nominal scale agreement among many raters (1971) Psychol Bull, 76, pp. 378-382; Carpenter, J., Bithell, J., Bootstrap confidence intervals: When, which, what? A practical guide for medical statisticians (2000) Stat Med, 19, pp. 1141-1164; Landis, J.R., Koch, G.G., The measurement of observer agreement for categorical data (1977) Biometrics, 33, pp. 159-174
Keywords: Agreement; Apgar score; Cardiotocography; correlation coefficient; Female; Fetal Blood; human; Humans; Hydrogen-Ion Concentration; Infant, Newborn; intrapartum care; limit of agreement; newborn assessment; normal human; observer variation; Obstetrics; outcome variable; Pregnancy; Pregnancy Outcome; priority journal; reproducibility; Reproducibility of Results; review; statistical data interpretation; statistical parameters; Umbilical Arteries; Umbilical artery blood pH; umbilical cord blood

Low frame rate cell tracking: A Delaunay graph matching approach - Chen, Y.; Quelhas, P.; Campilho, A. (Proceedings - International Symposium on Biomedical ImagingIEEE Comput. Soc. Conf. Comput. Vis. Pattern Recogn., 2011)
Cell tracking is a fundamental problem for studying live cell dynamics. A novel approach for low frame rate cell tracking in fluorescent microscopy image is herein proposed. The method is based on sliding band filter detection and Delaunay triangulation sub-graph matching. With this approach we can track a large amount of small cells without their motion model and not relying on cell motion continuity between consecutive images. The effectiveness and robustness of the method were validated by visual inspection and on a ground truth dataset. © 2011 IEEE.
Conference code: 87101Export Date: 21 November 2012Source: ScopusArt. No.: 5872573doi: 10.1109/ISBI.2011.5872573Language of Original Document: EnglishCorrespondence Address: Chen, Y.; INEB - Instituto de Engenharia Biomédica, Rua do Campo Alegre, 823, 4150-180 Porto, PortugalReferences: Godinez, W.J., Lampe, M., Worz, S., Muller, B., Eils, R., Rohr, K., Tracking of virus particles in time-lapse fluorescence microscopy image sequences (2007) Proceedings of the IEEE International Symposium on Biomedical Imaging, pp. 256-259;Finch, A.W., Wilson, R.C., Hancock, E.R., Symbolic graph matching with the em algorithm (1998) Pattern Recognit, 31 (11), pp. 1777-1790. , Nov; Finch, M.A., Wilson, C.R., Hancock, R.E., Matching delaunay graphs (1997) Pattern Recognit, 30 (1), pp. 123-140. , Nov; Quelhas, P., Marcuzzo, M., Mendonça, A.M., Campilho, A., Cell nuclei and cytoplasm joint segmentation using the sliding band filter (2010) IEEE Transactions on Medical Imaging, 29, pp. 1463-1473; Fortune, S., A sweepline algorithm for voronoi diagram (1987) Algorithmica, 2, pp. 153-174; Khoo, K., Suganthan, P., Evaluation of genetic operators and solution representations for shape recognition by genetic algorithms (2002) Patt. Recognit. Lett., 23 (13), pp. 1589-1597; Caetano, T.S., Caelli, T., Schuurmans, D., Barone, D., Graphical models and point pattern matching (2006) IEEE Trans. on Pattern Analysis and Machine Intelligence, 28 (10), pp. 1646-1662. , Oct; Raveaux, R., Burie, J.-C., Ogier, J.-M., A graph matching method and a graph matching distance based on subgraph assignments (2010) Pattern Recognition Letters, 31, pp. 394-406; Marcuzzo, M., Quelhas, P., Campilho, A., Cell division detection on the arabidopsis thaliana root (2009) IbPRIA 2009, 5524, pp. 168-175. , LNCS Sponsors: Inst. Electr. Electron. Eng., Eng. Med. Biol. Soc. (IEEE EMBS); Inst. Electr. Electron. Eng., Signal Process. Soc. (IEEE SPS)
Keywords: Band filters; cell motion; Cell tracking; Cells; Consecutive images; Data sets; Delaunay graph; Delaunay graph matching; Delaunay triangulation; Fluorescent microscopy; Frame rate; Fundamental problem; Ground truth; Live cell; low frame rate tracking; Medical imaging; Motion models; small target tracking; Small targets; Target tracking; Visual inspection

Novel TiN x-based biosignal electrodes for electroencephalography - Fiedler, P.; Cunha, L.T.; Pedrosa, P.; Brodkorb, S.; Fonseca, C.; Vaz, F.; Haueisen, J. (Measurement Science and TechnologyMeas. Sci. Technol., 2011)
A composition, structural, morphological and electrochemical study of two titanium nitride (TiN x) thin films, sample A and sample B, obtained by dc reactive sputtering on titanium substrates was carried out in this paper. In order to assess their applicability to be used as dry electrodes, several EEG signal acquisition tests were performed using the TiN x electrodes and compared to signals acquired with conventional silver/silver-chloride (Ag/AgCl) electrodes. The two films displayed some compositional differences, as sample B was over-stoichiometric (x = 1.34, x = N/Ti atomic ratio) and sample A was close-stoichiometric (x = 0.94). XRD diffractograms showed that both samples developed a similar fcc crystalline structure (δ-TiN phase). XRD peak fitting showed that sample B (over-stoichiometric) has a more oriented structure (highly [1 1 1] textured), with larger grains. A columnar-type structure with pyramid-like shape at column's top was common to both TiN x films. This morphology, in addition to some columnar disaggregation, gives rise to a rather rough surface and porous structure. Electrochemical impedance spectroscopy results in artificial sweat showed that the electric properties of the samples remain unchanged, even after prolonged contact with sweat. The comparison of EEG signals, simultaneously recorded using the novel TiN x electrodes and conventional Ag/AgCl electrodes, showed very similar results. The root mean square deviation, which was computed for different electrode-electrolyte combinations and signal sequences of 5 s, was in the range of 4.5-9.4 νV and 6.7-20.4 νV for samples A and B, respectively. An additional test with two sets of Ag/AgCl electrodes revealed similar results, thus indicating most of the signal differences are related to the spatial distance of the compared electrodes as well as environmental noise. Therefore, our results lead to the conclusion that the novel TiN x electrodes show promising signal quality for application in EEG biosignal measurements. © 2011 IOP Publishing Ltd.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusArt. No.: 124007CODEN: MSTCEdoi: 10.1088/0957-0233/22/12/124007Language of Original Document: EnglishCorrespondence Address: Fiedler, P.; Institute of Biomedical Engineering and Informatics, Ilmenau University of Technology, Gustav-Kirchhoff-Str. 2, 98693 Ilmenau, Germany; email: patrique.fiedler@tu-ilmenau.deReferences: Teplan, M., Fundamentals of EEG measurement (2002) Meas. Sci. Rev., 2, p. 2. , 1-11;Fonseca, C., Silva Cunha, J.P., Martins, R.E., Ferreira, V.M., Marques De Sa, J.P., Barbosa, M.A., Martins Da Silva, A., A novel dry active electrode for EEG recording (2007) IEEE Transactions on Biomedical Engineering, 54 (1), pp. 162-165. , DOI 10.1109/TBME.2006.884649, 23; Cunha, L.T., Pedrosa, P., Tavares, C.J., Alves, E., Vaz, F., Fonseca, C., The role of composition, morphology and crystalline structure in the electrochemical behaviour of TiN x thin films for dry electrode sensor materials (2009) Electrochim. Acta, 55 (1), pp. 59-67; Dias, N.S., Carmo, A., Ferreira Da Silva, A., Mendes, P.M., Correia, J.H., New dry electrodes based on iridium oxide (IrO) for non-invasive biopotential recordings and stimulation (2010) Sensors Actuators, 164 (1-2), pp. 28-34; Green, R.A., Baek, S., Poole-Warren, L.A., Martens, P.J., Conducting polymer-hydrogels for medical electrode applications (2010) Sci. Technol. Adv. Mater., 11 (1), p. 014107; Harland, C.J., Clark, T.D., Prance, R.J., Remote detection of human electroencephalograms using ultrahigh input impedance electric potential sensors (2002) Appl. Phys. Lett., 81 (17), pp. 3284-3286; Von, E.N., Spinelli, E., Muravchik, C.H., Capacitive electrodes in electroencephalography (2006) Conf. Proc. IEEE Eng. Med. Biol. Soc., 1, pp. 1126-1129; Kingsley, S.A., Sriram, S., Pollick, A., Marsh, J., Photrode optical sensor for electrophysiological monitoring (2003) Aviat. Space Environ. Med., 74, pp. 1215-1216; Fernandes, M.S., Dias, N.S., Silva, A.F., Nunes, J.S., Lanceros-Mendez, S., Correia, J.H., Mendes, P.M., Hydrogel-based photonic sensor for a biopotential wearable recording system (2010) Biosens. Bioelectron., 26 (1), pp. 80-86; Searle, A., Kirkup, L., A direct comparison of wet, dry and insulating bioelectric recording electrodes (2000) Physiological Measurement, 21 (2), pp. 271-283. , DOI 10.1088/0967-3334/21/2/307, PII S0967333400090511; Merletti, R., The electrode-skin interface and optimal detection of bioelectric signals (2010) Physiol. Meas., 31; Piscanec, S., Ciacchi, L.C., Vesselli, E., Comelli, G., Sbaizero, O., Meriani, S., De Vita, A., Bioactivity of TiN-coated titanium implants (2004) Acta Mater., 52 (5), pp. 1237-1245; Vaz, F., Ferreira, J., Ribeiro, E., Rebouta, L., Lanceros-Mendez, S., Mendes, J.A., Alves, E., De Rijk, J., Influence of nitrogen content on the structural, mechanical and electrical properties of TiN thin films (2005) Surface and Coatings Technology, 191 (2-3), pp. 317-323. , DOI 10.1016/j.surfcoat.2004.01.033, PII S025789720400060X; Vaz, F., Machado, P., Rebouta, L., Cerqueira, P., Goudeau, Ph., Riviere, J.P., Alves, E., De Rijk, J., Mechanical characterization of reactively magnetron-sputtered TiN films (2003) Surface and Coatings Technology, 174-175, pp. 375-382. , DOI 10.1016/S0257-8972(03)00711-4; Klem, G.H., Lüders, H.O., Jasper, H.H., Elger, C., The ten-twenty electrode system of the International Federation. The International Federation of Clinical Neurophysiology (1999) Electroencephalogr. Clin. Neurophysiol. Suppl., 52, pp. 3-6; Huigen, E., Peper, A., Grimbergen, C.A., Investigation into the origin of the noise of surface electrodes (2002) Med. Biol. Eng. Comput., 40 (3), pp. 332-338; Scheer, H.J., Sander, T., Trahms, L., The influence of amplifier, interface and biological noise on signal quality in high-resolution EEG recordings (2006) Physiological Measurement, 27 (2), pp. 109-117. , DOI 10.1088/0967-3334/27/2/002, PII S0967333406050039; Mayorga Martinez, C.C., Madrid, R.E., Felice, C.J., Electrochemical and geometrical characterization of iridium oxide electrodes in stainless steel substrate (2008) Sensors Actuators, 133 (2), pp. 682-686; Haueisen, J., Leistritz, L., Susse, T., Curio, G., Witte, H., Identifying mutual information transfer in the brain with differential-algebraic modeling: Evidence for fast oscillatory coupling between cortical somatosensory areas 3b and 1 (2007) Neuroimage, 37 (1), pp. 130-135; Graichen, U., Witte, H., Haueisen, J., Analysis of induced components in electroencephalograms using a multiple correlation method (2009) Biomed. Eng. Online, 8
Keywords: bioelectric; biomedical electrodes; Chlorine compounds; dc magnetron sputtering; Electric properties; Electrochemical impedance spectroscopy; Electrochemical properties; Electrodes; electroencephalography; Electrophysiology; Signal processing; signals; Surface structure; Thin films; Tinning; Titanium; Titanium nitride; titanium nitride thin films

Observer reliability and agreement: Differences, difficulties, and controversies - Costa Santos, C.; Bernardes, J.; Ayres-de-Campos, D. (Journal of Clinical EpidemiologyJ. Clin. Epidemiol., 2011)
Keywords: consensus; correlation coefficient; letter; methodology; organization; priority journal; reliability; research; scientific literature; validity

Segmentation of ultrasound images of the carotid using RANSAC and cubic splines - Rocha, R.; Campilho, A.; Silva, J.; Azevedo, E.; Santos, R. (Computer Methods and Programs in BiomedicineComput. Methods Programs Biomed., 2011)
A new algorithm is proposed for the semi-automatic segmentation of the near-end and the far-end adventitia boundary of the common carotid artery in ultrasound images. It uses the random sample consensus method to estimate the most significant cubic splines fitting the edge map of a longitudinal section. The consensus of the geometric model (a spline) is evaluated through a new gain function, which integrates the responses to different discriminating features of the carotid boundary: the proximity of the geometric model to any edge or to valley shaped edges; the consistency between the orientation of the normal to the geometric model and the intensity gradient; and the distance to a rough estimate of the lumen boundary.A set of 50 longitudinal B-mode images of the common carotid and their manual segmentations performed by two medical experts were used to assess the performance of the method. The image set was taken from 25 different subjects, most of them having plaques of different classes (class II to class IV), sizes and shapes.The quantitative evaluation showed promising results, having detection errors similar to the ones observed in manual segmentations for 95% of the far-end boundaries and 73% of the near-end boundaries. © 2011 Elsevier Ireland Ltd.
Cited By (since 1996): 10Export Date: 21 November 2012Source: ScopusCODEN: CMPBEdoi: 10.1016/j.cmpb.2010.04.015PubMed ID: 20554343Language of Original Document: EnglishCorrespondence Address: Rocha, R.; INEB, Divisão de Sinal e Imagem, Campus FEUP, 4200-465 Porto, Portugal; email: rhr@isep.ipp.ptReferences: Baldassarre, D., Amato, M., Bondioli, A., Sirtori, C.R., Tremoli, E., Carotid artery intima-media thickness measured by ultrasonography in normal clinical practice correlates well with atherosclerosis risk factors (2000) Stroke, 31, pp. 2426-2430;O'Leary, D., Polak, J., Kronmal, R., Manolio, T., Burke, G.W.S., Carotid-artery intima and media thickness as a risk factor for myocardial infarction and stroke in older adults (1999) N. Engl. J. Med., 340, pp. 14-22; Hodis, H., Mack, W., LaBree, L., Selzer, R., Liu, C., Liu, C., Azen, S., The role of carotid arterial intima-media thickness in predicting clinical coronary events (1998) Ann. Intern. Med., 128 (4), pp. 262-269; Reneman, R.S., Meinders, J.M., Hoeks, A.P.G., Non-invasive ultrasound in arterial wall dynamics in humans: what have we learned and what remains to be solved (2005) Eur. Heart J., 26, pp. 960-966; Gee, A., Prager, R., Treece, G., Berman, L., Engineering a freehand 3D ultrasound system (2003) Pattern Recogn. Lett., 24 (4-5), pp. 757-777; Sonka, M., Liang, W., Stefancik, R., Stolpen, A., (2000), 2. , Handbook of Medical Imaging: Medical Image Processing and Analysis,SPIEGiannoglou, G.D., Chatzizisis, Y.S., Koutkias, V., Kompatsiaris, I., Papadogiorgaki, M., Mezaris, V., Parissi, E., Louridas, G.E., A novel active contour model for fully automated segmentation of intravascular ultrasound images: in vivo validation in human coronary arteries (2008) Comput. Biol. Med., 37 (9), pp. 1292-1302; Tsai, A., Yezzi, A.J., Tempany, C., Tucker, D., Fan, A., Grimson, W.E.L., Willsky, A.S., A shape-based approach to the segmentation of medical imagery using level sets (2003) IEEE Trans. Med. Imaging, 22 (2), pp. 137-154; Cremers, D., Kohlberger, T., Schnorr, C., Nonlinear shape statistics in Mumford-Shah based segmentation (2002) Proc. European Conf. on Computer Vision (ECCV'2002), vol. 2351, pp. 93-108; Cremers, D., Sochen, N., Schnorr, C., Towards recognition-based variational segmentation using shape priors and dynamic labeling (2003) Proc. European Conf. on Computer Vision (ECCV'2003), vol. 2695, pp. 388-400; Cremers, D., Osher, S., Soatto, S., Kernel density estimation and intrinsic alignment for knowledge-driven segmentation: teaching level sets to walk (2004) Pattern Recognit., 3175, pp. 36-44; Halenka, M., Noninvasive measurement of early atherosclerosis by high-resolution B-mode ultrasonography (1999) Acta-Universitatis Palackianae Olomucensis Facultatis Medicae, 142, pp. 7-12; Touboul, P.J., Prati, P., Scarabin, P.-Y., Adrai, V., Thibout, E., Ducimetiere, P., Use of monitoring software to improve the measurement of carotid wall thickness by B-mode imaging (1992) J. Hypertension, 10 (5), pp. 37-41; Gariepy, J., Massonneau, M., Levenson, J., Heudes, D., Simon, A., Evidence for in vivo carotid and femoral wall thickness in human hypertension (1993) J. Hypertension, 22 (1), pp. 111-118. , the Groupe de Prevention Cardio-vasculaire en Medecine du Travail; Selzer, R.H., Hodis, H.N., Kwong-Fu, H., Mack, W.J., Lee, P.L., Liu, C.R., Liu, C.H., Evaluation of computerized edge tracking for quantifying intima-media thickness of the common carotid artery from B-mode ultrasound images (1994) Atherosclerosis, 111, pp. 1-11; Gustavsson, T., Liang, Q., Wendelhag, I., Wikstrand, J., A dynamic programming procedure for automated ultrasonic measurement of the carotid artery (1994) Comput. Cardiol., pp. 297-300; Kozick, R.J., Detecting interfaces on ultrasound images of the carotid artery by dynamic programming (1996) SPIE, 2666, pp. 233-241; Gustavsson, T., Abu-Gharbieh, R., Hamarneh, G., Liang, Q., Implementation and comparison of four different boundary detection algorithms for quantitative ultrasonic measurements of the human carotid artery (1997) Comput. Cardiol., pp. 69-72; Detmer, P., Bashein, G., Martin, R., Matched filter identification of left-ventricle endocardial borders in transesophageal echocardiograms (1990) IEEE Trans. Med. Imaging, 9 (4), pp. 396-404; Liang, Q., Wendelhag, I., Wikstrand, J., Gustavsson, T., A multiscale dynamic programming procedure for boundary detection in ultrasound artery images (2000) IEEE Trans. Med. Imaging, 19 (2), pp. 127-142; Schmidt-Trucksass, A., Cheng, D., Sandrock, M., Schulte-Monting, J., Rauramaa, R., Huonker, M., Burkhardt, H., Computerized analysing system using the active contour in ultrasound measurement of carotid artery intima-media thickness (2001) Clin. Physiol., 5, pp. 561-569; Cheng, D., Schmidt-Trucksass, A., Cheng, K., Sandrock, M., Pu, Q., Burkhardt, H., (1999), pp. 452-457. , Automatic detection of the intimal and the adventitial layers of the common carotid artery wall in ultrasound B-mode images using snakes, in: Int. Conf. on Image Analysis and Processing, B. WernerCheng, D., Schmidt-Trucksass, A., Cheng, K., Burkhardt, H., Using snakes to detect the intimal and adventitial layers of the common carotid artery wall in sonographic images (2002) Comput. Methods Programs Biomed., 67, pp. 27-37; Kass, M., Witkin, A., Terzopoulos, D., Snakes: active contour models (1988) Int. J. Comput. Vis., pp. 321-331; Christodoulou, C.I., Pattichis, C.S., Pantziaris, M., Nicolaides, A., Texture based classification of atherosclerotic carotid plaques (2003) IEEE Trans. Med. Imaging, 22 (7), pp. 902-912; Barratt, D., Ariff, B., Humphries, K., Thom, S., Hughes, A., Reconstruction and quantification of the carotid artery bifurcation from 3-D ultrasound images (2004) IEEE Trans. Med. Imaging, 23 (5), pp. 567-583; Fischler, M.A., Bolles, R.C., Random sample consensus: a paradigm for model fitting with applications to image analysis and automated cartography (1981) Commun. ACM, 24 (6), pp. 381-395; Rossi, A.C., Brands, P.J., Hoeks, A.P.G., Automatic recognition of the common carotid artery in longitudinal ultrasound B-mode scans (2008) Med. Image Anal., 12, pp. 653-665; Zack, G.W., Rogers, W.E., Latt, S.A., Automatic measurement of sister chromatid exchange frequency (1977) J. Histochem. Cytochem., 25 (7), pp. 741-753; Tauber, C., (2005), Filtrage anisotrope robuste et segmentation par b-spline snake: application aux images échographiques, Ph.D. thesis, Institut National Polytechnique de Toulouse, ToulouseYu, Y., Acton, S., Speckle reducing anisotropic diffusion (2002) IEEE Trans. Image Process., 11 (11), pp. 1260-1270; Yu, Y., Acton, S., Edge detection in ultrasound imagery using the instantaneous coefficient of variation (2004) IEEE Trans. Image Process., 13 (12), pp. 1640-1655; Black, M.J., Sapiro, G., Marimont, D.H., Heeger, D., Robust anisotropic diffusion (1998) IEEE Trans. Image Process., 7 (3), pp. 421-432; Rudin, L., Osher, S., Fatemi, E., Nonlinear total variation based noise removal algorithms (1992) Proceedings of the 11th Annual Int. Conf. of the Center for Nonlinear Studies on Experimental Mathematics: Computational Issues in Nonlinear Science, pp. 259-268; Rudin, L., Osher, S., Total variation based image restoration with free local constraints (1994) Proceedings of IEEE Int. Conf. on Image Processing (ICIP'94), vol. 1, pp. 31-35; Canny, J., A computational approach to edge detection (1986) IEEE Trans. Pattern Anal. Mach. Intell., 8 (6), pp. 679-698; Guo, Z., Hall, R.W., Parallel thinning with two-subiteration algorithms (1989) Commun. ACM, 32 (3), pp. 359-373; Burden, R., Faires, J.D., (2000) Numerical Analysis, , Brooks Cole; Forsyth, D.A., Ponce, J., (2003) Computer Vision: A Modern Approach, , Prentice Hall; Marquina, A., Osher, S., Explicit algorithms for a new time dependent model based on level set motion for nonlinear deblurring and noise removal (2000) SIAM J. Sci. Comput., 22 (2), pp. 387-405; Chum, O., Matas, J., Kittler, J., (2003), 81, pp. 236-243. , Locally optimized RANSAC, in: Lecture Notes in Computer Science - Pattern Recognition, Springer Berlin/Heidelberg, Springer LNCSBland, J.M., Altman, D.G., Statistical methods for assessing agreement between two methods of clinical measurement (1986) Lancet, 1 (8476), pp. 307-310
Keywords: Algorithms; article; B scan; B-mode images; Carotid; carotid artery; Carotid Artery Diseases; Carotid Artery, Common; Class II; clinical article; Common carotid artery; Cubic spline; Detection error; echography; Edge map; Female; Gain function; Geometric models; Geometry; human; Humans; Image Interpretation, Computer-Assisted; image processing; Image segmentation; Image sets; Intensity gradients; Longitudinal section; male; Manual segmentation; mathematical model; Medical experts; Medical imaging; Non-linear smoothing; Pattern Recognition, Automated; quantitative analysis; Quantitative evaluation; random sample; Random sample consensus; RANSAC; Semi-automatic segmentation; Splines; Ultrasonic applications; Ultrasonics; Ultrasonography; Ultrasound image; Ultrasound images

Access to computerised analysis of intrapartum cardiotocographs improves clinicians' prediction of newborn umbilical artery blood pH - Costa, A.; Santos, C.; Ayres-de-Campos, D.; Costa, C.; Bernardes, J. (BJOG: An International Journal of Obstetrics and GynaecologyBJOG Int. J. Obstet. Gynaecol., 2010)
Objective To evaluate the impact of access to computerised cardiotocograph (CTG) analysis on reproducibility and accuracy of clinicians' predictions of umbilical artery blood pH (UAB pH) and 5-minute Apgar score. Design Prospective evaluation of pre-recorded cases. Setting A tertiary-care university hospital. Population From databases of intrapartum CTGs acquired in singleton term pregnancies, 204 tracings with low signal loss and short time interval to delivery were consecutively selected. Methods Tracings were randomly assigned to computer analysis by the Omniview-SisPorto 3.5 ® system (study group n = 104) or to no analysis (control group n = 100). Three experienced clinicians evaluated all tracing printouts independently and were asked to predict the newborns' UAB pH and 5-minute Apgar scores from them. Main outcome measures Interobserver agreement (measured by the intraclass correlation coefficient [ICC]) and accuracy in prediction of neonatal outcomes with 95% CI. Results Agreement on prediction of UAB pH was significantly higher in the study group (ICC = 0.70; 95% CI 0.61-0.77) than in the control group (ICC = 0.43; 95% CI 0.21-0.60), and a trend towards better agreement was also seen in estimation of 5-minute Apgar scores (ICC = 0.55; 95% CI 0.38-0.68 versus ICC = 0.43; 95% CI 0.25-0.57). Observers predicted UAB pH values correctly within a 0.10 margin in 70% of cases in the study group (95% CI 0.61-0.79) versus 46% in the control group (95% CI 0.35-0.56). They predicted 5-minute Apgar scores within a margin of one in 81% of cases in the study group (95% CI 0.73-0.88) and in 70% of cases in the control group (95% CI 0.61-0.79). Conclusions Prediction of UAB pH is more reproducible and accurate when clinicians have access to computerised analysis of CTGs. © RCOG 2010 BJOG An International Journal of Obstetrics and Gynaecology.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: BIOGFdoi: 10.1111/j.1471-0528.2010.02645.xPubMed ID: 20618316Language of Original Document: EnglishCorrespondence Address: Costa, A.; Departamento de Ginecologia e Obstetrícia, Faculdade de Medicina da Universidade Do Porto, Alameda Hernani Monteiro, 4200-319 Porto, Portugal; email: cosantonia@gmail.comReferences: Ayres-De-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-10;Donker, D.K., Van Geijn, H.P., Hasman, A., Interobserver variation in the assessment of fetal heart rate recordings (1993) Eur J Obstet Gynecol Reprod Biol, 52, pp. 21-8; Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-65; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-5; Ayres-De-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto ® 3.5 - A central fetal monitoring station with online alerts based on computerized cardiotocogram+ST event analysis (2008) J Perinat Med, 36, pp. 260-4; Costa, A., Ayres-De-Campos, D., Costa, F., Santos, C., Bernardes, J., Prediction of neonatal acidemia by computer analysis of fetal heart rate and ST event signals (2009) Am J Obstet Gynecol, 201, pp. 464e1-6. , Jun 17. [Epub ahead of print]; Westerhuis, M., Van Horen, E., Kwee, A., Van Dertweel, I., Visser, G., Moons, K., Inter- and intra-observer agreement of intrapartum ST analysis of the fetal electrocardiogram in women monitored by STAN (2009) BJOG, 116, pp. 545-51; Ayres-De-Campos, D., Bernardes, J., Marsalb, K., Nickelsen, C., Makarainend, L., Banfield, P., Can the reproducibility of fetal heart rate baseline estimation be improved? (2004) Eur J Obstet Gynecol Reprod Biol, 112, pp. 49-54; Huch, A., Huch, C., Rooth, G., Guidelines for blood sampling and measurement of pH and blood gas values in Obstetrics (1994) Eur J Obstet Gynecol Reprod Biol, 54, pp. 165-75; Umbilical artery blood acid-base analysis (1996) Int J Gynecol Obstet, 52, pp. 305-10. , ACOG technical bulletin; Westgate, J., Garibaldi, J.M., Greene, K.R., Umbilical cord blood gas analysis at delivery: A time for quality data (1994) Br J Obstet Gynaecol, 101, pp. 1054-63; Costa-Santos, C., Costa Pereira, A., Bernardes, J., Agreement studies in obstetrics and gynaecology: Inappropriateness, controversies and consequences (2005) BJOG, 112, pp. 667-9; Bland, J.M., Altman, D.G., Agreement between methods of measurement with multiple observations per individual (2007) J Biopharm Stat, 17, pp. 571-82; Chauhan, S.P., Klauser, C.K., Woodring, T.C., Sanderson, M., Magann, E.F., Morrison, J.C., Intrapartum nonreassuring fetal heart rate tracing and prediction of adverse outcomes: Interobserver variability (2008) Am J Obstet Gynecol, 199, pp. 623e1-e5; Nielsen, P.V., Stigsby, B., Nickelsen, C., Nim, J., The value of computer assessment compared with visual assessment (1988) Acta Obstet Gynecol Scand, 67, pp. 461-464
Keywords: access to information; Apgar score; arterial pH; article; Cardiotocography; clinical competence; computer analysis; computerised analysis; controlled study; delivery; Diagnosis, Computer-Assisted; diagnostic accuracy; Female; Fetal Blood; Fetal heart rate; Fetal monitoring; Gestational Age; human; Humans; Hydrogen-Ion Concentration; Infant, Newborn; male; neonatal acidaemia; Neonatology; newborn; observer variation; outcome assessment; prediction; Pregnancy; priority journal; Prospective Studies; prospective study; reproducibility; Umbilical Arteries; umbilical artery; university hospital

Assessment of Disagreement: A New Information-Based Approach - Costa-Santos, C.; Antunes, L.; Souto, A.; Bernardes, J. (Annals of EpidemiologyAnn. Epidemiol., 2010)
Purpose: Disagreement on the interpretation of diagnostic tests and clinical decisions remains an important problem in medicine. As no strategy to assess agreement seems to be fail-safe to compare the degree of agreement, or disagreement, we propose a new information-based approach to assess disagreement. Methods: The sum over all logarithms of possible outcomes of a variable is a valid measure of the amount of information contained in the variable. The proposed measure is based on the amount of information contained in the differences between two observations. This measure is normalized and satisfies the flowing properties: it is a metric, scaled invariant and it has differential weighting. Results: Two real examples and a simulation were used to illustrate the usefulness of the proposed measure to compare the degree of disagreement. Conclusions: Used as complement to the existing methods, we believe our approach can be useful to compare the degree of disagreement among different populations. © 2010 Elsevier Inc.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: ANNPEdoi: 10.1016/j.annepidem.2010.02.011Language of Original Document: EnglishCorrespondence Address: Costa-Santos, C.; Biostatistics and Medical Informatics Department, Faculty of Medicine, University of Porto, Al. Prof. Hernâni Monteiro, 4200-319 Porto, Portugal; email: csantos@med.up.ptReferences: Bland, M., (2000) An introduction to medical statistics, , Oxford University Press, Oxford;Costa Santos, C., Costa Pereira, A., Bernardes, J., Agreement studies in obstetrics and gynecology: inappropriateness, controversies and consequences (2005) Br J Obstet Gynaecol, 112, pp. 667-669; Gow, R.M., Barrowman, N.J., Lai, L., Moher, D., A review of five cardiology journals found that observer variability of measured variables was infrequently reported (2008) J Clin Epidemiol, 61, pp. 394-401; Luiz, R.R., Szklo, M., More than one statistical strategy to assess agreement of quantitative measurements may usefully be reported (2005) J Clin Epidemiol, 58, pp. 215-216; de Vet, H., Observer reliability and agreement (1999) Encyclopedia of Biostatistics, pp. 3123-3127. , Wiley, Chichester, P. Armitage, T. Colton (Eds.); Shrout, P.E., Fleiss, J.L., Intraclass correlation: uses in assessing rater reliability (1979) Psychol Bull, 88, pp. 420-428; Burdock, E.I., Fleiss, J.L., Hardesty, A.S., A new view of interobserver agreement (1963) Psychol Bull, 16, pp. 373-384; McGraw, K.O., Wong, S.P., Forming inferences about some intraclass correlation coefficients (1996) Psychol Methods, 1, pp. 30-46; Muller, R., Buttner, P., A critical discussion of intraclass correlation coefficients (1994) Stat Med, 13, pp. 2465-2476; Steiner, D.L., Norman, G.R., (2003) Health measurements scales. A practical guide to their development and use, , Oxford University Press, Oxford; Lee, D., Koh, D., Ong, C.N., Statistical evaluation of the agreement between two methods for measuring a quantitative variable (1989) Comput Biol Med, 19, pp. 61-70; Lin, L.K., A concordance correlation coefficient to evaluate reproducibility (1989) Biometrics, 45, pp. 255-268; Nickerson, C.A.E., A note on " A Concordance Correlation Coefficient to Evaluate Reproducibility" (1997) Biometrics, 53, pp. 1503-1507; Atkinson, G., Nevill, A., Comment on the " Use of Concordance Correlation to Assess the Agreement between Two Variables" (1997) Biometrics, 53, pp. 775-777; Bland, J.M., Altman, D.G., Statistical methods for assessing two methods of clinical measurement (1986) Lancet, 1, pp. 307-310; Luiz, R.R., Costa, A.J., Kale, P.L., Werneck, G.L., Assessment of agreement of a quantitative variable: a new graphical approach (2003) J Clin Epidemiol, 56, pp. 963-967; Monti, K.L., Folded empirical distribution function curves-mountain plots (1995) Am Stat, 33, pp. 525-527; Shannon, I., A mathematical theory of communication (1948) Bell System Tech J, 27, pp. 379-423. , 623-656; Bland, J.M., Altaman, D.G., Measuring agreement in method comparison studies (1999) Stat Methods Med Res, 8, pp. 135-160
Keywords: analysis of variance; Apgar score; article; Blood Pressure Determination; blood pressure measurement; correlation coefficient; human; Humans; information science; Information Theory; intermethod comparison; mathematical computing; measurement error; medical research; metric system; Models, Statistical; observer variation; priority journal; probability; process model; reliability; Reproducibility of Results; scale up; standard; Statistical analysis; statistical model; statistics; Statistics as Topic; systolic blood pressure; validity; variance

Cell nuclei and cytoplasm joint segmentation using the sliding band filter - Quelhas, P.; Marcuzzo, M.; Mendonça, A.M.; Campilho, A. (IEEE Transactions on Medical ImagingIEEE Trans. Med. Imaging, 2010)
Microscopy cell image analysis is a fundamental tool for biological research. In particular, multivariate fluorescence microscopy is used to observe different aspects of cells in cultures. It is still common practice to perform analysis tasks by visual inspection of individual cells which is time consuming, exhausting and prone to induce subjective bias. This makes automatic cell image analysis essential for large scale, objective studies of cell cultures. Traditionally the task of automatic cell analysis is approached through the use of image segmentation methods for extraction of cells' locations and shapes. Image segmentation, although fundamental, is neither an easy task in computer vision nor is it robust to image quality changes. This makes image segmentation for cell detection semi-automated requiring frequent tuning of parameters. We introduce a new approach for cell detection and shape estimation in multivariate images based on the sliding band filter (SBF). This filter's design makes it adequate to detect overall convex shapes and as such it performs well for cell detection. Furthermore, the parameters involved are intuitive as they are directly related to the expected cell size. Using the SBF filter we detect cells' nucleus and cytoplasm location and shapes. Based on the assumption that each cell has the same approximate shape center in both nuclei and cytoplasm fluorescence channels, we guide cytoplasm shape estimation by the nuclear detections improving performance and reducing errors. Then we validate cell detection by gathering evidence from nuclei and cytoplasm channels. Additionally, we include overlap correction and shape regularization steps which further improve the estimated cell shapes. The approach is evaluated using two datasets with different types of data: a 20 images benchmark set of simulated cell culture images, containing 1000 simulated cells; a 16 images Drosophila melanogaster Kc167 dataset containing 1255 cells, stained for DNA and actin. Both image datasets present a difficult problem due to the high variability of cell shapes and frequent cluster overlap between cells. On the Drosophila dataset our approach achieved a precision/recall of 95%/69% and 82%/90% for nuclei and cytoplasm detection respectively and an overall accuracy of 76%. © 2010 IEEE.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusArt. No.: 5477157CODEN: ITMIDdoi: 10.1109/TMI.2010.2048253Language of Original Document: EnglishCorrespondence Address: Quelhas, P.; Instituto de Engenharia Biomédica (INEB), 4200-465 Porto, Portugal; email: pedro.quelhas@gmail.comChemicals/CAS: DNA, 9007-49-2; Actins; DNA, 9007-49-2References: Bleau, A., Leon, L., Watershed-based segmentation and region merging (2000) Comput. Vis. Image Understand., 77 (3), pp. 317-370;Clocksin, W., Automatic segmentation of overlapping nuclei with high background variation using robust estimation and flexible contour models (2003) Proc. 12th Int. Conf. Image Anal. Process., pp. 682-687; Cloppet, F., Boucher, A., Segmentation of overlapping/aggregating nuclei cells in biological images (2008) Proc. 19th Int. Conf. Pattern Recognit. (ICPR 2008), pp. 1-4; Danek, O., Matula, P., De Solorzano, C.O., Munoz-Barrutia, A., Maska, M., Kozubek, M., Segmentation of touching cell nuclei using a two-stage graph cut model (2009) LNCS, 5575, pp. 410-419. , Proc. SCIA; Fok, Y., Chan, J., Chin, R., Automated analysis of nerve-cell images using active contour models (1996) IEEE Trans. Med. Imag., 15 (3), pp. 353-368. , Jun; Harder, N., M-Bermudez, F., Godinez, W., Ellenberg, J., Eils, R., Rohr, K., Automated analysis of mitotic cell nuclei in 3-D fluorescence microscopy image sequences (2008) Workshop Bio-Image Inf.: Biol. Imag., Comput. Vis. Data Mining, pp. 17-18. , Santa Barbara, CA; Hill, A., Lapan, P., Li, Y., Haney, S., Impact of image segmentation on high-content screening data quality for sk-br-3 cells (2007) BMC Bioin-formatics, 8 (340), pp. 1-13; Hu, M., Ping, X., Ding, Y., A new active contour model and its application on cell segmentation (2004) 2004 8th International Conference on Control, Automation, Robotics and Vision (ICARCV), 2, pp. 1104-1107. , TuA7.09 - P0673, 2004 8th International Conference on Control, Automation, Robotics and Vision (ICARCV); Jones, T.R., Carpenter, A., Golland, P., Voronoi-based segmentation of cells on image manifolds (2005) ICCV Workshop Comput. Vis. Biomed. Image Appl. (CVBIA), pp. 535-543; Klemencic, A., Kovacic, S., Pernus, F., Automated segmentation of muscle fiber images using active contour models (1998) Cytometry, 32, pp. 317-326; Kobatake, H., Hashimoto, S., Convergence index filter for vector fields (1999) IEEE Trans. Image Process., 8 (8), pp. 1029-1038. , Aug; Lehmussola, A., Ruusuvuori, P., Selinummi, J., Huttunen, H., Yli-Harja, O., Computational framework for simulating fluorescence microscope images with cell populations (2007) IEEE Trans. Med. Imag., 26 (7), pp. 1010-1016. , Jul; Luc, V., Soille, P., Watersheds in digital spaces: An efficient algorithm based on immersion simulations (1991) IEEE Trans. Pattern Anal. Mach. Intell., 13 (6), pp. 583-598. , Jun; Marcuzzo, M., Guichard, T., Quelhas, P., Mendonça, A.M., Campilho, A., Cell division detection on the arabidopsis thaliana root (2009) LNCS, 5524, pp. 168-175. , Proceedings of IbPRIA. New York: Springer; Marcuzzo, M., Quelhas, P., Mendonça, A.M., Campilho, A., Evaluation of symmetry enhanced sliding band filter for plant cell nuclei detection in low contrast noisy fluorescent images (2009) LNCS, 5627, pp. 824-831. , Proceedings of ICIAR. New York: Springer; Moore, P., Molloy, D., A survey of computer-based deformable models (2007) Int. Mach. Vis. Image Process. Conf. (IMVIP), pp. 55-66; Otsu, N., A threshold selection method from gray-level histograms (1979) IEEE Tran. Syst., Man, Cybern., 9 (1), pp. 62-66. , Jan; Pereira, C.S., Fernandes, H., Mendonça, A.M., Campilho, A., Detection of lung nodule candidates in chest radiographs (2007) LNCS, 4478, pp. 170-177; Pereira, C.S., Mendonça, A.M., Campilho, A., Evaluation of contrast enhancement filters for lung nodule detection Proceedings of ICIAR. New York: Springer, 4633, pp. 878-888; Quelhas, P., Marcuzzo, M., Oliveira, M.J., Mendonça, A.M., Campilho, A., Cancer cell detection and invasion depth estimation in brightfield images (2009) Proc. 20th Br. Mach. Vis. Conf. (BMVC), , London, U.K; Ruusuvuori, P., Lehmussola, A., Selinummi, J., Rajala, T., Huttunen, H., Yli-Harja, O., Benchmark set of synthetic images for validating cell image analysis algorithms (2008) Proc. 16th Eur. Signal Process. Conf., , Lausanne, Switzerland; Solorzano, C., Malladi, R., Lelievre, S., Lockett, S., Segmentation of nuclei and cells using membrane related protein markers (2001) J. Microscopy, 201, pp. 404-415; Tek, F.B., Dempster, A.G., Kale, I., (2006) Mathematical Morphology:40 Years on, 30, pp. 441-454. , New York: Springer; Wei, J., Hagihara, Y., Kobatake, H., Detection of rounded opacities on chest radiographs using convergence index filter (1999) Proc. Int. Conf. Image Anal. Process., pp. 757-761; Xiong, G., Zhou, X., Ji, L., Bradley, P., Perrimon, N., Wong, S., Segmentation of drosophila RNAI fluorescence images using level sets (2006) Proc. IEEE Int. Conf. Image Process., pp. 73-76; Xiong, G., Zhou, X., Ji, L., Automated segmentation of drosophila RNAi fluorescence cellular images using deformable models (2006) IEEE Trans. Circ. Syst. i, 53 (11), pp. 2415-2424. , Nov; Yan, P., Zhou, X., Shah, M., Wong, S.T.C., Automatic segmentation of high-throughput RNAi fluorescent cellular images (2008) IEEE Trans. Inf. Technol. Biomed., 12 (1), pp. 109-117. , Jan; Yang, X., Li, H., Zhou, X., Nuclei segmentation using marker-controlled watershed, tracking using mean-shift, and kalman filter in time-lapse microscopy (2006) IEEE Trans. Circuits Syst., 53 (11), pp. 2405-2414. , Nov
Keywords: actin; Actins; animal; Animals; article; Band filters; Biological research; cell aggregation; Cell analysis; Cell culture; Cell detection; Cell images; cell nucleus; Cell segmentation; Cell Shape; Cell shapes; Cell size; Cells; chemistry; Computer vision; Convergence filters; Convex shapes; cytoplasm; Data sets; Databases, Factual; Digital image storage; DNA; Drosophila melanogaster; factual database; Fluorescence; Fluorescence microscopy; Fundamental tools; High variability; Image analysis; Image datasets; image processing; image processing in biology; Image Processing, Computer-Assisted; Image quality; Image segmentation; Imaging systems; Improving performance; Individual cells; Joint segmentation; Location; methodology; Microscopy, Fluorescence; Multivariate analysis; multivariate image processing; New approaches; Nuclear detection; Overlap correction; reproducibility; Reproducibility of Results; Semi-automated; Shape estimation; Shape regularization; ultrastructure; Visual communication; Visual inspection

Characterization of polymeric solutions as injectable vehicles for hydroxyapatite microspheres - Oliveira, S.M.; Almeida, I.F.; Costa, P.C.; Barrias, C.C.; Ferreira, M.R.P.; Bahia, M.F.; Barbosa, M.A. (AAPS PharmSciTechAAPS PharmSciTech, 2010)
A polymeric solution and a reinforcement phase can work as an injectable material to fill up bone defects. However, the properties of the solution should be suitable to enable the transport of that extra phase. Additionally, the use of biocompatible materials is a requirement for tissue regeneration. Thus, we intended to optimize a biocompatible polymeric solution able to carry hydroxyapatite microspheres into bone defects using an orthopedic injectable device. To achieve that goal, polymers usually regarded as biocompatible were selected, namely sodium carboxymethylcellulose, hydroxypropylmethylcellulose, and Na-alginate (ALG). The rheological properties of the polymeric solutions at different concentrations were assessed by viscosimetry before and after moist heat sterilization. In order to correlate rheological properties with injectability, solutions were tested using an orthopedic device applied for minimal invasive surgeries. Among the three polymers, ALG solutions presented the most suitable properties for our goal and a non-sterile ALG 6% solution was successfully used to perform preliminary injection tests of hydroxyapatite microspheres. Sterile ALG 7.25% solution was found to closely match non-sterile ALG 6% properties and it was selected as the optimal vehicle. Finally, sterile ALG 7.25% physical stability was studied at different temperatures over a 3-month period. It was observed that its rheological properties presented minor changes when stored at 25°C or at 4°C. © 2010 American Association of Pharmaceutical Scientists.
Cited By (since 1996): 1Export Date: 21 November 2012Source: Scopusdoi: 10.1208/s12249-010-9447-3PubMed ID: 20490958Language of Original Document: EnglishCorrespondence Address: Oliveira, S. M.; Dep. de Eng. Mecânica e Gestão Industrial, Escola Superior de Tecnologia e Gestão de Viseu, Campus Politécnico de Repeses, 3504-510, Viseu, Portugal; email: soliveira@estv.ipv.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; carboxymethylcellulose, 8050-38-2, 9000-11-7, 9004-32-4, 9050-04-8; hydroxyapatite, 1306-06-5, 51198-94-8; hydroxypropylmethylcellulose, 9004-65-3; Biocompatible Materials; Capsules; Durapatite, 1306-06-5; Excipients; Polymers; Solutions; VehiclesReferences: Verlaan, J.J., Oner, F.C., Dhert, W.J., Anterior spinal column augmentation with injectable bone cements (2006) Biomat, 27 (3), pp. 290-301;Chenite, A., Chaput, C., Wang, D., Combes, C., Buschmann, M.D., Hoemann, C.D., Novel injectable neutral solutions of chitosan form biodegradable gels in situ (2000) Biomat, 21 (21), pp. 2155-2161; Hoemann, C.D., Sun, J., Legare, A., McKee, M.D., Buschmann, M.D., Tissue engineering of cartilage using an injectable and adhesive chitosan-based cell-delivery vehicle (2005) Osteoarthritis Cart., 13 (4), pp. 318-329; Balakrishnan, B., Jayakrishnan, A., Self-cross-linking biopolymers as injectable in situ forming biodegradable scaffolds (2005) Biomat, 26 (18), pp. 3941-3951; Shu, X.Z., Ghosh, K., Liu, Y., Palumbo, F.S., Luo, Y., Clark, R.A., Attachment and spreading of fibroblasts on an RGD peptidemodified injectable hyaluronan hydrogel (2004) J. Biomed. Mater. Res., 68 A (2), pp. 365-375; Shu, X.Z., Ahmad, S., Liu, Y., Prestwich, G.D., Synthesis and evaluation of injectable, in situ crosslinkable synthetic extracellular matrices for tissue engineering (2006) J. Biomed. Mater. Res. A, 79 (4), pp. 902-912; Weiss, P., Gauthier, O., Bouler, J.-M., Grimandi, G., Daculsi, G., Injectable bone substitute using a hydrophilic polymer (1999) Bone, 25 (SUPPL. 1), pp. 67S-70S. , DOI 10.1016/S8756-3282(99)00146-5, PII S8756328299001465; Trojani, C., Weiss, P., Michiels, J.F., Vinatier, C., Guicheux, J., Daculsi, G., Three-dimensional culture and differentiation of human osteogenic cells in an injectable hydroxypropylmethylcellulose hydrogel (2005) Biomat, 26 (27), pp. 5509-5517; Virto, M.R., Frutos, P., Torrado, S., Frutos, G., Gentamicin release from modified acrylic bone cements with lactose and hydroxypropylmethylcellulose (2003) Biomat, 24 (1), pp. 79-87; Bodic, F., Amouriq, Y., Gayet-Delacroix, M., Gauthier, O., Bouler, J.-M., Daculsi, G., Méthode nom invasive d'evaluation d'un substitut osseux injectable/Non-invasive evaluation of an injectable bone substitute (2002) C R Biologies, 325, pp. 345-353; Andrews, G.P., Gorman, S.P., Jones, D.S., Rheological characterisation of primary and binary interactive bioadhesive gels composed of cellulose derivatives designed as ophthalmic viscosurgical devices (2005) Biomat, 26 (5), pp. 571-580; He, S., Yaszemski, M.J., Yasko, A.W., Engel, P.S., Mikos, A.G., Injectable biodegradable polymer composites based on poly (propylene fumarate) crosslinked with poly (ethylene glycol) dimethacrylate (2000) Biomat, 21 (23), pp. 2389-2394; Temenoff, J.S., Mikos, A.G., Injectable biodegradable materials for orthopedic tissue engineering (2000) Biomat, 21 (23), pp. 2405-2412; Iooss, P., Le Ray, A.M., Grimandi, G., Daculsi, G., Merle, C., A new injectable bone substitute combining poly (epsilon-caprolactone) microparticles with biphasic calcium phosphate granules (2001) Biomat, 22 (20), pp. 2785-2794; Uda, H., Sugawara, Y., Nakasu, M., Experimental studies on hydroxyapatite powder-carboxymethyl chitin composite: Injectable material for bone augmentation (2006) J. Plast. Reconstr. Aesthet. Surg., 59 (2), pp. 188-196; Carrodeguas, R.G., Lasa, B.V., Barrio, J.S.D., Injectable acrylic bone cements for vertebroplasty with improved properties (2004) J. Biomed. Mater. Res. B-Appl. Biomat., 68 (1), pp. 94-104; Oliveira, S.M., Barrias, C.C., Ribeiro, C.C., Almeida, I.F., Bahia, M.F., Barbosa, M.A., Morphology and mechanical properties of injectable ceramic microspheres (2009) Key Engineering Mat., 396-398, pp. 691-694; Barrias, C.C., Ribeiro, C.C., Barbosa, M.A., Adhesion and proliferation of human osteoblastic cells seeded on injectable hydroxyapatite microspheres (2004) Key Engineering Mat., 254-256, pp. 877-880; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Preparation and characterisation of calcium-phosphate porous microspheres with a uniform size for biomedical applications (2006) J. Mater. Sci. Mater. Med., 17 (5), pp. 455-463; Oliveira, S.M., Barrias, C.C., Almeida, I.F., Costa, P.C., Ferreira, M.P., Bahia, M.F., Injectability of a bone filler system based on hydroxyapatite microspheres and a vehicle with in situ gelforming ability (2008) J. Biomed. Mater. Res. B-Appl. Biomat., 87 B, pp. 49-58; Barnes, H.A., Hutton, J.F., Walters, K., (1998) An Introduction to Rheology, , Amsterdam: Elsevier Science; Leo, W.J., McLoughlin, A.J., Malone, D.M., Effects of sterilization treatments on some properties of alginate solutions and gels (1990) Biotech. Progress, 6 (1), pp. 51-53; Holme, H.K., Lindmo, K., Kristiansen, A., Smidsrød, O., Thermal depolymerization of alginate in the solid state (2003) Carbohydrate Polym., 54 (4), pp. 431-438; Bohner, M., Baroud, G., Injectability of calcium phosphate pastes (2005) Biomat, 26 (13), pp. 1553-1563; Hide, I.G., Gangi, A., Percutaneous vertebroplasty: History, technique and current perspectives (2004) Clin. Radiol., 59 (6), pp. 461-467; Lewis, G., Injectable bone cements for use in vertebroplasty and kyphoplasty: State-of-the-art review (2006) J. Biomed. Mat. Res. B-Appl. Biomat., 76 B (2), pp. 456-468; Baumann, A., Tauss, J., Baumann, G., Tomka, M., Hessinger, M., Tiesenhausen, K., Cement embolization into the vena cava and pulmonal arteries after vertebroplasty: Interdisciplinary management (2006) Europ J. Vasc. and End Surg., 31 (5), pp. 558-561; Mathis, J.M., Wong, W., Percutaneous vertebroplasty: Technical considerations (2003) J. Vasc. and Intervent Rad., 14 (8), pp. 953-960; Xu, H.H., Weir, M.D., Burguera, E.F., Fraser, A.M., Injectable and macroporous calcium phosphate cement scaffold (2006) Biomat, 27 (24), pp. 4279-4287; Gisep, A., Curtis, R., Hanni, M., Suhm, N., Augmentation of implant purchase with bone cements: An in vitro study of injectability and dough distribution (2006) J. Biomed. Mater. Res. B-Appl. Biomat., 77 (1), pp. 114-119; Krebs, J., Ferguson, S.J., Bohner, M., Baroud, G., Steffen, T., Heini, P.F., Clinical measurements of cement injection pressure during vertebroplasty (2005) Spine, 30 (5), pp. E118-E122; Draget, K.I., Skjak-Braek, G., Smidsrod, O., Alginate-based new materials (1997) Int. J. Biol. Macromol., 21 (1-2), pp. 47-55
Keywords: Alginate; alginic acid; article; Biocompatibility; Biocompatible Materials; Capsules; Carboxymethylcellulose; Drug Compounding; Durapatite; Excipients; hydroxyapatite; Hydroxypropylmethylcellulose; Injectability; injection; Injections; instrument sterilization; microsphere; Microspheres; minimally invasive surgery; molecular weight; orthopedic equipment; Polymers; priority journal; Solutions; Vehicles; viscometry

Characterization of two DLC coatings for joint prosthesis: The role of albumin on the tribological behavior - Carapeto, A.P.; Serro, A.P.; Nunes, B.M.F.; Martins, M.C.L.; Todorovic, S.; Duarte, M.T.; André, V.; Colaço, R.; Saramago, B. (Surface and Coatings TechnologySurf. Coat. Technol., 2010)
A commonly used strategy for reduction of wear and friction of the sliding surfaces in prosthetic pairs is the use of hard coatings. DLCs (diamond like carbons) offer a promising solution, because these coatings, already used in other biomedical applications, exhibit a unique combination of chemical inertness, mechanical and tribological properties. In the present work we investigated the role of albumin, the most abundant protein in the periprosthetic fluid, on the tribological behavior of two DLCs with different compositions, against ultra-high molecular weight polyethylene (UHMWPE). The results are compared with those obtained with uncoated stainless steel surfaces. We have characterized the coatings by atomic force microscopy, X-ray diffraction, Raman spectroscopy, ultramicrohardness and wettability measurements. The adsorption of albumin onto the surfaces was investigated by ellipsometry and using a quartz crystal microbalance. Both DLCs adsorb a larger amount of protein than stainless steel. The tribological tests were performed in microtribometer aiming for a deeper understanding of the tribological mechanisms which occur at the submicrometric contact scale. Results showed no significant differences between the tribological behavior of the two coatings. Under the tested conditions, the tribological performance does not improve significantly with the application of the DLCs. Moreover, the presence of albumin on the lubricant leads to higher friction of the polymer against all counterfaces. This effect was attributed to the formation of bridges between the two sliding surfaces by the denaturated protein. The significant differences in the adsorbed amounts of protein onto the stainless steel and the two types of DLCs did not affect considerably the tribological behavior of these materials. © 2010 Elsevier B.V.
Cited By (since 1996): 6Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.surfcoat.2010.04.022Language of Original Document: EnglishCorrespondence Address: Serro, A.P.; Centro de Química Estrutural, Complexo I, Instituto Superior Técnico, Av. Rovisco Pais, TU Lisbon, 1049-001 Lisboa, Portugal; email: anapaula.serro@ist.utl.ptReferences: Donnet, C., Erdemir, A., (2009), Springer Science & Business Media, New YorkGutensohn, K., Beythien, C., Bau, J., Fenner, T., Grewe, P., Koester, R., Padmanaban, K., Kuehnl, P., (2000) Thromb. Res., 99, p. 577;Cadosch, D., Chan, E., Gautschi, O.P., Simmen, H.-P., Filgueira, L., (2009) J. Orthop. Res., 27, p. 841; Gillespie, W.L., Frampton, C.M.A., Henderson, R.J., Ryan, P.M., (1988) J. Bone Joint Surg. Br., 70 (4), p. 539; Roy, R.K., Lee, K.-R., (2007) J. Biomed. Mater. Res. B Appl. Biomater., 83 B (1), p. 72; Alakoski, E., Tiainen, V.-M., Soininen, A., Konttinen, Y.T., (2008) Open Orthop. J., 2, p. 43; Fisher, J., Firkins, P., Reeves, E.A., Hailey, J.L., Isaac, G.H., (1995) Proc. Inst. Mech. Eng., 209, p. 263; Sheeja, D., Tay, B.K., Lau, S.P., Nung, L.N., (2001) Surf. Coat. Technol., p. 410; Tiainen, V.-M., (2001) Diamond Relat. Mater., 10 (2), p. 153; Oñate, J.I., Comin, M., Braceras, I., Garcia, A., Viviente, J.L., Brizuela, M., Garagorri, N., Alava, J.I., (2001) Surf. Coat. Technol., p. 1056; Shi, B., Ajayi, O.O., Fenske, G., Erdemir, A., Liang, H., (2003) Wear, 255, p. 1015; Lappalainen, R., Selenius, M., Anttila, A., Konttinen, Y.T., Santavirta, S.S., (2003) J. Appl. Biomater., 66 B, p. 410; Sheeja, D., Tay, B.K., Nung, L.N., (2004) Diamond Relat. Mater., 13, p. 184; Xu, T., Pruitt, L., (1999) J. Mater. Sci. Mater. Med., 10, p. 83; Lappalainen, R., Anttila, A., Heinonen, H., (1998) Clin. Orthop., 352, p. 118; Saikko, V., Ahlroos, T., Calonius, O., Keränen, J., (2001) Biomaterials, 22, p. 1507; Sheeja, D., Tay, B.K., Lau, S.P., Nung, L.N., (2001) Surf. Coat. Technol., 146, p. 410; Affatato, S., Frigo, M., Toni, A., (2000) J. Biomed. Mater. Res., 53 (3), p. 221; Scholes, S.C., Unsworth, A., Goldsmit, A.A.J., (2000) Phys. Med. Biol., 45, p. 3721; Ahlroos, T., Saikko, V., (1997) Wear, 211, p. 113; Fedel, M., Motta, A., Maniglio, D., (2009) J. Biomed. Mater. Res., 90 B (1), p. 338; Lousiniana, S., Logothetidis, S., Laskarakisa, A., Gioti, M., (2007) Biomolec. Eng., 24 (1), p. 107; Li, B.G., Kang, Y.Q., Yin, G.F., Zheng, C.Q., (2007) Key Eng. Mater. High-Performance Ceram. IV, p. 1814; Fenske, G.R., (2009) Presented to Chicago Section STLE meeting, , M; Eryilmaz, O.L., Erdemir, A., (2008) Surf. Coat. Technol., 203, p. 750; Gerwin, N., Hops, C., Lucke, A., (2006) Adv. Drug Deliv. Rev., 58 (2), p. 226; Visco, A.M., Torrisi, L., Campo, N., Emanuele, U., Trifiro, A., Trimarchi, M., (2009) J. Biomed. Mater. Res. B Appl. Biomater., 89 B, p. 55; Ferrari, A.C., Robertson, J., (2001) Phys. Rev. B, 64, p. 75414; Ferrari, A.C., Robertson, J., (2000) Phys. Rev. B, 61, p. 14095; Zhou, B., Prorok, B.C., Erdemir, A., Eryilmaz, O., (2007) Diamond Relat. Mater., 16, p. 342; Zhou, B., Prorok, B.C., Erdemir, A., Eryilmaz, O., (2006) Diamond Relat. Mater., 15, p. 2051; Beeman, D., Silverman, J., Lynds, R., Anderson, M.R., (1984) Phys. Rev. B., 30 (2), p. 870; Colaço, R., Serro, A.P., Eryilmaz, O.L., Erdemir, E., (2009) J. Phys. D Appl. Phys., 42, p. 85307; Paul, R., Das, S.N., Dalui, S., Gayen, R.N., Roy, R.K., Bhar, R., Pal, A.K., (2008) J. Phys. D Appl. Phys., 41 (5), p. 55309; Serro, A.P., Fernandes, A.C., Saramago, B., (1997) Colloids Surf. A Physicochem. Eng. Aspects, 125, p. 209; Serro, A.P., Degiampietro, K., Colaço, R., Saramago, B., (2010) Saramago, Adsorption of albumin and sodium hyaluronate on UHMWPE: A QCM-D and AFM study, Colloids and Surfaces B: Biointerfaces, 78, p. 1; de Feijter, J.A., Benjamins, J., Veer, F.A., (1978) Biopolymers, 17, p. 1759; Gispert, M.P., Serro, A.P., Colaço, R., Saramago, B., (2008) Surf. Int. Anal., 40 (12), p. 1529; Hook, F., Kasemo, B., Nylander, T., Fant, C., Sott, K., Elwing, H., (2001) Anal. Chem., 73 (24), p. 5796; Hook, F., Voros, J., Rodahl, M., Kurrat, R., Boni, P., Ramsden, J.J., Textor, M., Kasemo, B., (2002) Colloids Surf. B Biointerfaces, 24, p. 155; Colaço, R., Gispert, M.P., Serro, A.P., Saramago, B., (2007) Tribol. Lett., 26 (2), p. 119; Gispert, M.P., Serro, A.P., Colaço, R., Saramago, B., (2006) Wear, 260, p. 149; Serro, A.P., Completo, C., Colaço, R., Dos Santos, F., Lobato da Silva, C., Cabral, J.M.S., Araújo, H., Saramago, B., (2009) Surf. Coat. Technol., 203, p. 3701; Widmer, M.R., Heuberger, M., Vörös, J., Spencer, N.D., (2001) Tribol. Lett., 10, p. 111; Chen, X.M., Jin, Z.M., Fisher, J., (2008) Proc. Inst. Mech. Eng. Part J. Eng. Tribol., 222 (3), p. 513; Kumar, P., Oka, M., Ikeuchi, K., Shimizu, K., Yamamuro, T., Okumura, H., Kotoura, Y., (1991) J. Biomater. Mater. Res., 25, p. 813; Roba, M., Naka, M., Gautier, E., Spencer, N.D., Crockett, R., (2009) Biomaterials, 30, p. 2072; Karuppiah, K.S.K., Sundararajan, S., Xu, Z.-H., Li, X., (2006) Tribol. Lett., 22 (2), p. 181; Yang, C.-B., Fang, H.-W., Liu, H.-L., Chang, C.-H., Hsieh, M.-C., Lee, W.-M., Huang, H.-T., (2006) Chem. Phys. Lett., 431, p. 380; Fang, H.-W., Wang, H.-C., Tsai, T.-H., Tsai, W.-B., Hou, S.-Y., Liu, H.-L., Lee, W.-H., Huang, C.-H., (2008) J. Appl. Polym. Sci., 108, p. 2428; Zappone, B., Rosenberg, K.J., Israelachvili, J., (2007) Tribol. Lett., 26 (3), p. 191; Grill, A., (1997) Surf. Coat. Technol., (1-3), p. 507; Fontaine, J., Belin, M., Le Mogne, T., Grill, A., (2004) Tribol. Int., 37, p. 869; Sanchez-Lopez, J.C., Erdemir, A., Donnet, C., Rojas, T.C., (2003) Surf. Coat. Technol., 163, p. 444; Robertson, J., (2002) Mater. Sci. Eng., 37, p. 129
Keywords: Adsorbed amount; Adsorption; Albumin adsorption; Atomic force microscopy; Atomic spectroscopy; Biomedical applications; Chemical inertness; Corrosion resistant alloys; Diamond like carbon; DLC coatings; Friction; Hard coatings; Joint prostheses; Mechanical and tribological properties; Mechanical properties; Microtribology; Microtribometer; Nonmetallic matrix composites; Oxide minerals; Polyethylenes; Proteins; Quartz; Raman spectroscopy; Scanning electron microscopy; Sliding surface; Stainless steel; Stainless steel surface; Steel corrosion; Surfaces; Tribological behaviors; Tribological mechanism; Tribological performance; Tribological tests; Tribology; UHMW-PE; UHMWPE; Ultramicrohardness; Wear and friction; Wettability measurements; X ray diffraction

Comparison of a computer system evaluation of intrapartum cardiotocographic events and a consensus of clinicians. - Costa, M.A.; Ayres-de-Campos, D.; Machado, A.P.; Santos, C.C.; Bernardes, J. (Journal of perinatal medicineJ Perinat Med, 2010)
AIMS: To compare between computer analysis of intrapartum cardiotocography (CTG) features by the Omniview-SisPorto 3.5 and a consensus of clinicians. METHODS: Agreement study using 50 consecutively acquired tracings (206 h of signals) with >60 min duration, <10% signal loss and recorded in labor at term by internal fetal heart rate (FHR) monitoring. Tracings were divided into 10-min segments and independently analyzed by three experienced clinicians, in order to estimate the FHR baseline and identify periodic events. A consensus was reached using a three round Delphi procedure. Results were compared with the analysis provided by the Omniview-SisPorto 3.5 system. RESULTS: For baseline estimation, agreement between the computer and the consensus was high [intraclass correlation coefficient (ICC)=0.85; 95% confidence interval (CI) 0.46-0.93], with a mean difference of 3.7 bpm (limits of agreement -4.4-11.9 bpm), and 99% of differences under 15 bpm. A concordant identification was observed in 71% of accelerations (95% CI: 69%-73%), 68% of decelerations (95% CI: 66%-70%), and 87% of uterine contractions (95% CI: 85%-89%). CONCLUSIONS: A high agreement was observed between the Omniview-SisPorto 3.5 and a consensus of clinicians in evaluation of intrapartum CTG baseline, accelerations, decelerations and uterine contractions.
Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1515/JPM.2010.030PubMed ID: 20121542Language of Original Document: EnglishCorrespondence Address: Costa, M.A.email: cosantonia@gmail.com
Keywords: algorithm; Algorithms; article; Cardiotocography; comparative study; computer assisted diagnosis; Diagnosis, Computer-Assisted; Female; Fetal Heart; Fetal monitoring; fetus heart; fetus monitoring; human; Humans; instrumentation; methodology; physician; Physicians; physiology; Pregnancy

De novo expression of CD44 variants in sporadic and hereditary gastric cancer - Da Cunha, C.B.; Oliveira, C.; Wen, X.; Gomes, B.; Sousa, S.; Suriano, G.; Grellier, M.; Huntsman, D.G.; Carneiro, F.; Granja, P.L.; Seruca, R. (Laboratory InvestigationLab. Invest., 2010)
CD44 is the major ubiquitously expressed cell surface receptor for hyaluronate. The CD44 gene encodes several protein isoforms due to extensive alternative splicing and post-translational modifications. Some of these CD44 variable isoforms have been foreseen as key players in malignant transformation and their expression is highly restricted and highly specific, unlike the canonical CD44 standard isoform. In this study, we aimed at dissecting the mRNA splicing pattern of CD44 in normal stomach and gastric cancer (GC) cell lines (n9) using cloning and quantitative mRNA amplification assays. Moreover, we assessed the RNA levels and protein expression pattern of relevant splicing forms in distinct premalignant and malignant gastric lesions (sporadic (n43) and hereditary (n3) forms) using real-time RT-PCR and immunohistochemistry. We also explored the association of CD44 and E-cadherin expression by immunohistochemistry, as E-cadherin has a pivotal functional role in GC. We established the pattern of CD44 variant forms in normal stomach and gastric malignancy. We observed that although exon v6-containing isoforms were rarely expressed in normal gastric mucosa, they became increasingly expressed both in gastric premalignant (hyperplastic polyps, complete and incomplete intestinal metaplasia, low- and high-grade dysplasia) and malignant lesions (cell lines derived from GCs, primary sporadic GCs and hereditary diffuse GCs (HDGCs)). Moreover, we verified that whenever E-cadherin expression was absent, exon v6-containing CD44 isoforms were overexpressed. The lack of expression of CD44 isoforms containing exon v6 in the surface and foveolar epithelia of normal stomach and, its de novo expression in premalignant, as well as in sporadic and hereditary malignant lesions of the stomach, pinpoint CD44 v6-containg isoforms as potential biomarkers for early transformation of the gastric mucosa. Further, our results raise the hypothesis of using CD44v6 as a marker of early invasive intramucosal carcinoma in HDGC CDH1 mutation carriers that lack CDH1 expression in their tumors. © 2010 USCAP, Inc All rights reserved.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: LAINAdoi: 10.1038/labinvest.2010.155PubMed ID: 20856229Language of Original Document: EnglishCorrespondence Address: Da Cunha, C. B.; IPATIMUP, Institute of Molecular Pathology and Immunology, University of Porto, Rua Dr. Roberto Frias s/n, 4200-465 Porto, Portugal; email: rseruca@ipatimup.ptChemicals/CAS: uvomorulin, 112956-45-3; Antigens, CD44; CD44 protein, human; CD44v6 antigen; Cadherins; RNA, MessengerReferences: Aruffo, A., Stamenkovic, I., Melnick, M., CD44 is the principal cell surface receptor for hyaluronate (1990) Cell, 61, pp. 1303-1313;Screaton, G.R., Bell, M.V., Jackson, D.G., Genomic structure of DNA encoding the lymphocyte homing receptor CD44 reveals at least 12 alternatively spliced exons (1992) Proc Natl Acad Sci USA, 89, pp. 12160-12164; Ponta, H., Wainwright, D., Herrlich, P., Molecules in focus the CD44 protein family (1998) Int J Biochem Cell Biol, 30, pp. 299-305; Rudzki, Z., Jothy, S., CD44 and the adhesion of neoplastic cells (1997) Mol Pathol, 50, pp. 57-71; Shtivelman, E., Bishop, J.M., Expression of CD44 is repressed in neuroblastoma cells (1991) Mol Cell Biol, 11, pp. 5446-5453; De Marzo, A.M., Bradshaw, C., Sauvageot, J., CD44 and CD44v6 downregulation in clinical prostatic carcinoma: Relation to Gleason grade and cytoarchitecture (1998) Prostate, 34, pp. 162-168; Joensuu, H., Klemi, P.J., Toikkanen, S., Glycoprotein CD44 expression and its association with survival in breast cancer (1993) Am J Pathol, 143, pp. 867-874; Friedrichs, K., Kugler, G., Franke, F., CD44 isoforms in prognosis of breast cancer (1995) Lancet, 345, p. 1237; Kaufmann, M., Heider, K.H., Sinn, H.P., CD44 variant exon epitopes in primary breast cancer and length of survival (1995) Lancet, 345, pp. 615-619; Mulder, J.W., Kruyt, P.M., Sewnath, M., Colorectal cancer prognosis and expression of exon-v6-containing CD44 proteins (1994) Lancet, 344, pp. 1470-1472; Wielenga, V.J., Heider, K.H., Offerhaus, G.J., Expression of CD44 variant proteins in human colorectal cancer is related to tumor progression (1993) Cancer Res, 53, pp. 4754-4756; Terpe, H.J., Koopmann, R., Imhof, B.A., Expression of integrins and CD44 isoforms in non-Hodgkin's lymphomas: CD44 variant isoforms are preferentially expressed in high-grade malignant lymphomas (1994) J Pathol, 174, pp. 89-100; Takaishi, S., Okumura, T., Tu, S., Identification of gastric cancer stem cells using the cell surface marker CD44 (2009) Stem Cells, 27, pp. 1006-1020; Heider, K.-H., Dammrich, J., Skroch-Angel, P., Differential EXpression of CD44 splice variants in intestinal-and diffuse-type human gastric carcinomas and normal gastric mucosa (1993) Cancer Res, 53, pp. 4197-4203; Mayer, B., Jauch, K.W., Gunthert, U., De-novo expression of CD44 and survival in gastric cancer (1993) Lancet, 342, pp. 1019-1022; Muller, W., Schneiders, A., Heider, K.H., Expression and prognostic value of the CD44 splicing variants v5 and v6 in gastric cancer (1997) J Pathol, 183, pp. 222-227; Mirecka, J., Marx, D., Schauer, A., Immunohistochemical localization of CD44 variants 5 and 6 in human gastric mucosa and gastric cancer (1995) Anticancer Res, 15, pp. 1459-1465; Heider, K.H., Dammrich, J., Skroch-Angel, P., Differential expression of CD44 splice variants in intestinal-and diffuse-type human gastric carcinomas and normal gastric mucosa (1993) Cancer Res, 53, pp. 4197-4203; Hong, R.L., Lee, W.J., Shun, C.T., Expression of CD44 and its clinical implication in diffuse-type and intestinal-type gastric adenocarcinomas (1995) Oncology, 52, pp. 334-339; Ghaffarzadehgan, K., Jafarzadeh, M., Raziee, H.R., Expression of cell adhesion molecule CD44 in gastric adenocarcinoma and its prognostic importance (2008) World J Gastroenterol, 14, pp. 6376-6381; Carneiro, F., Huntsman, D.G., Smyrk, T.C., Model of the early development of diffuse gastric cancer in E-cadherin mutation carriers and its implications for patient screening (2004) J Pathol, 203, pp. 681-687; Suriano, G., Mulholland, D., De Wever, O., The intracellular E-cadherin germline mutation V832M lacks the ability to mediate cell-cell adhesion and to suppress invasion (2003) Oncogene, 22, pp. 5716-5719; Suriano, G., Oliveira, C., Ferreira, P., Identification of CDH1 germline missense mutations associated with functional inactivation of the E-cadherin protein in young gastric cancer probands (2003) Hum Mol Genet, 12, pp. 575-582; Suriano, G., Oliveira, M.J., Huntsman, D., E-cadherin germline missense mutations and cell phenotype: Evidence for the independence of cell invasion on the motile capabilities of the cells (2003) Hum Mol Genet, 12, pp. 3007-3016; Oliveira, C., Bordin, M.C., Grehan, N., Screening E-cadherin in gastric cancer families reveals germline mutations only in hereditary diffuse gastric cancer kindred (2002) Hum Mutat, 19, pp. 510-517; MacHado, J.C., Oliveira, C., Carvalho, R., E-cadherin gene (CDH1) promoter methylation as the second hit in sporadic diffuse gastric carcinoma (2001) Oncogene, 20, pp. 1525-1528; Huntsman, D.G., Carneiro, F., Lewis, F.R., Early gastric cancer in young, asymptomatic carriers of germ-line E-cadherin mutations (2001) N Engl J Med, 344, pp. 1904-1909; Carneiro, F., MacHado, J.C., Seruca, R., E-cadherin changes in gastric carcimona (1999) Histopathology, 35, pp. 477-478; Mateus, A.R., Simoes-Correia, J., Figueiredo, J., E-cadherin mutations and cell motility: A genotype-phenotype correlation (2009) Exp Cell Res, 315, pp. 1393-1402; Oliveira, C., Senz, J., Kaurah, P., Germline CDH1 deletions in hereditary diffuse gastric cancer families (2009) Hum Mol Genet, 18, pp. 1545-1555; Oliveira, C., Sousa, S., Pinheiro, H., Quantification of epigenetic and genetic second hits in CDH1 during hereditary diffuse gastric cancer syndrome progression (2009) Gastroenterology, 136, pp. 2137-2148; Lynch, H.T., Grady, W., Suriano, G., Gastric cancer: New genetic developments (2005) J Surg Oncol, 90, pp. 114-133. , discussion 133; Lauren, P., The two histological main types of gastric carcinoma: Diffuse and so-called intestinal-type carcinoma. An attempt at a histo-clinical classification (1965) Acta Pathol Microbiol Scand, 64, pp. 31-49; Filipe, M.I., Jass, J.R., Intestinal metaplasia subtypes and cancer risk (1986) Gastric Carcinoma, pp. 87-115. , Filipe MI, Jass JR (eds). Churchill Livingstone, London; Sato, S., Yokozaki, H., Yasui, W., Silencing of the CD44 gene by CpG methylation in a human gastric carcinoma cell line (1999) Jpn J Cancer Res, 90, pp. 485-489; Guilford, P.H.J., Harraway, J., McLeod, M., E-cadherin germline mutations in familial gastric cancer (1998) Nature, 26, p. 6674; Günthert, U., Hofmann, M., Rudy, W., A new variant of glycoprotein CD44 confers metastatic potential to rat carcinoma cells (1991) Cell, 65, pp. 13-24; Vr, O., Chen, L., Sleeman, J.P., CD44 is required for two consecutive steps in HGF/c-Met signaling (2002) Genes Dev, 16, pp. 3074-3086; Spk, D., Stefan, M., Wels, C., HGF-Promoted Motility in Primary Melanocytes Depends on CD44v6 Regulated via NF-kappa B, Egr-1, and C/EBP-beta (2010) J Investig Dermatol, 130, pp. 1893-1903; Mielgo, A., Van Driel, M., Bloem, A., A novel antiapoptotic mechanism based on interference of Fas signaling by CD44 variant isoforms (2006) Cell Death Differ, 13, pp. 465-477; Marhaba, R., Bourouba, M., Zoller, M., CD44v6 promotes proliferation by persisting activation of MAP kinases (2005) Cell Signal, 17, pp. 961-973; Bates, R.C., Edwards, N.S., Burns, G.F., A CD44 survival pathway triggers chemoresistance via lyn kinase and phosphoinositide 3-kinase/Akt in colon carcinoma cells (2001) Cancer Res, 61, pp. 5275-5283; Carvalho, R., Milne, A.N., Polak, M., A novel region of amplification at 11p12-13 in gastric cancer, revealed by representational difference analysis, is associated with overexpression of CD44v6, especially in early-onset gastric carcinomas (2006) Genes Chromosomes Cancer, 45, pp. 967-975; Heider, K.H., Hofmann, M., Hors, E., A human homologue of the rat metastasis-associated variant of CD44 is expressed in colorectal carcinomas and adenomatous polyps (1993) J Cell Biol, 120, pp. 227-233; Gulmann, C., Grace, A., Leader, M., CD44v6: A potential marker of malignant transformation in intestinal metaplasia of the stomach? An immunohistochemical study using tissue microarrays (2003) Eur J Gastroenterol Hepatol, 15, pp. 981-986; Wimmel, A., Kogan, E., Ramaswamy, A., Variant expression of CD44 in preneoplastic lesions of the lung (2001) Cancer, 92, pp. 1231-1236; Afify, A.M., Craig, S., Paulino, A.F., Expression of hyaluronic acid and its receptors, CD44s and CD44v6, in normal, hyperplastic, and neoplastic endometrium (2005) Ann Diagn Pathol, 9, pp. 312-318; Soon Cheol, H., Jae Yun, S., Jae Kwan, L., Significance of CD44v6 expression in gynecologic malignancies (2006) J Obstet Gynaecol Res, 32, pp. 379-386; Afify, A., Ma, M., Braggin, J., Expression of CD44s, CD44v6, and hyaluronan across the spectrum of normal-hyperplasia-carcinoma in breast (2008) Appl Immunohistochem Mol Morphol, 16, pp. 121-127; Judd, L.M., Andriga, A., Rubio, C.A., Gastric achlorhydria in H/K-ATPase-deficient (Atp4a(-/-)) mice causes severe hyperplasia, muco-cystic metaplasia and upregulation of growth factors (2005) J Gastroenterol Hepatol, 20, pp. 1266-1278; Liu, Y.J., Yan, P.S., Li, J., Expression and significance of CD44 s, CD44v6, and nm23 mRNA in human cancer (2005) World J Gastroenterol, 11, pp. 6601-6606; Polkowski, W.P., Skomra, D.G., Mielko, J., E-cadherin expression as predictive marker of proximal resection line involvement for advanced carcinoma of the gastric cardia (2004) E J Surg Oncol, 30, pp. 1084-1092; Seiter, S.A.R., Reber, S., Komitowski, D., Prevention of tumor metastasis formation by anti-variant CD44 (1993) J Experiment Med, 177, pp. 443-455; Reeder, J.A., Gotley, D.C., Walsh, M.D., Expression of ANTisense CD44 variant 6 inhibits colorectal tumor metastasis and tumor growth in a wound environment (1998) Cancer Res, 58, pp. 3719-3726; Nishii, T., Yashiro, M., Shinto, O., Cancer stem cell-like SP cells have a high adhesion ability to the peritoneum in gastric carcinoma (2009) Cancer Sci, 100, pp. 1397-1402; Carneiro, F., Huntsman, D.G., Smyrk, T.C., Model of the early development of diffuse gastric cancer in E-cadherin mutation carriers and its implications for patient screening (2004) J Pathol, 203, pp. 681-687; Pdp, P., Guilford, P., Caldas, C., The International Gastric Cancer Linkage C. Incidence of gastric cancer and breast cancer in CDH1 (E-cadherin) mutation carriers from hereditary diffuse gastric cancer families (2001) Gastroenterology, 121, pp. 1348-1353; Humar, B., Fukuzawa, R., Blair, V., Destabilized adhesion in the gastric proliferative zone and c-Src kinase activation mark the development of early diffuse gastric cancer (2007) Cancer Res, 67, pp. 2480-2489; Ferrari, M., Cancer nanotechnology: Opportunities and challenges (2005) Nat Rev Cancer, 5, pp. 161-171; Yww, W., Chen, Y., Huang, K., The investigation of polymer-siRNA nanoparticle for gene therapy of gastric cancer in vitro (2010) Int J Nanomed, 5, pp. 129-136
Keywords: Alternative Splicing; Antigens, CD44; article; Cadherins; CD44; CD44v6; CD44v6 antigen; CD44v7 antigen; Cell Line, Tumor; clinical article; controlled study; E-cadherin; familial cancer; Gastric Mucosa; Germ-Line Mutation; HDGC; Hermes antigen; human; human tissue; Humans; immunohistochemistry; intestine metaplasia; messenger RNA; Neoplasm Metastasis; priority journal; protein expression; real time polymerase chain reaction; reverse transcription polymerase chain reaction; RNA splicing; RNA, Messenger; splicing; sporadic GC; stomach; stomach cancer; stomach mucosa; Stomach Neoplasms; stomach polyp; tumor marker; unclassified drug; uvomorulin

Dynamic cell-cell interactions between cord blood haematopoietic progenitors and the cellular niche are essential for the expansion of CD34 +, CD34 +CD38 - Da Silva, C.L.; Gonçalves, R.; Dos Santos, F.; Andrade, P.Z.; Almeida-Porada, G.; Cabral, J.M.S. (Journal of Tissue Engineering and Regenerative MedicineJ. Tissue Eng. Regenerative Med., 2010)
Most clinical applications of haematopoietic stem/progenitor cells (HSCs) would benefit from their ex vivo expansion to obtain a therapeutically significant amount of cells from the available donor samples. We studied the impact of cellular interactions between umbilical cord blood (UCB) haematopoietic cells and bone marrow (BM)-derived mesenchymal stem cells (MSCs) on the ex vivo expansion and differentiative potential of UCB CD34 +-enriched cells. UCB cells were cultured: (a) directly in contact with BM MSC-derived stromal layers (contact); (b) separated by a microporous membrane (non-contact); or (c) without stroma (no stroma). Highly dynamic culture events occurred in HSC-MSC co-cultures, involving cell-cell interactions, which preceded HSC expansion. Throughout the time in culture [18 days], total cell expansion was significantly higher in contact (fold increase of 280 ± 37 at day 18) compared to non-contact (85 ± 25). No significant cell expansion was observed in stroma-free cultures. CD34 + cell expansion was also clearly favoured by direct contact with BM MSCs (35 ± 5- and 7 ± 3-fold increases at day 18 for contact and non-contact, respectively). Moreover, a higher percentage of CD34 +CD38
Cited By (since 1996): 8Export Date: 21 November 2012Source: Scopusdoi: 10.1002/term.226PubMed ID: 19937912Language of Original Document: EnglishCorrespondence Address: Da Silva, C. L.; IBB-Institute for Biotechnology and Bioengineering, Centre for Biological and Chemical Engineering, Instituto Superior Técnico, Avenida Rovisco Pais, 1049-001 Lisbon, Portugal; email: claudialobato@ist.utl.ptChemicals/CAS: Antigens, CD34; Antigens, CD38, 3.2.2.5; Antigens, CD7; SuspensionsReferences: Alakel, N., Jing, D., Muller, K., Direct contact with mesenchymal stromal cells affects migratory behavior and gene expression profile of CD133 + hematopoietic stem cells during ex vivo expansion (2009) Exp Hematol, 37 (4), pp. 504-513;Almeida-Porada, G., Brown, R.L., MacKintosh, F.R., Evaluation of serum-free culture conditions able to support the ex vivo expansion and engraftment of human hematopoietic stem cells in the human-to-sheep xenograft model (2000) J Hematother Stem Cell Res, 9 (5), pp. 683-693; Ando, K., Nakamura, Y., Chargui, J., Extensive generation of human cord blood CD34 + stem cells from Lin -CD34 - cells in a long-term in vitro system (2000) Exp Hematol, 28 (6), pp. 690-699; Bernstein, I.D., Boyd, R.L., van den Brink, M.R., Clinical strategies to enhance posttransplant immune reconstitution (2008) Biol Blood Marrow Transpl, 14 (1 and SUPPL. 1), pp. 94-99; Bilko, N.M., Votyakova, I.A., Vasylovska, S.V., Characterization of the interactions between stromal and haematopoietic progenitor cells in expansion cell culture models (2005) Cell Biol Int, 29 (1), pp. 83-86; Breems, D.A., Blokland, E.A., Siebel, K.E., Stroma contact prevents loss of hematopoietic stem cell quality during ex vivo expansion of CD34 + mobilized peripheral blood stem cells (1998) Blood, 91 (1), pp. 111-117; Cheng, X., Macvittie, T., Meisenberg, B., Human brain endothelial cells (HUBEC) promote SCID repopulating cell expansion through direct contact (2007) Growth Factors, 25 (3), pp. 141-150; Corre, J., Planat-Benard, V., Corberand, J., Human bone marrow adipocytes support complete myeloid and lymphoid differentiation from human CD34 + cells (2004) Br J Haematol, 127 (3), pp. 344-347; da Silva, C.L., Goncalves, R., Crapnell, K.B., A human stromal-based serum-free culture system supports the ex vivo expansion/maintenance of bone marrow and cord blood hematopoietic stem/progenitor cells (2005) Exp Hematol, 33 (7), pp. 828-835; da Silva, C.L., Goncalves, R., Porada, C.D., Differences amid bone marrow and cord blood hematopoietic stem/progenitor cell division kinetics (2009) J Cell Physiol, , DOI: 10.1002/jcp.21736; de Lima, M., Shpall, E., Strategies for widening the use of cord blood in hematopoietic stem cell transplantation (2006) Haematologica, 91 (5), pp. 584-587; Foguenne, J., Di Stefano, I., Giet, O., Ex vivo expansion of hematopoietic progenitor cells is associated with downregulation of α4 integrin- and CXCR4-mediated engraftment in NOD/SCID β2-microglobulin-null mice (2009) Haematologica, 94 (2), pp. 185-194; Freund, D., Bauer, N., Boxberger, S., Polarization of human hematopoietic progenitors during contact with multipotent mesenchymal stromal cells: Effects on proliferation and clonogenicity (2006) Stem Cells Dev, 15 (6), pp. 815-829; Frias, A.M., Porada, C.D., Crapnell, K.B., Generation of functional natural killer and dendritic cells in a human stromal-based serum-free culture system designed for cord blood expansion (2008) Exp Hematol, 36 (1), pp. 61-68; Goncalves, R., Lobato da Silva, C., Cabral, J.M.S., A Stro-1 + human universal stromal feeder layer to expand/maintain human bone marrow hematopoietic stem/progenitor cells in a serum-free culture system (2006) Exp Hematol, 34 (10), pp. 1353-1359; Gordon, M.Y.M.S., Davidson, R.J., Grand, F.H., Contact-mediated inhibition of human hematopoietic progenitor cell proliferationmay be conferred by stem cell antigen, CD34 (2000) Hematol J, 1, pp. 77-86; Hao, Q.L., Zhu, J., Price, M.A., Identification of a novel, human multilymphoid progenitor in cord blood (2001) Blood, 97 (12), pp. 3683-3690; Haylock, D.N., Nilsson, S.K., Osteopontin: A bridge between bone and blood (2006) Br J Haematol, 134 (5), pp. 467-474; Hidalgo, A., Robledo, M.M., Teixido, J., CD44-mediated hematopoietic progenitor cell adhesion and its complex role in myelopoiesis (2002) J Hematother Stem Cell Res, 11 (3), pp. 539-547; Hofmeister, C.C., Zhang, J., Knight, K.L., Ex vivo expansion of umbilical cord blood stem cells for transplantation: Growing knowledge from the hematopoietic niche (2007) Bone Marrow Transpl, 39 (1), pp. 11-23; Jones, P., May, G., Healy, L., Stromal expression of Jagged 1 promotes colony formation by fetal hematopoietic progenitor cells (1998) Blood, 92 (5), pp. 1505-1511; Katayama, Y., Frenette, P.S., Galactocerebrosides are required postnatally for stromal-dependent bone marrow lymphopoiesis (2003) Immunity, 18 (6), pp. 789-800; Kawada, H., Ando, K., Tsuji, T., Rapid ex vivo expansion of human umbilical cord hematopoietic progenitors using a novel culture system (1999) Exp Hematol, 27 (5), pp. 904-915; Kilroy, G.E., Foster, S.J., Wu, X., Cytokine profile of human adipose-derived stem cells: Expression of angiogenic, hematopoietic, and pro-inflammatory factors (2007) J Cell Physiol, 212 (3), pp. 702-709; Kim, J.A., Kang, Y.J., Park, G., Identification of a stromamediated Wnt/β-catenin signal promoting self-renewal of hematopoietic stem cells in the stem cell niche (2009) Stem Cells, 27 (6), pp. 1318-1329; Koller, M.R., Oxender, M., Jensen, T.C., Direct contact between CD34 +lin - cells and stroma induces a soluble activity that specifically increases primitive hematopoietic cell production (1999) Exp Hematol, 27 (4), pp. 734-741; Lewis, I.D., Almeida-Porada, G., Du, J., Umbilical cord blood cells capable of engrafting in primary, secondary, and tertiary xenogeneic hosts are preserved after ex vivo culture in a noncontact system (2001) Blood, 97 (11), pp. 3441-3449; Li, N., Feugier, P., Serrurrier, B., Human mesenchymal stem cells improve ex vivo expansion of adult human CD34 + peripheral blood progenitor cells and decrease their allostimulatory capacity (2007) Exp Hematol, 35 (3), pp. 507-515; Li, Y.P., Paczesny, S., Lauret, E., Human mesenchymal stem cells license adult CD34 + hemopoietic progenitor cells to differentiate into regulatory dendritic cells through activation of the Notch pathway (2008) J Immunol, 180 (3), pp. 1598-1608; Loeuillet, C., Bernard, G., Remy-Martin, J., Distinct hematopoietic support by two human stromal cell lines (2001) Exp Hematol, 29 (6), pp. 736-745; Mayani, H., Lansdorp, P.M., Biology of human umbilical cord blood-derived hematopoietic stem/progenitor cells (1998) Stem Cells, 16 (3), pp. 153-165; McKenzie, J.L., Gan, O.I., Doedens, M., Reversible cell surface expression of CD38 on CD34-positive human hematopoietic repopulating cells (2007) Exp Hematol, 35 (9), pp. 1429-1436; Moore, K.A., Lemischka, I.R., Stem cells and their niches (2006) Science, 311 (5769), pp. 1880-1885; Nolta, J.A., Smogorzewska, E.M., Kohn, D.B., Analysis of optimal conditions for retroviral-mediated transduction of primitive human hematopoietic cells (1995) Blood, 86 (1), pp. 101-110; Oostendorp, R.A., Robin, C., Steinhoff, C., Long-term maintenance of hematopoietic stem cells does not require contact with embryo-derived stromal cells in cocultures (2005) Stem Cells, 23 (6), pp. 842-851; Oritani, K., Wu, X., Medina, K., Antibody ligation of CD9 modifies production of myeloid cells in long-term cultures (1996) Blood, 87 (6), pp. 2252-2261; Sadlon, T.J., Lewis, I.D., D'Andrea, R.J., BMP4: Its role in development of the hematopoietic system and potential as a hematopoietic growth factor (2004) Stem Cells, 22 (4), pp. 457-474; Shih, C.C., Hu, M.C.T., Hu, J., Long-term ex vivo maintenance and expansion of transplantable human hematopoietic stem cells (1999) Blood, 94 (5), pp. 1623-1636; Shpall, E.J., Quinones, R., Giller, R., Transplantation of ex vivo expanded cord blood (2002) Biol Blood Marrow Transpl, 8 (7), pp. 368-376; Suzuki, T., Yokoyama, Y., Kumano, K., Highly efficient ex vivo expansion of human hematopoietic stem cells using Δ1-Fc chimeric protein (2006) Stem Cells, 24 (11), pp. 2456-2465; Verfaillie, C.M., Direct contact between human primitive hematopoietic progenitors and bone marrow stroma is not required for long-term in vitro hematopoiesis (1992) Blood, 79 (11), pp. 2821-2826; Wagner, W., Wein, F., Roderburg, C., Adhesion of hematopoietic progenitor cells to human mesenchymal stem cells as a model for cell-cell interaction (2007) Exp Hematol, 35 (2), pp. 314-325; Yin, T., Li, L., The stem cell niches in bone (2006) J Clin Invest, 116 (5), pp. 1195-1201; Zhang, C.C., Kaba, M., Iizuka, S., Angiopoietin-like 5 and IGFBP2 stimulate ex vivo expansion of human cord blood hematopoietic stem cells as assayed by NOD/SCID transplantation (2008) Blood, 111 (7), pp. 3415-3423; Zhang, Y., Chai, C., Jiang, X.S., Co-culture of umbilical cord blood CD34 + cells with human mesenchymal stem cells (2006) Tissue Eng, 12 (8), pp. 2161-2170
Keywords: Antigens, CD34; Antigens, CD38; Antigens, CD7; article; Bone marrow microenvironment; CD34 antigen; CD38 antigen; CD7 antigen; cell adhesion; Cell Communication; cell contact; Cell culture; cell differentiation; cell interaction; cell proliferation; Cells, Cultured; cellular distribution; clonogenic assay; coculture; Coculture Techniques; Colony-Forming Units Assay; controlled study; Ex vivo expansion; ex vivo study; Fetal Blood; flow cytometry; Haematopoietic stem/progenitor cells; hematopoietic stem cell; Hematopoietic Stem Cells; human; human cell; Humans; Lymphocytes; lymphoid cell; Mesenchymal stem cell; Mesenchymal Stem Cells; Microscopy, Electron, Scanning; phenotype; priority journal; Scanning electron microscopy; somatic gene therapy; stem cell expansion; Stem Cell Niche; stroma cell; Suspensions; umbilical cord blood

An improved collagen scaffold for skeletal regeneration - Oliveira, S.M.; Ringshia, R.A.; Legeros, R.Z.; Clark, E.; Yost, M.J.; Terracio, L.; Teixeira, C.C. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
Bone repair and regeneration is one of the most extensively studied areas in the field of tissue engineering. All of the current tissue engineering approaches to create bone focus on intramembranous ossification, ignoring the other mechanism of bone formation, endochondral ossification. We propose to create a transient cartilage template in vitro, which could serve as an intermediate for bone formation by the endochondral mechanism once implanted in vivo. The goals of the study are (1) to prepare and characterize type I collagen sponges as a scaffold for the cartilage template, and (2) to establish a method of culturing chondrocytes in type I collagen sponges and induce cell maturation. Collagen sponges were generated from a 1% solution of type I collagen using a freeze/dry technique followed by UV light crosslinking. Chondrocytes isolated from two locations in chick embryo sterna were cultured in these sponges and treated with retinoic acid to induce chondrocyte maturation and extracellular matrix deposition. Material strength testing as well as microscopic and biochemical analyzes were conducted to evaluate the properties of sponges and cell behavior during the culture period. We found that our collagen sponges presented improved stiffness and supported chondrocyte attachment and proliferation. Cells underwent maturation, depositing an abundant extracellular matrix throughout the scaffold, expressing high levels of type X collagen, type I collagen and alkaline phosphatase. These results demonstrate that we have created a transient cartilage template with potential to direct endochondral bone formation after implantation. © 2010 Wiley Periodicals, Inc.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32694PubMed ID: 20186736Language of Original Document: EnglishCorrespondence Address: Teixeira, C. C.; Department of Basic Science and Craniofacial Biology, Department of Biomaterials and Biomimetics, New York University College of Dentistry, New York, NY 10010, United States; email: ct40@nyu.eduChemicals/CAS: alkaline phosphatase, 9001-78-9; retinoic acid, 302-79-4; Biocompatible Materials; Collagen, 9007-34-5; Protein IsoformsReferences: Pountos, I., Jones, E., Tzioupis, C., Mcgonagle, D., Giannoudis, P.V., Growing bone and cartilage. The role of mesenchymal stem cells (2006) J Bone Joint Surg Br, 88, pp. 421-426;Newman, A.P., Articular cartilage repair (1998) Am J Sports Med, 26, pp. 309-324; Tomihisa, K., Tomoo, M., Toshitaka, T., Tomoyuki, S., New bone formation around porous hydroxyapatite wedge implanted in opening wedge high tibial osteotomy in patients with osteoarthritis (2001) Biomaterials, 22, pp. 1579-1582; Weiss, P., Layrolle, P., Clergeau, L.P., Enckel, B., Pilet, P., Amouriq, Y., Daculsi, G., Giumelli, B., The safety and efficacy of an injectable bone substitute in dental sockets demonstrated in a human clinical trial (2007) Biomaterials, 28, pp. 3295-3305; Verlaan, J.J., Oner, F.C., Dhert, W.J., Anterior spinal column augmentation with injectable bone cements (2006) Biomaterials, 27, pp. 290-301; Zelzer, E., Olsen, B.R., The genetic basis for skeletal diseases (2003) Nature, 423, pp. 343-348; Ivaska, K.K., Gerdhem, P., Åkesson, K., Garnero, P., Obrant, K.J., Effect of fracture on bone turnover markers: A longitudinal study comparing marker levels before and after injury in 113 elderly women (2007) J Bone Miner Res, 22, pp. 1155-1164; Hunziker, E.B., Articular cartilage repair: Basic science and clinical progress. A review of the current status and prospects (2002) Osteoarthritis Cartilage, 10, pp. 432-463; Curran, S.J., Chen, R., Curran, J.M., Hunt, J.A., Expansion of human chondrocytes in an intermittent stirred flow bioreactor, using modified biodegradable microspheres (2005) Tissue Eng, 11, pp. 1312-1322; Vinatier, C., Magne, D., Moreau, A., Gauthier, O., Malard, O., Vignes-Colombeix, C., Daculsi, G., Guicheux, J., Engineering cartilage with human nasal chondrocytes and a silanized hydroxypropyl methylcellulose hydrogel (2007) J Biomed Mater Res Part A, 80, pp. 66-74; Pound, J.C., Green, D.W., Chaudhuri, J.B., Mann, S., Roach, H.I., Oreffo, R.O., Strategies to promote chondrogenesis and osteogenesis from human bone marrow cells and articular chondrocytes encapsulated in polysaccharide templates (2006) Tissue Eng, 12, pp. 2789-2799; Kasten, P., Vogel, J., Luginbuhl, R., Niemeyer, P., Tonak, M., Lorenz, H., Helbig, L., Leo, A., Ectopic bone formation associated with mesenchymal stem cells in a resorbable calcium deficient hydroxyapatite carrier (2005) Biomaterials, 26, pp. 5879-5889; Joon Yung, L., Musgrave, D., Pelinkovic, D., Fukushima, K., Cummins, J., Usas, A., Robbins, P., Huard, J., Effect of bone morphogenetic protein-2-expressing muscle-derived cells on healing of critical-sized bone defects in mice (2001) Journal of Bone and Joint Surgery - Series a, 83 (7), pp. 1032-1039; Sumanasinghe, R.D., Osborne, J.A., Loboa, E.G., Mesenchymal stem cell-seeded collagen matrices for bone repair: Effects of cyclic tensile strain, cell density, and media conditions on matrix contraction in vitro (2008) J Biomed Mater Res Part A, 88, pp. 778-786; Alsberg, E., Anderson, K.W., Albeiruti, A., Rowley, J.A., Mooney, D.J., Engineering growing tissues (2002) Proc Natl Acad Sci USA, 99, pp. 12025-12030; Arpornmaeklong, P., Suwatwirote, N., Pripatnanont, P., Oungbho, K., Growth and differentiation of mouse osteoblasts on chitosan-collagen sponges (2007) Int J Oral Maxillacial Surgery, 36, pp. 328-337; Lode, A., Bernhardt, A., Gelinsky, M., Cultivation of human bone marrow stromal cells on three-dimensional scaffolds of mineralized collagen: Influence of seeding density on colonization, proliferation and osteogenic differentiation (2008) J Tissue Eng Regenerative Med, 2, pp. 400-407; Balooch, M., Habelitz, S., Kinney, J.H., Marshall, S.J., Marshall, G.W., Mechanical properties of mineralized collagen fibrils as influenced by demineralization (2008) J Struct Biol, 162, pp. 404-410; Gelse, K., Poschl, E., Aigner, T., Collagens-structure, function, and biosynthesis (2003) Adv Drug Deliv Rev, 55, pp. 1531-1546; Berglund, J.D., Mohseni, M.M., Nerem, R.M., Sambanis, A., A biological hybrid model for collagen-based tissue engineered vascular constructs (2003) Biomaterials, 24, pp. 1241-1254; Chvapil, M., Collagen sponge: Theory and practice of medical applications (1977) J Biomed Mater Res, 11, pp. 721-741; Chvapil, M., Kronenthal, L., Van Winkle, W., Medical and surgical applications of collagen (1973) Int Rev Connect Tissue Res, 6, pp. 1-61; Matton, G., Anseeuw, A., De Keyser, F., The history of injectable biomaterials and the biology of collagen (1985) Aesthetic Plastic Surgery, 9 (2), pp. 133-140. , DOI 10.1007/BF01570345; Radhika, M., Babu, M., Sehgal, P.K., Cellular proliferation on desamidated collagen matrices (1999) Comp Biochem Physiol C Pharmacol Toxicol Endocrinol, 124, pp. 131-139; Elliott, J.T., Woodward, J.T., Langenbach, K.J., Tona, A., Jones, P.L., Plant, A.L., Vascular smooth muscle cell response on thin films of collagen (2005) Matrix Biol, 24, pp. 489-502; Song, J., Rolfe, B.E., Hayward, I.P., Campbell, G.R., Campbell, J.H., Effects of collagen gel configuration on behavior of vascular smooth muscle cells in vitro: Association with vascular morphogenesis (2000) In Vitro Cell Dev Biol Anim, 36, pp. 600-610; Weinberg, C.B., Bell, E., A blood vessel model constructed from collagen and cultured vascular cells (1986) Science, 231 (4736), pp. 397-400; Reid, G.G., Gorham, S.D., Lackie, J.M., The attachment, spreading and growth of baby hamster-kidney cells on collagen, chemically modified collagen and collagen-composite substrata (1993) J Mater Sci-Mater Med, 4, pp. 201-209; Michalopoulos, G., Pitot, H.C., Primary culture of parenchymal liver cells on collagen membranes. Morphological and biochemical observations (1975) Exp Cell Res, 94, pp. 70-78; Winder, S.J., Turvey, A., Forsyth, I.A., Characteristics of ruminant mammary epithelial cells grown in primary culture in serumfree medium (1992) J Dairy Res, 59, pp. 491-498; Sato, T., Chen, G., Ushida, T., Ishii, T., Ochiai, N., Tateishi, T., Tissue-engineered cartilage by in vivo culturing of chondrocytes in PLGA-collagen hybrid sponge (2001) Mater Sci Engineering: C, 17, pp. 83-89; Takahiro, O., Keizo, T., Yosuke, H., Takashi, U., Tamotsu, T., Tetsuya, T., Effect of type I and type II collagen sponges as 3D scaffolds for hyaline cartilage-like tissue regeneration on phenotypic control of seeded chondrocytes in vitro (2004) Mater Sci Eng C, 24, pp. 407-411; Fuchs, J.R., Kaviani, A., Oh, J.T., Lavan, D., Udagawa, T., Jennings, R.W., Wilson, J.M., Fauza, D.O., Diaphragmatic reconstruction with autologous tendon engineered from mesenchymal amniocytes (2004) J Pediatr Surg, 39, pp. 834-838; Kall, S., Nöth, U., Reimers, K., Choi, C.Y.U., Muehlberger, T., Allmeling, C., Jahn, S., Vogt, P.M., In vitro fabrication of tendon substitutes using human mesenchymal stem cells and a collagen type i gel (2004) Handchir Mikrochir Plast Chir, 4, pp. 205-211; Domaschke, H., Gelinsky, M., Burmeister, B., Fleig, R., Hanke, T., Reinstorf, A., Pompe, W., Rosen-Wolff, A., In vitro ossification and remodeling of mineralized collagen i scaffolds (2006) Tissue Eng, 12, pp. 949-958; Rodrigues, C.V.M., Serricella, P., Linhares, A.B.R., Guerdes, R.M., Borojevic, R., Rossi, M.A., Duarte, M.E.L., Farina, M., Characterization of a bovine collagen-hydroxyapatite composite scaffold for bone tissue engineering (2003) Biomaterials, 24, pp. 4987-4997; Cooperman, L., Michaeli, D., The immunogenicity of injectable collagen. I. A 1-year prospective study (1984) J Am Acad Dermatol, 10, pp. 638-646; Delustro, F., Condell, R.A., Nguyen, M.A., Mcpherson, J.M., A comparative study of the biologic and immunologic response to medical devices derived from dermal collagen (1986) J Biomed Mater Res, 20, pp. 109-120; Sandberg, M., Vurio, E., Localization of types I, II, and III collagen mRNAs in developing human skeletal tissues by in situ hybridization (1987) J Cell Biol, 104, pp. 1077-1084; DeLustro, F., Smith, S.T., Sundsmo, J., Reaction to injectable collagen: Results in animal models and clinical use (1987) Plastic and Reconstructive Surgery, 79 (4), pp. 581-592; Lynn, A.K., Yannas, I.V., Bonfield, W., Antigenicity and immunogenicity of collagen (2004) J Biomed Mater Res Part B: Appl Biomaterials, 71, pp. 343-354; Mizuno, M., Shindo, M., Kobayashi, D., Tsuruga, E., Amemiya, A., Kuboki, Y., Osteogenesis by bone marrow stromal cells maintained on type I collagen matrix gels in vivo (1997) Bone, 20, pp. 101-107; Wambach, B.A., Cheung, H., Josephson, G.D., Cartilage tissue engineering using thyroid chondrocytes on a type i collagen matrix (2000) Laryngoscope, 110, pp. 2008-2011; Rajpurohit, R., Koch, C.J., Tao, Z., Teixeira, C.M., Shapiro, I.M., Adaptation of chondrocytes to low oxygen tension: Relationship between hypoxia and cellular metabolism (1996) J Cell Physiol, 168, pp. 424-432; Schipani, E., Ryan, H.E., Didrickson, S., Kobayashi, T., Knight, M., Johnson, R.S., Hypoxia in cartilage: HIF-1 alpha is essential for chondrocyte growth arrest and survival (2001) Genes Dev, 15, pp. 2865-2876; Maes, C., Carmeliet, P., Moermans, K., Stockmans, I., Smets, N., Collen, D., Bouillon, R., Carmeliet, G., Impaired angiogenesis and endochondral bone formation in mice lacking the vascular endothelial growth factor isoforms VEGF164 and VEGF188 (2002) Mech Dev, 111, pp. 61-73; Petersen, W., Tsokos, M., Pufe, T., Expression of VEGF121 and VEGF165 in hypertrophic chondrocytes of the human growth plate and epiphyseal cartilage (2002) J Anat, 201, pp. 153-157; Oliveira, S.M., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., Engineering endochondral bone: In vitro studies (2009) Tissue Eng, 15, pp. 625-634; Teixeira, C.C., Nemelivsky, Y., Karkia, C., Legeros, R.Z., Biphasic calcium phosphate: A scaffold for growth plate chondrocyte maturation (2006) Tissue Eng, 12, pp. 2283-2289; Oliveira, S.M., Turner, G., Mijares, D., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., Engineering endochondral bone: In vivo studies (2009) Tissue Eng, 15, pp. 635-643; Hiraoka, Y., Kimura, Y., Ueda, H., Tabata, Y., Fabrication and biocompatibility of collagen sponge reinforced with poly(glycolic acid) fiber (2003) Tissue Eng, 9, pp. 1101-1112; Yost, M.J., Baicu, C.F., Stonerock, C.E., Terracio, L., A novel tubular scaffold for cardiovascular tissue engineering (2004) Tissue Eng, 10, pp. 273-284; Mow, V.C., Kuei, S.C., Lai, W.M., Armstrong, C.G., Biphasic creep and stress relaxation of articular cartilage in compression? Theory and experiments (1980) J Biomech Eng, 102, pp. 73-84; Iwamoto, M., Shapiro, I.M., Yagami, K., Boskey, A.L., Leboy, P.S., Adams, S.L., Pacifici, M., Retinoic acid induces rapid mineralization and expression of mineralization-related genes in chondrocytes (1993) Exp Cell Res, 207, pp. 413-420; Teixeira, C.C., Hatori, M., Leboy, P.S., Pacifici, M., Shapiro, I.M., A rapid and ultrasensitive method for measurement of DNA, calcium and protein content, and alkaline phosphatase activity of chondrocyte cultures (1995) Calcif Tissue Int, 56, pp. 252-256; Leboy, P.S., Vaias, L., Uschmann, B., Golub, E., Adams, S.L., Pacifici, M., Ascorbic acid induces alkaline phosphatase, type X collagen, and calcium deposition in cultured chick chondrocytes (1989) Journal of Biological Chemistry, 264 (29), pp. 17281-17286; Whyte, M.P., Hypophosphatasia and the role of alkaline phosphatase in skeletal mineralization (1994) Endocr Rev, 15, pp. 439-461; Wang, W., Kirsch, T., Retinoic acid stimulates annexin-mediated growth plate chondrocyte mineralization (2002) J Cell Biol, 157, pp. 1061-1069; Chen, D., Zhao, M., Mundy, G.R., Bone morphogenetic proteins (2004) Growth Factors, 22, pp. 233-241; Gerstenfeld, L.C., Shapiro, F.D., Expression of bone-specific genes by hypertrophic chondrocytes: Implications of the complex functions of the hypertrophic chondrocyte during endochondral bone development (1996) J Cell Biochem, 62, pp. 1-9; Bianco, P., Cancedda, F.D., Riminucci, M., Cancedda, R., Bone formation via cartilage models: The "borderline" chondrocyte (1998) Matrix Biol, 17, pp. 185-192; De Bernard, B., Bianco, P., Bonucci, E., Costantini, M., Lunazzi, G.C., Martinuzzi, P., Modricky, C., Pollesello, P., Biochemical and immunohistochemical evidence that in cartilage an alkaline phosphatase is a Ca 2" - Binding glycoprotein (1986) J Cell Biol, 103, pp. 1615-1623; Galotto, M., Campanile, G., Robino, G., Cancedda, F.D., Bianco, P., Cancedda, R., Hypertrophic chondrocytes undergo further differentiation to osteoblast- Like cells and participate in the initial bone formation in developing chick embryo (1994) Journal of Bone and Mineral Research, 9 (8), pp. 1239-1249; Mark, M.P., Butler, W.T., Prince, C.W., Finkelman, R.D., Ruch, J.V., Developmental expression of 44-kDa bone phosphoprotein (osteopontin) and bone gamma-carboxyglutamic acid (Gla)-containing protein (osteocalcin) in calcifying tissues of rat (1988) Differentiation, 37, pp. 123-136; Sims, C.D., Butler, P.E., Casanova, R., Lee, B.T., Randolph, M.A., Lee, W.P., Vacanti, C.A., Yaremchuk, M.J., Injectable cartilage using polyethylene oxide polymer substrates (1996) Plast Reconstr Surg, 98, pp. 843-850; Woodard, J.C., Donovan, G.A., Fisher, L.W., Pathogenesis of vitamin (A and D)-induced premature growth-plate closure in calves (1997) Bone, 27, pp. 171-182; Liao, E., Yaszemski, M., Krebsbach, P., Hollister, S., Tissue-engineered cartilage constructs using composite hyaluronic acid/ collagen I hydrogels and designed poly(propylene fumarate) scaffolds (2007) Tissue Eng, 13, pp. 537-550; Gerstenfeld, L.C., Cruceta, J., Shea, C.M., Sampath, K., Barnes, G.L., Einhorn, T.A., Chondrocytes provide morphogenic signals that selectively induce osteogenic differentiation of mesenchymal stem cells (2002) Journal of Bone and Mineral Research, 17 (2), pp. 221-230
Keywords: alkaline phosphatase; animal cell; animal tissue; Animals; article; Biocompatible Materials; Body fluids; Bone; Bone and Bones; Bone Regeneration; Cartilage; cartilage cell; Cattle; Cell culture; cell maturation; chick embryo; Chondrocytes; Collagen; collagen implant; collagen type 1; collagen type 10; Compressive Strength; controlled study; embryo; enchondral ossification; Endochondral ossification; extracellular matrix; freeze drying; Humans; immunohistochemistry; Ligaments; materials testing; Microscopy, Electron, Scanning; nonhuman; Phosphatases; protein cross linking; Protein Isoforms; retinoic acid; Scaffolds; Scanning electron microscopy; Stress, Mechanical; Tissue engineering; tissue scaffold; Type I collagen; Type X collagen; Ultraviolet radiation

Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics): Preface - Campilho, A.; Kamel, M. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2010)
Conference code: 81097Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Campilho, A.; University of Porto, Faculty of Engineering, Institute of Biomedical Engineering, 4200-465 Porto, Portugal; email: campilho@fe.up.pt

Neuropeptide y expression and function during osteoblast differentiation - Insights from transthyretin knockout mice - Nunes, A.F.; Liz, M.A.; Franquinho, F.; Teixeira, L.; Sousa, V.; Chenu, C.; Lamghari, M.; Sousa, M.M. (FEBS JournalFEBS J., 2010)
To better understand the role of neuropeptide Y (NPY) in bone homeostasis, as its function in the regulation of bone mass is unclear, we assessed its expression in this tissue. By immunohistochemistry, we demonstrated, both at embryonic stages and in the adult, that NPY is synthesized by osteoblasts, osteocytes, and chondrocytes. Moreover, peptidylglycine α-amidating monooxygenase, the enzyme responsible for NPY activation by amidation, was also expressed in these cell types. Using transthyretin (TTR) KO mice as a model of augmented NPY levels, we showed that this strain has increased NPY content in the bone, further validating the expression of this neuropeptide by bone cells. Moreover, the higher amidated neuropeptide levels in TTR KO mice were related to increased bone mineral density and trabecular volume. Additionally, RT-PCR analysis established that NPY is not only expressed in MC3T3-E1 osteoblastic cells and bone marrow stromal cells (BMSCs), but is also detectable by RIA in BMSCs undergoing osteoblastic differentiation. In agreement with our in vivo observations, in vitro, TTR KO BMSCs differentiated in osteoblasts had increased NPY levels and exhibited enhanced competence in undergoing osteoblastic differentiation. In summary, this work contributes to a better understanding of the role of NPY in the regulation of bone formation by showing that this neuropeptide is expressed in bone cells and that increased amidated neuropeptide content is related to increased bone mass. © 2009 FEBS.
Cited By (since 1996): 5Export Date: 21 November 2012Source: Scopusdoi: 10.1111/j.1742-4658.2009.07482.xPubMed ID: 19954489Language of Original Document: EnglishCorrespondence Address: Sousa, M. M.; IBMC, Rua Campo Alegre 823, 4150-180 Porto, Portugal; email: msousa@ibmc.up.ptChemicals/CAS: neuropeptide Y, 82785-45-3, 83589-17-7; Amides; DNA Primers; Neuropeptide Y; Prealbumin; RNA, MessengerReferences: McDonald, A.C., Schuijers, J.A., Shen, P.J., Gundlach, A.L., Grills, B.L., Expression of galanin and galanin receptor-1 in normal bone and during fracture repair in the rat (2003) Bone, 33, pp. 788-797;Pacifici, R., Cytokines, estrogen, and postmenopausal osteoporosis - The second decade (1998) Endocrinology, 139, pp. 2659-2661; You, L., Temiyasathit, S., Lee, P., Kim, C.H., Tummala, P., Yao, W., Kingery, W., Jacobs, C.R., Osteocytes as mechanosensors in the inhibition of bone resorption due to mechanical loading (2008) Bone, 42, pp. 172-179; Chenu, C., Marenzana, M., Sympathetic nervous system and bone remodeling (2005) Joint Bone Spine, 72 (6), pp. 481-483. , DOI 10.1016/j.jbspin.2005.10.007, PII S1297319X05001661; Baldock, P.A., Sainsbury, A., Couzens, M., Enriquez, R.F., Thomas, G.P., Gardiner, E.M., Herzog, H., Hypothalamic Y2 receptors regulate bone formation (2002) J Clin Invest, 109, pp. 915-921; Baldock, P.A., Allison, S.J., Lundberg, P., Lee, N.J., Slack, K., Lin, E.J., Enriquez, R.F., During, M.J., Novel role of Y1 receptors in the coordinated regulation of bone and energy homeostasis (2007) J Biol Chem, 282, pp. 19092-19102; Ducy, P., Amling, M., Takeda, S., Priemel, M., Schilling, A.F., Beil, F.T., Shen, J., Karsenty, G., Leptin inhibits bone formation through a hypothalamic relay: A central control of bone mass (2000) Cell, 100, pp. 197-207; Elefteriou, F., Takeda, S., Liu, X., Armstrong, D., Karsenty, G., Monosodium glutamate-sensitive hypothalamic neurons contribute to the control of bone mass (2003) Endocrinology, 144, pp. 3842-3847; Elefteriou, F., Neuronal signaling and the regulation of bone remodeling (2005) Cell Mol Life Sci, 62, pp. 2339-2349; Bjurholm, A., Kreicbergs, A., Terenius, L., Goldstein, M., Schultzberg, M., Neuropeptide Y-, tyrosine hydroxylase- and vasoactive intestinal polypeptide-immunoreactive nerves in bone and surrounding tissues (1988) J Auton Nerv Syst, 25, pp. 119-125; Hill, E.L., Elde, R., Distribution of CGRP-, VIP-, D beta H-, SP-, and NPY-immunoreactive nerves in the periosteum of the rat (1991) Cell Tissue Res, 264, pp. 469-480; Tabarowski, Z., Gibson-Berry, K., Felten, S.Y., Noradrenergic and peptidergic innervation of the mouse femur bone marrow (1996) Acta Histochem, 98, pp. 453-457; Ahmed, M., Srinivasan, G.R., Theodorsson, E., Bjurholm, A., Kreicbergs, A., Extraction and quantitation of neuropeptides in bone by radioimmunoassay (1994) Regul Pept, 51, pp. 179-188; Ericsson, A., Schalling, M., McIntyre, K.R., Lundberg, J.M., Larhammar, D., Seroogy, K., Hokfelt, T., Persson, H., Detection of neuropeptide y and its mRNA in megakaryocytes: Enhanced levels in certain autoimmune mice (1987) Proc Natl Acad Sci USA, 84, pp. 5585-5589; Lundberg, P., Allison, S.J., Lee, N.J., Baldock, P.A., Brouard, N., Rost, S., Enriquez, R.F., Simmons, P., Greater bone formation of y2 knockout mice is associated with increased osteoprogenitor numbers and altered y1 receptor expression (2007) J Biol Chem, 282, pp. 19082-19091; Stephens, T.W., Basinski, M., Bristow, P.K., Bue-Valleskey, J.M., Burgett, S.G., Craft, L., Hale, J., Kriauciunas, A., The role of neuropeptide y in the antiobesity action of the obese gene product (1995) Nature, 377, pp. 530-532; Baldock, P.A., Sainsbury, A., Allison, S., Lin, E.J., Couzens, M., Boey, D., Enriquez, R., Gardiner, E.M., Hypothalamic control of bone formation: Distinct actions of leptin and y2 receptor pathways (2005) J Bone Miner Res, 20, pp. 1851-1857; Allison, S., Baldock, P., Enriquez, R., Lin, E., During, M., Gardiner, E., Eisman, J., Herzog, H., Critical interplay between neuropeptide y and sex steroid pathways in bone and adipose tissue homeostasis (2008) J Bone Miner Res, 24, pp. 294-304; Nunes, A.F., Saraiva, M.J., Sousa, M.M., Transthyretin knockouts are a new mouse model for increased neuropeptide y (2006) FASEB J, 20, pp. 166-168; Mains, R.E., Cullen, E.I., May, V., Eipper, B.A., The role of secretory granules in peptide biosynthesis (1987) Ann NY Acad Sci, 493, pp. 278-291; Prigge, S.T., Mains, R.E., Eipper, B.A., Amzel, L.M., New insights into copper monooxygenases and peptide amidation: Structure, mechanism and function (2000) Cell Mol Life Sci, 57, pp. 1236-1259; Eipper, B.A., Stoffers, D.A., Mains, R.E., The biosynthesis of neuropeptides: Peptide alpha-amidation (1992) Annu Rev Neurosci, 15, pp. 57-85; Teixeira, L., Sousa, D.M., Nunes, A.F., Sousa, M.M., Herzog, H., Lamghari, M., NPY revealed as a critical modulator of osteoblast function in vitro: New insights into the role of Y1 and Y2 receptors (2009) J Cell Biochem, 107, pp. 908-916; Amano, S., Arai, M., Goto, S., Togari, A., Inhibitory effect of NPY on isoprenaline-induced osteoclastogenesis in mouse bone marrow cells (2007) Biochim Biophys Acta, 1770, pp. 966-973; Baldock, P.A., Allison, S., McDonald, M.M., Sainsbury, A., Enriquez, R.F., Little, D.G., Eisman, J.A., Herzog, H., Hypothalamic regulation of cortical bone mass: Opposing activity of Y2 receptor and leptin pathways (2006) J Bone Miner Res, 21, pp. 1600-1607; Saper, C.B., Loewy, A.D., Swanson, L.W., Cowan, W.M., Direct hypothalamo-autonomic connections (1976) Brain Res, 117, pp. 305-312; Navia, J.M., Harris, S.S., Vitamin A influence on calcium metabolism and calcification (1980) Ann NY Acad Sci, 355, pp. 45-57; Wang, A., Ding, X., Sheng, S., Yao, Z., Retinoic acid inhibits osteogenic differentiation of rat bone marrow stromal cells (2008) Biochem Biophys Res Commun, 375, pp. 435-439; Takahashi, T., Kamiya, N., Kawabata, N., Takagi, M., The effect of retinoic acid on a zinc finger transcription factor, AJ18, during differentiation of a rat clonal preosteoblastic cell line, ROB-C20, into osteoblasts (2008) Arch Oral Biol, 53, pp. 87-94; Grouzmann, E., Comoy, E., Walker, P., Burnier, M., Bohuon, C., Waeber, B., Brunner, H., Production and characterization of four anti-neuropeptide y monoclonal antibodies (1992) Hybridoma, 11, pp. 409-424; Wei, S., Episkopou, V., Piantedosi, R., Maeda, S., Shimada, K., Gottesman, M.E., Blaner, W.S., Studies on the metabolism of retinol and retinol-binding protein in transthyretin-deficient mice produced by homologous recombination (1995) J Biol Chem, 270, pp. 866-870; Karga, H., Papapetrou, P.D., Korakovouni, A., Papandroulaki, F., Polymeris, A., Pampouras, G., Bone mineral density in hyperthyroidism (2004) Clin Endocrinol, 61, pp. 466-472; Episkopou, V., Maeda, S., Nishiguchi, S., Shimada, K., Gaitanaris, G.A., Gottesman, M.E., Robertson, E.J., Disruption of the transthyretin gene results in mice with depressed levels of plasma retinol and thyroid hormone (1993) Proc Natl Acad Sci USA, 90, pp. 2375-2379; Palha, J.A., Episkopou, V., Maeda, S., Shimada, K., Gottesman, M.E., Saraiva, M.J., Thyroid hormone metabolism in a transthyretin-null mouse strain (1994) J Biol Chem, 269, pp. 33135-33139; Palha, J.A., Hays, M.T., Morreale De Escobar, G., Episkopou, V., Gottesman, M.E., Saraiva, M.J., Transthyretin is not essential for thyroxine to reach the brain and other tissues in transthyretin-null mice (1997) Am J Physiol, 272, pp. 485-E493; Palha, J.A., Fernandes, R., De Escobar, G.M., Episkopou, V., Gottesman, M., Saraiva, M.J., Transthyretin regulates thyroid hormone levels in the choroid plexus, but not in the brain parenchyma: Study in a transthyretin-null mouse model (2000) Endocrinology, 141, pp. 3267-3272; Kingery, W.S., Offley, S.C., Guo, T.Z., Davies, M.F., Clark, J.D., Jacobs, C.R., A substance P receptor (NK1) antagonist enhances the widespread osteoporotic effects of sciatic nerve section (2003) Bone, 33, pp. 927-936; Hosaka, H., Nagata, A., Yoshida, T., Shibata, T., Nagao, T., Tanaka, T., Saito, Y., Tatsuno, I., Pancreatic polypeptide is secreted from and controls differentiation through its specific receptors in osteoblastic MC3T3-E1 cells (2008) Peptides, 29, pp. 1390-1395; Fleming, C.E., Saraiva, M.J., Sousa, M.M., Transthyretin enhances nerve regeneration (2007) J Neurochem, 103, pp. 831-839; Sainsbury, A., Cusin, I., Doyle, P., Rohner-Jeanrenaud, F., Jeanrenaud, B., Intracerebroventricular administration of neuropeptide y to normal rats increases obese gene expression in white adipose tissue (1996) Diabetologia, 39, pp. 353-356; Sainsbury, A., Herzog, H., Inhibitory effects of central neuropeptide y on the somatotropic and gonadotropic axes in male rats are independent of adrenal hormones (2001) Peptides, 22, pp. 467-471; Marques, F., Sousa, J.C., Oliveira, P., Oliveira, H.C., Palha, J.A., The absence of transthyretin does not impair regulation of lipid and glucose metabolism (2007) Horm Metab Res, 39, pp. 529-533; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Salingcarnboriboon, R., Tsuji, K., Komori, T., Nakashima, K., Ezura, Y., Noda, M., Runx2 is a target of mechanical unloading to alter osteoblastic activity and bone formation in vivo (2006) Endocrinology, 147, pp. 2296-2305
Keywords: 3T3 Cells; alpha amidating enzyme; Amidated neuropeptide; amidation; Amides; animal cell; animal tissue; Animals; article; Base Sequence; Bone Density; bone development; bone marrow cell; Bone Marrow Cells; Bone marrow stromal cells; bone mass; cartilage cell; cell differentiation; Cells, Cultured; Chondrocytes; controlled study; developmental stage; DNA Primers; embryo; embryo development; Homeostasis; immunohistochemistry; male; Mice; Mice, Knockout; mouse; Mus; neuropeptide Y; nonhuman; NPY; ossification; osteoblast; Osteoblastic differentiation; Osteoblasts; osteocyte; Osteocytes; peptide synthesis; prealbumin; priority journal; protein expression; protein function; radioimmunoassay; regulatory mechanism; reverse transcription polymerase chain reaction; RNA, Messenger; stroma cell; Stromal Cells; trabecular bone

Optical flow based Arabidopsis thaliana root meristem cell division detection - Quelhas, P.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2010)
The study of cell division and growth is a fundamental aspect of plant biology research. In this research the Arabidopsis thaliana plant is the most widely studied model plant and research is based on in vivo observation of plant cell development, by time-lapse confocal microscopy. The research herein described is based on a large amount of image data, which must be analyzed to determine meaningful transformation of the cells in the plants. Most approaches for cell division detection are based on the morphological analysis of the cells' segmentation. However, cells are difficult to segment due to bad image quality in the in vivo images. We describe an approach to automatically search for cell division in the Arabidopsis thaliana root meristem using image registration and optical flow. This approach is based on the difference of speeds of the cell division and growth processes (cell division being a much faster process). With this approach, we can achieve a detection accuracy of 96.4%. © 2010 Springer-Verlag.
Conference code: 81097Cited By (since 1996): 1Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-13775-4_22Language of Original Document: EnglishCorrespondence Address: Quelhas, P.; INEB - Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUPPortugalReferences: Campilho, A., Garcia, B., Toorn, H.V.D., Wijk, H.V., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the Arabidopsis thaliana root meristem (2006) Plant Journal, 48 (4), pp. 619-627. , DOI 10.1111/j.1365-313X.2006.02892.x;Iwamoto, A., Satoh, D., Furutani, M., Maruyama, S., Ohba, H., Sugiyama, M., Insight into the basis of root growth in arabidopsis thaliana provided by a simple mathematical model (2006) J. Plant Res., 119, pp. 85-93; Roberts, T., Mckenna, S., Wuyts, N., Valentine, T., Bengough, A., Performance of low-level motion estimation methods for confocal microscopy of plant cells in vivo (2007) Motion'07, p. 13; Beemster, G.T.S., Baskin, T.I., Analysis of Cell Division and Elongation Underlying the Developmental Acceleration of Root Growth in Arabidopsis thaliana (1998) Plant Physiology, 116 (4), pp. 1515-1526; Chen, X., Zhou, X., Wong, S.T.C., Automated segmentation, classification, and tracking of cancer cell nuclei in time-lapse microscopy (2006) IEEE Trans. on Biomedical Engineering, 53 (4), pp. 762-766; Mao, K.Z., Zhao, P., Tan, P., Supervised learning-based cell image segmentation for p53 immunohistochemistry (2006) IEEE Trans. on Biomedical Engineering, 53 (6), pp. 1153-1163; Harder, N., M-Bermudez, F., Godinez, W., Ellenberg, J., Rohr, K., Automated analysis of mitotic cell nuclei in 3rd fluorescence microscopy image sequences Workshop on Bio-Image Inf.: Bio. Imag., Comp. Vision and Data Mining (2008); Yang, F., Mackey, M.A., Ianzini, F., Gallardo, G., Sonka, M., Cell segmentation, tracking, and mitosis detection using temporal context (2005) Medical Image Computing and Computer-Assisted Intervention (MICCAI), pp. 302-309; Marcuzzo, M., Quelhas, P., Campilho, A., Mendonça, A.M., Campilho, A., Automated arabidopsis plant root cell segmentation based on svm classification and region merging (2009) Comp. in Biology and Medicine, 39, pp. 785-793; Marcuzzo, M., Guichard, T., Quelhas, P., Maria Mendonça, A., Campilho, A., Cell division detection on the arabidopsis thaliana root (2009) LNCS, 5524, pp. 168-175. , Araujo, H., Mendonça, A.M., Pinho, A.J., Torres, M.I. (eds.) IbPRIA 2009. Springer, Heidelberg; Pereira, C.S., Mendonça, A.M., Campilho, A., Evaluation of contrast enhancement filters for lung nodule detection (2007) LNCS, 4633, pp. 878-888. , Kamel, M.S., Campilho, A. (eds.) ICIAR 2007. Springer, Heidelberg; Garcia, B., Campilho, A., Scheres, B., Campilho, A., Automatic tracking of arabidopsis thaliana root meristem in confocal microscopy (2004) LNCS, 3212, pp. 166-174. , Campilho, A.C., Kamel, M.S. (eds.) ICIAR 2004. Springer, Heidelberg; Hartley, R., Zisserman, A., (2003) Multiple View Geometry in Computer Vision, , Cambridge University Press, Cambridge; Lowe, D.G., Distinctive image features from scale-invariant keypoints (2004) International Journal of Computer Vision, 60, pp. 91-110; Brox, T., Bruhn, A., Papenberg, N., Weickert, J., High accuracy optical flow estimation based on a theory for warping (2004) LNCS, 3024, pp. 25-36. , Pajdla, T., Matas, J(G.) (eds.) ECCV 2004. Springer, Heidelberg
Keywords: Arabidopsis thaliana; Biology; Biology image processing; cell division detection; Cell divisions; cell proliferation; confocal microscopy; Detection accuracy; Growth process; Image data; Image quality; Image segmentation; Imaging systems; In-vivo; In-vivo images; Metadata; Morphological analysis; Optical data processing; Optical flows; Plant biology; Plant cells; research; Root meristem

Plasma surface modification of polycarbonate and poly(propylene) substrates for biomedical electrodes - Pedrosa, P.; Chappé, J.-M.; Fonseca, C.; Machado, A.V.; Nóbrega, J.M.; Vaz, F. (Plasma Processes and PolymersPlasma Processes Polym., 2010)
The effects of surface plasma treatments on the properties of PP and PC substrates were studied. Main results showed that the 0.48 Pa Ar treatment promoted the most favorable changes: roughness increased from 15 to 17 nm for PC and from 12 to 30 nm for PP, while the CA lowered from 95° to 59° and from 87° to 35° for PC and PP, respectively. The effects of the activation treatment on adhesion were checked by depositing a thin layer of TiN on both untreated and 0.48 Pa Ar plasma treated PC samples, and the adhesion to both substrates compared using the standard X-cut tape test. The Ar activated samples displayed better adhesion of the TiN film than the untreated ones, confirming the benefits of the surface changes induced by the plasma treatments. (Figure Presented) © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Cited By (since 1996): 4Export Date: 21 November 2012Source: Scopusdoi: 10.1002/ppap.200900176Language of Original Document: EnglishCorrespondence Address: Vaz, F.; Universidade do Minho, Centro de Fisica, Campus de Azurém, 4800-058 Guimarães, Portugal; email: fvaz@fisica.uminho.ptReferences: Moon, M.-W., Vaziri, A., (2009) Scripta Mater., 60, p. 44;Pandiyaraj, K., Selvarajan, V., Deshmukh, R.R., Gao, C., (2009) Appl. Surf. Sci., 255, p. 3965; Pandiyaraj, K., Selvarajan, V., Deshmukh, R.R., Gao, C., (2009) Vacuum, 83, p. 332; Tavares, C.J., Marques, S.M., Rebouta, L., Lanceros-Méndez, S., Sencadas, V., Costa, C.M., Alves, E., Fernandes, A.J., (2008) Thin Solid Films, 517, p. 1161; Eom, J.S., Kim, S.H., (2008) Thin Solid Films, 516, p. 4530; Di Mundo, R., De Benedictis, V., Palumbo, F., D'Agostino, R., (2009) Appl. Surf. Sci., 255, p. 5461; Özenbas, M., Tan, C., (1986) J. Cryst Growth, 78, p. 519; Goddard, J.M., Hotchkiss, J.H., (2007) Prog. Potym. Sci., 32, p. 698; Nathawat, R., Kumar, A., Kulshrestha, V., Vijay, Y.K., Kobayashi, T., Kanjilal, D., (2008) Nuel. Instrum. Methods Phys. Res. B, 266, p. 4749; Shin, Y.N., Kim, B.S., Ahn, H.H., Lee, J.H., Kim, K.S., Lee, J.Y., Kim, M.S., Lee, H.B., (2008) Appl. Surf. Sci., 255, p. 293; Lisboa, P., Gilliland, D., Ceccone, G., Valsesia, A., Rossi, F., (2006) Appl. Surf. Sci., 252, p. 4397; Muck, A., Svatos, A., (2007) Talanta, 74, p. 333; Sandoval-Paz, M.G., Ramirez-Bon, R., (2008) Thin Solid Films, 517, p. 6747; Park, S.K., Han, J.I., Kim, W.K., Kwak, M.G., (2001) Thin Solid Films, 397, p. 49; Pihan, S.A., Tsukruk, T., Förch, R., (2009) Surf. Coat. Technol., 13, p. 1856; Dayss, E., Leps, G., Meinhardt, J., (1999) Surf. Coat Teehnol., 116, p. 986; Pandiyaraj, K.N., Selvarajan, V., Deshmukh, R.R., Bousmina, M., (2008) Surf. Coat Teehnol., 202, p. 4218; Cheng, C., Liye, Z., Zhan, R.-J., (2006) Surf. Coat Teehnol., 200, p. 6659; Lai, J., Sunderland, B., Xue, J., Yan, S., Zhao, W., Folkard, M., Michael, B.D., Wang, Y., (2006) Appl. Surf. Sci., 252, p. 3375; Phenton, M.J., Lovell-Hoare, M.C., Stevens, G.C., (2001) J. Phys. D: Appl. Phys., 34, p. 2754; Ozeki, K., Hirakuri, K.K., (2008) Appl. Surf. Sci., 254, p. 1614; Vallon, S., Drévillon, B., Poncin-Epaillard, F., KlembergSapieha, J.E., Martinu, L., (1996) J. Vac. Sci. Teehnol. A, 14, p. 3194; Mirabedini, S.M., Arabi, H., Salem, A., Asiaban, S., (2007) Prog. Org. Coat., 60, p. 105; Kogelschatz, U., Elliason, B., Egli, W., (1999) Pure Appl. Chem., 71, p. 1819; Dorai, R., Kushner, M.J., (2003) J. Phys. D: Appl. Phys., 36, p. 666; Corval, G.J., Gray, D.G., Goring, D.A.I., (1976) J. Polym. Sci., Polym. Lett, 14, p. 231; Guimond, S., Radu, I., Czeremuszkin, G., Caisson, D.J., Wertheimer, M.R., (2002) Plasmas Polym., 7, p. 71; Guimond, S., Radu, I., Czeremuszkin, G., Wertheimer, M.R., (2002) Proc. 8th Int. Symp. High Pressure Low Temp. Plasma Chem., p. 400. , Pühajärve, Estland; Kogelschatz, U., Elliason, B., Egli, W., (1999) Pure Appl. Chem., 71, p. 1819; Cho, J.-S., Kim, K.-H., Han, S., Beag, Y.-W., Koh, S.-K., (2003) Prog. Org. Coat., 48, p. 251; Baek, J.-Y., An, J.-H., Choi, J.-M., Park, K.-S., Lee, S.-H., (2008) Sens. Actuators A, 143, p. 423; Gruetzmann, A., Hansen, S., Müller, J., (2007) Physiol Meas., 28, p. 1375; Ribeiro, E., Malczyk, A., Carvalho, S., Rebouta, L., Fernandes, I.V., Alves, E., Miranda, A.S., (2002) Surf. Coat. Teehnol, 151-152, p. 515; Sharma, R., Holcomb, E., Trigwell, S., Mazumder, M., (2007) J. Electrostat., 65, p. 269; Cunha, L.T., Pedrosa, P., J.Tavares, C., Alves, E., Vaz, F., Fonseca, C., (2009) Electrochim. Acta, 55, p. 59; Müller, D.J.M., Janovjak, H., Lehto, T., Kuerschner, L., Anderson, K., (2002) Prog. Biophys. Mol. Biol., 79, p. 1; Wolansky, G., Marmur, A., (1999) Colloids Surf. A, 156, p. 381; Mohamed, S.H., Kappertz, O., Ngaruiya, J.M., Niemeier, T., Drese, R., Wakkad, M., Wuttig, M., (2004) Phys. Stat. Sol., 202, p. 90; Carrino, L., Moroni, G., Polini, W., (2002) J. Mater. Proc. Technol., 121, p. 373
Keywords: Activation treatment; Adhesion; Ar plasmas; biomedical electrodes; Deposition; Electrodes; Functional polymers; Plasma surface modifications; Plasma treatment; Plasma treatments; Plasmas; Polymers; Propylene; Surface changes; Surface modification; Surface plasma treatment; Thin layers; TiN films; Titanium nitride

Protein matrices for improved wound healing: Elastase inhibition by a synthetic peptide model - Vasconcelos, A.; Pêgo, A.P.; Henriques, L.; Lamghari, M.; Cavaco-Paulo, A. (BiomacromoleculesBiomacromolecules, 2010)
The unique properties of silk fibroin were combined with keratin to develop new wound-dressing materials. Silk fibroin/keratin (SF/K) films were prepared to reduce high levels of elastase found on chronic wounds. This improved biological function was achieved by the incorporation of a small peptide synthesized based on the reactive-site loop of the Bowman-Birk Inhibitor (BBI) protein. In vitro degradation and release were evaluated using porcine pancreatic elastase (PPE) solution as a model of wound exudate. It was found that biological degradation and release rate are highly dependent on film composition. Furthermore, the level of PPE activity can be tuned by changing the film composition, thus showing an innovative way of controlling the elastase-antielastase imbalance found on chronic wounds. © 2010 American Chemical Society.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm100537bPubMed ID: 20690591Language of Original Document: EnglishCorrespondence Address: Vasconcelos, A.; Universidade Do Minho, Departamento de Engenharia Têxtil, Campus de Azurém, 4800-058 Guimarães, Portugal; email: andreiav@det.uminho.ptChemicals/CAS: Bowman Birk inhibitor, 37330-34-0; Fibroins, 9007-76-5; Keratins, 68238-35-7; Pancreatic Elastase, 3.4.21.36; Peptide Fragments; Trypsin Inhibitor, Bowman-Birk Soybean; Trypsin Inhibitors; fibroin, silkwormReferences: Boateng, J.S., Matthews, K.H., Stevens, H.N.E., Eccleston, G.M., Wound healing dressings and drug delivery systems: A review (2008) J. Pharm. Sci., 97, pp. 2892-2923;Rothe, M., Falanga, V., Growth factors: Their biology and promise in dermatologic diseases and tissue repair (1989) AMA Arch. Dermatol., 125, pp. 1390-1398; Shakespeare, P., Burn wound healing and skin substitutes (2001) Burns, 27, pp. 517-522; Martin, C.R., Wound infection: A failure of wound healing caused by an imbalance of bacteria (1997) Surg. Clin. North Am., 77, pp. 637-650; Stadelmann, W.K., Digenis, A.G., Tobin, G.R., Physiology and healing dynamics of chronic cutaneous wounds (1998) Am. J. Surg., 176, pp. 26S-38S; Eaglstein Wh, F.V., Chronic wounds (1997) Surg. Clin. North Am., 77, pp. 689-700; Gray, D.W.R., The wound exudate continuum: An aid to wound assessment (2004) Wounds U.K.: Appl. Wound Manageme. Suppl., pp. 19-21; Chen, W.Y.J., Rogers, A.A., Lydon, M.J., Characterization of biologic properties of wound fluid collected during early stages of wound healing (1992) J. Invest. Dermatol., 99, pp. 559-564; Brooke, B., Edward, J.C., Caroline, A.O., Leukocyte proteinases in wound healing: Roles in physiologic and pathologic processes (1999) Wound Repair Regener., 7, pp. 410-422; Dorne, R.Y., Benedict, C.N., The proteolytic environment of chronic wounds (1999) Wound Repair Regener., 7, pp. 433-441; Naomi, J.T., Michael, C.S., Shawn, M., Neil, B., Jane, G., Frank, B., Gillian, M., Gregory, S., Analysis of the acute and chronic wound environments: The role of proteases and their inhibitors (1999) Wound Repair Regener., 7, pp. 442-452; Enoch, S., Leaper, D.J., Basic science of wound healing (2008) Surgery (Oxford), 26, pp. 31-37; Chufa, H., Margaret, A.H., George, W.C., Frank, A., Effects of chronic wound fluid on the bioactivity of platelet-derived growth factor in serum-free medium and its direct effect on fibroblast growth (1999) Wound Repair Regener., 7, pp. 97-105; Chen, P., Rose, J., Love, R., Wei, C.H., Wang, B.C., Reactive sites of an anticarcinogenic Bowman-Birk proteinase inhibitor are similar to other trypsin inhibitors (1992) J. Biol. Chem., 267, pp. 1990-1994; Werner, M.H., Wemmer, D.E., Three-dimensional structure of soybean trypsin/chymotrypsin Bowman-Birk inhibitor in solution (1992) Biochemistry, 31, pp. 999-1010; Guangda, L.I.N., Wolfram, B., Robert, H., Chengwu, C.H.I., Richard, A.E., The 0.25-nm X-ray structure of the Bowman-Birk-type inhibitor from mung bean in ternary complex with porcine trypsin (1993) Eur. J. Biochem., 212, pp. 549-555; Voss, R.-H., Ulrich, E., Lars-Oliver, E., Gabriele, W., Young-Mi, K., Peter, F., Crystal structure of the bifunctional soybean Bowman-Birk inhibitor at 0.28-nm resolution (1996) Eur. J. Biochem., 242, pp. 122-131; Wolfram, B., Robert, H., Natural protein proteinase inhibitors and their interaction with proteinases (1992) Eur. J. Biochem., 204, pp. 433-451; Laskowski, M., Qasim, M.A., What can the structures of enzyme-inhibitor complexes tell us about the structures of enzyme substrate complexes (2000) Biochim. Biophys. Acta, Protein Struct. Mol. Enzymol., 1477, pp. 324-337; McBride, J.D., Leatherbarrow, R.J., Synthetic peptide mimics of the Bowman-Birk inhibitor protein (2001) Curr. Med. Chem., 8, pp. 909-917; Jeffrey, D.M., Emma, M.W., Arnd, B.E.B., Agnès, M.J., Robin, J.L., Peptide mimics of the Bowman-Birk inhibitor reactive site loop (2002) Pept. Sci., 66, pp. 79-92; Vasconcelos, A., Freddi, G., Cavaco-Paulo, A., Biodegradable materials based on silk fibroin and keratin (2008) Biomacromolecules, 9, pp. 1299-1305; Ritger, P.L., Peppas, N.A., A simple equation for description of solute release II. Fickian and anomalous release from swellable devices (1987) J. Controlled Release, 5, pp. 37-42; Tanaka, H., Shimazu, T., Sugimoto, H., Yoshioka, T., Sugimoto, T., A sensitive and specific assay for granulocyte elastase in inflammatory tissue fluid using l-pyroglutamyl-l-prolyl-l-valine-p-nitroanilide (1990) Clin. Chim. Acta, 187, pp. 173-180; Yamauchi, K., Maniwa, M., Mori, T., Cultivation of fibroblast cells on keratin-coated substrata (1998) J. Biomater. Sci., Polym. Ed., 9, pp. 259-270; Li, M., Ogiso, M., Minoura, N., Enzymatic degradation behavior of porous silk fibroin sheets (2003) Biomaterials, 24, pp. 357-365; Minoura, N., Aiba, S., Higuchi, M., Gotoh, Y., Tsukada, M., Imai, Y., (1995) Biochem. Biophys. Res. Commun., 208, p. 511; Yamauchi, K., Hojo, H., Yamamoto, Y., Tanabe, T., Enhanced cell adhesion on RGDS-carrying keratin film (2003) Mater. Sci. Eng., C, 23, pp. 467-472; Roh, D.-H., Kang, S.-Y., Kim, J.-Y., Kwon, Y.-B., Young Kweon, H., Lee, K.-G., Park, Y.-H., Lee, J.-H., Wound healing effect of silk fibroin/alginate-blended sponge in full thickness skin defect of rat (2006) J. Mater. Sci.: Mater. Med., 17, pp. 547-552; Lu, S., Wang, X., Lu, Q., Hu, X., Uppal, N., Omenetto, F.G., Kaplan, D.L., Stabilization of Enzymes in Silk Films (2009) Biomacromolecules, 10, pp. 1032-1042; Hofmann, S., Wong Po Foo, C.T., Rossetti, F., Textor, M., Vunjak-Novakovic, G., Kaplan, D.L., Merkle, H.P., Meinel, L., Silk fibroin as an organic polymer for controlled drug delivery (2006) J. Controlled Release, 111, pp. 219-227; Numata, K., Cebe, P., Kaplan, D.L., Mechanism of enzymatic degradation of beta-sheet crystals (2010) Biomaterials, 31, pp. 2926-2933; Shudong, W., Youzhu, Z., Guibo, Y., Hongwei, W., Zhihui, D., Electrospun polylactide/silk fibroin-gelatin composite tubular scaffolds for small-diameter tissue engineering blood vessels (2009) J. Appl. Polym. Sci., 113, pp. 2675-2682; Motta, A., Migliaresi, C., Faccioni, F., Torricelli, P., Fini, M., Giardino, R., Fibroin hydrogels for biomedical applications: Preparation, characterization and in vitro cell culture studies (2004) J. Biomater. Sci., Polym. Ed., 15, p. 851; Bondar, B., Fuchs, S., Motta, A., Migliaresi, C., Kirkpatrick, C.J., Functionality of endothelial cells on silk fibroin nets: Comparative study of micro-and nanometric fibre size (2008) Biomaterials, 29, pp. 561-572; Fuchs, S., Motta, A., Migliaresi, C., Kirkpatrick, C.J., Outgrowth endothelial cells isolated and expanded from human peripheral blood progenitor cells as a potential source of autologous cells for endothelialization of silk fibroin biomaterials (2006) Biomaterials, 27, pp. 5399-5408; Unger, R.E., Wolf, M., Peters, K., Motta, A., Migliaresi, C., James Kirkpatrick, C., Growth of human cells on a non-woven silk fibroin net: A potential for use in tissue engineering (2004) Biomaterials, 25, pp. 1069-1075; Huang, Y., Yu, H., Xiao, C., PH-sensitive cationic guar gum/poly(acrylic acid) polyelectrolyte hydrogels: Swelling and in vitro drug release (2007) Carbohydr. Polym., 69, pp. 774-783; Edwards, J.V., Alvin, F.B., Sarah, B., Abul, J.U., Kelman, C.I., Robert, F.D., Steven, J.M., Inhibition of elastase by a synthetic cotton-bound serine protease inhibitor: In vitro kinetics and inhibitor release (1999) Wound Repair Regener., 7, pp. 106-118; Schneider, A., Wang, X.Y., Kaplan, D.L., Garlick, J.A., Egles, C., Biofunctionalized electrospun silk mats as a topical bioactive dressing for accelerated wound healing (2009) Acta Biomater., 5, pp. 2570-2578; Gariani, T., McBride, J.D., Leatherbarrow, R.J., The role of the P2′ position of Bowman-Birk proteinase inhibitor in the inhibition of trypsin: Studies on P2′ variation in cyclic peptides encompassing the reactive site loop (1999) Biochim. Biophys. Acta, Protein Struct. Mol. Enzymol., 1431, pp. 232-237; Zablotna, E., Kazmierczak, K., Jaskiewicz, A., Stawikowski, M., Kupryszewski, G., Rolka, K., Chemical synthesis and kinetic study of the smallest naturally occurring trypsin inhibitor SFTI-1 isolated from sunflower seeds and its analogues (2002) Biochem. Biophys. Res. Commun., 292, pp. 855-859
Keywords: animal cell; Animals; article; Atomic force microscopy; Biodegradation; Biological degradation; Biological functions; biomaterial; Bombyx; Bowman Birk inhibitor; Bowman-Birk inhibitors; cell proliferation; Chronic wounds; controlled study; Cytotoxicity test; Degradation; Elastase; elastase inhibitor; enzyme activity; Enzyme inhibition; Fibroins; Film composition; In-vitro; keratin; Keratins; mass spectrometry; materials testing; Mice; Microscopy, Atomic Force; NIH 3T3 Cells; nonhuman; pancreatic elastase; Peptide Fragments; Peptides; priority journal; protein binding; Protein matrices; Release rate; Silk; Silk fibroin; Spectrometry, Mass, Electrospray Ionization; Sus; Swine; Synthetic peptide; Trypsin Inhibitor, Bowman-Birk Soybean; Trypsin Inhibitors; wound fluid; Wound healing

Segmentation of the carotid intima-media region in B-mode ultrasound images - Rocha, R.; Campilho, A.; Silva, J.; Azevedo, E.; Santos, R. (Image and Vision ComputingImage Vision Comput, 2010)
This paper proposes a new approach for the segmentation of both near-end and far-end intima-media regions of the common carotid artery in ultrasound images. The method requires minimal user interaction and is able to segment the near-end wall in arteries with large, hypoechogenic and irregular plaques, issues usually not considered previously due to the increased segmentation difficulty. The adventitia is detected by searching for the best fit of a cubic spline to edges having features compatible with the adventitia boundary. The algorithm uses a global smoothness constraint and integrates discriminating features of the adventitia to reduce the attraction by other edges. Afterwards, using the information of the adventitia location, the lumen boundary is detected by combining dynamic programming, smooth intensity thresholding surfaces and geometric snakes. Smooth contours that correctly adapt to the intima are produced, even in the presence of deep concavities. Moreover, unlike balloon-based snakes, the propagation force does not depend on gradients and does not require a predefined direction. An extensive statistical evaluation is computed, using a set of 47 images from 24 different symptomatic patients, including several classes, sizes and shapes of plaques. Bland-Altman plots of the mean intima-media thickness, for manual segmentations of two medical experts, show a high intra-observer and inter-observer agreement, with mean differences close to zero (mean between -0.10 mm and 0.18 mm) and with the large majority of differences within the limits of agreement (standard deviation between 0.10 mm and 0.12 mm). Similar plots reveal a good agreement between the automatic and the manual segmentations (mean between -0.07 mm and 0.11 mm and standard deviation between 0.11 mm and 0.12 mm). © 2009 Elsevier B.V. All rights reserved.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: IVCODdoi: 10.1016/j.imavis.2009.09.017Language of Original Document: EnglishCorrespondence Address: Rocha, R.; INEB - Inst. de Eng. Biomédica, Divisão de Sinal e Imagem, Campus FEUP, 4200-465 Porto, Portugal; email: rhr@isep.ipp.ptReferences: O'Leary, D., Polak, J., Kronmal, R., Manolio, T., Burke, G., Wolfson Jr., S., Carotid-artery intima and media thickness as a risk factor for myocardial infarction and stroke in older adults (1999) New Engl. J. Med., 340, pp. 14-22;Hodis, H., Mack, W., LaBree, L., Selzer, R., Liu, C., Liu, C., Azen, S., The role of carotid arterial intima-media thickness in predicting clinical coronary events (1998) Ann. Intern. Med., 128 (4), pp. 262-269; Kern, R., Szabo, K., Hennerici, M., Meairs, S., Characterization of carotid artery plaques using real-time compound B-mode ultrasound (2004) Stroke, 35, pp. 870-875; Ellis, S.M., Naoumova, R.P., Neuwirth, C.K., Eckersley, R., Cosgrove, D.O., Thompson, G.R., Sidhu, P.S., Measurement of the reflectivity of the intima-medial layer of the common carotid artery improves the discriminatory value of intima-medial thickness measurement as a predictor of risk of atherosclerotic disease (2007) Ultrasound Med. Biol., 33 (7), pp. 1029-1038; Graf, I.M., Schreuder, F.H.B.M., Hameleers, J.M., Mess, W.H., Reneman, R.S., Hoeks, A.P.G., Wall irregularity rather than intima-media thickness is associated with nearby atherosclerosis (2009) Ultrasound Biol. Med., 35 (6), pp. 955-961; Baldassarre, D., Amato, M., Bondioli, A., Sirtori, C.R., Tremoli, E., Carotid artery intima-media thickness measured by ultrasonography in normal clinical practice correlates well with atherosclerosis risk factors (2000) Stroke, 31, pp. 2426-2430; Halenka, M., Noninvasive measurement of early atherosclerosis by high-resolution B-mode ultrasonography (1999) Acta Univ. Palacki. Olomu. Fac. Med., 142, pp. 7-12; Rocha, R., (2007) Image Segmentation and Reconstruction of 3D Surfaces from Carotid Ultrasound Images, , http://www.ineb.fe.up.pt/bmivic, Ph.D. thesis, Faculdade de Engenharia da Universidade do Porto, Porto July; Gee, A., Prager, R., Treece, G., Berman, L., Engineering a freehand 3D ultrasound system (2003) Pattern Recogn. Lett., 24 (4-5), pp. 757-777; Sonka, M., Liang, W., Stefancik, R., Stolpen, A., Handbook of Medical Imaging: Medical Image Processing and Analysis (2000) SPIE, 2; Yu, Y., Acton, S., Speckle reducing anisotropic diffusion (2002) IEEE Trans. Image Process., 11 (11), pp. 1260-1270; Yu, Y., Acton, S., Edge detection in ultrasound imagery using the instantaneous coefficient of variation (2004) IEEE Trans. Image Process., 13 (12), pp. 1640-1655; Thijssen, J.M., Ultrasonic speckle formation, analysis and processing applied to tissue characterization (2003) Pattern Recogn. Lett., 24 (4-5), pp. 659-675; Loizou, C.P., Pattichis, C.S., Christodoulou, C.I., Istepanian, R.S.H., Pantziaris, M., Nicolaides, A., Comparative evaluation of despeckle filtering in ultrasound imaging of the carotid artery (2005) IEEE Trans. Ultrason. Fer. Freq. Control, 52 (10), pp. 1653-1669; Chan, K.L., Ultrasonic tissue characterization using fractal feature (1993) IEE Conf. Acoustic Sensing and Imaging, 369, pp. 183-188; Touboul, P.J., Prati, P., Scarabin, P.-Y., Adrai, V., Thibout, E., Ducimetiere, P., Use of monitoring software to improve the measurement of carotid wall thickness by B-mode imaging (1992) J. Hypertens., 10 (5), pp. 37-41; Gariepy, J., Massonneau, M., Levenson, J., Heudes, D., Simon, A., the Groupe de prevention cardio-vasculaire en medecine du travail, evidence for in vivo carotid and femoral wall thickness in human hypertension (1993) J. Hypertens., 22 (1), pp. 111-118; Selzer, R.H., Hodis, H.N., Kwong-Fu, H., Mack, W.J., Lee, P.L., Liu, C.R., Liu, C.H., Evaluation of computerized edge tracking for quantifying intima-media thickness of the common carotid artery from B-mode ultrasound images (1994) Atherosclerosis, 111, pp. 1-11; Gustavsson, T., Liang, Q., Wendelhag, I., Wikstrand, J., A dynamic programming procedure for automated ultrasonic measurement of the carotid artery (1994) Comput. Cardiol.; Wendelhag, I., Liang, Q., Gustavsson, T., Wikstrand, J., A new automated computerized analyzing system simplifies readings and reduces the variability in ultrasound measurement of intima-media thickness (1997) Stroke, 28, pp. 2195-2200; Automatic detection of the intimal and the adventitial layers of the common carotid artery wall in ultrasound Bmode images using snakes, in: International Conference on Image Analysis and Processing, B. Werer, 1999, pp. 452-457Liang, Q., Wendelhag, I., Wikstrand, J., Gustavsson, T., A multiscale dynamic programming procedure for boundary detection in ultrasound artery images (2000) IEEE Trans. Med. Imag., 19 (2), pp. 127-142; Selzer, R.H., Mack, W.J., Lee, P.L., Kwong-Fu, H., Hodis, H.N., Improved common carotid elasticity and intima-media thickness measurements from computer analysis of sequential ultrasound frames (2001) Atherosclerosis, 154 (1), pp. 185-193; Schmidt-Trucksass, A., Cheng, D., Sandrock, M., Schulte-Monting, J., Rauramaa, R., Huonker, M., Burkhardt, H., Computerized analysing system using the active contour in ultrasound measurement of carotid artery intima-media thickness (2001) Clin. Physiol., 5, pp. 561-569; Cheng, D., Schmidt-Trucksass, A., Cheng, K., Burkhardt, H., Using snakes to detect the intimal and adventitial layers of the common carotid artery wall in sonographic images (2002) Comput. Methods Programs Biomed., 67, pp. 27-37; Stein, J.H., Korcarz, C.E., Mays, M.E., Douglas, P.S., Palta, M., Zhang, H., LeCaire, T., Fan, L., A semiautomated ultrasound border detection program that facilitates clinical measurement of ultrasound carotid intima-media thickness (2005) J. Am. Soc. Echocardiogr., 18 (3), pp. 244-251; Loizou, C.P., Pattichis, C.S., Pantziaris, M., Tyllis, T., Nicolaides, A., Snakes based segmentation of the common carotid artery intima media (2007) Med. Bio. Eng. Comput., 45, pp. 35-49; Yanowitz, S.D., Bruckstein, A.M., A new method for image segmentation (1989) Comput. Graph. Image Process., 46, pp. 82-95; Chan, T., Vese, L., Active contours without edges (2001) IEEE Trans. Image Process., 10 (2), pp. 266-277; Vese, L.A., Chan, T.F., A multiphase level set framework for image segmentation using the Mumford and Shah model (2002) Int. J. Comput. Vision, 50 (3), pp. 271-293; Fischler, M.A., Bolles, R.C., Random sample consensus: a paradigm for model fitting with applications to image analysis and automated cartography (1981) Commun. ACM, 24 (6), pp. 381-395; Zack, G.W., Rogers, W.E., Latt, S.A., Automatic measurement of sister chromatid exchange frequency (1977) J. Histochem. Cytochem., 25 (7), pp. 741-753; Canny, J., A computational approach to edge detection (1986) IEEE Trans. Pattern Anal. Mach. Intell., 8 (6), pp. 679-698; Rudin, L., Osher, S., Fatemi, E., Nonlinear total variation based noise removal algorithms (1992) Proceedings of the Eleventh Annual International Conference of the Center for Nonlinear Studies on Experimental Mathematics: Computational Issues in Nonlinear Science, pp. 259-268. , Elsevier North-Holland, Inc; Rudin, L., Osher, S., Total variation based image restoration with free local constraints (1994) Proceedings of IEEE International Conference on Image Processing (ICIP'94), 1, pp. 31-35; Sethian, J.A., (1999) Level Set Methods and Fast Marching Methods, , Cambridge University Press; Osher, S., Fedkiw, R., (2003) Level Set Methods and Dynamic Implicit Surfaces, , Springer-Verlag, New York; Mumford, D., Shah, J., Optimal approximations by piecewise smooth functions and associated variational problems (1989) Commun. Pure Appl. Math., 42 (5), pp. 577-685; Burden, R., Faires, J.D., (2000) Numerical Analysis, , Brooks Cole; Breu, H., Gil, J., Kirkpatrick, D., Werman, M., Linear time Euclidean distance transform algorithms (1995) IEEE Trans. Pattern Anal. Mach. Intell., 17 (5), pp. 529-533; Bland, J.M., Altman, D.G., Statistical methods for assessing agreement between two methods of clinical measurement (1986) Lancet, 1 (8476), pp. 307-310; Loizou, C.P., Pattichis, C.S., Pantziaris, M., Nicolaides, A., An integrated system for the segmentation of atherosclerotic carotid plaque (2007) IEEE Trans. Info. Tech. Biomed., 11 (6), pp. 661-667; de Boor, C., (1978) A Practical Guide to Splines, , Springer-Verlag; Unser, M., Splines: a perfect fit for signal and image processing (1999) IEEE Signal Processing Magazine, 16 (6), pp. 22-38; Yang, Z., Tuthill, T.A., Raunig, D.L., Fox, M.D., Analoui, M., Pixel compounding: resolution-enhanced ultrasound imaging for quantitative analysis (2007) Ultrasound Med. Biol., 33 (8), pp. 1309-1319
Keywords: Acoustic waves; B-mode ultrasound images; Best fit; Carotid; Common carotid artery; Cubic spline; Digital image storage; Dynamic programming; Edge detection; End-wall; Function evaluation; Geometric snake; Geometric snakes; Image segmentation; Intima-media thickness; Manual segmentation; Medical experts; New approaches; Smoothness constraints; Standard deviation; Statistical evaluation; statistics; Thresholding; Ultrasonics; Ultrasound image; Ultrasound images; User interaction

Synthesis and characterization of HAp nanorods from a cationic surfactant template method - Coelho, J.M.; Moreira, J.A.; Almeida, A.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2010)
Hydroxyapatite (HAp) [Ca 10(PO 4) 6(OH) 2] nanorods were synthesized using a surfactant templating method, with cetyltrimethylammonium bromide (CTAB) micelles acting as template for HAp growth. The effects of the sintering temperature on the morphological and crystallographic characteristics and on chemical composition of the "as-prepared" structures are discussed. The experimental results show that low heat-treatment temperatures are preferred in order to obtain high quality nanorods, with diameters ranging between 20 and 50 nm. High heat-treatment temperatures enhance the thermal decomposition of HAp into other calcium phosphate compounds, and the sintering of particles into micrometer ball-like structures. The stability of aqueous suspensions of HAp nanorods is also discussed. © 2010 Springer Science+Business Media, LLC.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-010-4122-5PubMed ID: 20623177Language of Original Document: EnglishCorrespondence Address: Moreira, J. A.; IFIMUP, IN-Institute of Nanoscience and Nanotechnology, Universidade Do Porto, Rua do Campo Alegre 687, Porto 4169-007, Portugal; email: jamoreir@fc.up.ptChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; Cations; Cetrimonium Compounds; Surface-Active Agents; cetrimonium, 6899-10-1References: Rao, C.N.R., Cheetham, A.K., Materials science at the nanoscale (2006) Nanomaterials Handbook, pp. 1-2. , Y. Gogotsi (eds). CRC Press, Taylor & Francis Group New York;Guo, Y., Shi, D., Lian, J., Zdw, W., Cho, H., Liu, G., Quantum dot conjugated hydroxylapatite nanoparticles for in vivo imaging (2008) Nanotechnology, 19, 6p. , 175102; Queiroz, A.C., Teixeira, S., Santos, J.D., Monteiro, F.J., Production of porous hydroxyapatite with potential for controlled drug delivery (2004) Mater Sci Forum, 455-456, pp. 358-360. , 10.4028/www.scientific.net/MSF.455-456.358; Vallet-Regi, M., Ceramics for medical applications (2001) Journal of the Chemical Society, Dalton Transactions, (2), pp. 97-108. , DOI 10.1039/b007852m; Dorozhkin, S.V., Epple, M., Biological and medical significance of calcium phosphates (2002) Angewandte Chemie - International Edition, 41 (17), pp. 3130-3146. , DOI 10.1002/1521-3773(20020902)41:17<3130::AID-ANIE3130>3.0.CO;2-1; Ferraz, M.P., Monteiro, F.J., Manuel, C.M., Hydroxyapatite nanoparticles: A review of preparation methodologies (2004) J Appl Biomater Biomech, 2, pp. 74-80. , 1:CAS:528:DC%2BD2cXnvFWiurk%3D; Cengiz, B., Gokce, Y., Yildiz, N., Aktas, Z., Calimi, A., Synthesis and characterization of hydroxyapatite nanoparticles (2008) Colloids Surf A Physichochem Eng Aspects, 322, pp. 29-33. , 1:CAS:528:DC%2BD1cXmt1OqtbY%3D 10.1016/j.colsurfa.2008.02.011; Ying, J.Y., Mehnert, P.C., Wong, M.S., Synthesis and application of supramolecular-templated mesoporous materials (1999) Angew Chem Int Ed, 38, pp. 56-77. , 1:CAS:528:DyaK1MXpsValtg%3D%3D 10.1002/(SICI)1521-3773(19990115)38:1/ 2<56::AID-ANIE56>3.0.CO;2-E; Cates, M.E., Fielding, S.M., Rheology of giant micelles (2006) Advances in Physics, 55 (7-8), pp. 799-879. , DOI 10.1080/00018730601082029, PII T6J4U87W3G5RTN2J; Nagarajan, R., Molecular thermodynamics of giant micelles (2007) Giant Micelles-properties and Applications, pp. 2-5. , R. Zana E.W. Kaler (eds). CRC Pess, Taylor & Francis Group New York; Li, Y., Tjandra, W., Tam, K.C., Synthesis of nanoporous hydroxyapatite using cationic surfactants as templates (2008) Mater Res Bull, 43, pp. 2318-2326. , 1:CAS:528:DC%2BD1cXnsVSrtr4%3D 10.1016/j.materresbull.2007.08.008; Yao, J., Tjandra, W., Chen, Y.Z., Tam, K.C., Mab, J., Soh, B., Hydroxyapatite nanostructure material derived using cationic surfactant as a template (2003) J Mater Chem, 13, pp. 3053-3057. , 1:CAS:528:DC%2BD3sXptlemsro%3D 10.1039/b308801d; Berret, J.F., Rheology of wormlike micelles: Equilibrium properties and shear banding transition (2006) Molecular Gels. Materials with Self-assembled Fibrillar Networks, pp. 667-720. , R.G. Weiss P. Terech (eds). Springer Dordrecht; Kresge, C.T., Leonowicz, M.E., Roth, W.J., Vartuli, J.C., Beck, J.S., Ordered mesoporous molecular sieves synthesized by a liquid-crystal template mechanism (1992) Nature, 359 (6397), pp. 710-712. , DOI 10.1038/359710a0; Beck, J.S., Vartuli, J.C., Roth, W.J., Leonowicz, M.E., Kresge, C.T., Schmitt, K.D., A new family of mesoporous molecular sieves prepared with liquid crystal templates (1992) J Am Chem Soc, 114, pp. 10834-10843. , 1:CAS:528:DyaK38Xms1entr8%3D 10.1021/ja00053a020; Li, Y.Y., Li, J., Nakajima, B., Nanostructured porous biomaterials for controlled drug release systems (2008) Biomaterials-fabrication and Processing, pp. 196-206. , K.C. Paul L. Xuanyong (eds). CRC Press, Taylor & Francis Group New York. 10.1201/9780849379741; Herzberg, G., (1945) The Infrared and Raman Spectra of Poliatomic Molecules, , D van Nostrand Company, Inc. New York; Awonusi, A., Morris, M.D., Tecklenburg, M.M.J., Carbonate assignment and calibration in the Raman spectrum of apatite (2007) Calcified Tissue International, 81 (1), pp. 46-52. , DOI 10.1007/s00223-007-9034-0; Fowler, B.O., Infrared studies of apatites. I. Vibrational assignments for calcium, strontium, and barium hydroxyapatites utilizing isotopic substitution (1974) Inorg Chem, 13, pp. 194-207. , 1:CAS:528:DyaE2cXlsVWktw%3D%3D 10.1021/ic50131a039; Aza, P.N., Santos, C., Pazo, A., Aza, S., Cuscó, R., Artus, L., Vibrational properties of calcium phospate coumpounds. 1. Raman spectrum of β-tricalcium phosphate (1997) Chem Mater, 9, pp. 912-915. , 10.1021/cm960425d
Keywords: Ammonium compounds; Aqueous suspensions; article; Bromine compounds; Calcium; calcium phosphate; cationic surfactant; Cationic surfactants; Cations; Cetrimonium Compounds; Cetyltrimethylammonium bromide; chemical composition; Chemical compositions; Chemical structure; Crystallographic characteristics; Dyes; Heat treatment temperature; High quality; hydroxyapatite; Microscopy, Electron, Scanning; Microscopy, Electron, Transmission; nanorod; Nanorods; Nanotubes; Phosphate compounds; priority journal; Pyrolysis; Scanning electron microscopy; Sintering; Sintering temperatures; Surface-Active Agents; Surfactant template method; Surfactant templating; Suspensions (fluids); synthesis; Synthesis and characterizations; Thermal decompositions; X-Ray Diffraction

TNF-α regulates the effects of irradiation in the mouse bone marrow microenvironment - Cachaço, A.S.; Carvalho, T.; Santos, A.C.; Igreja, C.; Fragoso, R.; Rio, C.O.; Ferreira, M.; Serpa, J.; Correia, S.; Pinto-Do-Ó, P.; Dias, S. (PLoS ONEPLoS ONE, 2010)
Background: Secondary bone marrow (BM) myelodysplastic syndromes (MDS) are increasingly common, as a result of radio or chemotherapy administered to a majority of cancer patients. Patients with secondary MDS have increased BM cell apoptosis, which results in BM dysfunction (cytopenias), and an increased risk of developing fatal acute leukemias. In the present study we asked whether TNF-α, known to regulate cell apoptosis, could modulate the onset of secondary MDS. Principal Findings:We show that TNF-α is induced by irradiation and regulates BM cells apoptosis in vitro and in vivo. In contrast to irradiated wild type (WT) mice, TNF-α deficient (TNF-α KO) mice or WT mice treated with a TNF-α-neutralizing antibody were partially protected from the apoptotic effects of irradiation. Next we established a 3-cycle irradiation protocol, in which mice were sub-lethally irradiated once monthly over a 3 month period. In this model, irradiated WT mice presented loss of microsatellite markers on BM cells, low white blood cell (WBC) counts, reduced megakaryocyte (MK) and platelet levels (thrombocytopenia) and macrocytic anemia, phenoypes that suggest the irradiation protocol resulted in BM dysfunction with clinical features of MDS. In contrast, TNF-α KO mice were protected from the irradiation effects: BM cell apoptosis following irradiation was significantly reduced, concomitant with sustained BM MK numbers and absence of other cytopenias. Moreover, irradiated WT mice with long term (≥5 months) BM dysfunction had increased BM angiogenesis, MMPs and VEGF and NFkB p65, suggestive of disease progression. Conclusion:Taken together, our data shows that TNF-α induction following irradiation modulates BM cell apoptosis and is a crucial event in BM dysfunction, secondary MDS onset and progression. © 2010 Cachaço et al.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusArt. No.: e8980doi: 10.1371/journal.pone.0008980Language of Original Document: EnglishCorrespondence Address: Cachaço, A. S.; Angiogenesis Laboratory, Centro de Investigação em Patobiologia Molecular (CIPM), Instituto Portugues de Oncologia de Francisco Gentil, Lisboa, PortugalChemicals/CAS: vasculotropin, 127464-60-2; vasculotropin A, 489395-96-2; Antibodies, Neutralizing; Matrix Metalloproteinases, 3.4.24.-; Tumor Necrosis Factor-alpha; Vascular Endothelial Growth Factor AReferences: Baud, V., Karin, M., Signal transduction by tumor necrosis factor and its relatives (2001) Trends Cell Biol, 11, pp. 372-377;Balkwill, F., Mantovani, A., Inflammation and cancer: Back to Virchow? (2001) Lancet, 357, pp. 539-345; Lejeune, F.J., Rüegg, C., Recombinant human tumor necrosis factor: An efficient agent for cancer treatment (2006) Bull Cancer, 93 (8), pp. E90-100; Moore, R.J., Owens, D.M., Stamp, G., Arnott, C., Burke, F., Mice deficient in tumor necrosis factor-alpha are resistant to skin carcinogenesis (1999) Nat Med, 5, pp. 828-831; Scott, K.A., Arnott, C.H., Robinson, S.C., Moore, R.J., Thompson, R.G., TNF-alpha regulates epithelial expression of MMP-9 and integrin alphavbeta6 during tumour promotion. A role for TNF-alpha in keratocyte migration? (2004) Oncogene, 23, pp. 6954-6966; Hagemann, T., Robinson, S.C., Schulz, M., Trumper, L., Balkwill, F.R., Enhanced invasiveness of breast cancer cell lines upon co-cultivation with macrophages is due to TNF-alpha dependent up-regulation of matrix metalloproteases (2004) Carcinogenesis, 25 (8), pp. 1543-1549; Yang, W.L., Godwin, A.K., Xu, X.X., Tumor necrosis factor-alpha-induced matrix proteolytic enzyme production and basement membrane remodeling by human ovarian surface epithelial cells: Molecular basis linking ovulation and cancer risk (2004) Cancer Res, 64 (4), pp. 1534-1540; Redondo-Muñoz, J., Escobar-Díaz, E., Samaniego, R., Terol, M.J., García-Marco, J.A., MMP-9 in B-cell chronic lymphocytic leukemia is up-regulated by alpha4beta1 integrin or CXCR4 engagement via distinct signaling pathways, localizes to podosomes, and is involved in cell invasion and migration (2006) Blood, 108 (9), pp. 3143-3151; Rosselli, F., Sancean, J., Gluckman, E., Abnormal lymphokine production: A novel feature of the genetic disease Fanconi anemia. In vitro and in vivo spontaneous overproduction of tumor necrosis factor α (1994) Blood, 83 (5), pp. 1216-1225; Dufour, C., Corcione, A., Svahn, J., Haupt, R., Poggi, V., TNF-alpha and IFN-gamma are overexpressed in the bone marrow of Fanconi anemia patients and TNF-alpha suppresses erythropoiesis in vitro (2003) Blood, 102 (6), pp. 2053-2059; Kuruvilla J, Leitch HA, Vickars LM, Galbraith PF, Li CH, et al. (2003) Aplastic anemia following administration of a tumor necrosis factor-alpha inhibitor. Eur J Haematol 71(5): 396-8. Erratum in: Eur J Haematol. (2004) 72(4):306Hara, T., Ando, K., Tsurumi, H., Moriwaki, H., Excessive production of tumor necrosis factor-alpha by bone marrow T lymphocytes is essential in causing bone marrow failure in patients with aplastic anemia (2004) Eur J Haematol, 73 (1), pp. 10-16; Kerbauy, D.B., Deeg, H.J., Apoptosis and antiapoptotic mechanisms in the progression of myelodysplastic syndromes (2007) Exp Hematol, 35 (11), pp. 1739-1746; Lv, L., Kerzic, P., Lin, G., Schnatter, A.R., Bao, L., The TNF-alpha 238A polymorphism is associated with susceptibility to persistent bone marrow dysplasia following chronic exposure to benzene (2007) Leuk Res, 31 (11), pp. 1479-1485; Boula, A., Voulgarelis, M., Giannouli, S., Katrinakis, G., Psyllaki, M., Effect of cA2 anti.tumor necrosis factor-alpha antibody therapy on hematopoiesis of patients with myelodysplastic syndromes (2006) Clin Cancer Res, 12, pp. 3099-3108; Deeg, H.J., Gotlib, J., Beckham, C., Dugan, K., Holmberg, L., Soluble TNF receptor fusion protein (etanercept) for the treatment of myelodysplastic syndrome: A pilot study (2002) Leukemia, 16 (2), pp. 162-164; Maciejewski JP, Risitano AM, Sloand EM, Wisch L, Geller N, et al. (2002) Br J Haematol 117(1): 119-26. Erratum in: Br J Haematol (2002) 117(4):1002. Ristiano Antonio M [corrected to Risitano Antonio M]De Roos, A.J., Deeg, H.J., Davis, S., A population-based study of survival in patients with secondary myelodysplastic syndromes (MDS): Impact of type and treatment of primary cancers (2007) Cancer Causes Control, 18 (10), pp. 1199-1208; Malcovati, L., Nimer, S.D., Myelodysplastic syndromes: Diagnosis and Staging (2008) Cancer Control, 15 (4 SUPPL.EMENT), pp. 4-13; Haran-Ghera, N., Peled, A., Krautghamer, R., Resnitzky, P., Initiation and promotion in radiation-induced myeloid leukemia (1992) Leukemia, 6 (7), pp. 689-695; Padmanabhan, A., Baker, J.A., Zirpoli, G., Sait, S.N., Ford, L.A., Acute myeloid leukemia and myelodysplastic syndrome following breast cancer: Increased frequency of other cancers and of cancers in multiple family members (2008) Leuk Res, 32 (12), pp. 1820-1823; Zhang, Y., Harada, A., Bluethmann, H., Wang, J.B., Nakao, S., Tumor necrosis factor (TNF) is a physiologic regulator of hematopoietic progenitor cells: Increase of early hematopoietic progenitor cells in TNF receptor p55-deficient mice in vivo and potent inhibition of progenitor cell proliferation by TNF alpha in vitro (1995) Blood, 86 (8), pp. 2930-2937; Rebel, V.I., Hartnett, S., Hill, G.R., Lazo-Kallanian, S.B., Ferrara, J.L., Essential role for the p55 tumor necrosis factor receptor in regulating hematopoiesis at a stem cell level (1999) J Exp Med, 190 (10), pp. 1493-1504; Drutskaya, M.S., Ortiz, M., Liepinsh, D.J., Kuprash, D.V., Nedospasov, S.A., Inhibitory effects of tumor necrosis factor on hematopoiesis seen in vitro are translated to increased numbers of both committed and multipotent progenitors in TNF-deficient mice (2005) Exp Hematol, 33 (11), pp. 1348-1356; Rübe, C.E., Wilfert, F., Uthe, D., Schmid, K.W., Knoop, R., Modulation of radiation-induced tumour necrosis factor alpha (TNF-alpha) expression in the lung tissue by pentoxifylline (2002) Radiother Oncol, 64 (2), pp. 177-187; Zhang, M., Qian, J., Xing, X., Kong, F.M., Zhao, L., Inhibition of the tumor necrosis factor-alpha pathway is radioprotective for the lung (2008) Clin Cancer Res, 14 (6), pp. 1868-1876; Daigle, J.L., Hong, J.H., Chiang, C.S., McBride, W.H., The role of tumor necrosis factor signaling pathways in the response of murine brain to irradiation (2001) Cancer Res, 61 (24), pp. 8859-8865; Dy, L.C., Pei, Y., Travers, J.B., Augmentation of ultraviolet B radiation-induced tumor necrosis factor production by the epidermal platelet-activating factor receptor (1999) J Biol Chem, 274 (38), pp. 26917-26921; Müller, K., Meineke, V., Radiation-induced alterations in cytokine production by skin cells (2007) Exp Hematol, 35 (4 SUPPL. 1), pp. 96-104; Tolle, D.V., Seed, T.M., Fritz, T.E., Lombard, L.S., Poole, C.M., Acute monocytic leukemia in an irradiated Beagle (1979) Vet Pathol, 16 (2), pp. 243-254; Seed, T.M., Chubb, G.T., Tolle, D.V., Sequential changes in bone marrow architecture during continuous low dose gamma irradiation (1981) Scan Electron Microsc, 4, pp. 61-72; Sato, H., Seiki, M., Regulatory mechanism of 92 kDa type IV collagenase gene expression which is associated with invasiveness of tumor cells (1993) Oncogene, 8, pp. 395-405; Wielockx, B., Lannoy, K., Shapiro, S.D., Inhibition of matrix metalloproteinases blocks lethal hepatitis and apoptosis induced by tumor necrosis factor and allows safe antitumor therapy (2001) Nat Med, 7, pp. 1202-1208; Heissig B, Hattori K, Dias S, Friedrich M, Ferris B, et al. (2002) Recruitment of stem and progenitor cells from the bone marrow niche requires MMP-9 mediated release of kit-ligand. Cell 31:109(5): 625-37.35Natoli G, Costanzo A, Guido F, Moretti F, Bernardo A, et al. (1998) Nuclear factor kB-independent cytoprotective pathways originating at tumor necrosis factor receptor-associated factor 2. J Biol Chem 273(47): 31262-72.36Barkett, M., Gilmore, T.D., Control of apoptosis by Rel/NF-kappaB transcription factors (1999) Oncogene, 18 (49), pp. 6910-6924; Priestley, G.V., Scott, L.M., Ulyanova, T., Papayannopoulou, T., Lack of a4 integrin expression in stem cells restricts competitive function and self-renewal activity (2006) Blood, 107, pp. 2959-2967; Walkley, C.R., Shea, J.M., Sims, N.A., Purton, L.E., Orkin, S.H., Rb regulates interactions between hematopoietic stem cells and their bone marrow microenvironment (2007) Cell, 129 (6), pp. 1081-1095. , A; Walkley, C.R., Olsen, G.H., Dworkin, S., Fabb, S.A., Swann, J., A microenvironment-induced myeloproliferative syndrome caused by retinoic acid receptor gamma deficiency (2007) Cell, 129 (6), pp. 1097-1110. , B; Leone, G., Pagano, L., Ben-Yehuda, D., Voso, M.T., Therapy-related leukemia and myelodysplasia: Susceptibility and incidence (2007) Haematologica, 92 (10), pp. 1389-1398; Reza, S., Shetty, V., Dar, S., Qawi, H., Raza, A., Tumor necrosis factor-α levels decrease with anticytokine therapy in patients with myelodysplastic syndromes (1998) J Interferon Cytokine Res, 18 (10), pp. 871-877; Raza, A., Qawi, H., Lisak, L., Andric, T., Dar, S., Patients with myelodysplastic syndromes benefit from palliative therapy with amifostine, pentoxifylline, and ciprofloxacin with or without dexamethasone (2000) Blood, 95 (5), pp. 1580-1587
Keywords: angiogenesis; animal; animal cell; animal experiment; animal model; animal tissue; Animals; Antibodies, Neutralizing; apoptosis; article; Blood; blood cell count; Blotting, Western; bone marrow; bone marrow cell; Bone Marrow Cells; C57BL mouse; Cell Line; clinical feature; controlled study; cytokine production; disease course; drug effect; Enzyme Activation; flow cytometry; genetics; immunology; in vitro study; in vivo study; irradiation; leukocyte; leukocyte count; Leukocytes; macrocytic anemia; male; matrix metalloproteinase; Matrix Metalloproteinases; megakaryocyte; Megakaryocytes; metabolism; Mice; Mice, Inbred C57BL; Mice, Knockout; microenvironment; microsatellite marker; mouse; mouse mutant; Mus; myelodysplastic syndrome; neovascularization (pathology); Neovascularization, Pathologic; neutralizing antibody; nonhuman; Pathology; phenotype; protein expression; radiation dose; radiation exposure; Reverse Transcriptase Polymerase Chain Reaction; reverse transcription polymerase chain reaction; thrombocytopenia; transcription factor RelA; tumor necrosis factor alpha; tumor necrosis factor alpha antibody; Tumor Necrosis Factor-alpha; Vascular Endothelial Growth Factor A; vascularization; vasculotropin; vasculotropin A; Western blotting; zymography

Automated Arabidopsis plant root cell segmentation based on SVM classification and region merging - Marcuzzo, M.; Quelhas, P.; Campilho, A.; Maria Mendonça, A.; Campilho, A. (Computers in Biology and MedicineComput. Biol. Med., 2009)
To obtain development information of individual plant cells, it is necessary to perform in vivo imaging of the specimen under study, through time-lapse confocal microscopy. Automation of cell detection/marking process is important to provide research tools in order to ease the search for special events, such as cell division. In this paper we discuss an automatic cell detection approach for Arabidopsis thaliana based on segmentation, which selects the best cell candidates from a starting watershed-based image segmentation and improves the result by merging adjacent regions. The selection of individual cells is obtained using a support vector machine (SVM) classifier, based on a cell descriptor constructed from the shape and edge strength of the cells' contour. In addition we proposed a novel cell merging criterion based on edge strength along the line that connects adjacent cells' centroids, which is a valuable tool in the reduction of cell over-segmentation. The result is largely pruned of badly segmented and over-segmented cells, thus facilitating the study of cells. When comparing the results after merging with the basic watershed segmentation, we obtain 1.5% better coverage (increase in F-measure) and up to 27% better precision in correct cell segmentation. © 2009 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: CBMDAdoi: 10.1016/j.compbiomed.2009.06.008PubMed ID: 19604506Language of Original Document: EnglishCorrespondence Address: Marcuzzo, M.; INEB - Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUP, Portugal; email: marcuzzo@fe.up.ptReferences: Baeza-Yates, R., Ribeiro-Neto, B., (1999) Modern Information Retrieval, , ACM Press;Bleau, A., Leon, L., Watershed-based segmentation and region merging (2000) Computer Vision and Image Understanding, 77 (3), pp. 317-370; M. Brown, W. Grundy, L.D.N. Cristianini, C. Sugnet, T. Furey, M. Ares, D. Haussler, Knowledge-based analysis of microarray gene expression data using support vector machines, in: Proceedings of the National Academy of Sciences, 97 (1), 1999, pp. 262-267Burges, C., A tutorial on support vector machines for pattern recognition (1998) Data Mining and Knowledge Discovery, 2 (2), pp. 121-167; Campilho, A., Garcia, B., Toorn, H., Wijk, H., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the Arabidopsis thaliana root meristem (2006) Plant Journal, 48, pp. 619-627; Chang, C., Lin, C., (2001) Libsvm: A library for support vector machines, , http://www.csie.ntu.edu.tw/∼cjlin/libsvm/faq.html#f203, Software available online at; Chen, X., Zhou, X., Wong, S.T.C., Automated segmentation classification, and tracking of cancer cell nuclei in time-lapse microscopy (2006) IEEE Transactions on Biomedical Engineering, 53 (4), pp. 762-766; Dabov, K., Foi, A., Katkovnik, V., Egiazarian, K., Image denoising by sparse 3d transform-domain collaborative filtering (2007) IEEE Transactions on Image Processing, 16 (8), pp. 2080-2095; (2004) Kernel Methods in Computational Biology, Computational Molecular Biology, , B. Schölkopf, K. Tsuda, J.-P. Vert, Eds, MIT Press, Cambridge, MA; Garcia, B., Campilho, A., Scheres, B., Campilho, A., Automatic tracking of Arabidopsis thaliana root meristem in confocal microscopy (2004) Springer Lecture Notes in Computer Science, 3212, pp. 166-174. , Proceedings of the International Conference on Image Analysis and Recognition, Springer, Berlin; Grandjean, O., Vernoux, T., Laufs, P., Belcram, K., Mizukami, Y., Traas, J., In vivo analysis of cell division, cell growth, and differentiation at the shoot apical meristem in Arabidopsis (2004) Plant Cell, 16 (1), pp. 74-87; Iwamoto, A., Satoh, D., Furutani, M., Maruyama, S., Ohba, H., Sugiyama, M., Insight into the basis of root growth in Arabidopsis thaliana provided by a simple mathematical model (2006) Journal of Plant Research, 119, pp. 85-93; Kittler, J., Hatef, M., Duin, R.P.W., Matas, J., On combining classifiers (1998) IEEE Transactions on Pattern Analysis and Machine Intelligence, 20 (3), pp. 226-239; P. Kovesi, Symmetry and asymmetry from local phase, in: Proceedings of the 10th Australian Joint Conference on Artificial Intelligence, December 1997, pp. 185-190P. Kovesi, Edges are not just steps, in: Proceedings of the Fifth Asian Conference on Computer Vision, January 2002, pp. 822-827Liao, L., Noble, W.S., Combining pairwise sequence similarity and support vector machines for remote protein homology detection (2002) Proceedings of the Sixth Annual International Conference on Computational Molecular Biology, pp. 225-232. , ACM Press; Luc, V., Soille, P., Watersheds in digital spaces: an efficient algorithm based on immersion simulations (1991) IEEE Transactions on Pattern Analysis and Machine Intelligence, 13 (6), pp. 583-598; Mao, K., Zhao, P., Tan, P.-H., Supervised learning-based cell image segmentation for p53 immunohistochemistry (2006) IEEE Transactions on Biomedical Engineering, 53 (6), pp. 1153-1163; M. Marcuzzo, P. Quelhas, A. Campilho, A.M. Mendonça, A.C. Campilho, Automatic cell segmentation from confocal microscopy images of the Arabidopsis root, in: IEEE International Symposium on Biomedical Imaging, May 2008, pp. 712-715Marcuzzo, M., Quelhas, P., Campilho, A., Mendonça, A.M., Campilho, A.C., A hybrid approach for cell image segmentation (2008) Springer Lecture Notes in Computer Science, 5112, pp. 739-749. , Proceedings of the International Conference on Image Analysis and Recognition, Springer, Berlin; Meyer, F., Beucher, S., Morphological segmentation (1990) Journal of Visual Communication and Image Representation, 1 (1), pp. 21-46; Perona, P., Malik, J., Scale-space and edge detection using anisotropic diffusion (1990) IEEE Transactions on Pattern Analysis and Machine Intelligence, 7 (12), pp. 629-639; T. Roberts, S. Mckenna, N. Wuyts, T. Valentine, A. Bengough, Performance of low-level motion estimation methods for confocal microscopy of plant cells in vivo, in: IEEE Workshop on Motion & Video Computing, February 2007, pp. 13-21Sathiya Keerthi, S., Lin, C.-J., Asymptotic behaviors of support vector machines with Gaussian kernel (2003) Neural Computation, 15 (7), pp. 1667-1689; Vapnik, V., (1998) Statistical Learning Theory, , Wiley, New York
Keywords: accuracy; Arabidopsis; Arabidopsis plant; Arabidopsis thaliana; article; artificial intelligence; automation; Bioinformatics; Biological cells; Biomedical image processing; Cell detection; Cell divisions; Cell membranes; Cell merging; cell proliferation; Cell segmentation; Cell Shape; Cell Wall; Computer simulation; confocal microscopy; controlled study; Descriptor; F-measure; Image analysis; image processing; Image Processing, Computer-Assisted; Image segmentation; Imaging systems; In-Vivo imaging; Individual cells; Landforms; Merging; Models, Biological; nonhuman; Over segmentation; Plant cells; plant root; Plant roots; Plants (botany); priority journal; Region-merging; Research tools; root morphology; Segmented cell; signal noise ratio; support vector machine; Support vector machines; SVM classification; Watershed segmentation; Watersheds

Cell division detection on the arabidopsis thaliana root - Marcuzzo, M.; Guichard, T.; Quelhas, P.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2009)
The study of individual plant cells and their growth structure is an important focus of research in plant genetics. To obtain development information at cellular level, researchers need to perform in vivo imaging of the specimen under study, through time-lapse confocal microscopy. Within this research field it is important to understand mechanisms like cell division and elongation of developing cells. We describe a tool to automatically search for cell division in the Arabidopsis thaliana using information of nuclei shape. The nuclei detection is based on a convergence index filter. Cell division detection is performed by an automatic classifier, trained through cross-validation. The results are further improved by a stability criterion based on the Mahalanobis distance of the shape of the nuclei through time. With this approach, we can achieve a correct detection rate of 94.7%. © 2009 Springer Berlin Heidelberg.
Conference code: 77027Cited By (since 1996): 5Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-02172-5_23Language of Original Document: EnglishCorrespondence Address: Marcuzzo, M.; INEB - Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUPReferences: Campilho, A., Garcia, B., Toorn, H., Wijk, H., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the arabidopsis thaliana root meristem (2006) The Plant Journal, 48, pp. 619-627;Iwamoto, A., Satoh, D., Furutani, M., Maruyama, S., Ohba, H., Sugiyama, M., Insight into the basis of root growth in arabidopsis thaliana provided by a simple mathematical model (2006) J. Plant Res, 119, pp. 85-93; Roberts, T., Mckenna, S., Wuyts, N., Valentine, T., Bengough, A.: Performance of low-level motion estimation methods for confocal microscopy of plant cells in vivo. In: Motion 2007, p. 13 (2007)Beemster, G., Baskin, T., Analysis of cell division and elongation underlying the developmental acceleration of root growth in arabidopsis thaliana (1998) Plant Physiology, 116, pp. 1515-1526; Chen, X., Zhou, X., Wong, S.T.C., Automated segmentation, classification, and tracking of cancer cell nuclei in time-lapse microscopy (2006) IEEE Trans. on Biomedical Engineering, 53 (4), pp. 762-766; Mao, K.Z., Zhao, P., Tan, P., Supervised learning-based cell image segmentation for p53 immunohistochemistry (2006) IEEE Trans. on Biomedical Engineering, 53 (6), pp. 1153-1163; Yang, X., Li, H., Zhou, X., Nuclei segmentation using marker-controlled watershed, tracking using mean-shift, and kalman filter in time-lapse microscopy (2006) IEEE Trans. on Circuits and Systems I-Regul. Papers, 53 (11), pp. 2405-2414; Harder, N., M-Bermudez, F., Godinez, W., Ellenberg, J., Eils, R., Rohr, K., Automated analysis of mitotic cell nuclei in 3d fluorescence microscopy image sequences (2008) Workshop on Bio-Image Informatics: Biological Imaging, Computer Vision and Data Mining; Kobatake, H., Hashimoto, S., Convergence index filter for vector fields (1999) IEEE Trans. on Image Processing, 8 (8); Wei, J., Hagihara, Y., Kobatake, H., Detection of rounded opacities on chest radiographs using convergence index filter (1999) Proceedings of the Int. Conference on Image Analysis and Processing, pp. 757-761; Pereira, C.S., Fernandes, H., Mendonça, A.M., Campilho, A.C.: Detection of lung nodule candidates in chest radiographs. In: Martí, J., Benedí, J.M., Mendonça, A.M., Serrat, J. (eds.) IbPRIA 2007. LNCS, 4478, pp. 170-177. Springer, Heidelberg (2007)Marcuzzo, M., Quelhas, P., Campilho, A., Mendonça, A.M., Campilho, A., A hybrid approach for cell image segmentation (2008) LNCS, 5112, pp. 739-749. , Campilho, A, Kamel, M.S, eds, ICIAR 2008, Springer, Heidelberg Sponsors: International Association for Pattern Recognition (IAPR); Fundacao para a Ciencia e a Tecnologia (FCT)
Keywords: A-stability; Arabidopsis thaliana; Automatic classifiers; Bioinformatics; Cell divisions; Cell membranes; cell proliferation; Cellular levels; confocal microscopy; Cross validation; Detection rates; Growth structures; Image analysis; In-plants; In-Vivo imaging; Mahalanobis distances; Pattern recognition; Plant cells; research; Research fields; Stability criteria

Chromatographic pattern recognition using optimized one-class classifiers - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2009)
This paper presents a method for automating the selection of the rejection rate of one-class classifiers aiming at optimizing the classifier performance. These classifiers are used in a new classification approach to deal with class imbalance in Thin-Layer Chromatography (TLC) patterns, which is due to the huge difference between the number of normal and pathological cases, as a consequence of the rarity of Lysosomal Storage Disorders (LSD) diseases. The classification is performed in two decision stages, both implemented using optimized one-class classifiers: the first stage aims at recognizing most of the normal samples; the outliers of this first decision level are presented to the second stage, which is a multiclassifier prepared to deal with both pathological and normal patterns. The results that were obtained proved that the proposed methodology is able to overcome some of the difficulties associated with the choice of the rejection rate of one-class classifiers, and generally contribute to the minimization of the imbalance problem in TLC pattern classification. © 2009 Springer Berlin Heidelberg.
Conference code: 77027Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-02172-5_58Language of Original Document: EnglishCorrespondence Address: Sousa, A. V.; Instituto de Engenharia Biomédica, Rua Roberto Frias, Porto 4200-465, Portugal; email: ats@isep.ipp.ptReferences: Skurichina, M., Raudys, S., Duin, R.P.W., K-Nearest Neighbors Directed Noise Injection in Multilayer Perceptron Training (2000) IEEE Transactions on Neural Networks, 11;Chawla, N.V., Japkowicz, N., Kolcz, A., Editorial: Special Issue: Learning from Imbal-anced Data Sets (2004) Sigkdd Explorations, 6, pp. 1-6; Tax, D.M.J., (2001) One-class Classification; Concept-learning in the Absence of Counterexamples, , Ph.D. thesis: Delft University of Technology; Durand, G., Seta, N., Protein Glycosylation and Diseases: Blood and Urinary Oligosac-charides as Markers for Diagnosis and Therapeutic Monitoring (2000) Clin. Chem, 46, pp. 795-805; Sewell, A.C., Urinary Oligosaccharides. Techniques in Diagnostic Human (1991) Biochemical Genetics, pp. 219-231; Pekalska, E., Duin, R.P.W., Dissimilarity Representations Allow for Building Good Classifiers (2002) Pattern Recogn. Lett, 23, pp. 943-956; Sousa, A.V., Mendonça, A.M., Campilho, A., Dissimilarity-based Classification of Chromatographic Profiles (2008) Pattern Analysis and Applications, 11 (3-4), pp. 409-423; Sousa, A.V., Mendonça, A.M., Campilho, A., Minimizing the Imbalance Problem in Chromatographic Profile Classification with One-class Classifiers (2008) LNCS, 5112, pp. 413-422. , Campilho, A, Kamel, M.S, eds, ICIAR 2008, Springer, Heidelberg; Sousa, A.V., Mendonça, A.M., Campilho, A., Chromatographic Pattern Classification (2008) IEEE Trans. on Biomedical Engineering, 55 (6), pp. 1687-1696; Visa, S., Ralescu, A., Learning Imbalanced and Overlapping Classes Using Fuzzy Sets (2003) Workshop on Learning from Imbalanced Datasets II, ICML, , Washington DC Sponsors: International Association for Pattern Recognition (IAPR); Fundacao para a Ciencia e a Tecnologia (FCT)
Keywords: Chromatographic analysis; Class imbalance; Classification approach; Classifier performance; Classifiers; Decision levels; Image analysis; Imbalance problem; Learning systems; Lysosomal storage disorder; Multi-classifier; One-class classifier; Optimization; Pathological case; Pattern classification; Pattern recognition; Rejection rates; Thin layer chromatography

Evaluation of symmetry enhanced sliding band filter for plant cell nuclei detection in low contrast noisy fluorescent images - Marcuzzo, M.; Quelhas, P.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2009)
The study of cell nuclei is fundamental for plant cell Biology research. To obtain information at cellular level, researchers image cells' nuclei which were modified with fluorescence proteins, through laser scanning confocal microscopy. These images are normally noisy and suffer from high background fluorescence, making grey-scale segmentation approaches inadequate for a usable detection. To obtain a successful detection even at low contrast we investigate the use of a particular convergence filter, the Symmetric Sliding Band filter (SSBF), for cell detection. This filter is based on gradient convergence and not intensity. As such it can detect low contrast cell nuclei which otherwise would be lost in the background noise. Due to the characteristics of cell nuclei morphology, a symmetry constrain is integrated in the filter which corrects some inadequate detections and results in a filter response that is more discriminative. We evaluate the use of this filter for cell nuclei detection on the Arabidopsis thaliana root tip, where the nuclei were stained using yellow fluorescence protein. The resulting cell nuclei detection precision is 89%. © 2009 Springer Berlin Heidelberg.
Conference code: 77746Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-02611-9_81Language of Original Document: EnglishCorrespondence Address: Marcuzzo, M.; INEB - Instituto de Engenharia Biomédica Divisão de Sinal e Imagem, Campus FEUPReferences: Campilho, A., Garcia, B., Toorn, H., Wijk, H., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the arabidopsis thaliana root meristem (2006) The Plant Journal, 48, pp. 619-627;Iwamoto, A., Satoh, D., Furutani, M., Maruyama, S., Ohba, H., Sugiyama, M., Insight into the basis of root growth in arabidopsis thaliana provided by a simple mathematical model (2006) J. Plant Res, 119, pp. 85-93; Roberts, T., Mckenna, S., Wuyts, N., Valentine, T., Bengough, A.: Performance of low-level motion estimation methods for confocal microscopy of plant cells in vivo. In: Motion 2007, p. 13 (2007)Beemster, G., Baskin, T., Analysis of cell division and elongation underlying the developmental acceleration of root growth in arabidopsis thaliana (1998) Plant Physiology, 116, pp. 1515-1526; Willemse, J., Kulikova, O., de Jong, H., Bisseling, T., A new whole-mount dna quantification method and the analysis of nuclear dna content in the stem-cell niche of arabidopsis roots (2008) The Plant Journal, 10, pp. 1365-1374; Chen, X., Zhou, X., Wong, S.T.C., Automated segmentation, classification, and tracking of cancer cell nuclei in time-lapse microscopy (2006) IEEE Trans. on Biomedical Engineering, 53 (4), pp. 762-766; Mao, K.Z., Zhao, P., Tan, P., Supervised learning-based cell image segmentation for p53 immunohistochemistry (2006) IEEE Trans. on Biomedical Engineering, 53 (6), pp. 1153-1163; Schmitt, M.H.O., Morphological multiscale decomposition of connected regions with emphasis on cell clusters (2009) Computer Vision and Image Understanding, 113, pp. 188-201; Yang, X., Li, H., Zhou, X., Nuclei segmentation using marker-controlled watershed, tracking using mean-shift, and kalman filter in time-lapse microscopy (2006) IEEE Trans. on Circuits and Systems I-Regul. Papers, 53 (11), pp. 2405-2414; Kobatake, H., Hashimoto, S., Convergence index filter for vector fields (1999) IEEE Trans. on Image Processing, 8 (8); Wei, J., Hagihara, Y., Kobatake, H., Detection of rounded opacities on chest radiographs using convergence index filter (1999) Proceedings of the Int. Conference on Image Analysis and Processing, pp. 757-761;
Keywords: Arabidopsis thaliana; Background noise; Band filters; Bioinformatics; Biology imaging; Cell detection; Cell membranes; cell nucleus; Cellular levels; confocal microscopy; Convergence filters; cytology; Filter response; Fluorescence; Fluorescence proteins; Fluorescent images; Image analysis; Laser scanning confocal microscopy; Low contrast; Plant cell culture; Plant cells; Positron emission tomography; Root tip; Yellow fluorescence proteins

Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide - Martins, M.C.L.; Curtin, S.A.; Freitas, S.C.; Salgueiro, P.; Ratner, B.D.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2009)
Systemic heparinization, used during haemodialysis to prevent blood clotting on the extracorporeal circuit, leads to a high incidence of hemorrhagic complications. The adverse reactions associated with heparin neutralization using protamine sulphate justify the development of an alternative system for blood deheparinization. The main objective of this work is to design nanostructured surfaces with the capacity to bind heparin from blood in a selective way. A heparin-binding polypeptide, composed of L-lysine and L-leucine (pKL), was synthesized and immobilized, in different concentrations, onto self-assembled monolayers (SAMs) terminated with tetra(ethylene-glycol) (EG4 SAMs). Immobilization was performed using a fixed concentration of pKL after surface activation to different degrees using a range of CDI (N,N′-carbonyldiimidazole) concentrations. Results demonstrated that the presence of pKL increases heparin adsorption to EG4-SAMs, independently of the pKL concentration and the way of immobilization (adsorption or covalent bound). Selectivity towards heparin was successfully achieved on SAMs with low concentrations of immobilized pKL (9-17% of pKL). Surfaces were characterized using ellipsometry, contact angle measurements, Fourier transform infrared reflection absorption spectroscopy (IRAS), atomic force microscopy, and X-ray photoelectron spectroscopy. Heparin adsorption was assessed using IRAS and N-sulphonate- 35S-heparin. Therefore, this study could give a good contribution for the design of blood deheparinization devices. © 2008 Wiley Periodicals, Inc.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31849PubMed ID: 18286636Language of Original Document: EnglishCorrespondence Address: Martins, M. C. L.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomaterials, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180, Porto, Portugal; email: cmartins@ineb.up.ptChemicals/CAS: carbonyldiimidazole, 530-62-1; heparin, 37187-54-5, 8057-48-5, 8065-01-8, 9005-48-5; imidazole, 1467-16-9, 288-32-4; leucine, 61-90-5, 7005-03-0; lysine, 56-87-1, 6899-06-5, 70-54-2; tetraethylene glycol, 112-60-7; Ethylene Glycol, 107-21-1; Heparin, 9005-49-6; Leucine, 61-90-5; Lysine, 56-87-1; PeptidesReferences: Dailey J. Blood. Ipswich, MA, USA: Medical Consulting Group; 1998Section, V., Chronic intermittent haemodialysis and prevention of clotting in the extracorporal system (2002) Nephrol Dialysis Transplant, 17, pp. 63-71;Zhang, Y.H., Singh, V.K., Yang, V.C., Novel approach for optimizing the capacity and efficacy of a protamine filter for clinical extracorporeal heparin removal (1998) Asaio J, 44, pp. M368-M373; Tao, W., Deyo, D.J., Brunston, R.L., Vertrees, R.A., Zwischenberger, J.B., Extracorporeal heparin adsorption following cardiopulmonary bypass with a heparin removal device - An alternative to protamine (1998) Critical Care Med, 26, pp. 1096-1102; Ameer, G.A., Barabino, G., Sasisekharan, R., Harmon, W., Cooney, C.L., Langer, R., Ex vivo evaluation of a Taylor-Couette flow, immobilized heparinase I device for clinical application (1999) Proc Natl Acad Sci USA, 96, pp. 2350-2355; Ostuni, E., Yan, L., Whitesides, G.M., The interaction of proteins and cells with self-assembled monolayers of alkanethiolates on gold and silver (1999) Colloids Surf B-Biointerfaces, 15, pp. 3-30; Mrksich, M., Whitesides, G.M., Using self-assembled monolayers that present oligo(ethylene glycol) groups to control the interactions of proteins with surfaces. Poly(Ethylene Glycol) (1997) ACS Symposium Series, 680, pp. 361-373; Cardin, A.D., Weintraub, H.J.R., Molecular modeling of proteinglycosaminoglycan interactions (1989) Arteriosclerosis, 9, pp. 21-32; Kricheldorf, H.R., (1987) α-Amino Acid N-Carboxyanhydrides and Related Heterocycles, , New York: Springer Verlag;; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methylterminated alkanethiols self-assembled monolayers (2003) J Biomed Mater Res A, 67, pp. 158-171; Lee, H.J., Nedelkov, D., Corn, R.M., Surface plasmon resonance imaging measurements of antibody arrays for the multiplexed detection of low molecular weight protein biomarkers (2006) Anal Chem, 78, pp. 6504-6510; Roeges, N.P.G., (1994) A Guide to the Complete Interpretation of Infrared Spectra of Organic Structures, , England: Wiley;; Li, L.Y., Chen, S.F., Zheng, J., Ratner, B.D., Jiang, S.Y., Protein adsorption on oligo(ethylene glycol)-terminated alkanethiolate self-assembled monolayers: The molecular basis for non-fouling behavior (2005) J Phys Chem B, 109, pp. 2934-2941; Beamson, G., High, B.D., (1992) Resolution XPS of Organic Polymers, , Chichester: Wiley;; Sousa, S.R., Moradas, F.P., Saramago, B., Viseu, M.L., Barbosa, M.A., Human serum albumin adsorption on TiO2 from single protein solutions and from plasma (2004) Langmuir, 20, pp. 9745-9754; Socrates, G., (2001) Infrared and Raman Characteristic Group Frequencies: Tables and Charts, , Chichester: Wiley;; Capila, I., Linhardt, R.J., Heparin - Protein interactions (2002) Angewandte Chemie-Int Ed, 41, pp. 391-112; Snell, C.R.F.G., Kinetics and thermodynamics of the alpha Helix - β Transconformation of poly(L-lysine) and L-leucine copolymers. A compensation phenomenon (1973) Biochemistry, 12, pp. 1017-1025; Hearn, M.T.W., 1,1′-Carbonyldiimidazole-mediated immobilization of enzymes and affinity ligands (1987) Methods Enzymol, 135, pp. 102-117; Stollner, D., Scheller, F.W., Warsinke, A., Activation of cellulose membranes with 1,1′-carbonyldiimidazole or 1-cyano-4-dimethylaminopyridinium tetrafluoroborate as a basis for the development of immunosensors (2002) Anal Biochem, 304, pp. 157-165
Keywords: Absorption spectroscopy; Adsorption; Alternative systems; Amines; Amino acids; Angle measurement; article; Atomic force microscopy; Atomic forces; Atomic spectroscopy; Binding peptides; Blood; Blood clotting; Carbonyl diimidazole; Carbonyldiimidazole; Contact angle; deheparinization; device; Dialysis; Electron energy levels; ellipsometry; Ethylene; Ethylene Glycol; Fourier Transform Infrared; Fourier transforms; Glycols; Haemodialysis; heparin; heparin binding protein; Heparinization; High incidences; Humans; imidazole; immobilization; infrared spectroscopy; leucine; Low concentrations; lysine; Methods; Missile bases; Monolayers; nanomaterial; Nanostructured surfaces; Nanostructures; Peptide immobilization; Peptides; Photoelectron spectroscopy; Polysaccharides; Protein adsorption; protein binding; Renal Dialysis; Self assembled monolayers; Self-assembled monolayers; Sulphate; Surface activations; Surface functionalization; Surface Properties; surface property; tetraethylene glycol; unclassified drug; X ray photoelectron spectroscopy; X-ray photoelectron spectroscopies

Neural cell growth on TiO 2 anatase nanostructured surfaces - Collazos-Castro, J.E.; Cruz, A.M.; Carballo-Vila, M.; Lira-Cantú, M.; Abad, L.; del Pino, Á.P.; Fraxedas, J.; San Juan, A.; Fonseca, C.; Pêgo, A.P.; Casañ-Pastor, N. (Thin Solid FilmsThin Solid Films, 2009)
Titanium oxides have anti-inflammatory activity and tunable electrochemical properties that make them attractive materials for biomedical applications. This work investigated the compatibility of nanometric coatings of low-temperature phases of TiO 2 with neurons in 4-day and 10-day cultures, using different cell densities to quantify cell survival and neurite extension. TiO 2 films were prepared by sol-gel and thermal treatment (250-450 °C) of hydrolyzed titanium tetra-isopropoxide on electrically conducting or insulating slides. The conducting substrates were not passivated by the nanometric oxide layer and could be used as electrodes. Characterization of the films showed nano-structured TiO 2 containing exclusively Ti +4 valence in anatase and amorphous phases. When coated with polylysine, all films permitted good neuron attachment and survival for at least ten days in culture. However, they generally reduced neurite growth compared to cell culture borosilicate glass, with dendrites more affected than axons. The analyses of surface topography, hydrophilicity, charge and chemical composition revealed that TiO 2 chemistry was the main factor responsible for neurite inhibition. © 2009 Elsevier B.V. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: THSFAdoi: 10.1016/j.tsf.2009.06.048Language of Original Document: EnglishCorrespondence Address: Casañ-Pastor, N.; Instituto de Ciencias de Materiales de Barcelona, CSIC, Campus la Universidad Autonoma Barcelona, E-08193 Barcelona, Spain; email: nieves@icmab.esReferences: Suzuki, R., Frangos, J.Á., (2000) Clin. Orthop. Relat. Res., 372, p. 280;Suzuki, R., Muyco, J., McKittrick, J., Frangos, J.A., (2003) J. Biomed. Mater. Res. A, 66, p. 396; Ulbrich, M.H., Fromherz, P., (2005) Appl. Phys. A., 81, p. 887; Topoglidis, E., Lutz, T., Willis, R.L., Barnett, C.J., Cass, A.E., Durrant, J.R., (2000) Faraday Discuss., 116, p. 35; Smith, J.R., Walsh, F.C., Clarke, R.L., (1998) J. Appl. Electrochem., 28, p. 1021; Dinh, N.N., Oan, N.T., Long, P.D., Bernard, M.N., Hugot-Le Goffb, A., (2003) Thin Solid Films, 423, p. 70; (2001) Titanium in Medicine, , Brunette D.M., Tengvall P., Textor M., and Thomsen P. (Eds), Springer-Verlag, Berlin; Textor, M., Sittig, C., Frauchiger, V., Tosatti, S., Brunette, D.M., (2001) Titanium in Medicine, 171. , Brunette D.M., Tengvall P., Textor M., and Thomsen P. (Eds), Springer-Verlag, Berlin; Contreras, R., Sahlin, H., Frangos, J.Á., (2007) J. Biomed. Mater. Res. A, 80, p. 480; Kolbrecka, K., Przyluski, J., (1994) Electrochim. Acta, 39, p. 1591; Diebold, U., (2003) Surf. Sci. Rep., 48, p. 53; Jeong, B.S., Norton, D.P., Budai, J.D., (2003) Solid-State Electron., 47, p. 2275; Moulton, S.E., Barisci, J.N., Bath, A., Stella, R., Wallace, G.C., (2005) Langmuir, 21, p. 316; Jackson, D.R., Omanovic, S., Roscoe, S.G., (2005) Langmuir, 16, p. 5449; Subramanian, V., Karki, A., Gnanasekar, K.I., Eddy, FP., Rambabu, B., (2006) J. Power Sources, 159, p. 186; Carballo-Vila, M., Moreno-Burriel, B., Jurado, J.R., Chinarro, E., Casañ-Pastor, N., Collazos-Castro, J.E., (2009) J. Biomed. Mater. Res. A, 90, p. 94; Brewer, G.J., Torricelli, J.R., Evege, E.K., Price, P.J., (1993) J. Neurosci. Res., 35, p. 567; Rajnicek, A.M., Britland, S., McCaig, C.D., (1997) J. Cell Sci., 110, p. 2905; Bao, W., Thullberg, M., Zhang, H., Onischenko, A., Strömblad, S., (2002) Mol. Cell. Biol., 22, p. 4587; Sanjana, N.E., Fuller, S.B., (2004) J. Neurosci. Methods, 136, p. 151; Parak, W.J., George, M., Kudera, M., Gaub, H.E., Behrends, J.C., (2001) Eur. Biophys. J., 29, p. 607; Dotti, C.G., Sullivan, C.A., Banker, G.A., (1988) J. Neurosci., 8, p. 1454; Davenport, R.W., McCaig, C.D., (1993) J. Neurobiology, 24, p. 89; Chuckowree, J.A., Vickers, J.C., (2003) J. Neurosci., 23, p. 3715; Long, T.C., Saleh, N., Tilton, R.D., Lowry, G.V., Veronesi, B., (2006) Environ. Sci. Technol., 40, p. 4346; Zhao, L., Chang, J., Zhai, W., (2005) J. Biomater. Appl., 19, p. 237; Swamy, V., Kusnetzov, A., Dubrovinsky, L.S., Caruso, R.A., Shchukin, D.G., Muddle, B.C., (2005) Phys. Rev., B, 71, p. 1; Lozano, M.P., Fraxedas, J., (2000) Surf. Interface Anal., 30, p. 623; Martínez-Ferrero, E., Sakatani, Y., Boissière, C., David Grosso, D., Fuertes, A., Fraxedas, J., Sánchez, C., (2007) Adv. Funct. Mater., 17, p. 3348; Roddick-Lanzilotta, A.D., McQuillan, A.J., (1999) J. Colloid Interface Sci., 217, p. 194; Kosmulski, M., (2002) Adv. Colloid Interface Sci., 99, p. 255; Ikegaya, Y., Itsukaichi-Nishida, Y., Ishihara, M., Tanaka, D., Matsuki, N., (2000) Neuroscience, 97, p. 215; Cyster, L.A., Parker, K.G., Parker, T.L., Grant, D.M., (2004) Biomaterials, 25, p. 97; Blau, A., Weinl, C., Mack, J., Kienle, S., Jung, G., Ziegler, C., (2001) J. Neurosci. Methods, 112, p. 65; Kommireddy, D.S., Sriram, S.M., Lvov, Y.M., Mills, D.K., (2006) Biomaterials, 27, p. 4296; Cai, K., Bossert, J., Jandt, K.D., (2006) Colloids Surf., B, 49, p. 136; Wang, Y.-X., Robertson, J.L., Spillman Jr., W.B., Claus, R.O., (2004) Pharm. Res., 21, p. 1362; Greve, F., Frerker, S., Bittermann, A.G., Burkhardt, C., Hierlemann, A., Hall, H., (2007) Biomaterials, 28, p. 5246; Yang, H., Fung, S.-Y., Pritzker, M., Chen, P., (2007) PLoS ONE, 2, pp. e1325; Giovambattista, N., Debenedetti, P.G., Rosky, P.J., (2007) J. Phys. Chem. B, 111, p. 9581; Onur, M.A., Taş, Z., Gürpnar, A., Şahin, A., Çehreli, M.C., (2004) Clin. Oral Implants Res., 15, p. 513; Lopez, T., Ortiz-Islas, E., Manjarrez, J., Rodríguez-Reinoso, F., Sepúlveda, A., Gonzalez, R.D., (2006) Opt. Mater., 29, p. 70
Keywords: Amorphous phasis; Anatase; Anti-inflammatory activity; Biomedical applications; Borosilicate glass; Cell culture; cell density; Cell membranes; cell survival; Chemical compositions; Coatings; Conducting substrates; Conductive films; Electrochemical properties; Gelation; Growth kinetics; Heat treatment; Iso-propoxide; Low temperature phasis; Nano-structured; Nanometrics; Nanostructured surface; Nanostructures; Neural cell; Neural cells; Neurite extension; Neurite growth; Neurites; Neurons; Oxide layer; polylysine; Surface topography; Thermal treatment; TiO; Titanium; Titanium dioxide; Titanium oxide; Titanium oxides

A new method for the detection of singular points in fingerprint images - Magalhães, F.; Oliveira, H.P.; Campilho, A.C. (2009 Workshop on Applications of Computer Vision, WACV 2009Workshop Appl. Comput. Vis., WACV, 2009)
Automatic biometric identification based on fingerprints is still one of the most reliable identification method in criminal and forensic applications. A critical step in fingerprint analysis without human intervention is to automatically and reliably extract singular points from the input fingerprint images. These singular points (cores and deltas) not only represent the characteristics of local ridge patterns but also determine the topological structure (i.e., fingerprint type) and largely influence the orientation field. Poincaré Index-based methods are one of the most common for singular points detection. However, these methods usually result in many spurious detections. Therefore, we propose an enhanced version of the method presented by Zhou et al. [13] that introduced a feature called DORIC to improve the detection. Our principal contribution lies in the adoption of a smoothed orientation field and in the formulation of a new algorithm to analyze the DORIC feature. Experimental results show that the proposed algorithm is accurate and robust, giving better results than the best reported results so far, with improvements in the range of 5% to 7%. © 2009 IEEE.
Conference code: 79821Export Date: 21 November 2012Source: ScopusArt. No.: 5403106doi: 10.1109/WACV.2009.5403106Language of Original Document: EnglishCorrespondence Address: Magalhães, F.; INESC, Porto, Portugal; email: filipe.magalhaes@inescporto.ptReferences: Drets, G.A., Liljenström, H.G., (1999) Intelligent Biometric Techniques in Fingerprint and Face Recognition, , CRC Press, New York;Hong, L., Wan, Y., Fingerprint image enhancement: Algorithm and performance evaluation (1998) IEEE Transactions On, Pattern Analysis and Machine Intelligence, 20 (8), pp. 777-789; Jain, A., Hong, L., Bolle, R., On-line fingerprint verification (1997) IEEE Transactions on Pattern Analysis and Machine Intelligence, 19 (4), pp. 302-314; Jinwei, G., Jie, Z., A novel model for orientation field of fingerprints (2003) Proceedings IEEE Computer Society Conference on Computer Vision and Pattern Recognition, 2, pp. II493-II498; Kara, K., Jain, A.K., Fingerprint classification (1996) Pattern Recognition, 29 (3), pp. 389-404; Kass, M., Witkin, A., Analyzing oriented patterns (1987) Cornput. Vision Graph. Image Process, 37 (3), pp. 362-385. , 27996; Kawagoe, M., Tojo, A., Fingerprint pattern classification (1984) Pattern Recognition, 17 (3), pp. 295-303; Maio, D., Maltoni, D., Cappelli, R., Wayman, J.L., Jain, A.K., FVC2002: Second fingerprint verification competition (2002) Proceedings - International Conference on Pattern Recognition, 16 (3), pp. 811-814; Maio, D., Maltoni, D., Cappelli, R., Wayman, J.L., Jain, A.K., Fvc2004: Third fingerprint verification competition (2004) Proceedings International Conference on Biometric Authentication (ICBA), pp. 1-7. , Hong Kong; Pankanti, S., Prabhakar, S., Jain, A.K., On the individuality of fingerprints (2002) IEEE Transactions on Pattern Analysis and Machine Intelligence, 24 (8), pp. 1010-1025; Sherlock, B.G., Monro, D.M., A model for interpreting fingerprint topology (1993) Pattern Recognition, 26 (7), pp. 1047-1055; Srinivasan, V.S., Murthy, N.N., Detection of singular points in fingerprint images (1992) Pattern Recognition, 25 (2), pp. 139-153; Zhou, J., Chen, F., Gu, J., A novel algorithm for detecting singular points from fingerprint images (2009) IEEE Transactions on Pattern Analysis and Machine Intelligence, 31 (7), pp. 1239-1250
Keywords: Algorithms; Biometric identifications; Biometrics; Computer applications; Computer vision; Critical steps; Fingerprint analysis; Fingerprint images; Forensic applications; Human intervention; Identification method; Orientation fields; Poincare; Ridge patterns; Singular points; Structural optimization; Technical presentations; Topological structure

Physical, chemical and in vitro biological profile of chitosan hybrid membrane as a function of organosiloxane concentration - Shirosaki, Y.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Costa, M.A.; Fernandes, M.H. (Acta BiomaterialiaActa Biomater., 2009)
We attempted to prepare chitosan-silicate hybrid for use in a medical application and evaluated the physico-chemical properties and osteocompatibility of the hybrids as a function of γ-glycidoxypropyltrimethoxysilane (GPTMS) concentration. Chitosan-silicate hybrids were synthesized using GPTMS as the reagent for cross-linking of the chitosan chains. Fourier transform infrared spectroscopy, 29Si CP-MAS NMR spectroscopy and the ninhydrin assay were used to analyze the structures of the hybrids, and stress-strain curves were recorded to estimate their Young's modulus. The swelling ability, contact angle and cytocompatibility of the hybrids were investigated as a function of the GPTMS concentration. A certain fraction of GPTMS in each hybrid was linked at the epoxy group to the amino group of chitosan, which was associated with the change in the methoxysilane group of GPTMS due to hybridization. The cross-linking density was around 80% regardless of the volume of GPTMS. As the content of GPTMS increased, the water uptake decreased and the hydrophilicity of the hybrids increased except when the content exceeded amolar ratio of 1.5, when it caused a decrease. The values of the mechanical parameters assessed indicated that significant stiffening of the hybrids was obtained by the addition of GPTMS. The adhesion and proliferation of the MG63 osteoblast cells cultured on the chitosan-GPTMS hybrid surface were improved compared to those on the chitosan membrane, regardless of the GPTMS concentration. Moreover, human bone marrow osteoblast cells proliferated on the chitosan-GPTMS hybrid surface and formed a fibrillar extracellular matrix with numerous calcium phosphate globular structures, both in the presence and in the absence of dexamethasone. Therefore, the chitosan-GPTMS hybrids are promising candidates for basic materials that can promote bone regeneration because of their controllable composition (chitosan/GPTMS ratio). © 2008 Acta Materialia Inc.
Cited By (since 1996): 10Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2008.07.022PubMed ID: 18722166Language of Original Document: EnglishCorrespondence Address: Hayakawa, S.; Biomaterial Laboratory, Graduate School of Natural Science and Technology, Okayama University, Tsushima, Okayama-shi, 700-8530, Japan; email: satoshi@cc.okayama-u.ac.jpChemicals/CAS: (3 glycidyloxypropyl)trimethoxysilane, 2530-83-8; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; chitosan, 9012-76-4; silicate, 12627-13-3; Chitosan, 9012-76-4; Cross-Linking Reagents; gamma-glycidoxypropyltrimethoxysilane, 2530-83-8; Silanes; SiloxanesTradenames: AldrichReferences: Lai, J.Y., Lin, F.C., Wang, C.C., Wang, D.M., Effect of nonsolvent additives on the porosity and morphology of asymmetric TPX membranes [J] (1996) J Membrane Sci, 118, pp. 49-61;Wang, D.M., Lin, F.C., Chiang, J.C., Lai, J.Y., Control of porosity of asymmetric TPX membranes [J] (1998) J Membrane Sci, 141, pp. 1-12; Piattelli, A., Scarano, A., Russo, P., Matarasso, S., Evaluation of guided bone regeneration in rabbit tibia using bioresorbable and non-resorbable membranes (1996) Biomaterials, 17 (8), pp. 791-796; Gotfredsen, K., Nimb, L., Hjorting-Hansen, E., Immediate implant placement using a biodegradable barrier, polyhydroxybutyratehydroxyvalerate reinforced with polyglactin 910: an experimental study in dogs (1994) Clin Oral Implants Res, 5 (2), pp. 83-91; Kostopoulos, L., Karring, T., Augmentation of the rat mandible using guided tissue regeneration (1994) Clin Oral Implants Res, 5 (2), pp. 75-82; Kostopoulos, L., Karring, T., Guided bone regeneration in mandibular defects in rats using a bioresorbable polymer (1994) Clin Oral Implants Res, 5 (2), pp. 666-674; Nyman, S., Gottlow, J., Karring, T., The regeneration potential of the periodontal ligament: an experimental study in the monkey (1982) J Clin Periodontal, 9, pp. 257-265; Dupoirieux, L., Pourquier, D., Picot, M.C., Neves, M., Comparative study of three different membranes for guided bone regeneration of rat cranial defects (2001) Int J Oral Maxillofac Surg, 30 (1), pp. 58-62; Zhang, R., Ma, P.X., Porous poly(l-lactic acid)/apatite composites created by biomimetic process (1999) J Biomed Mater Res, 45, pp. 285-293; Murphy, W.L., Kohn, D.H., Mooney, D.J., Growth of continuous bonelike mineral within porous poly(lactide-co-glycolide) scaffolds in vitro (2000) J Biomed Mater Res, 50, pp. 50-58; Lin, F.C., Wang, D.M., Lai, J.Y., Asymmetric TPX membranes. J membranes with high gas flux. (1996) J Membrane Sci, 110, pp. 25-36; Vert, M., Mauduit, J., Li, S., Biodegradation of PLA/GA polymers: increasing complexity (1994) Biomaterials, 15, pp. 1209-1213; Lee, Y.K., Mooney, D.J., Hydrogels for tissue enigineering (2001) Chem Rev, 101, pp. 1869-1879; Domard, A., Rinaudo, M., Preparation and characterization fully deacetylated chitosan (1983) Int J Biol Macromol, 5, pp. 49-52; Chandy, T., Sharma, P.C., Chitosan - as a biomaterial (1990) Biomater Artif Cells Artif Organo, 18, pp. 1-24; Ueno, H., Yamada, H., Tanaka, I., Kaba, N., Matsuura, M., Okumura, M., Accelerating effects of chitosan for healing at early phase of experimental open wound in dogs (1999) Biomaterials, 20, pp. 1407-1414; Muzzareli, R.A.A., Mattioli-Belmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Stimulatory effect on bone formation exerted by a modified chitosan (1994) Biomaterials, 15, pp. 1075-1081; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., In vitro cytocompatibility of MG63 cells on chitosan-organosiloxane hybrid membranes (2005) Biomaterials, 26, pp. 485-493; Prochazkova, S., Varum, K.M., Æstgaard. Quantitative determination of chitosans by ninhydrin (1999) Carbohydr Polym, 38, pp. 115-122; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part II: effect of ascorbic acid, β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Coelho, M.J., Cabral, A.T., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part I: osteoblastic differentiation of serially passaged human bone marrow cells cultured in α-MEM and in D-MEM (2000) Biomaterials, 21, pp. 1087-1094; Berridge, V., Tan, A.S., Characterization of the cellular reduction of 3-(4,5-dimethhylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT): subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch Biochem Biophys, 303, pp. 474-482; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Argüelles-Monal, W., Desbriéres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Sol-gel preparation and in vitro deposition of apatite on porous gelatin-siloxane hybrids (2001) J Non Cryst Solid, 285, pp. 116-122; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Novel approach to fabricate porous gelatin-siloxane hybrids for bone tissue engineering (2002) Biomaterials, 23, pp. 4765-4773; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Incorporation of Ca 2+ ions in gelatin-siloxane hybrids through a sol-gel process (2001) J Ceram Soc Jpn, 109, pp. 403-408; Rashidova, S.S.h., Shakarova, D.S.h., Ruzimuradov, O.N., Satabaldieva, D.T., Zalyalieva, S.V., Shpigun, O.A., Bionanocompositional chitosan-silica sorbent for liquid chromatography (2004) J Chromatogr B, 800, pp. 49-53; Hench, L.L., Ethridge, E.C., (1982) Biomaterials an interfacial approach, , Academic Press, New York 10; Xynos, I.D., Hukkanen, M.V.J., Batten, J.J., Buttery, L.D., Hench, L.L., Polak, J.M., Bioglass ® 45S5 stimulates osteoblast turnover and enhances bone formation in vitro: implications and applications for bone tissue engineering (2000) Calcif Tissue Int, 67, pp. 321-329; Xynos, I.D., Edgar, A.J., Buttery, L.D.K., Hench, L.L., Ionic products of bioactive glass dissolution increase proliferation of human osteoblasts and induce insulin-like growth factor II mRNA expression and protein synthesis (2000) Biochem Biophys Res Commun, 276, pp. 461-465; Gough, J.E., Jones, J.R., Hench, L.L., Nodule formation and mineralisation of human primary osteoblasts cultured on a porous bioactive glass scaffold (2004) Biomaterials, 25, pp. 2039-2046; Maniatopoulos, C., Sodek, J., Melcher, A., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Fernandes, M.H., Costa, M.A., Carvalho, G.S., Mineralization in serially passaged human alveolar bone cells (1997) J Mater Sci Mater Med, 8, pp. 61-65; Costa, M.A., Gutierres, M., Almeida, L., Lopes, M.A., Santos, J.D., Fernandes, M.H., In vitro mineralization of human bone marrow cells cultured on Bonelike ® (2004) Key Eng Mater, 254-256, pp. 821-824
Keywords: (3 glycidyloxypropyl)trimethoxysilane; article; assay; Biocompatibility; Bone Marrow Cells; calcium phosphate; cell adhesion; Cell Line, Tumor; cell proliferation; cell survival; cell viability; Chemical analysis; chitosan; concentration (parameters); controlled study; cross linking; Cross-Linking Reagents; extracellular matrix; human; human cell; Humans; hydrophobicity; in vitro study; infrared spectroscopy; Magnetic Resonance Spectroscopy; Microscopy, Electron, Scanning; molecular hybridization; Nuclear magnetic resonance spectroscopy; Organic-inorganic hybrid; osteoblast; Osteoblasts; Osteocompatibility; physical chemistry; priority journal; Silanes; silicate; siloxane; Siloxanes; Spectrophotometry, Ultraviolet; Spectroscopy, Fourier Transform Infrared; stress strain relationship; structure analysis; surface property; Tissue engineering; unclassified drug; water transport; γ-Glycidoxypropyltrimethoxysilane (GPTMS)

Prediction of neonatal acidemia by computer analysis of fetal heart rate and ST event signals - Costa, A.; Ayres-de-Campos, D.; Costa, F.; Santos, C.; Bernardes, J. (American Journal of Obstetrics and GynecologyAm. J. Obstet. Gynecol., 2009)
Objective: The objective of the study was to evaluate the accuracy of computer analysis of fetal heart rate (FHR) and ST event signals in prediction of neonatal acidemia. Study Design: One hundred forty-eight FHR tracings were evaluated to identify red alerts provided by the system, based on automated analysis of FHR and ST event signals, and compared with the occurrence of umbilical artery acidemia (pH ≤7.05). Results: The presence of red alerts obtained sensitivity of 1.00 (95% confidence interval [CI], 0.56-1.00), specificity of 0.94 (95% CI, 0.89-0.97), positive predictive value (PPV) of 0.47 (95% CI, 0.22-0.72), negative predictive value (NPV) of 1 (95% CI, 0.96-1.00), positive likelihood ratio (PLR) of 17.6 (95% CI, 9.0-34.5), and negative likelihood ratio (NLR) of 0. When limiting analysis to red alerts that did not include ST data, sensitivity was 0.57 (95% CI, 0.20-0.88), specificity was 0.97 (95% CI, 0.92-0.99), PPV was 0.50 (95% CI, 0.17-0.82), NPV was 0.98 (95% CI, 0.93-0.99), PLR was 20.14 (95% CI, 6.3-64.2), and NLR was 0.44 (95% CI, 0.19-1.04). Conclusion: Computer analysis of FHR and ST event signals provide higher accuracy in predicting neonatal academia. © 2009 Mosby, Inc. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: AJOGAdoi: 10.1016/j.ajog.2009.04.033PubMed ID: 19539895Language of Original Document: EnglishCorrespondence Address: Costa, A.; Departamento de Ginecologia e Obstetrícia, Faculdade de Medicina, Hospital S. JoãoPortugal; email: cosantonia@gmail.comReferences: (2006) Perinatal Mortality Surveillance 2004: England, Wales, and Northern Ireland, , CEMACH (Confidential Enquiry into Maternal and Child Health), Confidential Enquiry into Maternal and Child Health, London, UK;(1997) 4th annual report, , CESDI (Confidential Enquiry into Stillbirths and Deaths in Infancy), Maternal and Child Health Research Consortium, London, UK; Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310; Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-165; Bernardes, J., Costa-Pereira, A., Ayres-de-Campos, D., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57, pp. 33-37; Donker, D.K., van Geijn, H.P., Hasman, A., Interobserver variation in the assessment of fetal heart rate recordings (1993) Eur J Obstet Gynecol Reprod Biol, 52, pp. 21-28; Neilson, J.P., Fetal electrocardiogram (ECG) for fetal monitoring during labour (2006) Cochrane Database Syst Rev, 3; Doria, V., Papageorghiou, A., Gustafsson, A., Ugwumadu, A., Farrer, K., Arulkumaran, S., Review of the first 1502 cases of ECG-ST waveform analysis during labour in a teaching hospital (2007) BJOG, 114, pp. 1202-1207; Westerhuis, M., Kwee, A., van Ginkel, A., Drogtrop, A., Gyselaers, W., Visser, G., Limitations of ST analysis in clinical practice: three cases of intrapartum metabolic acidosis (2007) BJOG, 114, pp. 1194-1201; Amer-Wahlin, I., Arulkumaran, S., Hagberg, H., Marsal, K., Visser, G., Fetal electrocardiogram: ST waveform analysis in intrapartum surveillance (2007) BJOG, 114, pp. 1191-1193; Dawes, G.S., Redman, C.W., Smith, J.H., Improvements in the registration and analysis of fetal heart rate records at the bedside (1985) Br J Obstet Gynaecol, 92, pp. 317-325; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: the antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118, pp. 52-60. , SisPorto Multicentre Validation Study Group; Dawes, G.S., Moulden, M., Redman, C.W.G., System 8000: computerized antenatal FHR analysis (1991) J Perinat Med, 19, pp. 47-51; Bernardes, J., Moura, C., Marques-de-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sá, J.P., Pereira-Leite, L., SisPorto 2.0-a program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Ayres-de-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto® 3.5-a central fetal monitoring station with online alerts based on computerized cardiotocogram+S.T.event analysis (2008) J Perinat Med, 36, pp. 260-264; Ayres-de-Campos, D., Bernardes, J., Kwee, A., Westehuis, M., Visser, G.H.A., Computer quantification of short-term variability as an adjunct to fetal electrocardiographic monitoring (2007) BJOG, 114, pp. 1446-1447; Downing, J.W., Houlton, P.C., Barclay, A., Extradural analgesia for cesarean section: a comparison with general anesthesia (1979) Br J Anaesth, 51, pp. 367-374; Crawford, J.S., James, F.M., Davies, P., Crawley, M., A further study of general anaesthesia for cesarean section (1976) Br J Anaesth, 48, pp. 661-667; Huch, A., Huch, C., Rooth, G., Guidelines for blood sampling and measurement of pH and blood gas values in obstetrics (1994) Eur J Obstet Gynecol Reprod Biol, 54, pp. 165-175; ACOG technical bulletin. Umbilical artery blood acid-base analysis (1996) Int J Gynecol Obstet, 52, pp. 305-310; Westgate, J., Garibaldi, J.M., Greene, K.R., Umbilical cord blood gas analysis at delivery: a time for quality data (1994) Br J Obstet Gynaecol, 101, pp. 1054-1063; Low, J.A., Intrapartum fetal asphyxia: definition, diagnosis and classification (1997) Am J Obstet Gynecol, 176, pp. 957-959; Fleiss, J.L., (1981) Statistical methods for rates and proportions. 2nd ed., , John Wiley & Sons, New York, NY Section 5.6; Keith, R.D., Beckley, S., Garibaldi, J.M., Westgate, J.A., Ifeachor, E.C., Greene, K.R., A multicentre comparative study of 17 experts and an intelligent computer system for managing labour using cardiotocogram (1995) Br J Obstet Gynecol, 102, pp. 668-700; Chung, T.K., Mohajer, M.P., Yang, Z.j., Chang, A.M., Sahota, D.S., The prediction of fetal acidosis at birth by computerised analysis of intrapartum cardiotocography (1995) Br J Obstet Gynaecol, 102, pp. 454-460; Nielsen, P.V., Stigsby, B., Nickelsen, C., Nim, J., Computer assessment of the intrapartum cardiotocogram. II. The value of computer assessment compared with visual assessment (1988) Acta Obstet Gynecol Scand, 67, pp. 461-464; Policy statement. The Apgar score-American Academy of Pediatrics and American College of Obstetricians and Gynecologists (2006) Pediatrics, 117, pp. 1444-1447; Casey, B.M., McIntire, D.D., Leveno, K.J., The continuing value of the Apgar score for the assessment of the newborn infants (2001) N Engl J Med, 334, pp. 467-471; Moster, D., Lie, R.T., Irgens, L.M., Bjerkedal, T., Markestad, The association of Apgar score with subsequent death and cerebral palsy: a population-based study in term infants (2001) J Pediatr, 138, pp. 798-803
Keywords: acidemia; Acidosis; article; autoanalysis; Cardiotocography; computer analysis; computer assisted; computer prediction; Diagnosis, Computer-Assisted; diagnostic value; Electrocardiography; Female; Fetal heart rate; Fetal hypoxia; Fetal monitoring; fetus electrocardiography; fetus heart rate; Heart Rate, Fetal; human; Humans; Infant, Newborn; major clinical study; male; newborn; newborn acidosis; observational study; pH; Predictive Value of Tests; priority journal; Prospective Studies; prospective study; Reproducibility of Results; sensitivity and specificity; signal transduction; ST segment; umbilical artery

The role of composition, morphology and crystalline structure in the electrochemical behaviour of TiN x thin films for dry electrode sensor materials - Cunha, L.T.; Pedrosa, P.; Tavares, C.J.; Alves, E.; Vaz, F.; Fonseca, C. (Electrochimica ActaElectrochim Acta, 2009)
A morphological, structural and electrochemical study of titanium nitride (TiN x) thin films, obtained by DC reactive sputtering on titanium substrates, was carried out for a wide range of compositions (0 < x < 1.34) aiming a selection of the best coatings for dry biomedical electrodes. The films displayed a columnar-type structure, with morphologies strongly dependent on the composition: a compact and smooth surface was found for the Ti-rich films, (x < 1), whereas the N-rich films, (x ≥ 1) displayed a rough and porous structure. The electrochemical study of the TiN x films was performed in synthetic sweat, aiming at simulating the contact with the skin. The voltammetric analysis showed anodic currents higher for TiN x films than for titanium for low and medium polarization potentials, whereas for potentials beyond 2 V the blocking behaviour of the TiN x films allowed them to display lower current values. The passive dissolution currents in the sub-μA/cm 2 range and the charge transfer resistances of the order of the MΩ proved the excellent stability of all films in sweat conditions. Finally, the electrochemical noise analysis showed that the near-stoichiometric and N-rich films display the lowest noise, being therefore the most suitable for electrode applications, where signals in the microvolt range, such as the electroencephalographic (EEG) signals, are to be monitored. © 2009 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 10Export Date: 21 November 2012Source: ScopusCODEN: ELCAAdoi: 10.1016/j.electacta.2009.08.004Language of Original Document: EnglishCorrespondence Address: Fonseca, C.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cfonseca@ineb.up.ptReferences: McAdams, E., Bioelectrodes (1988) Encyclopedia of Medical Devices and Instrumentation, p. 120. , Webster J.G. (Ed), Wiley, New York;Teplan, M., (2002) Meas. Sci. Rev., 2 (2); Searle, A., Kirkup, L., (2000) Physiolog. Meas., 22, p. 71; Ko, W.K., Hynecek, J., Dry electrodes and electrode amplifiers (1974) Biomedical Electrode Technology, , Miller H.A., and Harrison D.C. (Eds), Academic Press, N.Y; Fonseca, C., Vaz, F., Barbosa, M.A., (2004) Corros. Sci., 46 (12), p. 3005; Tallgren, P., Vanhatalo, S., Kaila, K., Voipio, J., (2005) Clin. Neurophysiol., 116, p. 799; Abd El Aal, (2008) Corros. Sci., 50, p. 41; Malik, H., Mgaloblishvili, R., Mills, B., (2004) J. Mat. Sci. Lett., 19 (19), p. 1779; Piscanec, S., Ciacchi, L., Vesselli, E., Comelli, G., Sbaizero, O., Meriani, S., De Vita, A., (2004) Acta Mater., 52, p. 1237; Gao, L., Gstöttner, J., Emling, R., Linsmeier, Ch., Wiltner, A., Hansch, W., Schmitt-Landsiedel, D., (2004) Microelectronic Eng., 76 (1-4), p. 76; Vaz, F., Ferreira, J., Ribeiro, E., Rebouta, L., Lanceros-Méndez, S., Mendes, J.A., Alves, E., de Rijk, J., (2005) Surf. Coat. Technol., 191, p. 317; Barradas, N.P., Jeynes, C., Webb, R.P., (1997) Appl. Phys. Lett., 71, p. 291; Ramos, A.R., Paúl, A., Rijniers, L., da Silva, M.F., Soares, J.C., (2002) Nucl. Instr. Meth., B190, p. 95; Randin, J.-O., (1988) J. Biomed. Mat. Res., 22, p. 649; Subramaniam, T.K., Srinivasulu Naidu, B., Uthanna, S., (1999) Cryst. Res. Technol., 34, p. 8; Rizzo, A., Signore, M.A., De Riccardis, M.F., Capodieci, L., Dimaio, D., Nocco, T., (2007) Thin Solid Films, 515, p. 6665; Sundgren, J.-E., Johansson, B.-O., Karlsson, S.-E., (1983) Thin Solid Films, 105, p. 353; Elstner, F., Ehrlich, A., Giegengack, H., Kupfer, H., Richter, F., (1994) J. Vac. Sci. Technol. A, 12, p. 476; Han, Z., Tian, J., Lai, Q., Yu, X., Li, G., (2003) Surf. Coat. Technol., 162, p. 189; Wriedt, H.A., Murray, J.L., Bull. Alloy Phase Diagrams (1987) 8/4, p. 378; Lu, K., Sui, M.L., Lück, R., (1994) Nanostruct. Mat., 4 (4), p. 465; Vaz, F., Machado, P., Rebouta, L., Cerqueira, P., Goudeau, Ph., Rivière, J.P., Alves, E., de Rijk, J., (2003) Surf. Coat. Technol., 174-175, p. 375; Norlin, A., Pan, J., Leygraf, C., (2005) J. Electrochem. Soc., 152 (2), pp. J7; Milosev, I., Strehblow, H., Navinsek, B., (1997) Thin Solid Films, 303, p. 246; Orazem, M., Tribollet, B., (2008) Electrochemical Impedance Spectroscopy, , John Wiley &Sons 233; Chappé, J.-M., Matin, N., Pearson, J., GTerwagne, J., Lintymer, J., Gavoille, J., Takadoum, (2004) Applied Suf. Sci., 222, p. 229; Logothetidis, S., Meletis, E., Stergioudis, G., Adjaottor, A., (1999) Thin Solid Films, p. 304; Huigen, E., Peper, A., Grimbergen, C., (2002) Med. Biol. Eng. Comput., 40, p. 332; Hladky, K., Dawson, J., (1982) Corrosion Sci., 22, p. 231
Keywords: Anodic currents; Bioelectric phenomena; Biomedical devices; biomedical electrodes; Blocking behaviour; Charge transfer; Charge transfer resistance; Chemical analysis; Crystalline structure; DC reactive sputtering; Dissolution; Dry electrode; EIS; Electrochemical behaviour; Electrochemical corrosion; Electrochemical electrodes; Electrochemical Noise Analysis; Electrochemical studies; Electroencephalographic signals; Ion exchange; morphology; Polarization potential; Porous structures; Selection of the best; Sensor materials; Smooth surface; Sputtering; Thin films; Titanium; Titanium nitride; Titanium substrates; Type structures; Voltammetric analysis

Skin adhesive versus subcuticular suture for perineal skin repair after episiotomy - A randomized controlled trial - Mota, R.; Costa, F.; Amaral, A.; Oliveira, F.; Santos, C.C.; Ayres-de-Campos, D. (Acta Obstetricia et Gynecologica ScandinavicaActa Obstet. Gynecol. Scand., 2009)
Objective. Surgical repair of perineal lesions after delivery is frequently associated with pain and discomfort, interfering with the normal activities of the puerperium. The aim of this study was to compare perineal skin repair after episiotomy with adhesive glue versus a subcuticular suture, regarding the incidence of pain and wound complications. Study design. Randomized clinical trial. Setting. Tertiary care university hospital. Material and methods. One hundred women having mediolateral episiotomy at vaginal delivery were enrolled. They were randomized to receive skin adhesive (n = 53) or subcuticular suture (n = 47) for closure of perineal skin. The main outcome measure was self-evaluated pain in the 30 days following delivery. Secondary outcome measures were technical difficulties reported with the procedure, duration of surgical repair, wound complications observed at 42-68 hours post-partum and re-initiation of sexual activity by 30 days post-partum. Results. No significant differences were observed between the two groups in incidence of technical difficulties and failed procedures, pain during the procedure, wound complications at hospital discharge, self-evaluated measures of pain at 7 and 30 days or re-initiation of sexual activity by 30 days post-partum. The skin adhesive group had a significantly shorter mean duration of the procedure (four minutes less). Conclusion. Perineal skin closure using adhesive glue is faster than subcuticular suture, and associated with a similar incidence of complications and pain in the first 30 days.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: AOGSAdoi: 10.1080/00016340902883133Language of Original Document: EnglishCorrespondence Address: Mota, R.; Serviço de Ginecologia e Obstetrícia, Hospital de S. João, 4200-319 Porto, Portugal; email: sisporto@med.up.ptChemicals/CAS: Tissue Adhesives; cyanoacrylic acid octyl ester, 6701-17-3; polyglactin, 26780-50-7, 34346-01-5Tradenames: Dermabond, EthiconManufacturers: EthiconReferences: Kettle, C., Hills, R.K., Jones, P., Darby, L., Gray, R., Johanson, R., Continuous versus interrupted perineal repair with standard or rapidly absorbed sutures after spontaneous vaginal birth: A randomized controlled trial (2002) Lancet, 359, pp. 2217-2223;Gordon, B., Mackrodt, C., Fern, E., Truesdale, A., Ayers, S., Grant, A., The Ipswich Childbirth Study: 1. A randomized evaluation of two stage postpartum perineal repair leaving the skin unsutured (1998) Br J Obstet Gynaecol, 105, pp. 435-440; Mackrodt, C., Gordon, B., Fern, E., Ayers, S., Truesdale, A., Grant, A., The Ipswich Childbirth Study: 2. A randomized comparison of polyglactin 910 with chromic catgut for postpartum perineal repair (1998) Br J Obstet Gynaecol, 105, pp. 441-445; Kettle, C., Johanson, R.B., Continuous versus interrupted sutures for perineal repair (2000) Cochrane DataBase Syst Rev, (2). , CD000947; Kettle, C., Hills, R.K., Ismail, K.M.K., Continuous versus interrupted sutures for repair of episiotomy or second degree tears (2007) Cochrane DataBase Syst Rev, (4). , CD000947; Gemynthe, A., Langhoff-Roos, J., Sahl, S., Knudsen, J., New VICRYL formulation: An improved method of perineal repair? (1996) Br J Midwifery, 4, pp. 230-234; Oboro, V.O., Tabowei, T.O., Loto, O.M., Bosah, J.O., A multicentre evaluation of the two-layered repair of postpartum perineal trauma (2003) J Obstet Gynaecol, 23, pp. 5-8; Kindberg, S., Stehouwer, M., Hvidman, L., Henriksen, T.B., Postpartum perineal repair performed by midwives: A randomised trial comparing two suture techniques leaving the skin unsutured (2008) Br J Obstet Gynaecol, 115, pp. 472-479; Gennari, R., Rotmensz, N., Ballardini, B., Scevola, S., Perego, E., Zanini, V., A prospective, randomized, controlled clinical trial of tissue adhesive (2-octylcyanoacrylate) versus standard wound closure in breast surgery (2004) Surgery, 136, pp. 593-599; Bernard, L., Doyle, J., Friedlander, S.F., Eichenfield, L.F., Gibbs, N.F., Cunningham, B.B., A prospective comparison of octylcya-noacrylate tissue adhesive (dermabond) and suture for the closure of excisional wounds in children and adolescents (2001) Arch Dermatol, 137, pp. 1177-1180; Matin, S.F., Prospective randomized trial of skin adhesive versus sutures for closure of 217 laparoscopic port-site incisions (2003) J Am Coll Surg, 196, pp. 845-853; Bhende, S., Rothenburger, S., Spangler, D.J., Dito, M., In vitro assessment of microbial barrier properties of Dermabond( topical skin adhesive (2002) Surg Infect, 3, pp. 251-257; Rogerson, L., Mason, G.C., Roberts, A.C., Preliminary experience with twenty perineal repairs using Indermil tissue adhesive (2000) Eur J Obstet Gynecol Reprod Biol, 88, pp. 139-142; Bowen, M.L., Selinger, M., Episiotomy closure comparing enbucrilate tissue adhesive with conventional sutures (2002) Int J Gynecol Obstet, 78, pp. 201-205; Adoni, A., Anteby, E., The use of Histoacryl for the episiotomy repair (1991) Br J Obstet Gynaecol, 98, pp. 476-478; Man, J., Quinn, J., Cyanoacrylate tissue adhesives (1997) Am J Cosm Surg, 14, pp. 413-416; Maw, J.L., Quinn, J.V., Wells, G.A., Ducic, Y., Odell, P.F., Lamothe, A., A prospective comparison of octylcyanoacrylate tissue adhesive and suture for the closure of head and neck incisions (1997) J Otolaryngol, 26, pp. 26-30
Keywords: adult; article; clinical trial; comparative study; controlled clinical trial; controlled study; cyanoacrylic acid octyl ester; edema; episiotomy; Episiotomy closure; Female; granuloma; human; Humans; injury; major clinical study; obstetric care; pain; pain assessment; Perineal repair; perineum; perineum injury; polyglactin; priority journal; questionnaire; randomized controlled trial; sexual intercourse; Skin; Skin adhesive; suture; Suture Techniques; suturing method; Tissue adhesive; Tissue Adhesives; treatment outcome; vaginal delivery; wound closure; wound dehiscence; Wounds and Injuries

3-D biomodelling technology for maxillofacial reconstruction - Oliveira, M.; Sooraj Hussain, N.; Dias, A.G.; Lopes, M.A.; Azevedo, L.; Zenha, H.; Costa, H.; Santos, J.D. (Materials Science and Engineering CMater. Sci. Eng. C, 2008)
Biomodel is a product of rapid prototyping process that represents a new approach for surgical planning and simulation. Biomodels were found to be particularly effective to locate an exact defect with good measurement accuracy and without any risk to the patients' health. These models could provide surgeons a realistic impression of complex structures before surgical intervention, allowing a define diagnosis and a precise preoperative simulation of skeleton modifying interventions. This work reports on the application of innovative 3-D biomodelling technology in the maxillofacial reconstruction. This technology allows for the calculation of the exact contours, angulations, length and general morphology of iliac crest and fibula flaps for maxillofacial reconstruction in a total of 28 clinical cases. Clinical results have shown that by using this technique, much better facial symmetry and improved functionality were achieved after surgery, which resulted in enormous benefits for treated patients. © 2008 Elsevier B.V. All rights reserved.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.msec.2008.02.007Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Instituto de Engenharia Biomédica (INEB), Laboratório de Biomateriais, Rua Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Pessa, J.E., (2001) Am. J. Orthod. Dentofac. Orthop., 119, p. 117;Poukens, J., Haex, J., Riediger, D., (2003) Comput. Aided Surg., 8 (3), p. 146; Brown, G.A., Milner, B., Firoozbakhsh, K., (2002) J. Orthop. Trauma, 16 (5), p. 347; Berry, E., Brown, J.M., Connell, M., Craven, C.M., Efford, N.D., Radjenovic, A., Smith, M.A., (1997) Med. Eng. Phys., 19 (1), p. 90; Urso, P.S.D., Barker, T.M., Earwaker, W.J., Bruce, L.J., Atkinson, R.L., Lanigan, M.W., Arvier, J.F., Effeney, D.J., (1999) J. Cranio-Maxillo-Facial Surg., 27, p. 30; Urso, P.S.D., Thompson, R.G., (1998) Aust. N.Z. J. Obstet. Gynaecol., 38, p. 205; Clair, J.J., (1996) J. Mater. Process. Technol., 57, p. 393; Pham, D.T., Gault, R.S., (1998) Int. J. Mach. Tools Manuf., 38, p. 1257; Onuh, S.O., Hon, K.K.B., (1998) Int. J. Mach. Tools Manuf., 38, p. 329; Barker, T.M., Earwaker, W.J., Lisle, D.A., (1994) Australas. Radiol., 38, p. 106; Peckitt, N.S., (1999) Br. J. Oral Maxillofac. Surg., 37, p. 353; Holck, D.E.E., Boyd Jr., E.M., Ng, J., Mauffray, R.O., B, (1999) Ophthalmology, 106, p. 1214; Pessa, J.E., Desvigne, L.D., Lambros, V.S., Nimerick, J., Sugunan, B., Zadoo, V.P., (1999) Aesthet. Plast. Surg., 23, p. 337; Gutierres, M., Dias, A.G., Lopes, M.A., Sooraj Hussain, N., Cabral, A.T., Almeida, L., Santos, J.D., (2007) J. Mater. Sci. Mater. Med., 18, p. 2377; Gauthier, O., Bouler, J.M., Aguado, E., Pilet, P., Daculsi, G., (1998) Biomaterials, 19 (1-3), p. 133; Lu, J.X., Flautre, B., Anselme, K., Hardouin, P., Gallur, A., Descamps, M., Thierry, B., (1999) J. Mater. Sci., Mater. Med., 10 (2), p. 111; Martina, M., Subramanyam, G., Weaver, J.C., Hutmacher, D.W., Morse, D.E., Valiyaveettil, S., (2005) Biomaterials, 26 (28), p. 5609; Moroni, L., de Wijn, J.R., van Blitterswijk, C.A., (2006) Biomaterials, 27 (7), p. 974; Sanghera, B., Naique, S., Papaharilaou, Y., Amis, A., (2001) Rapid Prototyping J., 7 (5), p. 275; Pentecost, J.O., Icardo, J., Thornburg, K.L., (1999) Comput. Med. Imaging Graph., 23, p. 45; Urso, P.S.D., Atkinson, R.L., Lanigan, M.W., Earwaker, W.J., Bruce, L.J., Holmes, A., Barker, T.M., Thompson, RG., (1998) Br. J. Plast. Surg., 51, p. 522
Keywords: 3D Biomodelling; Biomodels; Complex structures; Concurrent engineering; Facial symmetries; Free flap designing; Health risks; Job analysis; Maxillofacial reconstruction; Measurement accuracies; New approaches; Process engineering; Prototyping processes; Rapid prototyping; Repair; Restoration; Surgical interventions; Surgical planning; Three dimensional

Automatic cell segmentation from confocal microscopy images of the Arabidopsis root - Marcuzzo, M.; Quelhas, P.; Campilho, A.; Mendonça, A.M.; Campilho, A. (2008 5th IEEE International Symposium on Biomedical Imaging: From Nano to Macro, Proceedings, ISBIIEEE Int. Symp. Biomed. Imaging: Nano Macro, Proc., ISBI, 2008)
In vivo observation and tracking of cell division in the Arabidopsis thaliana root meristem, by time-lapse confocal microscopy, is central to biology research. The research herein described is based on large amount of image data, which must be analyzed to determine the location and state of cells. The possibility of automating the process of cell detection/marking is an important step to provide research tools to the biologists in order to ease the search for a special event as cell division. This paper discusses an automatic cell segmentation method, which selects the best cell candidates from a starting watershed based image segmentation. The selection of individual cells is obtained using a Support Vector Machine (SVM) classifier, based on the shape and edge strength of the cells' contour. The resulting segmentation is largely pruned of badly segmented cells, which can reduce the false positive detection of cell division. This is a good result on its own and a starting point for improvement of cell segmentation methodology. ©2008 IEEE.
Conference code: 73366Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusArt. No.: 4541095doi: 10.1109/ISBI.2008.4541095Language of Original Document: EnglishCorrespondence Address: Marcuzzo, M.; INEB - Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUPPortugalReferences: Campilho, A., Garcia, B., Toorn, H., Wijk, H., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the arabidopsis thaliana root meristem (2006) The Plant Journal, 48, pp. 619-627;Iwamoto, A., Satoh, D., Furutani, M., Maruyama, S., Ohba, H., Sugiyama, M., Insight into the basis of root growth in arabidopsis thaliana provided by a simple mathematical model (2006) J. Plant Res, 119, pp. 85-93; Roberts, T., Mckenna, S., Wuyts, N., Valentine, T., Bengough, A., Performance of low-level motion estimation methods for confocal microscopy of plant cells in vivo (2007) Motion07, pp. 13-13; Beemster, G., Baskin, T., Analysis of cell division and elongation underlying the developmental acceleration of root growth in arabidopsis thaliana (1998) Plant Physiology, 116, pp. 1515-1526; Garcia, B., Campilho, A., Scheres, B., Campilho, A., Automatic tracking of arabidopsis thaliana root meristem in confocal microscopy (2004) Proc. of the Inter. Conf. on Image Analysis and Recognition, pp. 166-174; Perona, P., Malik, J., Scale-space and edge detection using anisotropic diffusion (1990) IEEE Trans. on PAMI, 7 (12), pp. 629-639; Dabov, K., Foi, A., Katkovnik, V., Egiazarian, K., Image denoising by sparse 3d transform-domain collaborative filtering (2007) IEEE Trans. on Image Processing, 16 (8), pp. 2080-2095. , August; Luc, V., Soille, P., Watersheds in digital spaces: An efficient algorithm based on immersion simulations IEEE Trans. on PAMI, 13 (6); Meyer, F., Beucher, S., Morphological segmentation (1990) JVCIR, 1 (1), pp. 21-46. , Sept; Bleau, A., Leon, L., Watershed-based segmentation and region merging (2000) Comput. Vis. Image Underst, 77 (3), pp. 317-370; Kovesi, P., Symmetry and asymmetry from local phase (1997) Proc. of the Tenth Australian Joint Conf. on Artificial Intelligence, , December; Burges, C., A tutorial on support vector machines for pattern recognition (1998) Data Mining and Knowledge Discovery, 2 (2), pp. 121-167 Sponsors: Institute of Electrical and Electronic Engineers; Engineering in Medicine and Biology Society; Signal Processing Society
Keywords: Biological cells; Biomedical image processing; Cell divisions; cell proliferation; Cell segmentation; Cells; confocal microscopy; image processing; Image segmentation; Microscopic examination; Support vector machines; Technical presentations

Biocompatibility evaluation of DLC-coated Si 3N 4 substrates for biomedical applications - Salgueiredo, E.; Vila, M.; Silva, M.A.; Lopes, M.A.; Santos, J.D.; Costa, F.M.; Silva, R.F.; Gomes, P.S.; Fernandes, M.H. (Diamond and Related MaterialsDiamond Relat. Mat., 2008)
DLC coatings are of enormous interest for biotribological applications due to their biocompatibility, auto-lubricious, and non-stick properties. The most demanding implant is the hip joint. Alternative materials to metal alloys are being increasingly investigated aiming low wear debris volume, in any case innocuous wear particles. Silicon nitride (Si 3N 4) ceramics are light, tough, mechanical resistant, inert materials, turning them suitable for high-load medical applications. In this study, Si 3N 4 polished substrates were coated with adherent DLC coatings grown by DC magnetron sputtering to reduce of the friction forces against any antagonist material. Surface characterization results showed that the developed material is quite hydrophobic, with a total surface tension of 45.7 mN/m (polar component: 9.1 mN/m; dispersive component: 36.6 mN/m), and a zeta potential of - 35.0 ± 1.3 mV. In vitro testing using an acellular simulated body fluid (SBF) showed no apatite layer formation ability, as confirmed by SEM observation and analysis of the solution ions concentration with immersion time. MG63 osteoblast-like cells showed poor adhesion on the DLC films but the adherent cells displayed a normal morphology and, as compared to standard polystyrene tissue culture plates, exhibited a higher cell growth rate, suggesting no indication of cytotoxicity. Results suggested that the novel DLC-coated Si 3N 4 biomaterial should be adequate to be used for articular prostheses medical application. © 2007 Elsevier B.V. All rights reserved.
Cited By (since 1996): 30Export Date: 21 November 2012Source: ScopusCODEN: DRMTEdoi: 10.1016/j.diamond.2007.08.019Language of Original Document: EnglishCorrespondence Address: Silva, R.F.; CICECO, Glass and Ceramics Eng. Department, University of Aveiro, 3810-193 Aveiro, Portugal; email: rsilva@cv.ua.ptReferences: Sargeant, A., Goswami, T., (2006) Mater. Des., 27, p. 287;Petzow, G., Herrmann, M., (2002) Structure and Bonding, 102, p. 47. , Janson M. (Ed), Springer-Verlag, Berlin; Narayan, R.J., (2005) Mater. Sci. Eng., C, Biomin. Mater., Sens. Syst., 25, p. 405; Cui, F.Z., Li, D.J., (2000) Surf. Coat. Technol., 131, p. 481; Zhao, Q., Liu, Y., Abel, E.W., (2004) J. Colloid Interface Sci., 280, p. 174; Vila, M., Abreu, C.S., Salgueiredo, E., Almeida, F.A., Fernandes, A.J.S., Costa, F.M., Gomes, J.R., Silva, R.F., (2006) Thin Solid Films, 515, p. 2192; Fairbrother, F., Mastin, H., (1924) J. Chem. Soc., 75, p. 2318; Owens, D.K., Wendt, R.D., (1969) J. Appl. Polym. Sci., 13, p. 1741; Kokubo, T., Takadama, H., (2006) Biomaterials, 27, p. 2907; Strom, G., Fredriksson, M., Stenius, P., (1987) J. Colloid Interface Sci., 119, p. 352; Schulz, H., Leonhardt, M., Scheibe, H.J., Schultrich, B., (2005) Surf. Coat. Technol., 200, p. 1123; Wilson, C.J., (2005) Tissue Eng., 11, p. 1; Haynes, C.A., Norde, W., (1994) Colloids Surf., B Biointerfaces, 2, p. 517; Shelton, R.M., Rasmussen, A.C., Davies, J.E., (1988) Biomaterials, 9, p. 24; Davies, J.E., Causton, B., Bovell, Y., Davy, K., Sturt, C.S., (1986) Biomaterials, 7, p. 231; Dearnaley, G., Arps, J.H., (2005) Surf. Coat. Technol., 200, p. 2518
Keywords: Biocompatibility; Biomedical applications; Cell cultures; Coatings; Diamond like carbon films; DLC coatings; Hip joint; hydrophobicity; Magnetron sputtering; Medical applications; Metal alloys; Simulated body fluid (SBF); Tribology; Wear of materials

Bone ingrowth in macroporous Bonelike ® for orthopaedic applications - Gutierres, M.; Lopes, M.A.; Sooraj Hussain, N.; Lemos, A.F.; Ferreira, J.M.F.; Afonso, A.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Acta BiomaterialiaActa Biomater., 2008)
The aim of this study was to evaluate the biological behaviour of porous scaffold structures of Bonelike ® which is suitable for either direct clinical use or tissue engineering applications. Porous cylindrical specimens 8 × 10 mm were implanted in the lateral aspect of the tibia of 13 patients (mean age 54 years), during osteotomy surgery for the treatment of medial compartment osteoarthritis of the knee. Implanted cylinders were retrieved at the same time as the removal of the blade plates at 3, 6, 9 and 12 months. Scanning electron microscopy and histological evaluations were performed to observe the biological responses of human bone tissue to porous Bonelike ®. The penetration depth was determined for all implantation periods, and after 6 months it was already possible to see new bone in the centre of the implanted cylinders, which gives 100% of penetration depth for all implantations periods except for 3 months when bone could only be seen in the peripherical region. Regarding the percentage of the area covered by new bone calculated from two-dimensional histological sections, values of 53 ± 15, 76 ± 12 and 88 ± 9% were achieved for 6, 9 and 12 months, respectively. Due to its structural features porous Bonelike ® permitted effective vascularization and bone ingrowth, and therefore was fully osteointegrated as shown in the histological surveys. A slow biomaterial degradation with implantation time is envisaged since the material has displayed surface degradation. Bonelike ® scaffolds show potential for complete ingrowth of osseous tissue and restoration of vascularization throughout the defected site. © 2007.
Cited By (since 1996): 13Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2007.06.009PubMed ID: 17716960Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; FEUP - Faculdade de Engenharia, Universidade do Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Bone SubstitutesTradenames: BonelikeReferences: Akamatsu, Y., Koshino, T., Saito, T., Wada, J., Changes in osteosclerosis of the osteoarthritic knee after high tibial osteotomy (1997) Clin Orthop, 334, pp. 207-214;Coventry, M.B., Ilstrup, D.M., Wallrichs, S.L., Proximal tibial osteotomy. A critical long-term study of eighty-seven cases (1993) J Bone Joint Surg, 75 -A, pp. 196-201; Hernigou, P., Medevielle, D., Debeyre, J., Goutallier, D., Proximal tibial osteotomy for osteoarthritis with varus deformity. A ten to thirteen-year follow-up study (1987) J Bone Joint Surg Am, 69, pp. 332-354; Hernigou, P., Ma, W., Open wedge tibial osteotomy with acrylic bone cement as bone substitute (2001) Knee, 8, pp. 103-110; Koshino, T., Murase, T., Saito, T., Medial opening-wedge high tibial osteotomy with use of porous hydroxyapatite to treat medial compartment osteoarthritis of the knee (2003) J Bone Joint Surg Am, 85, pp. 78-85; Simske SJ, Ayers RA, Bateman TA. Porous Materials for Bone Engineered. In: Materials Science Forum. Zurich: Trans Tech Publications; 1997. Vol. 250, pp. 151-182Hing, K.A., Bone repair in the twenty-first century: biology, chemistry or engineering? (2004) Philos Trans A Math Phys Eng Sci, 362 (1825), pp. 2821-2850; Hui, P.W., Leung, P.C., Sher, A., Fluid conductance of cancellous bone graft as a predictor for graft-host interface healing (1996) J Biomech, 29 (1), pp. 123-132; Ben-Nissan, B., Natural bioceramics: from coral to bone and beyond (2003) Curr Opin Solid State Mater Sci, 7 (4-5), p. 283; Shors, E.C., Holmes, R.E., Porous hydroxyapatite (1993) Introduction to Biomaterials, pp. 181-198. , Hench L.L., and Wilson J. (Eds), World Scientific, Singapore; Prado da Silva, M.H., Lemos, A.F., Gibson, I.R., Ferreira, J.M.F., Santos, J.D., Porous glass reinforced hydroxyapatite materials produced with different organic additives (2002) J Non-Cryst Solids, 304, pp. 286-292; Prado da Silva, M.H., Lemos, A.F., Ferreira, J.M.F., Lopes, M.A., Santos, J.D., Production of porous biomaterials based on glass reinforced hydroxyapatite composites (2002) Key Eng Mater, 230-232, pp. 483-486; Rocha, J., Lemos, A., Agathopoulos, S., Valério, P., Kannan, S., Oktar, F., Scaffolds for bone restoration from cuttlefish (2005) Bone, 37 (6), pp. 850-857; Sepulveda, P., Binner, J.G.P., Processing of cellular ceramics by foaming and in situ polymerization of organic monomers (1999) J Eur Ceram Soc, 19 (12), pp. 2059-2066; Ozgur Engin, N., Cuneyt Tas, A., Manufacture of macroporous calcium hydroxyapatite bioceramics (1999) J Eur Ceram Soc, 19 (13-14), pp. 2569-2572; Peng, H.X., Fan, Z., Evans, J.R.G., Busfield, J.J.C., Microstructure of ceramic foams (2000) J Eur Ceram Soc, 20 (7), pp. 807-813; Komlev Vladimir, S., Barinov Serguei, M., Koplik Elena, V., A method to fabricate porous spherical hydroxyapatite granules intended for time-controlled drug release (2002) Biomaterials, 23 (16), pp. 3449-3454; Milosevski, M., Bossert, J., Milosevski, D., Gruevska, N., Preparation and properties of dense and porous calcium phosphate (1999) Ceram Int, 25, pp. 693-696; Tadic, D., Beckmann, F., Schwarz, K., Epple, M., A novel method to produce hydroxyapatite objects with interconnecting porosity that avoids sintering (2004) Biomaterials, 25, pp. 3335-3340; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., Influence of characteristics of the starting hydroxyapatite powders and of deagglomeration procedure, on rheological behaviour of the suspensions (2004) Mater Sci Forum, 455-456, pp. 361-365; Lemos, A.F., Ferreira, J.M.F., Porous bioactive calcium carbonate implants processed by starch consolidation (2000) J Mat Sci Eng C, C11, pp. 35-40; Lemos, A.F., Ferreira, J.M.F., Combining foaming and starch consolidation methods to develop macroporous HA implants (2004) Key Eng Mater, 254-256, pp. 1041-1044; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., New method for the incorporation of soluble bioactive glasses to reinforce porous HA structures (2004) Key Eng Mater, 254-256, pp. 1033-1036; Gauthiera, O., Boulerb, J.M., Aguadoa, E., Piletb, P., Daculsi, G., Macroporous biphasic calcium phosphate ceramics: influence of macropore diameter and macroporosity percentage on bone ingrowth (1998) Biomaterials, 19, pp. 133-139; Hing, A.K., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Mediation of bone ingrowth in porous hydroxyapatite bone graft substitutes (2004) J Biomed Mater Res, 68 A, pp. 187-200; Rubin, P.A., Popham, J.K., Bilyk, J.R., Shore, J.W., Comparison of fibrovascular ingrowth into hydroxyapatite and porous polyethylene orbital implants (1994) Ophthal Plast Reconstr Surg, 10 (2), pp. 96-103; Hing, K.A., Annaz, B., Saeed, S., Revell, P.A., Buckland, T., Microporosity enhances bioactivity of synthetic bone graft substitutes (2005) J Mater Sci: Mater Med, 16, pp. 467-475; Klawitter, J.J., Bagwell, J.G., Weinstein, A.M., Sauer, B.W., An evaluation of bone growth into porous high density polyethylene (1976) J Biomed Mater Res, 10 (2), pp. 311-323; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Quantification of bone ingrowth within bone-derived porous hydroxyapatite implants of varying density (1999) J Mater Sci: Mater Med, 10, pp. 663-670; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Biomechanical assessment of bone ingrowth in porous hydroxyapatite (1997) J Mater Sci: Mater Med, 8, pp. 731-736; Ayers, R.A., Wolford, L.M., Bateman, T.A., Ferguson, V.L., Simske, S.J., Quantification of bone ingrowth into porous block hydroxyapatite in humans (1999) J Biomed Mater Res, 47, pp. 54-59; Lu, J.X., Flautre, B., Anselme, K., Hardouin, P., Gallur, A., Descamps, M., Role of interconnections in porous bioceramics on bone recolonization in vitro and in vivo (1999) J Mater Sci: Mater Med, 10 (2), pp. 111-120; Eggli, P.S., Muller, W., Schenk, R.K., Porous hydroxyapatite and tricalcium phosphate cylinders with two different pore size ranges implanted in the cancellous bone of rabbits - A comparative histomorphometric and histologic study of bony ingrowth and implant substitution (1988) Clin Orthop Relat Res, 232, pp. 127-138; Kuhne, J.H., Bartl, R., Frisch, B., Hammer, C., Jansson, V., Zimmer, M., Bone formation in coralline hydroxyapatite. Effects of pore size studied in rabbits (1994) Acta Orthop Scand, 65 (3), pp. 246-252; Holmes, R., Mooney, V., Bucholz, R., Tencer, A., A coralline hydroxyapatite bone graft substitute. Preliminary report (1984) Clin Orthop Relat Res, 188, pp. 252-262; Lopes, M.A., Knowles, J.C., Santos, J.D., Structural insights of glass-reinforced hydroxyapatite composites by Rietveld refinement (2000) Biomaterials, 21 (18), pp. 1905-1910; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass-reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39 (2), pp. 244-251; Santos JD, Hastings G, Knowles JC. Sintered hydroxyapatite compositions and method for the preparation thereof. Worldwide Application (PCT), Patent No. 1 189 851, 1999Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: fracture toughness and hardness dependence on microstructural characteristics (1999) Biomaterials, 20 (21), pp. 2085-2090; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: Secondary phase proportions and densification effects on biaxial bending strength (1999) J Biomed Mater Res, 48 (5), pp. 734-740; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, Surface tension and Zeta potential measurements of glass reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Direct and Indirect effects of P 2O 5 - glass reinforced - hydroxyapatite composites and growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibiae of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., HA and Double layer HA-P 2O 5/CaO Glass coatings: influence of chemical composition on human bone marrow cells osteoblastic behaviour (2001) J Mater Sci: Mater Med, 12, pp. 629-638; Gutierres, M., Hussain, N.S., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Biological behaviour of Bonelike ® graft implanted in the tibia of humans (2005) Key Eng Mater, 17, pp. 1041-1044; Duarte, F., Santos, J.D., Afonso, A., Medical applications of Bonelike ® in maxillofacial surgery (2004) Adv Mater Forum, pp. 370-373; Lobato, J.V., Hussain, N.S., Botelho, C.M., Titanium dental implants coated with Bonelike ®: clinical case report (2006) Thin Solid Films, 515, p. 279; Coventry, M.B., Osteotomy of the upper portion of the tibia for degenerative arthritis of the knee: a preliminary report (1965) J Bone Joint Surg Am, 47, pp. 984-990; Coventry, M.B., Upper tibia osteotomy for gonarthrosis. The evolution of the operation in the last 18 years and long term results (1979) Orthop Clin North Am, 10, pp. 191-210; Coventry, M.B., Current concepts review. Upper tibia osteotomy for osteoarthritis (1985) J Bone Joint Surg Am, 67 A, pp. 1136-1140
Keywords: adult; aged; article; biomaterial; bone defect; Bone graft; bone growth; Bone Regeneration; Bone Substitutes; bone tissue; Bonelike; clinical article; controlled study; Female; histology; human; human tissue; Humans; implant; knee osteoarthritis; male; materials testing; Microscopy, Electron, Scanning; Middle Aged; molecular scaffold; Orthopaedic; orthopedics; Osseointegration; Osteoarthritis; osteotomy; porosity; Porous materials; priority journal; Prostheses and Implants; Scanning electron microscopy; tibia; Time Factors; Tissue engineering; tissue section; vascularization; ®

Chromatographic pattern classification - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (IEEE Transactions on Biomedical EngineeringIEEE Trans. Biomed. Eng., 2008)
In this paper, we propose and evaluate methodologies for the classification of images from thin-layer chromatography. Each individual sample is characterized by an intensity profile that is further represented into a feature space. The first steps of this process aim at obtaining a robust estimate of the intensity profile by filtering noise, reducing the influence of background changes, and by fitting a mixture of Gaussians. The resulting profiles are represented by a set of appropriate features trying to characterize the state of nature, here spread out over four classes, one for normal subjects and the other three corresponding to lysosomal diseases, which are disorders responsible for severe nerve degeneration. For classification purposes, a novel solution based on a hierarchical structure is proposed. The main conclusion of this paper is that an automatically generated decision tree presents better results than more conventional solutions, being able to deal with the natural imbalance of the data that, as consequence of the rarity of lysosomal disorders, has very few representative cases in the disease classes when compared with the normal population. © 2008 IEEE.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusArt. No.: 8CODEN: IEBEAdoi: 10.1109/TBME.2008.919852PubMed ID: 18714832Language of Original Document: EnglishCorrespondence Address: Sousa, A. V.; Instituto de Engenharia Biomédica (INEB), Instituto Superior de Engenharia Do Porto, 4200-465 Porto, Portugal; email: ats@isep.ipp.ptChemicals/CAS: Hydrolases, EC 3.-References: Keir, G., Winchester, B., Clayton, P., Carbohydrate-deficient glycoprotein syndromes: Inborn errors of protein glycosylation (1999) Ann. Clin. Biochem, 36 (1), pp. 20-36;Durand, G., Seta, N., Protein glycosylation and diseases: Blood and urinary oligosaccharides as markers for diagnosis and therapeutic monitoring (2000) Clin. Chem, 46, pp. 795-805; Scriver, S., Beaudet, A., Sly, W., Valle, D., (2001) The Metabolic Bases of Inherited Disease, 3. , New-York: McGraw-Hill; Pinto, R., Caseiro, C., Lemos, M., Lopes, L., Fontes, A., Miranda, M., Prevalence of lysosomal storage diseases in Portugal (2004) Eur. J. Hum. Genet, 12, pp. 87-92; Friedman, R., Williams, M., Moser, H., Kolodny, E., Improved thin-layer chromatographic method in the diagnosis of mannosidosis (1978) Clin. Chem, 24, pp. 1576-1577; Kurczynski, T., Kendzierski, K., Sewell, A., Kuczynski, T., Urinary oligosaccharides in pregnant or lactating women: Pitfall in screening (1993) Clin. Chem, 39, pp. 2346-2347; Sewell, A., Urinary oligosaccharides (1991) Techniques Diagnostic Human Biochemical Genetics, pp. 219-231. , New York: Wiley; Reich, E., Blatter, A., Modern TLC: A key technique for identification and quality control of botanicals and dietary supplements (2005) J. Planar Chromatogr. - Modern TLC, 18, pp. 34-37. , Jan./Feb; Duvdevani-Bar, S., Edelman, S., Visual recognition and categorization on the basis of similarities to multiple class prototypes (1999) Int. J. Comput. Vis, 33, pp. 201-228; Pekalska, E., Duin, R., Dissimilarity representations allow for building good classifiers (2002) Pattern Recognit. Lett, 23, pp. 943-956; Goldstone, R., Son, J., Similarity (2005) Cambridge Handbook of Thinking and Reasoning, pp. 13-36. , K. Holyoak and R. Morrison, Eds. Cambridge, MA: Cambridge Univ. Press; Lavine, B., Clustering and classification of analytical data (2000) Encyclopedia of Analytical Chemistry: Instrumentation and Applications, pp. 9689-9710. , R. Meyers, Ed. Chichester, U.K, Wiley; Japkowicz, N., Learning from imbalanced data sets: A comparison of various strategies (2000) Proc. Learn. Imbalanced Data, pp. 10-15; Weiss, G., Mining with rarity: A unifying framework (2004) Sigkdd Explor, 6, pp. 7-19; Kubat, M., Holte, R., Matwin, S., Machine learning for the detection of oil spills in satellite radar images (1998) Mach. Learn, 30, pp. 195-215; Tax, D., One-class classification; concept-learning in the absence of counter-examples, (2001), ASCI, pp. 1-190. , Ph.D. dissertation, Delft Univ. Technol, Dissertation Ser, ppSousa, A., Aguiar, R., Mendonça, A., Campilho, A., Automatic lane and band detection in images of thin layer chromatography (2004) Lecture Notes in Computer Science, 3212, pp. 158-165. , Image Analysis and Recognition, New York: Springer-Verlag; Schwedt, G., (1997) The Essential Guide to Analytical Chemistry, , New York: Wiley; Bajla, I., Hollander, I., Fluch, S., Burg, K., Kollar, M., An alternative method for electrophoretic gel image analysis in the GelMaster software (2005) Comput. Methods Programs Biomed, 77, pp. 209-231; Eibrand, R., Kennedy, P., Cotter, D., MacEvilly, U., Wu, B., Analysis of Atlantic salmon skin mucus: COPS - A computer-based system for protein pattern analysis of 1D SDS-PAGE gels (2003) Proc. IEEE Symp. Bioinf. BioEng, pp. 45-52; Gerasimov, A., Use of the software processing of scanned chromatogram images in quantitative planar chromatography (2004) J. Anal. Chem, 59, pp. 348-353; Goulding, P., (2000) Electrophoresis Gel Analysis Software: Important Aspects, p. 14. , Cambridge, U.K, UVItec Ltd; Jedra, M., El Khattabi, N., Limouri, M., Essaid, A., Recognition of seed varieties using a time-delay neural network: Analysis of electrophoretic images (1999) Comput. Electron. Agric, 22, pp. 1-10; Machado, A., Campos, M., Siqueira, A., Carvalho, O., An iterative algorithm for segmenting lanes in gel electrophoresis images (1997) Proc. Comput. Graph. Image Process. X Braz. Symp, pp. 140-146. , Campos do Jordao, Brazil, Oct; Ye, X., Suen, C., Cheriet, M., Wang, E., A recent development in image analysis of electrophoresis gels (1999) Proc. Vis. Interface, pp. 432-438; Shadle, S., Allen, D., Guo, H., Pogozelski, W., Bashkin, J., Tullius, T., Quantitative analysis of electrophoresis data: Novel curve fitting methodology and its application to the determination of a protein-DNA binding constant (1997) Nucleic Acids Res, 25, pp. 850-860; Bajla, I., Hollander, I., Burg, K., Improvement of electrophoretic gel image analysis (2001) Meas. Sci. Rev, 1, pp. 5-10; Bajla, I., Hollander, I., Burg, K., Fluch, S., A novel approach to quantitative analysis of electrophoretic gel images of DNA fragments (2002) Proc. IEEE Int. Symp. Biomed. Imag, pp. 899-902; Lonni, A., Scarminio, I., Silva, L., Ferreira, D., Differentiation of species of Baccharis Genus by HPLC and chemometrics methods (2003) Anal. Sci, 19, pp. 1013-1017; Beltrán, N., Duarte-Mermoud, M., Salah, S., Bustos, M., Feature selection algorithms using Chilean wine chromatograms as examples (2005) J. Food Eng, 67, pp. 483-490; Landgrebe, D., Information extraction principles and methods for multispectral and hyperspectral image data (2000) Information Processing for Remote Sensing, , Hackensack, NJ: World Scientific, ch. 1; Landgrebe, D., Hyperspectral image data analysis as a high dimensional signal processing problem (2002) IEEE Signal Process. Mag, 19 (1), pp. 17-28. , Jan; Jimenez, L., Landgrebe, D., Hyperspectral data analysis and feature reduction via projection pursuit (1999) IEEE Trans. Geosci. Remote Sens, 37 (6), pp. 2653-2667. , Nov; Jimenez, L., Landgrebe, D., Supervised classification in high- dimensional space: Geometrical, statistical, and asymptotical properties of multivariate data (1998) IEEE Trans. Syst., Man, Cybern, 28 (1), pp. 39-54. , Pt. C, Feb; Marques deSá, J., (2001) Pattern Recognition - Concepts, Methods and Applications, , Berlin, Germany: Springer-Verlag; Heijden, F., Duin, R., Ridder, D., Tax, D., (2004) Classification, Parameter Estimation and State Estimation, , New York: Wiley; Dudoit, S., Fridlyand, J., Speed, T., Comparison of discrimination methods for the classification of tumors using gene expression data (2002) J. Amer. Stat. Assoc, 97, pp. 77-87; Zomer, S., Brereton, R., Carter, J., Eckers, C., Support vector machines for the discrimination of analytical chemical data: Application to the determination of tablet production by pyrolysis-gas chromatography-mass spectrometry (2004) Analyst, 129, pp. 175-181; Zomer, S., Guillo, C., Brereton, R., Hanna-Brown, M., Toxicological classification of urine samples using pattern recognition techniques and capilarity electrophoresis (2003) Anal. Bioanal. Chem, 378, pp. 2008-2020; Fan, X., Bai, J., Shen, P., Diagnosis of breast cancer using HPLC metabonomics fingerprints coupled with computational methods (2005) 27th Annu. Conf. Eng. Med. Biol, pp. 6081-6084. , Shanghai, China; Skurichina, M., Raudys, S., Duin, R., K-nearest neighbors directed noise injection in multilayer perceptron training (2000) IEEE Trans. Neural Netw, 11 (2), pp. 504-511. , Mar; Ha, T., Bunke, H., Off-line, handwritten numeral recognition by perturbation method (1997) IEEE Trans. Pattern Anal. Mach. Intell, 19, pp. 535-539; Lee, S., Noisy replication in skewed binary classification (2000) Comput. Stat. Data Anal, 34, pp. 165-191; Demant, C., Streicher-Abel, B., Waszkewitz, P., (1999) Industrial Image Processing, , New York: Springer-Verlag; Dempster, A., Laird, N., Rubin, D., Maximum likelihood from incomplete data via the EM algorithm (1977) J. Roy. Stat. Soc. B, 39 (1), pp. 1-38; Moré, J., Sorensen, D., Computing a trust region step (1983) SIAM J. Sci. Stat. Comput, 4, pp. 553-572; Byrd, R., Schnabel, R., Shultz, G., Approximate solution of the trust region problem by minimization over two-dimensional subspaces (1988) Math. Program, 40, pp. 247-263; Sousa, A., Mendonça, A., Campilho, A., Aguiar, R., Miranda, C., Feature extraction for classification of thin-layer chromatography images (2005) Lecture Notes in Computer Science, 3656, pp. 974-981. , Image Analysis and Recognition, New York: Springer-Verlag; Ripley, B., (2004) Pattern Recognition and Neural Networks, , New York: Cambridge Univ. Press; Visa, S., Ralescu, A., Learning imbalanced and overlapping classes using fuzzy sets (2003) ICML 2003, Workshop Learn. Imbalanced Datasets, 2. , presented at the, Washington, DC
Keywords: Acoustic variables control; Algorithms; article; Chromatographic analysis; Chromatographic pattern features; Chromatographic profiles; Chromatography; Chromatography, Thin Layer; Classification; Diagnosis, Computer-Assisted; Gaussian noise (electronic); Hierarchical classifier; Humans; Hydrolases; imaging; Lysosomal Storage Diseases; lysosome storage disease; mathematical analysis; nerve degeneration; noise; normal distribution; Pattern recognition; Pattern Recognition, Automated; Reproducibility of Results; sensitivity and specificity; Urinalysis

Dissimilarity-based classification of chromatographic profiles - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Pattern Analysis and ApplicationsPattern Anal. Appl., 2008)
This paper proposes a non-parametric method for the classification of thin-layer chromatographic (TLC) images from patterns represented in a dissimilarity space. Each pattern corresponds to a mixture of Gaussian approximation of the intensity profile. The methodology comprises various phases, including image processing and analysis steps to extract the chromatographic profiles and a classification phase to discriminate among two groups, one corresponding to normal cases and the other to three pathological classes. We present an extensive study of several dissimilarity-based approaches analysing the influence of the dissimilarity measure and the prototype selection method on the classification performance. The main conclusions of this paper are that, Match and Profile-difference dissimilarity measures present better results, and a new prototype selection methodology achieves a performance similar or even better than conventional methods. Furthermore, we also concluded that simplest classifiers, such as k-NN and linear discriminant classifiers (LDCs), present good performance being the overall classification error less than 10% for the four-class problem. © 2008 Springer-Verlag London Limited.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1007/s10044-008-0113-2Language of Original Document: EnglishCorrespondence Address: Sousa, A. V.; Instituto Superior de Engenharia do Porto, Rua Dr. António Bernardino Almeida, 431, 4200-072 Porto, Portugal; email: ats@isep.ipp.ptReferences: Reich, E., Blatter, A., Modern TLC: A key technique for identification and quality control of botanicals and dietary supplements (2004) Inside Laboratory Management-AOC International;Sousa, A.V., Aguiar, R., Mendonça, A.M., Campilho, A., Automatic lane and band detection in images of thin layer chromatography (2004) LNCS, 3212, pp. 158-165. , Proceedings of image analysis and recognition: international conference, ICIAR 2004, Porto Springer, Heidelberg; Keir, G., Winchester, B.G., Clayton, P., Carbohydrate-deficient glycoprotein syndromes: Inborn errors of protein glycosylation (1999) Ann Clin Biochem, 36, pp. 20-36. , Pt 1; Durand, G., Seta, N., Protein glycosylation and diseases: Blood and urinary oligosaccharides as markers for diagnosis and therapeutic monitoring (2000) Clin Chem, 46, pp. 795-805; Schwedt, G., (1997) The Essential Guide to Analytical Chemistry, , Wiley New York; Bajla, I., Hollander, I., Fluch, S., Burg, K., Kollar, M., An alternative method for electrophoretic gel image analysis in the GelMaster software (2005) Comput Methods Programs Biomed, 77, pp. 209-231; Eibrand, R., Kennedy, P., Cotter, D., MacEvilly, U., Wu, B., Analysis of atlantic salmon skin mucus: COPS-a computer-based system for protein pattern analysis of 1D SDS-PAGE gels (2003) Proceedings of the Third IEEE Symposium on Bioinformatics and Bioengeneering; Gerasimov, A.V., Use of the software processing of scanned chromatogram images in quantitative planar chromatography (2004) J Anal Chem, 59, pp. 348-353; (2000) Gel Analysis Software: Important Aspects, , Goulding electrophoresis PN UVItec Ltd; Jedra, M., El Khattabi, N., Limouri, M., Essaid, A., Recognition of seed varieties using a time-delay neural network: Analysis of electrophoretic images (1999) Comput Electron Agric, 22, pp. 1-10; MacHado, A.M.C., Campos, M.F.M., Siqueira, A.M., De Carvalho, O.S.F., An iterative algorithm for segmenting lanes in gel electrophoresis images. Computer graphics and image processing (1997) Proceedings of X Brazilian Symposium, pp. 140-146; Ye, X., Suen, C.Y., Cheriet, M., Wang, E., A recent development in image analysis of electrophoresis gels (1999) Vision Iterface 99, , Trois-Rivieres, Canada; Wang, D., Keller, J.M., Carson, C.A., Pulsed-field gel electrophoresis pattern recognition of bacterial DNA: A systemic approach (2001) Pattern Anal Appl, 4, pp. 244-255; Shadle, S.E., Allen, D.F., Guo, H., Pogozelski, W.K., Bashkin, J.S., Tullius, T.D., Quantitative analysis of electrophoresis data: Novel curve fitting methodology and its application to the determination of a protein-NA binding constant (1997) Nucleic Acids Res, 25, pp. 850-860; Bajla, I., Hollander, I., Burg, K., Improvement of electrophoretic gel image analysis (2001) Measurement Science Review, 1; Bajla, I., Hollander, I., Burg, K., Fluch, S., (2002) A Novel Approach to Quantitative Analysis of Electrophoretic Gel Images of DNA Fragments, pp. 899-902. , IEEE international symposium on biomedical imaging Washington; Lavine, B.K., Meyers, R.A., Clustering and classification of analytical data (2000) Encyclopedia of Analytical Chemistry: Instrumentation and Applications, pp. 9689-9710. , Wiley Chichester; Lonni, A., Scarminio, I., Silva, L., Ferreira, D., Differentiation of species of bacharis genus by HPLC and chemometrics methods (2003) Analytical Sciences, 19; Beltrán, N.H., Duarte-Mermoud, M.A., Salah, S.A., Bustos, M.A., Feature selection algorithms using Chilean wine chromatograms as examples (2005) J Food Eng, 67, pp. 483-490; Landgrebe, D., Information extraction principles and methods for multispectral and hyperspectral image data (1999) Proceedings of Information Processing for Remote Sensing, , World Scientific, Singapore; Landgrebe, D., Hyperspectral image data analysis as a high dimensional signal processing problem (2002) IEEE Signal Process Mag, 19, pp. 17-28; Jimenez, L., Landgrebe, D., Hyperspectral data analysis and feature reduction via projection pursuit (1999) IEEE Trans Geosci Remote Sens, 37, pp. 2653-2667; Jimenez, L.O., Landgrebe, D.A., Supervised classification in high-dimensional space: Geometrical, statistical, and asymptotical properties of multivariate data (1998) IEEE Transaction on Systems Man, and Cybernetics-Part C: Applications and Reviews, 28; Paclik, P., Duin, R.P.W., Dissimilarity-based classification of spectra: Computational issues (2003) Real-Time Imaging, 9, pp. 237-244; Paclik, P., Duin, R.P.W., Classifying spectral data using relational representation (2003) Proceedings of Spectral Imaging Workshop, , Graz; Pekalska, E., Paclik, P., Duin, R.P.W., A generalized kernel approach to dissimilarity-based classification (2001) J Mach Learn Res, 2, pp. 175-211; Pekalska, E., Duin, R.P.W., Dissimilarity representations allow for building good classifiers (2002) Pattern Recogn Lett, 23, pp. 943-956; Pekalska, E., Duin, R.P.W., (2005) The Dissimilarity Representation for Pattern Recognition-foundations and Applications, 64. , World Scientific, Singapore; Pekalska, E., Duin, R.P.W., Paclik, P., Prototype selection for dissimilarity-based classifiers (2006) Pattern Recogn, 39, pp. 189-208; Harol, A., Lai, C., Pekalska, E., Duin, R.P.W., Pairwise feature evaluation for constructing reduced representations (2007) Pattern Anal Appl, 10, pp. 55-68; Dubuisson, M.-P., Jain, A.K., A modified Hausdorff distance for object matching (1994) Proceedings of International Conference on Pattern Recognition, pp. 566-568. , Jerusalem; Heijden, F., Robert, P.W.D., Ridder, D., Tax, D.M.J., (2004) Classification, Parameter Estimation and State Estimation, , Wiley, New York; Dasarathy, B.V., Sánchez, J.S., Townsend, S., Nearest neighbour editing and condensing tools-synergy exploitation (2000) Pattern Anal Appl, 3, pp. 19-30; Devijver, P., Kittler, J., (1982) Pattern Recognition: A Statistical Approach, , Prentice-Hall, New Jersey; Cheng, Y., Mean shift, mode seeking, and clustering (1995) IEEE Trans Pattern Anal Mach Intell, 17, pp. 790-799; Vijaya, P.A., Murty, M.N., Subramanian, D.K., Efficient median based clustering and classification techniques for protein sequences (2006) Pattern Anal Appl, 9, pp. 243-255; Sousa, A.V., Mendonça, A.M., Campilho, A., Aguiar, R., Miranda, C.S., Feature extraction for classification of thin-layer chromatography images (2005) Proceedings of Image Analysis and Recognition, Second International Conference, ICIAR 2005, 3656, pp. 974-981. , LNCS Springer, Toronto; Dempster, A., Laird, N., Rubin, D., Maximum likelihood from incomplete data via the em algorithm (1977) J R Stat Soc, B-39, pp. 1-38. , 1; Moré, J.J., Sorensen, D.C., Computing a trust region step (1983) SIAM J Sci Stat Comput, 4, pp. 553-572; Byrd, R.H., Schnabel, R.B., Shultz, G.A., Approximate solution of the trust region problem by minimization over two-dimensional subspaces (1988) Math Program, 40, pp. 247-263; Visa, S., Ralescu, A., Learning imbalanced and overlapping classes using fuzzy sets (2003) Workshop on Learning from Imbalanced Datasets II, , ICML, Washington DC; Sousa, A.V., Mendonça, A.M., Campilho, A.C., The class imbalance problem in TLC image classification (2006) Proceedings of Image Analysis and Recognition, Third International Conference, ICIAR 2006, 4142, pp. 513-523. , September 18-20, 2006, proceedings, Part II, Póvoa de Varzim. LNCS Springer, Portugal
Keywords: Chromatographic images; Dissimilarity representation; Nearest neighbour classifiers; Prototype selection

A hybrid approach for arabidopsis root cell image segmentation - Marcuzzo, M.; Quelhas, P.; Campilho, A.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
In vivo observation and tracking of the Arabidopsis thaliana root meristem, by time-lapse confocal microscopy, is important to understand mechanisms like cell division and elongation. The research herein described is based on a large amount of image data, which must be analyzed to determine the location and state of cells. The automation of the process of cell detection/marking is an important step to provide research tools for the biologists in order to ease the search for special events, such as cell division. This paper discusses a hybrid approach for automatic cell segmentation, which selects the best cell candidates from a starting watershed-based image segmentation and improves the result by merging adjacent regions. The selection of individual cells is obtained using a Support Vector Machine (SVM) classifier, based on the shape and edge strength of the cells' contour. The merging criterion is based on edge strength along the line that connects adjacent cells' centroids. The resulting segmentation is largely pruned of badly segmented and over-segmented cells, thus facilitating the study of cell division. © 2008 Springer-Verlag Berlin Heidelberg.
Conference code: 72695Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-540-69812-8_73Language of Original Document: EnglishCorrespondence Address: Marcuzzo, M.; INEB - Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUPPortugalReferences: Campilho, A., Garcia, B., Toorn, H., Wijk, H., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the arabidopsis thaliana root meristem (2006) The Plant Journal, 48, pp. 619-627;Iwamoto, A., Satoh, D., Furutani, M., Maruyama, S., Ohba, H., Sugiyama, M., Insight into the basis of root growth in arabidopsis thaliana provided by a simple mathematical model (2006) J. Plant Res, 119, pp. 85-93; Roberts, T., Mckenna, S., Wuyts, N., Valentine, T., Bengough, A.: Performance of low-level motion estimation methods for confocal microscopy of plant cells in vivo. In: Motion 2007, pp. 13-13 (2007)Beemster, G., Baskin, T., Analysis of cell division and elongation underlying the developmental acceleration of root growth in arabidopsis thaliana (1998) Plant Physiology, 116, pp. 1515-1526; Garcia, B., Campilho, A., Scheres, B., Campilho, A., Automatic Tracking of Arabidopsis thaliana Root Meristem in Confocal Microscopy (2004) LNCS, 3212, pp. 166-174. , Campilho, A.C, Kamel, M, eds, ICIAR 2004, Springer, Heidelberg; Perona, P., Malik, J., Scale-space and edge detection using anisotropic diffusion (1990) IEEE Trans. on PAMI, 7 (12), pp. 629-639; Dabov, K., Foi, A., Katkovnik, V., Egiazarian, K., Image denoising by sparse 3d transform-domain collaborative filtering (2007) IEEE Trans. on Image Processing, 16 (8), pp. 2080-2095; Luc, V., Soille, P., Watersheds in digital spaces: An efficient algorithm based on immersion simulations (1991) IEEE Trans. on PAMI, 13 (6), pp. 583-598; Meyer, F., Beucher, S., Morphological segmentation (1990) JVCIR, 1 (1), pp. 21-46; Bleau, A., Leon, L., Watershed-based segmentation and region merging (2000) Comput. Vis. Image Underst, 77 (3), pp. 317-370; Kovesi, P.: Symmetry and asymmetry from local phase. In: Proc. of the Tenth Australian Joint Conf. on Artificial Intelligence (December 1997)Burges, C., A tutorial on support vector machines for pattern recognition (1998) Data Mining and Knowledge Discovery, 2 (2), pp. 121-167
Keywords: Arabidopsis (Arabidopsis thaliana); Arabidopsis thaliana (ELIP); Cell divisions; Cell image segmentation; cell proliferation; Cell segmentation; Cells; confocal microscopy; Digital image storage; Heidelberg (CO); Hybrid approaches; Image analysis; Image data; image processing; Image segmentation; Imaging techniques; In vivo observation; Individual (PSS 544-7); International conferences; Merging; Microscopic examination; Research tools; Root meristem; Strength (IGC: D5/D6); Support Vector Machine (SVM); Support vector machines; Time lapse confocal microscopy

Hybrid chitosan membranes tested in sheep for guided tissue regeneration - Cortez, P.P.; Shirosaki, Y.; Botelho, C.M.; Simões, M.J.; Gartner, F.; Da Costa, R.M.G.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Maurício, A.C. (Key Engineering MaterialsKey Eng Mat, 2008)
Previous in vitro studies confirmed an improved cytocompatibility of chitosan-silicate hybrid membranes over chitosan membranes. The main goal of this study was to assess the in vivo histocompatibility of both membranes through subcutaneous implantations at different time periods, 1 week, 1, 2 and 3 months, using a sheep model. Chitosan membranes elicited an exuberant inflammatory response and were consequently rejected. The hybrid chitosan membranes were not rejected and the degree of inflammatory response decreased gradually until the third month of implantation. Histological evaluation also showed that these membranes can be resorbed in vivo. This study demonstrates that the incorporation of silicate into the chitosan solution improves its histocompatibility, indicating that the hybrid chitosan-silicate membranes are suitable candidates to be used in clinical applications.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Cortez, P.P.; Centro de Estudos de Ciência Animal (CECA), Instituto de Ciências e Tecnologias Agrárias e Agro-Alimentares (ICETA), Campus Agrário de Vairão, Rua P. Armando Quintas, 4485-661, Vairão, Portugal; email: pcortez@mail.icav.up.ptReferences: Nasser, N.J., Friedman, A., Friedman, M., Moor, E., Mosheiff, R., (2005) Injury, 36, p. 1460;Chandy, T., Sharma, C.P., (1990) Biomater. Artif. Cells Artif. Organs, 18, p. 1; Domard, A., Rinaudo, M., (1983) Int J Biol Macromol, 5, p. 49; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2004) Key Eng. Mat, 254-256, p. 857; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2005) Biomaterials, 26, p. 485; Ueno, H., Yamada, H., Tanaka, I., Kaba, N., Matsuura, M., Okumura, M., Kadosawa, T., Fujinaga, T., (1999) Biomaterials, 20, p. 1407
Keywords: biodegradability; Biodegradable membrane; Biodegradable membranes; chitosan; Chitosan-silicate hybrid; Guided tissue regeneration (GTR); histology; in vivo study; Membranes; Silicates; Tissue culture

Injectability of a bone filler system based on hydroxyapatite microspheres and a vehicle with in situ gel-forming ability - Oliveira, S.M.; Barrias, C.C.; Almeida, I.F.; Costa, P.C.; Pena Ferreira, M.R.; Bahia, M.F.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part B Applied BiomaterialsJ. Biomed. Mater. Res. Part B Appl. Biomater., 2008)
The aim of this study was to test the injectability of a bone filler system based on the combination of ceramic microspheres with a gel-like vehicle, for noninvasive surgery. Porous hydroxyapatite microspheres with a uniform size and an average diameter of 535 ± 38 μm were prepared, and their compression strength and friability were tested. The sodium-alginate solution with a concentration of 7.25% (w/v) was used as the vehicle. To promote its in situ gelation, calcium carbonate and D-gluconic-δ-lactone were added to the solution. Microspheres were mixed with the vehicle at different percentages (20-40 wt %). Gelation times in the range of 8-20 min, were obtained, depending on the formulation. Mixtures of HAp microspheres with alginate solution at 7.25% originating a gel in 11 min present an adequate handling time to perform an injection. Their injectability was evaluated using an injection device commonly employed in vertebroplasty surgical procedures, coupled to a texturometer in compression mode. Using an extrusion rate of 0.1 mm/s, the force required to extrude any of the mixtures tested was lower than 100 N. For an extrusion rate of 1 mm/s mixtures with 40 wt % of microspheres were very difficult to inject. Mixtures with 35 wt % of microspheres presented the best compromise between injectability and compression strength of the gelled system. MicroCT analysis revealed a homogeneous distribution of the microspheres inside the vehicle, as well as full interconnection of the intra-microspheres spaces. The compression strength for the gelled systems ranged from 80 kPa (gel itself) to 600 kPa (composite with 40 Wt % of microspheres). © 2008 Wiley Periodicals, Inc.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: JBMRGdoi: 10.1002/jbm.b.31066PubMed ID: 18437700Language of Original Document: EnglishCorrespondence Address: Oliveira, S. M.; Escola Superior de Tecnologia de Viseu (ESTV), Dep. de Eng. Mecânica e Gestão Industrial, 3504-510 Viseu, Portugal; email: serafim@ineb.up.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; calcium carbonate, 13397-26-7, 13701-58-1, 14791-73-2, 471-34-1; gluconolactonase, 9012-44-6, 9012-73-1; hydroxyapatite, 1306-06-5, 51198-94-8; Bone Substitutes; Durapatite, 1306-06-5; GelsTradenames: Captal S, Plasma BiotalManufacturers: Plasma BiotalReferences: Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Calcium phosphate-alginate microspheres as enzyme delivery matrices (2004) Biomaterials, 25, pp. 4363-4373;Grabowski, G.A., Leslie, N., Wenstrup, R., Enzyme therapy for Gaucher disease: The first 5 years (1998) Blood Rev, 12, pp. 115-133; Melton, L.J., Melton, L.J., Kan, S.H., Frye, M.A., Wahner, H.W., O'Fallon, W.M., Riggs, B.L., Epidemiology of vertebral fractures in women (1989) Am J Epidemiol, 129, pp. 1000-1011; Carrodeguas, R.G., Lasa, B.V., Del Barrio, J.S., injectable acrylic bone cements for vertebroplasty with improved properties (2004) J Biomed Mater Res B Appl Biomater, 68, pp. 94-104; Hee, H.T., Percutaneous vertebroplasty: Current concepts and local experience (2005) Neurol India, 53, pp. 475-482; Hide, I.G., Gangi, A., Percutaneous vertebroplasty: History, technique and current perspectives (2004) Clin Radiol, 59, pp. 461-467; Verlaan, J.J., Oner, F.C., Verbout, A.J., Dhert, W.J., Temperature elevation after vertebroplasty with polymethylmethacrylate in the goat spine (2003) J Biomed Mater Res B Appl Biomater, 67, pp. 581-585; Hardouin, P., Grados, F., Cotten, A., Cortet, B., Should percutaneous vertebroplasty be used to treat osteoporotic fractures? An update (2001) Joint Bone Spine, 68, pp. 216-221; Berlemann, U., Ferguson, S.J., Nolte, L.P., Heini, P.F., Adjacent vertebral failure after vertebroplasty. A biomechanical investigation (2002) J Bone Joint Surg Br, 84, pp. 748-752; Wilcox, R.K., The biomechanical effect of vertebroplasty on the adjacent vertebral body: A finite element study (2006) Proc Inst Mech Eng [H], 220, pp. 565-572; Uppin, A.A., Hirsch, J.A., Centenera, L.V., Pfiefer, B.A., Pazianos, A.G., Choi, I.S., Occurrence of new vertebral body fracture after percutaneous vertebroplasty in patients with osteoporosis (2003) Radiology, 226, pp. 119-124; Barrias, C.C., Ribeiro, C.C., Barbosa, M.A., Adhesion and proliferation of human osteoblastic cells seeded on injectable hydroxyapatite microspheres (2004) Bioceramics, 254, pp. 877-880; Becker, T.A., Kipke, D.R., Brandon, T., Calcium alginate gel: A biocompatible and mechanically stable polymer for endovascular embolization (2001) J Biomed Mater Res, 54, pp. 76-86; Alsberg, E., Anderson, K.W., Albeiruti, A., Franceschi, R.T., Mooney, D.J., Cell-interactive alginate hydrogels for bone tissue engineering (2001) J Dent Res, 80, pp. 2025-2029; Steinert, A., Weber, M., Dimmler, A., Julius, C., Schutze, N., Noth, U., Cramer, H., Hendrich, C., Chondrogenic differentiation of mesenchymal progenitor cells encapsulated in ultrahigh-viscosity alginate (2003) J Orthop Res, 21, pp. 1090-1097; Wang, L., Shelton, R.M., Cooper, P.R., Lawson, M., Triffitt, J.T., Barralet, J.E., Evaluation of sodium alginate for bone marrow cell tissue engineering (2003) Biomaterials, 24, pp. 3475-3481; Shapiro, L., Cohen, S., Novel alginate sponges for cell culture and transplantation (1997) Biomaterials, 18, pp. 583-590; Eiselt, P., Yeh, J., Latvala, R.K., Shea, L.D., Mooney, D.J., Porous carriers for biomedical applications based on alginate hydrogels (2000) Biomaterials, 21, pp. 1921-1927; Wee, S., Gombotz, W.R., Protein release from alginate matrices (1998) Adv Drug Deliv Rev, 31, pp. 267-285; Draget, K.I., Skjak-Braek, G., Smidsrod, O., Alginate based new materials (1997) Int J Biol Macromol, 21, pp. 47-55; Bajpai, S.K., Sharma, S., Investigation of swelling/degradation behaviour of alginate beads crosslinked with Ca2+ and Ba2+ ions (2004) React Funct Polym, 59, pp. 129-140; Ouwerx, C., Velings, N., Mestdagh, M.M., Axelos, M.A.V., Physico-chemical properties and rheology of alginate gel beads formed with various divalent cations (1998) Polym Gels Networks, 6, pp. 393-408; Paul, W., Sharma, C.P., Development of porous spherical hydroxyapatite granules: Application towards protein delivery (1999) J Mater Sci Mater Med, 10, pp. 383-388; Jarcho, M., Calcium-phosphate ceramics as hard tissue prosthetics (1981) Clin Orthop Relat Res, 157, pp. 259-278; Uda, H., Sugawara, Y., Nakasu, M., Experimental studies on hydroxyapatite powder-carboxymethyl chitin composite: Injectable material for bone augmentation (2006) Br J Plast Surg, 59, pp. 188-196; Xu, H.H., Weir, M.D., Burguera, E.F., Fraser, A.M., Injectable and macroporous calcium phosphate cement scaffold (2006) Biomaterials, 27, pp. 4279-4287; Weiss, P., Gauthier, O., Bouler, J.M., Grimandi, G., Daculsi, G., Injectable bone substitute using a hydrophilic polymer (1999) Bone, 25, pp. 67S-70S; Iooss, P., Le Ray, A.M., Grimandi, G., Daculsi, G., Merle, C., A new injectable bone substitute combining poly(epsilon-caprolactone) microparticles with biphasic calcium phosphate granules (2001) Biomaterials, 22, pp. 2785-2794; Gauthier, O., Khairoun, I., Bosco, J., Obadia, L., Bourges, X., Rau, C., Magne, D., Weiss, P., Noninvasive bone replacement with a new injectable calcium phosphate biomaterial (2000) J Biomed Mater Res A, 66, pp. 47-54; Kuo, C.K., Ma, P.X., Ionically crosslinked alginate hydrogels as scaffolds for tissue engineering, Part 1: Structure, gelation rate and mechanical properties (2001) Biomaterials, 22, pp. 511-521; Oakenfull, D., Scott, A., Stabilization of gelatin by sugars and polyols (1986) Food Hydrocolloyds, 1, pp. 163-175; Poon, C.Y., Tonicity, O., Osmolality and Osmolarity (2006) Philadelphia: The Science and Practice of Pharmacy, pp. 250-265. , 21st ed; Gauthier, O., Bouler, J.M., Weiss, P., Bosco, J., Aguado, E., Daculsi, G., Short-term effects of mineral particle sizes on cellular degradation activity after implantation of injectable calcium phosphate biomaterials and the consequences for bone substitution (1999) Bone, 25, pp. 71S-74S; Gisep, A., Curtis, R., Hanni, M., Suhm, N., Augmentation of implant purchase with bone cements: An in vitro study of injectability and dough distribution (2006) J Biomed Mater Res B Appl Biomater, 77, pp. 114-119; Ginebra, M.P., Rilliard, A., Fernandez, E., Elvira, C., San Roman, J., Planell, J.A., Mechanical and rheological improvement of a calcium phosphate cement by the addition of a polymeric drug (2001) J Biomed Mater Res, 57, pp. 113-118; Krebs, J., Ferguson, S.J., Bohner, M., Baroud, G., Steffen, T., Heini, P.F., Clinical measurements of cement injection pressure during vertebroplasty (2005) Spine, 30, pp. E118-E122; Bohner, M., Baroud, G., Injectability of calcium phosphate pastes (2005) Biomaterials, 26, pp. 1553-1563; Hernandez, L., Gurruchaga, M., Goni, I., Influence of powder particle size distribution on complex viscosity and other properties of acrylic bone cement for vertebroplasty and kyphoplasty (2006) J Biomed Mater Res B Appl Biomater, 77, pp. 98-103; Yoshimine, F., Latta, L.L., Milne, E.L., Sliding characteristics of compression hip screws in the intertrochanteric fracture: A clinical study (1993) J Orthop Trauma, 7, pp. 348-353; Jasper, L.E., Deramond, H., Mathis, J.M., Belkoff, S.M., Material properties of various cements for use with vertebroplasty (2002) J Mater Sci Mater Med, 13, pp. 1-5
Keywords: Alginate; alginic acid; Apatite; article; Average diameter; bioengineering; Bone; bone filler system; Bone Substitutes; Calcium; Calcium carbonate; Ceramic; Ceramic microspheres; Coagulation; Colloids; compression; Compression mode; Compression strengths; Compressive Strength; Computerized tomography; Concentration (process); Data compression; Durapatite; Extrusion; Extrusion rates; Fillers; Forming; Gel-forming ability; Gelation; Gels; gluconolactonase; Handling time; Homogeneous distribution; hydrogel; hydroxyapatite; In situ gelation; in situ hybridization; In-situ; Injectability; injection; Injection (oil wells); Micro-CT; microsphere; Microspheres; Mixtures; non invasive procedure; Particle Size; Porous hydroxyapatite; Sodium; Surgery; Surgical procedures; Uniform size; Vehicles; Vertebroplasty

Jaw avascular osteonecrosis after treatment of multiple myeloma with zoledronate - Lobato, J.V.; Maurício, A.C.; Rodrigues, J.M.; Cavaleiro, M.V.; Cortez, P.P.; Xavier, L.; Botelho, C.; Hussain, N.S.; Santos, J.D. (Journal of Plastic, Reconstructive and Aesthetic SurgeryJ. Plast. Reconstr. Aesthetic Surg., 2008)
Purpose: Multiple myeloma, the second most common haematopoietic cancer, which represents the collection of plasma-cell neoplasms that invariably becomes fatal when self-renewing myeloma cells begin unrestrained proliferation. The major clinical manifestation of multiple myeloma is related to the loss of bone through osteolysis. This can lead to pathologic fractures, spinal cord compression, hypercalcaemia, and pain. It is also a major cause of morbidity and mortality in these patients, who frequently require radiation therapy, surgery and analgesic medications. Bisphosphonates are specific inhibitors of osteoclastic activity, and are currently used to prevent bone complications and to treat malignant hypercalcaemia in patients with multiple myeloma, or bone metastases from breast and prostate cancers. Hence, osteonecrosis of the mandible has been reported in three patients from Centro Hospitalar de Vila Nova de Gaia (CHVNG) with multiple myeloma treated for over 18-48 months with intravenous zoledronate, commonly prescribed for multiple myeloma therapy. Although, this report alerts clinicians about the potential complication of bone necrosis in patients receiving bisphosphonate therapy, many questions remain concerning the underlying pathogenesis of this process. Patients and methods: The medical and dental records of three patients with multiple myeloma, who were treated in CHVNG in the past 4 years, were reviewed. These three patients presented exposed bone and osteonecrosis of the mandible, and shared one common clinical feature: all of them were treated with bisphosphonate zoledronate, administered intravenously for long periods. Sequential orthopantomograms (OPGs) and histological evaluation have been analysed from the biopsies of the non healing dental extraction sites of these patients. Results: After a routine dental extraction, these patients developed avascular osteonecrosis of the mandible and secondary bone infection with Actinomyces israelii (actinomycotic osteomyelitis), with no evidence of metastatic disease evaluated by biopsy. In these three described clinical cases, surgical debridment without flap elevation, intensive antibiotherapy and the suspension of the zoledronate treatment allowed a partial recovery of the patients. The purpose of this clinical report is to point out that patients suffering from multiple myeloma can develop bone osteonecrosis induced by treatment with bisphosphonates. Research to determine the mechanism of this dental phenomenon is needed to fully validate and substantiate the possible link between bisphosphonate treatment of multiple myeloma or other cancer diseases and avascular osteonecrosis of the jaws. Until then, clinicians involved in the care of patients at risk should consider this possible complication. © 2006 British Association of Plastic, Reconstructive and Aesthetic Surgeons.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.bjps.2006.06.016PubMed ID: 18068658Language of Original Document: EnglishCorrespondence Address: Maurício, A.C.; Centro de Estudos de Ciência Animal (CECA), Instituto de Ciências, Tecnologias Agrárias e Agro-Alimentares (ICETA), Campus Agrario Vairao, Rua Padre Armando Quintas, 4485-661 Vairão, Portugal; email: ana.colette@mail.icav.up.ptChemicals/CAS: amoxicillin, 26787-78-0, 34642-77-8, 61336-70-7; cyclophosphamide, 50-18-0; cyclosporin, 79217-60-0; dexamethasone, 50-02-2; erythropoietin, 11096-26-7; thalidomide, 50-35-1; zoledronic acid, 118072-93-8, 131654-46-1, 165800-06-6, 165800-07-7; Bone Density Conservation Agents; Diphosphonates; Imidazoles; zoledronic acid, 118072-93-8References: Mundy, G.R., Bertoline, D.R., Bone destruction and hypercalcemia in plasma cell myeloma (1986) Semin Oncol, 13 (3), pp. 291-299;Belch, A.R., Bergsagel, D.E., Wilson, K., Effect of daily etidronate on the osteolysis of multiple myeloma (1991) J Clin Oncol, 9 (8), pp. 1397-1402; Kyle, R.A., Jowsey, J., Kelly, P.J., Multiple myeloma bone disease. The comparative effect of sodium fluoride and calcium carbonate or placebo (1975) N Engl J Med, 293 (26), pp. 1334-1338; Kyle, R.A., Multiple myeloma: review of 869 cases (1975) Mayo Clin Proc, 50 (1), pp. 29-40; Roodman, G.D., Pathogenesis of myeloma bone disease (2004) Blood Cells Mol Dis, 32 (2), pp. 290-292; Berenson, J.R., Myeloma bone disease (2005) Best Pract Res Clin Haematol, 18 (4), pp. 653-672; Ruggerio, S.L., Mekrotra, B., Rosenberg, T.J., Osteonecrosis of the jaws associated with the use of bisphosphonates: a review of 63 cases (2004) J Oral Maxillofac Surg, 62, pp. 527-534; Rodan, G.A., Fleisch, H.A., Bisphosphonates: mechanism of action (1996) J Clin Invest, 97 (12), pp. 2692-2696; Coleman, R.E., Metastatic bone disease: clinical features, pathophysiology and treatment strategies (2001) Cancer Treat Rev, 27 (3), pp. 165-176; Sietsema, W.K., Ebetino, F.H., Salvagno, A.M., Antiresorptive dose-response relationship across three generations of bisphosphonates (1989) Drugs Exp Clin Res, 15 (9), pp. 389-396; Schenk, R., Eggli, P., Fleisch, H., Quantitative morphometric evaluation of the inhibitory activity of new amino-bisphosphonates on bone resorption in the rat (1986) Calcif Tissue Int, 38, pp. 342-349; Jung, A., Bisaz, S., Fleisch, H., The binding of pyrophosphate and two diphosphonates by hydroxyapatite crystals (1973) Calcif Tissue Res, 11 (4), pp. 269-280; Coukell, A.J., Markham, A., Pamidronate. A review of its use in the management of osteolytic bone metastases, tumor-induced hypercalcaemia and Paget's disease of bone (1998) Drugs Aging, 12 (2), pp. 149-168; Hughes, D.E., MacDonald, B.R., Russel, R.G.G., Inhibition of osteoclast-like cell formation by bisphosphonates in long-term cultures of human bone marrow (1989) J Clin Invest, 83 (6), pp. 1930-1935; Hughes, D.E., Wright, K.R., Uy, H.L., Bisphosphonates promote apoptosis in murine osteoclasts in vitro and in vivo (1995) J Bone Miner Res, 10 (10), pp. 1478-1487; Murakami, H., Takahashi, N., Sasaki, T., A possible mechanism of the specific action of bisphosphonates on osteoclasts: tiludronate preferentially affects polarized osteoclasts having ruffled borders (1995) Bone, 17 (2), pp. 137-144; Sahni, M., Guenther, H.L., Fleisch, H., Bisphosphonates act on rat bone resorption through the mediation of osteoblasts (1993) J Clin Invest, 91 (5), pp. 2004-2011; Fleisch, H., Bisphosphonates: mechanisms of action (1998) Endocr Rev, 19 (1), pp. 80-100; Shinoda, H., Adamek, G., Félix, R., Structure-activity relationships of various bisphosphonates (1983) Calcif Tissue Int, 35 (1), pp. 87-99; Pereira, J., Mancini, I., Walker, P., The role of bisphosphonates in malignant bone pain: a review (1998) J Palliat Care, 14 (2), pp. 25-36; Purohit, O.P., Radstone, C.R., Anthony, C., A randomized double-blind comparison of intravenous pamidronate and clodronate in the hypercalcemia of malignancy (1995) Br J Cancer, 72 (5), pp. 1289-1293; Hillner, B.E., Ingle, J.N., Chlebowski, R.T., American Society of Clinical Oncology 2003 update on the role of bisphosphonates and bone health issues in women with breast cancer (2003) J Clin Oncol, 21 (21), pp. 4042-4057. , [Erratum in J Clin Oncol 2004;22(7):1351]; Hillner, B.E., Ingle, J.N., Berenson, J.R., American Society of Clinical Oncology guideline on the role of bisphosphonates in breast cancer. American Society of Clinical Oncology Bisphosphonates Expert Panel (2000) J Clin Oncol, 18 (6), pp. 1378-1391; Lacerna, L., Hohneker, J., Zoledronic acid for the treatment of bone metastases in patients with breast cancer and other solid tumours (2003) Semin Oncol, 30 (5 SUPPL. 16), pp. 150-160; Lipton, A., Costa, L., Ali, S., Use of markers of bone turnover for monitoring bone metastases and the response to therapy (2001) Semin Oncol, 28 (4 SUPPL. 11), pp. 54-59; Brincker, H., Westin, J., Abildgaard, N., Failure of oral pamidronate to reduce skeletal morbidity in multiple myeloma: a double-blind placebo-controlled trial. Danish-Swedish Co-operative Study Group (1998) Br J Haematol, 101 (2), pp. 3280-3286; Berenson, J.R., Lichtenstein, A., Porter, L., Long-term pamidronate treatment of advanced multiple myeloma patients reduces skeletal events. Myeloma Aredia Study Group (1998) J Clin Oncol, 16 (7), pp. 593-602; Berenson, J.R., Vescio, R.A., Lee, S.R., Phase I dose-ranging trial of monthly infusions of zoledronic acid for the treatment of osteolytic bone metastases (2001) Clin Cancer Res, 7 (3), pp. 478-485; Van Poznak, C.H., The use of bisphosphonates in patients with breast cancer (2002) Cancer Control, 9 (6), pp. 480-489; Marx, R.E., Pamidronate (Aredia) and zoledronate (Zometa) induced avascular necrosis of the jaws: a growing epidemic (2003) J Oral Maxillofac Surg, 61 (9), pp. 1115-1117; Vannucchi, A.M., Ficarra, G., Antonioli, E., Osteonecrosis of the jaw associated with zoledronate therapy in patient with multiple myeloma (2005) Br J Haematol, 128 (6), pp. 738-739; Wang, J., Goodger, N.M., Pogrel, M.A., Osteonecrosis of the jaws associated with cancer chemotherapy (2003) J Oral Maxillofac Surg, 61 (9), pp. 1104-1107; Purcell, P.M., Boyd, I.W., Bisphosphonates and osteonecrosis of the jaw (2005) Med J Aust, 182 (8), pp. 417-418; Carter, G., Goss, A.N., Doecke, C., Bisphosphonates and avascular necrosis of the jaw: a possible association (2005) Med J Aust, 182 (8), pp. 413-415; Durie, B., Katz, M., Crowley, J., Osteonecrosis of the jaw and bisphosphonates (2005) N Engl J Med, 353, pp. 99-102; Migliorati, C.A., Bisphosphonates and oral cavity avascular bone necrosis (2003) J Clin Oncol, 21 (22), pp. 4253-4254; Robinson, N.A., Yeo, J.F., Bisphosphonates - a word of caution (2004) Ann Acad Med Singapore, 33 (4), pp. 48-49; Starck, W.J., Epker, B.N., Failure of osseointegrated dental implants after diphosphonate therapy for osteoporosis: a case report (1995) Int J Oral Maxillofac Implants, 10 (1), pp. 74-78; Melo, M., Obeid, G., Osteonecrosis of the maxilla in a patient with a history of bisphosphonate therapy (2005) J Can Dent Assoc, 71 (2), pp. 111-113
Keywords: Actinomyces israelii; adult; aged; amoxicillin; antibiotic therapy; article; avascular necrosis; Avascular osteonecrosis; biopsy; Bisphosphonates; Bone Density Conservation Agents; case report; clinical feature; cyclophosphamide; cyclosporin; dexamethasone; Diphosphonates; drug induced disease; drug inhibition; drug withdrawal; erythropoietin; Female; histology; human; Humans; hypercalcemia; Imidazoles; Jaw; jaw avascular osteonecrosis; male; Mandibular Diseases; morbidity; mortality; Multiple myeloma; osteolysis; Osteonecrosis; pain; panoramic radiography; pathologic fracture; priority journal; Radiography, Panoramic; risk assessment; spinal cord compression; thalidomide; tooth extraction; zoledronic acid

Joint detection of the carotid boundaries in longitudinal B-mode images - Rocha, R.; Campilho, A.; Silva, J. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
This paper proposes a new approach for the automatic segmentation of the carotid adventitia in longitudinal B-scans, with and without the presence of plaque. The top and bottom adventitia contours are jointly detected with a 3D dynamic programing scheme that searches for the best pair of boundaries according to a specified fuzzy cost function. Some discriminating features of the adventitia in B-mode images are used to reduce the attraction by other edges. The final contours are filtered with a smoothing spline fitting. The proposed approach was quantitatively evaluated in a set of 38 images. In order to avoid high correlation of the results, a maximum of two images was selected from each patient. The carotid boundaries manually traced by a medical expert were used as the ground truth. Several statistics show that the proposed algorithm gives good results in most of the cases, including many poor quality images. Examples of the detected contours are presented and compared with the ground truth. © 2008 Springer-Verlag Berlin Heidelberg.
Conference code: 72695Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-540-69812-8_75Language of Original Document: EnglishCorrespondence Address: Rocha, R.; INEB - Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUP, 4200-465 Porto, PortugalReferences: Gee, A., Prager, R., Treece, G., Berman, L., Engineering a freehand 3D ultrasound system (2003) Pattern Recogn. Lett, 24 (4-5), pp. 757-777;Sonka, M., Liang, W., Stefancik, R., Stolpen, A., Handbook of Medical Imaging: Medical Image Processing and Analysis (2000) SPIE, 2; Gustavsson, T., Liang, Q., Wendelhag, I., Wikstrand, J., A dynamic programming procedure for automated ultrasonic measurement of the carotid artery (1994) Computers in Cardiology, 297-300; Liang, Q., Wendelhag, I., Wikstrand, J., Gustavsson, T., A multiscale dynamic programming procedure for boundary detection in ultrasound artery images (2000) IEEE Trans. Med. Imag, 19 (2), pp. 127-142; Cheng, D., Jiang, X., Schmidt-Trucksass, A., Cheng, K., Automatic intima-media thickness measurement of carotid artery wall in B-mode sonographic images (2006) IEEE International Symposium on Biomedical Imaging (ISBI, pp. 912-915. , IEEE, Los Alamitos; Halenka, M., (1999) Noninvasive measurement of early atherosclerosis by high-resolution B-mode ultrasonography, 142, pp. 7-12. , Acta- Universitatis Palackianae Olomucensis Facultatis Medicae; Yu, Y., Acton, S., Speckle reducing anisotropic diffusion (2002) IEEE Trans. Image Processing, 11 (11), pp. 1260-1270; Yu, Y., Acton, S., Edge detection in ultrasound imagery using the instantaneous coefficient of variation (2004) IEEE Trans. Image Processing, 13 (12), pp. 1640-1655; Canny, J., A computational approach to edge detection (1986) IEEE Trans. Pattern Analysis and Machine Intelligence, 8 (6), pp. 679-698; Guo, Z., Hall, R.W., Parallel thinning with two-subiteration algorithms (1989) Commun. ACM, 32 (3), pp. 359-373; Black, M.J., Sapiro, G., Marimont, D.H., Heeger, D., Robust anisotropic diffusion (1998) IEEE Trans. Image Processing, 7 (3), pp. 421-432; Tauber, C., (2005) Filtrage anisotrope robuste et segmentation par B-spline snake: Application aux images échographiques, , PhD thesis, Institut National Polytechnique de Toulouse, Toulouse Février; de Boor, C., (1978) A Practical Guide to Splines, , Springer, Heidelberg
Keywords: Automatic segmentations; B-Mode imaging; Edge detection; Fuzzy costs; Ground truth; Heidelberg (CO); Image analysis; Image enhancement; Imaging techniques; International conferences; Joint detection (JD); Medical experts; New approaches; Regression analysis; Smoothing splines

Minimizing the imbalance problem in chromatographic profile classification with one-class classifiers - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
This paper presents a new classification approach to deal with class imbalance in TLC patterns, which is due to the huge difference between the number of normal and pathological cases as a consequence of the rarity of LSD diseases. The proposed architecture is formed by two decision stages: the first is implemented by a one-class classifier aiming at recognizing most of the normal samples; the second stage is a hierarchical classifier which deals with the remaining outliers that are expected to contain the pathological cases and a small percentage of normal samples. We have also evaluated this architecture by a forest of classifiers, using the majority voting as a rule to generate the final classification. The results that were obtained proved that this approach is able to overcome some of the difficulties associated with class imbalance. © 2008 Springer-Verlag Berlin Heidelberg.
Conference code: 72695Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-540-69812-8_41Language of Original Document: EnglishCorrespondence Address: Sousa, A. V.; Instituto de Engenharia Biomédica, Rua Roberto Frias, 4200-465 Porto, Portugal; email: ats@isep.ipp.ptReferences: Keir, G., Winchester, B.G., Clayton, P., Carbohydrate-deficient Glycoprotein Syndromes: Inborn Errors of Protein Glycosylate (1999) Ann. Clin. Biochem, 36 (PART 1), pp. 20-36;Durand, G., Seta, N., Protein Glycosylation and Diseases: Blood and Urinary Oligosaccharides as Markers for Diagnosis and Therapeutic Monitoring (2000) Clin. Chem, 46, pp. 795-805; Scriver, S.R., Beaudet, A.L., Sly, W.S., Valle, D., (2001) The Metabolic Bases of Inherited Disease, 3. , MCGraw-Hill, New-York; Friedman, R.B., Williams, M.A., Moser, H.W., Kolodny, E.H., Improved Thin-Layer Chromatographic Method in the Diagnosis of Mannosidosis (1978) Clinical Chemistry, 24, pp. 1576-1577; Kurczynski, T.W., Kendzierski, K.S., Sewell, A.C., Kuczynski, T.W., Urinary Oligosaccharides in Pregnant or Lactating Women: Pitfall in Screening (1993) Clin. Chem, 39, pp. 2346-2347; Sewell, A.C., Urinary Oligosaccharides. Techniques in Diagnostic Human (1991) Biochemical Genetics, 219-231; Duvdevani-Bar, S., Edelman, S., Visual Recognition and Categorization on the Basis of Similarities to Multiple Class Prototypes (1999) Int. J. Comput. Vision, 33, pp. 201-228; Pekalska, E., Duin, R.P.W., Dissimilarity Representations Allow for Building Good Classifiers (2002) Pattern Recogn. Lett, 23, pp. 943-956; Goldstone, R.L., Son, J.Y., Similarity (2005) Cambridge Handbook of Thinking and Reasoning, pp. 13-36. , Holyoak, K, Morrison, R, eds, Cambridge University Press, Cambridge; Pekalska, E., Duin, R.P.W., (2005) The Dissimilarity Representation for Pattern Recognition -Fundations and Applications, 64. , World Scientific Publishing, Singapore; Lavine, B.K., Clustering and Classification of Analytical Data (2000) Encyclopedia of Analytical Chemistry: Instrumentation and Applications, pp. 9689-9710. , Meyers, R.A, ed, John Wiley & Sons, Chichester; Kubat, M., Holte, R., Matwin, S.: Learning when Negative Examples Abound. In: van Someren, M., Widmer, G. (eds.) ECML 1997. LNCS, 1224, pp. 146-153. Springer, Heidelberg (1997)Skurichina, M., Raudys, S., Duin, R.P.W., K-Nearest Neighbors Directed Noise Injection in Multilayer Perceptron Training (2000) IEEE Transactions on Neural Networks, 11; Chawla, N.V., Japkowicz, N., Kolcz, A., Editorial: Special Issue: Learning from Imbalanced Data Sets (2004) Sigkdd Explorations, 6, pp. 1-6; Tax, D.M.J., (2001) One-class Classification; Concept-learning in the Absence of Counter-examples, , Ph.D. thesis: Delft University of Technology; Sousa, A.V., Mendonça, A.M., Campilho, A., Chromatographic Pattern Classification (2007) IEEE Trans. on Biomedical Engineering, , doi:10.1109/TBME.2008.919852; Paclik, P., Duin, R.P.W., Dissimilarity-based Classification of Spectra: Computational Issues (2003) Real-Time Imaging, 9, pp. 237-244; Paclik, P., Duin, R.P.W., Classifying Spectral Data using Relational Representation (2003) Proc. of Spectral Imaging Workshop, , Graz, Austria; Sousa, A.V., Mendonça, A.M., Campilho, A., Dissimilarity-based Classification of Chromatographic Profiles (2007) Pattern Analysis and Applications, , doi:10.1007/sl0044-008-0113-2; Pekalska, E., Paclik, P., Duin, R.P.W., A Generalized Kernel Approach to Dissimilarity-based Classifcation (2001) Journal of Machine Learning Research, 2, pp. 175-211; Ripley, B.D., (2004) Pattern Recognition and Neural Networks, , Cambridge University Press, Cambridge; Visa, S., Ralescu, A., Learning Imbalanced and Overlapping Classes Using Fuzzy Sets (2003) Workshop on Learning from Imbalanced Datasets II, ICML, , Washington DC
Keywords: Class imbalances; Classification (of information); Classification approach; Classifiers; Heidelberg (CO); Hierarchical classifiers; Image analysis; Imaging techniques; Imbalance problems; International conferences; Learning systems; Majority voting; Pathological cases

Molecular epidemiology of pseudomonas aeruginosa clinical isolates from Portuguese Central Hospital - Fonseca, A.P.; Correia, P.; Extremina, C.I.; Sousa, J.C.; Tenreiro, R.; Barros, H. (Folia MicrobiologicaFolia Microbiol., 2008)
The relatedness between clinical isolates of P. aeruginosa obtained from patients during their stay in a Portuguese Central Hospital was evaluated. Genotypic fingerprinting (M13-PCR), phenotypic methods (biotyping and antibiotyping) and epidemiological information (spatial and temporal links) were used to evaluate the relatedness between 88 clinical isolates (68 patients), selected randomly out of 189. Sixty-two M13 types were found, 12 of them containing isolates from more than one patient. Thirty-four antibiotypes were found, as well as a significant association (p < 0.05) between epidemic isolates and multiresistance patterns. The nosocomial transmission of P. aeruginosa strains may be limited since M13 typing demonstrated a high degree of diversity among all the isolates, suggesting the occurrence of mainly independent infectious episodes. The results show the possible occurrence of cross-acquisition, cross-colonization and cross-infection and suggest an epidemic population structure for P. aeruginosa in this hospital.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: FOMIAdoi: 10.1007/s12223-008-0086-yLanguage of Original Document: EnglishCorrespondence Address: Fonseca, A. P.Rua Roberto Frias s/n, 4200-465 Porto, Portugal; email: apfonseca08@sapo.ptChemicals/CAS: DNA, BacterialReferences: Bergmans, D., Bonten, M., van tiel, F., Gaillard, C., London, N., van der Geest, S., de Leeuw, P., Stobbrringh, E., Value of phenotyping methods as an initial screening of Pseudomonas aeruginosa in epidemiologic studies (1997) Infection, 25, pp. 350-354;Bertrand, X., Thouverez, M., Talon, D., Boillot, A., Capellier, G., Floriot, C., Helias, J.P., Endemicity, molecular diversity and colonization routes of Pseudomonas aeruginosa in intensive care units (2001) Intens.Care Med., 27, pp. 1263-1268; Brízio, A., Silva, A., Canas, E., Ferreira, T., Lito, L.M., Cristino, J.M., Salgado, M.J., Duarte, A., Spread of ln58 containing bla VIM-2 among Pseudomonas aeruginosa (2006) Clin.Microbiol.Infect.Dis., 12 (SUPPL. 4), p. 931; Brízio, A., Vasco, S., Gonçalves, A.R., Lito, L.M., Cristino, J.M., Salgado, M.J., Duarte, A., Survey of extended-spectrum β-lactamases in Escherichia coli isolates from a Portuguese hospital and characterisation of a novel class 1 integron (In60A) carrying the blaCTX-M-9 gene (2006) Internat.J.Antimicrob.Agents, 28, pp. 320-324; Buchholz, P., Richter, M., Fiedler, G., Halle, E., Epidemiological fingerprinting of multiresistant strains of Pseudomonas aeruginosa isolated from patients of intensive care units of the Charité Hospital, Berlin (1995) Med.Microbiol.Lett., 4, pp. 7-13; Černohorská, L., Votava, M., Antibiotic synergy against biofilm-forming Pseudomonas aeruginosa (2008) Folia Microbiol, 53, pp. 57-61; Elaichouni, A., Verschraegen, G., Claeys, G., Devleeschouwer, M., Godard, C., Vaneechoutte, M., Pseudomonas aeruginosa serotype O12 outbreak studied by arbitrary primer PCR (1994) J.Clin.Microbiol., 32, pp. 666-671; Fonseca, A.P., Correia, P., Fonseca, A.F., Tenreiro, R., Sousa, J.C., Polyphasic approach to the characterization of Pseudomonas aeruginosa isolates from a Portuguese Central Hospital (2004) Clin.Microbiol.Infect., 10 (SUPPL. 3), p. 1113; Fonseca, A.P., Correia, P., Sousa, J.C., Tenreiro, R., Association patterns of Pseudomonas aeruginosa clinical isolates as revealed by virulence traits, antibiotic resistance, serotype and genotype (2007) FEMS Immunol.Med.Microbiol., 51, pp. 505-516; Grundmann, H., Kropec, A., Hartung, D., Berner, R., Daschner, F., Pseudomonas aeruginosa in a neonatal intensive care unit: Reservoirs and ecology of the nosocomial pathogen (1993) J.Infect.Dis., 168, pp. 943-947; Grundmann, H.J., Towner, K.J., Dijkshoorn, L., Gerner-smidt, P., Maher, M., Seifert, H., Vaneechoutte, M., Multicenter study using standardized protocols and reagents for evaluation of reproducibility of PCR-based fingerprinting of Acinetobacter spp (1997) J.Clin.Microbiol., 35, pp. 3071-3077; Hoštacká, A., Čižnár, I., Slobodníková, L., Kotulová, D., Clinical Pseudomonas aeruginosa: Potential factors of pathogenicity and resistance to antimicrobials (2006) Folia Microbiol, 51, pp. 633-638; Hunter, P.R., Gaston, M.M., Numerical index of the discriminatory ability of typing systems: An application of Simpson's index of diversity (1989) J.Clin.Microbiol., 26, pp. 2465-2466; Huston, W.M., Potter, A.J., Jennings, M.P., Rello, J., Hauser, A.R., McEwan, A.G., Survey of ferroxidase expression and siderophore production in clinical isolates of Pseudomonas aeruginosa (2004) J.Clin.Microbiol., 42, pp. 2806-2809; Jalaluddin, S., Devaster, J.-M., Scheen, R., Gerard, M., Butzler, J.-P., Molecular epidemiological study of nosocomial Enterobacter aerogenes isolates in a Belgian hospital (1998) J.Clin.Microbiol., 36, pp. 1846-1852; Juretschko, S., Labombardi, V.J., Lerner, S.A., Schreckenberger, P.C., Pseudomonas AST Study Group: Accuracies of β-lactam susceptibility test results for Pseudomonas aeruginosa with four automated systems (BD Phoenix, MicroScan WalkAway, Vitek, and Vitek 2) (2007) J.Clin.Microbiol., 45, pp. 1339-1342; King, E.O., Ward, M.K., Raney, D.E., Two simple media for the demonstration of pyocyanin and fluorescein (1954) J.Lab.Clin.Med., 44, pp. 301-307; Kiska, D.L., Gilligan, P.H., Pseudomonas and Burkholderia (1999) Manual of Clinical Microbiology, pp. 517-525. , in P.R.Murray,E.J.Baron,M.A.Pfaller,F.C.Tenover,R.H.Yolken(Eds) 7th ed. American Society for Microbiology,Washington (DC); Morales, G., Wiehlmann, L., Gudowius, P., van Delden, C., Tümmler, B., Martínez, J.L., Rojo, F., Structure of Pseudomonas aeruginosa populations analyzed by single nucleotide polymorphism and pulsed-field gel electrophoresis genotyping (2004) J.Bacteriol., 186, pp. 4228-4237; Nogueira, J.A., (1995) Pseudomonas Aeruginosa - Agente Nosocomial, , (In Portuguese) PhD Thesis. Faculdade de Medicina, Universidade do Porto, Porto (Portugal); Olive, P.B.D., Principles and applications of methods for DNA-based typing of microbial organisms (1999) J.Clin.Microbiol., 37, pp. 1661-1669; Pirnay, J.P., de Vos, D., Cochez, C., Bilocq, F., Vanderkelen, A., Zizi, M., Ghysels, B., Cornelis, P., Pseudomonas aeruginosa displays an epidemic population structure (2002) Environ.Microbiol., 4, pp. 898-911; Pirnay, J.P., Matthijs, S., Colak, H., Chablain, P., Bilocq, F., Van eldere, J., de Vos, D., Cornelis, P., Global Pseudomonas aeruginosa biodiversity as reflected in a Belgian river (2005) Environ.Microbiol., 7, pp. 969-980; Speijer, H., Savelkoulp, P.H.M., Bonten, M.J., Stobberingh, E.E., Tjhie, J.H.T., Application of different genotyping methods for Pseudomonas aeruginosa in a setting of endemicity in an intensive care unit (1999) J.Clin.Microbiol., 37, pp. 3654-3661; Tenover, F., Arbeit, R.D., Goering, R.V., Mickelsen, P.A., Murray, B.E., Persing, D.H., Swaminathan, B., Interpreting chromosomal DNA restriction patterns produced by pulsed-field gel electrophoresis: Criteria for bacterial strain typing (1995) J.Clin. Microbiol., 33, pp. 2233-2239; Wiehlmann, L., Wagner, G., Cramer, N., Siebert, B., Gudowius, P., Morales, G., Köhler, T., Tümmler, B., Population structure of Pseudomonas aeruginosa (2007) Proc.Nat.Acad.Sci.USA, 104, pp. 8101-8106
Keywords: antibiotic resistance; article; bacterial DNA; cross infection; disease transmission; DNA, Bacterial; Drug Resistance, Microbial; Electrophoresis, Gel, Pulsed-Field; epidemiology; genetics; genotype; Hospitals, Teaching; human; Humans; isolation and purification; microbiology; polymerase chain reaction; Portugal; Pseudomonas aeruginosa; Pseudomonas infection; Pseudomonas Infections; pulsed field gel electrophoresis; Sampling Studies; statistics; teaching hospital

Omniview-SisPorto® 3.5 - A central fetal monitoring station with online alerts based on computerized cardiotocogram+ST event analysis - Ayres-de-Campos, D.; Sousa, P.; Costa, A.; Bernardes, J. (Journal of Perinatal MedicineJ. Perinat. Med., 2008)
Visual analysis of cardiotocograms is poorly reproducible and is currently recognized as the main weakness of the STAN® methodology. The Omniview-SisPorto® 3.5 program is the most recent version of a central monitoring system that provides visual and sound alerts, based on computer analysis of cardiotocographic and ST event features. This paper describes the program's main characteristics and provides an overview of the system's online alerts. Omniview-SisPorto® 3.5 is the first central monitoring system to incorporate computerized analysis of cardiotocographic and ST event features, providing health professionals with online alerts for minor and major changes in monitored signals. The system is currently undergoing extensive clinical evaluation. © 2008 by Walter de Gruyter.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JPEMAdoi: 10.1515/JPM.2008.030Language of Original Document: EnglishCorrespondence Address: Ayres-De-Campos, D.; Departmento Ginecologia e Obstetricia, Faculdade de Medicina, Universidade Do Porto, Alameda Hernani Monteiro, 4200-319 Porto, Portugal; email: sisporto@med.up.ptTradenames: Omniview-SisPorto 3.5 system, SpeculumManufacturers: SpeculumReferences: Amer-Wahlin, I., Arulkumaran, S., Hagberg, H., Marsal, K., Visser, G., Fetal electrocardiogram: ST waveform analysis in intrapartum surveillance (2007) Br J Obstet Gynaecol, 114, pp. 1191-1193;Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marquesde-Sá, J., Pereira-Leite, L., SisPorto 2.0: A program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Ayres-de-Campos, D., Bernardes, J., Comparison of fetal heart rate baseline estimation by SisPorto 2.01 and a consensus of clinicians (2004) Eur J Obstet Gynecol Reprod Biol, 117, pp. 174-178; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., SisPorto Multicentre Validation Study Group. Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118, pp. 52-60; Ayres-de-Campos, D., Bernardes, J., Kwee, A., Westehuis, M., Visser, G.H.A., Computer quantification of short-term variability as an adjunct to fetal electrocardiographic monitoring (2007) Br J Obstet Gynaecol, 114, pp. 1446-1447; Bernardes, J., Moura, C., Marques de, S.J., Pereira Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Electronic fetal heart rate monitoring: Research guidelines for interpretation (1997) Am J Obstet Gynecol, 177, pp. 1385-1390. , National Institute of Child Health and Human Development Research Planning Workshop; Neilson, J.P., Fetal electrocardiogram (ECG) for fetal monitoring during labor (2006) Cochrane Database of Systematic Reviews, (3); Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-165; (2001) Evidence-based clinical guideline: The use of electronic fetal monitoring, , RCOG, Royal College of Obstetricians and Gynaecologists, London, RCOG Press; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring (1987) Int J Gynecol Obstet, 25, pp. 159-167
Keywords: article; Cardiotocography; computer program; Computer-assisted; Electrocardiography; Female; Fetal; Fetal hypoxia; Fetal monitoring; fetus hypoxia; fetus monitoring; Heart rate; human; Humans; instrumentation; online system; Pregnancy; priority journal; Signal processing; ST segment

Region and graph-based motion segmentation - Monteiro, F.C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
This paper describes an approach for integrating motion estimation and region clustering techniques with the purpose of obtaining precise multiple motion segmentation. Motivated by the good results obtained in static segmentation we propose a hybrid approach where motion segmentation is achieved within a region-based clustering approach taken the initial result of a spatial pre-segmentation and extended to include motion information. Motion vectors are first estimated with a multiscale variational method applied directly over the input images and then refined by incorporating segmentation results into a region-based warping scheme. The complete algorithm facilitates obtaining spatially continuous segmentation maps which are closely related to actual object boundaries. A comparative study is made with some of the best known motion segmentation algorithms. © 2008 Springer-Verlag Berlin Heidelberg.
Conference code: 72695Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-540-69812-8_60Language of Original Document: EnglishCorrespondence Address: Monteiro, F. C.; INEB - Instituto de Engenharia BiomédicaPortugalReferences: Ayer, S., Sawhney, U.S.: Layered representation of motion video using robust maximum-likelihood estimation of mixture models and mdl encoding. In: Proc. IEEE International Conference on Computer Vision, June 1995, pp. 777-784 (1995)Brox, T., (2005) From pixels to regions: Partial differential equation in image analysis, , PhD thesis, Department of Mathematics and Computer Science, Saarland University, Germany;Brox, T., Bruhn, A., Papenberg, N., Weickert, J.: High Accuracy Optical Flow Estimation Based on a, Theory for Warping. In: Pajdla, T., Matas, J(G.) (eds.) ECCV 2004. LNCS, 3024, pp. 25-36. Springer, Heidelberg (2004)Bruhn, A., Weickert, J., Schnörr, C., Lucas/Kanade meets Horn/ Schunck: Combining local and global optic flow methods (2005) International Journal of Computer Vision, 61 (3), pp. 1-21; Chang, S.-F., Sikora, T., Puri, A., Overview of the MPEG-7 standard (2001) IEEE Transactions on Circuits and Systems for Video Technology, 11 (6), pp. 688-695; Horn, B.K.P., Schunck, B.G., Determining optical flow (1981) Artificial Intelligence, 17 (1-3), pp. 185-203; Monteiro, F.C., (2007) Region-based spatial and temporal image segmentation, , PhD thesis, Faculdade de Engenharia da Universidade do Porto, Portugal; Monteiro, F.C., Campilho, A.: Spectral Methods in Image Segmentation: A Combined Approach. In: Marques, J.S., Pérez de la Blanca, N., Pina, P. (eds.) IbPRIA 2005. LNCS, 3523, pp. 191-198. Springer, Heidelberg (2005)MPEG4. MPEG-4 video verification model, version 15.0. ISO/IEC/JTC1/SC29/WG11 N3093 1999Papenberg, N., Bruhn, A., Brox, T., Didas, S., Weickert, J., Highly accurate optic flow computation with theoretically justified warping (2006) Int. Journal of Computer Vision, 67 (2), pp. 141-158; Shi, J., Malik, J., Motion segmentation and tracking using normalized cuts (1998) Proc. of IEEE Int. Conference on Computer Vision, pp. 1154-1160; Smith, P., (2001) Edge-based motion segmentation, , PhD thesis, Department of Engineering, University of Cambridge; Vasconcelos, N., Lippman, A., Empirical bayesian motion segmentation (2001) IEEE Transactions on Pattern Analysis and Machine Intelligence, 23 (2), pp. 217-221; Wang, J., Adelson, E., Representing moving images with layers (1994) IEEE Transactions on Image Processing, 3 (5), pp. 625-638; Weiss, Y., Adelson, E.H., A unified mixture framework for motion segmentation: Incorporating spatial coherence and estimating the number of models (1996) Proc. of IEEE International Conference on Computer Vision and Pattern Recognition, pp. 321-326. , San Francisco, USA, June
Keywords: Clustering approach; Comparative studies; Conformal mapping; Estimation; Flow of solids; Graph-based; Heidelberg (CO); Hybrid approaches; Image analysis; Image segmentation; Imaging techniques; Input Images; International conferences; Maps; Motion estimation; Motion information; Motion segmentation; Motion vector (MV); Multi scaling; Multiple motion segmentation; Object boundaries; Region clustering; Region-based; Segmentation maps; Segmentation results; Static segmentation; Variational methods

Tracking of Arabidopsis thaliana root cells in time-lapse microscopy - Marcuzzo, M.; Quelhas, P.; Mendonça, A.M.; Campilho, A. (Proceedings - International Conference on Pattern RecognitionProc. Int. Conf. Pattern Recognit., 2008)
In vivo observation of cells in the Arabidopsis thaliana root, by time-lapse confocal microscopy, is central to biology research. The research herein described is based on large amount of image data, which must be analyzed to determine the location and state of individual cells. Automating the process of cell tracking is an important step to create tools which will facilitate the analysis of cells' evolution through time. Here we introduce a confocal tracking system designed in two stages. At the image acquisition stage, we track the area under analysis based on point-to-point correspondences and motion estimation. After image acquisition, we compute cell-to-cell correspondences through time. The final result is a temporal structured information about each cell. © 2008 IEEE.
Conference code: 81859Export Date: 21 November 2012Source: ScopusArt. No.: 4761746CODEN: PICRELanguage of Original Document: EnglishCorrespondence Address: Marcuzzo, M.; INEB - Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUPPortugalReferences: Beemster, G., Baskin, T., Analysis of cell division and elongation underlying the developmental acceleration of root growth in arabidopsis thaliana (1998) Plant Physiology, 116, pp. 1515-1526;Campilho, A., Garcia, B., Toorn, H., Wijk, H., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the arabidopsis thaliana root meristem (2006) The Plant Journal, 48, pp. 619-627; Dabov, K., Foi, A., Katkovnik, V., Egiazarian, K., Image denoising by sparse 3d transform-domain collaborative filtering (2007) IEEE Trans. on Image Processing, 16 (8), pp. 2080-2095. , August; Garcia, B., Campilho, A., Scheres, B., Campilho, A., Automatic tracking of arabidopsis thaliana root meristem in confocal microscopy (2004) Proc. of the Inter. Conf. on Image Analysis and Recognition, pp. 166-174. , Springer LCNS 3212; Harris, C., Stephens, M., A combined corner and edge detector (1988) Proc. of the 4th Alvey Vision Conf.; Hartley, R., Zisserman, A., (2003) Multiple View Geometry in Computer Vision, , Cambridge University Press; Iwamoto, A., Satoh, D., Furutani, M., Maruyama, S., Ohba, H., Sugiyama, M., Insight into the basis of root growth in arabidopsis thaliana provided by a simple mathematical model (2006) J. Plant Res., 119, pp. 85-93; Luc, V., Soille, P., Watersheds in digital spaces: An efficient algorithm based on immersion simulations (1991) IEEE Trans. on PAMI, 13 (6), pp. 583-598; Marcuzzo, M., Quelhas, P., Campilho, A., Mendonça, A.M., Campilho, A., A hybrid approach for cell image segmentation (2008) Proc. of the ICIAR, pp. 739-749. , Springer LCNS 5112; Meyer, F., Beucher, S., Morphological segmentation (1990) JVCIR, 1 (1), pp. 21-46. , Sept; Mohinder, S., Angus, P., (1993) Kalman Filtering Theory and Practice, , Prentice Hall; Roberts, T., Mckenna, S., Wuyts, N., Valentine, T., Bengough, A., Performance of low-level motion estimation methods for confocal microscopy of plant cells in vivo (2007) Motion07, pp. 13-13
Keywords: Arabidopsis thaliana; Bioinformatics; Cell tracking; confocal microscopy; Image acquisition; Image data; In-vivo; Individual cells; Motion estimation; Pattern recognition; Point correspondence; Root cells; Structured information; Time-lapse microscopy; Tracking system; Two stage

Watershed framework to region-based image segmentation - Monteiro, F.C.; Campilho, A. (Proceedings - International Conference on Pattern RecognitionProc. Int. Conf. Pattern Recognit., 2008)
This paper proposes a new framework to image segmentation which combines edge- and region-based information with spectral techniques through the morphological algorithm of watersheds. A pre-processing step is used to reduce the spatial resolution without losing important image information. An initial partitioning of the image into primitive regions is set by applying a rainfalling watershed algorithm on the image gradient magnitude. This initial partition is the input to a computationally efficient region segmentation process which produces the final segmentation. The latter process uses a region-based similarity graph representation of the image regions. The experimental results clearly demonstrate the effectiveness of the proposed approach to produce simpler segmentations and to compare favourably with state-of-the-art methods. © 2008 IEEE.
Conference code: 81859Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusArt. No.: 4761587CODEN: PICRELanguage of Original Document: EnglishCorrespondence Address: Monteiro, F. C.; INEB - Instituto de Engenharia BiomédicaPortugal; email: monteiro@ipb.ptReferences: Callaghan, R.O., Bull, D., Combined morphologicalspectral unsupervised image segmentation (2005) IEEE Transactions on Image Processing, 14 (1), pp. 49-62;Comaniciu, D., Meer, P., Mean shift: A robust approach toward feature space analysis (2002) IEEE Trans. Pattern Analysis and Machine Intelligence, 24 (5), pp. 603-619; Cour, T., Benezit, F., Shi, J., Spectral segmentation with multiscale graph decomposition (2005) Proc. of IEEE Int. Conf. on Computer Vision and Pattern Recognition, 2, pp. 1124-1131. , June; De Bock, J., De Smet, P., Philips, W., Image segmentation using watersheds and normalized cuts (2005) Proceedings of SPIE - The International Society for Optical Engineering, 5675, pp. 164-173. , Imaging - Vision Geometry XIII; Deng, Y., Manjunath, B., Unsupervised segmentation of color-texture regions in images and video (2001) IEEE Transactions on Pattern Analysis and Machine Intelligence, 23 (8), pp. 800-810; Martin, D., Fowlkes, C., Tal, D., Malik, J., A database of human segmented natural images and its application to evaluating segmentation algorithms and measuring ecological statistics (2001) Proc. of IEEE Int. Conference on Computer Vision, 2, pp. 416-423. , http://www.cs.berkeley.edu/projects/vision/grouping/segbench/, online at; Monteiro, F., (2007) Region-based Spatial and Temporal Image Segmentation, , PhD thesis, Faculdade de Engenharia da Universidade do Porto, Portugal
Keywords: Computationally efficient; Edge detection; Graph representation; Image gradients; Image information; Image regions; Image segmentation; Landforms; Pre-processing step; Process use; Rainfalling watershed; Region segmentation; Region-based; Spatial resolution; Spectral techniques; State-of-the-art methods; Watersheds

Attachment, spreading and short-term proliferation of human osteoblastic cells cultured on chitosan films with different degrees of acetylation - Amaral, I.F.; Cordeiro, A.L.; Sampaio, P.; Barbosa, M.A. (Journal of Biomaterials Science, Polymer EditionJ. Biomater. Sci. Polym. Ed., 2007)
Chitosan (Ch) is being actively investigated as a non-protein template for the growth of an increasing number of anchorage-dependent cells, including chondrocytes and bone cells. In the present work, Ch films with degrees of N-acetylation (DAs) in the range of 4 to 49% were evaluated with respect to the attachment, spreading and short-term proliferation of osteoblasts, using human osteoblastic MG-63 cells. The films were characterized in terms of surface morphology and surface charge by atomic force microscopy and streaming potential measurements, respectively. Cell attachment was assessed after 3 and 24 h of cell culture. After 24 h of incubation, cell attachment was found to be dependent on the DA, lower DAs favouring cell adhesion. With time, cell spreading and cytoskeleton organization were only attained for DAs ≤ 13%. Regarding cell proliferation, cells grown on films with the lowest DA (4%) revealed a higher specific growth rate as compared to those grown on films with higher DAs. Films with a DA of 49% failed to sustain cell proliferation. In addition, a longer lag-phase was observed on Ch, as compared to TCPS, in accordance to an observed delay of cell spreading. The present findings revealed that differences in the DA as small as 9% may be critical in terms of the osteoblast response to two-dimensional Ch-based matrices. © 2007 VSP.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JBSEEdoi: 10.1163/156856207780425068Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; Biocompatible Materials; Chitosan, 9012-76-4References: Vacanti, C.A., Bonassar, L.J., Vacanti, J.P., (2000) Principles of Tissue Engineering, p. 671. , R. P. Lanza, R. Langer and J. Vacanti Eds, p, Academic Press, San Diego, CA;Bruder, S.P., Caplan, A.I., (2000) Principles of Tissue Engineering, p. 683. , R. P. Lanza, R. Langer and J. Vacanti Eds, p, Academic Press, San Diego, CA; Burg, K.J.L., Porter, S., Kellam, J.F., (2000) Biomaterials, 21, p. 2347; Khor, E., Lim, L.Y., (2003) Biomaterials, 24, p. 2339; Nettles, D.L., Elder, S.H., Gilbert, J.A., (2002) Tissue Eng, 8, p. 1009; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., (2002) J. Control. Rel, 78, p. 187; Muzzarelli, R.A.A., (1997) Cell. Mol. Life Sci, 53, p. 131; Madihally, S.V., Matthew, H.W.T., (1999) Biomaterials, 20, p. 1133; Chupa, J.M., Foster, A.M., Sumner, S.R., Madihally, S.V., Matthew, H.W.T., (2000) Biomaterials, 21, p. 2315; Lahiji, A., Sohrabi, A., Hungerford, D.S., Frondoza, C.G., (2000) J. Biomed. Mater. Res, 51, p. 586; Ho, M.H., Wang, D.M., Hsieh, H.J., Liu, H.C., Hsien, T.Y., Lai, J.Y., Hou, L.T., (2005) Biomaterials, 26, p. 3197; A. Domard, in: Advances in Chitin Science, II, A. Domard, G. A. F. Roberts and K. M. Varum (Eds), p. 410. Jacques André, Lyon (1997)Tomihata, K., Ikada, Y., (1997) Biomaterials, 18, p. 567; Baxter, A., Dillon, M., Taylor, K.D.A., Roberts, G.A.F., (1992) Int. J. Biol. Macromol, 14, p. 166; Anselme, K., (2000) Biomaterials, 21, p. 667; Prasitsilp, M., Jenwithisuk, R., Kongsuwan, K., Damrongchai, N., Watts, P., (2000) J. Mater. Sci. Mater. Med, 11, p. 773; Chatelet, C., Damour, O., Domard, A., (2001) Biomaterials, 22, p. 261; Dhiman, H.K., Ray, A.R., Panda, A.K., (2004) Biomaterials, 25, p. 5147; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., (2001) Polymer, 42, p. 3569; Mima, S., Miya, M., Iwamoto, R., Yoshikawa, S., (1983) J. Appl. Polym. Sci, 28, p. 1909; Aiba, S., (1986) Int. J. Biol. Macromol, 8, p. 173; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., (1996) Carbohydr. Polym, 29, p. 63; (1987) Guideline on Validation of the Limulus Amebocyte Lysate Test as an End-product Endotoxin Test for Human and Animal Parental Drugs, Biological Products, and Medical Devices, , US Department of Health and Human Services, Public Health Service, Food and Drug Administration, US Department of Health and Human Services, Washington, DC; Nakagawa, Y., Murai, T., Hasegawa, C., Hirata, M., Tsuchiya, T., Yagami, T., Haishima, Y., (2003) J. Biomed. Mater. Res, 66 B, p. 347; Walker, S.L., Bhattacharjee, S., Hoek, E.M.V., Elimelech, M., (2002) Langmuir, 18, p. 2193; Clover, J., Gowen, M., (1994) Bone, 15, p. 585; Mosmann, T., (1983) J. Immunol. Methods, 65, p. 55; Domke, J., Dannohl, S., Parak, W.J., Muller, O., Aicher, W.K., Radmacher, M., (2000) Colloid Surfaces B: Biointerfaces, 19, p. 367; Sorlier, P., Denuziere, A., Viton, C., Domard, A., (2001) Biomacromolecules, 2, p. 765; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., (2005) J. Biomed. Mater. Res, 75 A, p. 387; Andrade, J.D., Smith, L.M., Gregonis, D.E., (1985) Surface and Interfacial Aspects of Biomedical Polymers, 1, p. 249. , J. D. Andrade Ed, p, Plenum Press, New York, NY; Dewez, J.L., Doren, A., Schneider, Y.J., Rouxhet, P.G., (1999) Biomaterials, 20, p. 547; Kikuchi, T., Yoshikai, Y., Miyoshi, J., Katsuki, M., Musikacharoen, T., Mitani, A., Tanaka, S., Matsuguchi, T., (2003) J. Dent. Res, 82, p. 546; Denuziere, A., Ferrier, D., Damour, O., Domard, A., (1998) Biomaterials, 19, p. 1275; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2005) Biomaterials, 26, p. 485; Wang, J.H., Wei, C.W., Liu, H.C., Young, T.H., (2003) J. Biomed. Mater. Res, 64 A, p. 606; Michael, K.E., Vernekar, V.N., Keselowsky, B.G., Meredith, J.C., Latour, R.A., Garcia, A.J., (2003) Langmuir, 19, p. 8033; Keselowsky, B.G., Collard, D.M., Garcia, A.J., (2003) J. Biomed. Mater. Res, 66 A, p. 247; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., (2003) J. Biomed. Mater. Res, 67 A, p. 538; McFarland, C.D., Mayer, S., Scotchford, C., Dalton, B.A., Steele, J.G., Downes, S., (1999) J. Biomed. Mater. Res, 44, p. 1; Cowles, E.A., Brailey, L.L., Gronowicz, G.A., (2000) J. Biomed. Mater. Res, 52, p. 725; Marco, R.A.W., Diaz-Montero, C.M., Wygant, J.N., Kleinerman, E.S., McIntyre, B.W., (2003) J. Cell. Biochem, 88, p. 1038; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Dean, D.D., Boyan, B.D., (1995) J. Biomed. Mater. Res, 29, p. 389; Anselme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Iost, A., Hardouin, P., (2000) J. Biomed. Mater. Res, 49, p. 155; Zinger, O., Anselme, K., Denzer, A., Habersetzer, P., Wieland, M., Jeanfils, J., Hardouin, P., Landolt, D., (2004) Biomaterials, 25, p. 2695
Keywords: Acetylation; AFM; article; Atomic force microscopy; Biocompatible Materials; biofilm; Biofilms; biomaterial; bone cell; cartilage cell; cell adhesion; cell anchorage; Cell culture; cell growth; Cell Line, Tumor; cell proliferation; Cell Shape; cell spreading; cell survival; Chemical structure; chemistry; Chitin; chitosan; comparative study; controlled study; cytoskeleton; Degree of acetylation; drug effect; Growth kinetics; human; human cell; Humans; incubation time; metabolism; Microscopy, Atomic Force; osteoblast; Osteoblast-like cells; Osteoblasts; Pathology; priority journal; Surface charge; Surface Properties; surface property; Surface treatment; tumor cell line; Zeta potential

Automatic vertebra detection in x-ray images - Moura, D.C.; Correia, M.V.; Barbosa, J.G.; Reis, A.M.; Laranjeira, M.; Gomes, E. (Proceedings of the International Symposium CompIMAGE 2006 - Computational Modelling of Objects Represented in Images: Fundamentals, Methods and ApplicationsProc. Int. Symp. CompIMAGE - Comput. Model. Objects Represent. Images: Fundam., Methods Appl., 2007)
In this paper we will describe our experiments with x-ray image analysis for vertebra detection in juvenile/adolescent patients with idiopathic scoliotic spines. We will focus on detecting vertebrae location in a anterior-posterior x-ray image in a fully automatic way. For accomplishing this, we propose a set of techniques for (i) isolating the spine by removing other bone structures (e.g. ribs), (ii) detecting vertebrae location along the spine using an hierarchical and progressive threshold analysis, and (iii) detecting vertebrae lateral boundaries. © 2007 Taylor & Francis Group.
Conference code: 75470Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Moura, D. C.; INEB - Instituto de Engenharia Biomédica, Laboratório de Sinal e Imagem, Porto, PortugalReferences: Benameur, S., Mignotte, M., Labelle, H., Guise, J.A.D., A hierarchical statistical modeling approach for the unsupervised 3-d biplanar reconstruction of the scoliotic spine (2005) IEEE Trans Biomed Eng, 52 (12), pp. 2041-2057. , December;de Bruijne, M. and M. Nielsen (2004a). Image segmentation by shape particle filtering, Chapter III, pp. 722-725. International Conference on Pattern Recognition. IEEE Computer Society Pressde Bruijne, M., Nielsen, M., Shape particle filtering for image segmentation (2004) Lecture Notes in Computer Science, 3216, pp. 168-175. , of, Chapter I, pp, Springer; Ghebreab, S., Smeulders, A., Combining strings and necklaces for interactive threedimensional segmentation of spinal images using an integral deformable spine model (2004) IEEE Trans Biomed Eng, 51 (10), pp. 1821-1829. , October; Pomero, V., Mitton, D., Laporte, S., de Guise b, J.A., Skalli, W., Fast accurate stereoradiographic 3d-reconstruction of the spine using a combined geometric and statistic model (2004) Clinical Biomechanics, 19 (3), pp. 240-247. , March; Scott, I., Cootes, T., Taylor, C., Shape particle filtering for image segmentation (2003) Lecture Notes in Computer Science, 2732, pp. 258-269. , of, Springer; Smyth, P., Taylor, C., Adams, J., Vertebral shape: Automatic measurement with active shape models (1999) Radiology, 211 (2), pp. 571-578; Zamora, G., Sari-Sarrafa, H., Long, R., Hierarchical segmentation of vertebrae from x-ray images (2003) Med Imaging: Image Process, 5032, pp. 631-642. , SPIE Press
Keywords: Anterior posteriors; Bone structures; Image analysis; Lateral boundaries; Mammals; Threshold analysis; X ray analysis; X ray apparatus; X-ray images

Degradation studies of some polymeric biomaterials: Polypropylene PP and polyvinylidene difluoride (PVDF) - Silva, R.A.; Silva, P.A.; Carvalho, M.E. (Materials Science ForumMater Sci Forum, 2007)
Degradation studies of PP and PVDF monofilaments were carried out using a special chamber for several periods of time. One set of the samples was exposed to a 0.9 % NaCl solution and to ultraviolet radiation at 83° C and the other set involved the exposition in air under the same conditions of irradiation and temperature. Scanning Electron Microscopy (SEM) analysis showed direct evidence of PP degradation. Meanwhile, the PVDF monofilaments showed no apparent evidence of degradation under the same conditions. Differential Thermal Analysis (DTA) curves, FTIR spectra and Oxidation Induction Time experiments confirmed the results of SEM Analysis.
Conference code: 71122Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: MSFOELanguage of Original Document: EnglishCorrespondence Address: Silva, R.A.; Instituto Superior de Engenharia do Porto, Rua Dr. António Bernardino de Almeida, 431, 4200-072 Porto, Portugal; email: rasilva@isep.ipp.ptReferences: Kurosaki, S., Otsuka, H., Kunitomo, M., Koiama, M., Pawankar, R., Matumoto, K., (1999) J. Nippon. Med. Sch, 66, pp. 41-44;Salthouse, T.N., Biocompatibility of Sutures (1982) Biocompatibility in Clinical Practice, 1, pp. 11-33. , D. F. Williams ed, Boca Raton, FL: CRC Press Inc; Craig, P.A., Williams, I.A., Magoun, A.D., Levin, A.J., Bogdansky, S., Jones, J.P., (1975) Surg. Gynecol. Obstet, 141, pp. 1-8; D. F. Williams. Corrosion and Degradation of implant Materials, B. C. Syrett, A. Acharya, eds. STP 684, Philadelphia, PA: ASTM Special Technical Publication, (1978) 61-75Dahlke, H., Docia, N., Thurran, K., (1980) J. Biomed. Mater. Res, 14, pp. 51-68; Postlethwait, R.W., (1975) Ann. Sur, 190, pp. 127-132; Salthouse, T.N., Matlaga, B.F., (1985) J. Surg. Res, 19, pp. 127-132; Alaymo, F., Vacarri, M., (1985) Ann. Thoracic. Surg, 39, pp. 400-404; Cornel, G., (1982) Ann. Thoracic. Surg, 33, pp. 64-67; Kawai, H., (1969) Jpn. J. Appl. Phys, 8, pp. 975-976; Bergman Jr., J.G., Mcfee, J.H., Crane, G.R., (1971) Appl. Phys. Lett, 18, pp. 203-205; Xiao, D.Q., Lang, S.B., (1989) IEEE Trans. Elec. Insul, 24, pp. 503-516; Ganz, B., (1989) IEEE Trans. Elec. Insul, 24, pp. 499-502; Laroche, G., Marois, Y., Guidoin, R., King, M., Martin, L., How, T., Douville, Y., (1995) J. Biomed. Mater. Res, 29, pp. 1525-1536; Ademovic, Z., Klee, D., Kingshott, P., Kaufman, R., Hocker, H., (2002) Biomolecular Engineering, 19, pp. 277-182; Klee, D., Ademovic, Z., Bosserhoff, A., Hocker, H., Maziolis, G., Erli, H.-J., (2003) Biomaterials, 24, pp. 3663-3670; Wada, A., Kubota, H., Hatanaka, H., Miura, H., Iwamoto, Y., (2001) J. Hand Surg, 26 B, pp. 212-216; Klinge, U., Klosterhalfen, B., Hottinger, A.P., Junge, K., Schumpelick, V., (2002) Biomaterials, 23, pp. 3487-3493
Keywords: Biomaterials; Degradation; Degradation of polypropylene and polyvinylidene difiuoride; Fourier transform infrared spectroscopy; FTIR spectroscopy; Monofilament sutures; Monofilaments; Oxidation induction time; Polypropylenes; Redox reactions; Thermal analysis; Thermoanalysis

Detection of lung nodule candidates in chest radiographs - Pereira, C.S.; Fernandes, H.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2007)
This paper presents an automated method for the selection of a set of lung nodule candidates, which is the first stage of a computeraided diagnosis system for the detection of pulmonary nodules. An innovative operator, called sliding band filter (SBF), is used for enhancing the lung field areas. In order to reduce the influence of the blood vessels near the mediastinum, this filtered image is multiplied by a mask that assigns to each lung field point an a priori probability of belonging to a nodule. The result is further processed with a watershed segmentation method that divides each lung field into a set of non-overlapping areas. Suspicious nodule locations are associated with the regions containing the highest regional maximum values. The proposed method, whose result is an ordered set of lung nodule candidate regions, was evaluated on the 247 images of the JSRT database with very promising results. © Springer-Verlag Berlin Heidelberg 2007.
Conference code: 70962Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Pereira, C.S.; INEB - Instituto de Engenharia Biomédica, Laboratório de Sinal e Imagem, Campus FEUP (Faculdade de Engenharia da Universidade do Porto), Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: cmsp@fe.up.ptReferences: Wei, J., Hagihara, Y., Shimizu, A., Kobatake, H., Optimal image feature set for detecting lung nodules on chest X-ray images (2002) CARS 2002;Keserci, B., Yoshida, H., Computerized detection of pulmonary nodules in chest radiographs based on morphological features and wavelet snake model (2002) Medical Image Analysis, 6, pp. 431-447; Yoshida, H., Local contralateral subtraction based on bilateral symmetry of lung for reduction of false positives in computerized detection of pulmonary nodules, Biomedical Engineering (2004) IEEE Transactions, 51, pp. 778-789; Suzuki, K., Shiraishi, J., Abe, H., MacMahon, H., Doi, K., False-positive reduction in computer-aided diagnostic scheme for detecting nodules in chest radiographs by means of massive training artificial neural network (2005) Academic Radiology, 12, pp. 191-201; Schilham, A., van Ginneken, B., Loog, M., Multi-scale Nodule Detection in Chest Radiographs (2003) LNCS, 2878, pp. 602-609. , Ellis, R.E, Peters, T.M, eds, MICCAI 2003, Springer, Heidelberg; Schilham, A., van Ginneken, B., Loog, M., A computer-aided diagnosis system for detection of lung nodules in chest radiographs with an evaluation on a public database (2006) Medical Image Analysis, 10, pp. 247-258; Kobatake, H., Hashimoto, S., Convergence index filter for vector fields (1999) IEEE Transactions on Image Processing, 8 (8); Shiraishi, J., Katsuragawa, S., Kezoe, S., Matsumoto, T., Kobayashi, T., Komatsu, K., Matsui, M., Doi, K., Development of a Digital Image Database for Chest Radiographs With and Without a Lung Nodule: Receiver Operating Characteristic Analysis of Radiologists' Detection of Pulmonary Nodules (2000) American Journal of Roentgenology, 174, pp. 71-74; Kobatake, H., Murakami, M., Adaptive filter to detect rounded convex regions: Iris filter (1996) Int. Conf. Pattern Recognition, 11, pp. 340-344; Wei, J., Hagihara, Y., Kobatake, H.: Detection of cancerous tumors on chest X-ray images - Candidate detection filter and its evaluation, ICIP99, no. 27AP4.2 (1999)Kobatake, H., Wei, J., Yoshinaga, Y., Hagihara, Y., Shimizo, A., Nonlinear Adaptine Convergence Index Filters and Their Characteristics (2000) Int. Conf. Pattern Recognition, pp. 522-525
Keywords: Blood Vessels; Computer aided diagnosis; Database systems; Lung nodule candidates; Non-overlapping areas; Pulmonary diseases; Pulmonary nodules; Radiography; Sliding band filter (SBF)

Efficient approximation of the mahalanobis distance for tracking with the Kalman filter - Pinho, R.R.; Tavares, J.M.R.S.; Correia, M.V. (Proceedings of the International Symposium CompIMAGE 2006 - Computational Modelling of Objects Represented in Images: Fundamentals, Methods and ApplicationsProc. Int. Symp. CompIMAGE - Comput. Model. Objects Represent. Images: Fundam., Methods Appl., 2007)
We address the problem of tracking efficiently feature points along image sequences. To estimate the undergoing movement we use an approach based on Kalman filtering which performs the prediction and correction of the features movement in every image frame. In this paper measured data is incorporated by optimizing the global correspondence set based on efficient approximations of the Mahalanobis distances (MD). We analyze the difference between using the MD and its efficient approximation in the tracking results, and also examine the related computational costs. Experimental results which validate our approach are presented. © 2007 Taylor & Francis Group.
Conference code: 75470Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Pinho, R. R.; FEUP- Faculdade de Engenharia da Universidade do PortoPortugalReferences: Brown, L., Senior, A., Tian, Y., Connell, J., Hampapur, A., Shu, C., Merkl, H., Lu, M., Performance evaluation of surveillance systems under varying conditions (2005) IEEE International Workshop on Performance Evaluation of Tracking and Surveillance, , Colorado, USA;Cucchiara, R., Grana, C., Piccardi, M., Prati, A., Statistic and knowledge-based moving object detection in traffic scenes (2000) IEEE Conference on Intelligent Transportation Systems, , Dearborn, USA; Jorge, P., Abrantes, A., Marques, J., On-line tracking groups of pedestrians with bayesian networks (2004) Workshop PETS, , Prague, Czech Republic; Kato, N., M. Abe, and Y. Nemoto (1996). A handwritten character recognition system using modified mahalanobis distance. Transactions Institute of Electronics, Information and Communication Engineers (IEICE) J79-D{1), 45-52Kimura, F., Shridhar, M., Handwritten numerical recognition based on multiple algorithms (1991) Pattern Recognition, 24, pp. 969-983; Kurita, M., Tsuruoka, S., Yokoi, S., Miyake, Y., Handprinted "kanji" and "hiragana" character recognition using weighting direction index histograms and quasimahalanobis distance. Technical report (1983) IEICE Technical Report, , PRL82-79; Lin, L., Bar-Shalom, Y., New assignment-based data association for tracking move-stop-move targets (2004) IEEE Transactions on Aerospace and Electronic Systems, 40 (2), pp. 714-725; O'Malley, P., Nechyba, M., Arroyo, A., Human activity tracking for wide-area surveillance (2002) 2002 Florida Conference on Recent Advances in Robotics, , Miami, USA; Pinho, R., Tavares, J., Correia, M., Human movement tracking and analysis with kalman filtering and global optimization techniques (2005) II International Conference On Computational Bioengineering, , Lisbon, Portugal; Sun, F., Omachi, S., Kato, N., Aso, H., Kono, S., Takagi, T., Two-stage computational cost reduction algorithm based on mahalanobis distance approximations (2000) International Journal of Pattern Recognition, 2, pp. 2969-2973; Welch, G., Bishop, G., An Introduction to Kalman Filter (1995), Technical report, University of North Carolina at Chapel HillWren, C., Azarbayejani, A., Darell, T., Pentland, A., Pfinder: Real-time tracking of the human body (1997) IEEE Transactions on Pattern Analysis and Machine Intelligence, 19 (1), pp. 780-785
Keywords: Computational costs; Control theory; Feature points; Image frames; Image sequences; Kalman filters; Kalman-filtering; Mahalanobis distances; Measured datum

Efficient approximation of the mahalanobis distance for tracking with the Kalman filter - Pinho, R.R.; Tavares, J.M.R.S.; Correia, M.V. (International Journal of Simulation ModellingInt. J. Simul. Model., 2007)
In this paper, we address the problem of tracking feature points along image sequences efficiently. Thus, to estimate the undergoing movement we use an approach based on Kalman filtering, which performs the prediction and correction of the features' movement in every image frame. Measured data is incorporated by optimizing the global association set built on efficient approximations of the Mahalanobis distance (MD). We analyze the difference between the usage in the tracking results of the original MD formulation and its more efficient approximation, as well as the related computational costs. Experimental results which validate our approach are presented.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.2507/IJSIMM06(2)S.03Language of Original Document: EnglishCorrespondence Address: Pinho, R.R.; FEUP - Faculdade de Engenharia da Universidade do Porto, INEGI - Instituto de Engenharia. Mecânica e Gestão Industrial, LOMe - Lab. de Óptica e Mecånica ExperimentalPortugal; email: rpinho@fe.up.ptReferences: Wren, C., Azarbayejani, A., Darrell, T., Pentland, A., Pfinder: Real-Time Tracking of the Human Body (1997) IEEE Transactions on Pattern Analysis and Machine Intelligence, 19 (7), pp. 780-785;Cucchiara, R., Grana, C., Piccardi, M., Prati, A., Statistic and Knowledge-based Moving Object Detection in Traffic Scenes (2000) Proceedings of the 3rd IEEE Conference on Intelligent Transportation Systems (ITSC2000), , Dearborn, Indiana, USA; Jorge, P., Abrantes, A., Marques, J., On-line Tracking Groups of Pedestrians with Bayesian Networks (2004) Workshop PETS, , Prague, Czech Republic; Lin, L., Bar-Shalom, Y., New Assignment-Based Data Association for Tracking Move-Stop-Move Targets (2004) IEEE Transactions on Aerospace and Electronic Systems, 40 (2), pp. 714-725; O'Malley, P., Nechyba, M., Arroyo, A., Human Activity Tracking for Wide-Area Surveillance (2002) 2002 Florida Conference on Recent Advances in Robotics, , Miami, USA; Kurita, M., Tsuruoka, S., Yokoi, S., Miyaké, Y., Handprinted "Kanji" and "Hiragana" character recognition using weighting direction index histograms and quasi-Mahalanobis distance (1983) IEICE Technical Report, , PRL82-79; Kato, N., Abe, M., Nemoto, Y., A Handwritten Character Recognition System Using Modified Mahalanobis Distance (1996) Transactions Institute of Electronics, Information and Communication Engineers (IEICE), J79-D (L), pp. 45-52; Kimura, F., Shridhar, M., Handwritten numerical recognition based on multiple algorithms (1991) Pattern Recognition, 24 (10), pp. 969-983; Sun, F., Omachi, S., Kato, N., Aso, H., Kono, S., Takagi, T., Two-Stage Computational Cost Reduction Algorithm Based on Mahalanobis Distance Approximations (2000) International Conference of Pattern Recognition, , Barcelona, Spain; Pinho, R., Tavares, J., Correia, M., Human Movement Tracking and Analysis with Kalman Filtering and Global Optimization Techniques (2005) II International Conference On Computational Bioengineering, , Lisbon, Portugal; Welch, G., Bishop, G., An Introduction to Kalman Filter (1995), University of North Carolina at Chapel Hill, Technical Report, TR 95-041Pinho, R., Tavares, J., Correia, M., A Movement Tracking Management Model with Kaiman Filtering, Global Optimization Techniques and Mahalanobis Distance (2005) ICCMSE 2005 International Conf. on Computational Methods in Science and Engineering, , Loutraki, Greece; Pinho, R., Tavares, J., Correia, M., An Improved Management Model for Tracking Missing Features in Computer Vision Long Image Sequences (2007) WSEAS Transactions on Information Science and Applications, 4 (1), pp. 196-203; Brown, L., Senior, A.W., Tian, Y., Connell, J., Hampapur, A., Shu, C., Merkl, H., Lu, M., Performance Evaluation of Surveillance Systems Under Varying Conditions (2005) IEEE Int. Workshop on Performance Evaluation of Tracking and Surveillance, , Colorado, USA
Keywords: Computational vision; Data association; Kalman filter; Mahalanobis distance; Tracking

Evaluation of contrast enhancement filters for lung nodule detection - Pereira, C.S.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2007)
The aim of this paper is to evaluate and compare the performance of three convergence index (CI) filters when applied to the enhancement of chest radiographs, aiming at the detection of lung nodules. One of these filters, the sliding band filter (SBF), is the proposal of an innovative operator, while the other two CI class members, the iris filter (IF) and the adaptive ring filter (ARF), are already known in this application. To demonstrate the adequacy of the new filter for the enhancement of chest x-ray images, we calculated several figures of merit with the goal of comparing (i) the contrast enhancement capability of the filters, and (ii) the behavior of the filters for the detection of lung nodules. The results obtained for 154 images with nodules of the JSRT database show that the SBF outperforms both the IF and ARF. The proposed filter demonstrated to be a promising enhancement method, thus justifying its use in the first stage of a computer-aided diagnosis system for the detection of lung nodules. © Springer-Verlag Berlin Heidelberg 2007.
Conference code: 70855Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Pereira, C.S.; INEB - Instituto de Engenharia Biomédica, Laboratório de Sinal e Imagem, Campus FEUP (Faculdade de Engenharia da Universidade do Porto), Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: cmsp@fe.up.ptReferences: Kobatake, H., Murakami, M., Adaptive filter to detect rounded convex regions: Iris filter (1996) Int. Conf. Pattern Recognition, 2, pp. 340-344;Kobatake, H., Hashimoto, S., Convergence index filter for vector fields (1999) IEEE Transactions on Image Processing, 8 (8); Wei, J., Hagihara, Y., Kobatake, H.: Detection of cancerous tumors on chest X-ray images - Candidate detection filter and its evaluation. In: ICIP99, 27AP4.2 (1999)Kobatake, H., Wei, J., Yoshinaga, Y., Hagihara, Y., Shimizo, A., Nonlinear Adaptinc Convergence Index Filters and Their Characteristics (2000) Int. Conf. Pattern Recognition, pp. 522-525; Shiraishi, J., Katsuragawa, S., Kezoe, S., Matsumoto, T., Kobayashi, T., Komatsu, K., Matsui, M., Doi, K., Development of a Digital Image Database for Chest Radiographs With and Without a Lung Nodule: Receiver Operating Characteristic Analysis of Radiologists' Detection of Pulmonary Nodules (2000) American Journal of Roentgenology, 174, pp. 71-74; Keserci, B., Yoshida, H., Computerized detection of pulmonary nodules in chest radiographs based on morphological features and wavelet snake model (2002) Medical Image Analysis, 6, pp. 431-447; Song, X., Pogue, B., Jiang, S., Doyley, M., Dehghani, H., Tosteson, T., Paulsen, K., Automated region detection based on the contrast-to-noise ratio in near-infrared tomography (2004) Applied Optics, 43 (5), pp. 1053-1062; Singh, S., Bovis, K., An evaluation of contrast enhancement techniques for mammographic breast masses (2005) IEEE Transactions On Information Technology in Biomedicine, 9 (1), pp. 109-119; Wei, J., Hagihara, Y., Shimizu, A., Kobatake, H., Optimal image feature set for detecting lung nodules on chest X-ray images (2002) CARS; Suzuki, K., Shiraishi, J., Abe, H., MacMahon, H., Doi, K., False-positive reduction in computer-aided diagnostic scheme for detecting nodules in chest radiographs by means of massive training artificial neural network (2005) Academic Radiology, 12, pp. 191-201;
Keywords: Adaptive systems; Contrast enhancement filters; Database systems; Image segmentation; Iris filter (IF); Medical imaging; Radiography; X rays

Face detection based on skin color in video images with dynamic background - Ferreira, A.M.; Correia, M.V. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2007)
Face detection is a problem in image processing that has been extensively studied in the last decades. This fact is justified due to the innumerous applications this subject has in computer vision. In this paper we present a technique to detect a face in an image where several persons may be. The images were recorded from news broadcasts from different networks. First, a model based on normalized RGB color space was built to define a skin color model: skin regions were selected from several face images and extracted statistical characteristics. Second, each pixel of the image was classified in two categories: skin and not skin. Third, the face region was identified. A MATLAB function was created to detect faces of any size, achieving high detection rates. © Springer-Verlag Berlin Heidelberg 2007.
Conference code: 70855Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Ferreira, A.M.; Instituto de Engenharia Biomédica, Laboratório de Sinal e Imagem, Departamento de Engenharia Electrotécnica e de Computadores, Rua Dr. Roberto Frias, s/n, 4200-465 Porto, Portugal; email: mota.ferreira@fe.up.ptReferences: Chelllappa, R., Wilson, C., Sirohey, S., Human and machine recognition of faces: A survey (1995) IEEE, 83, pp. 705-740;Viola, P., Jones, M., Robust Real-Time Face Detection (2004) International Journal of Computer Vision, 57 (2), pp. 137-154; Schneiderman, H., Kanade, T., A Statistical Method for 3D Object Detection Applied to Faces and Cars (2000) IEEE Conference on Computer Vision and Pattern Recognition, June, , IEEE Computer Society Press, Los Alamitos; Rowley, H., Baluja, S., Kanade, T., (1995) Human face detection in visual scenes, , November; Vazhnevets, V., Sazonov, V., Andreeva, A., A Survey on Pixel-Based Skin Color Detection Techniques (2003) Proceedings Graphicon-2003, pp. 85-92. , Moscow, Russia, September; Crowley, J.L., Berard, F., Multimodel Tracking of Faces for Video Communications (1997) IEEE Proc. Conference on Computer Vision and Pattern Recognition, pp. 640-645. , IEEE Computer Society Press, Los Alamitos; Garcia, C., Zikos, G., Tziritas, G., Face detection in Color Images Using Wavelet Packet Analisis (1999) ICMCS, 1, pp. 703-708
Keywords: Color; Color segmentation; Computer vision; Face detection; Face recognition; MATLAB; Skin; Skin color model; Skin detection

A Gait Analysis Laboratory for rehabilitation of patients with musculoskeletal impairments - Sousa, D.S.S.; Tavares, J.M.R.S.; Correia, M.V.; Barbosa, J.G.; Chã, C.V.; Mendes, E. (Proceedings of the International Symposium CompIMAGE 2006 - Computational Modelling of Objects Represented in Images: Fundamentals, Methods and ApplicationsProc. Int. Symp. CompIMAGE - Comput. Model. Objects Represent. Images: Fundam., Methods Appl., 2007)
This paper describes the technology (software & hardware) used in the Gait Analysis Laboratory of CRPG - Centro de Reabilitação Projissional de Gaia. This laboratory is mainly intended to support CRPG with quantitative data for clinical rehabilitation of patients with musculoskeletal pathologies, namely in the lower limbs. Usually, for the gait analysis is considered data obtained from several acquisition sensors, such as: image cameras, electromyographic devices, pressure devices and force plates. This paper also presents briefly how quantitative motion analysis can be used for a clinical point of view and it presents the influence of image algorithms in gait rehabilitation. © 2007 Taylor & Francis Group.
Conference code: 75470Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Sousa, D. S. S.; INEGI, Instituto de Engenharia Mecǎnica e Gestão Industrial, Porto, PortugalReferences: Baker, R., Gait analysis methods in rehabilitation (2006) Journal of Neuro Engineering and Rehabilitation, 3 (1), p. 4;Cappozzo, A., Delia Croce, U., Human movement analysis using stereophotogrammetry. Part I: Theoretical background (2005) Gait & Posture, 21, pp. 186-196; Chau, T., A review of analytical techniques for gait data. Part 1: Fuzzy, statistical and fractal methods (2001) Gait & Posture, 13 (1), pp. 49-66; Davis, R.B., Reflections on clinical gait analysis (1997) Journal of Electromyography and Kinesiology, 7 (4), pp. 251-257; Davis III, R.B., Clinical gait analysis (1988) Engineering in Medicine and Biology Magazine, IEEE, 7 (3), pp. 35-40; Figueroa, P.J., Leite, N.J., A flexible software for tracking of markers used in human motion analysis (2003) Computer Methods and Programs in Biomedicine, 72, pp. 155-165; Gavrila, D., The visual analysis of human movement: A survey (1999) Computer Vision and Image Understanding, 73 (1), pp. 82-98; Merletti, R., Parker, P., (2004) Electromyography: Physiology, engineering and noninvasive applications, , Wiley-IEEE Press; (1978) NASA Reference Publication, , NASA, Springfield: NASA; Orlin, M., McPoil, T., Plantar pressure assessment (2000) Physical therapy, 80 (4), pp. 399-409; Perry, J., The contribution of dynamic electromyography to gait analysis (1998) Monograph 002: Gait analysis in the science of rehabilitation. 1998, , J. DeLisa ed, Washington, DC; Pinho, R., Tavares, J., A Movement Tracking Management Model with Kalman Filtering, Global Optimization Techniques and Mahalanobis Distance (2005) ICCMSE 2005 - International Conference of Computational Methods in Sciences and Engineering; Loutraki, 21-26 October 2005, , Korinthos: Greece; Pinho, R., Tavares, J., Human Movement Tracking and Analysis with Kalman Filtering and Global Optimization Techniques (2005) ICCB2005 - II International Conference on Computational Bioengineering; Instituto Superior Técnico, Lisboa, 14-16 September 2005, , Lisboa: Portugal; Rosenbaum, D., Becker, H., Plantar pressure distribution measurements. Technical background and clinical applications (1997) Foot and Ankle Surgery, 3 (1), pp. 1-14; Roy, K., Force, pressure and motion measurements in the foot: Current concepts (1988) Clinics in Podiatric Medicine and Surgery, 5, pp. 491-508; Schmalz, T., Blumentrit, S., Energy expenditure and biomechanical characteristics of lower limb amputee gait: The influence of prosthetic alignment and different prosthetic components (2002) Gait & Posture, 16, pp. 255-263; Shabana, A., (2001) Computational Dynamics, , NY: John Wiley; Sisto, S. 1998. An overview of the value of information resulting from instrumented gait analysis for the physical therapist. In J. DeLisa (ed.) Monograph 002: Gait analysis in the science of rehabilitation. 1998. Washington, DC. Sutherland, D. 2001. The evolution of clinical gait analysis part 1: kinesiological EMG. Gait & Posture 14(1): 61-70Sutherland, D., The evolution of clinical gait analysis: Part II Kinematics (2002) Gait & Posture, 16 (2), pp. 159-179; Tavares, J., Bastos, L., Improvement of Modal Matching Image Objects in Dynamic Pedobarography using Optimization Techniques (2005) Electronic Letters on Computer Vision and Image Analysis, special issue on Articuled Motion & Deformable Objects, 5, pp. 1-20; Tavares, J., Barbosa, J., Matching Image Objects in Dynamic Pedobarography (2000) RecPad 2000 - 11th Portuguese Conference on Pattern Recognition; Porto, 11-12 Maio 2000, , Porto, Portugal; Urry, S., Plantar pressure-measurement sensors (1999) Measurement Science and Technology, 10, pp. 16-32; Whittle, M., Clinical gait analysis: A review (1996) Human Movement Science, 15, pp. 369-387; Whittle, M., (2003) Gait analysis an introduction, , Oxford, Boston: Butterworth-Heinemann; Winter, D., (2005) Biomechanics and motor control of human movement, , Hoboken: John Wiley & Sons
Keywords: Acquisition sensors; Electromyographic; Force plates; Gait analysis; Gait rehabilitations; Image algorithms; Lower limbs; Motion analysis; Patient rehabilitation; Pressure devices; Quantitative datum

An improved management model for tracking missing features in computer vision long image sequences - Pinho, R.R.; Tavares, J.M.R.S.; Correia, M.V. (WSEAS Transactions on Information Science and ApplicationsWSEAS Trans. Inf. Sci. Appl., 2007)
In this paper we present a management model to deal with the problem of tracking missing features during long image sequences using Computational Vision. Some usual difficulties related with missing features are that they may be temporarily occluded or might even have disappeared definitively, and the computational cost involved should always be reduced to the strictly necessary. The proposed Net Present Value (NPV) model, based on the economic Theory of Capital, considers the tracking of each missing feature as an investment. Thus, using the NPV criterion, with adequate receipt and outlay functions, each occluded feature may be kept on tracking or it may be excluded of the tracking process depending on its historical behavior. This approach may be applied to any tracking system as long as the tracking results may be evaluated in each temporal step, and it can deal with the appearance, occlusion and disappearance of features especially useful for tracking in long image sequences. Experimental results, both on synthetic and real image sequences, which validate our model, will be also presented.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Pinho, R.R.; FEUP - Faculdade de Engenharia da Universidade do Porto, INEGI - Instituto de Engenharia Mecânica e Gestão Industrial, LOME - Lab. de Óptica e Mecânica Experimental, Rua Dr. Roberto Frias, s/n, 4200-465 Porto, Portugal; email: rpinho@fe.up.ptReferences: Davison, A., Deutscher, J., Reid, I., "Markerless motion Capture of Complex Full-Body Movement for Character Animation" (2001) Proceedings Eurographics Workshop on Animation and Simulation, , Manchester, UK;Lakany, H., Hayes, G., Hazlewood, M., Hillman, S., "Human Walking: Tracking and Analysis" (1999) IEEE Electronic & Communications, Colloquium on Motion Analysis and Tracking; Rosales, R., Sclaroff, S., "Improved Tracking of Multiple Humans with Trajectory Prediction and Occlusion Modelling" (1998) Proceedings IEEE Conference on Computer Vision and Pattern Recognition, Workshop on the Interpretation of Visual Motion, , Santa Barbara, USA; Huang, Y., Essa, I., "Tracking Multiple Objects through Occlusions" (2005) IEEE Conference on Computer Vision and Pattern Recognition 2005 (CVPR 2005), , San Diego, USA; Zhao, T.S., Nevatia, R., "Tracking Multiple Humans in Complex Situations" (2004) IEEE Transactions on Image Processing, 26 (9), pp. 1208-1221; Plänkers, R., Fua, P., "Tracking and Modeling People in Video Sequences" (2001) Computer Vision and Image Understanding, 81 (3), pp. 285-302; Jorge, P., Abrantes, A., Marques, J., "On-line Tracking Groups of Pedestrians with Bayesian Networks" (2004) Workshop PETS, , Prague, Czech Republic; Wren, C., Azarbayejani, A., Darrell, T., Pentland, A., "Pfinder: Real-Time Tracking of the Human Body" (1997) IEEE Transactions on Pattern Analysis and Machine Intelligence, 19 (7), pp. 780-785; Tavares, J., Padilha, A., "Matching Lines in Image Sequences with Geometric Constraints" (1995) 7° Congresso Português De Reconhecimento De Padrões, , Aveiro, Portugal; Pinho, R., Tavares, J., Correia, M., "A Movement Tracking Management Model with Kalman Filtering, Global Optimization Techniques and Mahalanobis Distance" (2005) ICCMSE 2005 - International Conference on Computational Methods in Science and Engineering, , Loutraki, Greece; Baumol, W., (1985) Economic Theory and Operations Research, , Prentice-Hall; Levy, H., (1994) Capital Investment and Financial Decisions, , Prentice-Hall; Pinho, R., Tavares, J., Correia, M., "Human Movement Tracking and Analysis with Kalman Filtering and Global Optimization Techniques" (2005) II International Conference On Computational Bioengineering, , Lisbon, Portugal;
Keywords: Automatic target recognition; Computer vision; Feature extraction; Long image sequences; Management; Mathematical models; Missing features; Motion estimation; Net Present Value (NPV); Occlusion; Tracking

Opening wedge high tibial osteotomy using 3D biomodelling Bonelike® macroporous structures: Case report - Gutierres, M.; Dias, A.G.; Lopes, M.A.; Hussain, N.S.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2007)
Two synthetic calcium phosphates in porous wedge shape, Bonelike® and a commercial HA/β-TCP biphasic material, were used as an alternative to bone autografts and allografts in the treatment of medial compartment osteoarthritis of varus knees. The structure of Bonelike® has a 3D architecture that is computer controlled, and a composition that mimics the mineral composition of natural bone. The HA/β-TCP biphasic material used as a control material in this study was prepared using conventional foaming based methods. No signs of inflammatory reactions were observed post-operatively for both materials. After 4 months signs of fusion at the osteotomy site and good integration of the implanted wedges were observed, showing good mechanical resistance. Concerning the final correction attained, the left knee revealed a satisfactory valgus of 10°, but the right one only had a final value of 6°. The clinical evaluation using International Knee Score (IKS) showed good outcome in all parameters with complete range of motion in both knees and climbing stairs without crutches with only slight pain. © 2007 Springer Science+Business Media, LLC.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-007-3171-xPubMed ID: 17569003Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratório de Biomateriais, Instituto de Engenharia Biomédica (INEB), Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; Bone Substitutes; Calcium Phosphates; Ceratite, 124097-42-3; HydroxyapatitesTradenames: BonelikeReferences: Gaasbeek, R.D.A., Welsing, R.T.C., Verdonschot, N., Rijnberg, W.J., Van Loon, C.J.M., Van Kampen, A., (2005) Knee Surg. Sports Traumatol. Arthrosc., 13, p. 689. , 8;Scott, W.N., Clarke, H.D., (2004) Orthopedics, 27, p. 975. , 9; Virolainen, P., Aro, H.T., (2004) Arch. Orthop. Trauma Surg., 124, p. 258. , 4; Wright, J.M., Crockett, H.C., Slawski, D.P., Madsen, M.W., Windsor, R.E., (2005) J. Am. Acad. Orthop. Surg., 13, p. 279. , 4; Fujisawa, Y., Masura, K., Shiomi, S., (1979) Clin. Orthop. North Am., 10, p. 585; Odenbridge, S., Egund, N., Lindstrand, A., Lohmander, L.S., Willen, H., (1992) Clin Orthop., 277, p. 210; Koshino, T., Wada, S., Ara, Y., Saito, T., (2003) Knee, 10, p. 229; Hernigou, P., (2002) Knee, 9, p. 15. , 1; Hoell, S., Suttmoeller, J., Stoll, V., Fuchs, S., Gosheger, G., (2005) Arch. Orthop. Trauma Surg., 125, p. 638. , 9; Betz, R.R., (2002) Orthopedics, 25, p. 561. , 5; Legeros, R.Z., (2002) Clin. Orthop. Relat. Res., 395, p. 81; Steffen, T., Stoll, T., Arvinte, T., Schenk, R.K., (2001) Eur. Spine J., 10, p. 132; Chu, T.M.G., Orton, D.G., Hollister, S.J., Feinberg, S.E., Halloran, J.W., (2002) Biomaterials, 23, p. 1283. , 5; Hutmacher, D.W., Sittinger, M., Risbud, M.V., (2004) Trends Biotechnol., 22, p. 354. , 7; Jones, J.R., Ehrenfried, L.M., Hench, L.L., (2006) Biomaterials, 27, p. 964. , 7; Gauthier, O., Bouler, J.M., Aguado, E., Pilet, P., Daculsi, G., (1998) Biomaterials, 19, p. 133. , 1-3; LU, J.X., Flautre, B., Anselme, K., Hardouin, P., Gallur, A., Descamps, M., Thierry, B., (1999) J. Mater. Sci. Mater. Med., 10, p. 111. , 2; Martina, M., Subramanyam, G., Weaver, J.C., Hutmacher, D.W., Morse, D.E., Valiyaveettil, S., (2005) Biomaterials, 26, p. 5609. , 28; Moroni, L., De Wijn, J.R., Van Blitterswijk, C.A., (2006) Biomaterials, 27, p. 974. , 7; Duarte, F., Santos, J.D., Afonso, A., (2004) Adv. Mater. Forum, 455-456, p. 370; Lobato, J.V., Hussain, N.S., Botelho, C.M., Mauricio, A.C., Lobato, J.M., Lopes, M.A., Afonso, A., Santos, J.D., (2006) Thin Solid Films, 515, p. 279. , 1; Gutierres, M., Hussain, N.S., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Santos, J.D., (2005) Bioceramics, 17, p. 1041; Lobato, J.V., Hussain, N.S., Botelho, C.M., Rodrigues, J.M., Luís, A.L., Maurício, A.C., Lopes, M.A., Santos, J.D., (2005) Key Eng. Mater., 284-286, p. 877; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463; Leong, K.F., Cheah, C.M., Chua, C.K., (2003) Biomaterials, 24, p. 2363. , 13; Hutmacher, D.W., (2001) J. Biomater. Sci. Polym. Ed., 12, p. 107. , 1; Santos, J., Hastings, G., Knowles, J., Sintered hydroxyapatite compositions and method for the preparation thereof (1999), Worldwide Application (PCT), Patent No. 1 189 851Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) J. Biomed. Mater. Res., 39, p. 244. , 2; Lopes, M.A., Knowles, J.C., Santos, J.D., (2000) Biomaterials, 21, p. 1905. , 18; Schwartz, C., Liss, P., Jacquemaire, B., Lecestre, P., Frayssinet, P., (1999) J. Mater. Sci. Mater. Med., 10, p. 821. , 12; Van Hemert, W.L.W., Willems, K., Anderson, P.G., Van Heerwaarden, R.J., Wymenga, A.B., (2004) Knee, 11, p. 451. , 6; Gaasbeek, R.D.A., Toonen, H.G., Van Heerwaarden, R.J., Buma, P., (2005) Biomaterials, 26, p. 6713. , 33; Hernigou, P., Ma, W., (2001) Knee, 8, p. 103. , 2; Koshino, T., Murase, T., Saito, T., (2003) J. Bone Joint Surg. Am., 85, p. 78. , 1; Koshino, T., Murase, T., Takagi, T., Saito, T., (2001) Biomaterials, 22, p. 1579. , 12; Zhim, F., Laflamme, G.Y., Viens, H., Saidane, K., Yahia, L., (2005) Clin. Biomech., 20, p. 871. , 8; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 20, p. 2085. , 21; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 48, p. 734. , 5
Keywords: adult; article; Biological organs; Biomodeling; Bone; bone allograft; Bone graft; bone mineral; Bone Substitutes; calcium phosphate; Calcium phosphates; case report; climbing; clinical evaluation; Computer simulation; Grafts; human; Humans; hydroxyapatite; Hydroxyapatites; Imaging, Three-Dimensional; knee; knee pain; Macroporous structures; male; Mechanical properties; Middle Aged; Osteoarthritis; Osteoarthritis, Knee; Osteoblasts; osteotomy; pain assessment; porosity; Porous wedge shapes; priority journal; Prostheses and Implants; range of motion; structure analysis; tibia; tibia osteotomy; Tibial osteotomy; Valgus; valgus knee

Adsorption of albumin on prosthetic materials: Implication for tribological behavior - Serro, A.P.; Gispert, M.P.; Martins, M.C.L.; Brogueira, P.; Colaço, R.; Saramago, B. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
The orthopedic prosthesis used to substitute damaged natural joints are lubricated by a pseudosynovial fluid that contains biological macromolecules with potential boundary lubrication properties. Proteins are some of those macromolecules whose role in the lubrication process is not yet completely understood. In a previous work, we investigated the influence of the presence of albumin, the major synovial protein, upon the tribological behavior of three of the most used pairs of artificial joint materials: ultra high molecular weight polyethylene (UHMWPE) against counterfaces of alumina, CoCrMo alloy, and 316L stainless steel. Albumin was found to cause a significant decrease in the friction coefficient when the counterfaces were metallic because transfer of UHMWPE was avoided, but this effect was much weaker in the case of alumina. The objective of the present work was to look for an explanation for these differences in tribological behavior in terms of albumin adsorption. With this goal, studies on adsorption of bovine serum albumin (BSA) on the counterface materials, from a biological model fluid (Hanks' balanced salt solution), were carried out using radiolabeled albumin ( 125I-BSA), X-ray photoelectron spectroscopy, and atomic force microscopy. The conclusion from all techniques is that the driving force for albumin adsorption is higher on the metals than on alumina. These results confirm that the greater the amount of protein adsorbed on the counterface, the more efficient is the protection against the transfer of polymeric film to the counterface. © 2006 Wiley Periodicals, Inc.
Cited By (since 1996): 25Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30754PubMed ID: 16739106Language of Original Document: EnglishCorrespondence Address: Serro, A.P.; Centro de Química Estrutural, Instituto Superior Técnico, Av. Rovisco Pais, 1049-001 Lisboa, Portugal; email: anapaula.serro@ist.utl.ptChemicals/CAS: aluminum oxide, 1302-74-5, 1318-23-6, 1344-28-1, 14762-49-3; iodine 125, 14158-31-7, 22822-81-7; molybdenum, 7439-98-7; protein, 67254-75-5; stainless steel, 12597-68-1; Albumins; Biocompatible MaterialsTradenames: CHIRULEN, Poly Hi Solidur, GermanyManufacturers: Maret, Switzerland; MediMet, Germany; Poly Hi Solidur, GermanyReferences: Widmer, M.R., Heuberger, M., Vörös, J., Spencer, N.D., Influence of polymer surface chemistry on frictional properties under protein-lubrication conditions: Implications for hip-implant design (2001) Tribol Lett, 10, pp. 111-116;Saikko, V., Effect of lubricant protein concentration on the wear of ultrahigh molecular weight polyethylene sliding against a CoCr counterface (2003) Trans ASME, 125, pp. 638-642; Sawae, Y., Murakami, T., Chen, J., Effect of synovia constituents on friction and wear of ultra-high molecular weight polyethylene sliding against prosthetic joint materials (1998) Wear, 216, pp. 213-219; Kumar, P., Oka, M., Ikeuchi, K., Shimizu, K., Yamamuro, T., Okumura, H., Kotoura, Y., Low wear rate of UHMWPE against zirconia ceramic (Y-PSZ) in comparison to alumina ceramic and SUS 316L alloy (1991) J Biomed Mater Res, 25, pp. 813-828; Kitano, T., Ateshian, G.A., Mow, V.C., Kadoya, Y., Yamano, Y., Constituents and pH changes in protein rich hyaluronan solution affect the biotribological properties of artificial cartilage (2001) J Biomech, 34, pp. 1031-1037; Gispert, M.P., Serro, A.P., Colaço, R., Saramago, B., Friction and wear mechanisms in hip prosthesis: Comparison of joint materials behaviour in several lubricants (2006) Wear, 260, pp. 149-158; Van Enckevort, H.J., Dass, D.V., Langdon, A.G., The adsorption of bovine serum albumin at the stainless-steel/aqueous solution interface (1984) J Colloid Interface Sci, 98, pp. 138-143; Fukuzaki, S., Urano, H., Nagata, K., Adsorption of protein onto stainless-steel surfaces (1995) J Ferment Bioeng, 80, pp. 6-11; Rubio, C., Costa, D., Bellon-Fontaine, M.N., Relkin, P., Pradier, C.M., Marcus, P., Characterization of bovine serum albumin adsorption on chromium and AISI 304 stainless steel, consequences for the Pseudomonas fragi K1 adhesion (2002) Colloid Surf B Biointerface, 24, pp. 193-205; Sakiyama, T., Tomura, J., Imamura, K., Nakanishi, K., Adsorption characteristics of bovine serum albumin and its peptide fragments on a stainless steel surface (2004) Colloid Surf B Biointerface, 33, pp. 77-84; Fukuzaki, S., Urano, H., Yamaguchi, T., Effect of modification of alumina surfaces by ozone on adsorption behaviour of bovine serum albumin at alumina-water interfaces (1997) J Ferment Bioeng, 84, pp. 407-413; Urano, H., Fukuzaki, S., Conformation of adsorbed bovine serum albumin governing its desorption behavior at alumina-water interfaces (2000) J Ferm Bioeng, 90, pp. 105-110; Williams, R.L., Williams, D.F., Albumin adsorption on metal surfaces (1998) Biomaterials, 9, pp. 206-212; Haynes, C.A., Norde, W., Globular proteins at solid/liquid interfaces (1994) Colloid Surf B Biointerface, 2, pp. 517-566; Owens, D.K., Wendt, R.C., Estimation of the surface free energy of polymers (1969) J Appl Polym Sci, 13, pp. 1741-1747; Michalski, M.C., Hardy, J., Saramago, B., On the surface tension of PVC/EVA polymer blends: Comparison of different calculation methods (1998) J Colloid Interface Sci, 208, pp. 319-328; Cheng, P., Li, D., Boruvka, L., Rotenberg, Y., Neumann, A.W., Automation zof axisymmetric drop shape analysis for measurements of interfacial tensions and contact angles (1990) Colloid Surf, 43, pp. 151-197; Cheng, P., Neumann, A.W., Computational evaluation of Axisymmetric Drop Shape Analysis - Profile (ADSA-P) (1992) Colloid Surf, 62, pp. 297-306; (1990) Practical Surface Analysis, Vol. 1: Auger and X-Ray Photoelectron Spectroscopy, 1. , Briggs D, Seah MP, editors. Cichester: Wiley; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., Interactions between calcium, phosphate, and albumin on the surface of titanium (2001) J Biomed Mater Res, 55, pp. 45-53; (1993) Iodine-125, a Guide to Radioiodination Techniques, p. 64. , Little Chalfont, Buckinghamshire, UK: Amersham Life Science; Feng, L., Andrade, J.D., Protein adsorption on low temperature isotropic carbon. III. Isotherms, competitivity, desorption and exchange of albumin and fibrinogen (1994) Biomaterials, 15, pp. 323-333; Paynter, R.W., Ratner, B.D., Horbett, T.A., Thomas, H.R., XPS studies on the organization of adsorbed protein films on fluoropolymers (1984) J Colloid Interface Sci, 101, pp. 233-245; Paynter, R.W., Ratner, B.D., The study of interfacial proteins and biomolecules by X-ray photoelectron spectroscopy (1985) Surface and Interfacial Aspects of Biomedical Polymers, Vol. 2: Protein Adsorption, 2, pp. 189-216. , Andrade JD, editor. New York: Plenum; Seah, M.P., Dench, W.A., Quantitative electron spectroscopy of surfaces: A standard data base for electron inelastic mean free paths in solids (1979) Surf Interface Anal, 1, pp. 2-11; Tanuma, S., Powell, C.J., Penn, D.R., Calculations of electron inelastic mean free paths. II. Data for 27 elements over the 50-2000 eV range (1991) Surf Interface Anal, 17, pp. 911-926; Carter, D.C., He, X.M., Munson, S.H., Twigg, P.D., Gernet, K.M., Broom, M.B., Miller, T.Y., Three-dimensional structure of human serum albumin (1989) Science, 244, pp. 1195-1198; Pradier, C.M., Costa, D., Rubio, C., Compère, C., Marcus, P., Role of salts on BSA adsorption on stainless steel in aqueous solutions. I. FT-IRRAS and XPS characterization (2002) Surf Interface Anal, 34, pp. 50-54; Lori, J.A., Hanawa, T., Adsorption characteristics of albumin on gold and titanium metals in Hanks' solution using EQCM (2004) Spectroscopy, 18, pp. 545-552; Sousa, S.R., Moradas-Ferreira, P., Saramago, B., Melo, L.V., Barbosa, M.A., Human serum albumin adsorption on TiO 2 from single protein solutions and from plasma (2004) Langmuir, 20, pp. 9745-9754; Uyen, H.M.W., Schakenraad, J.M., Sjollema, J., Noordmans, J., Jongebloed, W.L., Stokroos, I., Busscher, H.J., Amount and different surface structure of albumin adsorbed to solid substrata with different wettabilities in a parallel plate flow cell (1990) J Biomed Mater Res, 24, pp. 1599-1614; Young, B.R., Pitt, W.G., Cooper, S.L., Protein adsorption on polymeric biomaterials. II. Adsoption kinetics (1988) J Colloid Interface Sci, 125, pp. 246-260; Dulm, P.V., Norde, W., The adsorption of human plasma albumin on solid surfaces, with special attention to the kinetic aspects (1983) J Colloid Interface Sci, 91, pp. 248-255; Malmsten, M., Formation of adsorbed protein layers (1998) J Colloid Interface Sci, 207, pp. 186-199; Smith, I.O., Baumann, M.J., McCabe, L.R., Electrostatic interactions as a predictor for osteoblast attachment to biomaterials (2004) J Biomed Mater Res A, 70, pp. 436-441
Keywords: Adsorption; Albumin; Albumin adsorption; Albumins; Alumina; aluminum oxide; article; Atomic force microscopy; balanced salt solution; Biocompatible Materials; Body fluids; bovine serum albumin; chromium derivative; Cobalt alloy; Cobalt alloys; cobalt derivative; force; Friction; iodine 125; isotope labeling; joint fracture; Joints (anatomy); lubrication; macromolecule; metal; molecular weight; molybdenum; orthopedic prosthesis; orthopedics; Polyethylenes; polymer; Prostheses and Implants; prosthesis material; Prosthetics; protein; Proteins; Pseudosynovial fluid; Stainless steel; Thermodynamics; Tribology; ultra high molecular weight polyethylene; Ultra high molecular weight polyethylene (UHMWPE); X ray photoelectron spectroscopy

The class imbalance problem in TLC image classification - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2006)
The paper presents the methodology developed to solve the class imbalanced problem that occurs in the classification of Thin-Layer Chromatography (TLC) images. The proposed methodology is based on resampling, and consists in the undersampling of the majority class (normal class), while the minority classes, which contain Lysosomal Storage Disorders (LSD) samples, are oversampled with the generation of synthetic samples. For image classification two approaches are presented, one based on a hierarchical classifier and another uses a multiclassifier system, where both classifiers are trained and tested using balanced data sets. The results demonstrate a better performance of the multiclassifier system using the balanced sets. © Springer-Verlag Berlin Heidelberg 2006.
Conference code: 68310Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Sousa, A.V.; Instituto Superior de Engenharia do Porto, Rua Dr. Antonio Bernardino de A. 431, 4200-072 Porto, Portugal; email: ats@isep.ipp.ptReferences: Kubat, M., Holte, R., Matwin, S., Learning when negative examples abound (1997) European Conference on Machine Learning, pp. 146-153;Lazarević, A., Srivastava, J., Kumar, V., Data mining for analysis of rare events: A case study in security, financial and medical applications (2004) PAKDD-2004; Skurichina, M., Raudys, S., Duin, R.P.W., K-nearest neighbors directed noise injection in multilayer perceptron training (2000) IEEE Transactions on Neural Networks, 11 (2); Chawla, N.V., Japkowicz, N., Kolcz, A., Editorial: Special issue on learning from imbalanced data sets (2004) Sigkdd Explorations, 6 (1), pp. 1-6; Japkowicz, N., Class imbalances: Are we focusing on the right issue? Workshop on Learning from Imbalanced Datasets II, p. 6. , (2003) ICML, Washington DC; Chawla, N.V., Lazarević, A., Hall, L.O., Bowyer, K.W., SMOTEBoost: Improving the prediction of minority class in boosting (2003) 7th European Conference on Principles and Practice of Knowledge Discovery in Databases (PKDD), pp. 107-119; Domingos, P., MetaCost: A general method for making classifiers cost-sensitive (1999) Conference on Knowledge Discovery in Data Proceedings of the Fifth ACM SIGKDD International Conference on Knowledge Discovery and Data Mining, pp. 155-164; Fan, W., Stolfo, S., Zhang, J., Chan, P., Adacost: Misclassication cost-sensitive boosting (1999) Proceedings of Sixteenth International Conference on Machine Learning, pp. 983-990; Tax, D.M.J., One-class classification; Concept-learning in the absence of counterexamples (2001) ASCI Dissertation Series, 65, pp. 1-190. , PhD thesis Delft University of Technology; Ridder, D., Tax, D.M.J., Duin, R.P.W., An experimental comparison of one-class classification methods (1998) Proc ASCI'98, 4th Annual Conf of the Advanced School for Computing and Imaging, pp. 213-218. , (Lommel, Belgium, June 9-11), ASCI, Delft; Lazarevic, A., Ertoz, L., Ozgur, A., Srivastava, J., Kumar, V., A comparative study of anomaly detection schemes in network intrusion detection (2003) Proceedings of Third SIAM Conference on Data Mining, , San Francisco; Weiss, G.M., Mining with rarity: A unifying framework (2004) Sigkdd Explorations, 6 (1), pp. 7-19; Lewis, D.D., Gale, W.A., A sequential algorithm for training text classifiers (1994) Proceedings of International ACM Conference on Research and Development in Information Retrieval, pp. 3-12; Visa, S., Ralescu, A., Learning imbalanced and overlapping classes using fuzzy sets (2003) Workshop on Learning from Imbalanced Datasets II, , ICML, Washington DC; Sousa, A.V., Aguiar, R., Mendonça, A.M., Campilho, A., Automatic lane and band detection in images of thin layer chromatography (2004) LNCS, 3212. , Springer; Sousa, A.V., Mendonça, A.M., Campilho, A., Aguiar, R., Miranda, C.S., Feature extraction for classification of thin-layer chromatography images (2005) LNCS, 3656. , Springer; Japkowicz, N., Learning from imbalanced data sets: A comparison of various strategies (2000) Proceedings of Learning from Imbalanced Data, pp. 10-15; Kubat, M., Holte, R., Matwin, S., Machine learning for the detection of oil spills in satellite radar images (1998) Machine Learning, 30, pp. 195-215; Ha, T., Bunke, H., Off-Line, handwritten numeral recognition by perturbation method (1997) Pattern Analysis and Machine Intelligence, 19 (5), pp. 535-539; Lee, S., Noisy replication in skewed binary classification (2000) Computational Statistics & Data Analysis; Heijden, F., Robert, P.W.D., Ridder, D., Tax, D.M.J., (2004) Classification, Parameter Estimation and State Estimation, , Wiley; Demant, C., Streicher-Abel, B., Waszkewitz, P., (1999) Industrial Image Processing, , Springer-Verlag; Chawla, N.V., Bowyer, K., Hall, L., Kegelmeyer, W., SMOTE: Synthetic minority over-sampling technique (2002) Jounal of Artificial Intelligence Research, 16, pp. 321-357
Keywords: Chromatographic analysis; Class imbalanced problem; Classification (of information); Hierarchical systems; Lysosomal Storage Disorders (LSD); Medical imaging; Multiclassifier system; Problem solving; Thin-Layer Chromatography (TLC) images

Histological and scanning electron microscopy analyses of bone/implant interface using the novel Bonelike® synthetic bone graft - Gutierres, M.; Hussain, N.S.; Lopes, M.A.; Alfonso, A.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Journal of Orthopaedic ResearchJ. Orthop. Res., 2006)
Synthetic bone grafts provide an alternative to autografts and allografts. Bonelike® is a patented synthetic bone graft that mimics the mineral composition of bone. The aim of the present work was to assess the biological behavior of Bonelike® graft in humans, before using the material in orthopedic applications of bone regeneration, for example, in opening wedge high tibial osteotomies for medial knee osteoarthritis. Bonelike® granules were implanted in cortical bone of 11 patients undergoing osteotomies, and new bone formation, osteoconductive properties, and resorption characteristics of the granules were analyzed. The granules ranged from 500 to 1000 μm and were implanted in the lateral aspect of the tibia. The patients' mean age was 59 years (range 48 to 70 years); there were eight women and three men, all suffering from medial compartment osteoarthritis of the knee. At surgery, a 1 × 1 × 1-cm cortical defect was created 3 cm distal to the entry point of the screws, in line with the long axis of tibia. The implanted Bonelike® graft sample was extracted for analysis during removal of the metallic prosthesis after implantation times of 6, 9, and 12 months. Radiological follow-up, scanning electron microscopy, histological analysis, and histomorphometric measurements were conducted on the retrieved samples to assess bone regeneration in the defect area. Osteoconductive capacity was demonstrated by extensive mature bone formation around the implanted granules and high levels of percentage bone-to-graft contact (from 67-84%). Bonelike® acted as an excellent bioactive scaffold, allowing the migration, proliferation, and differentiation of bone cells on its surface, and therefore regeneration of the defects was achieved in a rapid, controlled manner. Our results suggest that Bonelike® graft is an excellent candidate for orthopedic applications where rapid new bone formation is a fundamental requirement. © 2006 Orthopaedic Research Society. Published by Wiley Periodicals, Inc.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JOREDdoi: 10.1002/jor.20117Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; DEMM, Faculty of Engg., University of Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Bone SubstitutesTradenames: Bonelike; JSM 630IF, JeolManufacturers: JeolReferences: Peter, P., Heinrich, R., Meinrad, P., (2003) Orthopaedic Issues in Osteoporosis, , YH An, editor. Boca Raton, FL: CRC Press;Hench, L.L., Wilson, J., (1999) An Introduction to Bioceramics, , Singapore: World Scientific Publishing Co. Pvt. Ltd; Corpe, R.S., Steflik, D.E., Whitehead, R.Y., Correlative experimental animal and human clinical retrieval evaluations (2000) Crit Rev Biomed Eng, 28, pp. 395-398; Kitsugi, T., Yamamuro, T., Nakamura, T., Four calcium phosphate ceramics as bone substitutes for non-weight bearing (1993) Biomaterials, 14, pp. 216-224; Koshino, T., Murase, T., Takagi, T., New bone formation around porous hydroxyapatite wedge implanted in opening wedge high tibial osteotomy in patients with osteoarthritis (2001) Biomaterials, 22, pp. 1579-1582; LeGeros, R.Z., (1991) Calcium Phosphates in Oral Biology and Medicine, pp. 4-45. , Meyers HM, editor. New York: Karger; Macdonald, D.E., Betts, F., Stranick, M., Physicochemical study of plasma-sprayed hydroxyapatite-coated implants in humans (2001) J Biomed Mater Res, 54, pp. 480-490; Oonishi, H., Yamamoto, M., Ishimaru, H., The effect of hydroxyapatite coating on bone growth into porous titanium alloy implants (1989) J Bone Surg Br, 71, pp. 213-216; Thomas, K.A., Hydroxyapatite coatings (1994) Orthopedics, 17, pp. 267-278; Doron, H., Amy, L.L., Bone graft substitutes (2003) Oper Tech Plastic Reconstruct Surg, 9, pp. 151-160; Write, S., The bone-graft market in Europe. Commentary extracted from a report entitled "Emerging technologies in orthopedics I.: Bone graft substitutes, bone growth stimulators and bone growth factors" (1999), pp. 591-595. , London: Datamonitor plcBotelho, C.M., Brooks, R.A., Best, S.M., Biological and physical-chemical characterization of phase pure HA and si-substituted hydroxyapatite by different microscopy techniques (2004) Key Eng Mater, 254, p. 845; Costa, M.A., Gutierres, M., Almeida, L., In vitro mineralisation of human bone marrow cells cultured on bonelike® (2004) Key Eng Mater, 254-256, pp. 821-824; Gutierres, M., Hussain, N.S., Afonso, A., Biological behaviour of bonelike® graft Implanted in the tibia of humans (2005) Key Eng Mater, 284-286, pp. 1041-1044; Lopes, M.A., Santos, J.D., Monteiro, F.J., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: Fracture toughness and hardness dependence on microstructural characteristics (1999) Biomaterials, 20, pp. 2085-2090; Lopes, M.A., Silva, R.F., Monteiro, F.J., Microstructural dependence of Young's and shear moduli of P 2O 5 glass reinforced hydroxyapatite for biomedical applications (2000) Biomaterials, 21, pp. 749-754; Lopes, M.A., Knowles, J.C., Santos, J.D., Structural insights of glass-reinforced hydroxyapatite composites by Rietveld refinement (2000) Biomaterials, 21, pp. 1905-1910; Santos, J.D., Knowles, J.C., Reis, R.L., Microstructural characterization of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Lopes, M.A., Santos, J.D., Monteiro, F.J., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Felson, D.T., Naimark, A., Anderson, J., The prevalence of knee osteoarthritis in the elderly: The Framingham Study (1987) Arthritis Rheum, 30, pp. 914-918; Guincamp, C., Pap, T., Schedel, J., Gene therapy in osteoarthritis (2000) Joint Bone Spine, 67, pp. 570-571; Marc, F., Serge, P., Mario, M.L.C., Assessment of the test-retest reliability and construct validity of a modified lequesne index in knee osteoarthritis (2003) Joint Bone Spine, 70, pp. 520-525; Pendleton, A., Arden, N., Dougados, M., EULAR recommendations for the management of knee osteoarthritis: Report of a task force of the Standing Committee for International Clinical Studies Including Therapeutic Trials (ESCISIT) (2000) Ann Rheum Dis, 59, pp. 936-944; Santos, J.D., Hastings, G.W., Knowles, J.C., Sintered hydroxyapatite compositions and method for the preparation thereof (1999) Eur. Pat. WO 0068164; Coventry, M.B., Osteotomy of the upper portion of the tibia for degenerative arthritis of the knee: A preliminary report (1965) J Bone Joint Surg Am, 47, p. 984; Hing, K.A., Assessment of porous hydroxyapatite for bone replacement (1996), (Ph D Thesis). London: University of LondonLopes, M.A., Knowles, J.C., Santos, J.D., Direct and indirect effects of P 2O 5-glass reinforced-hydroxyapatite composites and growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Knowles, J.C., Santos, J.D., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Ross, M.H., Romrell, L.J., Kaye, G.I., (1995) Histology - A Text and Atlas, , 3rd ed. Baltimore, MD: Williams & Wilkins; Lobato, J.V., Hussain, N.S., Botelho, C.M., Assessment of the potential of Bonelike® graft for bone regeneration by using an animal model (2005) Key Eng Mater, 284-286, pp. 877-880; Duarte, F., Lopes, M.A., Santos, J.D., Bonelike® composites for the regeneration of bone lesions (2004) Mater Sci Forum, 455-456, pp. 370-373; Laurencin, C.T., (2003) Bone Graft Substitutes, , West Conshohocken, PA: ASTM International
Keywords: adult; aged; article; Bone; Bone and Bones; bone cell; bone conduction; bone development; Bone graft; bone prosthesis; bone radiography; Bone Regeneration; bone screw; Bone Substitutes; bone transplantation; Bonelike®; cell differentiation; cell migration; cell proliferation; Clinical applications; clinical article; controlled study; Female; follow up; Histological analysis; histology; human; Humans; knee osteoarthritis; male; Microscopy, Electron, Scanning; Middle Aged; morphometrics; orthopedics; ossification; Osteoconduction; Osteogenesis; osteolysis; Pathology; priority journal; Prostheses and Implants; prostheses and orthoses; prosthesis material; Scanning electron microscopy; surgical technique; Synthetic bone graft; tibia osteotomy; ultrastructure

An improved management model for tracking multiple features in long image sequences - Pinho, R.R.; Tavares, J.M.R.S.; Correia, M.V. (WSEAS Transactions on Information Science and ApplicationsWSEAS Trans. Inf. Sci. Appl., 2006)
In this paper we present a management model to deal with the problem of tracking a large number of features during long image sequences. Some usual difficulties are related to this problem: features may be temporarily occluded or might even have disappeared definitively; the computational cost involved should always be reduced to the strictly necessary. The proposed Net Present Value (NPV) model, based on the economic Theory of Capital, considers the tracking of each missing feature as an investment. Thus, using the NPV criterion, with adequate receipt and outlay functions, each occluded feature may be kept on tracking or it may be excluded of the tracking process depending on its historical behavior. This methodology may be applied to any tracking system as long as the tracking results may be evaluated in each temporal step. Experimental results, both on synthetic and real image sequences, which validate our model, will be also presented.
Keywords: Computer vision; Costs; Feature extraction; Image sequences; Imaging systems; Management; Management model; Motion estimation; Net Present Value (NPV); Occlusion; Tracking; Tracking (position); Tracking multiple features

Leptin effect on RANKL and OPG expression in MC3T3-E1 osteoblasts - Lamghari, M.; Tavares, L.; Camboa, N.; Barbosa, M.A. (Journal of Cellular BiochemistryJ. Cell. Biochem., 2006)
Recent studies have suggested that leptin hormone may play a pivotal role on bone remodeling through a direct effect by modulating positively the OPG/RANKL balance. Here, we investigate the effect of leptin hormone on RANKL and OPG expression in MC3T3-E1 osteoblasts using RT-PCR and ELISA measurements. We have at first identified the expression of Ob-Rb and Ob-Ra leptin receptor isoforms in MC3T3-E1 and observed that these cells respond to mrleptin treatments. We then investigated the effect of mrleptin on RANKL and OPG expression. We show that mrleptin dose-dependently regulated the expression of RANKL mRNA with complete inhibition observed at concentrations higher than 12 ng/ml. This effect was confirmed with sRANKL protein measurements. However, the exposure of MC3T3-E1 to mrleptin had no effect on OPG mRNA. Taken together, these results suggest that leptin modulates positively OPG/RANKL balance by inhibiting the expression of RANKL gene. © 2006 Wiley-Liss, Inc.
Cited By (since 1996): 17Export Date: 21 November 2012Source: ScopusCODEN: JCEBDdoi: 10.1002/jcb.20853PubMed ID: 16479591Language of Original Document: EnglishCorrespondence Address: Lamghari, M.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua Campo Alegre 823, 4150-180, Porto, Portugal; email: lamghari@ineb.up.ptChemicals/CAS: osteoclast differentiation factor, 200145-93-3; osteoprotegerin, 205944-50-9; Alkaline Phosphatase, EC 3.1.3.1; Carrier Proteins; Glycoproteins; leptin receptor; Leptin; Membrane Glycoproteins; Osteoprotegerin; RANK Ligand; Receptor Activator of Nuclear Factor-kappa B; Receptors, Cell Surface; Receptors, Cytoplasmic and Nuclear; Receptors, Tumor Necrosis Factor; RNA, Messenger; Tnfrsf11a protein, mouse; Tnfrsf11b protein, mouse; Tnfsf11 protein, mouseReferences: Burguera, B., Hofbauer, L.C., Thomas, T., Gori, F., Evans, G.L., Khosla, S., Riggs, B.L., Turner, R.T., Leptin reduces ovariectomy-induced bone loss in rats (2001) Endocrinology, 142, pp. 3546-3553;Cornish, J., Callon, K.E., Bava, U., Lin, C., Naot, D., Hill, B.L., Grey, A.B., Reid, I.R., Leptin directly regulates bone cell function in vitro and reduces bone fragility in vivo (2002) J Endocrinol, 175, pp. 405-415; Ducy, P., Amling, M., Takeda, S., Priemel, M., Schilling, A.F., Beil, F.T., Shen, J., Karsenty, G., Leptin inhibits bone formation through a hypothalamic relay: A central control of bone mass (2000) Cell, 100, pp. 197-207; Elefteriou, F., Ahn, J.D., Takeda, S., Starbuck, M., Yang, X., Liu, X., Kondo, H., Karsenty, G., Leptin regulation of bone resorption by the sympathetic nervous system and CART (2005) Nature, 434, pp. 514-520; Elmquist, J.K., Hypothalamic pathways underlying the endocrine, autonomic, and behavioral effects of leptin (2001) Physiol Behav, 74, pp. 703-708; Gordeladze, J.O., Drevon, C.A., Syversen, U., Reseland, J.E., Leptin stimulates human osteoblastic cell proliferation, de novo collagen synthesis, and mineralization: Impact on differentiation markers, apoptosis, and osteoclastic signaling (2002) J Cell Biochem, 85, pp. 825-836; Holloway, W.R., Collier, F.M., Aitken, C.J., Myers, D.E., Hodge, J.M., Malakellis, M., Gough, T.J., Nicholson, G.C., Leptin inhibits osteoclast generation (2002) J Bone Miner Res, 17, pp. 200-209; Horwood, N.J., Elliott, J., Martin, T.J., Gillespie, M.T., Osteotropic agents regulate the expression of osteoclast differentiation factor and osteoprotegerin in osteoblastic stromal cells (1998) Endocrinology, 139, pp. 4743-4746; Kanematsu, M., Yoshimura, K., Takaoki, M., Sato, A., Vector-averaged gravity regulates gene expression of receptor activator of NF-κB (RANK) ligand and osteoprotegerin in bone marrow stromal cells via cyclic AMP/protein kinase A pathway (2002) Bone, 30, pp. 553-558; Lacely, D.L., Timms, E., Tan, H.L., Dunstan, C.R., Burgess, T., Elliott, R., Colombero, A., Boyle, W.J., Osteoproteferin ligand is a cytokine that regulates osteoclast differentiation and activation (1998) Cell, 93, pp. 165-167; Lee, S.K., Lorenzo, J.A., Parathyroid hormone stimulates TRANCE and inhibits osteoprotegerin messenger ribonucleic acid expression in murine bone marrow cultures: Correlation with osteoclast-like cell formation (1999) Endocrinology, 140, pp. 3552-3561; Lee, S.K., Lorenzo, J.A., Regulation of receptor activator of nuclear factor-κB ligand and osteoprotegerin mRNA expression by parathyroid hormone is predominantly mediated by the protein kinase a pathway in murine bone marrow cultures (2002) Bone, 31, pp. 252-259; Lee, Y.J., Park, J.H., Ju, S.K., You, K.H., Ko, J.S., Kim, H.M., Leptin receptor isoform expression in rat osteoblasts and their functional analysis (2002) FEBS Lett, 528, pp. 43-47; Liu, J., Yang, H., Liu, W., Cao, X., Feng, X., Sp1 and Sp3 regulate the basal transcription of receptor activator of nuclear factor kappa B ligand gene in osteoblasts and bone marrow stromal cells (2005) J Cell Biochem, 96 (4), pp. 716-727; Martin, A., De Vittoris, R., David, V., Moraes, R., Bégeot, M., Lafage-Proust, M.H., Alexandre, C., Thomas, T., Leptin modulates both résorption and formation while preventing disuse-induced bone loss in tail-suspended female rats (2005) Endocrinology, 146, pp. 3652-3659; Nagai, M., Sato, N., Reciprocal gene expression of osteoclastogenesis inhibitory factor and osteoclast differentiation factor regulates osteoclast formation (1999) Biochem Biophys Res Commun, 257, pp. 719-723; Nakajima, R., Inada, H., Koike, T., Yamano, T., Effects of leptin to cultured growth plate chondrocytes (2003) Horm Res, 60 (2), pp. 91-98; Parhami, F., Tintut, Y., Ballard, A., Fogelman, A.M., Demer, L.L., Leptin enhances the calcification of vascular cells: Artery wall as a target of leptin (2001) Circ Res, 88 (9), pp. 954-960; Reseland, J.E., Syversen, U., Bakke, I., Ovigstad, G., Eide, L.G., Hjertner, O., Gordeladze, J.O., Drevon, C.A., Leptin is expressed in and secreted from primary cultures of human osteoblasts and promotes bone mineralization (2001) J Bone Miner Res, 16, pp. 1426-11414; Rubin, J., Ackert-Bicknell, C., Zhu, L., Fan, X., Murphy, T., Nanes, M., Marcus, R., Rosen, C., Insulin like growth factor-I (IGF-I) regulates osteoprotegerin (OPG) and RANK ligand (RANKL) in vitro and osteoprotogerin in vivo (2002) J Clin Endocrinal Metab, 87, pp. 4273-4279; Rubin, J., Murphy, T., Fan, X., Goldschmidt, M., Taylor, W., Mechanical strain inhibits RANKL expression through activation of ERK1/2 in bone marrow stromal cells (2002) J Bone Miner Res, 17, pp. 1452-1460; Simonet, W.S., Lacey, D.L., Dunstan, C.R., Kelley, M., Chang, M.S., Luthy, R., Nguyen, H.Q., Boyle, W.J., Osteoprotegerin: A novel secreted protein involved in the regulation of bone density (1997) Cell, 89, pp. 309-319; Steppan, C.M., Crawford, T., Chidsey-Frink, K.L., Ke, H.Z., Swick, A.G., Leptin is a potent stimulator of bone growth in ob/ob mice (2000) Regul Pept, 92, pp. 73-78; Suda, T., Ueno, Y., Fujii, K., Shinki, T., Vitamin D and bone (2003) J Cell Biochem, 88, pp. 259-266; Thomas, T., Gori, F., Khosla, S., Jensen, M.D., Burguera, B., Riggs, B.L., Leptin acts on human marrow stromal cells to enhance differentiation to osteoblasts and to inhibit differentiation to adipocytes (1999) Endocrinology, 140, pp. 1630-1638; Udagawa, N., Takahashi, N., Yasuda, H., Mizuno, A., Itoh, K., Ueno, Y., Shinki, T., Suda, T., Osteoprotegerin produced by osteoblasts is an important regulator in osteoclast development and function (2000) Endocrinology, 141, pp. 3478-3484; Wamoto, I., Fujino, T., Douchi, T., The leptin receptor in human osteoblasts and the direct effect of leptin on bone metabolism (2004) Gynecol Endocrinol, 19, pp. 97-104; Yasuda, H., Shima, N., Nakagawa, N., Yamaguchi, K., Kinosaki, M., Mochizuki, S., Tomoyasu, A., Suda, T., Osteoclast differentiation factor is a ligand for osteoprotegerin/ osteoclastogenesis-inhibitory factor and is identical to TRANCE/RANKL (1998) Proc Natl Acad Sci USA, 95, pp. 3597-3602
Keywords: alkaline phosphatase; animal cell; Animals; article; bone remodeling; Carrier Proteins; Cell Line; enzyme linked immunosorbent assay; gene expression; gene expression regulation; Glycoproteins; hormone action; leptin; leptin receptor; leptin receptor a; leptin receptor b; MC3T3-E1; Membrane Glycoproteins; messenger RNA; Mice; mouse; nonhuman; Ob-Ra; Ob-Rb; OPG; osteoblast; Osteoblasts; osteoclast differentiation factor; Osteoprotegerin; priority journal; protein expression; RANK Ligand; RANKL; Receptor Activator of Nuclear Factor-kappa B; Receptors, Cell Surface; Receptors, Cytoplasmic and Nuclear; Receptors, Tumor Necrosis Factor; reverse transcription polymerase chain reaction; RNA extraction; RNA, Messenger; unclassified drug

Lung parenchyma segmentation from CT images based on material decomposition - Vinhais, C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2006)
We present a fully automated method for extracting the lung region from volumetric X-ray CT images based on material decomposition. By modeling the human thorax as a composition of different materials, the proposed method follows a threshold-based, hierarchical voxel classification strategy. The segmentation procedure involves the automatic computation of threshold values and consists on three main steps: patient segmentation and decomposition, large airways extraction and lung parenchyma decomposition, and lung region of interest segmentation. Experimental results were performed on thoracic CT images acquired from 30 patients. The method provides a reproducible set of thresholds for accurate extraction of the lung parenchyma, needed for computer aided diagnosis systems. © Springer-Verlag Berlin Heidelberg 2006.
Conference code: 68310Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Vinhais, C.; Instituto de Engenharia Biomédica, Laboratório de Sinal e Imagem Biomédica, Campus da FEUP, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: cav@isep.ipp.ptReferences: Armato, S.G., Giger, M.L., Moran, C.J., Doi, K., MacMahon, H., Computerized detection of lung nodules in computed tomography scans (1998) Proceedings of the 1st International Workshop on Computer-aided Diagnosis, pp. 119-124;Armato III, S.G., Giger, M.L., Morgan, C.J., Blackburn, J.T., Doi, K., MacMahon, H., Computerized detection of pulmonary nodules on CT scans (1999) RadioGraphics, 19 (5), pp. 1303-1311; Brown, M.S., McNitt-Gray, M.F., Goldin, J.G., Suh, R.D., Sayre, J.W., Aberle, D.R., Patient-specific models for lung nodule detection and surveillance in CT images (2001) IEEE Trans. on Medical Imaging, 20 (12), pp. 1242-1250; Gurcan, M.N., Sahiner, B., Petrick, N., Chan, H.-P., Kazerooni, E.A., Cascade, P.N., Hadjiiski, L., Lung nodule detection on thoracic computed tomography images: Preliminary evaluation of a computer-aided diagnosis system (2002) Medical Physics, 29 (11), pp. 2552-2558; Armato III, S.G., Sensakovic, W.F., Automated lung segmentation for thoracic CT: Impact on computer-aided diagnosis (2004) Academic Radiology, 11, pp. 1011-1021; Kemerink, G.J., Lamers, R.J.S., Pellis, B.J., Kruize, H.H., Van Engelshoven, J.M.A., On segmentation of lung parenchyma in quantitative computed tomography of the lung (1998) Medical Physics, 25 (12), pp. 2432-2439; Brown, M.S., McNitt-Gray, M.F., Goldin, J.G., Greaser, L.E., Aberle, D.R., Knowledge-based method for segmentation and quantitative analysis of lung function from CT (1998) Proceedings of the 1st International Workshop on Computer-aided Diagnosis, pp. 113-118; Leader, J.K., Zheng, B., Rogers, R.M., Sciurba, F.C., Perez, A., Chapman, B.E., Patel, S., Gur, D., Automated lung segmentation in X-ray computed tomography: Development and evaluation of a heuristic threshold-based scheme (2003) Academic Radiology, 10, pp. 1224-1236; Hu, S., Hoffman, E.A., Reinhardt, J.M., Automatic lung segmentation for accurate quantitation of volumetric X-ray CT images (2001) IEEE Trans. on Medical Imaging, 20 (6), pp. 490-498; Alvarez, R.E., Macovsky, A., Energy-selective reconstruction in X-ray computerized tomography (1976) Phys. Med. Biol., 21, pp. 733-744; Lehmann, L.A., Alvarez, R.E., Macovski, A., Brody, W.R., Generalized image combinations in dual KVP digital radiography (1981) Medical Physics, 8 (5), pp. 659-667; Macovsky, A., (1983) Medical Imaging Systems, , Information and Systems Science Series, Prentice Hall, Inc; Tissue substitutes in radiation dosimetry and measurement (1989) Report 44 of the International Commission on Radiation Units and Measurements, , Bethesda, MD; Berger, M.J., Hubbell, J.H., XCOM: Photon cross sections on a personal computer (1987) NBSIR, 87 (3597); Boone, J.M., Seibert, J.A., An accurate method for computer-generating tungsten anode x-ray spectra from 30 to 140 kV (1997) Medical Physics, 24 (11), pp. 1661-1670; Rijsbergen, C.J.V., (1979) Information Retrieval, , London, Butterworths, 2nd ed
Keywords: Biological organs; Classification (of information); Computer simulation; Computerized tomography; Image segmentation; Lung parenchyma; Medical imaging; Patient segmentation; Patient treatment; Volumetric X-ray CT images; Voxel classification strategy

A multiclassifier approach for lung nodule classification - Pereira, C.S.; Alexandre, L.A.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2006)
The aim of this paper is to examine a multiclassifier approach to the classification of the lung nodules in X-ray chest radiographs. The approach investigated here is based on an image region-based classification whose output is the information of the presence or absence of a nodule in an image region. The classification was made, essentially, in two steps: firstly, a set of rotation invariant features was extracted from the responses of a multi-scale and multi-orientation filter bank; secondly, different classifiers (multi-layer perceptrons) are designed using different features sets and trained in different data. These classifiers are further combined in order to improve the classification performance. The obtained results are promising and can be used for reducing the false-positives nodules detected in a computer-aided diagnosis system. © Springer-Verlag Berlin Heidelberg 2006.
Conference code: 68310Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Pereira, C.S.; Instituto de Engenharia Biomédica, Rua Roberto Frias, 4200-465 Porto, Portugal; email: cpereira@estgl.ipv.ptReferences: Jemal, A., Murray, T., Ward, E., Samuels, A., Tiwari, R.C., Ghafoor, A., Feuer, E.J., Thun, M.J., (2005) Cancer Statistics, 2005, 55, pp. 10-30. , CA Cancer J Clin;Keserci, B., Yoshida, H., Computerized detection of pulmonary nodules in chest radiographs based on morphological features and wavelet snake model (2002) Medical Image Analysis, 6, pp. 431-447; Van Ginneken, B., Romeny, B.M.H., Viergever, M.A., Computer-aided diagnosis in chest radiography: A survey (2001) IEEE Transactions on Medical Imaging, 20 (12), pp. 1228-1241; Wei, J., Hagihara, Y., Shimizu, A., Kobatake, H., Optimal image feature set for detecting lung nodules on chest X-ray images (2002) CARS 2002; Van Ginneken, B., Katsuragawa, S., Ter Haar Romeny, B.M., Kunio, D., Viergever, M.A., Automatic detection of abnormalities in chest radiographs using local texture analysis (2002) IEEE Transactions on Medical Imaging, 21, pp. 139-149; Schilham, A.M.R., Van Ginneken, B., Loog, M., Multi-scale nodule detection in chest radiographs (2003) Lecture Notes in Computer Science, LNCS 2878, pp. 602-609; Shiraishi, J., Katsuragawa, S., Ikezoe, J., Matsumoto, T., Kobayashi, T., Matsu, K.-I.K., Matsui, M., Doi, K., Development of a digital image database for chest radiographs with and without a lung nodule: Receiver operating characteristic analysis of radiologists' detection of pulmonary nodules (2000) American Journal of Roentgenology, 174, pp. 71-74; Yoshida, H., Local contralateral subtraction based on bilateral symmetry of lung for reduction of false positives in computerized detection of pulmonary nodules (2004) IEEE Transactions on Biomedical Engineering, 51, pp. 778-789; Suzuki, K., Shiraishi, J., Abe, H., MacMahon, H., Doi, K., False-positive reduction in computer-aided diagnostic scheme for detecting nodules in chest radiographs by means of massive training artificial neural network (2005) Academic Radiology, 12, pp. 191-201; Randen, T., Husoy, J.H., Filtering for texture classification: A comparative study (1999) IEEE Transactions on Pattern Analysis and Machine Intelligence, 21 (4); Grigorescu, S.E., Petkov, N., Kruizinga, P., Comparison of texture features based on Gabor filters (2002) IEEE Transactions on Image Processing, 11 (10), pp. 195-203; Kumar, A., Pang, G.K.H., Defect detection in textured materials using Gabor filters (2002) IEEE Transactions on Industry Applications, 38 (2); Varma, M., Zisserman, A., Unifying statistical texture classification frameworks (2004) Image and Vision Computing, 22, pp. 1175-1183; Leung, T., Malik, J., Representing and recognizing the visual appearance of materials using three-dimensional textons (2001) International Journal of Computer Vision, 43, pp. 29-44; Alexandre, L.A., Campilho, A.C., Kamel, M., On combining classifiers using sum and product rules (2001) Pattern Recognition Letters, 22, pp. 1283-1289
Keywords: Biological organs; Classification (of information); Computer aided diagnosis; False-positives nodules; Medical imaging; Multi-orientation filter bank; Radiography; X rays; X-ray chest radiographs

The N-terminal half of the peroxisomal cycling receptor Pex5p is a natively unfolded domain - Carvalho, A.F.; Costa-Rodrigues, J.; Correia, I.; Costa Pessoa, J.; Faria, T.Q.; Martins, C.L.; Fransen, M.; Sá-Miranda, C.; Azevedo, J.E. (Journal of Molecular BiologyJ. Mol. Biol., 2006)
Targeting of most newly synthesised peroxisomal matrix proteins to the organelle requires Pex5p, the so-called PTS1 receptor. According to current models of peroxisomal biogenesis, Pex5p interacts with these proteins in the cytosol, transports them to the peroxisomal membrane and catalyses their translocation across the membrane. Presently, our knowledge on the structural details behind the interaction of Pex5p with the cargo proteins is reasonably complete. In contrast, information regarding the structure of the Pex5p N-terminal half (a region containing its peroxisomal targeting domain) is still limited. We have recently observed that the Stokes radius of this Pex5p domain is anomalously large, suggesting that this portion of the protein is either a structured elongated domain or that it adopts a low compactness conformation. Here, we address this issue using a combination of biophysical and biochemical approaches. Our results indicate that the N-terminal half of Pex5p is best described as a natively unfolded pre-molten globule-like domain. The implications of these findings on the mechanism of protein import into the peroxisome are discussed. © 2005 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 34Export Date: 21 November 2012Source: ScopusCODEN: JMOBAdoi: 10.1016/j.jmb.2005.12.002PubMed ID: 16403517Language of Original Document: EnglishCorrespondence Address: Azevedo, J.E.; Instituto de Biologia Molecular e Celular, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jazevedo@ibmc.up.ptChemicals/CAS: Amino Acids; peroxisome-targeting signal 1 receptor; Receptors, Cytoplasmic and NuclearReferences: Brown, L.A., Baker, A., Peroxisome biogenesis and the role of protein import (2003) J. Cell. Mol. Med., 7, pp. 388-400;Heiland, I., Erdmann, R., Biogenesis of peroxisomes. Topogenesis of the peroxisomal membrane and matrix proteins (2005) FEBS J., 272, pp. 2362-2372; Lazarow, P.B., Peroxisome biogenesis: Advances and conundrums (2003) Curr. Opin. Cell Biol., 15, pp. 489-497; Moyersoen, J., Choe, J., Fan, E., Hol, W.G., Michels, P.A., Biogenesis of peroxisomes and glycosomes: Trypanosomatid glycosome assembly is a promising new drug target (2004) FEMS Microbiol. Rev., 28, pp. 603-643; Weller, S., Gould, S.J., Valle, D., Peroxisome biogenesis disorders (2003) Annu. Rev. Genomics Hum. Genet., 4, pp. 165-211; Gould, S.J., Keller, G.A., Hosken, N., Wilkinson, J., Subramani, S., A conserved tripeptide sorts proteins to peroxisomes (1989) J. Cell Biol., 108, pp. 1657-1664; Klein, A.T., Barnett, P., Bottger, G., Konings, D., Tabak, H.F., Distel, B., Recognition of peroxisomal targeting signal type 1 by the import receptor Pex5p (2001) J. Biol. Chem., 276, pp. 15034-15041; Lametschwandtner, G., Brocard, C., Fransen, M., Van Veldhoven, P., Berger, J., Hartig, A., The difference in recognition of terminal tripeptides as peroxisomal targeting signal 1 between yeast and human is due to different affinities of their receptor Pex5p to the cognate signal and to residues adjacent to it (1998) J. Biol. Chem., 273, pp. 33635-33643; Brocard, C., Kragler, F., Simon, M.M., Schuster, T., Hartig, A., The tetratricopeptide repeat-domain of the PAS10 protein of Saccharomyces cerevisiae is essential for binding the peroxisomal targeting signal-SKL (1994) Biochem. Biophys. Res. Commun., 204, pp. 1016-1022; Dodt, G., Braverman, N., Wong, C., Moser, A., Moser, H.W., Watkins, P., Mutations in the PTS1 receptor gene, PXR1, define complementation group 2 of the peroxisome biogenesis disorders (1995) Nature Genet., 9, pp. 115-125; Fransen, M., Brees, C., Baumgart, E., Vanhooren, J.C., Baes, M., Mannaerts, G.P., Van Veldhoven, P.P., Identification and characterization of the putative human peroxisomal C-terminal targeting signal import receptor (1995) J. Biol. Chem., 270, pp. 7731-7736; Gatto Jr., G.J., Geisbrecht, B.V., Gould, S.J., Berg, J.M., A proposed model for the PEX5-peroxisomal targeting signal-1 recognition complex (2000) Proteins: Struct. Funct. Genet., 38, pp. 241-246; Otera, H., Setoguchi, K., Hamasaki, M., Kumashiro, T., Shimizu, N., Fujiki, Y., Peroxisomal targeting signal receptor Pex5p interacts with cargoes and import machinery components in a spatiotemporally differentiated manner: Conserved Pex5p WXXXF/Y motifs are critical for matrix protein import (2002) Mol. Cell. Biol., 22, pp. 1639-1655; Terlecky, S.R., Nuttley, W.M., McCollum, D., Sock, E., Subramani, S., The Pichia pastoris peroxisomal protein PAS8p is the receptor for the C-terminal tripeptide peroxisomal targeting signal (1995) EMBO J., 14, pp. 3627-3634; Gatto Jr., G.J., Geisbrecht, B.V., Gould, S.J., Berg, J.M., Peroxisomal targeting signal-1 recognition by the TPR domains of human PEX5 (2000) Nature Struct. Biol., 7, pp. 1091-1095; Agne, B., Meindl, N.M., Niederhoff, K., Einwachter, H., Rehling, P., Sickmann, A., Pex8p: An intraperoxisomal organizer of the peroxisomal import machinery (2003) Mol. Cell., 11, pp. 635-646; Albertini, M., Girzalsky, W., Veenhuis, M., Kunau, W.H., Pex12p of Saccharomyces cerevisiae is a component of a multi-protein complex essential for peroxisomal matrix protein import (2001) Eur. J. Cell Biol., 80, pp. 257-270; Reguenga, C., Oliveira, M.E., Gouveia, A.M., Sa-Miranda, C., Azevedo, J.E., Characterization of the mammalian peroxisomal import machinery: Pex2p. Pex5p, Pex12p, and Pex14p are subunits of the same protein assembly (2001) J. Biol. Chem., 276, pp. 29935-29942; Huhse, B., Rehling, P., Albertini, M., Blank, L., Meller, K., Kunau, W.-H., Pex17p of Saccharomyces cerevisiae is a novel peroxin and component of the peroxisomal protein translocation machinery (1998) J. Cell Biol., 140, pp. 49-60; Liu, H., Tan, X., Russell, K.A., Veenhuis, M., Cregg, J.M., PER3, a gene required for peroxisome biogenesis in Pichia pastoris, encodes a peroxisomal membrane protein involved in protein import (1995) J. Biol. Chem., 270, pp. 10940-10951; Rehling, P., Skaletz-Rorowski, A., Girzalsky, W., Voorn-Brouwer, T., Fransen, M.M., Distel, B., Pex8p, an intraperoxisomal peroxin of Saccharomyces cerevisiae required for protein transport into peroxisomes binds the PTS1 receptor pex5p (2000) J. Biol. Chem., 275, pp. 3593-3602; Smith, J.J., Szilard, R.K., Marelli, M., Rachubinski, R.A., The peroxin Pex17p of the yeast Yarrowia lipolytica is associated peripherally with the peroxisomal membrane and is required for the import of a subset of matrix proteins (1997) Mol. Cell. Biol., 17, pp. 2511-2520; Waterham, H.R., Titorenko, V.I., Haima, P., Cregg, J.M., Harder, W., Veenhuis, M., The Hansenula polymorpha PER1 gene is essential for peroxisome biogenesis and encodes a peroxisomal matrix protein with both carboxy- and amino-terminal targeting signals (1994) J. Cell Biol., 127, pp. 737-749; Costa-Rodrigues, J., Carvalho, A.F., Gouveia, A.M., Fransen, M., Sa-Miranda, C., Azevedo, J.E., The N terminus of the peroxisomal cycling receptor, Pex5p, is required for redirecting the peroxisome-associated peroxin back to the cytosol (2004) J. Biol. Chem., 279, pp. 46573-46579; Dodt, G., Gould, S.J., Multiple, P.E.X., Genes are required for proper subcellular distribution and stability of Pex5p, the PTS1 receptor: Evidence that PTS1 protein import is mediated by a cycling receptor (1996) J. Cell Biol., 135, pp. 1763-1774; Gouveia, A.M., Guimaraes, C.P., Oliveira, M.E., Reguenga, C., Sa-Miranda, C., Azevedo, J.E., Characterization of the peroxisomal cycling receptor, Pex5p, using a cell-free in vitro import system (2003) J. Biol. Chem., 278, pp. 226-232; Oliveira, M.E., Gouveia, A.M., Pinto, R.A., Sa-Miranda, C., Azevedo, J.E., The energetics of Pex5p-mediated peroxisomal protein import (2003) J. Biol. Chem., 278, pp. 39483-39488; Glover, J.R., Andrews, D.W., Rachubinski, R.A., Saccharomyces cerevisiae peroxisomal thiolase is imported as a dimer (1994) Proc. Natl Acad. Sci. USA, 91, pp. 10541-10545; McNew, J.A., Goodman, J.M., An oligomeric protein is imported into peroxisomes in vivo (1994) J. Cell Biol., 127, pp. 1245-1257; Stewart, M.Q., Esposito, R.D., Gowani, J., Goodman, J.M., Alcohol oxidase and dihydroxyacetone synthase, the abundant peroxisomal proteins of methylotrophic yeasts, assemble in different cellular compartments (2001) J. Cell Sci., 114, pp. 2863-2868; Walton, P.A., Hill, P.E., Subramani, S., Import of stably folded proteins into peroxisomes (1995) Mol. Biol. Cell, 6, pp. 675-683; Saidowsky, J., Dodt, G., Kirchberg, K., Wegner, A., Nastainczyk, W., Kunau, W.H., Schliebs, W., The di-aromatic pentapeptide repeats of the human peroxisome import receptor PEX5 are separate high affinity binding sites for the peroxisomal membrane protein PEX14 (2001) J. Biol. Chem., 276, pp. 34524-34529; Schliebs, W., Saidowsky, J., Agianian, B., Dodt, G., Herberg, F.W., Kunau, W.H., Recombinant human peroxisomal targeting signal receptor PEX5. Structural basis for interaction of PEX5 with PEX14 (1999) J. Biol. Chem., 274, pp. 5666-5673; Costa-Rodrigues, J., Carvalho, A.F., Fransen, M., Hambruch, E., Schliebs, W., Sa-Miranda, C., Azevedo, J.E., Pex5p, the peroxisomal cycling receptor, is a monomeric non-globular protein (2005) J. Biol. Chem., 280, pp. 24404-24411; Elgersma, Y., Elgersma-Hooisma, M., Wenzel, T., McCaffery, J.M., Farquhar, M.G., Subramani, S., A mobile PTS2 receptor for peroxisomal protein import in Pichia pastoris (1998) J. Cell Biol., 140, pp. 807-820; Rehling, P., Marzioch, M., Niesen, F., Wittke, E., Veenhuis, M., Kunau, W.H., The import receptor for the peroxisomal targeting signal 2 (PTS2) in Saccharomyces cerevisiae is encoded by the PAS7 gene (1996) EMBO J., 15, pp. 2901-2913; Zhang, J.W., Lazarow, P.B., Peb1p (Pas7p) is an intraperoxisomal receptor for the NH2-terminal, type 2, peroxisomal targeting sequence of thiolase: Peb1p itself is targeted to peroxisomes by an NH2-terminal peptide (1996) J. Cell Biol., 132, pp. 325-334; Dodt, G., Warren, D., Becker, E., Rehling, P., Gould, S.J., Domain mapping of human PEX5 reveals functional and structural similarities to Saccharomyces cerevisiae Pex18p and Pex21p (2001) J. Biol. Chem., 276, pp. 41769-41781; Einwachter, H., Sowinski, S., Kunau, W.H., Schliebs, W., Yarrowia lipolytica Pex20p Saccharomyces cerevisiae Pex18p/Pex21p and mammalian Pex5pL fulfil a common function in the early steps of the peroxisomal PTS2 import pathway (2001) EMBO Rep., 2, pp. 1035-1039; Matsumura, T., Otera, H., Fujiki, Y., Disruption of the interaction of the longer isoform of Pex5p, Pex5pL, with Pex7p abolishes peroxisome targeting signal type 2 protein import in mammals. Study with a novel Pex5-impaired Chinese hamster ovary cell mutant (2000) J. Biol. Chem., 275, pp. 21715-21721; Gouveia, A.M., Guimaraes, C.P., Oliveira, M.E., Sa-Miranda, C., Azevedo, J.E., Insertion of Pex5p into the peroxisomal membrane is cargo protein-dependent (2003) J. Biol. Chem., 278, pp. 4389-4392; De La Torre, J.G., Hydrodynamics of segmentally flexible macromolecules (1994) Eur. Biophys. J., 23, pp. 307-322; Denning, D.P., Uversky, V., Patel, S.S., Fink, A.L., Rexach, M., The Saccharomyces cerevisiae nucleoporin Nup2p is a natively unfolded protein (2002) J. Biol. Chem., 277, pp. 33447-33455; Permyakov, S.E., Millett, I.S., Doniach, S., Permyakov, E.A., Uversky, V.N., Natively unfolded C-terminal domain of caldesmon remains substantially unstructured after the effective binding to calmodulin (2003) Proteins: Struct. Funct. Genet., 53, pp. 855-862; Uversky, V.N., Natively unfolded proteins: A point where biology waits for physics (2002) Protein Sci., 11, pp. 739-756; Lydakis-Simantiris, N., Hutchison, R.S., Betts, S.D., Barry, B.A., Yocum, C.F., Manganese stabilizing protein of photosystem II is a thermostable, natively unfolded polypeptide (1999) Biochemistry, 38, pp. 404-414; Sreerama, N., Woody, R.W., Estimation of protein secondary structure from circular dichroism spectra: Comparison of CONTIN, SELCON, and CDSSTR methods with an expanded reference set (2000) Anal. Biochem., 287, pp. 252-260; Stanley, W.A., Sokolova, A., Brown, A., Clarke, D.T., Wilmanns, M., Svergun, D.I., Synergistic use of synchrotron radiation techniques for biological samples in solution: A case study on protein-ligand recognition by the peroxisomal import receptor Pex5p (2004) J. Synchrotron Radiat., 11, pp. 490-496; Oberg, K.A., Fink, A.L., A new attenuated total reflectance Fourier transform infrared spectroscopy method for the study of proteins in solution (1998) Anal. Biochem., 256, pp. 92-106; Navea, S., Tauler, R., De Juan, A., Application of the local regression method interval partial least-squares to the elucidation of protein secondary structure (2005) Anal. Biochem., 336, pp. 231-242; Obradovic, Z., Peng, K., Vucetic, S., Radijovac, P., Dunker, A.K., Exploiting heterogeneous sequence properties improves prediction of protein disorder (2006) Proteins, , In the press; Gould, S.J., Collins, C.S., Opinion: Peroxisomal-protein import: Is it really that complex? (2002) Nature Rev. Mol. Cell. Biol., 3, pp. 382-389; Shoemaker, B.A., Portman, J.J., Wolynes, P.G., Speeding molecular recognition by using the folding funnel: The fly-casting mechanism (2000) Proc. Natl Acad. Sci. USA, 97, pp. 8868-8873; Pontius, B.W., Close encounters: Why unstructured, polymeric domains can increase rates of specific macromolecular association (1993) Trends Biochem. Sci., 18, pp. 181-186; Tompa, P., Intrinsically unstructured proteins (2002) Trends Biochem. Sci., 27, pp. 527-533; Gouveia, A.M., Reguenga, C., Oliveira, M.E., Sa-Miranda, C., Azevedo, J.E., Characterization of peroxisomal Pex5p from rat liver. Pex5p in the Pex5p-Pex14p membrane complex is a transmembrane protein (2000) J. Biol. Chem., 275, pp. 32444-32451; Dammai, V., Subramani, S., The human peroxisomal targeting signal receptor, Pex5p, is translocated into the peroxisomal matrix and recycled to the cytosol (2001) Cell, 105, pp. 187-196; Imanaka, T., Small, G.M., Lazarow, P.B., Translocation of acyl-CoA oxidase into peroxisomes requires ATP hydrolysis but not a membrane potential (1987) J. Cell Biol., 105, pp. 2915-2922; Wendland, M., Subramani, S., Cytosol-dependent peroxisomal protein import in a permeabilized cell system (1993) J. Cell Biol., 120, pp. 675-685; Azevedo, J.E., Costa-Rodrigues, J., Guimaraes, C.P., Oliveira, M.E., Sa-Miranda, C., Protein translocation across the peroxisomal membrane (2004) Cell Biochem. Biophys., 41, pp. 451-468; Wang, D., Visser, N.V., Veenhuis, M., Van Der Klei, I.J., Physical interactions of the peroxisomal targeting signal 1 receptor pex5p, studied by fluorescence correlation spectroscopy (2003) J. Biol. Chem., 278, pp. 43340-43345; Oliveira, M.E., Reguenga, C., Gouveia, A.M., Guimaraes, C.P., Schliebs, W., Kunau, W.H., Mammalian Pex14p: Membrane topology and characterisation of the Pex14p-Pex14p interaction (2002) Biochim. Biophys. Acta, 1567, pp. 13-22; Fransen, M., Wylin, T., Brees, C., Mannaerts, G.P., Van Veldhoven, P.P., Human pex19p binds peroxisomal integral membrane proteins at regions distinct from their sorting sequences (2001) Mol. Cell. Biol., 21, pp. 4413-4424; Sreerama, N., Venyaminov, S.Y., Woody, R.W., Estimation of protein secondary structure from circular dichroism spectra: Inclusion of denatured proteins with native proteins in the analysis (2000) Anal. Biochem., 287, pp. 243-251; Vigano, C., Margolles, A., Van Veen, H.W., Konings, W.N., Ruysschaert, J.M., Secondary and tertiary structure changes of reconstituted LmrA induced by nucleotide binding or hydrolysis. a Fourier transform attenuated total reflection infrared spectroscopy and tryptophan fluorescence quenching analysis (2000) J. Biol. Chem., 275, pp. 10962-10967; Laurent, T.C., Killander, J., Theory of gel filtration + its experimental verification (1964) J. Chromatog., 14, pp. 217-230;
Keywords: Amino acids; amino terminal sequence; article; biogenesis; Calorimetry, Differential Scanning; cell membrane; cell receptor; Chromatography, Gel; circular dichroism; cytosol; differential scanning calorimetry; human; Humans; infrared spectroscopy; matrix protein; Natively unfolded; Peroxisomal protein import; peroxisome; Pex5p; priority journal; Protein conformation; protein degradation; protein domain; protein folding; protein interaction; protein Pex5p; protein structure; Protein Structure, Secondary; Protein Structure, Tertiary; protein transport; pts1 receptor; PTS1-receptor; Receptors, Cytoplasmic and Nuclear; Spectroscopy, Fourier Transform Infrared; unclassified drug

Time-lapse analysis of stem-cell divisions in the Arabidopsis thaliana root meristem - Campilho, A.; Garcia, B.; Toorn, H.V.D.; Wijk, H.V.; Campilho, A.; Scheres, B. (Plant JournalPlant J., 2006)
In the Arabidopsis root, asymmetric stem-cell divisions produce daughters that form the different root cell types. Here we report the establishment of a confocal tracking system that allows the analysis of numbers and orientations of cell divisions in root stem cells. The system provides direct evidence that stem cells have lower division rates than cells in the proximal meristem. It also allows tracking of cell division timing, which we have used to analyse the synchronization of root cap divisions. Finally, it gives new insights into lateral root cap formation: epidermal stem-cell daughters can rotate the orientation of the division plane like the stem cell. © 2006 The Authors.
Cited By (since 1996): 33Export Date: 21 November 2012Source: ScopusCODEN: PLJUEdoi: 10.1111/j.1365-313X.2006.02892.xPubMed ID: 17087761Language of Original Document: EnglishCorrespondence Address: Scheres, B.; Department of Molecular Genetics, University of Utrecht, Utrecht, Netherlands; email: b.scheres@bio.uu.nlReferences: Aida, M., Beis, D., Heidstra, R., Willemsen, V., Blilou, I., Galinha, C., Nussaume, L., Scheres, B., The PLETHORA genes mediate patterning of the Arabidopsis root stem cell niche (2004) Cell, 119, pp. 109-120;Baskin, T.I., On the constancy of cell-division rate in the root meristem (2000) Plant Mol. Biol., 43, pp. 545-554; Van Den Berg, C., Willemsen, V., Hendriks, G., Weisbeek, P., Scheres, B., Short-range control of cell differentiation in the Arabidopsis root meristem (1997) Nature, 390, pp. 287-289; Van Den Berg, C., Hage, W., Weisbeek, P., Scheres, B., Laser ablation in Arabidopsis roots: A tool to study cell-to-cell communication (1998) NATO ASI Ser., H104, pp. 237-250; Boisnard-Lorig, C., Colon-Carmona, A., Bauch, M., Hodge, S., Doerner, P., Bancharel, E., Dumas, C., Berger, F., Dynamic analyses of the expression of the HISTONE::YFP fusion protein in Arabidopsis show that syncytial endosperm is divided in mitotic domains (2001) Plant Cell, 13, pp. 495-509; Buvat, R., Structure, evolution et functionnement du méristèm apical de quelques dicotylédones (1952) Ann. Sci. Nat. Bot. Ser., 13, pp. 199-300; Clough, S.J., Bent, A.F., Floral dip: A simplified method for Agrobacterium-mediated transformation of Arabidopsis thaliana (1998) Plant J., 16, pp. 735-743; Clowes, F.A.L., Nucleic acids in root apical meristems of Zea (1956) New Phytol., 55, pp. 29-34; Cutler, S.R., Ehrhardt, D.W., Griffitts, J.S., Somerville, C.R., Random GFP::cDNA fusions enable visualization of subcellular structures in cells of Arabidopsis at a high frequency (2000) Proc. Natl Acad. Sci. USA, 97, pp. 3718-3723; Dolan, L., Janmaat, K., Willemsen, V., Linstead, P., Poethig, S., Roberts, K., Scheres, B., Cellular organization of the Arabidopsis thaliana root (1993) Development, 119, pp. 71-84; Dolan, L., Duckett, C.M., Grierson, C., Linstead, P., Schneider, K., Lawson, E., Dean, C., Roberts, K., Clonal relationships and cell patterning in the root epidermis of Arabidopsis (1994) Development, 120, pp. 2465-2474; Dolznig, H., Grebien, F., Sauer, T., Beug, H., Mullner, E.W., Evidence for a size-sensing mechanism in animal cells (2004) Nat. Cell Biol., 6, pp. 899-905; Furner, I.J., Pumfrey, J.E., Cell fate in the shoot apical meristem of Arabidopsis thaliana (1992) Development, 115, pp. 755-764; Garcia, B., Campilho, A., Scheres, B., Campilho, A., Automatic tracking of Arabidopsis thaliana root meristem in confocal microscopy (2004) ICIAR 2004 LNCS 3212, pp. 166-174. , (Campilho, A. and Kamel, M., eds). New York, Springer Verlag; Irish, V.F., Sussex, I.M., A fate map of the Arabidopsis embryonic shoot apical meristem (1992) Development, 115, pp. 745-753; Jorgensen, P., Nishikawa, J., Breitkreutz, B.J., Tyers, M., Systematic identification of pathways that couple cell growth and division in yeast (2002) Science, 297, pp. 395-400; Nance, J., Priess, J.R., Cell polarity and gastrulation in C. elegans (2002) Development, 129, pp. 387-397; O'Connell, K.F., Leys, C.M., White, J.G., A genetic screen for temperature-sensitive cell-division mutants of Caenorhabditis elegans (1998) Genetics, 149, pp. 1303-1321; Otsu, N., A threshold selection method from gray level histograms (1979) IEEE Trans. Syst. Man. Cybernet., 9, pp. 62-66; Perona, P., Malik, J., Scale space and edge detection using anisotropic diffusion (1990) IEEE Trans. Pattern Anal. Mach. Intel., 12, pp. 629-639; Reddy, G.V., Heisler, M.G., Ehrhardt, D.W., Meyerowitz, E.M., Real-time lineage analysis reveals oriented cell divisions associated with morphogenesis at the shoot apex of Arabidopsis thaliana (2004) Development, 131, pp. 4225-4237; Sabatini, S., Heidstra, R., Wildwater, M., Scheres, B., SCARECROW is involved in positioning the stem cell niche in the Arabidopsis root meristem (2003) Genes Dev., 17, pp. 354-358; Scheres, B., Wolkenfelt, H., Willemsen, V., Terlouw, M., Lawson, E., Dean, C., Weisbeek, P., Embryonic origin of the Arabidopsis primary root and root meristem initials (1994) Development, 120, pp. 2475-2487; Sulston, J.E., Schierenberg, E., White, J.G., Thomson, J.N., The embryonic cell lineage of the nematode Caenorhabditis elegans (1983) Dev. Biol., 100, pp. 64-119; Thomas, C., Devries, P., Hardin, J., White, J., Four-dimensional imaging: Computer visualization of 3D movements in living specimens (1996) Science, 273, pp. 603-607; Watt, F., Hogan, B., Out of Eden: Stem cells and their niches (2000) Science, 287, pp. 1427-1430; Wildwater, M., Campilho, A., Perez-Perez, J.M., Heidstra, R., Blilou, I., Korthout, H., Chatterjee, J., Scheres, B., The RETINOBLASTOMA-RELATED gene regulates stem cell maintenance in Arabidopsis (2005) Cell, 123, pp. 1337-1349
Keywords: Arabidopsis; Arabidopsis thaliana; article; cell cycle; Cell Division; Cells; cytology; Development; Growth; Growth kinetics; Image analysis; meristem; Photoperiod; photoperiodicity; Plant; plant root; Plant roots; Plants; Plants (botany); Real-time; stem cell; Stem cells; Stem-cell daughters; time; Time Factors

Biocatalytic synthesis of highly ordered degradable dextran-based hydrogels - Ferreira, L.; Gil, M.H.; Cabrita, A.M.S.; Dordick, J.S. (BiomaterialsBiomaterials, 2005)
We have prepared unique macroporous and ordered dextran-based hydrogels using a single-step biocatalytic transesterification reaction between dextran and divinyladipate in neat dimethylsulfoxide. These hydrogels show a unimodal distribution of interconnected pores with average diameters from 0.4 to 2.0 μm depending on the degree of substitution. In addition, the hydrogels show a higher elastic modulus for a given swelling ratio than chemically synthesized dextran-based hydrogels. In vivo studies in rats show that the hydrogel networks are degradable over a range of time scales from 5 to over 40 days, and possess good biocompatibility, as reflected in only a mild inflammatory reaction and minor fibrous capsule formation during the time-frame of subcutaneous implantation. These combined properties may offer competitive advantages in biomedical applications ranging from tissue engineering to controlled drug delivery. © 2004 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 29Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2004.11.051PubMed ID: 15763250Language of Original Document: EnglishCorrespondence Address: Dordick, J.S.; Dept. of Chem. and Biol. Engineering, Rensselaer Polytechnic Institute, 102 Ricketts Bldg., Troy, NY 12180, United States; email: dordick@rpi.eduChemicals/CAS: dextran, 87915-38-6, 9014-78-2; dimethyl sulfoxide, 67-68-5; Biocompatible Materials; Dextrans, 9004-54-0; Hydrogels; Peptide Hydrolases, EC 3.4.-Manufacturers: Fluka, SwitzerlandReferences: Lee, K.Y., Peters, M.C., Anderson, K.W., Mooney, D.J., Controlled growth factor release from synthetic extracellular matrices (2000) Nature, 408, pp. 998-1000;Zhu, G., Mallery, S.R., Schwendeman, S.P., Stabilization of proteins encapsulated in injectable poly(lactide-co- glycolide) (2000) Nature Biotechnol, 18, pp. 52-57; Shea, L.D., Smiley, E., Bonadio, J., Mooney, D.J., DNA delivery from polymer matrices for tissue engineering (1999) Nature Biotechnol, 17, pp. 551-554; Griffith, L.G., Naughton, G., Tissue engineering-current challenges and expanding opportunities (2002) Science, 295, pp. 1009-1014; Lee, K.Y., Mooney, D.J., Hydrogels for tissue engineering (2001) Chem Rev, 101, pp. 1869-1879; Wong, W.H., Mooney, D.J., Synthesis and properties of biodegradable polymers used as synthetic matrices for tissue engineering (1997) Synthetic Biodegradable Polymer Scaffolds, pp. 49-82. , A. Atala D.J. Mooney Birkhäuser Boston; Holmes, T.C., Novel peptide-based biomaterial scaffolds for tissue engineering (2002) TIBTECH, 20, pp. 16-21; Mehvar, R., Dextrans for targeted and sustained delivery of therapeutic and imaging agents (2000) J Control Rel, 69, pp. 1-25; Kim, S.-H., Chu, C.-C., Synthesis and characterization of dextran-methacrylate hydrogels and structural study by SEM (2000) J Biomed Mater Res, 49, pp. 517-527; Kim, S.-H., Chu, C.-C., Pore structure analysis of swollen dextran-methacrylate hydrogels by SEM and mercury intrusion porosimetry (2000) J Biomed Mater Res (Appl Biomater), 53, pp. 258-266; Meyvis, T., De Smedt, S., Stubbe, B., Hennink, W., Demeester, J., On the release of proteins from degrading dextran methacrylate hydrogels and the correlation with the rheologic properties of the hydrogels (2001) Pharm Res, 18, pp. 1593-1599; Patil, N.S., Dordick, J.S., Rethwisch, D.G., Macroporous poly(sucrose acrylate) hydrogel for controlled release of macromolecules (1996) Biomaterials, 17, pp. 2343-2350; Park, H., Park, K., Biocompatibility issues of implantable drug delivery systems (1996) Pharm Res, 13, pp. 1770-1776; Loebsack, A., Greene, K., Wyatt, S., Culberson, C., Austin, C., Beiter, R., Roland, W., Halberstadt, C., In vivo characterization of a porous hydrogel material for use as a tissue bulking agent (2001) J Biomed Mater Res, 57, pp. 575-581; Cadée, J.A., Luyn, M.J.A., Brouwer, L.A., Plantinga, J.A., Van Wachem, P.B., Groot, C.J., Otter, W., Hennink, W.E., In vivo biocompatibility of dextran-based hydrogels (2000) J Biomed Mater Res, 50, pp. 397-404; Ferreira, L., Gil, M.H., Dordick, J.S., Enzymatic synthesis of dextran-containing hydrogels (2002) Biomaterials, 23, pp. 3957-3967; Washburn, E.W., Note on a method of determining the distribution of pore sizes in a porous material (1921) Proc Natl Acad Sci, 7, pp. 115-116; Brancroft, J.D., Stevens, A., (1996) Theory and Practice of Histological Techniques, , Churchill Livingstone Edinburgh; Martin, B.D., Linhardt, R.J., Dordick, J.S., Highly swelling hydrogels from ordered galactose-based polyacrylates (1998) Biomaterials, 19, pp. 69-76; Ferreira, L., Ramos, M.A., Gil, M.H., Dordick, J.S., Exquisite regioselectivity and transesterification activity enhancement of an immobilized Bacillus subtilis protease (2002) Biotechnol Prog, 18, pp. 986-993; Ferreira, L., Gil, M.H., Carvalho, R., Geraldes, C.F.G.C., Kim -., D.Y., Dordick, J.S., Biocatalytic polytransesterification of inulin with divinyladipate (2002) Chem Mater, 14, pp. 4009-4011; Zaks, A., Klibanov, A.M., Enzymatic catalysis in nonaqueous solvents (1988) J Biol Chem, 263, pp. 3194-3201; Almarsson, Ö., Klibanov, A.M., Remarkable activation of enzymes in nonaqueous media by denaturing organic cosolvents (1996) Biotechnol Bioeng, 49, pp. 87-92; Brøndsted, H., Hovgaard, L., Simonsen, L., Dextran hydrogels for colon-specific drug delivery II. Synthesis and characterization (1996) Eur J Pharm Biopharm, 42, pp. 85-89; De Smedt, S.C., Lauwers, A., Demeester, J., Van Steenbergen, M.J., Hennink, W.E., Roefs, S.P.F.M., Characterization of the network structure of dextran glycidyl methacrylate hydrogels by studying the rheological and swelling behavior (1995) Macromolecules, 28, pp. 5082-5088; Dziubla, I.D., Torjman, M.C., Joseph, J.I., Murphy-Tatum, M., Lowman, A.M., Evaluation of porous networks of poly(2-hydroxyethylmethacrylate) as interfacial drug delivery devices (2001) Biomaterials, 22, pp. 2893-2899; Kuijpers, A.J., Wachem, P.B., Luyn, M.J.A., Plantinga, J.A., Engbers, G.H.M., Krijgsveld, J., Zaat, S.A.J., Feijen, J., In vivo compatibility and degradation of crosslinked gelatin gels incorporated in knitted Dacron (2000) J Biomed Mater Res, 51, pp. 136-145; Suggs, L.J., Krishnan, R.S., Garcia, C.A., Peter, S.J., Anderson, J.M., Mikos, A.G., In vitro and in vivo degradation of poly(propylene fumarate-co-ethylene glycol) hydrogels (1998) J Biomed Mater Res, 42, pp. 312-320; Ferreira, L., Rafael, A., Lamghari, M., Barbosa, M.A., Gil, M.H., Cabrita, A.M.S., Dordick, J.S., Biocompatibility of chemoenzymatically derived dextran-acrylate hydrogels (2004) J Biomed Mater Res, 68, pp. 584-596; Van Dijk-Wolthuis, W.N.E., Hoogeboom, J.A.M., Van Steenbergen, M.J., Tsang, S.K.Y., Hennink, W.E., Degradation and release behavior of dextran-based hydrogels (1997) Macromolecules, 30, pp. 4639-4645
Keywords: Absorbable Implants; adipic acid derivative; animal experiment; animal tissue; Animals; article; Bacillus subtilis; Biocatalysts; Biocompatibility; Biocompatible Materials; Biodegradation; Biomedical engineering; biosynthesis; catalysis; Controlled drug delivery; controlled study; Cross-linking; dextran; Dextran-based hydrogels; Dextrans; dimethyl sulfoxide; Dimethylsulfoxide; Elastic moduli; Elasticity; Enzyme; Foreign-Body Reaction; hydrogel; Hydrogels; implantation; in vivo study; Inflammation; male; materials testing; nonhuman; Peptide Hydrolases; porosity; priority journal; rat; Rats; Rats, Wistar; substitution reaction; Sulfur compounds; Surface Properties; Swelling; Swelling ratio; synthesis; Tissue; transesterification; Transesterification reactions

Biological behaviour of Bonelike® graft implanted in the tibia of humans - Gutierres, M.; Hussain, N.S.; Afonso, A.; Almeida, L.; Cabral, T.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2005)
This paper reports the ability of Bonelike® to regenerate bone defected areas when implanted in the tibia of 3 patients (average age of 59 years) during a high tibial osteotomy (HTO) to treat medial compartment osteoarthritis of the knee. Bonelike® is a synthetic bone graft designed to mimic the inorganic composition of bone using a patent process that consists of liquid sintering hydroxyapatite in the presence of CaO-P 2O 5 based glass. The preliminary clinical evaluation performed showed that an intimate contact between new formed bone and Bonelike® was established (67±10%), with no fibrous interface. Therefore, Bonelike® is a single-handedly viable osteoconductive synthetic grafting material as it has been demonstrated from the profiles of radiological, histological and scanning electron microscopy analyses for the six months implantation period.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Gutierres, M.; Faculdade de Medicina da Universidade do Porto, Hospital de São João, Largo Hernâni Monteiro, 4200 Porto, Portugal; email: m.gutierres@clix.ptReferences: Bauer, T.W., Muschler, G.F., Bone Graft Materials. An Overview of the Basic Science (2000) Clin orthop Rel. Res, 371, pp. 10-27;Perry, C.R., Bone Repair Techniques, Bone Graft and Bone Graft Substitutes (1999) Clin Orthop Rel Res, 360, pp. 71-86; Ilan, D.I., Ladd, A.L., Bone graft substitutes (2003) Operative Tech. in plastic and Reconstructive Surgery, 9 (4), pp. 151-160; Santos, J.D., Hastings, G.W., Knowles, J.C., Sintered Hydroxyapatite Compositions and Method for the Preparation Thereof European Patent WO 0068164Lopes, M.A., Glass reinforced hydroxyapatite composites: Structural, Physicochemical characterisation and Biological performance (1999), PhD thesis, FEUP, University of Porto, PortugalCoventry, M.B., Osteotomy of the upper portion of the tibia for degenerative arthritis of the knee: A preliminary report (1965) J. Bone Joint Surg.Am, 47, p. 984; Lopes, M.A., Santos, J.D., (2001) J.Biomed Mat Res, 54, pp. 463-469
Keywords: Biological behavior; Bone; Bonelike® graft; Clinical trials; histology; hydroxyapatite; Implants (surgical); Radiology; Scanning electron microscopy; Surgery; Synthetic grafting material

Feature extraction for classification of thin-layer chromatography images - Sousa, A.V.; Mendonça, A.M.; Campilho, A.; Aguiar, R.; Sá Miranda, C. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2005)
Thin-Layer Chromatography images are used to detect and identify the presence of specific oligosaccharides, expressed by the existence, at different positions, of bands in the gel image. ID gaussian deconvolution, commonly used for band detection, does not produce good results due to the large curvature observed in the bands. To overcome this uncertainty on the band position, we propose a novel feature extraction methodology that allows an accurate modeling of curved bands. The features are used to classify the data into two different classes, to differentiate normal from pathologic cases. The paper presents the developed methodology together with the analysis and discussion of the results. © Springer-Verlag Berlin Heidelberg 2005.
Conference code: 67124Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1007/11559573_118Language of Original Document: EnglishCorrespondence Address: Sousa, A.V.; Instituto de Engenharia Biomédica, Rua Roberto Frias, 4200-465 Porto, Portugal; email: ats@isep.ipp.ptReferences: Bajla, I., Holländer, I., Burg, K., Improvement of electrophoretic gel image analysis (2001) M. S.R, 1 (1);Ye, X., Suen, C., Cheriet, M., Wang, E., A recent development in image analysis of electrophoresis gels (1999) Vision Interface 99, , Canada; Shadle, S., Allen, D., Guo, H., Pogozelski, W., Bashkin, J., Tullius, T., Quantitative analysis of electrophoresis data: Novel curve fitting methodology and its application to the determination of aprotein-DNA binding constant (1997) Nucleic Acids Research, 25 (4); Sousa, A., Aguiar, R., Mendonça, A.M., Campilho, A., Automatic lane and band detection in images of thin layer chromatography (2004) Springer Lecture Notes on Computer Science, LNCS, 3212, pp. 372-380; Heijden, F., Duin, R., Ridder, D., Tax, D., (2004) Classification, Parameter Estimation and State Estimation, , John Wiley and Sons, England; Sewell, A., (1991) Urinary Oligosaccharides. Techniques in Diagnostic Human Biochemical Genetics, pp. 219-231. , Willey-Liss, Inc; Thomas, G., Disorders of Glycoprotein Degradation. α-Mahnosidosis, β-Mannosidosis, Fucosidosis and Sialidosis. Disorders of Glycoprotein Degradation, , Chap. 140; Durant, G., Seta, N., Protein glycosylation and diseases: Blood and urinary oligosaccharides as markers for diagnosis and therapeutic monitoring (2000) Clinical Chemistry, 46 (6), pp. 795-805; Marques De Sá, J., (2003) Applied Statistics Using SPSS, STATISTICA and MATLAD, , Springer Verlag
Keywords: Edge detection; Feature extraction; Image analysis; Image segmentation; Oligosaccharides; Thin layer chromatography; Thin-Layer Chromatography images

Genetic model-based segmentation of chest X-ray images using free form deformations - Vinhais, C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2005)
A method is proposed to segment digital posterior-anterior chest X-ray images. The segmentation is achieved through the registration of a deformable prior model, describing the anatomical structures of interest, to the X-ray image. The deformation of the model is performed using a deformation grid. A coarse matching of the model is done using anatomical landmarks automatically extracted from the image, and maps of oriented edges are used to guide the deformation process, optimized with a probabilistic genetic algorithm. The method is applied to extract the ribcage and delineate the mediastinum and diaphragms. The segmentation is needed for defining the lungs region, used in computer-aided diagnosis systems. © Springer-Verlag Berlin Heidelberg 2005.
Conference code: 67124Export Date: 21 November 2012Source: Scopusdoi: 10.1007/11559573_116Language of Original Document: EnglishCorrespondence Address: Vinhais, C.; INEB - Instituto de Engenharia Biomédica, Laboratório de Sinai e Imagem Biomédica, Campus da FEUP, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: cav@isep.ipp.ptReferences: Carreira, M., Cabello, D., Penedo, M., Mosquera, A., Computer-aided diagnoses: Automatic detection of lung nodules (1998) Medical Physics, 25 (10), pp. 1998-2006;Nakaromi, N., Doi, K., MacMahon, H., Sasaki, Y., Montner, S.M., Effect on heart-size parameters computed from digital chest radiographs on detection of cardiomegaly: Potencial usefulness for computer-aided diagnosis (1991) Inv. Radiology, 26, pp. 546-550; Van Ginneken, B., Romeny, B.H., Viergever, M.A., Computer-aided diagnosis in chest radiography: A survey (2001) IEEE Trans. on Medical Imaging, 20 (12), pp. 1228-1241; Cootes, T.E., Hill, A., Taylor, C.J., Haslam, J., The use of active shape models for locating structures in medical images (1994) Image, and Vision Computing, 12 (6), pp. 355-366; Sederberg, T.W., Parry, S.R., Free-form deformation of solid geometric models (1986) ACM SIGGRAPH Computer Graphics, 20 (4), pp. 151-160; Field, D.J., Relations between the statistics of natural images and the response properties of cortical cells (1987) J. Opt. Soc. Am. A, 4 (12), pp. 2379-2394; Petkov, N., Kruizinga, P., Computational models of visual neurons specialised in the detection of periodic and aperiodic oriented visual stimuli: Bar and grating cells (1997) Biol. Cybern., 76, pp. 83-96; Carpenter, M.B., (1991) Core Text of Neuroanatomy. 4th Ed.; Lotjonen, J., Magnin, I., Nenonen, J., Katila, T., Reconstruction of 3-D geometry using 2-D profiles and a geometric prior model (1999) IEEE Trans. on Medical Imaging, 18 (10), pp. 992-1002; Goldberg, D.E., (1989) Genetic Algorithms in Search, Optimization and Machine Learning; Gofman, Y., Kiryati, N., Detecting symmetry in grey level images: The global Optimization approach (1998) International Journal of Computer Vision (IJCV), 29, pp. 29-45
Keywords: Computer aided analysis; Diaphragms; Feature extraction; Free Form Deformation; Gabor Filters; Genetic Algorithms; Image segmentation; Model-based Image Segmentation; Optimization; Pattern matching; X ray analysis

Neural network classification: Maximizing zero-error density - Silva, L.M.; Alexandre, L.A.; De Sá, J.M. (Lecture Notes in Computer ScienceLect. Notes Comput. Sci., 2005)
We propose a new cost function for neural network classification: the error density at the origin. This method provides a simple objective function that can be easily plugged in the usual backpropagation algorithm, giving a simple and efficient learning scheme. Experimental work shows the effectiveness and superiority of the proposed method when compared to the usual mean square error criteria in four well known datasets. © Springer-Verlag Berlin Heidelberg 2005.
Conference code: 65875Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Silva, L.M.; Instituto de Engenharia Biomédica, Lab. de Sinai e Imagem Biomédica, Campus da FEUP, Rua Dr. Roberto Frias, 4200 - 465 Porto, PortugalReferences: Erdogmus, D., Principe, J.C., An error-entropy minimization algorithm for supervised training of nonlinear adaptive systems (2002) IEEE Transactions on Signal Processing, 50 (7), pp. 1780-1786;Erdogmus, D., Principe, J., Generalized information potential criterion for adaptive system training (2002) IEEE Transactions on Neural Networks, 13 (5), pp. 1035~1044; Santos, J.M., Alexandre, L.A., Marques De Sá, J., The error entropy minimization algorithm for neural network classification (2004) Int. Conf. on Recent Advances in Soft Computing, , Nottingham, United Kingdom; Santos, J.M., Alexandre, L.A., De Sa, J.M., Optimization of the error entropy minimization algorithm for neural network classification (2004) Intelligent Engineering Systems Through Artificial Neural Networks, 14, pp. 81-86. , C. Dagli, A. Buczak, D. Enke, M. Embrechts, and O. Ersoy, editors, ASME Press Series; Silva, L.M., De Sa, J.M., Alexandre, L.A., Neural network classification using shannon's entropy (2005) European Symposium on Artificial Neural Networks; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, 3, pp. 79-87; Blake, C.L., Merz, C.J., (1998) UCI Repository of Machine Learning Databases, , http://www.ics.uci.edu/~mlearn/MLRepository.html, University of California, Irvine, Dept. of Information and Computer Sciences
Keywords: Algorithms; Backpropagation; Backpropagation algorithm; Classification (of information); Costs; Error analysis; Function evaluation; Learning systems; Mean square error; Neural network classification; Neural networks; Zero-error density

Segmentation of ultrasonic images of the carotid - Rocha, R.; Campilho, A.; Silva, J. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2005)
A new algorithm for an effective and automatic segmentation of the carotid wall in ultrasonic images is proposed. It combines the speed of thresholding algorithms with the accuracy, flexibility and robustness of a successful geometric active contour model which incorporates an optimal image segmentation model in a level set framework. Due to the multiphase nature of these images, a sequential minimum cross entropy thresholding is used to get a first approximation of the segments, reducing the problem to a two phase segmentation. This thresholding solution is then used as a starting point for a two phase piecewise constant version of a geometric active contour model to reduce noise, smooth contours, improve their position accuracy and close eventual gaps in the carotid wall. © Springer-Verlag Berlin Heidelberg 2005.
Conference code: 67124Export Date: 21 November 2012Source: Scopusdoi: 10.1007/11559573_115Language of Original Document: EnglishCorrespondence Address: Rocha, R.; INEB - Instituto de Engenharia Biomédica, Laboratório de Sinai e Imagem Biomédica, Porto, PortugalReferences: Gee, A., Prager, R., Treece, G., Berman, L., Engineering a freehand 3D ultrasound system (2003) Pattern Recogn. Lett., 24, pp. 757-777;Sonka, M., Liang, W., Stefancik, R., Stolpen, A., (2000) Handbook of Medical Imaging: Medical Image Processing and Analysis, 2. , SPIE; Christodoulou, C.I., Pattichis, C.S., Pantziaris, M., Nicolaides, A., Texture based classification of atherosclerotic carotid plaques (2003) IEEE Trans. Med. Imaging, 22, pp. 902-912; Barratt, D., Ariff, B., Humphries, K., Thom, S., Hughes, A., Reconstruction and quantification of the carotid artery bifurcation from 3-d ultrasound images (2004) IEEE Trans. Med. Imaging, 23, pp. 567-583; Li, C., Lee, C., Minimum cross entropy thresholding (1993) Pattern Recogn, 26, pp. 617-625; Brink, A., Pendock, N., Minimum cross-entropy threshold selection (1996) Pattern Recogn., 29, pp. 179-188; Chan, T., Vese, L., Active contours without edges (2001) IEEE Trans. on Image Processing, 10, pp. 266-277; Vese, L.A., Chan, T.F., A multiphase level set framework for image segmentation using the Mumford and Shah model (2002) Int. J. Comput. Vision, 50, pp. 271-293; Touboul, P., Prati, P., Abd, V., Adrai, P.Y.S., Thibout, E., Ducimetiere, P., Use of monitoring software to improve the measurement of carotid wall thickness by B-mode imaging (1992) J. Hypertension, 10, pp. 37-41; Liang, Q., Wendelhag, I., Wikstrand, J., Gustavsson, T., A multiscale dynamic programming procedure for boundary detection in ultrasound artery images (2000) IEEE Trans. Med. Imaging, 19, pp. 127-142; Schmidt-Trucksass, A., Cheng, D., Sandrock, M., Schulte-Monting, J., Rauramaa, R., Huonker, M., Burkhardt, H., Computerized analysing system using the active contour in ultrasound measurement of carotid artery intima-media thickness (2001) Clinical Physiology, 5, pp. 561-569; Cheng, D., Schmidt-Trucksass, A., Cheng, K., Sandrock, M., Pu, Q., Burkhardt, H., Automatic detection of the intimal and the adventitial layers of the common carotid artery wall in ultrasound B-mode images using snakes (1999) International Conference on Image Analysis and Processing, pp. 452-457. , B. Werner; Cheng, D., Schmidt-Trucksass, A., Cheng, K., Burkhardt, H., Using snakes to detect the intimal and adventitial layers of the common carotid artery wall in sonographic images (2002) Computer Methods and Programs in Biomedicine, 67, pp. 27-37; Baillard, C., Barillot, C., Bouthemy, P., Robust adaptive segmentation of 3D medical images with level sets (2000) Technical Report, , IRISA, Campus Universitaire de Beaulieu, Prance; Tsai, A., Yezzi III, A.J., W., W.M., Tempany, C., Tucker, D., Fan, A., Grimson, W.E.L., Willsky, A.S., A shape-based approach to the segmentation of medical imagery using level sets (2003) IEEE Trans. Med. Imaging, 22, pp. 137-154; Perona, P., Malik, J., Scale-space and edge detection using anisotropic diffusion (1990) IEEE Trans. Pattern Anal. Mach. Intell., 12, pp. 629-639; Sethian, J.A., (1999) Level Set Methods and Fast Marching Methods, , Cambridge University Press; Osher, S., Fedkiw, R., (2003) Level Set Methods and Dynamic Implicit Surfaces, , Springer-Verlag. New York; Mumford, D., Shah, J., Optimal approximations by piecewise smooth functions and associated variational problems (1989) Communications on Pure and Applied Mathematics, 42, pp. 577-685; Gao, S., Bui, T.D., Image segmentation and selective smoothing by using the Mumford-Shah model (2005) IEEE Trans. on Image Processing, , To be published in
Keywords: Active contour model; Algorithms; Approximation theory; Carotid wall; Image segmentation; Image segmentation model; Mathematical models; Optimization; Ultrasonic imaging

Spectral methods in image segmentation: A combined approach - Monteiro, F.C.; Campilho, A.C. (Lecture Notes in Computer ScienceLect. Notes Comput. Sci., 2005)
Grouping and segmentation of images remains a challenging problem in computer vision. Recently, a number of authors have demonstrated a good performance on this task using spectral methods that are based on the eigensolution of a similarity matrix. In this paper, we implement a variation of the existing methods that combines aspects from several of the best-known eigenvector segmentation algorithms to produce a discrete optimal solution of the relaxed continuous eigensolution. © Springer-Verlag Berlin Heidelberg 2005.
Conference code: 65649Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Monteiro, F.C.; INEB - Instituto de Engenharia Biomédica, Campus de Santa Apolónia, Apartado 134, 5301-857 Bragança, Portugal; email: monteiro@ipb.ptReferences: Fowlkes, C., Belongie, S., Chung, F., Malik, J., Spectral grouping using nyström method (2004) Trans. on Pattern Analysis and Machine Intelligence, 26 (2), pp. 214-225;Malik, J., Belongie, S., Leung, T., Shi, T., Contour and texture analysis for image segmentation (2001) International Journal of Computer Vision, 43 (1), pp. 7-27; Martin, D., Fowlkes, C., Tal, D., Malik, J., A database of human segmented natural images and its application to evaluating segmentation algorithms and measuring ecological statistics (2001) IEEE Int. Conf. on Computer Vision, 2, pp. 416-424; Meila, M., Shi, J., Learning segmentation by random walks (2000) Neural Information Processing Systems, pp. 873-879; Ng, A., Jordan, M., Weiss, Y., On spectral clustering: Analysis and an algorithm (2002) Advances in Neural Information Processing Systems, 14, pp. 849-856; Scott, D.S., Solving sparse symmetric generalized eigenvalue without factorization (1981) SIAM Journal of Numerical Analisys, 18, pp. 102-110. , http://www.netlib.org/laso/snlaso.f; Scott, G.L., Longuet-Higgins, H.C., Feature grouping by "relocalisation" of eigenvectors of the proximity matrix (1990) Proc. British Machine Vision Conf., pp. 103-108; Shi, J., Malik, J., Normalized cuts and image segmentation (2000) IEEE Trans. on Pattern Analysis and Machine Intelligence, 22 (8), pp. 888-905; Weiss, Y., Segmentation using eigenvectors: A unifying view (1999) International Conference on Computer Vision, pp. 975-982; Wertheimer, M., Laws of organization in perceptual forms (1938) A Sourcebook of Gestalt Psychology, pp. 71-88. , W. B. Ellis Editor; Wu, Z., Leahy, R., An optimal graph theoretic approach to data clustering: Theory and its application to image segmentation (1993) IEEE Trans. on Pattern Analysis and Machine Intelligence, 15, pp. 1101-1113; Yu, S., Shi, J., Multiclass spectral clustering (2003) International Conference on Computer Vision, pp. 313-319. , Nice, France
Keywords: Algorithms; Computer vision; Discrete optimal solution; Eigensolution; Eigenvalues and eigenfunctions; Image segmentation; Matrix algebra; Problem solving; Similarity matrix; Spectral methods

Synthesis and characterization of new injectable and degradable dextran-based hydrogels - Maia, J.; Ferreira, L.; Carvalho, R.; Ramos, M.A.; Gil, M.H. (PolymerPolymer, 2005)
Injectable and degradable hydrogels are very interesting networks for drug delivery and cell transplantation applications since they can be administered in the human body in a minimally invasive way. In most cases, the crosslinking reaction occurs by photopolymerisation or free radical polymerisation; however, the use of chemical initiators may promote cell death. In the current work, injectable and degradable dextran-based hydrogels were prepared without the use of initiators. Dextran, a natural glucose-containing polysaccharide, was oxidized with sodium periodate (dexOx) and the derivatives characterized by NMR and FTIR spectroscopy's as well as by colorimetric techniques. The oxidized derivatives were crosslinked with adipic acid dihydrazide (AAD), forming a gel within 2-4 min. The obtained hydrogels were characterized by their mechanical properties, swelling and degradation behavior under physiologic conditions. In addition, the hydrogel interior morphology as well as porous structure was evaluated by scanning electron microscopy (SEM) and mercury intrusion porosimetry (MIP). MIP analysis showed that dexOx hydrogels crosslinked with 10% of AAD were macroporous with pore sizes ranging from 0.32 to 0.08 μm. As expected, the average pore size increased during hydrogel degradation as confirmed by SEM and MIP studies. © 2005 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 49Export Date: 21 November 2012Source: ScopusCODEN: POLMAdoi: 10.1016/j.polymer.2005.07.089Language of Original Document: EnglishCorrespondence Address: Maia, J.; Departamento de Engenharia Química, Universidade de Coimbra, Pinhal de Marrocos, 3030 Coimbra, Portugal; email: joao.rm.silva@networkcontacto.comReferences: Ferreira, L., Carvalho, R., Gil, M.H., Dordick, J.S., (2002) Biomacromolecules, 3, p. 333;Ferreira, L., Gil, M.H., Dordick, J.S., (2002) Biomaterials, 23, p. 3957; Ferreira, L., Rafael, A., Lamghari, M., Barbosa, M.A., Gil, M.H., Cabrita, A.M.S., (2004) J Biomed Mater Res, 68, p. 584; Lee, K.Y., Mooney, D.J., (2001) Chem Rev, 101 (7), p. 1869; Peppas, N.A., Bures, P., Leobandung, W., Ichikawa, H., (2000) Eur J Pharma Biopharm, 50, p. 27; Wong, W.H., Mooney, D.J., (1997) Synthetic Biodegradable Polymer Scaffolds, pp. 49-82. , A. Atala D.J. Mooney Birkhäuser Boston; Mehvar, R., (2000) J Controlled Release, 69, p. 1; Nguyen, K.T., West, J.L., (2002) Biomaterials, 23, p. 4307; Liu, V.A., Bhatia, S.N., (2002) Biomed Microdevices, 4 (4), p. 257; Williams, C.G., Malik, A.N., Kim, T.K., Manson, P.N., Elisseeff, J.H., (2005) Biomaterials, 26, p. 1211; Bouhadir, K.H., Hausman, D.S., Mooney, D.J., (1999) Polymer, 40, p. 3575; Lee, K.Y., Alsberg, E., Mooney, D.J., (2001) J Biomed Mater Res, 56, p. 228; Lee, K.Y., Bouhadir, K.M., Mooney, D.J., (2000) Macromolecules, 33, p. 97; Kim, S.-H., Chu, C.C., (2000) J Biomed Mater Res, Appl Biomater, 53, p. 258; Meyvis, T., De Smedt, S., Stubbe, B., Hennink, W.E., Demeester, J., (2001) Pharm Res, 18 (11), p. 1593; Dziubla, T.D., Torjman, M.C., Joseph, J.I., Murphy-Tatum, M., Lowman, A.M., (2001) Biomaterials, 22, p. 2893; Jen, A.C., Wake, M.C., Mikos, A.G., (1996) Biotechnol Bioeng, 50, p. 357; Schneerson, R., Barrera, O., Sutton, A., Robbis, J.B., (1980) J Exp Med, 152, p. 361; Jia, X., Burdick, J.A., Kobler, J., Clifton, R.J., Rosowski, J.J., Zeitels, S.M., (2004) Macromolecules, 37, p. 3239; Edwards-Lévy, F., Andry, M.C., Lévy, M.C., (1993) Int J Pharm, 96, p. 85; Meyvis, T.K.L., De Smedt, S.C., Demeester, J., Hennin, W.E., (1999) J Rheol, 43, p. 933; Behravesh, E., Jo, S., Zygourakis, K., Mikos, A.G., (2002) Biomacromolecules, 3, p. 374; Washburn, E.W., (1921) Proc Natl Acad Sci, 7, p. 115; Ishak, M.F., Painter, T.J., (1978) Carbohyd Res, 64, p. 189; Tiziani, S., Sussich, F., Cesáro, A., (2003) Carbohyd Res, 338, p. 1083; Van Dijk-Wolthuis, W.N.E., Franssen, O., Talsma, H., Van Steenbergen, M.J., Kettenes-Van Den Bosch, J.J., Hennink, W.E., (1995) Macromolecules, 28, p. 6317; Yu, R.J., Bishop, C.T., (1967) Can J Chem, 45, p. 2195; Domb, A.J., Linden, G., Polacheck, I., Benita, S., (1996) J Polym Sci, Part A: Polym Chem, 34, p. 1229; Pavia, D.L., Lampma, G.M., Kriz, G.S., (1996) Introduction to Spectroscopy, , 2nd ed Saunders College Publishing London; Vervoort, L., Vinckier, I., Moldenaers, P., Van Den Mooter, G., Augustijns, P., Kinget, R., (1999) J Pharm Sci, 88, p. 209; Smedt, S.C.D., Lauwers, A., Demeester, J., Van Steenbergen, M.J., Hennink, W.E., Roefs, S.P.F.M., (1995) Macromolecules, 28, p. 5082; Bell, C.L., Peppas, N.A., (1995) Adv Polym Sci, 122, p. 125; Van Dijk-Wolthuis, W.N.E., Hoogeboom, J.A.M., Van Steenbergen, M.J., Tsang, S.K.Y., Hennink, W.E., (1997) Macromolecules, 30, p. 4639; Dawlee, S., Sugandhi, A., Balakrishnan, B., Labarre, D., Jayakrishnan, A., (2005) Biomacromolecules, 6, p. 2040; Peppas, N.A., Hydrogels (1996) Biomaterials Science: An Introduction to Materials in Medicine, p. 60. , B.D. Ratner A.S. Hoffman F.J. Schoen J.E. Lemons Academic Press London; Pirard, R., Rigacci, A., Maréchal, J.C., Quenard, D., Chevalier, B., Achard, P., (2003) Polymer, 44, p. 4881; Ferreira, L., Gil, M.H., Cabrita, A.M.S., Dordick, J.S., (2005) Biomaterials, 26, p. 4707
Keywords: Cell Death; Cell transplantation; Colorimetry; Crosslinking; Degradation; Drug delivery; Drug dosage; Fourier transform infrared spectroscopy; Free radical polymerization; hydrogel; Hydrogels; Mercury intrusion porosimetry (MIP); morphology; Nuclear magnetic resonance spectroscopy; Photopolymerization; Polysaccharides; Pore size; Porosimeters; Scanning electron microscopy; Synthesis (chemical)

Automatic delimitation of lung fields on chest radiographs - Mendonça, A.M.; Da Silva, J.A.; Campilho, A. (2004 2nd IEEE International Symposium on Biomedical Imaging: Macro to NanoIEEE Int. Symp. Biomed. Imaging Macro Nano, 2004)
The purpose of the research herein presented is the automatic delimitation of lung fields in posterior-anterior digital chest radiographs. In a computer-aided diagnosis system the precise location of the lungs is important as it allows the reduction of the region under analysis, decreasing the computation time and facilitating data compression. Furthermore, it allows the delimitation of the search area, easing the selective tuning of the abnormalities detection algorithms. The results produced by the automatic method were validated by comparison with manual contours traced by experienced radiologists. Two programs with friendly interfaces were developed for this purpose. © 2004 IEEE.
Conference code: 64593Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Mendonça, A.M.; Inst. de Engenharia Biomédica, Lab. de Sinai e Imagem Biomedica, Campus da FEUP, Rua Dr. Roberto Frias, s/n, 4200-465 Porto, PortugalReferences: Tsujii, O., Freedman, M., Mun, S., Automated segmentation of anatomic regions in chest radiographs using an adaptive-sized hybrid neural network (1998) Medical Physics, 25, pp. 998-1007;Armato III, S., Giger, M., MacMahon, H., Computerized detection of abnormal asymetry in digital lateral chest radiographs (1994) Medical Physics, 21, pp. 1761-1768; Armato III, S., Giger, M., Ashizawa, K., MacMahon, H., Automated lung segmentation in digital lateral chest radiographs (1998) Medical Physics, 25, pp. 1507-1520; Carrascal, F., Carreira, J., Souto, M., Automatic calculation of total lung capacity from automatically traced lung boundaries in posterior-anterior and lateral digital chest radiographs (1998) Medical Physics, 25, pp. 1118-1131; Ginneken, B., Romeny, B., Automatic segmentation of lung fields in chest radiographs (2000) Medical Physics, 27, pp. 2445-2455; Li, L., Zheng, Y., Kallergi, M., Clark, R., Improved method for automatic identification of lung regions on chest radiographs (2001) Academic Radiology, 8, pp. 629-638; Monteiro, M., Mendonça, A.M., Campilho, A., Lung field detection on chest radiographs (2002) Proceedings of VIIP02, IASTED International Conference on Visualization, Imaging and Image Processing, pp. 367-372. , J. Villanueva (eds.), Spain Sponsors: IEEE
Keywords: Algorithms; Chest radiographs; Computer aided diagnosis; Contour detection; Data compression; Edge detection; Image segmentation; Lung fields; Pulmonary diseases; Radiography; X ray analysis; X ray imaging

Automatic lane and band detection in images of thin layer chromatography - Sousa, A.V.; Aguiar, R.; Mendonca, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2004)
This work aims at developing an automatic method for the analysis of TLC images for measuring a set of features that can be used for the characterization of the distinctive patterns that result from the separation of oligosaccharides contained in human urine. This paper describes the methods developed for the automatic detection of the lanes contained in TLC images, and for the automatic separation of bands for each detected lane. The extraction of quantitative information related with each band was accomplished with two methods: the EM expectation-maximization and nonlinear least squares trustregion algorithms. The results of these methods, as well as additional quantitative information related with each band, are also presented. © Springer-Verlag 2004.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Sousa, A.V.; Institute de Engenharia Biomédica, Rua Roberto Prias, 4200-465 Porto, Portugal; email: ats@isep.ipp.ptReferences: Sewell, A., (1991) Urinary Oligosaccharides. Techniques in Diagnostic Human Biochemical Genetics, pp. 219-231. , Willey-Liss, Inc;Thomas, G., Disorders of Glycoprotein Degradation. α-Mannosidosis, β-Mannosidosis, Fucosidosis and Sialidosis, , Disorders of Glycoprotein Degradation (Chap. 140); Starr, C., Masada, R., Hague, C., Klock, J., Fluorophore-assisted Carbohydrate Electrophoresis in the Separation, Analysis, and Sequencing of Carbohydrates (1996) Journal of Chromatography A, 720, pp. 295-321; Klein, A., Lebreton, A., Lemoine, J., Périni, J., Roussel, P., Michalski, J., Identification of Urinary Oligosaccharides by Matrix-assisted Laser Desorption Ionization Time-of-flight Mass Spectrometry (1998) Clinical Chemistry, 44 (12), pp. 2422-2428; Dempster, A., Laird, N., Rubin, D., Maximum Likelihood from Incomplete Data via the em Algorithm (1977) Journal of the Royal Statistical Society, B, 39 (1), pp. 1-38; Schwedt, G., The Essential Guide to Analytical Chemistry, , John Wiley & Sons; Dennis, J., Nonlinear Least-squares, State of the Art in Numerical Analysis, , D. Jacobs Academic Press; Byrd, R., Schnabel, R., Shultz, G., Approximate Solution of the Trust Region Problem by Minimization over Two-Dimensional Subspaces (1988) Mathematical Programming, 40, pp. 247-263; Branch, M., Coleman, T., Li, Y., A Subspace, Interior, and Conjugate Gradient Method for Large-Scale Bound-Constrained Minimization Problems (1999) SIAM SISC, 21 (1), pp. 1-23; Nabney, I., Netlab Algorithms for Pattern Recognition (2003) Advances in Pattern Recognition, , Springer; Marques, J., Reconhecimento de Padrões, , Métodos Estatisticos e Neuronais, IST-Press; Machado, A., Campos, M., Siqueira, A., Carvalho, O., (1997) An Iterative Algorithm for Segmenting Lanes in Gel Electrophoresis Images;

Biocompatibility of chemoenzymatically derived dextran-acrylate hydrogels - Ferreira, L.; Rafael, A.; Lamghari, M.; Barbosa, M.A.; Gil, M.H.; Cabrita, A.M.S.; Dordick, J.S. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2004)
The biocompatibility of chemoenzymatically generated dextran-acrylate hydrogels has been evaluated in vitro, using human foreskin fibroblasts, and in vivo, by subcutaneous and intramuscular implantation in Wistar rats for up to 40 days. In vitro tests show that hydrogel extracts only minimally reduced (<10%) the mitochondrial metabolic activity of fibroblasts. Direct contact of the hydrogels with cells induced a cellular proliferation inhibition index (CPII) of 50-80%, compared with a control, whereas through indirect contact, the CPII values were <16%, suggesting that the high CPII values achieved in the direct assay test were likely due to mechanical stress or limitations in oxygen diffusion. Hence, the hydrogels were noncytotoxic. Moreover, cell-material interaction studies show that these hydrogels were nonadhesive. Finally, histologic evaluation of tissue response to subcutaneous and intramuscular implants showed acceptable levels of biocompatibility, as characterized by a normal cellular response and the absence of necrosis of the surrounding tissues of the implant. In the first 10 days, the foreign-body reaction in the intramuscular implantation was more severe than in subcutaneous implantation, becoming identical after 30 days. In both cases, dextran hydrogels did not show signs of degradation 6 weeks postimplantation and were surrounded by a thin fibrous capsule and some macrophages and giant cells. This response is typical with a number of nondegradable biocompatible materials. These results indicate that dextran hydrogels are biocompatible, and may have suitable applications as implantable long-term peptide/protein delivery systems or scaffolds for tissue engineering. © 2004 Wiley Periodicals, Inc.
Cited By (since 1996): 21Export Date: 21 November 2012Source: ScopusCODEN: JBMRCPubMed ID: 14762939Language of Original Document: EnglishCorrespondence Address: Dordick, J.S.; Department of Chemical Engineering, Rensselaer Polytechnic Institute, Troy, NY 12180, United States; email: dordick@rpi.eduChemicals/CAS: acrylic acid, 10344-93-1, 79-10-7; dextran, 87915-38-6, 9014-78-2; Acrylates; Biocompatible Materials; Dextrans, 9004-54-0; Enzymes; HydrogelsReferences: Ferreira, L., Gil, M.H., Dordick, J.S., Enzymatic synthesis of dextran-containing hydrogels (2002) Biomaterials, 23, pp. 3957-3967;Peppas, N.A., Bures, P., Leobandung, W., Ichikawa, H., Hydrogels in pharmaceutical formulations (2000) Eur J Pharm Biopharm, 50, pp. 27-46; Park, K., Park, H., Biocompatibility issues of implantable drug delivery systems (1996) Pharm Res, 13 (12), pp. 1770-1776; Novick, S.J., Dordick, J.S., Preparation of active and stable biocatalytic hydrogels for use in selective transformation (1998) Chem Mater, 10 (4), pp. 955-958; Letourneur, D., Machy, D., Pellé, A., Marcon-Bachari, E., Dángelo, G., Vogel, M., Chaubert, F., Michel, J.-B., Heparin and non-heparin-like dextrans differentially modulate endothelial cell proliferation: In vitro evaluation with soluble and crosslinked polysaccharide matrices (2002) J Biomed Mater Res, 60, pp. 94-100; Österberg, E., Bergström, K., Holmberg, K., Schuman, T.P., Riggs, J.A., Burns, N.L., Van Alstine, J.M., Harris, J.M., Protein-rejecting ability of surface-bound dextran in end-on and side-on configurations: Comparison to PEG (1995) J Biomed Mater Res, 29, pp. 741-747; Frazier, R.A., Matthijs, G., Davies, M.C., Roberts, C.J., Schacht, E., Tendler, S.J.B., Characterization of protein-resistant dextran monolayers (2000) Biomaterials, 21, pp. 957-966; Massia, S.P., Stark, J., Immobilized RGD peptides on surface-grafted dextran promote biospecific cell attachment (2001) J Biomed Mater Res, 56, pp. 390-399; Wong, W.H., Mooney, D.J., Synthesis and properties of biodegradable polymers used as synthetic matrices for tissue engineering (1997) Synthetic Biodegradable Polymer Scaffolds, p. 50. , Atala A, Mooney DJ, editors. Boston, MA: Birkhäuser; Lee, K.Y., Mooney, D.J., Hydrogels for tissue engineering (2001) Chem Rev, 101 (7), pp. 1869-1879; Hern, D.L., Hubbell, J.A., Incorporation of adhesion peptides into nonadhesive hydrogels useful for tissue resurfacing (1998) J Biomed Mater Res, 39, pp. 266-276; Mann, B.K., Gobin, A.S., Tsai, A.T., Schmedlen, R.H., West, J.L., Smooth muscle cell growth in photopolymerized hydrogels with cell adhesive and proteolytically degradable domains: Synthetic ECM analogs for tissue engineering (2001) Biomaterials, 22, pp. 3045-3051; De Groot, C.J., Van Luyn, M.J.A., Van Dijk-Wolthuis, W.N.E., Cadée, J.A., Plantinga, J.A., Den Otter, W., Hennink, W.E., In vitro biocompatibility of biodegradable dextran-based hydrogels tested with human fibroblasts (2001) Biomaterials, 22, pp. 1197-1203; Cadée, J.A., Luyn, M.J.A., Brouwer, L.A., Plantinga, J.A., Van Wachem, P.B., Groot, C.J., Otter, W., Hennink, W.E., In vivo biocompatibility of dextran-based hydrogels (2000) J Biomed Mater Res, 50, pp. 397-404; Anderson, J.M., In vivo biocompatibility of implantable delivery systems and biomaterials (1994) Eur J Pharm Biopharm, 40 (1), pp. 1-8; Anderson, J.M., Inflammation, wound healing, and the foreign body reaction response (1996) Biomaterials Science, pp. 165-173. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE, editors. New York: Academic Press; (1992) ISO 10993-5: Biological Evaluation of Medical Devices. Test for Cytotoxicity: In Vitro Methods, , Geneva, Switzerland: International Organization for Standardization; Pizzoferato, A., Ciapetti, G., Stea, S., Cenni, E., Arciola, C.R., Granchi, D., Savarino, L., Cell culture methods for testing biocompatibility (1994) Clin Mater, 15, pp. 173-190; Bancroft, J.D., Stevens, A., (1996) Theory and Practice of Histological Techniques, pp. 99-211. , Edinburg: Churchill Livingstone; Mosmann, T., Rapid colorimetric assay for cellular growth and survival: Application to proliferation and cytotoxicity assays (1983) J Immunol Methods, 65, pp. 55-63; Moreau, M.F., Chappard, D., Lesourd, M., Monthéard, J.P., Baslé, M.F., Free radicals and side products released during methylmethacrylate are cytotoxic for osteoblastic cells (1998) J Biomed Mater Res, 40, pp. 124-131; Black, J., The inflammatory response (1999) Biological Performance of Materials, p. 131. , Black J, editor. New York: Marcel Dekker; Murch, A.R., Grounds, M.D., Marshall, C.A., Papadimitriou, J.M., Direct evidence that inflammatory multinucleate giant cells form by fusion (1982) J Pathol, 137, pp. 177-180; Kuijpers, A.J., Wachem, P.B., Luyn, M.J.A., Plantinga, J.A., Engbers, G.H.M., Krijgsveld, J., Zaat, S.A.J., Feijen, J., In vivo compatibility and degradation of crosslinked gelatin gels incorporated in knitted Dacron (2000) J Biomed Mater Res, 51, pp. 136-145; Kuijpers, A.J., Van Wachem, P.B., Luyn, M.J.A., Brouwer, L.A., Engbers, G.H.M., Krijgsveld, J., Zaat, S.A.J., Feijen, J., In vitro and in vivo evaluation of gelatin-chondroitin sulphate hydrogels for controlled release of antibacterial proteins (2000) Biomaterials, 21, pp. 1763-1772; Hooper, K.A., Macon, N.D., Kohn, J., Comparative histological evaluation of new tyrosine-derived polymers and poly(L-lactic acid) as a function of polymer degradation (1998) J Biomed Mater Res, 41, pp. 443-454; Bos, R.R.M., Rozema, F.R., Boering, G., Nijenhuis, A.J., Pennings, A.J., Verwey, A.B., Nieuwenhuis, P., Jansen, H.W.B., Degradation of and tissue reaction to biodegradable poly(L-lactide) for use as internal fixation of fractures: A study in rats (1991) Biomaterials, 12, pp. 32-36; Nakamura, T., Veda, H., Tsuda, T., Li, Y.-H., Kiyotani, T., Inoue, M., Matsumoto, K., Shimizu, Y., Long-term implantation test and tumorigenicity of polyvinyl alcohol hydrogel plates (2001) J Biomed Mater Res, 56, pp. 289-296; Dziubla, T.D., Torjman, M.C., Joseph, J.I., Murphy-Tatum, M., Lowman, A.M., Evaluation of porous networks of poly(2-hydroxyethylmethacrylate) as interfacial drug delivery devices (2001) Biomaterials, 22, pp. 2893-2899; Spector, M., Lalor, P.A., In vivo assessment of tissue compatibility (1996) Biomaterials Science, pp. 220-228. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE, editors. New York: Academic Press
Keywords: Acrylates; acrylic acid; animal experiment; animal model; animal tissue; Animals; article; Biocatalytic polyester; Biocompatibility; Biocompatible Materials; Biodegradation, Environmental; Biodiversity; Biomaterials; cell adhesion; Cell Division; cell interaction; cell proliferation; Cells, Cultured; Coenzymes; controlled study; Cytotoxicity; dextran; dextran acrylate; dextran acrylate hydrogel; dextran hydrogel; Dextrans; drug delivery system; Enzymes; fibroblast; Fibroblasts; Fibrous capsules; foreign body reaction; Foreign-Body Reaction; giant cell; human; human cell; Humans; hydrogel; Hydrogels; implantation; Implants (surgical); Implants, Experimental; in vitro study; in vivo study; macrophage; male; materials testing; mechanical stress; Mechanical stresses; metabolism; Mitochondria; mitochondrial respiration; nonhuman; oxygen diffusion; prepuce; rat; Rats; Rats, Wistar; Tissue; Tissue engineering; unclassified drug

Biological Activity of Two Glass Ceramics in the Meta- and Pyrophosphate Region: A Comparative Study - Dias, A.G.; Costa, M.A.; Lopes, M.A.; Santos, J.D.; Fernandas, M.H. (Key Engineering MaterialsKey Eng Mat, 2004)
Based upon the CaO-P 2O 5 glass system, two glass ceramics were prepared in the metaand pyrophosphate regions. The present work describes preliminary results concerning the biological activity of MK5B (45CaO-45P 2O 5-5MgO-5K20, in mol %) and MT13B (45CaO-37P 2O 55-5MgO-13TiO 2, in mol %) using MG63 osteoblast-like cells. Both materials supported cell growth and proliferation which increased with the incubation time. However, cell growth was significantly lower on seeded MK5B samples. SEM observation showed that cell adhesion and spreading were hampered on this material. Evident degradation of the material surface was observed with simultaneous cell proliferation and material precipitation. By contrast, MT13B presented a relatively stable surface throughout the culture time. Results suggest that the in vitro biological behaviour of MK5B and MT13B is related with differences in the degradation rates of the two materials during the culture time.
Conference code: 62053Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Dias, A.G.; Faculdade de Engenharia, Universidade do Porto, DEMM, Rua Dr. Roberta Frias, 4200 Porto, PortugalReferences: Dias, A.G., Lopes, M.A., Gibson, I., Santos, J.D., J. Non-Crystal. Solids, , in press;Dias, A.G., Lopes, M.A., Tsuru, K., Hayakawa, S., Santos, J.D., Osaka, A., Physiscs and Chemistry of Glasses, , in press; Dias, A.G., Lopes, M.A., Santos, J.D., Advance Materials Science, , in press; Rykke, M., Rolla, G., Sonju, T., (1988) Scand. J. Dent. Res., 96, pp. 517-522
Keywords: Adhesion; Biodegradable glass ceramics; Biodegradation; Bone; cell proliferation; Cells; Crystallization; Degradation; Glass ceramics; incubation time; MG63 osteoblast-like cells; Scanning electron microscopy; X ray diffraction

Bonelike®/PLGA hybrid materials for bone regeneration: In vivo evaluation - Oliveira, J.M.; Kawai, T.; Lopes, M.A.; Ohtsuki, C.; Santos, J.D.; Afonso, A. (Materials Science ForumMater Sci Forum, 2004)
The biocompatibility and osteoconductive potential of Bonelike® and Bonelike®/PLGA hybrid materials were evaluated through subcutaneous and tibiae implantations for a 4 week period. Qualitative histology was performed to evaluate new bone formation and characterise bone-implant interface and results showed that Bonelike®/PLGA hybrid materials promote extensive bone growth. After the 4 week implantation period, Bonelike® resorption was recognized, which may be due to the presence of resorbable β and α-tricalcium phosphate phases.
Conference code: 63332Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: MSFOELanguage of Original Document: EnglishCorrespondence Address: Oliveira, J.M.; Inst. de Engenharia Biomédica, Lab. de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jmolive@fe.up.ptReferences: Praemer, A., Furner, S., Rice, D.P., (1992) Am. Acad. Orthop. Surg., p. 1;Glowacki, J., Mulliken, J.B., (1985) Clin. Plast. Surg., 12, p. 233; Buck, B.E., Malinin, T.I., Brown, M.D., (1989) Clin. Orthop., 36, p. 129; Sepulveda, P., Bressiani, A.H., Bressiani, J.C., Mesenguer, L., König Jr., B., (2002) J. Biomed. Mater. Res. Vol., 62, p. 587; Glimcher, M.J., (1987) Instr. Course Lect., 36, p. 46; Yakamuro, T., Hench, L.L., Wilson, J., (1990) CRC Handbook of Bioactive Ceramics, 2, pp. 245-252; Klemm, K.W., (1993) Clin. Orthop. & Rel. Res., 295, pp. 63-76; Agrawal, C.M., Ray, R.B., (2001) J. Biomed. Mater. Res., 55, p. 141; Santos, J.D., Campbell, J.K., Winton, G.H., (2000), European Patent N° W00068164Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463
Keywords: Bacteria; Biodegradation; Bone; Bonelike resorption; Bonelike®; Histological studies; histology; Hybrid materials; hydroxyapatite; In vivo; physiology; PLGA; Polymers; Surgery; Tissue

Bounds for the Average Generalization Error of the Mixture of Experts Neural Network - Alexandre, L.A.; Campilho, A.; Kamel, M. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2004)
In this paper we derive an upper bound for the average-case generalization error of the mixture of experts modular neural network, based on an average-case generalization error bound for an isolated neural network. By doing this we also generalize a previous bound for this architecture that was restricted to special problems. We also present a correction factor for the original average generalization error, that was empirically obtained, that yields more accurate error bounds for the 6 data sets used in the experiments. These experiments illustrate the validity of the derived error bound for the mixture of experts modular neural network and show how it can be used in practice. © Springer-Verlag 2004.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Alexandre, L.A.; Networks and Multimedia Group, IT, Covilhã, Portugal; email: lfbaa@di.ubi.ptReferences: Gu, H., Takahashi, H., Towards more practical average bounds on supervised learning (1996) IEEE Trans. Neural Networks, 7, pp. 953-968;Vapnik, V., (1999) The Nature of Statistical Learning Theory., , Springer; Haykin, S., (1999) Neural Networks: A Comprehensive Foundation, 2nd Edition., , Prentice Hall; Alexandre, L., Campilho, A., Kamel, M., Average error bound for the mixture of experts MNN architecture (2002) Proceedings of the 12th Portuguese Conference on Pattern Recognition, , Aveiro, Portugal; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, pp. 79-87; Auda, G., Kamel, M., Modular neural network classifiers: A comparative study (1998) J. Intel. Robotic Systems, pp. 117-129; Jordan, M., Jacobs, R., Hierarchical mixture of experts and the em algorithm (1994) Neural Computation, pp. 181-214; Jacobs, R., Peng, F., Tanner, M., A bayesian approach to model selection in hierarchical mixtures-of-experts architectures (1997) Neural Networks, 10, pp. 231-241; De Marques Sa, J., Pattern Recognition: Concepts (2001) Methods and Applications, , Springer; Blake, C., Keogh, E., Merz, C., (1998) UCI repository of machine learning databases, , http://www.ics.uci.edu/~mlearn/MLRepository.html; Gu, H., Takahashi, H., Estimating learning curves of concept learning (1997) Neural Networks, 10, pp. 1089-1102; Bishop, C., (1995) Neural Networks for Pattern Recognition., , Oxford University Press; Riedmiller, M., Braun, H., A direct adaptive method for faster backpropagation learning: The RPROP algorithm (1993) IEEE International Conference on Neural Networks, pp. 586-591. , San Francisco
Keywords: Generalization error bounds; Mixture of experts; Modular neural networks

Detection of Rib Borders on X-ray Chest Radiographs - Moreira, R.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2004)
The purpose of the research herein presented is the automatic detection of the rib borders in posterior-anterior (PA) digital chest radiographs. In a computer-aided diagnosis system, the precise location of the ribs is important as it allows reducing the false positive in the detection of abnormalities such as nodules, rib lesions and lung lesions. We adopted an edge based approach aiming at detecting the lower border of each rib. For this purpose, the rib geometric model is described as a parabola. For each rib, the upper limit is obtained using the position of the corresponding lower border. © Springer-Verlag 2004.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: INEB - Instituto de Engenharia Biomedica, Laboratóries de Sinai, Imagem BiomédicaPortugalReferences: Volgelsang, F., Weiler, F., Dahmen, J., Kilbinger, M., Wein, B., Günther, R.W., (1998) Detection and Compensation of Rib Structures in Chest Radiographs for Diagnose Assistance, Proceedings of SPIE, 3338, pp. 774-785;Park, M., Jin, J.S., Wilson, L.S., Detection and labeling ribs on expiration chest radiographs (2003) The Phisics of Medical Imaging Conference, SPIE, pp. 1021-1031. , 15-20 Feb; Ginneken, B., Romeny, Bart, M.H., Automatic delineation of ribs in frontal chest radiographs (2000) Medical Imaging 2000:Image Processing, Proceedings of SPIE, 3979, pp. 825-836; Monteiro, M., Mendonça, A.M., Campilho, A., Lung field detection on chest radiographs (2002) Proceedings of VIIP02, pp. 367-372. , IASTED International Conference on Visualization, Imaging and Image Processing, Spain; Mendonça, A.M., Suva, J., Campilho, A., Automatic delimitation of lung fields on chest radiographs (2004) Proceeding of ISBI04, IEEE International Symposium on Biomedical Imaging, , Arlington, USA; Otsu, N., A threshold selection method from gray-level histograms (1979) IEEE Transactions on Systems, Man, and Cybernetics, 9 (1), pp. 62-66

Effect of the Solvents on the Solution Mixture Derived Polylactide/hydroxyapatite Composites - Li, Y.; Weng, W.; Cheng, K.; Du, P.; Shen, G.; Han, G.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2004)
Polylactide/hydroxyapatite composites were prepared by a solution mixture method. Chloroform and tetrahydrofuran were used as solvents. The effect of the solvents on the polylactide/hydroxyapatite composites was investigated by TEM, mechanical properties, sedimentation time and UV-Vis transmission spectra. The results indicate that the polylactide/hydroxyapatite prepared using tetrahydrofuran as solvent has better dispersion of the hydroxyapatite filler in the matrix and larger bend strength than the one using chloroform as solvent. This is ascribed to the proper interaction between the solvent and hydroxyapatite filler.
Conference code: 62053Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Weng, W.; Dept. of Mat. Sci. and Engineering, Zhejiang University, Hangzhou 310027, China; email: wengwj@zju.edu.cnReferences: Hench, L.L., (1998) Journal of American Ceramic Society, 81, p. 1705;Wang, M., (2003) Biomaterials, 24, p. 2133; Hao, J., Yuan, M., Deng, X., (2001) Biomaterials, 22, p. 2867; Ignjatovic, N., Tomic, S., Dakic, M., Miljkovic, M., Plavsic, M., Uskokovic, D., (1999) Biomaterials, 20, p. 809; Misra, D.N., (1988) Langmuir, 4, p. 953; Dean, J.A., (1999) Lange's Handbook of Chemistry (15th Edition), , McGraw-HILL, INC. New York
Keywords: Bend strength; Composite; Composite materials; dispersion; Dispersions; Fillers; Heat treatment; Hydroxvapatite; hydroxyapatite; Polarity; polylactide; Sedimentation; Solutions; Solvent; Solvents; transmission electron microscopy; Ultraviolet radiation

An electronic instrumentation course for non-electronic engineering students - Campilho, A.; Cardoso, A. (International Journal of Electrical Engineering EducationInt J Electr Eng Educ, 2004)
This paper reports on the implementation of a required course on electronic instrumentation for informatics engineering students. These students had proved in previous years to require a special approach, as their motivation for this subject was low. The course focuses on the basic concepts of Electronic Instrumentation, including analogue-to-digital and digital-to-analogue conversion and introducing the concept of instrument control. The course was organised in a set of lectures coupled with laboratory experiments, and a small project. To foster collaborative learning all the students work on the same laboratory experiments, simultaneously, organised in groups of two. The students' feedback on the course was more positive than in previous years, although not substantially so in terms of results. We feel that a change of attitude took place effectively, and that this could be attributed to the laboratory experiments using LabVIEW.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: IJEEALanguage of Original Document: EnglishCorrespondence Address: Campilho, A.; Inst. de Engenharia Bioméd., Universidade do Porto, Porto, Portugal; email: campilho@fe.up.ptReferences: (2000) LabVIEW Graphical Programming for Instrumentation, , National Instruments, Austin, Texas, TX, Version 6.1;Consonni, D., Seabra, A.C., A modern approach to teaching basic experimental electricity and electronics (2000) IEEE Trans. Educ., 43, pp. 5-18; Goulart, T.J., Consonni, D., Automated system for measurement electrical three-phase power components (2001) IEEE Trans. Educ., 44, pp. 336-341; Edward, N.S., The role of laboratory work in engineering education: Student and staff perceptions (2002) Int. J. Elec. Engng. Educ., 39 (1), pp. 11-19; Jiménez-Leube, F.J., Almendra, A., González Sanz-Maudes, C., Networked implementation of an electrical measurement laboratory for first course engineering studies (2001) IEEE Trans. Educ., 44, pp. 377-383; Campilho, A., (2002) Instrumentação Electrónica. Métodos e Técnicas de Medição, , Edições FEUP, Porto
Keywords: Analog to digital conversion; Analogue-to-digital conversion; Collaborative learning; Collaborative learning (CL); Curricula; Data processing; Electronic instrumentation; Electronics engineering; Engineering education; LabVIEW; Learning systems; Motivation; Project management; Students

In Vitro Mineralisation of Human Bone Marrow Cells Cultured on Bonelike® - Costa, M.A.; Gutierres, M.; Almeida, L.; Lopes, M.A.; Santos, J.D.; Fernandes, M.H. (Key Engineering MaterialsKey Eng Mat, 2004)
Bonelike® is a CaO-P 2O 5 based glass-reinforced hydroxyapatite (HA) designed to mimic the inorganic composition of the bone tissue. This work evaluates the response of human bone marrow cells to Bonelike® concerning cell proliferation and osteoblast differentiation. HA was used as control material. Results showed that Bonelike® allowed the proliferation of bone marrow cells and their complete differentiation, as evidenced by the formation of cell-mediated mineralisation. In comparison with HA, Bonelike® had a positive effect on the expression of alkaline phosphatase and also on the formation of a mineralised matrix, two osteoblast markers.
Conference code: 62053Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Costa, M.A.; Inst. Cie. Blomed. de Abel Salazar, Universidade do Porto, Largo Abel Salazar, 4000 Porto, PortugalReferences: Santos, J.D., Campbell, J.K., Winston, G.H., European Patent N° WO0068164, 2000Lopes, M.A., Knowles, J.C., Santos, J.D., (2000) Biomaterials, 21, p. 1905;Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res.:App. Biomater., 48, p. 734; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., (1998) J. Biomed. Mater. Res., 41, p. 649; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., (2000) Biomaterials, 21, p. 1165; Ferraz, M.P., Fernandes, M., Santos, J.D., Monteiro, F.J., (2001) J. Mat. Sci.: Mat. Med., 12, p. 629; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463; Duarte, F., Santos, J.D., Afonso, A., Advanced Materials Forum, , in press; Coelho, M.J., Fernandes, M.H., (2000) Biomaterials, 21, p. 1095; Kleerekoper, M., (1996) Principles of Bone Biology, p. 1053. , Academic Press
Keywords: Bone; Bonelike®; Cell culture; cell proliferation; Composition; Grafts; Human bone marrow cells; hydroxyapatite; In vitro mineralisation; mineralization; Scanning electron microscopy; Sintering; X ray diffraction

Influence of characteristics of the starting hydroxyapatite powders and of deagglomeration procedure, on rheological behaviour of HA suspensions - Lemos, A.F.; Santos, J.D.; Ferreira, J.M.F. (Materials Science ForumMater Sci Forum, 2004)
In order to evaluate how the characteristics of starting HA powders affect their dispersion ability, several tests were made, including particle size distribution, particle morphology (SEM) and rheological measurements of the suspensions. To enable the preparation of concentrated suspensions as high as possible, the influence of deagglomeration procedure on rheological behaviour of hydroxyapatite aqueous suspensions was evaluated. The results revealed significant differences in the dispersing ability of the powders and on the maximum achievable solids loading. In fact, the maximum solids volume fraction that was possible to incorporate in the initial suspension of HA R was only 35-vol.%, while with the HA S it has been possible to start from 45-vol.% suspensions. Ball milling revealed to be more efficient than planetary milling in the preparation of HA R suspensions, and enabled to achieve a maximum solids volume fraction of 45-vol.% at the end of long milling period, which included successive incremental additions of powder. The powder HA S exhibited a much better dispersing ability, enabling the preparation of 60-vol.% solids only after two hours of planetary milling.
Conference code: 63332Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: MSFOELanguage of Original Document: EnglishCorrespondence Address: Ferreira, J.M.F.; Dept. of Ceramics Engineering, CICECO, Univ. of Aveiro, 3810-193 Aveiro, Portugal; email: jmf@cv.ua.ptReferences: Kanazawa, T., (1989) Inorganic Phosphate Materials, 52, p. 15. , Materials Science Monographs, (Elsevier Science Publishers, Amsterdam);Elliot, J.C., (1994) Structure and Chemistry of the Apatites and Other Calcium Orthophosphates. Studies in Organic Chemistry, 18. , Elsevier Science, Netherlands; Ohgushi, H., Okumura, M., Yoshikawa, T., Inoue, K., Senpuku, N., Tamai, S., Shors, E.C., (1992) J. Biomed. Mater. Res., 26, p. 885; Saggio-Woyanski, J., Scott, C., (1992) Am. Ceram. Soc. Bull., 71, p. 1674; Lyckfeldt, O., Ferreira, J.M.F., (1998) J. Eur. Ceram. Soc., 18, p. 131; Lorenzo, L.M.R., (1999), PhD Thesis MadridOlhero, S.M., Ferreira, J.M.F., (2003) Powder Thecnology, , accepted for publication
Keywords: Agglomeration; Bioceramics; crystallography; Deagglomeration; Foaming processes; hydroxyapatite; medicine; morphology; Particle size analysis; Powder characteristics; Powders; rheology; Scanning electron microscopy; Sedimentation; Sintering

Mineralised membranes for bone regeneration - Mesquita, P.; Branco, R.; Afonso, A.; Vasconcelos, M.; Cavalheiro, J. (Key Engineering MaterialsKey Eng Mat, 2004)
Guided bone regeneration can be achieved using filling biomaterials and protective membranes. The aim of this work is to study a new membrane prepared from shrimp shells, without modification of the natural concave shape. The "in vitro" bioactivity was evaluated using a simulated body fluid prepared with substitution of calcium by strontium (SBR-Sr). The bioactivity behaviour was increased using a surface treatment with sodium silicate. The "in vitro" and "in vivo" tests allow to conclude that these membranes are bioactive and can induce bone growth on their surfaces.
Conference code: 62053Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Mesquita, P.; Inst. de Engenharia Biomédica, R. do Campo Alegre 823, 4150-180 Porto, PortugalReferences: Baron, M., Haas, R., Dörtbudak, O., Watzek, G., Experimentally induced peri-implantitis: A review (2000) Int J Oral Maxillofac Implants, 15, pp. 533-544;Hammerle, C.H., Jung, R.E., Feloutzis, A., A systematic review of the survival of implants in bone sites augmented with barrier membranes (guided bone regeneration) in partially edentulous patients (2002) J Clin. Periodontol., 29 (SUPPL. 3), pp. 226-231; Brunel, G., Brocard, D., Duffort, J.F., Jacquet, E., Justumus, P., Simonet, T., Benque, E., Bioabsorbable materials for guided bone regeneration prior to implant placement and 7-year followup: Report of 14 cases (2001) J Periodontol., 72 (2), pp. 257-264; Karapati, S., Hugson, A., Kugelberg, C.F., Healing following GTR treatment of bone defects distal to mandibular 2 nd molars after removal of impacted 3 rd molars (2000) J. Clin. Periodontol., 27, pp. 325-332; Simões, R., Fonseca, L., Vasconcelos, M., Afonso, A., Cavalheiro, J., Modified exoskeleton of shrimp for guided bone regeneration (2002) 17 th ESB, , Barcelona, Spain, September
Keywords: Biological membranes; biomaterial; Biomaterials; Bone; Bone Regeneration; Calcium; Ceramic materials; Deproteinization; Membrane; Mineralised membranes; Natural material; Optical microscopy; Shear strength; Sodium compounds; Strontium; Substitution reactions

Production of porous hydroxyapatite with potential for controlled drug delivery - Queiroz, A.C.; Teixeira, S.; Santos, J.D.; Monteiro, F.J. (Materials Science ForumMater Sci Forum, 2004)
Porous hydroxyapatite was prepared in order to be used as a drug carrier and promote bone ingrowth. For this purpose, the microstructure should have interconnective pores and micro as well as macro porosity, for bone cell adhesion and bone ingrowth. The porous hydroxyapatite prepared by the burn-out method exhibits all these features. For measuring porosity, SEM analysis, mercury intrusion porosimetry and BET were used. FT-IR and XRD analysis revealed that only hydroxyapatite phase was present, being this result similar to the one found for dense samples. The morphology obtained appears to be well adapted to bone growth and drug adsorption.
Conference code: 63332Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: MSFOELanguage of Original Document: EnglishCorrespondence Address: Queiroz, A.C.; INEB, Inst. de Engenharia Biomédica, R do Campo Alegre, 823, 4150-180 Porto, Portugal; email: aqueiroz@ineb.up.ptReferences: Krejci, C.B., Bissada, N.F., Farah, C., Greenwell, H., (1987) J. Periodontology, 58, p. 521;Seymour, R.A., Heasman, P.A., MacGregor, I.D.M., The pathogenesis of periodontal disease (1992) Drugs, Diseases, and the Periodontium, , Oxford University Press; (1996) Journal of Periodontology, 67, p. 831; Soskolne, W.A., Heasman, H.A., Stabholz, A., Smart, G.J., Palmer, M., Flashner, M., Newman, H.N., (1997) Journal of Periodontology, 68, p. 32; Da Silva, M.H.P., Lemos, A.F., Gibson, I.R., Ferreira, J.M.F., Santos, J.D., (2002) J. of Non-crystaline Solids, 304, p. 286; Chang, B., Lee, C., Hong, K., Youn, H., Ryu, H., Chung, S., Park, K., (2000) Biomat., 21, p. 1291; Ewers, R., Simons, B., (1992) Biomaterials - Hard Tissue Repair and Replacement, , Elsevier Sc; Ohgushi, H., Okumura, M., Yoshikawa, T., Inoue, K., Senpuku, N., Tamai, S., Shors, E.C., (1992) Journal of Biomedical Materials Research, 26, p. 885; Barinov, S.M., Baschenko, Y.V., (1992) Bioceramics and the Human Body, , Elsevier Sc; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., (1997) J. Mater. Sc.: Materials in Medicine, 8, p. 731; Queiroz, A.C., Teixeira, S., Santos, J.D., Monteiro, F.J., (2003) Bioceramics, , accepted for; Santos, J.D., Monteiro, F.J., Gibson, I.R., Knowles, J.C., (2001) Biomaterial, 22, p. 1393
Keywords: Adsorption; Antibiotics; Bioceramics; Controlled drug delivery; Drug Carriers; Drug delivery; Fourier transform infrared spectroscopy; hydroxyapatite; morphology; Polyurethanes; porosity; Porous; Porous materials; Scanning electron microscopy; X ray diffraction analysis

Protein adsorption effect on in vitro acellular biodegradation of CaO-P 2O 5 glass ceramics - Dias, A.G.; Lopes, M.A.; Santos, J.D. (Materials Science ForumMater Sci Forum, 2004)
This work reports the in vitro accelular behaviour of a glass ceramic (45P 2O 5-45CaO-5MgO-5K 2O), which has significant potential for being used as an alloplastic bone graft. Experiments were carried out by immersing granule samples for a period up to 90 days in Trisbuffer solution at pH 7.4, in the presence and absence of a foetal bovine serum (FBS). The release of calcium, phosphorus, and potassium ions as well as the amount of protein adsorbed was followed by several techniques. The results obtained seem to indicate that the adsorption of proteins on the surface of the material, although causing an initial delay in the degradation, does not hamper the ionic exchange and therefore it is not a barrier for the degradation of the glass ceramic.
Conference code: 63332Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: MSFOELanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; Inst. de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Zeng, Chittur, K.K., Lacefield, W.R., (1999) Biomaterials, 20, p. 377;Ohta, Monna, H., Takahashi, S., (2001) J. Biomed. Mater. Res., 55, p. 409; Zyman, Z., Dedukh, N.V., Glusko, V.I., Shcherbyna, S.V., (2002) 17 th European Society for Biomaterials Conference Proceedings, , Barcelona; Krajewski, Malavoti, R., Piancatelli, A., (1996) Biomaterials, 17, p. 53; El-Ghannam, Ducheyne, P., Shapiro, I.M., (1997) Biomaterials, 18 (4); Takami, (1998) J. Biomed. Mater. Res., 40, p. 24; Puleo, A., Bizios, R., (1992) J. Biomed. Mater. Res., 26, p. 291; Dubois, C., Souchier, C., Couble, M.L., Exbrayat, P., Lissac, M., (1999) Biomat., 20, p. 1841; Green, J., Davies, M.C., Roberts, C.J., Tendler, S.J.B., (1997) Biomaterials, 18, p. 405; Haynes, C.A., Norde, W., (1994) Colloids and Surfaces B: Biointerfaces, 2, p. 517; Dias, G., Lopes, M.A., Gibson, I.R., Santos, J.D., (2002) 17 th Europ. Soc. for Biomat. Conf. Proc., , Barcelona; Chun, Na, S.W., Lee, J.H., Chung, J.P., Ryu, I.C., Kim, S.Y., (2002) Key Eng. Mat., 218-220, p. 149
Keywords: Adsorption; Bioceramics; Biodegradation; Calcium Compounds; Foetal bovine serum (FBS); Glass ceramics; Hard tissue; Ion exchange; Ionic strength; pH effects; Protein adhesion; Proteins; Tissue

Ribcage Boundary Delineation in Chest X-ray Images - Vinhais, C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2004)
We propose a method for segmenting the ribcage boundary of digital postero-anterior chest X-ray images. The segmentation is achieved by first defining image landmarks: the center of the ribcage and, using polar transformation from this point, two initial points belonging to the ribcage. A bank of Gabor filters (in analogy with the simple cells present in the human visual cortex) is used to obtain an orientation edges enhanced image. In this enhanced image, an edge following, starting from the landmarks previously determined, is performed for delineating the left and right sections of the ribcage. The complete segmentation is then accomplished by connecting these sections with the top section of the ribcage, obtained by means of spline interpolation. © Springer-Verlag 2004.
Keywords: Edge following; Gabor Filters; Polar image transform; Probabilistic genetic algorithm; Ribcage boundary segmentation

Study of a Silicate Cement for Dental Applications - Pereira, S.; Cavalheiro, J.; Branco, R.; Afonso, A.; Vasconcelos, M. (Key Engineering MaterialsKey Eng Mat, 2004)
Dental cements have a wide field of applications in clinical practice. The use as a base material is a very important one in dentistry. The aim of this study is to assess some relevant properties of a silicate cement (SC) developed for dental applications, comparing it with two other cements already commercialised, a zinc phosphate cement De Trey Zinc Cement Improved® (DT) and ProRootMTA®(MTA). Their compressive strength, dimensional changes and weight variation in water after setting, according to ISO standards were compared. The mean compressive strength of DT, MTA and SC were, respectively, 134MPa, 31MPa and 46MPa. There were no statistically significant differences for the three tested cements at the various time intervals, in respect to their weight variation or dimensional changes. However, there was a little loss of weight for DT (0.15%) and for MTA (3%) and a gain of 3% for the SC. Regarding the dimensional changes, all materials undergo little expansion, more significant in the MTA and in the SC samples of 2,07% and 0,4%, respectively. The new Silicate Cement, presented enough compressive strength, low weight variation, very small dimensional changes and good adaptation to the surface of dental cavity. For these reasons this new cement could be a valuable proposal as a base material for dental applications.
Conference code: 62053Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Pereira, S.; Fac. de Medicina Dentária, Universidade do Porto, R. Dr. Manuel Pereira da Silva, 4200-393 Porto, PortugalReferences: Craig, R.G., Rovers, J.M., (2002) Restorative Dental Materials. 9th Ed., pp. 593-627. , St Louis: Mosby;Gladwin, M., Bagby, M., (2000) Clinical Aspects of Dental Materials. First Edition, pp. 81-92. , Philadelphia: Lippincott Williams & Wilkins; Leinfelder, K.F., Changing Restorative Traditions: The Use of Bases and Liners (1994) JADA, 125, pp. 65-67; Macchi, R.L., (2000) Mat. Dentales. 3 a Ed., pp. 129-135. , Buenos Aires: Edit. Médica P.americana S.A; Wise, D.L., (1995) Encyclopedic Handbook of Biomaterials and Bioengineering, pp. 1398-1411. , New York: Marcel Dekver; Gordan, V.V., Mjör, I.A., Hucke, R.D., Smith, G.E., Effect of Different Liner Treatments on Postoperative Sensivity of Amalgam Restorations (1999) Quintessence Int, 30, pp. 55-59; Me, M., Nakai, H., Effect of Immersion in Water on Linear Expansion and Strength of Three Base/Liner Materials (1995) Dent Mater, 14, pp. 70-77; Leevailoj, C., Cochran, M.A., Matis, B.A., Moore, B.K., Platt, J.A., Microleakage of Posterior Packable Resin Composites with and without Flowable Liners (2001) Oper Dent, 26, pp. 302-307; Weiner, R.S., Weiner, L.K., Kugel, G., Teaching the Use of Bases and Liners: A Survey of the North American Dental Schools (1996) JADA, 127, pp. 1640-1645; Pereira, S., Branco, R., Cavalheiro, J., Afonso, A., Vasconcelos, M., (2003) Sealing Ability of a New Dental Base Material, , Bioeng; (1991) Specification for Dental Water-based Cements, , ISO 9917 (F)
Keywords: Biocompatibility; Body fluids; Ceramic materials; ceramics; Compressive Strength; Dental cement; Dental cements; Dental prostheses; Dimensional stability; Precipitation (chemical); Scanning electron microscopy; Silicate cements; Silicates; Stainless steel; Weight variation

Detection and validation of lung field contours on chest radiographs - Mendonça, A.M.; Alves Da Silva, J.; Campilho, A. (Proceedings of the IASTED International Conference on Biomedical EngineeringProc. IASTED Internat. Conf. Biomed. Eng., 2003)
The purpose of the research herein presented is the automatic detection of lung boundaries in posterior-anterior digital chest radiographs. The precise location of the two lungs is important in a computer-aided diagnosis system as it allows the reduction of the region under analysis, decreasing the computation time and facilitating data compression. Furthermore, it allows the delimitation of the search area, easing the selective tuning of the abnormalities detection algorithms. The results produced by the automatic method were validated by comparison with manual contours traced by an experienced radiologist. For this particular purpose, two programs with friendly interfaces were developed. The achieved comparison results demonstrate the good performance of the automatic method.
Conference code: 63063Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Mendonça, A.M.; INEB, Inst. de Engenharia Biomédica, Campus da FEUP, Rua Dr. Roberto Frias, s/n, 4200-465 Porto, Portugal; email: amendon@fe.up.ptReferences: Tsujii, O., Freedman, M., Mun, S., Automated segmentation of anatomic regions in chest radiographs using an adaptive-sized hybrid neural network (1998) Medical Physics, 25, pp. 998-1007;Armato III, S., Giger, M., MacMahon, H., Computerized detection of abnormal asymetry in digital lateral chest radiographs (1994) Medical Physics, 21, pp. 1761-1768; Armato III, S., Giger, M., Ashizawa, K., MacMahon, H., Automated lung segmentation in digital lateral chest radiographs (1998) Medical Physics, 25, pp. 1507-1520; Carrascal, F., Carreira, J., Souto, M., Automatic calculation of total lung capacity from automatically traced lung boundaries in posterior-anterior and lateral digital chest radiographs (1998) Medical Physics, 25, pp. 1118-1131; Ginneken, B., Romeny, B., Automatic segmentation of lung fields in chest radiographs (2000) Medical Physics, 27, pp. 2445-2455; Li, L., Zheng, Y., Kallergi, M., Clark, R., Improved method for automatic identification of lung regions on chest radiographs (2001) Academic Radiology, 8, pp. 629-638; Monteiro, M., Mendonça, A.M., Campilho, A., Lung field detection on chest radiographs (2002) Proceedings of VIIP02, IASTED International Conference on Visualization, Imaging and Image Processing, pp. 367-372. , J. Villanueva (ed): Spain Sponsors: IASTED
Keywords: Algorithms; automation; Biological organs; Chest radiographs; Computational time; Computer aided diagnosis; Computer-aided diagnosis; Data compression; Image analysis; Medical image processing; Medical imaging; Radiography; Regions of interest (ROI)

Optimal detection of symmetry axis in digital chest X-ray images - Vinhais, C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2003)
We present a method for detecting the axis of bilateral symmetry in a digital chest X-ray image and subsequently measuring the degree of symmetry of the image. The detection is achieved by analysing rotated-reflected digital chest X-ray images and it is posed as a global optimization problem solved with a probabilistic genetic algorithm (PGA). The global search is initially based on natural peak orientation information related to the orientation of the symmetry axis. Only a few generations of the PGA are needed to achieve convergence to all the images in the database. This method is applied directly on the intensity input image and does not require any prior segmentation. © Springer-Verlag Berlin Heidelberg 2003.
Keywords: image processing; Probabilistic genetic algorithm; Reflectional Symmetry

A probabilistic model for the cooperative modular neural network - Alexandre, L.A.; Campilho, A.; Kamel, M. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2003)
This paper presents a model for the probability of correct classification for the Cooperative Modular Neural Network (CMNN). The model enables the estimation of the performance of the CMNN using parameters obtained from the data set. The performance estimates for the experiments presented are quite accurate (less than 1% relative difference). We compare the CMNN with a multi-layer perceptron with equal number of weights and conclude that the CMNN is preferred for complex problems. We also investigate the error introduced by one of the CMNN voting strategies. © Springer-Verlag Berlin Heidelberg 2003.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Alexandre, L.A.; Departamento de Informática, Universidade da Beira Interior, Covilhã, Portugal; email: lfbaa@di.ubi.ptReferences: Auda, G., Kamel, M., Modular neural network classifiers: A comparative study (1998) J. Intel. Robotic Systems, pp. 117-129;De Bollivier, M., Gallinari, P., Thiria, S., Cooperation of neural nets and task decomposition (1991) Int. Joint Conf. on Neural Networks, 2, pp. 573-576. , Seattle, USA; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, pp. 79-87; Jacobs, R., Peng, F., Tanner, M., A bayesian approach to model selection in hierarchical mixtures-of-experts architectures (1997) Neural Networks, 10, pp. 231-241; Wanas, N., Kamel, M., Auda, G., Karray, F., Feature-based decision aggregation in modular neural network classifiers (1999) Pattern Recognition Letters, 20, pp. 1353-1359; Alexandre, L., Campilho, A., Kamel, M., Combining independent and unbiased classifiers using weighted average (2000) Proceedings of the 15th International Conference on Pattern Recognition, 2, pp. 495-498. , Barcelona, Spain, IEEE Press; Alexandre, L., Campilho, A., Kamel, M., On combining classifiers using sum and product rules (2001) Pattern Recognition Letters, 22, pp. 1283-1289; Kittler, J., Hatef, M., Duin, R., Matas, J., On combining classifiers (1998) IEEE Trans. PAMI, 20, pp. 226-239; Auda, G., Kamel, M., CMNN: Cooperative modular neural networks for pattern recognition (1997) Pattern Recognition Letters, 18, pp. 1391-1398; Auda, G., Kamel, M., Raafat, H., Voting schemes for cooperative neural network classifiers (1995) IEEE Int. Conference on Neural Networks, 3, pp. 1240-1243. , Australia

Real-time implementation of an optical flow algorithm - Correia, M.V.; Campilho, A.C. (Proceedings - International Conference on Pattern RecognitionProc. Int. Conf. Pattern Recognit., 2002)
This paper presents the implementation of an optical flow algorithm on a pipeline image processor. The overall optical flow computation method is presented and evaluated on a common set of image sequences. Results are compared to other implementations according to two different error measures. Due to its deterministic architecture, this implementation achieves very low computation delays that allow it to operate at standard video frame-rate and resolutions. It compares favorably to recent implementations in parallel hardware. © 2002 IEEE.
Cited By (since 1996): 29Export Date: 21 November 2012Source: ScopusCODEN: PICRELanguage of Original Document: EnglishCorrespondence Address: Correia, M.V.; Instituto de Engenharia Biomédica, Faculdade de Engenharia, Dept. Eng. Electrotécnica e de Computadores, R. Dr. Roberto Frias, 4200-465 Porto, Portugal; email: mcorreia@fe.up.ptReferences: Barron, J.L., Fleet, D.J., Beauchemin, S.S., Performance of optical flow techniques (1994) International Journal of Computer Vision, 12 (1), pp. 43-77;Correia, M.V., Campilho, A.C., Santos, J.A., Nunes, L.B., Optical flow techniques applied to the calibration of visual perception experiments (1996) Proceedings of 13th International Conference on Pattern Recognition, ICPR '96, pp. 498-502. , Vienna, Austria, August; Fleet, D.J., Langley, K., Recursive filters for optical flow (1995) IEEE Transactions on Pattern Analysis and Machine Intelligence, 17 (1), pp. 61-67. , January; Fleury, M., Clark, A.F., Downton, A.C., Evaluating optical-flow algorithms on a parallel machine (2001) Image and Vision Computing, 19, pp. 131-143; Lin, T., Barron, J.L., Image reconstruction error for optical flow (1994) Proceedings of Vision Interface'94, pp. 73-80. , Banff National Park, Canada, May; Liu, H., Hong, T.-H., Herman, M., Camus, T., Accuracy vs efficiency trade-offs in optical flow algorithms (1998) Computer Vision and Image Understanding, 72 (3), pp. 271-286. , December; Lucas, B.D., (1984) Generalized Image Matching by the Method of Differences, , PhD thesis, Carnegie Mellon University; Olson, T.J., Taylor, J.R., Lockwood, R.J., Programming a pipelined image processor (1996) Computer Vision and Image Understanding, 64 (3), pp. 351-367. , November; Santos, J., Noriega, P., Correia, M., Campilho, A., Albuquerque, P., (2000) Object Motion Segmentation and Optical Flow Contrast, , Relatórios de investigação C.E.E.P., Universidade do Minho, Braga; Simoncelli, E.P., (1993) Distributed Representation and Analysis of Visual Motion, , PhD thesis, Massachusetts Institute of Technology, January
Keywords: Algorithms; Computational methods; Image analysis; Image processors; Image sequences; Optical flow algorithm; Optical flows; Real time systems; Video frame-rate; Video signal processing

Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and support the osteogenic differentiation of human bone marrow cells - Amaral, M.; Costa, M.A.; Lopes, M.A.; Silva, R.F.; Santos, J.D.; Fernandes, M.H. (BiomaterialsBiomaterials, 2002)
The in vitro osteocompatibility of a novel Si 3N 4-bioglass composite (70-30% weight proportion) with improved mechanical properties (fracture toughness=4.4MPam 1/2; bending strength=383±47MPa) is reported. Immersion of the composite samples in culture medium (30min to 7 days) resulted in rapid protein adsorption to the surface and, also, dissolution of the intergranular phase of bioglass (time-dependent process) with the formation of different size cavities. "As-received" and pre-treated material samples presented a similar behaviour concerning the proliferation of MG63 osteoblast-like cells, evaluated during a 5-day culture period. Seeded materials showed a higher cell growth rate as compared to cultures performed on the standard plastic culture plates. To assess the osteogenic potential of the composite, "as-received" material samples were seeded with human bone marrow cells and cultured for 35 days in experimental conditions that favour the development of the osteoblastic phenotype. The cell adhesion process was similar to that observed in control cultures. Cells successfully adapted to the irregularities of the surface and were able to grow towards inside the cavities; in addition, osteogenic differentiation occurred with the formation of abundant cell-mediated mineralised deposits. Results suggest that this Si 3N 4-bioglass composite seems to be a promising candidate for high-stress medical applications. © 2002 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 31Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(02)00249-1PubMed ID: 12361631Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Universidade do Porto, Rua Dr Manuel Pereira da Silva, 4200-393 Porto, Portugal; email: mhrf@portugalmail.ptChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Calcium, 7440-70-2; Phosphorus, 7723-14-0; Silicon Compounds; silicon nitride, 12033-89-5References: Amaral, M., Lopes, M.A., Silva, R.F., Santos, J.D., Densification route and mechanical properties of Si 3N 4-bioglass biocomposites (2002) Biomaterials, 23, pp. 857-862;Kue, R., Sahrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201; Howlett, C., McCartney, E., Ching, W., The effects of silicon nitride ceramic on rabbit skeletal cells and tissues (1989) Clin Orthop, 244, pp. 296-301; Hench, L.L., Biomaterials: A forecast for the future (1998) Biomaterials, 19, pp. 1419-1423; Radin, S., Ducheyne, P., Falaize, S., Hammond, A., In vitro transformation of bioactive glass granules into Ca-P shells (2000) J Biomed Mater Res, 49, pp. 264-272; Santos, J.D., Amaral, M., Oliveira, S.M., Lopes, M.A., Silva, R.F., Silicon Nitride - Bioglass ® 45S5 composite for biomedical applications (2001) Key Eng Mater, 192-195, pp. 589-592; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Maniatopoulos, C., Sodek, J., Melcher, A., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblastic phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 43, pp. 213-221; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Stein, G.S., Lian, J.B., Stein, J.L., Van Wijnem, A.J., Frenkel, B., Montecino, M., Mechanisms regulating osteoblast proliferation and differentiation (1996) Principles of bone biology, pp. 69-86. , J.P. Bilizikian, L.G. Raisz, & G.A. Rodan. New York: Academic Press; Fernandes, M.H., Costa, M.A., Carvalho, G.S., Mineralization in serially passaged human alveolar bone cells (1997) J Mater Sci: Mater Med, 8, pp. 61-65; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part II: Effect of ascorbic acid β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Costa, M.A., Fernandes, M.H., Long-term effects of parathyroid hormone, 1,25-dihydroxyvitamin D3 and dexamethasone on the cell growth and functional activity of human osteogenic alveolar bone cell cultures (2000) Pharmacol Res, 42, pp. 345-353; Coelho, M.J., Trigo Cabral, A., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part I: Osteoblastic differentiation of serially passaged human bone marrow cells cultured in α-MEM and in DMEM (2000) Biomaterials, 21, pp. 1087-1094; Aubin, J.E., Liu, F., The osteoblastic lineage (1996) Principles of bone biology, pp. 51-67. , J.P. Bilizikian, L.G. Raisz, & G.A. Rodan. New York: Academic Press; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P 2O 5 glass hydroxyapatite double layer plasma sprayed coatings: In vitro bioactivity evatuation (1999) J Biomed Mater Res, 45, pp. 376-383; Kokubo, T., Ito, S., Huang, Z.T., Hayashi, T., Sakka, S., Ca, P-rich layer formed on high-strenght bioactive glass-ceramic A-W (1990) J Biomed Mater Res, 24, pp. 331-343; Daculsi, G., Legeros, R.Z., Heughebaert, M., Barbieux, I., Formation of carbonato-apatite crystals after implantation of calcium phosphate ceramics (1990) Calcif Tissue Int, 46 (1), pp. 20-27; Neo, M., Nakamura, T., Ohtsuki, C., Kokubo, T., Yamamuro, T., Apatite formation on three kinds of bioactive material at an early stage in vivo: A comparative study by transmission electron microscopy (1993) J Biomed Mater Res, 27, pp. 999-1006; Bagambisa, F.B., Joos, U., Schilli, W., Mechanisms and structure of the bond between bone and hydroxyapatite ceramics (1993) J Biomed Mater Res, 27, pp. 1047-1055; Bagambisa, F.B., Kappert, H.F., Schilli, W., Interfacial reactions of osteoblast to dental and implant materials (1994) J Oral Maxillofac Surg, 52, pp. 52-56; De Bruijn, J.D., Van Blitterswijk, C.A., Davies, J.E., Initial bone matrix formation at the hydroxyapatite interface (1995) J Biomed Mater Res, 29 (1), pp. 89-99; Hulshott, J.E.G., Van Kijk, K., De Ruijter, J.E., Rietveld, F.J.R., Ginsel, L.A., Jansen, J.A., Interfacial phenomena: An in vitro study of the effect of calcium phosphate (Ca-P) ceramic on bone formation (1998) J Biomed Mater Res, 40, pp. 464-474; De Santis, D., Guerriero, C., Nocini, P.F., Vangersbock, A., Richard, G., Gotte, P., Armato, U., Adult human bone cells from jaw bones cultured on plasma-sprayed or polished surfaces of titanium or hydroxyapatite discs (1996) J Mater Sci Mater Med, 7, pp. 21-28; Anselme, K., Sharrock, P., Hardouin, P., Dard, M., In vitro growth of human adult bone-derived cells on hydroxyapatite plasma-sprayed coatings (1997) J Biomed Mater Res, 34, pp. 247-259; Ferraz, M.P., Fernandes, M.H., Trigo Cabral, A., Santos, J.D., Monteiro, F.J., In vitro growth and differentiation of osteoblastic-like human bone marrow cells on a glass reinforced hydroxyapatite plasma-speayed coating (1999) J Mater Sci: Mater Med, 10, pp. 567-576; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of pre-immersion on the biocompatibility of glass-reinforced hydroxyapatite plasma sprayed coatings (2000) Biomaterials, 21, pp. 813-820; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., HA and double-layer HA/CaO-P 2O 5 glass coatings: Influence of chemical composition on human bone marrow cells osteoblastic behaviour (2001) J Mater Sci: Mater Med, 7, pp. 628-638; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Direct and indirect effects of P 2O 5-glass reinforced hydroxyapatite composites on the growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Gwynn, I.A.P., Cell biology at interfaces (1994) J Mater Sci Mater Med, 5, pp. 357-360; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681; KirkPatrick, C.J., Wagner, M., Kohler, H., Bittinger, F., Otto, M., Klein, C.L., The cell and molecular biological approach to biomaterial research: A perspective (1997) J Mater Sci Mater Med, 8, pp. 131-141; Verrier, S., Bareille, R., Rovira, A., Dard, M., Amedee, J., Human osteoprogenitor responses to orthopaedic implant: Mechanism of cell attachment and cell adhesion (1996) J Mater Sci Mater Med, 7, pp. 46-51; Dee, K.C., Rueger, D.C., Andersen, T.T., Bizios, R., Conditions which promote mineralization at the bone-implant interface: A model for in vitro study (1996) Biomaterials, 17, pp. 209-215; Anseme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Iost, A., Hardouin, P., Qualitative and quantitative study of human osteoblast adhesion on materials with various surface roughnesses (2000) J Biomed Mater Res, 49, pp. 155-166; Diniz, M.G., Soares, G.A., Coelho, M.J., Fernandes, M.H., Surface topography modulates the osteogenesis in human bone marrow cell cultures grown on titanium samples prepared by a combination of mechanical and acid treatments (2002) J Mater Sci: Mater Med, 13, pp. 421-432; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Min, 14, pp. 27-40; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralization of osteoid nodules in vitro (1992) Bone Min, 17, pp. 15-29
Keywords: 3N; 4-bioglass composite; Adhesion; Adsorption; alkaline phosphatase; article; Biocompatibility; Bioglass; Biomaterials; bone marrow cell; Bone Marrow Cells; Calcium; cell adhesion; Cell Culture Techniques; cell differentiation; Cell Division; cell growth; cell proliferation; composite material; controlled study; culture medium; Dissolution; glass; Growth kinetics; human; Human bone marrow cells; human cell; Humans; immersion; in vitro study; Mechanical properties; MG63 osteoblast-like cells; Microscopy, Electron, Scanning; osteoblast; Osteoblasts; Osteocompatibility; Osteogenic differentiation; phenotype; phosphorus; priority journal; Proteins; rigidity; Si; Silicon compounds; silicon derivative; surface property; tensile strength; Time Factors

Silicon and iron levels in tissues of animals treated with a "ferrimagnetic ceramic" with oncotherapeutic potential (anti-tumor) value - Almeida, T.; Soares, M.E.; Cavalheiro, J.; Bastos, M.D.L. (Journal of Trace Elements in Medicine and BiologyJ. Trace Elem. Med. Biol., 2002)
The stability in a biological environment of an injectable cement with oncotherapeutic potential - consisting of a glass powder of SiO 2 (35.6%), CaO (42.4%), P 2O 5 (17%), Na 2O (5%) and 30% of its weight of Fe 3O 4 dissolved in (NH 4) 2HPO 4 plus NH 4H 2PO 4 - was evaluated referring to the release of silicon and iron. The experimental model was the rat, and organs (liver, kidney, spleen, lung, heart, and brain) of the implanted and control animals were collected for quantification of these elements by electrothermal atomization atomic absorption spectrometry methods. In most of the analysed organs no significant difference in the contents of silicon and iron between the implanted and the control animals was found.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JTEBFdoi: 10.1016/S0946-672X(02)80054-2PubMed ID: 12530589Language of Original Document: EnglishCorrespondence Address: Bastos, M.D.L.; Toxicology Department, Faculty of Pharmacy, University of Porto, Rua Aníbal Cunha 164, 4050 Porto, PortugalChemicals/CAS: calcium oxide, 1305-78-8; iron, 14093-02-8, 53858-86-9, 7439-89-6; phosphorus pentoxide, 1314-56-3; silicon dioxide, 10279-57-9, 14464-46-1, 14808-60-7, 15468-32-3, 60676-86-0, 7631-86-9; silicon, 7440-21-3; Biocompatible Materials; Ceramics; Iron, 7439-89-6; Silicon, 7440-21-3; Tissue ExtractsReferences: Rofstad, E.K., Brustad, T., Primary and secondary cell death in human melanoma xenografts following hyperthermic treatment (1986) Cancer Res., 46, pp. 355-361;Nishimura, Y., Shibamoto, Y., Jo, S., Akuta, K., Hiraoka, M., Takahashi, M., Abe, M., Relationship between heat-induced vascular damage and thermosensitivity in four mouse tumors (1988) Cancer Res., 48, pp. 7226-7230; Brown, S.L., Hunt, J.W., Hill, R.P., Differential thermal sensitivity of tumour and normal tissue microvascular response during hyperthermia (1992) Int. J. Hyperthermia, 8, pp. 501-514; Dudar, T.E., Jain, R.K., Differential response of normal and tumor microcirculation to hyperthermia (1984) Cancer Res., 44, pp. 605-612; Hill, S.A., Smith, K.A., Denekamp, J., Reduced thermal sensitivity of the vasculature in a slowly growing tumour (1989) Int. J. Hyperthermia, 5, pp. 359-370; Bicher, H.I., Hetzel, F.W., Sandhu, T.S., Frinak, S., Vaupel, P., O'Hara, M.D., O'Brien, T., Effects of Hyperthermia on normal and tumor microenvironment (1980) Radiology, 137, pp. 523-530; Song, C.W., Kang, M.S., Rhee, J.G., Levitt, S.H., The effect of hyperthermia on vascular function, pH, and cell survival (1980) Radiology, 137, pp. 795-803; Emami, B., Song, C.W., Physiological mechanisms in hyperthermia: A review (1984) Int. J. Radiation Oncology Biol. Phys., 10, pp. 289-295; Cavalheiro, J., Vasconcelos, M., Afonso, A., Branco, R., Ferrimagnetic and biocompatible cement for tumours thermotherapy (1996) Bioceramics, 9, pp. 243-246; Coury, A.J., Levy, R.J., McMillin, C.R., Pathak, Y., Ratner, B.D., Schoen, F.J., Williams, D.F., Williams, R.L., Degradation of materials in the biological environment (1996) Biomaterials Science, pp. 243-260. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE (Eds). Academic Press, San Diego; Williams, D.F., Williams, R.L., Degradative effects of the biological environment on metals and ceramics (1996) Biomaterials Science, pp. 260-267. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE (Eds). Academic Press, San Diego; Van Dyck, K., Robberecht, H., Van Cauwenbergh, R., Deelstra, H., Arnaud, J., Willemyns, L., Benijts, F., Uytterhoeven, M., Spectrometric determination of silicon in food and biological samples: An interlaboratory trial (2000) J. Anal. At. Spectrom., 15, pp. 735-741; Adler, A.J., Etzion, Z., Berlyne, G.M., Uptake, distribution, and excretion of 31silicon in normal rats (1986) Am. J. Physiol., 251, pp. E670-E673; Beattie, J.H., Avenell, A., Trace element nutrition and bone metabolism (1992) Nutrition Res. Rev., 5, pp. 167-188; Robinson, C.H., Lawler, M.R., Mineral elements (1982) Normal and Therapeutic Nutrition, 16 th Edition, pp. 131-160. , Robinson CH, Lawler MR (Eds). Macmillan Publishing Co., Inc., New York, Collier Macmillan Publishers, London; Sorond, F.A., Ratan, R.R., Ironing-out mechanisms of neuronal injury under hypoxic-ischemic conditions and potential role of iron chelators as neuroprotective agents (2000) Antioxid. Redox Signal, 2, pp. 421-436; Bonkovsky, H.L., Lambrecht, R.W., Iron-induced liver injury (2000) Clin. Liver Dis., 4, pp. 409-429; Bartfay, W.J., Bartfay, E., Iron-overload cardiomyopathy: Evidence for a free radical-mediated mechanism of injury and dysfunction in a murine model (2000) Biol. Res. Nurs., 2, pp. 49-59; Kang, J.L., Pack, I.S., Lee, H.S., Castranova, V., Enhancement of nuclear factor-KB activation and protein tyrosine phosphorylation by a tyrosine phosphatase inhibitor, pervanadate, involves reactive oxygen species in silica-stimulated macrophages (2000) Toxicology, 151, pp. 81-89
Keywords: animal model; animal tissue; Animalia; Animals; article; atomic absorption spectrometry; Biocompatible Materials; calcium oxide; cancer therapy; cement; ceramics; controlled study; experimental model; Ferrimagnetic ceramic; heat; Humans; implant; Iron; Magnetics; materials testing; Neoplasms; nonhuman; Oncotherapy; phosphorus pentoxide; powder; priority journal; Prostheses and Implants; rat; Rats; Reproducibility of Results; Silicon; silicon dioxide; tissue distribution; Tissue Extracts

On combining classifiers using sum and product rules - Alexandre, L.A.; Campilho, A.C.; Kamel, M. (Pattern Recognition LettersPattern Recogn. Lett., 2001)
This paper presents a comparative study of the performance of arithmetic and geometric means as rules to combine multiple classifiers. For problems with two classes, we prove that these combination rules are equivalent when using two classifiers and the sum of the estimates of the a posteriori probabilities is equal to one. We also prove that the case of a two class problem and a combination of two classifiers is the only one where such equivalence occurs. We present experiments illustrating the equivalence of the rules under the above mentioned assumptions. © 2001 Elsevier Science B.V. All rights reserved.
Cited By (since 1996): 51Export Date: 21 November 2012Source: Scopusdoi: 10.1016/S0167-8655(01)00073-3Language of Original Document: EnglishCorrespondence Address: Alexandre, L.A.; INEB-Inst. de Engenharia Biomedica, Rua Dr. Roberto Frias s/n, Porto 4200-465, Portugal; email: lfbaa@noe.ubi.ptReferences: Alexandre, L., Campilho, A., Kamel, M., Combining independent and unbiased classifiers using weighted average (2000) Proc. 15th Internat. Conf. on Pattern Recognition, 2. , IEEE Press, Barcelona, Spain;Bishop, C., (1995) Neural Networks for Pattern Recognition, , Oxford University Press, Oxford; Blake, C., Keogh, E., Merz, C., (1998) UCI Repository of Machine Learning Databases, , http://www.ics.uci.edu/~mlearn/MLRepository.html; Demuth, H., Beale, M., (1998) Neural Network Toolbox User's Guide, , The MathWorks, Inc; Hansen, L., Salamon, P., Neural network ensembles (1990) IEEE Trans. PAMI, 12 (10), pp. 993-1001; Hashem, S., Optimal linear combinations of neural networks (1997) Neural Networks, 10 (4), pp. 599-614; Kittler, J., Hatef, M., Duin, R., Combining classifiers (1996) Proc. Internat. Conf. on Pattern Recognition'96; Kittler, J., Hatef, M., Duin, R., Matas, J., On combining classifiers (1998) IEEE Trans. PAMI, 20 (3), pp. 226-239; Opitz, D., Maclin, R., Popular ensemble methods: An empirical study (1999) J. Artif. Intell. Res, 11, pp. 169-198; Richard, M., Lippmann, R., Neural network classifiers estimate Bayesian a posteriori probabilities (1991) Neural Comput, 3, pp. 461-483; Rogova, G., Combining the results of several neural network classifiers (1994) Neural Networks, 7 (5), pp. 777-781; Tax, D., Duin, R., Breukelen, M., Comparison between product and mean classifier combination rules (1997) Workshop on Statistical Techniques in Pattern Recognition, , Prague Czech Republic; Ueda, N., Optimal linear combination of neural networks for improving classification performance (2000) IEEE Trans. PAMI, 22 (2), pp. 207-215
Keywords: artificial neural network; Classification; Classifier fusion; Combinatorial mathematics; Combining classifiers; Equivalence classes; Estimation; K nearest-neighbours; Multiple classifiers; Neural networks; Pattern recognition; probability

Starch based copolymers as biomaterials in vivo biocompatibility study - Souillac, V.; Fricain, J.C.; Bareille, R.; Reis, R.L.; Chauveaux, D.; Baquey, C. (Key Engineering MaterialsKey Eng Mat, 2001)
This report is a preliminary study of a starch-based copolymer that was used as a bone substitute. The interest of this study was to evaluate the possibility of using a hydrophilic material as a bone substitute. We studied this copolymer alone, after phosphorylation, and after hydroxyapatite coating.
Conference code: 57760Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Souillac, V.; Universite Bordeaux 2, Bordeaux, FranceReferences: Hollinger, J.O., Brekke, J., Gruskin, E., Lee, D., (1996) Clin. Orthop., 324, p. 55;Nizard, R., Bizot, P., Sedel, L., (1996) Encycl. Med. Chir., Orthopédie-traumatologie, 44 (3). , 20p; Delécrin, J., Dupraz, A., Passuti, N., (1996) Cahiers D'enseignement de la SOFCOT, 57, p. 97; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1996) J. Polym. Adv. Technol., 7, p. 784; Kokubo, T., Hata, K., Nakamura, T., Yamamuro, T., (1991) Bioceramics, 4, p. 113. , UK; Reis, R.L., Cunha, A.M., Fernandes, M.H., (1997) J. Mater. Sci. : Mater, in Medecine, 8, p. 897; Vilamitjana-Amedee, J., Bareille, R., Rouais, F., Harmand, M.F., (1993) In Vitro Cell Dev. Biol., 29, p. 699; Parish, C.R., Mullbacher, A., (1983) J. Immunol. Meth., 58, p. 225; Mosmann, T., (1983) J. Immunol. Meth., 65, p. 55; Koshino, T., Kubota, W., Morii, T., (1995) Biomaterials, 16, p. 125; Pasquier, G., Flautre, B., Blary, M.C., Anselme, K., Hardouin, P., (1996) Journal of Materials Science, 7, p. 683; Nagano, M., Kitsugi, T., Nakamura, T., Kokubo, T., Tanahashi, M., (1996) J. Biomed. Mater. Res., 31, p. 487; Miyamoto, T., Takahashi, S., Ito, H., Inagaki, H., (1989) J. Biomed. Mater. Res., 23, p. 125
Keywords: Biocompatibility; Bone; Bone substitute; Copolymers; Ethanol; Ethylene; hydroxyapatite; Hydroxyapatite coating; Implants (surgical); orthopedics; Phosphates; phosphoric acid; Phosphorylation; Starch; Substitution reactions; Vinyl resins

A computational model of visual cortex receptive fields using spatio-temporal filters - Milanova, M.G.; Elmaghraby, A.S.; Wachowiak, M.P.; Campilho, A. (Proceedings of the IEEE/EMBS Region 8 International Conference on Information Technology Applications in Biomedicine, ITABProc IEEE EMBS Reg 8 Int Conf Inf Technol Appl Biomed ITAB, 2000)
It is known that neurons in the primary visual cortex are characterized by receptive fields that are selective for specific spatial orientations. It is believed that the sense of object motion and velocity are also related to these fields, as objects in natural scenes are represented by a sparse set of statistically independent components, such as edges. Currently, computational models of receptive fields consider only spatial components, and thus cannot account for time-varying sensory stimuli. In this paper, a model based on independent components analysis and cellular neural networks is proposed. This approach extends existing models to incorporate temporal aspects of sequences of images of natural scenes.
Conference code: 58015Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Milanova, M.G.; INEB, Inst. of Biomedical Engineering, University of Porto, Praça Coronel Pacheco, 1 4050 Porto, Portugal; email: milanova@ineb.fe.up.ptReferences: Hubel, D.H., Wiesel, T.N., Receptive fields, binocular interaction, and functional architecture in the cat's visual cortex (1962) Journal of Physiology (London), 160, pp. 106-154;DeAngelis, G.C., Ohzawa, I., Freeman, R.D., Receptive-field dynamic in the central visual pathways (1995) Trends in Neuroscience, 18, pp. 451-458; Atick, J., Redlich, N., What does the retina know about natural scenes? (1992) Neural Computation, 4, pp. 196-210; Barlow, H.B., What is the computational goal of the neocortex? (1994) Large-Scale Neuronal Theories of the Brain, pp. 1-22. , C. Koch and J. L. Davis, eds, Cambridge, MA, MIT Press; Olshausen, B.A., Field, D.J., Emergence of simple-cell receptive field properties by learning a sparse code for natural images (1996) Nature, 381, pp. 607-609; Rao, R.P.N., Ballard, D.H., Dynamic model of visual recognition predicts neural response properties in the visual cortex (1997) Neural Computation, 9, pp. 721-763; Olshausen, B.A., (2000) Sparse coding of time-varying natural images, , http://psyweb.ucdavis.edu/olshausen; Oja, E.E., Neural networks, principal components and subspaces (1989) International Journal of Neural Systems, 1, pp. 61-68; Field, D.J., What is the goal of sensory coding? (1994) Neural Computation, 6, pp. 559-601; Field, D.J., Relations between the statistics of natural images and the response properties of cortical cells (1987) J. Opt. Soc. Am.A, 4, pp. 2379-2394; Bell, A.J., Sejnowski, T.J., The independent components of natural scenes are edge filters (1997) Vision Research, 37, pp. 3327-3338; Smith, A.T., Snowdon, R.S., (1994) Visual Detection of Motion, , Academic Press Inc., San Diego; Zemel, R.S., Sejnowski, T.J., A model for encoding multiple object motions and self-motion in area MST of primate visual cortex (1998) Journal of Neuroscience, 18, pp. 531-547; Van Hateren, J.H., Ruderman, D.L., Independent component analysis of natural image sequences yields spatio-temporal filters similar to simple cells in primary visual cortex (1998) Proc. Royal Soc. London B, 265, pp. 2315-2320; Jones, J.P., Palmer, L.A., The two-dimensional spatial structure of simple receptive fields in cat striate cortex (1987) Journal of Neurophysiology, 58, pp. 1187-1211; Jones, J.P., Palmer, L.A., An Evaluation of the two-dimensional Gabor filter model of simple receptive fields in cat striate cortex (1987) Journal of Neurophysiology, 58, pp. 1233-1258; Jones, J.P., Stepnoski, A., Palmer, L.A., The two-dimensional spectral structure of simple receptive fields in cat striate cortex (1987) Journal of Neurophysiology, 58, pp. 1212-1232; Lewicki, M.S., Olshausen, B.A., Probabilistic framework for the adaptation and comparison of image codes (1999) Journal of the Optical Society of America, 16, pp. 1587-1601; Chua, L.O., Yang, L.L., Cellular Neural Networks: Theory and Applications (1988) IEEE Trans. on Circuits and Systems, 35, pp. 1257-1290 Sponsors: IEEE
Keywords: Cellular neural networks; Computational methods; ICA; Independent component analysis; Mathematical models; Neurology; Receptive fields; Receptive fields (RF); Spatial filters; Spatio-temporal filters; Visual modeling

Fetal heart rate baselines in twins: Interobserver agreement in antepartum estimation - Bernardes, J.; Costa-Pereira, A.; Calejo, L.; Ayres-de-Campos, D.; Patrício, B.; Pereira-Leite, L. (Journal of Reproductive Medicine for the Obstetrician and GynecologistJ. Reprod. Med. Obstet. Gynecol., 2000)
OBJECTIVE: To assess interobserver agreement in antepartum estimation of fetal heart rate (FHR) baselines in twins. STUDY DESIGN: Two residents and one specialist in obstetrics and gynecology, all with special interest in FHR monitoring, independently estimated baselines in 162 consecutive antepartum FHR tracings recorded in 24 twins. Tracings were obtained with a dual-channel fetal monitor for the simultaneous recording of both twins' heart rates. Baselines were estimated, as single values corresponding to the mean of the lowest stable FHR segment, in the absence of fetal movements and uterine contractions, within physiologic limits (110-150 beats per minute [bpm]). If these criteria were not met, the possibility of persistent bradycardia or tachycardia was considered, and if this was confirmed in a tracing with at least 40 minutes, a baseline < 110 or > 150 bpm was chosen. Interobserver agreement was assessed by the proportions of agreement (PA), kappa statistic (K) and intraclass correlation coefficient (ICCC), with 95% confidence intervals (CIs). RESULTS: Interobserver agreement was excellent, with a PA of 0.90 (95% CI: 0.89-0.91), K of 0.88 (95% CI: 0.84-0.92) and ICCC of 0.91 (95% CI: 0.88-0.94). CONCLUSION: Interobserver agreement in antepartum estimation of fetal heart rate baselines in twins was excellent with the baseline concept used in this study.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JRPMAPubMed ID: 10710739Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Depto. de Ginecologia e Obstetricia, Faculdade de Medicina do Porto, Al. Prof. Hernani Monteiro, 4200 Porto, Portugal; email: Jbernardes@mail.telepac.ptReferences: Sherman, S.J., Kovacs, B.W., Medearis, A.L., Nonstress test assessment of twins (1992) J Reprod Med, 37, pp. 804-808;Grant, J.M., The fetal heart rate is normal, isn't it?: Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Cibils, L.A., On intrapartum fetal monitoring (1996) Am J Obstet Gynecol, 174, pp. 1382-1389; Bernardes, J., Costa-Pereira, A., Ayres-De-Campos, D., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57, pp. 33-37; Bernardes, J., Costa-Pereira, A., Van Geijn, H.P., A more objective fetal heart rate baseline estimation (1996) Br J Obstet Gynaecol, 103, pp. 714-715; Bernardes, J., Ayres-De-Campos, D., Costa-Pereira, A., Objective computerized fetal heart rate analysis (1998) Int J Gynecol Obstet, 62, pp. 141-147; Bland, J.M., Altman, D.G., Statistical methods for assessing two methods of clinical measurement (1986) Lancet, 11, pp. 307-310; Armitage, P., Berry, G., (1994) Statistical Methods in Medical Research, pp. 273-276. , Oxford, Blackwell Science Ltd; Khan, K.S., Chien, P.F.W., Honest, M.R., Evaluating measurement variability of clinical investigations: The case of ultrasonic estimation of urinary bladder volume (1997) Br J Obstet Gynaecol, 104, pp. 1036-1043; Devoe, L.D., Carlton, E., Prescott, P., Neural network prediction of nonstress test results: How often should we perform nonstress tests? (1995) Am J Obstet Gynecol, 173, pp. 1128-1131; Bernardes, J., Ayres De Campos, D., Costa-Pereira, A., Baseline estimation in typical fetal heart rate patterns using different computerized methods (1997) Acta Obstet Gynecol Scand (Suppl), 76, p. 56;
Keywords: adult; article; clinical article; Electrocardiography; Female; Fetal heart rate; Fetal monitoring; fetus; fetus heart rate; fetus monitoring; Heart rate variability; Heart Rate, Fetal; human; Humans; Internship and Residency; observer variation; Obstetrics; Pregnancy; Prenatal Care; priority journal; Professional Competence; Twins

Enhancement of the mechanical properties of a high-density polyethylene - Kalay, G.; Sousa, R.A.; Reis, R.L.; Cunha, A.M.; Bevis, M.J. (Journal of Applied Polymer ScienceJ. Appl. Polym. Sci., 1999)
This paper describes the process optimization in injection molding of high-density polyethylene (HDPE). Both conventional injection molding and shear controlled orientation (SCORIM) were employed in processing. The process optimization was based on design of experiments and complemented with analysis of variance. Mechanical characterization was carried out by tensile testing. Wide-angle X-ray diffraction and differential scanning calorimetry were used for the structural characterization of the moldings. High-density polyethylene exhibits 7.2 GPa Young's modulus and 155 MPa of ultimate tensile strength following the application of SCORIM processing. These results account for a fourfold increase in Young's modulus and a fivefold increase in ultimate tensile strength compared to conventional injection molding. The maintenance of toughness while enhancing stiffness and strength of the SCORIM moldings is attributable to an oriented morphology developed during shear flow, i.e., shish-kebab structure. The frequency of shearing action has the strongest influence on the morphology development. It is also demonstrated that the studied parameters are very much interdependent. It is possible to achieve substantial gains in mechanical properties of HDPE in SCORIM processing without causing a substantial increase in cycle time.
Cited By (since 1996): 48Export Date: 21 November 2012Source: ScopusCODEN: JAPNAdoi: 10.1002/(SICI)1097-4628(19990919)73:12<2473::AID-APP16>3.0.CO;2-OLanguage of Original Document: EnglishCorrespondence Address: Kalay, Gurhan; Brunel Univ, Middlesex, United KingdomReferences: Kalay, G., Allan, P.S., Bevis, M.J., (1997) Kunststoffe, 87, p. 6;Kalay, G., Bevis, M.J., (1997) J Polym Sci Polym Phys, 35, p. 241; Kalay, G., Bevis, M.J., (1997) J Polym Sci Poly Phys, 35, p. 265; Kalay, G., Bevis, M.J., (1997) J Polym Sci Polym Phys, 35, p. 415; Kalay, G., Ogbonna, C.I., Allan, P.S., Bevis, M.J., (1995) Trans IChemE Part A Chem Eng Res Design, 73, p. 798; Keller, A., Kolnaar, H., (1997) Mat Sci Technol, 18, p. 191; Allan, P.S., Bevis, M.J., (1987), British Patent 2170-140-BAllan, P.S., Bevis, M.J., (1990) Composites Manufact, 1, p. 79; Wang, L., Allan, P.S., Bevis, M.J., (1995) Plastics Rubber Composites Process Appl, 23, p. 139; Gil, E.M., Kalay, G., Allan, P.S., Bevis, M.J., (1997) Polymer Process Engineering 97, pp. 40-54. , Coates, P. D., Ed.; The Institute of Materials: London; Ogbonna, C.I., Kalay, G., Allan, P.S., Bevis, M.J., (1995) J Appl Polym Sci, 58, p. 2131; Kubát, J., Månson, J.A., (1983) Polym Eng Sci, 23, p. 86; Kubát, J., Månson, J.A., Rigdahl, M., (1983) Polym Eng Sci, 23, p. 877; Boldizar, A., Kubát, J., Rigdahl, M., (1990) J Appl Polym Sci, 39, p. 63; Guan, Q., Shen, K., Ji, J., Zhu, J., (1995) J Appl Polym Sci, 55, p. 1797; Guan, Q., Shen, K., (1995) Z. Chem J Chinese Univers, 16, p. 1129; Ross, J.P., (1998) Taguchi Techniques for Quality Engineering, , McGraw-Hill: New York; Schmidt, S.R., Launsby, R.G., (1994) Understanding Industrial Designed Experiments, 4th Ed., , Air Academy Press: CO; Montgomery, D.C., (1991) Design and Analysis of Experiments, 3rd Ed., , Wiley: New York
Keywords: differential scanning calorimetry; Elastic moduli; High density polyethylenes; Injection molding; morphology; Optimization; Shear controlled orientation in injection molding; Shear flow; Shish kebab structure; Stiffness; Strength of materials; tensile strength; Tensile testing; Toughness; Wide angle X ray diffraction; X ray diffraction analysis

In vitro growth and differentiation of osteoblast-like human bone marrow cells on glass reinforced hydroxyapatite plasma-sprayed coatings - Ferraz, M.P.; Fernandes, M.H.; Cabral, A.T.; Santos, J.D.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1999)
Human osteoblastic bone marrow cells were cultured far periods of up to 28 days in control conditions and on the surface of a glass reinforced hydroxyapatite composite (HA/G1) and commercial hydroxyapatite (HA) plasma-sprayed coatings, in the 'as-received' condition and after immersion treatment in culture medium for 21 days. Cultures were characterized for total protein content and alkaline phosphatase activity. Scanning electron microscope analyses were performed on control cultures, seeded materials and materials incubated in the absence of cells. Culture media were analyzed for total and ionized calcium and phosphorus concentrations throughout the incubation period. Immersion of HA/G1 and HA coatings in culture medium resulted in significant alterations to the levels of calcium and phosphorus in the medium, leading to surface modifications. However, seeded material samples showed significant differences in the pattern of variation of the levels of these species. Cell proliferation was observed in the 'as-received' HA/G1 composite, but cell mediated formation of mineral deposits was not proved. In contrast, 'as-received' HA hardly supported cell growth. Previously immersed material samples showed cell proliferation and evidence of biological formation of mineral deposits. However, the HA/G1 composite presented better surface characteristics for cell growth as the behavior of bone marrow eel Is was closer to that observed in control cultures.Human osteoblastic bone marrow cells were cultured for periods of up to 28 days in control conditions and on the surface of a glass reinforced hydroxyapatite composite (HA/G1) and commercial hydroxyapatite (HA) plasma-sprayed coatings, in the 'as-received' condition and after immersion treatment in culture medium for 21 days. Cultures were characterized for total protein content and alkaline phosphatase activity. Scanning electron microscope analyses were performed on control cultures, seeded materials and materials incubated in the absence of cells. Culture media were analyzed for total and ionized calcium and phosphorus concentrations throughout the incubation period. Immersion of HA/G1 and HA coatings in culture medium resulted in significant alterations to the levels of calcium and phosphorous in the medium, leading to surface modifications. However, seeded material samples showed significant differences in the pattern of variation of the levels of these species. Cell proliferation was observed in the 'as-received' HA/G1 composite, but cell mediated formation of mineral deposits was not proved. In contrast, 'as-received' HA hardly supported cell growth. Previously immersed material samples cell proliferation and evidence of biological formation of mineral deposits. However, the HA/G1 composite presented better surface characteristics for cell growth as the behavior of bone marrow cells was closer to that observed in control cultures.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1008924516146Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Institute of Biomedical Engineering, Faculties of Dental Medicine, Universidade do Porto, 4200 Porto, PortugalChemicals/CAS: alkaline phosphatase, 9001-78-9; calcium ion, 14127-61-8; hydroxyapatite, 1306-06-5, 51198-94-8; phosphorus, 7723-14-0; protein, 67254-75-5References: Passuti, N., Daculsi, G., Martin, S., (1990) Clinical Implant Materials, p. 255. , edited by V. Soltesz and A. Lee (Elsevier, Amsterdam);Legeros, R., (1988) Adv. Dental Res., 2, p. 164; Hench, L.L., (1992) J. Amer. Ceram. Soc., 74, p. 1487; Kokubo, T., (1993) Bone-Bonding Biomaterals, p. 31. , edited by P. Ducheyne, T. Kokubo and C. A. Blitterswijk (Reed Health-Care Comunications, Leiden, The Netherlands); Daculsi, G., Legeros, R.Z., Henghebaert, M., Barbieux, I., (1990) Calcif. Tissue Int., 46, p. 20; Bagambisa, F.B., Joos, U., Schilli, W., (1993) J. Biomed. Mater. Res., 27, p. 1047; De Bruijn, J.D., Van Blitterswijk, C.A., Davies, J.E., (1995) J. Biomed. Mater. Res., 29, p. 89; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , JAAS; Raemdonck, W., Ducheyne, P., Meester, P., (1984) Metal and Ceramic Materials, p. 143. , edited by P. Ducheyne and G. W. Hastings (CRC Press, Boca Raton, FL); Rey, C., Freche, M., Heughebaert, M., Vignoles, M., (1991) Bioceramics 4, p. 57. , edited by W. Bonfield, G. W. Hastings and K. E. Tanner (Butterworth-Heinemann, London); Nagase, M., Abe, Y., Udagawa, E., (1992) Biomaterials, 13, p. 172; Burnie, J., Gilchrist, T., (1993) Ceramics in Surgery, p. 169. , edited by P. Vincenzini (Elsevier, Amsterdam); Burnie, F., Gilchrist, T., Ceramics in Surgery, p. 177; Rawlings, R.D., Rogers, P.S., Stokes, P.M., (1987) High Tech Ceramics, p. 73. , edited by P. Vincenzini (Elsevier, Amsterdam); Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Santos, J.D., Lakhan, J.J., Monteiro, F.J., (1995) Biomaterials, 16, p. 521; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., (1995) J. Mater. Sci. Mater. Med., 6, p. 348; Klein, C.P.A.T., Patka, P., Van Der Lubbe, H.B.M., (1991) J. Biomed. Mater. Res., 25, p. 53; Jansen, J.A., Van Der Waerden, J.P.C.M., Wolke, J.G.C., (1993) J. Mater. Sci. Mater. Med., 4, p. 466; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., (1992) J. Biomed. Mater. Res., 26, p. 1365; Frayssinet, P., Tourenne, F., Rouquet, P., Conte, P., Delga, C., Bonel, G., (1994) J. Mater. Sci. Mater. Med., 5, p. 11; Lugscheider, E., Knepper, M., Heimberg, B., Dekker, A., Kirkpatrick, C.J., (1994) J. Mater. Sci. Mater. Med., 5, p. 371; Courteney-Harris, R.G., Kayser, M.V., Downes, S., (1995) Biomaterials, 16, p. 489; Labat, B., Chanson, A., Frey, J., (1995) J. Biomed. Mater. Res., 29, p. 1397; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., (1996) J. Mater. Sci. Mater. Med., 7, p. 21; Anselme, K., Sharrock, P., Hardouin, P., Dard, M., (1997) J. Biomed. Mater. Res., 34, p. 247; Ong, J.L., Prince, C.W., Lucas, L.C., (1995) J. Biomed. Mater. Res., 29, p. 165; Vrouwenvelder, W.C.A., Groot, C.G., De Groot, K., (1995) J. Mater. Sci. Mater. Med., 6, p. 144; Amédée, J., Bareille, R., Jeandot, R., Bordenave, L., Rémy, M., Rouais, F., Baquey, C., (1994) Biomaterials, 15, p. 1029; Maniatopoulos, C., Sodek, J., Melcher, A., (1988) Cell Tissue Res., 254, p. 317; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., (1990) J. Cell Phys., 143, p. 213; Gundle, R., Joyner, C.J., Triffit, J.T., (1995) Bone, 16, p. 597; Fernandes, M.H., Costa, M.A., Carvalho, G.S., (1997) J. Mater. Sci. Mater. Med., 8, p. 61; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., (1997) J. Mater. Sci. Mater. Med., 8, p. 233; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., (1996) J. Mater. Sci. Mater. Med., 7, p. 291; Morais, S., Dias, N., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., (1999) J. Biomed. Mater. Res., 44, p. 176; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., (1991) Bone and Min., 14, p. 27; Ferraz, M.P., Monteiro, F.J., Santos, J.D., J. Biomed. Mater. Res., , submitted; Owen, T.A., Aronow, M., Shalhoub, V., (1990) J. Cell Phys., 143, p. 420; Martin, T.J., Findlay, D.M., Heath, J.K., Ng, K.W., (1993) Handbook of Experimental Pharmacology, p. 149. , edited by J. R. Mundy and T. J. Martin Berlin (Springer-Verlag); Stein, G.S., Lian, J.B., (1993) Cellular and Molecular Biology of Bone, p. 47. , edited by M. Noda (Academic Press, Tokyo); Anderson, H.C., Morris, D.C., (1993) Handbook of Experimental Pharmacology, p. 267. , edited by J. R. Mundy and T. J. Martin Berlin (Springer-Verlag); Gwynn, I.A.P., (1994) J. Mater. Sci. Mater. Med., 5, p. 357; Kirkpatrick, C.J., Wagner, M., Kohler, H., Bittinger, F., Otto, M., Klein, C.L., (1997) J. Mater. Sci. Mater. Med., 8, p. 131; Legeros, R.Z., Orly, I., Gregoire, M., Daculsi, G., (1991) The Bone-Biomaterial Interface, p. 76. , edited by J. E. Davies (University of Toronto Press, Toronto); Chern Lin, J.H., Liu, M.L., Ju, C.P., (1994) J. Biomed. Mater. Res., 28, p. 723; Ghannam, E.L., Ducheyne, P., Spapiro, I., (1995) J. Biomed. Mater. Res., 29, p. 359; Radin, S.R., Ducheyne, P., (1993) J. Biomed. Mater. Res., 27, p. 35; Radin, S.R., Ducheyne, P., (1993) J. Biomed. Mater. Res., 27, p. 1047; Best, S., Sim, B., Kayser, M., Downes, S., (1997) J. Mater. Sci. Mater. Med., 8, p. 97
Keywords: adult; alkaline phosphatase; article; Bone; bone marrow cell; Bone replacement materials; Calcium; calcium ion; case report; Cell culture; cell differentiation; cell growth; Cells; controlled study; culture medium; enzyme activity; Enzyme kinetics; glass; Growth kinetics; human; Human bone marrow cell; human cell; hydroxyapatite; male; osteoblast; Phosphates; phosphorus; priority journal; protein; protein determination; Proteins; scanning electron microscope; Scanning electron microscopy; Sprayed coatings

In vitro osteoblastic differentiation of human bone marrow cells in the presence of metal ions - Morais, S.; Dias, N.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
For periods up to 21 days human bone marrow was cultured in control conditions that favor the proliferation and differentiation of osteoblastic cells. The effect of AISI 316L corrosion products and the corresponding major separate metal ions (Fe, Cr, and Ni) were studied in three different phases of the culture period in order to investigate the effects of metal ions in cell populations representative of osteoblastic cells in different stages of differentiation. Toxicity consequences of the presence of metal ions in bone marrow cultures were evaluated by biochemical parameters (enzymatic reduction of MTT, alkaline phosphatase activity, and total protein content), histochemical assays (identification of ALP-positive cells and Ca and phosphates deposits), and observation of the cultures by light and scanning electron microscopy. Culture media were analyzed for total and ionized Ca and P and also for metal ions (Fe, Cr, and Ni). The presence of AISI 316L corrosion products and Ni salt in bone marrow cultures during the first and second weeks of culture significantly disturbs the normal behavior of these cultures, interfering in the lag phase and exponential phase of cell growth and ALP expression. However, the presence of these species during the third week of culture, when expression of osteoblastic functions occurs (mineralization process), did not result in any detectable effect. Fe salt also disturbs the behavior of bone marrow cell cultures when present during the lag phase and proliferation phase, and a somewhat compromised response between the normal pattern (control cultures) and intense inhibition (AISI 316L corrosion products and Ni salt-added cultures) was observed. Fe did not affect the progression of the mineralization phase. Osteogenic cultures exposed to Cr salt (Cr 3+) presented a pattern similar to the controls, indicating that this element does not interfere, in the concentration studied, in the osteoblastic differentiation of bone marrow cells. Quantification of metal ions in the culture media showed that Cr (originated from AISI 316L corrosion products but from not Cr 3+ salt) and Ni (originated from AISI 316L corrosion products and Ni salt) appear to be retained by the bone marrow cultures. For periods up to 21 days human bone marrow was cultured in control conditions that favor the proliferation and differentiation of osteoblastic cells. The effect of AISI 316L corrosion products and the corresponding major separate metal ions (Fe, Cr, and Ni) were studied in three different phases of the culture period in order to investigate the effects of metal ions in cell populations representative of osteoblastic cells in different stages of differentiation. Toxicity consequences of the presence of metal ions in bone marrow cultures were evaluated by biochemical parameters (enzymatic reduction of MTT, alkaline phosphatase activity, and total protein content), histochemical assays (identification of ALP-positive cells and Ca and phosphates deposits), and observation of the cultures by light and scanning electron microscopy. Culture media were analyzed for total and ionized Ca and P and also for metal ions (Fe, Cr, and Ni). The presence of AISI 316L corrosion products and Ni salt in bone marrow cultures during the first and second weeks of culture significantly disturbs the normal behavior of these cultures, interfering in the lag phase and exponential phase of cell growth and ALP expression. However, the presence of these species during the third week of culture, when expression of osteoblastic functions occurs (mineralization process), did not result in any detectable effect. Fe salt also disturbs the behavior of bone marrow cell cultures when present during the lag phase and proliferation phase, and a somewhat compromised response between the normal pattern (control cultures) and intense inhibition (AISI 316L corrosion products and Ni salt-added cultures) was observed. Fe did not affect the progression of the mineralization phase. Osteogenic cultures exposed to Cr salt (Cr 3+) presented a pattern similar to the controls, indicating that this element does not interfere, in the concentration studied, in the osteoblastic differentiation of bone marrow cells. Quantification of metal ions in the culture media showed that Cr (originated from AISI 316L corrosion products but from not Cr 3+ salt) and Ni (originated from AISI 316L corrosion products and Ni salt) appear to be retained by the bone marrow cultures.
Cited By (since 1996): 35Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(199902)44:2<176::AID-JBM8>3.0.CO;2-6PubMed ID: 10397919Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Universidade do Porto, Rua Dr Manuel Pereira da Silva, 4200 Porto, PortugalChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Alloys; Biocompatible Materials; Calcium, 7440-70-2; Chromium, 7440-47-3; Iron, 7439-89-6; Metals; Nickel, 7440-02-0; Phosphorus, 7723-14-0; Proteins; Stainless Steel, 12597-68-1; Tetrazolium Salts; Thiazoles; thiazolyl blue, 298-93-1References: Williams, D., Cahn, R.W., Bever, M.B., (1990) Concise Encyclopedia of Medical & Dental Materials, pp. 4-70. , Oxford, New York, Beijing, Frankfurt, São Paulo, Sydney, Tokyo, Toronto: Permagon Press;Linden, J.V., Hopler, S.M., Gossling, H.R., Sunderman Jr., F.W., Blood nickel concentrations in patients with stainless-steel hip protheses (1985) Ann Clin Lab Sci, 15, pp. 459-464. , 1985; Weber, G.W., Reid, B.L., Nickel toxicity in young growing mice (1969) J Animal Sci, 28, pp. 620-623; O'Dell, G.D., Miller, W.J., King, W.A., Moore, S.L., Blackmon, D.M., Nickel toxicity in the young bovine (1970) J Nutrition, 100, pp. 1447-1453; Louria, D.B., Joselow, M.M., Browder, A.A., The human toxicity of certain trace elements (1972) Ann Intern Med, 76, pp. 307-319; Whanger, P.D., Effects of dietary nickel on enzyme activities and mineral contents in rats (1973) Toxicol Appl Pharmacol, 25, pp. 323-331; Woodman, J.L., Black, J., Jimenez, S., Organometallic corrosion products of 316L SS and HS-21 in serum: In vitro and in vivo comparison in an acute rat model (1982) Biomaterials 1980, pp. 245-253. , Winter GD, Gibbon DF, Plenk Jr H, editors. Chichester, New York, Brisbone, Toronto, Singapore: John Wiley & Sons; Parfitt, A.M., The physiological and clinical significance of bone histomorphometric data (1983) Bone Histomorphometry: Techniques and Interpretation, pp. 143-223. , Recker RR, editor. Boca Raton, Florida: CRC Press; Jilka, R.L., Manolagas, S.C., The cellular and biochemical basis of bone remodeling (1994) Osteoporosis, pp. 17-48. , Marcus R, editor. Boston: Blackwell Scientific Publications; Owen, M., Lineage of osteogenic cells and their relationship to the stromal system (1985) Bone and Mineral Research, 3, pp. 1-25. , Peck WA, editor. Amsterdam: Elsevier Science Publishers; Owen, T.A., Aronow, M., Shalhoub, V., Progressive development of the rat osteoblast phenotype in vitro: Reciprocal relationships in expression of genes associated with osteoblast proliferation and differentiation during formation of the bone extracellular matrix (1990) J Cell Physiol, 143, pp. 420-430; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionized Ca in osteoblast-like cell culture medium (1996) Electroanalysis, 8 (12), pp. 1174-1178; Morais, S., Carvalho, G.S., Sousa, J.P., Iron determination in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode (1997) Electroanalysis, 9 (10), pp. 791-795; Morais, S., Carvalho, G.S., Sousa, J.P., Chromium determination in osteoblast-like cell culture medium by catalytic cathodic stripping voltammetry with a mercury microelectrode (1998) J Trace Elements Med Biol, 2, pp. 101-108; Morais, S., Carvalho, G.S., Sousa, J.P., Determination of Ni in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with mercury microelectrodes (1997) Electroanalysis, 9 (5), pp. 422-426; Morais, S., Carvalho, G.S., Sousa, J.P., Optimization study for nickel quantification in cell culture medium using mercury film microelectrodes (1996) Portugaliae Electrochimica Acta, 14, pp. 267-272; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tiss Res, 254, pp. 317-330; Berridge, V., Tan, A.S., Characterization of the cellular reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT): Subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch Biochem Biophys, 303, pp. 474-482; Bessey, O., Lowry, O., Breck, M., A method for the rapid determination of alkaline phosphatase with five cubic millileters of serum (1946) J Biol Chem, 164, pp. 321-326; McGee-Russell, M., Histochemical methods for calcium (1958) J Histochem Cytochem, 6, pp. 22-42; Fiske, C.H., Subbarow, Y., The colorimetric determination of phosphorus (1925) J Biol Chem, 66, pp. 373-400; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulate formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 143, pp. 213-221; Gotoh, Y., Hiraiwa, K., Narajama, M., In vitro mineralization of osteoblastic cells derived from human bone (1990) Bone and Miner, 8, pp. 239-250; Cheng, S.L., Yang, J.W., Riffas, L., Zhang, S.F., Avioli, L.V., Differentiation of human bone marrow osteogenic stromal cells in vitro. Induction of the osteoblast phenotype by dexamethasone (1994) Endocrinology, 134, pp. 277-286; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone-derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Arcicla, C.R., Granchi, D.C., Savarino, L., Cell culture methods for testing biocompatibility (1994) Clin Mater, 15, pp. 173-190; Gerstenfeld, L.C., Chipman, S.D., Glowacki, J., Lian, J.B., Expression of differential function by mineralizing cultures of chicken osteoblasts (1987) Dev Biol, 122, pp. 46-60; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone and Miner, 14, pp. 27-40; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralization of osteoid nodules in vitro (1992) Bone and Miner, 17, pp. 15-29; Chung, C.H., Golub, E.E., Forbes, E., Tokuoka, T., Shapiro, I.M., Mechanisms of action of β-glycerophosphate on bone cell mineralization (1992) Calcif Tissue Int, 51, pp. 305-311; Boskey, A.L., Stiner, D., Doty, S.B., Binderman, I., Levoy, P., Studies of mineralization in tissue culture: Optimal conditions for cartilage calcification (1992) Bone and Miner, 16, pp. 11-36; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., De Bruijn, J.D., Van Blitterswijk, C.A., Decreased consumption of Ca and P during in vitro biomineralization and biologically induced deposition of Ni and Cr in presence of stainless steel corrosion products (1998) J Biomed Mater Res, 42, pp. 199-212; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralization by osteoblast-like cells. 1. Retardation of tissue mineralization by metal salts (1998) Biomaterials, 19, pp. 13-21; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., De Bruijn, J.D., Van Blitterswijk, C.A., Effects of AISI 316L corrosion products in in vitro bone formation (1998) Biomaterials, 19, pp. 999-1007; Stein, G.S., Lian, J.B., Molecular mechanisms mediating developmental and hormone-regulated expression of genes in osteoblasts: An integrated relationship of cell growth and differentiation (1993) Cellular and Molecular Biology of Bone, pp. 47-95. , Noda M, editor. Tokyo: Academic Press Inc; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., The ultrastructure of the one-hydroxyapatite interface in vitro (1992) J Biomed Mater Res, 26, pp. 1365-1382; Stein, G.S., Lion, J.B., Molecular mechanisms mediated proliferation-differentiation interrelationships during progressive development of the osteoblast phenotype: Update 1995 (1995) Endocrin Rev, 4, pp. 290-297; Abe, Y., Akamine, A., Aida, Y., Maeda, K., Differentiation and mineralization in osteogenic precursor cells derived from fetal rat mandibular bone (1993) Calcif Tissue Int, 52, pp. 365-371; Lomri, A., Tran, M.P.V., Mott, M., Characterization of endosteal osteoblastic cells isolated from mouse caudal vertebrae (1988) Bone, 9, pp. 165-175; McCulloch, C.A.G., Fair, C.A., Tenebaum, H.C., Limeback, H., Homareau, R., Clonal distribution of osteoprogenitor cells in cultured chick peristoa: Functional relationship to bone formation (1990) Dev Biol, 140, pp. 352-361; Sun, Z.L., Wataha, J.C., Hanks, C.T., Effects of metal ions on osteoblast-like cell metabolism and differentiation (1997) J Biomed Mater Res, 34, pp. 29-37; Puleo, D.A., Huh, W.W., Acute toxicity of metal ions in cultures of osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 109-116; Katz, S.A., Salem, H., The toxicology of Cr with respect to its chemical speciation: A review (1993) J Appl Toxicol, 13, pp. 217-224; Anderson, H.C., Morris, D.C., Mineralization (1993) Handbook of Experimental Pharmacology, pp. 267-298. , Mundy GR, Martin TJ, editors. Berlin: Springer-Verlag; Merritt, K., Brown, S.A., Biological effects of corrosion products from metals (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 195-207. , Fraker AC, Griffin CD, editors. ASTM STP 859. Philadelphia: American Society for Testing and Materials; Rae, T., The toxicity of metals used in orthopaedic prostheses (1981) J Bone Joint Surg, 63 B, pp. 435-440; Webb, M., Weinzier, S.M., Uptake of 63Ni 2+ from its complexes with proteins and other ligands by mouse dermal fibroblasts in vitro (1972) Br J Cancer, 26, pp. 292-298; Merritt, K., Wortman, R.S., Millard, M., Brown, S.A., XPS analysis of 316LVM corroded in serum and saline (1983) Biomater Med Devices Artif Organs, 11, pp. 115-124; Bianchi, V., Toso, R.D., Debetto, P., Mechanisms of chromium toxicity in mammalian cell cultures (1980) Toxicology, 17, pp. 219-224; Lucas, L.C., Bearden, L.J., Lemons, J.E., Ultrastructural examination of in vitro and in vivo cells exposed to elements from type 316L stainless steel (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 208-222. , Fraker AC, Griffin CD, editors. ASTM STP 859. Philadelphia: American Society for Testing and Materials
Keywords: alkaline phosphatase; Alloys; article; Batch cell culture; Biocompatible Materials; biotechnology; Bone; Bone cells; bone marrow cell; Bone Marrow Cells; bone mineralization; bone prosthesis; Calcium; Cell culture; cell differentiation; Cell Division; cell population; Cells, Cultured; Chromium; controlled study; Corrosion; Corrosion products; Cytotoxicity; Differentiation; human; human cell; Human osteoblast-like cells; Humans; Implants (surgical); Ions; Iron; joint prosthesis; materials testing; metal ion; Metal ions; Metals; Nickel; osteoblast; Osteoblasts; phosphorus; Prostheses and Implants; Proteins; Stainless steel; Steel corrosion; Tetrazolium Salts; Thiazoles

Miniaturization and application of the MTT assay to evaluate metabolic activity of protozoa in the presence of toxicants - Dias, N.; Nicolau, A.; Carvalho, G.S.; Mota, M.; Lima, N. (Journal of Basic MicrobiologyJ. Basic Microbiol., 1999)
This paper describes a critical evaluation of a miniaturised colorimetric assay, using MTT (3-[4,5-dimethyl-thiazol-2-yl]-2,5-diphenyl-tetrazolium bromide) reduction, applied to protozoan viability testing. The toxic substances used were copper, zinc, Triton X-100 (a membrane surfactant) and cycloheximide (an inhibitor of the protein synthesis). The viability assay of the ciliate protozoan Tetrahymena pyriformis was optimised in terms of MTT concentration and incubation time. Since protozoa are non adherent cells the MTT assay was modified in order to maintain the medium in the well. MTT proved to be effective in the measurement of Tetrahymena pyriformis viability. Four hours of MTT incubation followed by 30 minutes of incubation with DMSO were found to be the best incubation times for optical density reading. Furthermore, 10 mg/ml of MTT solution was the concentration that gave higher values of optical densities with minor medium interference.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JBMIEdoi: 10.1002/(SICI)1521-4028(199905)39:2<103::AID-JOBM103>3.0.CO;2-DPubMed ID: 10335603Language of Original Document: EnglishCorrespondence Address: Lima, N.; Centro de Engenharia Biologica, Universidade do Minho, 4700 Braga, Portugal; email: nelson@iec.uminho.ptChemicals/CAS: Copper, 7440-50-8; Cycloheximide, 66-81-9; Octoxynol, 9002-93-1; Tetrazolium Salts; Thiazoles; thiazolyl blue, 298-93-1; Zinc, 7440-66-6References: Berridge, M.V., Tan, S., Characterization of the cellular reduction of using 3-[4,5-dimethyl-thiazol-2-y1]-2,5-diphenyl-tetrazolium bromide-MTT: Subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch. Biochem. Biophysics, 303, pp. 474-482;Berridge, M.V., Tan, S., McCoy, K.D., Wang, R., The biochemical and cellular basis of cell proliferation assays that use tetrazolium salts (1996) Biochemica, 4, pp. 15-20; Carvalho, G.S., Castanheira, M., Diogo, I., Abreu, A.M., Sousa, J.P., Loon, J.A., Van Blitterswijk, C.A., Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts (1996) J. Mat. Science: Mat. in Medicine, 7, pp. 77-83; Ciappeti, G., Cenni, E., Pratelli, L., Pizzoferrato, A., In vitro evaluation of cell/biomaterial interaction by MTT assay (1993) Biomaterials, 14, pp. 359-364; Colgan, D.J., Spectrophotometric quantitation of DNA on blots after ethanol-solubilization of the MTT-formazan from anti-digoxigenin-based detection of nucleic acids (1993) Appl. Theor. Electrophoresis, 3, pp. 219-222; Cote, J., Kamen, A.A., Andre, G., Protein-free culture medium improvement. Testing additives and their interactive effects in 96-well plates (1993) Appl. Microb. Biotechnol., 39, pp. 577-584; Dias, N., Lima, N., Carvalho, G.S., Mota, M., Miniaturização do ensaio do MTT para avaliação da actividade metabólica dos protozoários (1997) Congresso Nacional de Microbiologia-MICRO' 97, , Tomar; Hanel, T., Gareis, M., Kollarczik, B., Citotoxicity of mycotoxins evaluated by the MTT-cell culture Assay (1994) Mycopathologia, 128, pp. 167-174; Lemieux, P., Michaud, M., Pagé, M., A new formazan amplified clonogenic assay for cytotoxicity testing (1993) Biotechnol. Techniques, 7, pp. 597-602; Martin, A., Clynes, C., Comparison of 5 microplate assays for in vitro cytotoxicity testing and cell proliferation assays (1993) Cytotechnology, 11, pp. 49-58; Mossman, T., Rapid colorimetric assay for cellular growth and survival: Application to proliferation and cytotoxicity assays (1983) J. Immunol. Methods, 65, pp. 55-63; Roberts, Ch.T., Orias, E., A cycloheximide-resistant mutant of Tetrahymena pyriformis (1973) Exp. Cell Res., 81, pp. 312-316; Sasaki, C.Y., Passaniti, A., Identification of anti-invasive but noncytotoxic chemotherapeutic agents using the tetrazolium dye MTT to quantitative viable cells in matrigel (1998) Bio-techniques, 24, pp. 1038-1043; Stowe, R.P., Koenig, D.W., Mishra, S.K., Pierson, D.L., Non destructive and continuous spectrophotometric measurement of cell respiration using a tetrazolium-formazan microemulsion (1995) J. Microbiol. Methods, 22, pp. 283-292; Wilson, A.P., Citotoxicity and viability assays (1995) Animal Cell Culture - A Practical Approach. 2nd Ed., pp. 277-289. , (R. I. FRESHNEY, Editor). Oxford University Press, Oxford
Keywords: Animals; Ciliophora; Colorimetry; Copper; Cycloheximide; MTT assay; Octoxynol; Protozoa; Tetrahymena pyriformis; Tetrazolium Salts; Thiazoles; Zinc

Decreased consumption of Ca and P during in vitro biomineralization and biologically induced deposition of Ni and Cr in presence of stainless steel corrosion products - Morais, S.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S.; De Bruijn, J.D.; Van Blitterswijk, C.A. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1998)
The purpose of this study was to investigate the effects of 316L stainless steel (SS) corrosion products on the in vitro biomineralization process, because tissue necrosis, bone loss, impaired bone mineralization, and loosening of orthopedic implants are associated with ions and debris resulting from biodegradation. Rat bone marrow cells were cultured in experimental conditions that favored the proliferation and differentiation of osteoblastic cells and were exposed to SS corrosion products obtained by electrochemical means for periods ranging from 1 to 21 days. Quantification of total and ionized Ca and P, as well as Fe, Cr, and Ni, ions in the culture media of control and metal added cultures during the incubation period was performed to study the influence of corrosion products on the Ca and P consumption that occurs during the mineralization process. Control cultures and metal effects on cultures were evaluated concerning DNA content, enzymatic reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), and alkaline phosphatase (ALP) activity. Histochemical detection of ALP, Ca, and phosphate deposition, and examination of the cultures by scanning and transmission electron microscopy (SEM and TEM) were also performed. The presence of SS corrosion products resulted in impairment of the normal behavior of rat bone marrow cultures. Levels of Cr and Ni in the medium of cultures exposed to 316L SS corrosion products decreased throughout the incubation period, suggesting a regular deposition of these species; these results were supported by TEM observation of the cultures. Cultures exposed to the corrosion products presented lower DNA content, MTT reduction, and ALP activity and failed to form mineralized areas. These cultures showed negative staining on histochemical reactions for the identification of calcium and phosphate deposition and SEM and TEM examination did not show mineral globular structures or mineralization foci, respectively, which is characteristic of cultures grown in control conditions. These results suggest that metal ions associated with 316L SS are toxic to osteogenic cells, affecting their proliferation and differentiation.The purpose of this study was to investigate the effects of 316L stainless steel (SS) corrosion products on the in vitro biomineralization process, because tissue necrosis, bone loss, impaired bone mineralization, and loosening of orthopedic implants are associated with ions and debris resulting from biodegradation. Rat bone marrow cells were cultured in experimental conditions that favored the proliferation and differentiation of osteoblastic cells and were exposed to SS corrosion products obtained by electrochemical means for periods ranging from 1 to 21 days. Quantification of total and ionized Ca and P, as well as Fe, Cr, and Ni, ions in the culture media of control and metal added cultures during the incubation period was performed to study the influence of corrosion products on the Ca and P consumption that occurs during the mineralization process. Control cultures and metal effects on cultures were evaluated concerning DNA content, enzymatic reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), and alkaline phosphatase (ALP) activity. Histochemical detection of ALP, Ca, and phosphate deposition, and examination of the cultures by scanning and transmission electron microscopy (SEM and TEM) were also performed. The presence of SS corrosion products resulted in impairment of the normal behavior of rat bone marrow cultures. Levels of Cr and Ni in the medium of cultures exposed to 316L SS corrosion products decreased throughout the incubation period, suggesting a regular deposition of these species; these results were supported by TEM observation of the cultures. Cultures exposed to the corrosion products presented lower DNA content, MTT reduction, and ALP activity and failed to form mineralized areas. These cultures showed negative staining on histochemical reactions for the identification of calcium and phosphate deposition and SEM and TEM examination did not show mineral globular structures or mineralization foci, respectively, which is characteristic of cultures grown in control conditions. These results suggest that metal ions associated with 316L SS are toxic to osteogenic cells, affecting their proliferation and differentiation.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(199811)42:2<199::AID-JBM5>3.0.CO;2-KPubMed ID: 9773816Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Universidade do Porto, Rua Manuel Pereira da Silva, 4200 Porto, PortugalChemicals/CAS: Biocompatible Materials; Calcium, 7440-70-2; Chromium, 7440-47-3; Nickel, 7440-02-0; Phosphorus, 7723-14-0; Steel, 12597-69-2References: Ferguson Jr., B., Akahoshi, Y., Laing, P.G., Hodge, E.S., Trace metal ion concentration in the liver, kidney, spleen and lung of normal rabbits (1962) J. Bone Joint Surg., 44 A, pp. 317-322;Ferguson Jr., A.B., Akahoshi, Y., Laing, P.G., Hodge, E.S., Characteristics of trace ions released from embedded metal implants in the rabbit (1962) J. Bone Joint Surg., 44 A, pp. 323-336; Ferguson Jr., A.B., Laing, P.G., Hodge, E.S., The ionization of metal implants in living tissues (1960) J. Bone Joint Surg., 42 A, pp. 77-90; Lux, F., Ziesler, R., Investigations of the corrosive deposition of components of metal implants and of the behavior of biological trace elements in metallosis tissue by means of instrumental multi-elemental activation analysis (1974) J. Radioanal. Chem., 19, pp. 289-297; Smith, G.K., Black, J., Estimation of in vivo type 316L stainless steel corrosion rate from blood transport and organ accumulation data (1985) Corrosion and Degradation of Implant Materials: Second Symposium, ASTM STP 859, pp. 223-247. , A. C. Fraker and C. D. Griffin (eds.), American Society for Testing and Materials, Philadelphia, Pennsylvania; Merritt, K., Brown, S.A., Biological effects of corrosion products from metals (1985) Corrosion and Degradation of Implant Materials: Second Symposium, ASTM STP 859, pp. 195-207. , A. C. Fraker and C. D. Griffin, (eds.), American Society for Testing and Materials, Philadelphia, Pennsylvania; Smith, G.K., Black, J., Models for systemic effects of corrosion products (1977) Retrieval and Analysis of Orthopedics Implants, pp. 23-28. , A. Weinstein D. Gibbons, S. A. Brown, and A. W. Ruff (eds.), NBS Special Publication 472, U.S. Government Printing Office, Washington, D.C; Deutman, R., Mulder, T.J., Brian, R., Nater, J.P., Metal sensitivity before and after total hip arthroplasty (1977) J. Bone Joint Surg., 59 A, pp. 862-865; Verne, J., Sannie, C., Etude de l'action toxique des cations sur les fibroblastes cultivés in vitro (1933) Compt. Rend. Acad. Sci., 196, pp. 1246-1247; Kirkpatrick, C.J., A critical view of current and proposed methodologies for biocompatibility testing: Cytotoxicity in vitro (1992) Regul. Affairs, 4, pp. 13-22; Pereira, M.L., Silva, A., Tracana, R., Carvalho, G.S., Toxic effects caused by stainless steel corrosion products on mouse seminiferous cells (1994) Cytobios, 77, pp. 73-80; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Chromium accumulation and ultrastructural changes in the mouse liver caused by stainless steel corrosion products (1995) J. Mater. Sci. Mater. Med., 6, pp. 523-527; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Stainless steel corrosion products cause alterations on mouse spleen cellular populations (1995) J. Mater. Sci. Mater. Med., 6, pp. 56-61; Bravo, I., Sousa, S.R., Carvalho, G.S., Barbosa, M., Metals electrochemically dissolved in human serum inhibit T-lymphocyte function (1992) Advances in Biomaterials, pp. 7-11. , P. J. Doherty et al. (eds.), Amsterdam, Elsevier; Carvalho, G.S., Castanheira, M., Diogo, I., Abreu, A.M., Sousa, J.P., Loon, J.A., Blitterswijk, C.A., Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts (1995) J. Mater. Sci. Mater. Med., 7, pp. 77-83; Evans, E.M., Freeman, M.A.R., Miller, A.J., Vernon-Roberts, B., Metal sensitivity as a cause of bone necrosis and loosening of the prosthesis in total joint replacement (1974) J. Bone Joint Surg., 56 B, pp. 626-642; Betts, F., Wright, T., Salvati, E.A., Boskey, A., Mansal, M., Cobalt alloy metal debris in periarticular tissues from total hip revision arthoplasties (1992) Clin. Orthop., 278, pp. 75-82; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralization by osteoblast-like cells: Part 1-Retardation of tissue mineralization by metal salts (1998) Biomaterials, 19, pp. 13-21; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionized calcium in osteoblast-like cell culture medium (1996) Electroanalysis, 8, pp. 1174-1178; Morais, S., Carvalho, G.S., Sousa, J.P., Iron determination in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode (1997) Electroanalysis, 9, pp. 791-795; Morais, S., Carvalho, G.S., Sousa, J.P., Electrochemical characterization of iron species in osteoblast-like cell culture medium (1995) Port. Electrochim. Acta, 13, pp. 483-487; Morais, S., Carvalho, G.S., Sousa, J.P., Determination of nickel in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with mercury microelectrodes (1997) Electroanalysis, 9, pp. 422-426; Morais, S., Carvalho, G.S., Sousa, J.P., Optimization study for nickel quantification in cell culture medium using mercury film microelectrodes (1996) Port. Electrochim. Acta, 14, pp. 267-272; Morais, S., Carvalho, G.S., Sousa, J.P., Chromium determination in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode J. Trace Elements Med. Biol., , in press; Nurnberg, H.W., The voltammetric approach in trace metal chemistry of natural waters and atmospheric precipitation (1984) Anal.Chim. Acta, 164, pp. 1-21; Merritt, K., Wortman, R.S., Millard, M., Brown, S.A., XPS analysis of 316 LVM corroded in serum and in saline (1983) Biomater. Med. Devices Artif. Org., 11, pp. 115-127; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res., 254, pp. 317-330; Fiske, H., Subbarow, Y., The colorimetric determination of phosphorus (1925) J. Biol. Chem., 66, pp. 373-400; Vrouwenvelder, W.C.A., Groot, C.G., De Groot, K., Histological and biochemical evaluation of osteoblasts cultured on bioactive glass, hydroxylapatite, titanium alloy, and stainless steel (1993) J. Biomed. Mater. Res., 27, pp. 465-475; Bessey, O.A., Lowry, O.H., Breck, M.J., A method for the rapid determination of alkaline phosphatase with five cubic millimeters of serum (1946) J. Biol. Chem., 164, pp. 321-326; Karster, U., Wollenberger, A., Improvements in the ethidium bromide method for direct fluorometric estimation of DNA and RNA in cell and tissue homogenates (1977) Anal. Biochem., 77, pp. 464-470; McGee-Russell, S.M., Histochemical methods for calcium (1958) J. Histochem. Cytochem., 6, pp. 22-42; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulte formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Tassinari, M.S., Stein, G.S., Lian, J.B., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J. Cell Physiol., 143, pp. 213-221; Gotoh, Y., Hiraiwa, K., Narajama, M., In vitro mineralization of osteoblastic cells derived from human bone (1990) Bone Miner., 8, pp. 239-250; Cheng, S.L., Yang, J.W., Rifas, L., Zhang, S.F., Avioli, L.V., Differentiation of human bone marrow osteogenic stromal cells in vitro. Induction of the osteoblast phenotype by dexamethasone (1994) Endocrinology, 134, pp. 277-286; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Berridge, V., Tan, A.S., Characterization of the cellular reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT): Subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch. Biochem. Biophys, 303, pp. 474-482; Ciapetti, G., Cenni, E., Stea, S., Pizzoferrato, A., In vitro evaluation of cell/biomaterial interaction by MTT assay (1993) Biomaterials, 14, pp. 359-364; Sgouras, D., Duncan, R., Methods for the evaluation of biocompatibility of soluble synthetic polymers which have potential for biomedical use: 1-Use of the tetrazolium-based colorimetric assay (MTT) as a preliminary screen for evaluation of in vitro cytotoxicity (1990) J. Mater. Sci. Mater. Med., 1, pp. 61-68; Martin, A., Clynes, M., Comparison of 5 microplate colorimetric assays for in vitro cytotoxicity testing and cell proliferation assays (1993) Cytotechnology, 11, pp. 49-58; Stein, G.S., Lion, J.B., Molecular mechanisms mediated proliferation-differentiation interrelationships during progressive development of the osteoblast phenotype: Update 1995 (1995) Endosc. Rev., 4, pp. 290-297; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., The ultradtructure of the bone hydroxyapatite interface in vitro (1992) J. Biomed, Mater. Res., 26, pp. 1365-1382; Davies, J.E., Chernecky, R., Lowenberg, B., Shiga, A., Deposition and resorption of calcified matrix in vitro by rat marrow cells (1991) Cells Mater., 1, pp. 3-15; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., De Bruijn, J.D., Van Blitterswijk, C.A., Effects of AISI 316L corrosion products in in vitro bone formation (1998) Biomaterials, 19, pp. 999-1007; Pohler, E.M., Degradation of metallic orthopedic implants (1983) Biomaterials in Reconstructive Surgery, pp. 158-228. , L. R. Rubin (ed.), C. V. Mosby, St. Louis, Missouri; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Miner., 14, pp. 27-40; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralization of osteoid nodules in vitro (1992) Bone Miner., 17, pp. 15-29; Chung, C.H., Golub, E.E., Forbes, E., Tokuoka, T., Shapiro, I.M., Mechanisms of action of β-glycerophosphate on bone cell mineralization (1992) Calcif. Tissue Int., 51, pp. 305-311; Boskey, A.L., Stiner, D., Doty, S.B., Binderman, I., Levoy, P., Studies of mineralization in tissue culture: Optimal conditions for cartilage calcification (1992) Bone Miner., 16, pp. 11-36; Rae, T., The toxicity of metals used in orthopaedic prostheses (1981) J. Bone Joint Surg., 63 B, pp. 435-440; Webb, M., Weinzierl, S.M., Uptake of 63Ni 2+ from its complexes with proteins and other ligands by mouse dermal fibroblasts in vitro (1972) Br. J. Cancer, 26, pp. 292-298; Katz, S.A., Salem, H., The toxicology of chromium with respect to its speciation: A review (1993) J. Appl.Toxicol., 13, pp. 217-224; Pules, D.A., Huh, W.W., Acute toxicity of metal ions in cultures of osteogenic cells derived from bone marrow stromal cells (1995) J. Appl. Biomater., 6, pp. 109-116; Thompson, G.J., Pules, D.A., Effects of sublethal metal ion concentrations on osteogenic cells derived from bone marrow stromal cells (1995) J. Appl. Biomater., 6, pp. 249-258
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; alkaline phosphatase; animal cell; Animal cell culture; Animals; article; Biocompatible Materials; Biodegradation; biomineralization; Bioprosthesis; Bone; Bone and Bones; bone atrophy; bone marrow; Calcification, Physiologic; Calcium; calcium ion; Catalyst activity; Cells, Cultured; Chromium; controlled study; Corrosion; Corrosion products; Enzymes; Implants (surgical); metal implantation; mineralization; Nickel; nonhuman; osteoblast; Osteoblast-like cells; phosphate; phosphorus; prosthesis loosening; rat; Rats; Scanning electron microscopy; Stainless steel; Stainless steel corrosion products; Steel; Steel corrosion; tissue necrosis; transmission electron microscopy

Effects of AISI 316L corrosion products in in vitro bone formation - Morais, S.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S.; De Bruijn, J.D.; Van Blitterswijk, C.A. (BiomaterialsBiomaterials, 1998)
Rat bone marrow cells were cultured in experimental conditions that favour the proliferation and differentiation of osteoblastic cells (i.e., 2.52 x 10
Cited By (since 1996): 38Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(97)00234-2PubMed ID: 9692798Language of Original Document: EnglishCorrespondence Address: Morais, S.; Universidade do Porto, Porto, PortugalChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Calcium Phosphates; Calcium, 7440-70-2; Phosphorus, 7723-14-0; Stainless Steel, 12597-68-1References: Spector, M., Cease, C., Tong-Li, X., The local tissue response to biomaterials (1989) Crit Rev Biocompat, 5, pp. 269-295;Van Blitterswijk, C.A., Bakker, D., Hesseling, S.C., Koerten, H.K., Reactions of cells at implant surfaces (1991) Biomaterials, 12, pp. 187-193; Bagambisa, F.B., Kappert, H.F., Schilli, W., Interfacial reactions of osteoblasts to dental and implant materials (1994) J Oral Maxillofac Surg, 52, pp. 52-56; Bruijn, J.D., Van Blitterswijk, C.A., Davies, J.E., Initial bone matrix formation at the hydroxyapatite interface in vivo (1995) J Biomed Mat Res, 29, pp. 89-99; Pilliar, R.M., Porous-surface metallic implants for orthopedic applications (1987) J Biomed Mat Res, 21 (A1), pp. 1-33; Bobyn, J.D., Tanzer, M., Drygier, J.J., Du Joune, A.R., Brooks, C.E., Concerns with modularity in total hip arthroplasty (1994) Clin Orthop, 298, pp. 27-36; Bartolozzi, A., Black, J., Chromium concentrations in serum, blood clot and urine from patients following total hip arthroplasty (1985) Biomaterials, 6, pp. 2-8; Dorr, L.D., Blocbaum, R., Emmanual, J., Meldrum, R., Histologic, biochemical and ion analysis of tissue and fluids retrieved during total hip arthroplasty (1990) Clin Orthop, 261, pp. 82-95; Hennig, F.F., Raithel, H.J., Schaller, K.H., Dohler, J.R., Nickel-chromand cobalt-concentrations in human tissue and body fluids of hip prosthesis patients (1992) J Trace Elem Electrolytes Health Dis, 6, pp. 239-243; Evans, E.M., Freeman, M.A.R., Miller, A.J., Vernon-Roberts, B., Metal sensitivity as a cause of bone necrosis and loosening of the prosthesis in total joint replacement (1974) J Bone Jt Surg, 56 B, pp. 626-642; Deutman, R., Rulder, T.J., Brian, R., Nater, J.P., Metal sensitivity before and after total hip arthroplasty (1977) J Bone Jt Surg, 59 A, pp. 862-865; Huo, M.H., Salvati, E.A., Lieberman, Jr., Betts, F., Bansal, M., Metallic debris in femoral endoseolysis in failed cemented total hip arthroplasties (1992) Clin Orthop, 276, pp. 157-168; Kirkpatrick, C.J., Mittermayer, C., Theoretical and practical aspects of testing potential biomaterials in vitro (1990) J Mat Mat Med, 1, pp. 9-13; Kirkpatrick, C.J., A critical view of current and proposed methodologies for biocompatibility testing: Cytotoxicity in vitro (1992) Regulatory Affairs, 4, pp. 13-22; Pizzoferrato, A., Ciapetti, G., Stea, S., Cell culture methods for testing biocompatibility (1994) Clin Mat, 15, pp. 173-190; Bizios, R., Mini review: Osteoblasts: An in vitro model of bone-implant interactions (1994) Biotechnol and Bioeng, 43, pp. 582-585; Pules, D.A., Huh, W.W., Acute toxicity of metal ions in cultures of osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 109-116; Thompson, G.J., Pules, D.A., Effects of sublethal metal ion concentrations on osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 249-258; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., Effects of Co-Cr corrosion products and corresponding separate metal ions on human osteoblast-like cell cultures (1996) J Mater Sc Mater Med, 7, pp. 291-296; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., The use of rat, rabbit or human bone marrow derived cells for cytocompatibility evaluation of metallic elements (1997) J Mater Sc Mater Med, 8, pp. 233-238; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralisation by osteoblast-like cells: Part 1 - Retardation of tissue mineralisation by metal salts Biomaterials 1998; Pereira, M.L., Silva, A., Tracana, R., Carvalho, G.S., Toxic effects caused by stainless steel corrosion products on mouse seminiferous cells (1994) Cytobios, 77, pp. 73-80; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Chromium accumulation and ultrastructural changes in the mouse liver caused by stainless steel corrosion products (1995) J Mater Sci Mater Med, 6, pp. 523-527; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Stainless steel corrosion products cause alterations on mouse spleen cellular populations (1995) J Mater Sci Mater Med, 6, pp. 56-61; Bravo, I., Sousa, S.R., Carvalho, G.S., Barbosa, M., Metals electrochemically dissolved in human serum inhibit T-lymphocyte function (1992) Advances in Biomaterials, pp. 7-11. , Doherty PJ et al., editors. Amsterdam: Elsevier; Carvalho, G.S., Castanheira, M., Diogo, I., Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts (1995) J Mater Sci Mater Med, 7, pp. 77-83; Pohler, O.E.M., Degradation of metallic orthopedic implants Biomaterials in Reconstructive Surgery, pp. 158-228. , Rubin LR, editor. St. Louis: C. V. Mosby, 1983; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tiss Res, 254, pp. 317-330; McGee-Russell, S.M., Histochemical methods for calcium (1958) J Histochem Cytochem, 6, pp. 22-42; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionized calcium in osteoblast-like cell culture medium (1996) Electroanalysis, 8, pp. 1174-1178; Fiske, C.H., Subbarow, Y., The colorimetric determination of phosphorus (1925) J Biol Chem, 66, pp. 373-400; Miller, J.C., Miller, J.N., (1993) Statistics for Analytical Chemistry (3rd Ed.), pp. 32-35. , Massen M, Tyson J, Stockwell P, Miller J, Chalmers R, Harwood E, editors. New York, London: Ellis Horwood, PTR Prentice Hall; De Bruijn, J.D., Cpat, K., De Groot, K., Van Blitterswijk, C.A., The ultrastructure of the one-hydroxyapatite interface in vitro (1992) J Biomed Mat Res, 26, pp. 1365-1382; Davies, J.E., Chernecky, R., Lowenberg, B., Shiga, A., Deposition and resorption of calcified matrix in vitro by rat marrow cells (1991) Cells and Mat, 1, pp. 3-15; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulte formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 143, pp. 213-221; Gotoh, Y., Hiraiwa, K., Narajama, M., In vitro mineralization of osteoblastic cells derived from human bone (1990) Bone Min, 8, pp. 239-250; Cheng, S.L., Yang, J.W., Riffins, L., Differentiation of human bone marrow osteogenic stromal cells in vitro. Induction of the osteoblast phenotype by dexamethasone (1994) Endocrinology, 134, pp. 277-286; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralization of osteoid nodules in vitro (1992) Bone Min, 17, pp. 15-29; Boskey, A.L., Stiner, D., Doty, S.B., Binderman, I., Levoy, P., Studies of mineralization in tissue culture: Optimal conditions for cartilage calcification (1992) Bone Min, 16, pp. 11-36; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Min, 14, pp. 27-40; Chung, C.H., Golub, E.E., Forbes, E., Mechanisms of action of β-glycerophosphate on bone cell mineralization (1992) Calcif Tissue Int, 51, pp. 305-311
Keywords: Absorption spectroscopy; alkaline phosphatase; animal cell; Animal cell culture; Animals; article; ascorbic acid; atomic absorption spectrometry; Bioassay; Biomaterials; bone development; bone marrow cell; Bone Marrow Cells; Calcium; Calcium phosphates; Cell culture; Cell Death; Cells, Cultured; Corrosion; Corrosion products; culture medium; dexamethasone; electrochemical analysis; electrochemistry; Enzymes; glycerophosphate; histochemistry; Histocytochemistry; in vitro study; male; metal ion; Mineralisation; mineralization; nonhuman; ossification; osteoblast; Osteoblast-like cells; Osteoblasts; phosphate; Phosphate minerals; phosphorus; priority journal; rat; Rats; Rats, Wistar; Scanning electron microscopy; Slurries; Stainless steel; Stainless steel 316L; Stainless-steel corrosion products; Steel corrosion

In situ characterization of the p-Si/NH 4F interface during dissolution in the current oscillations regime - Cattarin, S.; Chazalviel, J.-N.; Da Fonseca, C.; Ozanam, F.; Peter, L.M.; Schlichthörl, G.; Stumper, J. (Journal of the Electrochemical SocietyJ Electrochem Soc, 1998)
Several physicochemical properties of the p-Si/NH 4F interface have been monitored by in situ techniques in the regime of current oscillations. Comparison of evolution of infrared absorption, microwave reflectivity, electrode admittance, hydrogen evolution, and electron injection rate shows interesting correlations. An integrated description of the processes involved is attempted on the basis of the current models for the Si/acidic fluoride interface.
Cited By (since 1996): 31Export Date: 21 November 2012Source: ScopusCODEN: JESOALanguage of Original Document: EnglishCorrespondence Address: Cattarin, S.; Ist. Polarografia ed E., C. N. R., 35100 Padova, ItalyReferences: Zhang, X.G., Collins, S.D., Smith, R.L., (1989) This Journal, 136, p. 1561;Smith, R.L., Collins, S.D., (1992) J. Appl. Phys., 71, pp. R1; Jung, K.H., Shih, S., Kwong, D.L., (1993) This Journal, 140, p. 3046; Lewerenz, H.J., Stumper, J., Pettenkofer, C., Greef, R., (1989) Electrochim. Acta, 34, p. 1729; Bitzer, T., Lewerenz, H.J., (1992) Surf. Sci., 269-270, p. 886; Lewerenz, H.J., Bitzer, T., Gruyters, M., Jacobi, K., (1993) This Journal, 140, pp. L44; Lewerenz, H.J., (1992) Electrochim. Acta, 37, p. 847; Chazalviel, J.-N., (1992) Electrochim. Acta, 37, p. 865; Ozanam, F., Chazalviel, J.-N., (1993) J. Electron Spec. Rel. Phenomena, 64-65, p. 395; Ozanam, F., Da Fonseca, C., Chazalviel, J.-N., (1995) Proc. Indian Acad. Sci. (Chem. Sci.), 107, p. 709; Da Fonseca, C., Ozanam, F., Chazalviel, J.-N., (1996) Surface Science, 365, p. 1; Stumper, J., Peter, L.M., (1991) J. Electroanal. Chem., 309, p. 325; Stumper, J., Greef, R., Peter, L.M., (1991) J. Electroanal. Chem., 310, p. 445; Blackwood, D.J., Borazio, A., Greef, R., Peter, L.M., Stumper, J., (1992) Electrochim. Acta, 37, p. 889; Gerischer, H., Lüke, M., (1988) Ber. Bunsenges. Phys. Chem., 92, p. 573; Chazalviel, J.-N., Ozanam, F., Etman, M., Paolucci, F., Peter, L.M., Stumper, J., (1992) J. Electroanal. Chem., 327, p. 343; Aggour, M., Giersig, M., Lewerenz, H.-J., (1995) J. Electroanal. Chem., 383, p. 67; Lehmann, V., (1996) This Journal, 143, p. 1313; Lewerenz, H.J., Aggour, M., (1993) J. Electroanal. Chem., 351, p. 159; Chazalviel, J.-N., Ozanam, F., (1992) This Journal, 139, p. 2501; Cattarin, S., Peter, L.M., Jason Riley, D., (1997) J. Phys. Chem. B, 101, p. 4071; Kirk, C.T., (1988) Phys. Rev. B, 38, p. 1255; Schlichtörl, G., Peter, L.M., (1994) This Journal, 141, pp. L171; Myamlin, V.A., Pleskov, Y.V., (1967) Electrochemistry of Semiconductors, p. 213. , Plenum Press, New York; Chazalviel, J.-N., Da Fonseca, C., Ozanam, F., To be publishedPankove, J.I., (1971) Optical Processes in Semiconductors, p. 75. , Prentice-Hall Inc., Englewood Cliffs, NJ; Tardella, A., Chazalviel, J.-N., (1985) Phys. Rev. B, 32, p. 2439; Peter, L.M., Schlichthörl, G., In preparationRappich, J., Timoshenko, V.Y., Dittrich, T., (1997) Ber. Bunsenges. Phys. Chem., 101, p. 139; Matsumura, M., Morrison, S.R., (1983) J. Electroanal. Chem., 147, p. 157; Franck, U.F., (1974) Faraday Symp. Chem. Soc., 9, p. 137
Keywords: Ammonium compounds; Ammonium fluoride; Dissolution; Electric currents; Electric Impedance; Electrochemical electrodes; Electron injection rate; Hydrogen; Interfaces (materials); Microwave reflectivity; Porous silicon

In situ infrared study of the oscillating anodic dissolution of silicon in fluoride electrolytes - Chazalviel, J.-N.; Da Fonseca, C.; Ozanam, F. (Journal of the Electrochemical SocietyJ Electrochem Soc, 1998)
In the far anodic regime, the anodic dissolution of silicon exhibits a resonant behavior, which results from an oscillating behavior on the microscopic scale. The interface has been investigated using in situ infrared spectroscopy in the strong oscillating regime. The interface oxide film varies in thickness by up to a factor of two, and the oxide quality, as determined from a fine analysis of the infrared polarized spectra, is also found to vary periodically during the oscillation. The relative phase of these periodic variations suggests that the origin of the oscillation mechanism lies in a periodic breakdown of the blocking properties of the oxide, which may be initiated by ion permeation in the outer part of the film. The study of oxide dissolution kinetics evidences a stratified structure of the oxide, with layers of "soft" and "strong" oxide. The fast dissolution of the soft oxide is associated with the periodic drop of the oxide thickness.
Cited By (since 1996): 32Export Date: 21 November 2012Source: ScopusCODEN: JESOALanguage of Original Document: EnglishCorrespondence Address: Chazalviel, J.-N.; Lab. de Phys. de la Matiere Cond., U. de Rech. Associée, CNRS-École Polytechnique, F-91128 Palaiseau-Cedex, FranceReferences: Gerischer, H., Lübke, M., (1988) Ber. Bunsenges. Phys. Chem., 92, p. 573;Gershinskii, A.E., Mironova, L.V., (1989) Élektrokhimiya, 25, p. 1374; (1990) Sov. Electrochem., 25, p. 1224; Chazalviel, J.-N., Etman, M., Ozanam, F., (1991) J. Electroanal. Chem., 297, p. 533; Hassan, H.H., Sculfort, J.-L., Etman, M., Ozanam, F., Chazalviel, J.-N., (1995) J. Electroanal. Chem., 380, p. 55; Hassan, H.H., Fotouhi, B., Sculfort, J.-L., Abdel-Rehiem, S.S., Etman, M., Ozanam, F., Chazalviel, J.-N., (1996) J. Electroanal. Chem., 407, p. 105; Chazalviel, J.-N., (1992) Electrochim. Acta, 37, p. 865; Da Fonseca, C., Ozanam, F., Chazalviel, J.-N., (1996) Surf. Sci., 365, p. 1; Turner, D.R., (1958) This Journal, 105, p. 402; Ozanam, F., Chazalviel, J.-N., Radi, A., Etman, M., (1991) Ber. Bunsenges. Phys. Chem., 95, p. 98; Ozanam, F., Chazalviel, J.-N., Radi, A., Etman, M., (1992) J. Electrochem. Soc., 139, p. 2491; Stumper, J., Greef, R., Peter, L.M., (1991) J. Electroanal. Chem., 310, p. 445; Lewerenz, H.J., Schlichthörl, G., (1992) J. Electroanal. Chem., 327, p. 85; Chazalviel, J.-N., Ozanam, F., Etman, M., Paolucci, F., Peter, L.M., Stumper, J., (1992) J. Electroanal. Chem., 327, p. 343; Chazalviel, J.-N., Ozanam, F., (1992) J. Electrochem. Soc., 139, p. 2501; Lewerenz, H.J., Aggour, M., (1993) J. Electroanal. Chem., 351, p. 159; Lehmann, V., (1995) J. Electrochem. Soc., 143, p. 1313; Ozanam, F., Chazalviel, J.-N., (1993) J. Electron Spectrosc. Relat. Phenom., 64-65, p. 395; Ozanam, F., Da Fonseca, C., Chazalviel, J.-N., (1995) Proc. Indian Acad. Sci. Chem. Sci., 107, p. 709; Da Fonseca, C., Ozanam, F., Chazalviel, J.-N., (1997) Mikrochim. Acta (Suppl.), 14, p. 811; Cattarin, S., Chazalviel, J.-N., Da Fonseca, C., Ozanam, F., Peter, L.M., Schlichthörl, G., Stumper, J., (1998) J. Electrochem. Soc., 145, p. 498; Matsumura, M., Morrison, S.R., (1983) J. Electroanal. Chem., 147, p. 157; Lewerenz, H.J., (1992) Electrochim. Acta, 37, p. 847; Harbecke, B., Heinz, B., Grosse, P., (1985) Appl. Phys. A, 38, p. 263; Gaskell, P.H., Johnson, D.W., (1976) J. Non-Cryst. Solids, 20, p. 171; Kirk, C.T., (1988) Phys. Rev. B, 38, p. 1255; Ozanam, F., Da Fonseca, C., Venkateswara Rao, A., Chazalviel, J.-N., (1997) Appl. Spectrosc., 51, p. 519; Crozier, D., Douglas, R.W., (1965) Phys. Chem. Glasses, 6, p. 240; Handke, M., Mozgawa, W., (1993) Vib. Spectrosc., 5, p. 75; Aggour, M., Giersig, M., Lewerenz, H.J., (1995) J. Electroanal. Chem., 383, p. 67; Sharpe, C.D., Lilley, P., (1980) J. Electrochem. Soc., 127, p. 1918; Peiner, E., Schlachetzki, A., (1992) J. Electrochem. Soc., 139, p. 552; Chazalviel, J.-N., Unpublished workBerreman, D.W., (1963) Phys. Rev., 130, p. 2193
Keywords: Anodic dissolution; Anodic oxidation; Dissolution; infrared spectroscopy; Interfaces (materials); Oxide films; Oxides; Semiconducting silicon

In vitro biomineralization by osteoblast-like cells I. Retardation of tissue mineralization by metal salts - Morais, S.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S. (BiomaterialsBiomaterials, 1998)
The cytocompatibility of stainless steel 316L (SS 316L) corrosion products was investigated with particular focus on the dose- and time-effect of electrochemically dissolved SS and the corresponding separate metal ions on osteogenic bone marrow derived cells. Type AISI 316L stainless steel (Fe 63.9%, Cr 18.0%, Ni 12.5%, Mo 2.8%, Si 1.2%, Mn 1.6% and C 0.025%, weight for weight) was anodically dissolved in Hank's Balanced Salt Solution (HBSS) and diluted to the following concentrations: 500 μgml
Cited By (since 1996): 39Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(97)00149-XPubMed ID: 9678845Language of Original Document: EnglishCorrespondence Address: Carvalho, G.S.; IEC, Universidade do Minho, Largo do Paco, 4719 Braga Codex, PortugalChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Calcium, 7440-70-2; Cations; Chromium, 7440-47-3; Iron, 7439-89-6; Metals; Nickel, 7440-02-0; Phosphates; Stainless Steel, 12597-68-1; Tetrazolium Salts; Thiazoles; thiazolyl blue, 298-93-1References: Evans, E.M., Freeman, M.A.R., Miller, A.J., Vernon-Roberts, B., Metal sensitivity as a cause of bone necrosis and loosening of the prosthesis in total joint replacement (1974) J Bone Jt Surg, 56 B, pp. 626-642;Deutman, R., Rulder, T.J., Brian, R., Nater, J.P., Metal sensitivity before and after total hip arthroplasty (1977) J Bone Jt Surg, 59 A, pp. 862-865; Bartolozzi, A., Black, J., Chromium concentrations in serum, blood clot and urine from patients following total hip arthroplasty (1985) Biomaterials, 6, pp. 2-8; Dorr, L.D., Blocbaum, R., Emmanual, J., Meldrum, R., Histologic, biochemical and ion analysis of tissue and fluids retrieved during total hip arthroplasty (1990) Clin Orthop, 261, pp. 82-95; Henning, F.F., Raithel, H.J., Schaller, K.H., Dohler, J.R., Nickel-, chromium- and cobalt-concentrations in human tissue and body fluids of hip prosthesis patients (1992) J Trace Elem Electrolytes Health Dis, 6, pp. 239-243; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., Effects of Co-Cr corrosion products and corresponding separate metal ions on human osteoblast-like cell cultures (1996) J Mater Sci Mater Med, 7, pp. 291-296; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., The use of rat, rabbit or human bone marrow derived cells for cytocompatibility evaluation of metallic elements (1997) J Mater Sci Mater Med, 8, pp. 233-238; Pules, D.A., Huh, W.W., Acute toxicity of metal ions in cultures of osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 109-116; Thompson, G.J., Pules, D.A., Effects of sublethal metal ion concentrations on osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 249-258; McGee-Russell, S.M., Histochemical methods for calcium (1958) J Histochem Cytochem, 6, pp. 22-42; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulate formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Wong, M., Rao, L.G., Li, H., Long-term effects of physiologic concentrations of dexamethasone on human bone derived cells (1990) J Bone Miner Res, 5, pp. 803-813; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 143, pp. 213-221; Gotoh, Y., Hiraiwa, K., Narajama, M., In vitro mineralisation of osteoblastic cells derived from human bone (1990) Bone Miner, 8, pp. 239-250; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralisation of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Miner, 14, pp. 27-40; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralisation of osteoid nodules in vitro (1992) Bone Miner, 17, pp. 15-29; Chung, C.H., Golub, E.E., Forbes, E., Mechanisms of action of β-glycerophosphate on bone cell mineralisation (1992) Calcif Tissue Int, 51, pp. 305-311; Schimdt, R., Kulbe, K.D., Long term cultivation of human osteoblasts (1993) Bone Miner, 20, pp. 211-221; Cheng, S.L., Yang, J.W., Riffins, L., Differentiation of human bone marrow osteogenic stromal cells in vitro. Induction of the osteoblast phenotype by dexamethasone (1994) Endocrinology, 134, pp. 277-286; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Fernandes, M.H., Costa, M.A., Carvalho, G.S., Mineralisation in serially passaged human alveolar bone cells (1997) J Mater Sci Mater Med, 8, pp. 73-76; Martin, A., Clynes, M., Comparison of 5 microplate colorimetric assays for in vitro cytotoxicity testing and cell proliferation assays (1993) Cytotechnology, 11, pp. 49-58; Sgouras, D., Duncan, R., Methods for the evaluation of biocompatibility of soluble synthetic polymers which have potential for biomedical use. 1. Use of the tetrazolium-based colorimetric assay (MTT) as a preliminary screen for evaluation of in vitro cytotoxicity (1990) J Mater Sci Mater Med, 1, pp. 61-68; Ciapetti, G., Cenni, E., Stea, S., Pizzoferrato, A., In vitro evaluation of cell/biomatrial interaction by MTT assay (1993) Biomaterials, 14, pp. 359-364; Yoshimura, T., Kurita, C., Hayata, M., Nagai, H., Diagnosis of drug allergy by the lymphocyte stimulation test with the MTT (3-(4,5-dimethyl thiazol-2-yl)-2,2-diphenyl tetrazolium bromide) assay (1993) Biol Pharm Bull, 16, pp. 686-689; Sasanaluckit, P., Albustany, K.R., Doherty, P.J., Williams, D.F., Biocompatibility of glass ionomer cements (1993) Biomaterials, 14, pp. 906-916; Carvalho, G.S., Castanheira, M., Diogo, I., Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts (1996) J Mater Sci Mater Med, 7, pp. 77-83; Vrouwenvelder, W.C.A., Groot, C.G., De Groot, K., Histological and biochemical evaluation of osteoblasts cultured on bioactive glass, hydroxylapatite, titanium alloy and stainless steel (1993) J Biomed Mater Res, 27, pp. 465-475; Owen, M., Marrow stromal stem cells (1988) J Cell Sci, 10, pp. 63-76; Beresford, J.N., Osteogenic stem cells and the stromal system of bone and marrow (1989) Clin Orthop Rel Res, 240, pp. 270-280; Owen, T.A., Arohow, M., Shalhonb, V., Progressive development of the rat osteoblast phenotype in vitro: Reciprocal relationships in expression of genes associated with osteoblast proliferation during formation of bone extracellular matrix (1990) J Cell Phys, 143, pp. 420-430; Malaval, L., Modrowski, D., Gupta, K., Aubin, J.E., Cellular expression of bone related proteins during in vitro osteogenesis in rat bone marrow stromal cell cultures (1994) J Cell Phys, 158, pp. 555-572; Stein, G.S., Lion, J.B., Molecular mechanisms mediated proliferation-differentiation interrelationships during progressive development of the osteoblast phenotype: Update 1995 (1995) End Rev, 4, pp. 290-297
Keywords: Absorption spectroscopy; alkaline phosphatase; animal cell; Animalia; Animals; article; ascorbic acid; atomic absorption spectrometry; balanced salt solution; Bioassay; Biocompatibility; biomaterial; Biomaterials; biomineralization; bone marrow cell; bone mineralization; Bovinae; Calcification, Physiologic; Calcium; calcium phosphate; Carbon; Cations; Cattle; Cell Division; cell proliferation; cell survival; cell viability; Cells, Cultured; Chromium; controlled study; Corrosion; dexamethasone; electrochemistry; enzyme activity; Enzyme kinetics; glycerol 2 phosphate; histochemistry; Iron; Kinetics; manganese; metal ion; Metal ions; Metals; molybdenum; Nickel; nonhuman; Oryctolagus cuniculus; osteoblast; Osteoblast cells; Osteoblast-like cells; Osteoblasts; Phosphates; priority journal; rabbit; Rabbits; serum; Silicon; Stainless steel; Steel corrosion; Tetrazolium Salts; Thiazoles; Tissue culture

In vitro biomineralization by osteoblast-like cells II. Characterization of cellular culture supernatants - Morais, S.; Carvalho, G.S.; Faria, J.L.; Gomes, H.T.; Sousa, J.P. (BiomaterialsBiomaterials, 1998)
The quantification of total calcium, phosphorus, iron, chromium and nickel in cell culture medium by electrochemical or spectroscopic means may require digestion of samples. Nevertheless, when pH adjustment is performed for values higher than about 6.5, the formation of two phases occurs: a white precipitate and a clear solution. Analysing both phases using microelectrodes, atomic absorption spectrometry (AAS), diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy. X-ray dispersive (XRD) analysis, scanning electron microscopy (SEM) and energy dispersive spectroscopic (EDS) analysis, it was oberved that iron, chromium and nickel are not co-precipitating with the white solid phase. If quantification of calcium, phosphorus and magnesium is intended, a ten-fold dilution at least, must be performed to avoid most of these elements going into the precipitate. This knowledge is crucial if a mineralization study is going to be made.The quantification of total calcium, phosphorus, iron, chromium and nickel in cell culture medium by electrochemical or spectroscopic means may require digestion of samples. Nevertheless, when pH adjustment is performed for values higher than about 6.5, the formation of two phases occurs: a white precipitate and a clear solution. Analyzing both phases using microelectrodes, atomic absorption spectrometry (AAS), diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy, X-ray dispersive (XRD) analysis, scanning electron microscopy (SEM) and energy dispersive spectroscopic (EDS) analysis, it was observed that iron, chromium and nickel are not co-precipitating with the white solid phase. If quantification of calcium, phosphorus and magnesium is intended, a ten-fold dilution at least, must be performed to avoid most of these elements going into the precipitate. This knowledge is crucial if a mineralization study is going to be made.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(97)00150-6PubMed ID: 9678846Language of Original Document: EnglishCorrespondence Address: Carvalho, G.S.; IEC, Universidade do Minho, Largo do Paco, 4719 Braga Codex, PortugalChemicals/CAS: Calcium, 7440-70-2; Chromium, 7440-47-3; Culture Media; Iron, 7439-89-6; Metals; Nickel, 7440-02-0; Phosphorus, 7723-14-0; Stainless Steel, 12597-68-1References: Pereira, M.L., Silva, A., Tracana, R., Carvalho, G.S., Toxic effects caused by stainless steel corrosion products on mouse seminiferous cells (1994) Cytobios, 77, pp. 73-80;Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Chromium accumulation and ultrastructural changes in the mouse liver caused by stainless steel corrosion products (1995) J Mater Sci Mater Med, 6, pp. 523-527; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Stainless steel corrosion products cause alterations on mouse spleen cellular populations (1995) J Mater Sci Mater Med, 6, pp. 56-61; Bravo, I., Sousa, S.R., Carvalho, G.S., Barbosa, M., Metals electrochemically dissolved in human serum inhibit T-lymphocyte function (1992) Advances in Biomaterials, pp. 7-11. , Doherty PJ, et al., editors. Amsterdam: Elsevier; Carvalho, G.S., Castanheira, M., Diogo, I., Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts (1995) J Mater Sci Mater Med, 7, pp. 77-83; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro bone formation in the presence of stainless steel corrosion products (1994) Poster Section, 11th European Conference on Biomaterials, , Pisa, Italy; Sousa, J.P., Requirements in materials for biosensors J Mater Sci Mater Med, , in press; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralisation by osteoblast like cells. I. Retardation of tissue mineralisation by metal salts (1998) Biomaterials, 19, pp. 13-21; Morais, S., Carvalho, G.S., Sousa, J.P., Determination of nickel in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with mercury microelectrodes (1997) Electroanalysis, 9 (5), pp. 422-426; Morais, S., Carvalho, G.S., Sousa, J.P., Optimization study for nickel quantification in cell culture medium using mercury film microelectrodes (1996) Portugaliae Electrochimica Acta, 14, pp. 267-272; Morais, S., Carvalho, G.S., Sousa, J.P., Iron determination in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode (1997) Electroanalysis, 9, pp. 791-795; Morais, S., Carvalho, G.S., Sousa, J.P., Chromium determination in osteoblast-like cell culture medium by catalytic stripping voltammetry with a mercury microelectrode Electroanalysis, , submitted for publication; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionised calcium in osteoblast-like cell culture medium (1996) Electroanalysis, 8 (12), pp. 1174-1178; Morais, S., Carvalho, G.S., Sousa, J.P., Inorganic phosphorus determination in osteoblast-like cell culture for in vitro mineralisation study (1996) Poster Section, 15th Meeting of the Portuguese Chemical Society, , Porto; Pend, J., Jin, W., Anodic stripping voltammetric determination of trace lead in micro-samples with a mercury ultramicroelectrode (1992) Anal Chim Acta, 264, pp. 213-219; Pereira, M.C., Faria, J.L., Reis, M.L., Sousa, J.P., Nickel quantification in mice organs by adsorptive cathodic stripping voltammetry using mercury microelectrodes (1997) Electroanalysis, 9, p. 1501; Wurfels, W., Jackwerth, E., Stoeppler, M., Residues from biological materials after pressure decomposition with nitric acid. Part 3a (1989) Anal Chim Acta, 226, pp. 31-41; Wurfels, W., Jackwerth, E., Stoeppler, M., Residues from biological materials after pressure decomposition with nitric acid. Part 2a (1989) Anal Chim Acta, 226, pp. 17-30; Kotz, L., Henze, G., Kaiser, G., Pahlke, S., Veber, R., Tolg, G., Wet mineralisation of organic matrices in glassy carbon vessels in a pressure-bomb system for trace element analysis (1979) Talanta, 26, pp. 681-691; Nakamoto, K., (1970) Infrared Spectra of Inorganic and Coordination Compounds, 2nd Edn., , NY: Wiley Interscience; Lin-Vien, D., Colthup, N.B., Fateley, W.G., Grasselli, J.G., (1991) The Handbook of Infrared and Raman Characteristic Frequencies of Organic Molecules, , Boston: Academic Press; Walsh, W.R., Christiansen, D.L., Demineralized bone matrix as a template for mineral-organic composites (1995) Biomaterials, 16 (18), pp. 1363-1371; Koeneman, J., Lemons, J., Ducheyne, P., Lacefield, W., Magee, F., Calahan, K.J., Workshop on characterisation of calcium phosphate materials (1990) J Appl Biomater, 1, pp. 79-90; Mann, S., Webb, J., Williams, R.J.P., (1989) Biomineralization: Chemical and Biochemical Perspectives, , Germany: VCH, Weinheim; Evans, E.M., Freeman, M.A.R., Miller, A.J., Vernon-Roberts, B., Metal sensitivity as a cause of bone necrosis and loosening of the prosthesis in total joint replacement (1974) J Bone Jt Surg, 566, pp. 626-642; De Vernejoul, M.C., Pointillart, A., Golenzer, C.C., Metals in bone (1985) Lancaster, pp. 321-331. , Priest ND, editor. MTT; Kusec, R., Nikolic, V., Hancevic, J., Davila, S., Alkovic, V., Trace elements in periosteal callus and cortical bone after plating for fracture (1990) Periodicum Biologorum, 92 (3), pp. 325-327; Betts, F., Wright, T., Salvati, E.A., Boskey, A., Mansal, M., Cobalt alloy metal debris in periarticular tissues from total hip revision arthoplasties (1992) Clin Orthop, 278, pp. 75-82; Brien, W.W., Salvati, E.A., Betts, F., Metal levels in cemented total hip arthroplasty: A comparison of well-fixed and loose implants (1992) Clin Orthop, 276, pp. 66-74
Keywords: Absorption spectroscopy; Animals; article; atomic absorption spectrometry; Biomaterials; bone mineralization; Calcification, Physiologic; Calcium; Cell culture medium; Cells, Cultured; Chromium; Culture Media; culture medium; Diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy; electrochemistry; Energy dispersive spectroscopic analysis; Fourier transform infrared spectroscopy; Hydrogen-Ion Concentration; infrared spectroscopy; Iron; Magnesium; Metals; microelectrode; Microelectrodes; Nickel; nonhuman; osteoblast; Osteoblast cells; Osteoblasts; pH effects; phosphorus; precipitation; Precipitation (chemical); priority journal; Rabbits; Scanning electron microscopy; Spectrophotometry, Atomic; Spectroscopic techniques; Spectroscopy; Stainless steel; supernatant; Supernatants; Tissue culture; X ray analysis; X ray dispersive analysis

New starch-based thermoplastic hydrogels for use as bone cements or drug-delivery carriers - Pereira, C.S.; Cunha, A.M.; Reis, R.L.; Vázquez, B.; San Román, J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1998)
The development of new biodegradable hydrogels, based on corn starch/cellulose acetate blends, produced by free-radical polymerization with methyl methacrylate monomer (MMA) and/or an acrylic acid monomer (AA), is reported. The polymerization was initiated by a redox system consisting of a benzoyl peroxide and 4-dimethlyaminobenzyl alcohol at low temperature. These hydrogels may constitute an alternative to the materials currently used as bone cements or drug-delivery carriers. Swelling studies were carried out, as a function of pH and temperature, in buffered solutions. The xerogels were further characterized by Fourier transform-infrared spectroscopy. Tensile and compression tests, and dynamic mechanical thermal analysis were used to assess the mechanical performance of the developed materials. The fracture surfaces were observed by scanning electron microscopy. The developed materials are sensitive to the pH, showing a clear reversible transition in a relatively narrow interval of pH, which is just in the range of physiological conditions. These properties make the materials developed in this study very promising for biomedical applications. Fickian-type diffusion is the mechanism predominant in these systems, except for the composition with a higher concentration of AA, that corresponds to the most desirable kinetical behavior for controlled release (case II-transport mechanism). Furthermore, the results obtained in the mechanical tests are in the range of those reported for typical PMMA bone cements, showing that it is possible to develop partially degradable cements with an adequate mechanical behavior.
Cited By (since 1996): 67Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1008944127971Language of Original Document: EnglishCorrespondence Address: Reis, R.L.; INEB-Inst for Biomedical Engineering, Biomaterials Laboratory, Rua do Campo Alegre 823, 4150 Porto, Portugal; email: rgreis@fe.up.ptChemicals/CAS: acrylic acid, 10344-93-1, 79-10-7; alcohol, 64-17-5; benzoyl peroxide, 94-36-0; cellulose acetate, 9004-35-7; poly(methyl methacrylate), 39320-98-4, 9008-29-1; starch, 9005-25-8, 9005-84-9Tradenames: AA, Merck, Germany; BPO, Merck, Germany; Master-Bi Y101U, novamont, Italy; MMA, Merck, GermanyManufacturers: Merck, Germany; novamont, ItalyReferences: Peppas, N.A., Mikos, A.G., (1988) Hydrogels in Medicine and Pharmacy-Fundamentals, 1, p. 1. , edited by N. A. Peppas CRC Press, Boca Raton, FL;Netti, P.A., Shelton, J.C., Revell, P.A., Pirie, C., Smith, S., Ambrosio, L., Nicolais, L., Bonfield, W., (1993) Biomaterials, 14, p. 1098; Woerly, S., (1993) Biomaterials, 14, p. 1056; Peppas, N.A., (1996) Biomaterials Science an Introduction to Materials in Medicine-Part I, p. 60. , edited by B. D. Ratner, A. S. Hoffman, F. J. Schoen and J. E. Lemons Academic Press, London; Pascual, B., Castellano, I., Vázquez, B., Gurruchaga, M., Goñi, I., (1996) Polymer, 37, p. 1005; Mack, E.J., Okano, T., Kim, S.W., (1988) Hydrogels in Medicine and Pharmacy-Polymers, 2, p. 65. , edited by N. A. Peppas CRC Press, Boca Raton, FL; Karadag, E., Saraydin, D., Çetinkaya, S., Guven, O., (1996) Biomaterials, 17, p. 67; Kim, S.W., Bae, Y.H., Okano, T., (1992) Pharmaceut. Res., 9, p. 283; Blanco, M.D., García, O., Trigo, R.M., Teijon, J.M., Katime, I., (1996) Biomaterials, 17, p. 1061; Abusafieh, A., Siegler, S., Kalidingi, S.R., (1997) J. Biomed. Res., 38, p. 314; Norman, T.L., Kish, V., Blaha, J.D., Gruen, T.A., Hustosky, K., (1995) J. Biomed. Mater. Res., 29, p. 495; Yang, J., (1997) Biomaterials, 18, p. 1293; Lewis, G., Nyman, J.S., Trieu, H.H., (1997) J. Biomed. Mater. Res., 38, p. 221; Lewis, G., (1997) J. Biomed. Mater. Res., 38, p. 155; Domb, A.J., Manor, N., Elmalak, O., (1996) Biomaterials, 17, p. 411; Kost, J., Langer, R., (1988) Hydrogels in Medicine and Pharmacy-Properties and Applications, 3, p. 95. , edited by N. A. Peppas CRC Press, Boca Raton, FL; Lohmann, D., (1995) Macromol. Symp., 100, p. 25; Ogawa, Y., (1997) J. Biomater. Sci. Polymer Edn, 8, p. 391; Di Silvio, L., Gurav, N., Kayser, M.V., Braden, M., Downes, S., (1994) Biomaterials, 15, p. 931; Andreopoulos, A.G., (1994) Clin. Mater., 15, p. 691; Langer, R., (1995) MRS Bull., p. 18; Heller, J., (1996) Applications of Materials in Medicine and Dentistry-Part II, p. 346. , edited by B. D. Ratner, A. S. Hoffman, F. J. Schoen and J. E. Lemons Academic Press, London; Bastioli, C., (1994) Recycle'94 - Davos Global Forum and Exposition, , Switzerland, March; Bastioli, C., (1995) Degradadble Polymers-Principles and Applications, p. 112. , Chapman and Hall, London; Reis, R.L., Cunha, A.M., (1995) J. Mater. Sci. Mater. Med., 6, p. 786; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1996) Polym. Adv. Technol., 7, p. 784; Reis, R.L., Mendes, S.C., Cunha, A.M., Bevis, M.J., (1997) Polym. Int., 43, p. 347; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1997) Adv. Poly. Technol., 16, p. 263; Reis, R.L., Cunha, A.M., Bevis, M.J., (1997) Med. Plast. Biomateri., p. 46; Pereira, C.S., Gomes, M.E., Reis, R.L., Cunha, A.M., (1998) Foams, Emulsion and Cellular Materials, , edited by J. F. Sadoc and N. River NATO/ASI series, Kluwer Press, Dordrecht, in press; Reis, R.L., Cunha, A.M., (1998) Antec'98-Plastics on My Mind, , Society of Plastics Engieers, Atlanta, April/May in press; Reis, R.L., Cunha, A.M., (1998) Antec'98-Plastics on My Mind; Elvira, C., Levenfeld, B., Vázquez, B., San Román, J., (1996) J. Polym. Sci. A Polym. Chem., 34, p. 2783; Liso, P.A., Vázquez, B., Rebuelta, M., Hernáhz, M.L., Rotger, R., San, J., (1997) Biomaterials, 18, p. 15; Vázquez, B., Elvira, C., Levenfeld, B., Pascual, B., Goñi, I., Gurruchaga, M., Ginerba, M.P., San Róman, J., (1997) J. Biomed. Mater. Res., 34, p. 129; Vázquez, B., Elvira, C., San Román, J., Levenfeld, B., (1997) Polymer, 38, p. 4365; Castellano, I., Pascual, B., Vázquez, B., Goñi, I., Gurrruchaga, M., (1994) J. Appl. Polym. Sci., 54, p. 577; Jane, J., (1995) J.M.S. Pure Appl. Chem., A32, p. 751; Peppas, N.A., Korsmeyer, R.W., (1988) Medicine and Pharmacy-Properties and Applications, 3, p. 109. , edited by N. A. Peppas CRC Press, Boca Raton, FL; Saha, S., Pal, S., (1984) J. Biomed. Mater. Res., 18, p. 435; Lautenschlager, E.P., Moore, B.K., Schoenfeld, C.M., (1974) J. Biomed. Mater. Res. Symp., p. 185; Migiaresi, C., Fambri, L., Kolanik, J., (1994) Biomaterials, 15, p. 875; Topoleski, L.D.T., Ducheyne, P., Cuckler, J.M., (1993) Biomaterials, 14, p. 1165; Clarke, R.L., (1989) Biomaterials, 10, p. 494
Keywords: acrylic acid; alcohol; article; benzoyl peroxide; Biodegradation; bone cement; buffer; cellulose acetate; compression; Diffusion; drug delivery system; dynamics; fracture; free radical; hydrogel; infrared spectroscopy; Kinetics; low temperature; mechanical stress; oxidation reduction reaction; pH; poly(methyl methacrylate); Polymerization; priority journal; Scanning electron microscopy; Starch; tensile strength; Thermal analysis

Objective computerized fetal heart rate analysis - Bernardes, J.; Ayres-de-Campos, D.; Costa-Pereira, A.; Pereira-Leite, L.; Garrido, A. (International Journal of Gynecology and ObstetricsInt. J. Gynecol. Obstet., 1998)
Objective: To assess the validity of a computerized methodology for cardiotocogram analysis based on a recently described reproducible visual estimation of the baseline. Methods: Forty-two antepartum and 43 intrapartum cardiotocograms (CTGs) acquired by a personal computer were selected. Antepartum tracings were performed in the 48 h that preceded an elective cesarean section, and intrapartum tracings were performed until delivery. FHR baselines were estimated by an expert, according to an objective and reproducible methodology. Using these baselines, automated detection of accelerations and decelerations and estimation of variability was performed by the personal computer. A quantitative adaptation of the FIGO guidelines for fetal monitoring was used to classify tracings. Perinatal outcome was classified according to the Apgar score and umbilical arterial pH. Validity was then assessed by the proportions of agreement (PA), kappa statistic (κ), sensitivity and specificity, with 95% confidence intervals (95% CI). Cases showing a disagreement between CTG and perinatal classification were reviewed and an adjustment in baseline definition was tested. Results: The initial overall PA and κ between CTG and perinatal classification were, respectively, 0.79 (95% CI: 0.69-0.87) and 0.62 (95% CI: 0.41-0.83). The overall PA and κ, after baseline adjustment were, respectively, 0.89 (95% CI: 0.81-0.95) and 0.78 (95% CI: 0.58-0.98). Sensitivities and specificities ranged between 79% (95% CI: 60-92%) and 100% (95% CI: 95-100%). Conclusions: Good clinical prediction may be possible with an objective methodology for cardiotocogram analysis based on a recently described reproducible baseline estimation.
Cited By (since 1996): 23Export Date: 21 November 2012Source: ScopusCODEN: IJGOAdoi: 10.1016/S0020-7292(98)00079-4PubMed ID: 9749885Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Departmento Ginecologia Obstetricia, Faculdade Medicina-Hospital S. Joao, Porto, Portugal; email: sisporto@mail.telepac.ptReferences: Bernardes, J., Costa-Pereira, A., Ayres-De-Campos, D., Van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57 (1), pp. 33-37;Bernardes, J., Costa-Pereira, A., Van Geijn, H.P., Pereira-Leite, L., A more objective fetal heart rate baseline estimation (1996) Br J Obstet Gynaecol, 103, pp. 714-715; Grant, A., Principles for clinical evaluation of methods of perinatal monitoring (1984) J Perinat Med, 12, pp. 227-231; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Pereira-Leite, L., Van Geijn, H.P., The Porto System (1994) A Critical Appraisal of Fetal Surveillance, pp. 315-324. , In: van Geijn HP, Copray FJA, editors. Amsterdam: Elsevier Science; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring. FIGO news (1987) Int J Gynaecol Obstet, 25, pp. 159-167; Mohide, P., Grant, A., Evaluating diagnosis and screening during pregnancy and childbirth (1989) Effective Care in Pregnancy and Childbirth, pp. 66-80. , In: Chalmers I, Enkin M, Keirse M JNC, editors. Oxford University Press; Garcia-Romero, H., Garcia-Barrios, C., Ramos-Gutierrez, F.R., Effects of uncertain results on sensitivity and specificity of diagnostic tests (1996) Lancet, 348, pp. 1745-1746; Grant, J.M., The fetal heart rate is normal, isn't it?. Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Guzman, E., Vintzileos, A., Martins, M., Benito, C., Houlihan, C., The efficacy of individual computer heart rate indices in detecting acidemia at birth in growth-restricted fetuses (1996) Obstet Gynecol, 87, pp. 969-974; Nielsen, P.V., Stigsby, B., Nickelsen, C., Nim, J., Computer assessment of the intrapartum cardiotocogram. II. The value of compared with visual assessment (1988) Acta Obstet Gynecol Scand, 67, pp. 461-464; Chung, T.K.H., Mohajer, M.P., Yang, Z.J., Chang, A.M.Z., Sahota, D.S., The prediction of fetal acidosis at birth by computerized analysis of intrapartum cardiotocography (1995) Br J Obstet Gynaecol, 102, pp. 454-460; Stigsby, B., Nielson, P.V., Nickelsen, C., Nim, J., Computer assessment of the intrapartum cardiotocogram. I. Methods of data reduction and diagnostic procedure (1988) Acta Obstet Gynecol Scand, 67, pp. 455-460
Keywords: Apgar score; arterial pH; article; Cardiotocography; cesarean section; computer analysis; Computerized analysis; Female; Fetal heart rate; fetus; fetus heart rate; fetus monitoring; Heart Rate, Fetal; human; Humans; Image Processing, Computer-Assisted; practice guideline; Predictive Value of Tests; Pregnancy; priority journal; umbilical artery; validity

Semiautomated ultrasonographic measurement of fetal nuchal translucency using a computer software tool - Bernardino, F.; Cardoso, R.; Montenegro, N.; Bernardes, J.; Marques de Sá, J. (Ultrasound in Medicine and BiologyUltrasound Med. Biol., 1998)
Nuchal translucency (NT) thickness measurement has been recently proposed as a part of routine ultrasound scanning during the late first trimester of pregnancy, for the early screening of chromosomal abnormalities. Manual determination of NT is currently performed using electronic callipers placed by the operator in the middle of two echogenic fines displayed on the screen. Therefore, intraobserver and interobserver repeatability can be questioned. This paper presents a software tool that has been developed for achieving this goal in a semiautomatic way, improving the reproducibility of the method.Nuchal translucency (NT) thickness measurement has been recently proposed as a part of routine ultrasound scanning during the late first trimester of pregnancy, for the early screening of chromosomal abnormalities. Manual determination of NT is currently performed using electronic callipers placed by the operator in the middle of two echogenic lines displayed on the screen. Therefore, intraobserver and interobserver repeatability can be questioned. This paper presents a software tool that has been developed for achieving this goal in a semiautomatic way, improving the reproducibility of the method.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: USMBAdoi: 10.1016/S0301-5629(97)00235-4PubMed ID: 9483771Language of Original Document: EnglishCorrespondence Address: Marques De Sa, J.; Instituto de Engenharia Biomedica, Pt. Coronel Pacheco 1, P-4050 Porto, Portugal; email: jmsa@garfield.fe.up.ptTradenames: Microsoft Visual C++, microsoft, United StatesManufacturers: microsoft, United StatesReferences: Jain, A.K., (1982) Fundamentals of Digital Image Processing, , New York: Prentice Hall International Editions;Neilson, J., Grant, A., Ultrasound in pregnancy (1989) A Guide to Effective Care in Pregnancy and Childbirth., pp. 48-56. , Enkin M, Keirse MJN, Chalmers I. eds. New York, London: Oxford University Press; Nicolaides, K.H., Azar, G., Byrne, D., Mansur, C., Marks, K., Fetal nuchal translucency: Ultrasound screening for chromosomal detects in first trimester of pregnancy (1992) BMJ, 304, pp. 867-869; Pandya, P.P., Brizot, M.L., Kuhn, P., Snijders, R.J.M., Nicolaides, K.H., First trimester fetal nuchal translucency thickness and risk for trisomies (1994) Obstet Gynecol, 84, pp. 420-423; Pandya, P.P., Kondylios, A., Hilbert, L., Snijders, R.J.M., Nicolaides, K.H., Chromosomal defects and outcome in 1015 fetuses with increased nuchal translucency (1995) Ultrasound Obstet Gynecol, 5, pp. 15-19; Pandya, P.P., Altman, D.G., Brizot, M.L., Pettersen, H., Nicolaides, K.H., Repeatability of measurement of fetal nuchal translucency thickness (1995) Ultrasound Obstet Gynecol, 5, pp. 334-337; Roberts, L.J., Bewley, S., Mackinson, A.M., Rodeck, C.H., First trimester fetal nuchal translucency: Problems of screening the general population (1995) Br J Obstet Gynaecol, 102, pp. 381-385; Zador, I.E., Salari, V., Sokol, R.J., Computer applications in fetal medicine (1994) The Fetus As A Patient, pp. 117-124. , Kurjak A, Chervenak FA, eds. London/ New York: Parthenon Publ
Keywords: article; cervical spine; chromosome aberration; Chromosome Aberrations; Chromosome Disorders; Computer aided diagnosis; computer program; Computer software; computer system; Female; Fetal monitoring; Fetal nuchal translucency; fetus echography; first trimester pregnancy; Humans; Image analysis; Image Processing, Computer-Assisted; Image thresholding; Medical imaging; Neck; observer variation; Pregnancy; Pregnancy Trimester, First; priority journal; reproducibility; Reproducibility of Results; Software; Software package NUCA; Thickness measurement; Ultrasonic imaging; Ultrasonography, Prenatal; ultrasound

Guided bone regeneration using osteopatite® granules and polytetrafluoroethylene membranes - Vasconcelos, M.; Afonso, A.; Branco, R.; Cavalheiro, J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1997)
Granules of a modified hydroxyapatite, Osteopatite®, were implanted in the right posterior tibiae of adult rabbits. We studied the extent of bone regeneration in bone holes. In the right tibiae, that were filled with granules of this biomaterial covered with a polytetrafluoroethylene (PTFE) membrane using, as a control, uncovered granules. In the left tibia, an empty hole was covered with PTFE membrane and a second hole was left empty to be used as a control. A histomorphometric study was carried out using light microscopy, four and eight weeks after the surgery. The covered granules presented a higher percentage of bone contact than the uncovered ones, and it was also possible to observe a better bone tissue organization, mainly produced by the immobilization action of the PTFE membrane. Empty bone defects covered with PTFE membranes, two months after implantation, presented large areas of Haversian bone and direct bone contact to the PTFE membrane.Granules of a modified hydroxyapatite, Osteopatite, were implanted in the right posterior tibiae of adult rabbits. We studied the extent of bone regeneration in bone holes. In the right tibiae, that were filled with granules of this biomaterial covered with a polytetrafluoroethylene (PTFE) membrane using, as a control, uncovered granules. In the left tibia, an empty hole was covered with PTFE membrane and a second hole was left empty to be used as a control. A histomorphometric study was carried out using light microscopy, four and eight weeks after the surgery. The covered granules presented a higher percentage of bone contact than the uncovered ones, and it was also possible to observe a better bone tissue organization, mainly produced by the immobilization action of the PTFE membrane. Empty bone defects covered with PTFE membranes, two months after implantation, presented large areas of Haversian bone and direct bone contact to the PTFE membrane.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1018533217238Language of Original Document: EnglishCorrespondence Address: Vasconcelos, M.; Faculty of Dental Medicine, University of Porto, Rua Dr. Roberto Frias, 4200 Porto, PortugalTradenames: OsteopatiteReferences: Cavalheiro, J., Branco, R., Vasconcelos, M., (1991) Proceedings of the 4th International Conference on Bioceramics, p. 205. , edited by W. Bonfield, G. W. Hastings and K. E. Tanner, London, UK Butterworth-Heinemann, Oxford;Cavalheiro, J., Vasconcelos, M., Afonso, A., Peres, F., Branco, R., (1994) Stoma, 30, p. 15; Dahlin, C., Lekholm, U., Becker, W., Becker, B., Higuchi, K., Callens, A., Steenberghe, D., (1995) Int. J. Oral Maxillofac. Implants, 3, p. 312; Aughtun, M., Doz, P., Yildirim, M., Spiekermann, H., Biesterfeld, S., (1995) Int. J. Oral Maxillofac. Implants, 4, p. 421; Simion, M., Scarano, A., Gionso, L., Piattelli, A., (1995) Int. J. Oral Maxillofac. Implants, 3, p. 312; Afonso, A., Santos, J.D., Vasconcelos, M., Branco, R., Cavalheiro, J., (1996) J. Mater. Sci: Mater. Med., 7, p. 507; Jovanovic, S.A., Schenk, R.K., Orsini, M., Kenney, E.B., (1995) Int. J. Oral Maxillofac. Implants, 1, p. 27; Sander, L., Karring, T., (1995) J. Clin. Periodontol., 22, p. 295; Grevstad, H.J., Leknes, K.N., (1993) J. Clin. Periodontol., 20, p. 193; Piattelli, A., Scarano, A., Russo, P., Matarasso, S., (1996) Biomaterials, 17, p. 791
Keywords: animal experiment; Animalia; biomaterial; Bone; bone defect; Bone Regeneration; conference paper; controlled study; haversian canal; hydroxyapatite; Implants (surgical); microscopy; nonhuman; Optical microscopy; Oryctolagus cuniculus; Phosphate minerals; politef; Polymeric membranes; Polytetrafluoroethylenes; priority journal; rabbit; tibia

Iron Determination in Osteoblast-Like Cell Culture Medium by Adsorptive Cathodic Stripping Voltammetry with a Mercury Microelectrode - Morais, S.; Carvalho, G.S.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1997)
Mercury film microelectrodes were used to determine iron in osteoblast-like cell culture medium by performing adsorptive cathodic stripping voltammetry in the presence of catechol. The optimized analytical conditions are a catechol concentration of 5.00×10
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: ELANELanguage of Original Document: EnglishCorrespondence Address: Sousa, J.P.; Inst. de Engenharia Biomedica, Depto. de Engenharia Química, Universidade do Porto, Praça Coronel Pacheco, 1, 4050 Porto, PortugalReferences: Cigada, A., (1994) Proc. Symp. Compatibility of Biomedical Implants, 94 (15), pp. 185-192. , (Eds.: P. Kovacs, N.S. Istephanous), The Electrochemical Society, Pennington, NJ;Pohler, O.E.M., (1983) Biomaterials in Reconstrutive Surgery, p. 158. , C.V. Mosby, St. Louis; Black, J., Oppenheimer, P., Morris, D.M., Peduto, A.M., Clark, C.C., (1987) J. Biomed. Mater. Res., 21, p. 1213; Sunderman, F.W., Hopper, S.M., Swift, T., Rezuke, W.N., Ziebra, L., Highman, P., Edwards, B., Gossling, H.R., (1989) J. Orthop. Res., 7, p. 307; Traisnel, M., Maguer, D., Hildebrand, H.F., (1990) Clin. Mater., 5, p. 309; Moore, R.M., Hamburger, S., Jeng, L.J., Hamilton, P.M., (1991) J. Appl. Biomater., 2, p. 127; Henning, E.F., Raithel, H.J., Schaller, K.H., Dohler, J.R., (1992) J. Trace Elem. Electrolytes Health Dis., 6, p. 239; Brown, S.A., Zhang, K., Merritt, K., Payer, J.H., (1993) J. Biomed. Mater. Res., 27, p. 1007; Albore-Saavedra, J., Vuitch, F., Delgado, R., Wiley, E., Hagler, H., (1994) Am. Surg. Pathol., 18, p. 83; Buechel, F.F., Drucker, D., Jasty, M., Jiranek, W., Harris, W.H., (1994) Clin. Orthop. Related Res., 298, p. 202; Valenta, P., Rutzel, H., Nurnberg, H.W., Stoeppler, M., (1977) Z. Anal. Chem., 285, p. 25; Nurnberg, H.W., (1977) Electrochim. Acta, 22, p. 935; Nurnberg, H.W., (1978) Proc. Anal. Div. Chem. Soc., 15, p. 275; Golimowski, S.J., Valenta, P., Stoepper, M., Nurnberg, H.W., (1979) Talanta, 26, p. 649; Cox, J.A., Majda, M., (1980) Anal. Chim. Acta, 118, p. 271; Van Den Berg, C.M.G., Huang, Z.Q., (1984) J. Electroanal. Chem., 177, p. 269; Wang, J., Mahmoud, J.S., (1986) J. Electroanal. Chem., 208, p. 383; Van Den Berg, C.M.G., Nimmo, N., Abollino, O., Mentasti, E., (1991) Eleclroanalysis, 3, p. 477; Sousa, J.P., Morais, S., Pereira, M.C., Pereira, M.L., Carvalho, G.S., Barbosa, M.A., (1994) Biomaterials, 15, p. 821; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci.: Mater. Med., 6, p. 523; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci.: Mater. Med., 6, p. 56; Vilamitjana-Amedee, J., Bareille, R., Rouais, F., Caplan, A.I., Harmand, M.F., (1993) In Vitro Cell. Dev. Biol., 29 A, p. 699; Bizios, R., (1994) Biotechnol. Bioeng., 43, p. 582; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Arciola, C.R., Granchi, D., Savarino, L., (1994) Clin. Mater., 15, p. 173; Winter, G.D., (1974) J. Biomed. Mater. Res. Symp., 5, p. 11; De Vernejoul, M.C., Pointillart, A., Golenzer, C.C., Morieux, C., Bielakoff, J., Modrowski, D., Miravet, L., (1985) Metals in Bone, pp. 321-331. , (Ed: N.D. Priest), MTT Press Dordrecht; Pend, J., Jin, W., (1992) Anal. Chim. Acta, 264, p. 213; Van Den Berg, C.M.G., (1984) Anal. Chim. Acta, 164, p. 195; Maniatopoulos, C., Sodek, J., Melcher, A.H., (1988) Cell Tissue Res., 254, p. 317; Kotz, L., Henze, G., Kaiser, G., Pahlke, S., Veber, M., Tolg, G., (1979) Talanta, 26, p. 681; Huizenga, D.L., Rester, D.R., (1984) J. Electroanal. Chem., 164, p. 229; Capodaglio, G., Van Den Berg, C.M.G., Scarponi, G., (1987) J. Electroanal. Chem., 235, p. 275; Torrance, K., Gatford, C., (1986) Analyst, 111, p. 359; Wang, J., Lu, J., Olsen, K., (1992) Analyst, 117, p. 1913; Miller, J.N., (1991) Analyst, 116, p. 3; Morais, S., Sousa, J.P., Fernandes, H., Carvalho, G.S., (1994) Last Minute Posters Abstracts Book, 11th European Conference on Biomaterials, pp. 10-11. , Pisa, Italy; Lugowski, S., Smith, D.C., Van Loon, J.C., (1987) J. Biomed. Mater. Res., 21, p. 657
Keywords: Cell culture medium; Iron; Mercury film microelectrode

Mineralization in serially passaged human alveolar bone cells - Fernandes, M.H.; Costa, M.A.; Carvalho, G.S. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1997)
Well-characterized human bone cell cultures have been regarded as a useful tool to study bone control mechanisms and also to analyse bone/biomaterials interactions. In the present study, human alveolar bone cells were cultured in a-minimal essential medium (α-MEM) containing 10% foetal bovine serum (FBS), 50 μg/ml ascorbic acid, 10 mM sodium β-glycerophosphate and either in the presence or in the absence of 10 nM dexamethasone (Dexa). Cultures were characterized concerning cell viability/proliferation, alkaline phosphatase (ALP), acid phosphatase (ACP) and tartraric acid resistant phosphatase (TRAP) activities, and formation of mineralized areas. Cell proliferation increased gradually for approximately 20 days. In the presence of Dexa, cells formed isolated or interconnected multilayered clusters that increased with culture time. Histochemical assays revealed strong positive reactions for ALP and calcium and phosphates deposits, mainly in relation to cells associated with the clusters. High levels of ALP activity (biochemical determination) were observed. Cells cultured in the absence of Dexa showed significantly lower ALP activity and no calcium and phosphates deposits were present. Serially passaged cells kept the proliferation rate constant but a decrease in ALP activity was observed either in the presence or in the absence of Dexa. The ability to form mineralized areas (cultures fed with Dexa) also decreased on serial subculture.Well-characterized human bone cell cultures have been regarded as a useful tool to study bone control mechanisms and also to analyse bone/biomaterials interactions. In the present study, human alveolar bone cells were cultured in α-minimal essential medium (α-MEM) containing 10% foetal bovine serum (FBS), 50 μg/ml ascorbic acid, 10 mM sodium β-glycerophosphate and either in the presence or in the absence of 10 nM dexamethasone (Dexa). Cultures were characterized concerning cell viability/proliferation, alkaline phosphatase (ALP), acid phosphatase (ACP) and tartaric acid resistant phosphatase (TRAP) activities, and formation of mineralized areas. Cell proliferation increased gradually for approximately 20 days. In the presence of Dexa, cells formed isolated or interconnected multilayered clusters that increased with culture time. Histochemical assays revealed strong positive reactions for ALP and calcium and phosphates deposits, mainly in relation to cells associated with the clusters. High levels of ALP activity (biochemical determination) were observed. Cells cultured in the absence of Dexa showed significantly lower ALP activity and no calcium and phosphates deposits were present. Serially passaged cells kept the proliferation rate constant but a decrease in ALP activity was observed either in the presence or in the absence of Dexa. The ability to form mineralized areas (cultures fed with Dexa) also decreased on serial subculture.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1018598430983Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Rua do Doutor Roberto Frias, 4200 Porto, PortugalReferences: Spector, M., Cease, C., Tong, X., (1989) Crit. Rev. Biocompat., 5, p. 269;Van Blitterswijk, C.A., Bakker, D., Hesseling, S.C., Koerten, H.K., (1991) Biomaterials, 12, p. 187; Galante, J.O., Lemons, J., Spector, M., Wilson Jr., P.D., Wright, T.M., (1991) J. Orthop. Res., 9, p. 760; Bagambisa, F.B., Kappert, H.F., Schilli, W., (1994) J. Oral Maxillofac. Surg., 5, p. 52; Bruijn, J.D., Bovell, Y.D., Blitterwijk, C.A., (1994) Biomaterials, 15, p. 543; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., (1991) Bone and Mineral, 14, p. 27; Davies, J.E., Chernecky, R., Loweenberg, B., Shiga, A., (1991) Cells and Materials, 1, p. 3; Bruijn, J.D., Davies, J.E., Flach, J.S., De Groot, K., Blitterwijk, C.A., (1992) Mater. Res. Soc. Symp. Proc., 252, p. 63; Puleo, D.A., Bizios, R., (1992) J. Biomed. Mater. Res., 26, p. 291; Bruijn, J.D., Klein, C.P., De Groot, K., Van Blitterswijk, C.A., (1992) J. Biomed. Mater. Res., 26, p. 1365; Bruijn, J.D., Klein, C.P., De Groot, K., Van Blitterswijk, C.A., (1993) Cells and Materials, 3, p. 407; Shen, X., Roberts, E., Peel, S.A., Davies, J.E., (1993) Cells and Materials, 3, p. 257; Meyer, U., Szulczewski, D.H., Moller, K., Heide, H., Jones, D.B., (1993) Cells and Materials, 3, p. 129; Meyer, U., Szulczewski, D.H., Brackhaus, R.H., Atkinson, M., Jones, D.B., (1993) Biomaterials, 14, p. 917; Bizios, R., (1994) Biotechnol. Bioeng., 43, p. 582; Gotoh, Y., Hiraiwa, K., Nagayama, M., (1990) Bone and Mineral, 8, p. 23; Berstein, A., Bernauer, I., Marx, R., Geurtsen, W., (1992) Biomaterials, 13, p. 98; Schmiddt, R., Kulbe, K.D., (1993) Bone and Mineral, 20, p. 211; Maniatopoulos, C., Sodek, J., Melcher, A.H., (1988) Cell Tissue Res., 254, p. 317; Benayahu, D., Kletter, Y., Zipori, D., Wientroub, S., (1989) J. Cell Physiol., 140, p. 1; Wong, M.-M., Rao, L.G., Ly, H., Hamilton, L., Tong, J., Sturtridge, W., Mcbroom, R., Murray, T.M., (1990) J. Bone Miner. Res., 5, p. 803; Leboy, P.S., Beresford, J.N., Devlin, C., Owen, M.E., (1991) J. Cell Physiol., 146, p. 370; Shalhoub, V., Conlon, D., Tassinari, M., Quinn, C., Partridge, N., Stein, G.S., Lian, J.B., (1992) J. Cell Biochem., 50, p. 425; Cheng, S.-L., Yang, J.W., Rifas, L., Zhang, S.-F., Avioli, L.V., (1994) Endocrinology, 134, p. 277; Bellows, C.G., Aubin, J.E., Heersche, J.M.N., (1991) Bone and Mineral, 14, p. 27; Satomura, K., Nagayama, M., (1991) Acta Anat., 142, p. 97; Van Straalen, J.P., Sanders, E., Prummel, M.F., Sanders, G.T.B., (1991) Clin. Chem. Acta, 201, p. 27; Aufmkolk, B., Hauschka, P.V., Schwartz, E.R., (1987) Calcif. Tissue Int., 37, p. 228
Keywords: Acid phosphatase; Acid resistance; alkaline phosphatase; alveolar bone; article; ascorbic acid; Bioassay; Biocompatibility; Biomaterials; Bone; bone cell; Bovinae; Cell culture; cell proliferation; Characterization; Chemical reactions; controlled study; culture medium; dexamethasone; Foetal bovine serum; glycerophosphate; Histochemical assays; histochemistry; human; Human alveolar bone cells; human cell; mineralization; Minimal essential medium; Phosphates; priority journal; Proteins; tartaric acid; Tartraric acid resistant phosphatase; Tissue culture

Nickel Determination in Osteoblast-Like Cell Culture Medium by Adsorptive Cathodic Stripping Voltammetry with a Mercury Microelectrode - Morais, S.; Carvalho, G.S.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1997)
The purpose of this study is to investigate the influence of nickel, which is an alloying element in commonly used metallic biomaterials, on the biomaterials mineralization process. An electrochemical method was developed to quantify this metal ion in osteoblast-like cell culture medium (OST) by performing adsorptive cathodic stripping voltammetry (CSV) with dimethylglyoxime (DMG) at a mercury film microelectrode (MFM). The optimized analytical conditions and the square-wave CSV parameters for the analysis are: DMG concentration: 5.00 × 10
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: ELANELanguage of Original Document: EnglishCorrespondence Address: Sousa, J.P.; Inst. de Engenharia Biomedica, Depto. de Engenharia Química, Universidade do Porto, Praça Coronel Pacheco, 1, 4050 Porto, PortugalReferences: Williams, D.F., (1981) Biomaterials and Biocompatibility: An Introduction, in Fundamental Aspects of Biocompatibility, 1. , CRC Press, Boca Raton, FL;Tsalev, D.L., Zaprianov, Z.K., (1983) Atomic Absorption Spectrometry in Occupational and Environmental Health Practice, 1. , CRC Press, Boca Raton, FL; Fishbein, L., Mehlman, M.A., (1987) Advances in Modern Environmental Toxicology, pp. 145-183. , CRC Press, Boca Raton, FL; Costa, M., (1989) Env. Health. Perspect., 81, p. 73; Ward, J., Thornbury, D.D., Lemons, J.., Dunham, W.., (1990) Clin. Orthoped., 252, p. 299; Florence, T.M., (1970) J. Electroanal. Chem., 27, p. 273; Batley, J.E., Florence, T.M., (1976) J. Electroanal. Chem., 72, p. 121; Wang, J., Zadeii, Z., (1988) J. Electroanal. Chem., 246, p. 297; Daniele, S., Baldo, M.A., Ugo, P., Mazzocchin, G., (1989) Anal. Chim. Acta, 219, p. 9; Daniele, S., Baldo, M.A., Ugo, P., Mazzocchin, G., (1989) Anal. Chim. Acta, 219, p. 19; Eskilsson, H., Haraldsson, C., Jagner, D., (1985) Anal. Chim. Acta., 175, p. 79; Economou, A., Fielden, P.R., (1993) Analyst, 118, p. 47; Wightman, R.M., Wipt, D.O., (1989) Voltammetry at Ultramicroelectrodes, pp. 335-336. , Ed: A.J. Bard, Marcel Dekker, New York; Pereira, M.C., Pereira, M.L., Sousa, J.P., (1995) Biomed. Lett., 52, p. 235; Sousa, J.P., Morais, S., Pereira, M.C., Pereira, M.L., Carvalho, G.S., Barbosa, M.A., (1994) Biomaterials, 15, p. 821; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci.: Mater. Med., 6, p. 523; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci.: Mater. Med., 6, p. 56; Maniatopoulos, C., Sodek, J., Melcher, A.H., (1988) Cell Tiss. Res., 254, p. 317; Morais, S., Sousa, J.P., Fernandes, H., Carvalho, G.S., (1994) Last Minute Posters Abstracts Book, 11th European Conference on Biomaterials, Pisa, Italy, pp. 10-11; Peng, J., Jin, W., (1992) Anal. Chim. Acta, 264, p. 213; Gunawardena, G., Hills, G., Montenegro, I., Scharifker, B., (1982) J. Electroanal. Chem., 138, p. 225; Milchev, A., Scharifker, B., Hills, G., (1981) J. Electroanal. Chem., 132, p. 277; Sousa, J.P., (1991), Ph.D. Dissertation, University of UtahBailey, F., Malinski, T., Kiechle, F., (1991) Anal. Chem., 63, p. 395; Wightman, R.M., (1981) Anal. Chem., 53, pp. 1125A; Turner, A.P.F., Karube, I., Wilson, G.S., (1987) Biosensors Fundamentals and Applications, , Oxford University Press, Oxford; Golas, J., Galus, Z., Osteryoung, J., (1987) Anal. Chem., 59, p. 389; Baranski, A.S., (1987) Anal. Chem., 59, p. 662; Kounaves, S.P., (1992) Anal. Chem., 64, p. 2998; Feinberg, J.S., Bowyer, W.J., (1993) Microchem. J., 47, p. 72; Kounaves, S.P., Deng, W., (1993) Anal. Chem., 65, p. 375; Bustin, D., Mesaros, S., Rievaj, M., Tomcik, P., (1995) Electroanalysis, 4, p. 7; Ostapczuk, P., Valenta, P., Nurnberg, H., (1986) J. Electroanal. Chem., 214, p. 51; Pihlar, B., Valenta, P., Nurnberg, H.W., (1981) Z. Anal. Chem., 307, p. 337; Gammelgaar, B., Andersen, J.R., (1985) Analyst, 110, p. 1197; Vos, L., Komy, Z., Reggers, G., Rockens, E., Van Grieken, R., (1986) Anal. Chim. Acta, 184, p. 271; Torrance, K., Gatford, C., (1985) Talanta, 32, p. 273; Braun, H., Metzgar, M., (1984) Z. Anal. Chem., 318, p. 321; Adeloju, S.B., Bond, A.M., Briggs, M.H., (1984) Anal. Chim. Acta, 164, p. 181; Wahdat, F., Neeb, R., (1985) Z. Anal. Chem., 320, p. 334; Kotz, L., Henze, G., Kaiser, G., Pahlke, S., Veber, R., Tolg, G., (1979) Talanta, 26, p. 681; Wurfels, M., Jackwerth, E., Stoeppler, M., (1989) Anal. Chim. Acta, 226, p. 17; Wurfels, M., Jackwerth, E., Stoeppler, M., (1989) Anal. Chim. Acta, 226, p. 31; Basu, B.J., Rajagopalan, S.R., (1992) Analyst, 117, p. 1623; Bond, A.M., Luscombe, D.L., (1986) J. Electroanal. Chem., 214, p. 21; Van Den Berg, C.M.G., (1991) Anal. Chim. Acta, 250, p. 265; Miller, J.N., (1991) Analyst, 116, p. 3; Wu, T.G., Wong, J.L., (1991) Anal. Chim. Acta, 246, p. 301; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., (1991) Bone and Mineral, 14, p. 27; Wehmeyer, K.R., Wightman, R.M., (1985) Anal. Chem., 57, p. 1989; Nurnberg, H.W., (1977) Electrochim. Acta, 22, p. 935
Keywords: Cell culture medium; Mercury film microelectrode; Nickel

Processing and in vitro degradation of starch/EVOH thermoplastic blends - Reis, R.L.; Mendes, S.C.; Cunha, A.M.; Bevis, M.J. (Polymer InternationalPolym. Int., 1997)
This paper describes the processing dependence of the mechanical properties of three blends of starch/ethylene vinyl alcohol (EVOH) with potential uses as biomaterials. These blends exhibit a distinct rheological behaviour and mechanical performance. Using shear controlled orientation in injection moulding (Scorim) it was possible to induce anisotropy into the mouldings and to simultaneously enhance stiffness and ductility. Degradation was studied in simulated physiological solutions (Hank's balanced salt solution) with and without added bovine serum. Both the dry weight loss and the changes in mechanical properties were determined for ageing periods up to 80 days. The degradation behaviour proved to be strongly dependent on the formulation of the material studied, and on the addition of proteins. The susceptibility of the starch/EVOH blends to degradation when sterilised with ethylene oxide (EtO) was also studied, and showed that the polymers could stand one EtO sterilisation cycle. However, two consecutive cycles severely degraded the polymer structure and properties.
Cited By (since 1996): 77Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Reis, R.L.; Dept. of Metallurgical Engineering, University of Porto, FEUP, Rua dos Bragas, 4099 Porto Codex, PortugalReferences: Hayashi, T., (1994) Prog. Polym. Sci., 19, p. 663;Daniels, A.U., Andriano, K.P., Smutz, W.P., Chang, M.K.O., Heller, J., (1994) J. Appl. Biomater., 5, pp. 5l; Andriano, K.P., Pohjonen, T., Tormalla, P., (1994) J. Appl. Biomater., 5, p. 133; Knowles, J.C., Hastings, G.W., (1992) J. Mater. Sci.: Mater. Med., 3, p. 352; Rokkanen, P.U., (1991) Ann. Med., 23, p. 109; Reis, R.L., Cunha, A.M., (1995) J. Mater, Sci.: Mater. Med., 6, p. 786; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1996) J. Polym. Advanced Techniques, 1, p. 784; Bastioli, C., Bellotti, V., Del Giudice, L., Lombi, R., (1991) PCT Int. Pat. Appl, , WO91/02025; Bhattarcharya, M., Vaidya, U.R., Zhang, D., Narayan, R., (1995) J. Appl Polym. Sci., 57, p. 539; Bastioli, C., Bellotti, V., Del Guidice, L., Gilli, G., (1993) J. Environ. Polym. Degrad., 1, p. 181; Bastioli, C., Bellotti, V., Rallis, A., (1994) Rheol. Acta., 33, p. 307; Griffin, G.J.L., (1994) Polym. Degrad. Stabil, 45, p. 241; Ogbona, G.L., Kalay, G., Allan, P.S., Bevis, M.J., (1995) J. Appl. Polym. Sci., 58, p. 213; Allan, P.S., Bevis, M.J., (1987), Br. Pat., 2170-140-BAllan, P.S., Bevis, M.J., (1987) Plast. Rubb. Process. Applic., 1, p. 3; Allan, P.S., Bevis, M.J., (1990) Comp. Manuf., 2, p. 79; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1996) Polymers in Medicine and Surgery, p. 195. , eds J. Courtney et al. Institute of Materials, London; Bastioli, C., Bellotti, V., Camia, M., Del Giudice, L., Rallis, A., (1994) Biodegradable Plastics and Polymers, p. 200. , eds Y. Doi and K. Fukuda. Eisevier, Amsterdam
Keywords: Aging of materials; Anisotropy; Biodegradable polymers; Biodegradation; Biomaterials; Degradation; Ductility; Ethylene oxide; Ethylene vinyl alcohol; Hank's salt solution; Injection molding; Polyethylenes; Polymer blends; Polyvinyl alcohols; Processing; Proteins; rheology; Shear controlled orientation injection molding (Scorim); Starch; Sterilisation; Stiffness

Structure development and control of injection-molded hydroxylapatite-reinforced starch/EVOH composites - Reis, R.L.; Cunha, A.M.; Allan, P.S.; Bevis, M.J. (Advances in Polymer TechnologyAdv Polym Technol, 1997)
This article reports on the development of novel composites of starch-based polymers reinforced with hydroxylapatite (HA). Two different grades of blends of starch and ethylene vinyl alcohol copolymers were reinforced with up to 30% (wt) of sintered and nonsintered HA. The initial compounding stage was carried out either in a rotating drum or by twin-screw extrusion (TSE). Compounds were injection molded using both conventional molding and a shear-controlled orientation in injection molding (Scorim) technique. It was possible to obtain composites with very good mechanical properties, approaching those of cortical bone. The best results were achieved for 30% sintered HA composites processed by TSE and Scorim, due to the in situ formation of HA fibers, and the development of molecular orientation and more compact microstructures in the moldings. This was confirmed by SEM analysis of the fracture surfaces, x-ray diffraction, and Raman spectroscopy. The biodegradability of the composites was also assessed and was found to be faster than that of the matrix. © 1997 John Wiley & Sons, Inc.
Cited By (since 1996): 53Export Date: 21 November 2012Source: ScopusCODEN: APTYDLanguage of Original Document: EnglishCorrespondence Address: Reis, R.L.; Dept. of Metallurgical Engineering, Faculty of Engineering, University of Porto, Rua dos Bragas, 4099 Porto Codex, PortugalReferences: Hayashi, T., (1994) Prog. Polym. Sci., 19, p. 663;Rokkanen, P.U., (1991) Ann. Med., 23, p. 109; Knowles, J.C., Hastings, G.W., (1992) J. Mater. Sci. Mater. Med., 3, p. 352; Adriano, K.P., Pohjonen, T., Tormalla, P., (1994) J. Appl. Biomater., 5, p. 133; Daniels, A.U., Andriano, K.P., Smutz, W.P., Chang, M.K.O., Heller, J., (1994) J. Appl. Biomater., 5, p. 51; Bastioli, C., Bellotti, V., Del Guidice, L., Gilli, G., (1993) J. Environ. Polym. Degrad., 1, p. 181; Griffin, G.J.L., (1994) Polym. Degrad. Stabil., 45, p. 241; Stepto, R.F.T., Tomka, I., (1987) Chimia, 41, p. 76; Bhattarcharya, M., Vaidya, U.R., Zhang, D., Narayan, R., (1995) J. Appl. Polym. Sci., 57, p. 539; Reis, R.L., Cunha, A.M., (1995) J. Mater. Sci. Mater. Med., 6, p. 786; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1996) J. Polym. Adv. Technol., 7, p. 784; Wang, M., Bonfield, W., Hench, L.L., (1995) Bioceramics 8, p. 383. , J. Wilson and L. L. Hench (Eds). Butterworth-Heinemann, New York; Verheyen, C.C.P.M., Wijn, J.R., Van Blitterswijk, C.A., De Groot, K., (1992) J. Biomedd. Mater. Res., 26, p. 1277; Verheyen, C.C.P.M., Klein, C.P.A.T., De Blieck-Hogervorst, J.M.A., Wolke, J.G.C., Van Blitterswijk, C.A., De Groot, K., (1993) J. Mater. Sci. Mater. Med., 4, p. 58; Higashi, S., Yamamuro, T., Nakamura, T., Ikada, Y., Hyon, S.H., Jamshidi, K., (1986) Biomaterials, 7, p. 183; Knowles, J.C., Hastings, G.W., (1993) J. Mater. Sci. Mater. Med., 4, p. 102; Oréfice, R.L., La Torre, G.P., West, J.K., Hench, L.L., (1995) Bioceramics 8, p. 409. , J. Wilson, and L. L. Hench (Eds)., Butterworth-Heinemann, New York; Allan, P.S., Bevis, M.J., British Patent 2170-140-B (1987)Allan, P.S., Bevis, M.J., (1987) Plast. Rubber Proc. Appl., 7, p. 3; Allan, P.S., Bevis, M.J., (1990) Comp. Manuf., 2, p. 79; Bastioli, C., Bellotti, V., Rallis, A., (1994) Rheol. Acta, 33, p. 307; Reis, R.L., Mendes, S.C., Cunha, A.M., Bevis, M.J., (1997) Polym. Int, 43, p. 347
Keywords: Biodegradation; Composition effects; Compounding (chemical); Copolymers; Extrusion molding; hydroxyapatite; Injection molding; Microstructure; Molecular orientation; Phosphate minerals; Polymer blends; Polyvinyl alcohols; Reinforced plastics; Rotating drum extrusion; Starch; Twin screw extrusion

Treatments to induce the nucleation and growth of apatite-like layers on polymeric surfaces and foams - Reis, R.L.; Cunha, A.M.; Fernandes, M.H.; Correia, R.N. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1997)
In this work, a bioactive glass is used as a percusor of calcium-phosphate (Ca-P) film deposition onto several polymer-based materials. Both bioinert (high molecular weight polyethylene, HMWPE), and biodegradable (corn starch-based blends, SEVA-C) polymers, unreinforced or reinforced with hydroxylapatite (HA), were coated by the very simple proposed route. Also polyurethane (PU) foams, with an open-cell structure, were mineralized by the proposed method. In fact, it was possible to induce the growth of the Ca-P films not only at the surface, but also in the bulk of the PU foam. These cellular materials are intended for cancellous bone replacement applications. The morphology of the formed films was strongly dependent on the used substrate, its polar character, and on the presence of HA in its composition, as observed by SEM. Nevertheless, a well defined needle like structure was observed in all samples at high magnifications. The Ca:P ratios of the films were between 1.5 and 1.7, i.e. in the range of tricalcium phosphate-hydroxylapatite. Raman spectroscopy and thin-film x-ray diffraction (XRD) evidenced the formation of mostly amorphous calcium-phosphate films. After scraping the coating from the polymer surface and heat-treating the resulting powder at 1000°C for 1 h, HA and β-tricalcium phosphate (TCP) typical peaks were found on XRD patterns.In this work, a bioactive glass is used as a percussor of calcium-phosphate (Ca-P) film deposition onto several polymer-based materials. Both bioinert (high molecular weight polyethylene, HMWPE), and biodegradable (corn starch-based blends, SEVA-C) polymers, unreinforced or reinforced with hydroxylapatite (HA), were coated by the very simple proposed route. Also polyurethane (PU) foams, with an open-cell structure, were mineralized by the proposed method. In fact, it was possible to induce the growth of the Ca-P films not only at the surface, but also in the bulk of the PU foam. These cellular materials are intended for cancellous bone replacement applications. The morphology of the formed films was strongly dependent on the used substrate, its polar character, and on the presence of HA in its composition, as observed by SEM. Nevertheless, a well defined needle like structure was observed in all samples at high magnifications. The Ca:P ratios of the films were between 1.5 and 1.7, i.e. in the range of tricalcium phosphate-hydroxylapatite. Raman spectroscopy and thin-film x-ray diffraction (XRD) evidenced the formation of mostly amorphous calcium-phosphate films. After scraping the coating from the polymer surface and heat-treating the resulting powder at 1000 °C for 1 h, HA and β-tricalcium phosphate (TCP) typical peaks were found on XRD patterns.
Cited By (since 1996): 51Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1018514107669Language of Original Document: EnglishCorrespondence Address: Reis, R.L.; INEB-Inst. Biomedical Engineering, Praca do Coronel Pacheco 1, 4050 Porto, PortugalTradenames: Hostalen GM9255F, hoechst, Germany; SEVA-CManufacturers: hoechst, GermanyReferences: Lowenstam, H.A., Weiner, S., (1989) On Biomineralization, , Oxford University Press, Oxford;Mann, S., (1988) Nature, 332, p. 119; Mann, S., (1991) Endeavour, 15, p. 120; Mann, S., (1993) Nature, 365, p. 499; Heur, A.H., Fink, D.J., Laraia, V.J., Calvert, P.D., Kendall, K., Messing, G.L., Blackwell, J., Caplan, A.I., (1992) Science, 255, p. 1098; Hench, L.L., (1991) J. Amer. Ceram. Soc., 74, p. 1487; Legeros, R.Z., Orly, I., Gregoire, M., Daculsi, G., (1991) The Bone-Biomaterial Interface, p. 76. , edited by J. E. Davies University of Toronto Press, Torento; Hench, L.L., (1995) Chem. & Indust., 17, p. 547; Hayakawa, S., Isuru, S., Iida, H., Ohtsuki, C., Osaka, A., (1996) Phys. Chem. Glasses, 37, p. 188; Li, P., Ye, X., Kangasniemi, I., De Blieckhogervorst, J.M.A., Klein, C.P.A.T., De Groot, K., (1995) J. Biomed. Matter. Res., 29, p. 325; Li, P., Othsuki, C., Kokubo, T., Nakanish, K., Soga, N., Nakamura, T., Yamamuro, T., (1992) J. Amer. Ceram. Soc., 75, p. 2094; Cho, S.B., Nakanishi, K., Kokubo, T., Saga, N., Ohtsuki, C., Nakamura, T., (1996) J. Biomed. Mater. Res., 33, p. 145; Radder, A.M., Leenders, H., Van Blitterswijk, C.A., (1994) J. Biomed. Mater. Res., 28, p. 141; Ries, R.L., Cunha, A.M., (1995) J. Mater. Sci. Mater. Med., 6, p. 786; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1996) J. Polym. Adv. Technol., 7, p. 784; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1997) Adv. Polym. Technol., , in press; Reis, R.L., Mendes, S.C., Cunha, A.M., Bevis, M.J., (1997) Polym. Int., 43, p. 347; Bonfield, W., Grynpas, M.D., Tully, A.E., Bowman, J., Abram, J., (1981) Biomaterials, 2, p. 185; Wang, M., Porter, D., Bonfield, W., (1994) Br. Ceram. Trans., 93, p. 104; Campbell, A.A., Fryxell, G.E., Linehan, J.C., Graff, G.L., (1996) J. Biomed. Mater. Res., 32, p. 111; Tanahashi, M., Yao, T., Kokubo, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., (1994) J. Amer. Ceram. Soc., 77, p. 2805; Hata, K., Kokubo, T., Nakamura, T., Yamamuro, T., (1995) J. Amer. Ceram. Soc., 78, p. 1049; Kokubo, T., Hata, K., Nakamura, T., Yamamuro, T., (1991) Bioceramics, 4, p. 113. , edited by W. Bonfied, G. W. Hastings and K. E. Tanner Butterworth-Heineman, London; Tanahashi, M., Yao, T., Kokubo, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., (1995) J. Mat. Sci. Mater. Med., 6, p. 319; Tanahashi, M., Yao, T., Kokubo, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., (1995) J. Biomed. Mater. Res., 29, p. 349; Li, S.H., Liu, Q., Wijn, J.R., Zhou, B.L., De Groot, K., (1997) Biomaterials, 18, p. 389; Li, S.H., Liu, Q., Wijn, J.R., De Groot, K., Zhou, B.L., (1996) J. Mater. Sci. Lett., 15, p. 1882; Golomb, G., Barashi, A., Wagner, D., Nachmias, O., (1993) Clin. Mater., 13, p. 61; Oliveira, J.M., Fernandes, M.H., Correia, R.N., (1992) Bioceramics, 5, p. 7. , edited by T. Yamumuro, T. Kokubu, T. Nakamura and Kobunshi, Konkokai, Tokyo; Oliveira, J.M., Correia, R.N., Fernandes, M.H., (1995) Biomaterials, 16, p. 849
Keywords: Apatite; Bioactivity; Biomaterials; calcium phosphate; cancellous bone; conference paper; Deposition; Film growth; Foamed plastics; glass; Heat treatment; hydroxyapatite; implantation; mineralization; molecular weight; morphology; Nucleation; Phosphate coatings; Phosphate minerals; polyethylene; polymer; polyurethan foam; Polyurethanes; priority journal; Raman spectrometry; Raman spectroscopy; Scanning electron microscopy; X ray diffraction; Zea mays

Amino acid and metal content of Crassostrea gigas shell infested by Polydora sp. in the prismatic layer insoluble matrix and blister membrane - Almeida, M.J.; Moura, G.; MacHado, J.; Coimbra, J.; Vilarinho, L.; Ribeiro, C.; Soares-Da-Silva, P. (Aquatic Living ResourcesAquatic Living Resour., 1996)
The spionid polychaete Polydora sp. can live and reproduce inside the oysters' shell, excavating a U-shaped burrow the central portion of which is filled with detritus and particles of dissolved shell. The oyster responds by secreting an organic layer, confining the worm, and later covering it with calcitostracum. This process creates a characteristic "mud blister". Crassostrea gigas were analysed for the organic matrix amino acid content and 14 metals of the whole shell of normal oysters and severely Polydora infested ones. Amino acid, DOPA and FT-Raman analyses were also performed on isolated membranes from the characteristic mud blister and on prismatic layer insoluble matrix (PLIM) of infested oysters, with the aim of detecting any differences between the two organic matrices. Membranes and PLIM composition differ from whole normal shell organic matrix by having lower aspartate and glycine and higher levels of virtually all hydrophobic amino acids, especially alanine. There are no significant differences between membranes and PLIM in the ratio of charged to non-polar amino acids, respectively 0.54 and 0.59. L-DOPA content is also similar in the two matrices with 0.45 (±0.18) and 0.57 (±0.30) ng.mg
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: ALREELanguage of Original Document: EnglishCorrespondence Address: Almeida, M.J.; Laboratório de Fisiologia Aplicada, Instituto de Ciências Biomédicas Abel Salazar, 4050 Porto, PortugalReferences: Allen, J.A., Manganese deposition on the shell of living molluscs (1960) Nature, 185, pp. 336-337;Beedham, G.E., Repair of the shell in species of Anodonta (1965) Proc. Zool. Soc. London, 145, pp. 107-125; Boggess, R.K., Martin, R.B., Copper chelation by DOPA, epinephrine and other catechols (1975) J. Am. Soc. Chem., 97, pp. 3076-3081; Brown, C.H., (1975) Structural Materials in Animals, , Wiley, New York; Bubel, A., An electron microscope study of periostracum repair in Mytilus edulis (1973) Mar. Biol., 20, pp. 235-244; Carriker, M.R., Swann, C.P., Prezant, R.S., Counts, C.L., Chemical elements in the aragonitic and calcitic microstructural groups of shell of the oyster Crassostrea virginica: A proton probe study (1991) Mar. Biol., 109, pp. 289-297; Catherine, M., Blateau, D., Mazurié, J., Le Bec, C., (1990) Anomalies des Coquilles D'huîtres Creuses Crassostrea Gigas Observées sur le Littoral Français en Mai-juin 1989, Dues au ver Polydora et aux Peintures Antisalissures., pp. 13-14. , Rapp. Int. Dir. Ressources Vivantes, IFREMER Nantes; Degens, E.T., Spencer, D.W., Parker, R.H., Paleobiochemistry of Molluscan shell proteins (1967) Comp. Biochem. Physiol., 79, pp. 553-579; Dorsett, D.A., The behavior of Polydora ciliata (Johnst.). Tube building and burrowing (1961) J. Mar. Biol. Assoc. U.K., 41, pp. 577-590; Felix, C.C., Sealy, R.C., Electron spin resonance characterization of radicals from 3-4-dihydroxyphenylalanine: Semiquinone anions and their metal chelates (1981) J. Am. Chem. Soc., 103, pp. 2831-2835; Galstoff, P.S., The American oyster Crassostrea virginica (Gmelin) (1964) Fish. Bull. U.S., p. 64; Gergely, A., Kiss, T., Coordination chemistry of L-DOPA and related ligands (1979) Met. Ions Biol. Syst., 9, pp. 143-172; Haigler, S., Boring mechanism of Polydora websteri inhabiting Crassostrea virginica (1969) Am. Zool., 9, pp. 821-828; Jones, G.M., Saleuddin, A.S.M., Cellular mechanisms of periostracum formation in Physa spp. (Mollusca: Pulmonata) (1978) Can. J. Zool., 56, pp. 2299-2311; Kawaguchi, T., Watabe, N., The organic matrices of the shell of the American oyster Crassostrea virginica Gmelin (1993) J. Exp. Mar. Biol. Ecol., 170, pp. 11-28; Kawaguti, S., Ikemoto, N., Electron microscopy on the mantle of a bivalve Musculus senhousia, during regeneration of shell (1962) Biol. J. Okayama Univ., 8, pp. 31-42; Krampitz, G., Drolshagen, H., Hotta, S., Simultaneous binding of calcium and bicarbonate by conchiolin of oyster shells (1983) Experiemia, 39, pp. 1104-1105; Laukner, G., Diseases of Mollusca: Bivalvia (1983) Diseases of Marine Animals, Vol. II, Bivalvia to Scaphopoda, 2, pp. 477-978. , Biologische Anstalt Helgoland, O. Kinne ed. Hamburg; Levitt, M., A simplified representation of protein conformation for rapid simulation of protein folding (1976) J. Mol. Biol., 104, pp. 59-108; Linderstrom-Lang, K., Duspiva, F., Studies in enzymatic histochemistry. XVI. the digestion of keratin by larvae of clothes moth (Tineola biselliela Humm.) (1936) C. R. Trav. Lab. Carlsberg, Ser. Chim., 21, pp. 1-82; Lowry, O.H., Rosebrough, N.J., Farr, A.L., Randall, R.J., Protein determination with the Folin phenol reagent (1951) J. Biol. Chem., 193, pp. 265-275; Martius, K.V., Schwarzhans, K.E., Preparation of the Mn (II) complex with 3,4-dihydroxyphenylalanine (DOPA) (1978) Z Naturforsch., 33 B, p. 124; Meenaakshi, V.R., Hare, P.E., Watabe, N., Wilbur, K.M., The chemical composition of the periostracum of the molluscan shell (1969) Comp. Biochem. Physiol., 29, pp. 611-620; Nozaki, Y., Tanford, C., The solubility of amino acids and two glycyl peptides in aqueous ethanol and dioxane solutions (1971) J. Biol. Chem., 246, pp. 2211-2217; Saleuddin, A.S.M., Petit, H.P., The mode of formation and the structure of the periostracum (1983) The Mollusca, 4, pp. 199-234. , K. M. Wilbur ed. Academic Press, New York; Sato-Okoshi, W., Okoshi, K., Microstructure of scallop and oyster shells infested with boring Polydora (1993) Nippon Suisan Gakkaishi, 59, pp. 1243-1247; Segar, D.A., Collins, J.D., Riley, J.P., The distribution of the major and some minor elements in marine animals. Part II (1971) Molluscs. J. Mar. Biol. Assoc. U.K., 51, pp. 131-136; Swinehart, J.H., Smith, K.W., Iron and manganese deposition in the periostraca of several bivalve molluscs (1979) Biol. Bull., 156, pp. 369-381; Travis, D.F., Gonsalves, M., Comparative ultrastructure and organization of the prismatic region of two bivalves and its possible relation to the chemical mechanism of boring (1969) Am. Zool., 9, pp. 635-661; Tsujii, T., An electron microscopic study of the mantle epithelial cells of Anodonta sp. during shell regeneration (1976) The Mechanisms of Mineralization in the Invertebrates and Plants, pp. 339-353. , N. Watabe, K. M. Wilbur eds. Univ. South Carolina Press, Columbia; Vovelle, J., Sclérotisation et minéralisation des structures squellettiques chez les Mollusques (1974) Haliotis, 2, pp. 133-165; Waite, J.H., Evidence for the mode of sclerotization in a molluscan periostracum (1977) Comp. Biochem. Physiol., 58 B, pp. 157-162; Waite, J.H., Quinone-tanned scleroproteins (1983) The Mollusca, 1, pp. 467-504. , K. M. Wilbur ed. Academic Press, New York; Waite, J.H., Andersen, S.O., 3,4-dihydroxyphenyl-alanine in an insoluble shell protein of Mytilus edulis (1978) Biochem. Biophys. Acta, 541, pp. 107-114; Wheeler, A.P., Rusenko, K.W., Swift, D.M., Sikes, C.S., Regulation of in vitro and in vivo CaCO 3 crystallization by fractions of oyster shell organic matrix (1988) Mar. Biol., 98, pp. 71-80; Zottoli, R.A., Carriker, M.R., Burrow morphology, tube formation and microarchitecture of shell dissolution by the spionid polychaete Polydora websteri (1974) Mar. Biol., 27, pp. 307-316
Keywords: Amino acids; Crassostrea gigas; Metals; Polydora sp.; Shell organic matrix

Effects of Co-Cr corrosion products and corresponding separate metal ions on human osteoblast-like cell cultures - Tomás, H.; Carvalho, G.S.; Fernandes, M.H.; Freire, A.P.; Abrantes, L.M. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
The cytocompatibility of the degradation products of a Co-Cr orthopaedic alloy was investigated with particular focus on the dose-effect of an electrochemically dissolved alloy extract and of the corresponding separate metal ions on human osteogenic bone marrow derived cells. The extract solution contained 15ppm of Co and 8ppm of Cr as analysed by atomic absorption spectroscopy. Stock salt solutions of CoCl 2·6H 2O, CrCl 3·6H 2O and Na 2CrO 4 at corresponding concentrations were also prepared. Several dilutions of the above metallic solutions were tested for a period of 21 days on cells (third subculture) cultured in α-minimal essential medium containing foetal bovine serum and supplemented with antibiotics, dexamethasone ascorbic acid and β-glycerophosphate. The osteoblast response to the presence of metal ions was evaluated by several biochemical parameters: cell viability (MTT reduction by intracellular enzymes), alkaline phosphatase activity (an osteoblast marker) and protein production (both intracellular and extracellular). Co-Cr corrosion products showed opposite effects to their respective metal salts only on day 1. With time the different metal solutions presented a similar pattern of inhibition. These results suggest that impaired bone formation in vitro can occur in the presence of Co-Cr corrosion products. The cytocompatibility of the degradation products of a Co-Cr orthopaedic alloy was investigated with particular focus on the dose-effect of an electrochemically dissolved alloy extract and of the corresponding separate metal ions on human osteogenic bone marrow derived cells. The extract solution contained 15 ppm of Co and 8 ppm of Cr as analyzed by atomic absorption spectroscopy. Stock salt solutions of COCl 2·6H 2O, CrCl 3·6H 2O and Na 2CrO 4 at corresponding concentrations were also prepared. Several dilutions of the above metallic solutions were tested for a period of 21 days on cells (third subculture) cultured in α-minimal essential medium containing foetal bovine serum and supplemented with antibiotics, dexamethasone ascorbic acid and β-glycerophosphate. The osteoblast response to the presence of metal ions was evaluated by several biochemical parameters: cell viability (MTT reduction by intracellular enzymes), alkaline phosphatase activity (an osteoblast marker) and protein production (both intracellular and extracellular). Co-Cr corrosion products showed opposite effects to their respective metal salts only on day 1. With time the different metal solutions presented a similar pattern of inhibition. These results suggest that impaired bone formation in vitro can occur in the presence of Co-Cr corrosion products.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Tomas, H.; Faculdade de Ciencias, Universidade de Lisboa, Campo Grande, C1, Piso 5, 1700 Lisboa, PortugalReferences: Pohler, O.E.M., (1983) Biomaterials in Reconstructive Surgery, p. 158. , C. V. Mosby, St. Louis;Black, J., Oppenheiner, P., Morris, R.O.M., Peduto, A.M., Clark, C.C., (1987) J. Biomed. Mater. Res., 21, p. 1213; Sunderman Jr., F.W., Hopfer, S.M., Swift, T., Rezuke, W.N., Ziebka, L., Highman, P., Edwards, B., Gossling, H.R., (1989) J. Orthop. Res., 7, p. 307; Traisnel, M., Maguer, D., Hildebrand, H.F., (1990) Clin. Mater., 5, p. 309; Moore Jr., R.M., Hamburger, S., Jeng, L.J., Hamilton, P.M., (1991) J. Appl. Biomater., 2, p. 127; Henning, E.F., Raithel, H.J., Schaller, K.H., Dòhler, J.R., (1992) J. Trace Elem. Electrolytes Health Dis., 6, p. 239; Brown, S.A., Zhang, K., Merritt, K., Payer, J.H., (1993) J. Biomed. Mater. Res., 27, p. 1007; Albore-Saavedra, J., Vuitch, F., Delgado, R., Wiley, E., Hagler, H., (1994) Amer. Surg. Pathol., 18, p. 83; Buechel, F.F., Drucker, D., Jasty, M., Jiranek, W., Harris, W., (1994) Clin. Orthop. Related Res., 298, p. 202; De Bruijn, J.D., (1993), p. 9. , PhD thesis, LeidenNasser, S., Campbell, P.A., Kilgus, D., Kossovsky, N., Amstutz, H.C., (1990) Clin. Orthop., 261, p. 171; Revell, P.A., Weightman, B., Freeman, M.A.R., Roberts, B.V., (1978) Arch. Orthop. Trauma Surg., 91, p. 167; Vilamitjana-Amedee, J., Bareille, R., Rouais, F., Caplan, A.I., Harmand, M.F., (1993) In Vitro Cell. Dev. Biol., 29 A, p. 699; Bizios, R., (1994) Biotechnol. Bioeng., 43, p. 582; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Arciola, C.R., Granchi, D., Savarino, L., (1994) Clin. Mater., 15, p. 173; Tomás, H., Freire, A.P., Abrantes, L.M., (1994) J. Mater. Sci. Mater. Med., 5, p. 446; Lowry, O.H., Rosebrough, N.J., Farr, A.L., Randall, R.J., (1951) J. Biol. Chem., 193, p. 256; Maniatopoulos, C., Sodek, J., Melcher, A.H., (1988) Cell Tissue Res., 254, p. 317; Berridge, M.V., Tan, A.S., (1993) Arch. Biochem. Biophys., 303, p. 474; Ciapetti, G., Cenni, E., Pratelli, L., Pizzoferrato, A., (1993) Biomaterials, 14, p. 359; Martin, A., Clynes, M., (1993) Cytotechnology, 11, p. 49; Carvalho, G.S., Castanheira, M., Diogo, I., Abreu, A.M., Sousa, J.P., Loon, J.A., Van Blitterswijk, C.A., J. Mater. Sci. Mater. Med., , in press; Gotoh, Y., Hiraiwa, K., Nagayama, M., (1990) Bone and Mineral, 8, p. 239; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., (1991) Bone and Mineral, 14, p. 27
Keywords: Absorption spectroscopy; article; Atomic spectroscopy; Biocompatibility; Bone; Cell culture; Chromium alloys; Cobalt alloys; Corrosion; Corrosion resistance; Cytocompatibility; Enzyme inhibition; human; human cell; Human osteoblasts; Implants (surgical); Orthopaedic alloys; ossification; osteoblast; priority journal; surface property

Granules of osteoapatite and glass-reinforced hydroxyapatite implanted in rabbit tibiae - Afonso, A.; Santos, J.D.; Vasconcelos, M.; Branco, R.; Cavalheiro, J. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
Granules of a modified hydroxyapatite, glass-reinforced hydroxyapatite composite and commercial hydroxyapatite were implanted in rabbit tibiae. Histological studies were carried out after 1 and 2 months implantation periods using light and fluorescence microscopy. A much higher percentage of bone contact was developed for both the glass-reinforced hydroxyapatite composite and the modified hydroxyapatite when compared to commercial hydroxyapatite (89-91% versus 66%) after 2 months implantation. The mechanism of bone formation and growth around implants is discussed in terms of the influence of elements incorporated into these novel materials which are commonly found in bone tissues, such as Na, K and Mg, and the presence of a soluble β-tricalcium phosphate phase in the microstructure of the composite.
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Afonso, A.; Faculty of Dental Medicine, University of Porto, Rua Dr Roberto Frias, 4200 Porto, PortugalChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; magnesium, 7439-95-4; potassium, 7440-09-7; sodium, 7440-23-5References: Ravaglioli, A., Krajewski, A., (1992) Bioceramics-materials, Properties and Applications, p. 100. , Chapman & Hall, London;Cranin, A.N., Ronen, E., Puntoff, R.S.H., Tobim, G., Dibeling, J.B., (1988) J. Biomed. Mater. Res., 22, p. 1165; De Groot, K., Klein, C.P.A.T., (1990) "Handbook of Bioactive Ceramics", Vol. II-Calcium Phosphate and Hydroxylapatite Ceramics, 2, p. 3. , edited by T. Yamamuro CRC Press, Boston; Hollinger, J.O., Schmitz, J.P., Mizgala, J.W., Hassler, C., (1989) J. Biomed. Mater. Res., 23, p. 17; Cavalheiro, J., Branco, R., Vasconcelos, M., (1991) Proceedings of the 4th International Conference on Bioceramics, p. 205. , edited by W. Bonfield, G. W. Hastings and K. E. Tanner, London, UK Butterworth-Heinemann, Oxford; Santos, J.D., Reis, R.L., Knowles, J.C., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Nery, E.B., Legeros, R.Z., Lynch, K.L., Kalbleisch, J., (1988) J. Dent. Res., 67, p. 178; Ellinger, R.F., Nery, E.B., Lynch, K.L., (1986) Int. J. Period. Restor. Dent., 3, p. 223; Legeros, R.Z., Daculsi, G., (1990) "Handbook of Bioactive Ceramics", Vol. II-Calcium Phosphate and Hydroxylapatite Ceramics, 2, p. 17. , edited by T. Yamamuro CRC Press, Boston
Keywords: animal experiment; animal tissue; article; Bone; Bone formation; bone growth; Calcium Compounds; calcium phosphate; Composite materials; Fiber reinforced materials; glass; Glass fibers; Glass reinforced hydroxyapatite; Granular materials; histology; hydroxyapatite; implant; Implants (surgical); Magnesium; Microstructure; Modified hydroxyapatite; nonhuman; Optical microscopy; ossification; Osteoapatite; Oxides; Phosphates; Physiological models; potassium; priority journal; rabbit; Rabbit tibiae; Sodium; tibia; X ray diffraction analysis

Histological evaluation of two bioactive cements - Vasconcelos, M.; Afonso, A.; Branco, R.; Planell, J.; Driessens, F.; Cavalheiro, J. (Transactions of the Annual Meeting of the Society for Biomaterials in conjunction with the International Biomaterials SymposiumTrans Annu Meet Soc Biomater Int Biomater Symp, 1996)
Two bioactive bone cements were compared with poly(methylmethacrylate) (PMMA) cement. Cement A was prepared from precipitated hydroxyapatite and tricalcium phosphate, using an aqueous solution of Na 2HPO 4. Cement B was prepared by crushing a bioactive glass composed of SiO 2, CaO, P 2O 5 and Na 2O. The powder was mixed with NH 4H 2PO 4/(NH 4) 2 PO 4 aqueous solution buffered at pH = 7.4. The bioactive cements exhibited different in vivo behaviors but both performed better than PMMA cement.
Conference code: 45651Export Date: 21 November 2012Source: ScopusCODEN: TAMSELanguage of Original Document: EnglishCorrespondence Address: Vasconcelos, M.; INEB-Inst Eng. Biomedica, Porto, Portugal
Keywords: Bioactive bone cements; bone cement; glass; hydroxyapatite; Ion exchange; Lime; pH; Phosphate minerals; Polymethyl methacrylates; Silica; Sodium compounds; Solutions; Sorption; Tricalcium phosphate

Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts - Carvalho, G.S.; Castanheira, M.; Diogo, I.; Abreu, A.M.; Sousa, J.P.; Loon, J.A.; Van Blitterswijk, C.A. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
Fibroblasts from normal human skin were cultured for a period of 21 days in the absence or in the presence of metal ions. The effects of stainless steel (SS) corrosion products were compared to the effects of iron, chromium and nickel ions used either separately (Fe, Cr, or Ni solutions) or combined (Fe+Cr+Ni solution). At several periods of time (4, 7, 14 and 21 days) the cell cultures were analysed for the following parameters: (a) metal ion accumulation by atomic absorption spectrometry; (b) cell morphology and viability by the neutral red assay; (c) cell proliferation by DNA assessment, and enzyme activity by both (d) MTT reduction and (e) acid phosphatase activity. Results showed that SS-corrosion products and the corresponding metal ions combined at the same concentrations, Fe+Cr+Ni solution, had opposite effects on fibroblast cultures. In fact, SS-corrosion products caused no apparent effects on cell morphology nor on cell proliferation whereas Fe+Cr+Ni solution stimulated both neutral red uptake and cell proliferation. The enzymatic assays showed that SS-corrosion products caused inhibition of both MTT reduction and acid phosphatase activity in contrast to Fe+Cr+Ni solution which stimulated their activity. Furthermore, in all biological parameters studied, a strong association was observed between the effects of Fe+Cr+Ni solution and Cr alone, suggesting that Cr was the metal ion mostly involved in the stimulatory effects of the combined solution.Fibroblasts from normal human skin were cultured for 21 days in the absence, or presence, of metal ions. The effects of stainless steel (SS) corrosion products were compared to the effects of iron, chromium, and nickel ions used either separately or combined. At different periods of time, the cell cultures were analyzed for the following parameters: metal ion accumulation by atomic absorption spectrometry; cell morphology and viability by the neutral red assay; cell proliferation by DNA assessment; and enzyme activity by both MTT reduction and acid phosphatase activity. Results show that SS-corrosion products and the corresponding metal ions combined at the same concentrations, Fe+Cr+Ni solution, have opposite effects on fibroblast cultures.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Carvalho, G.S.; INEB-Instituto Engenharia Biomedica, Portugal Universidade do Minho, Praca Coronel Pacheco, 1, 4000 Porto, PortugalChemicals/CAS: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide, 298-93-1; acid phosphatase, 9001-77-8, 9025-88-1; chromium, 16065-83-1, 7440-47-3; DNA, 9007-49-2; iron, 14093-02-8, 53858-86-9, 7439-89-6; neutral red, 553-24-2; nickel, 7440-02-0; stainless steel, 12597-68-1References: Pohler, O.E.M., (1983) Biomaterials in Reconstructive Surgery, p. 158. , C.V. Mosby, St. Louis;Galante, J.O., Lemons, J., Spector, M., Wilson Jr., P.D., Wright, T.M., (1991) J. Orthop. Res., 9, p. 760; Henning, E.F., Raithel, H.J., Schaller, K.H., Döhler, J.R., (1992) J. Trace Elem. Electrolytes Health Dis., 6, p. 239; Maloney, W.J., Smith, R.L., Castro, F., Schurman, J., (1993) J. Bone Joint Surg., 75 A, p. 835; Jorgensen, T.J., Munno, F., Mitchell, T.G., Hungerford, D., (1983) Clin. Orthop., 176, p. 124; Jones, L.C., Hungerford, D.S., (1987) Trans Orthop. Res. Soc., 32, p. 317; Stulberg, B.N., Watson, J.T., Shull, S.L., Merritt, K., Crowe, T.D., Stulberg, S.D., Guidry, C.H., (1987) Trans Orthop. Res. Soc., 33, p. 314; Sunderman Jr., F.W., Hopfer, S.M., Swift, T., Rezuke, W.N., Ziebka, L., Highman, P., Edwards, B., Gossling, H.R., (1989) J. Orthop. Res., 7, p. 307; Merritt, K., Brown, S.A., Sharkey, N.A., (1984) J. Biomed. Mater. Res., 18, p. 991; Brown, S.A., Farnsworth, L.J., Merritt, K., Crowe, T.D., (1988) Biomed. Mater. Res., 22, p. 321; Merritt, K., Crowe, T.D., Brown, S.A., (1989) J. Biomed. Mater. Res., 23, p. 845; Merritt, K., Margevicius, R.W., Brown, S.A., (1992) J. Biomed. Mater. Res., 26, p. 1503; Brown, S.A., Zhang, K., Merritt, K., Payer, J.H., (1993) J. Biomed. Mater. Res., 27, p. 1007; Pereira, M.L., Silva, A., Tracana, R., Carvalho, G.S., (1994) Cytobios, 77, p. 73; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci. Mater. Med., 6, p. 523; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci. Mater. Med., 6, p. 56; Bravo, I., Sousa, S.R., Carvalho, G.S., Barbosa, M., (1992) Advances in Biomaterials, p. 7. , edited by P. J. Doherty et al. Elsevier, Amsterdam; Vrouwenvelder, W.C.A., Groot, C.G., DeGroot, K., (1993) J. Biomed. Mater. Res., 27, p. 465; Ciapetti, G., Cenni, E., Pratelli, L., Pizzoferrato, A., (1993) Biomaterials, 14, p. 359; Martin, A., Clynes, M., (1991) In Vitro Cell. Dev. Biol., 27 A, p. 183; Borenfreund, E., Puerner, J.A., (1983) J. Tissue Culture Methods, 9, p. 7; Hansen, M.B., Nielsen, S.E., Berg, K., (1989) J. Immunol. Methods, 119, p. 203; Rosdy, M., Grisoni, B., Claus, L.C., (1991) Biomaterials, 12, p. 511; Van Sliedregt, A., Radder, A.M., De Groot, K., Van Blitterswijk, C.A., (1992) J. Mater. Sci. Mater. Med., 3, p. 365; Caughman, W.F., Caughman, G.B., Shiflett, R.A., Rueggeberg, F., Schuster, G.S., (1991) Biomaterials, 12, p. 737; Carvalho, G.S., Bravo, I., (1993) J. Mater. Sci. Mater. Med., 4, p. 366; Harmand, M.F., Bordenave, L., Bareille, R., Naji, A., Jeandot, R., Rouais, F., Ducassou, D., (1991) J. Biomater. Sci. Polymer Edn., 2, p. 67; Katz, A., Feldman, M., Eisenbach, L., (1992) J. Immunol. Methods, 149, p. 117; Naji, A., Harmand, M.F., (1990) J. Biomed. Mater. Res., 24, p. 861; Mosmann, T., (1983) J. Immunol. Methods, 65, p. 55; Berridge, M.V., Tan, S., (1993) Arch. Biochem. Biophys., 303, p. 474
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; Absorption spectroscopy; Acid phosphatase; article; atomic absorption spectrometry; Atomic spectroscopy; Bioassay; Cell culture; Cell morphology; cell proliferation; cell structure; cell viability; Chromium; controlled study; Corrosion; Corrosion products; cytology; DNA; Enzymatic assays; Enzyme Activation; enzyme activity; Enzyme inhibition; fibroblast; human; human cell; Ions; Iron; metal; Metal ion accumulation; Metal salts; Metals; neutral red; Nickel; priority journal; Salts; Skin; skin fibroblast; Stainless steel; Steel corrosion

Mechanical behavior of injection-molded starch-based polymers - Reis, R.L.; Cunha, A.M.; Allan, P.S.; Bevis, M.J. (Polymers for Advanced TechnologiesPolym. Adv. Technol., 1996)
This work evaluates the mechanical performance of injection-molded starch-based copolymers, 60/40 (mol/ mol) starch/poly(ethylene vinyl alcohol), and the possibility of improving material properties through deliberately induced anisotropy during processing. Different types of samples were produced by conventional and shear-controlled injection molding (Scorim) and tested under tensile and impact loading. The behavior of three distinct grades is discussed in terms of the respective fracture morphology (evaluated by scanning electron microscopy). A comparison is made between the behavior of conventional and Scorim samples. The results show that the mechanical properties of the materials used were significantly improved by the employment of the Scorim process. The stiffness values of the conventional moldings were doubled, without reducing the ductility of the polymer. The impact data showed a material sensitivity, and consequent loss of properties, to the localized shear imposed to the melt during processing. This situation is attributed to very narrow mold gates (in the case of pingated systems) and leads to much reduced impact performance.
Cited By (since 1996): 58Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Reis, R.L.; Dept. of Metallurgical Engineering, FEUP, Rua dos Bragas, 4099 Porto Codex, PortugalReferences: Rokkanen, P.U., (1991) Ann. Med., 23, p. 109;Danniels, A.U., Adriano, K.P., Smutz, W.P., Chang, M.K.O., Heller, J., (1994) J. Appl. Biomater., 5, p. 51; Baumgart, F.W., Perren, S.M., (1994) Clinical and Laboratory Performance of Bone Plates, p. 42. , J. P. Harvey and R. F. Games, eds., ASTM STP1217, Philadelphia; Knowles, J.C., Hastings, G.W., (1992) J. Mater. Sci.: Mater. Med., 3, p. 352; Knowles, J.C., Hastings, G.W., (1993) J. Mater. Sci.: Mater. Med., 4, p. 102; Bastioli, C., Bellotti, V., Del Guidice, L., Gilli, G., (1993) J. Environ. Polym. Degr., 1, p. 181; Yoshida, Y., Uemura, T., (1994) Biodegradable Plastics and Polymers, p. 443. , Y. Doi and K. Fukuda, eds, Elsevier Science, Tokyo; Bastioli, C., Bellotti, V., Camia, M., Del Giudice, L., Rallis, A., (1994) Biodegradable Plastics and Polymers, p. 200. , Y. Doi and K. Fukuda, eds, Elsevier Science, Tokyo; Allan, P.S., Bevis, M.J., British Patent 2170-140-BAllan, P.S., Bevis, M.J., (1987) Plast. Rubb. Proc. Appl., 7, p. 3; Allan, P.S., Bevis, M.J., (1990) Comp. Manufac., 2, p. 79; Reis, R.L., Cunha, A.M., (1995) J. Mater. Sci.: Mater. Med., 6, p. 786; Bastioli, C., Belloti, V., Rallis, A., (1994) Rheological Acta, 33, p. 307
Keywords: Anisotropy; Biomaterials; Copolymers; differential scanning calorimetry; Ductility; fracture; Impact performance; Impact testing; Injection molding; Mechanical performance; Melting temperature; morphology; Narrow mold gates; performance; Scanning electron microscopy; Scorim; Scorim process; Starch-based polymers; Starched based polymers; Stiffness; Tensile testing

Potentiometric Determination of Total and Ionized Calcium in Osteoblast-Like Cell Culture Medium - Morais, S.; Carvalho, G.S.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1996)
The effect of the ionic strength and composition of solutions in the direct potentiometric determination of total and ionized calcium content using a calcium selective electrode was investigated. In the presence of a constant complexation buffer (CCB), the addition of sodium chloride and sodium bicarbonate causes a decrease in the limit of detection of the potentiometric response. When the procedure was tested in osteoblast-like cell culture medium no electrode interferences or method interferences were observed by the presence of proteins, i.e., the total and ionized calcium in this medium can be measured by potentiometric means.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: ELANELanguage of Original Document: EnglishCorrespondence Address: Sousa, J.P.; Inst. de Engenharia Biomédica, Faculdade de Engenharia, Universidade do Porto, Praça Coronel Pacheco, 1, P-4050 Porto, PortugalReferences: Nernst, W., (1886) Z. Phys. Chem., 2, p. 613;Nernst, W., (1889) Z. Phys. Chem., 4, p. 129; Morf, W.E., (1981) The Principle of Ion-Selective Electrodes and of Membrane Transport, , Elsevier, Amsterdam; Hulanicki, A., Trojanowicz, M., (1974) Anal. Chim. Acta, 68, p. 155; Anker, P., Wieland, E., Ammann, D., Dohner, R.E., Asper, R., Simon, W., (1981) Anal. Chem., 53, p. 1970; Manzoni, A., Premoli, P., (1985) Methodology and Clinical Applications of Ion-Selective Electrodes, pp. 131-136. , (Eds: A. H. J. Maas, A. B. T. J. Boink, N. E. L. Saris, R. Sprokholt, P. D. Wimberley), Radiometer, Copenhagen; Hulanicki, A., Lewandowski, R., Michalska, A., Lewenstam, A., (1990) Anal. Chim. Acta, 233, p. 269; Morais, S., Sousa, J.P., Fernandes, H., Carvalho, G.S., (1994) 11th European Conference on Biomaterials, Pisa, pp. 10-11. , Last Minute Posters Abstracts Book, European Society for Biomaterials; Ruzicka, J., Tjell, J.C., (1969) Anal. Chim. Acta, 47, p. 475; Ross, J.W., (1967) Science, 15, p. 1378; Rechnitz, G.A., Hseu, T.M., (1969) Anal. Chem., 41, p. 111; Oreskez, I., Hirsch, C., Douglas, K.S., Kupfer, S., (1968) Clin. Chim. Acta, 21, p. 203; Recomendations for Nomenclature of Ion-Selective Electrodes (1994) Pure Appl. Chem., 66, p. 2527; Ringbom, A., (1963) Complexation in Analytical Chemistry, , Interscience, New York; Russell Instruction Manual of Calcium Electrode Model 93-3209; Baudet, S., (1994) Methods in Cell Biology, pp. 93-113. , Academic Press, New York; Scharff, O., (1979) Anal. Chim. Acta, 109, p. 291
Keywords: Cell culture medium; potentiometry; Total and ionized calcium

Computerized fetal heart rate analysis in labour based on 2-s sampling. Can it proceed with confidence? [1] - Bernardes, J.; Garrido, A.; Chang, A.; Sahota, D.S.; Reed, N.N.; James, D.K.; Mohajer, M.P. (European Journal of Obstetrics Gynecology and Reproductive BiologyEUR. J. OBSTET. GYNECOL. REPROD. BIOL., 1995)
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: EOGRAdoi: 10.1016/0301-2115(95)02215-SPubMed ID: 8674558Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Instituto Engenharia Biomedica, Praca Coronel Pacheco 1, 4000 Porto, Portugal
Keywords: computer analysis; Computers; Female; Fetal monitoring; fetus; fetus heart rate; Heart Rate, Fetal; human; labor; Labor, Obstetric; letter; measurement; Pregnancy; priority journal; sampling; Time Factors

Stainless steel corrosion products cause alterations on mouse spleen cellular populations - Tracana, R.B.; Pereira, M.L.; Abreu, A.M.; Sousa, J.P.; Carvalho, G.S. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
Stainless steel is a metallic biomaterial commonly used in orthopaedic surgery. In this study we looked at the effects of stainless steel corrosion products on spleen, in order to evaluate their potential immunotoxicological effects. For this purpose stainless steel, type AISI 316L, was electrochemically dissolved in a physiological salt solution. The final solution, containing 490 μg/ml Fe, 224 μg/ml Cr and 150 μg/ml Ni, was injected subcutaneously in mice. After several periods of time (4, 10 and 14 days) spleens were removed and analysed for: (a) their contents in Fe, Cr and Ni, (b) histological alterations, (c) enumeration of cellular populations. Results showed that stainless steel corrosion products accumulated in spleen, caused histological alterations, and induced changes in cellular populations. When compared to chromium and nickel, iron was the metal ion preferentially accumulated in spleen. The increase of the multinucleated giant cell population was accompanied by depletion of lymphocyte populations. This study indicates that stainless steel corrosion products can spread systemically and accumulate in spleen inducing histological and cellular alterations which may give rise to immunotoxicological consequences.Stainless steel is a metallic biomaterial commonly used in orthopaedic surgery. In this study we looked at the effects of stainless steel corrosion products on spleen, in order to evaluate their potential immunotoxicological effects. For this purpose stainless steel, type AISI 316L, was electrochemically dissolved in a physiological salt solution. The final solution, containing 490 μg/ml Fe, 224 μg/ml Cr and 150 μg/ml Ni, was injected subcutaneously in mice. After several periods of time (4, 10 and 14 days) spleens were removed and analysed for: (a) their contents in Fe, Cr and Ni, (b) histological alterations, (c) enumeration of cellular populations. Results showed that stainless steel corrosion products accumulated in spleen, caused histological alterations, and induced changes in cellular populations. When compared to chromium and nickel, iron was the metal ion preferentially accumulated in spleen. The increase of the multinucleated giant cell population was accompanied by depletion of lymphocyte populations. This study indicates that stainless steel corrosion products can spread systematically and accumulate in spleen inducing histological and cellular alterations which may give rise to immunotoxicological consequences.
Cited By (since 1996): 19Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00121249Language of Original Document: EnglishCorrespondence Address: Tracana, R.B.; Natl. Inst. Biomedical Engineering, INEB, Praca Coronel Pacheco 1, 4000 Porto, Portugal
Keywords: animal cell; animal experiment; animal tissue; Animalia; article; Biocompatibility; biomaterial; cell population; Cells; Chromium; Chronoamperometry; controlled study; Corrosion; Corrosion products; Dissolution; electrochemistry; giant cell; histology; immunology; immunotoxicity; Immunotoxicological effects; Ions; Iron; Lymphocyte; lymphocyte subpopulation; male; mouse; Nickel; nonhuman; orthopedic surgery; priority journal; sodium chloride; Spleen; spleen cell; Stainless steel; Steel corrosion; subcutaneous drug administration; toxicity

Mouse inflammatory response to stainless steel corrosion products - Tracana, R.B.; Sousa, J.P.; Carvalho, G.S. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1994)
Corrosion occurs regularly following long-term implantation of stainless steel. Little is known about the inflammatory and immunological potential of stainless steel corrosion products. AISI 316L stainless steel was anodically dissolved in a physiologically solution, HBSS, through a chronoamperometric process by imposing an external constant current of 0.5 mA. The solution, containing 245 μg of Fe, 112 μg of Cr, 75 μg of Ni and 13 μg of Mo, was injected in the peritoneal cavity of male C57BL/6 mice. Five animals were used per survival period of time: 4, 16, 24, and 48 h, 1, 2, 4, 8 and 16 weeks. Three control mice per survival period of time were injected with HBSS. For each assay, peritoneal samples were analysed not only for the total number of cells but also for the percentages of macrophages, lymphocytes and polymorphonuclear (PMN) cells, which were estimated by differential counting on Wright-stained cytocentrifuge preparations. Our follow-up study showed that stainless steel corrosion products induced an acute inflammatory response for a period of one week as demonstrated by the influx of PMN cells and macrophages. In contrast neither a chronic inflammation nor an immune response was observed indicating that the stainless steel solution caused a minor tissue response.A follow-up study of the changes to mouse peritoneal cell populations, succeeding intraperitoneal injection of stainless steel corrosion products, in order to assess the inflammatory response to such metals was presented. AISI stainless steel was anodically dissolved in a physiologically solution, Hank's balanced salt solution (HBSS), which was injected in the peritoneal cavity of male mice. Five animals were designated per survival time interval of 4, 16, 24, and 48 h, 1, 2, 4, 8 and 16 weeks. Three control mice per survival period of time were treated with HBSS. For each assay, peritoneal samples were tested for total number of cells and percentages of macrophages, lymphocytes and polymorphonuclear (PMN) cells. The follow-up study revealed that stainless steel corrosion products induced an acute inflammatory response for a duration of one week as shown by the influx of PMN cells and macrophages. In contrast, neither a chronic inflammation nor an immune response was noted suggesting that stainless steel solution caused a minor tissue response.
Cited By (since 1996): 15Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00120337Language of Original Document: EnglishCorrespondence Address: Tracana, R.B.; Nat. Inst. Biomedical Engineering, Praca Coronel Pacheco 14000 Porto, Portugal
Keywords: animal cell; animal experiment; Animalia; article; Assays; Cell Count; Cells; Chromium; Chronoamperometry; controlled study; Corrosion; Dissolution; follow up; immune response; immunology; Inflammation; Inflammatory response; Iron; Lymphocyte; Lymphocytes; macrophage; Macrophages; male; metal implantation; Mice (animal); molybdenum; mouse; Nickel; nonhuman; Peritoneal cavity; Polymorphonuclear; polymorphonuclear cell; priority journal; Stainless steel; time; Tissue; Wright stained cytocentrifuge

In vitro immuno-cytotoxicity of iron evaluated by DNA synthesis of human T lymphocytes stimulated via CD2 and CD3 - Carvalho, G.S.; Bravo, I. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1993)
In previous studies it was demonstrated that the in vitro exposure of human lymphocytes to iron, nickel or cobalt salts causes a significant reduction of lymphocytes expressing CD2 and CD3 surface antigens. Since both molecules are involved in T lymphocyte activation, these studies suggest that the above metals might affect T-cell activation and proliferation. Thus a method was developed for the stimulation of lymphocytes in which both CD2 and CD3 molecules were triggered simultaneously. For this purpose an anti-CD3 monoclonal antibody (mAb) was chemically bound to human erythrocytes (HE), forming HEαCD3 conjugates, which were used for lymphocyte stimulation. In this work the effects of iron on lymphocyte proliferation was studied, following stimulation.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00122194Language of Original Document: EnglishCorrespondence Address: Carvalho, G.S.; Natl Inst for Biomedical Engn (INEB), Praca Coronel Pacheco, Porto, Portugal
Keywords: article; Biochemistry; Biomedical engineering; cd2 antigen; cd3 antigen; cd8 antigen; Cell culture; cell stimulation; concentration response; DNA; DNA synthesis; erythrocyte; human; human cell; Human lymphocytes; Immuno-cytotoxicity; immunocytotoxicity; Iron; lymphocyte proliferation; monoclonal antibody; monocyte; Synthesis (chemical); t lymphocyte; toxicity

Stimulation of human T lymphocytes via CD2 and CD3 molecules: establishment of the method and characterisation of proliferating cells. - Bravo, I.; Carvalho, G.S. (CytobiosCytobios, 1993)
The in vitro exposure of human lymphocytes to degradation products (Fe, Ni or Co) of metallic biomaterials causes a significant reduction of lymphocytes expressing the molecules involved in T lymphocyte activation, CD2 and CD3. A method is described which was developed for the stimulation of lymphocytes in which both CD2 and CD3 molecules were triggered simultaneously. For this purpose an anti-CD3 monoclonal antibody (mAb) was chemically bound to sheep (SE) or human (HE) erythrocytes, forming SE alpha CD3 or HE alpha CD3 conjugates, respectively, which were used for lymphocyte stimulation. Stimulation via CD2 and CD3 was compared with classical phytohaemagglutinin stimulation as well as with soluble alpha CD3 mAb stimulation. Phenotypical characterisation of DNA synthesising lymphocytes was assessed by autoradiography of 3H-thymidine pulsed cultures combined with immunocytochemical tests. Results indicate that this method of T lymphocyte stimulation via CD2 and CD3 is reliable and consistent, and it seems to be very convenient for the evaluation of immunocytotoxicity of metal ions derived from metallic biomaterials.
Keywords: Antigens, CD2; Antigens, CD3; Antigens, Differentiation, T Lymphocyte; Antigens, Differentiation, T-Lymphocyte; article; cd2 antigen; cd3 antigen; Cell culture; Cell Division; Cells, Cultured; cytology; human; immunoglobulin receptor; immunology; lymphocyte activation; metabolism; Receptors, Immunologic; t lymphocyte; T lymphocyte antigen; T-Lymphocytes